23Na magnetic resonance imaging-determined tissue sodium in healthy subjects and hypertensive patients - Kopp, Christoph; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Mueller, Dominik N.; Schmieder, Roland; Cavallaro, Alexander Josef; Eckardt, Kai-Uwe; Uder, Michael; Luft, Friedrich C.; Titze, Jens (Hypertension, 2013)
High dietary salt intake is associated with hypertension; the prevalence of salt-sensitive hypertension increases with age. We hypothesized that tissue Na might accumulate in hypertensive patients and that aging might be accompanied by Na deposition in tissue. We implemented Na magnetic resonance imaging to measure Na content of soft tissues in vivo earlier, but had not studied essential hypertension. We report on a cohort of 56 healthy control men and women, and 57 men and women with essential hypertension. The ages ranged from 22 to 90 years. Na magnetic resonance imaging measurements were made at the level of the calf. We observed age-dependent increases in Na content in muscle in men, whereas muscle Na content did not change with age in women. We estimated water content with conventional MRI and found no age-related increases in muscle water in men, despite remarkable Na accumulation, indicating water-free Na storage in muscle. With increasing age, there was Na deposition in the skin in both women and men; however, skin Na content remained lower in women. Similarly, this sex difference was found in skin water content, which was lower in women than in men. In contrast to muscle, increasing Na content was paralleled with increasing skin water content. When controlled for age, we found that patients with refractory hypertension had increased tissue Na content, compared with normotensive controls. These observations suggest that Na magnetic resonance imaging could have utility in assessing the role of tissue Na storage for cardiovascular morbidity and mortality in longitudinal studies. © 2013 American Heart Association, Inc.
CRIS-Team Scopus Importer:2023-03-08
Keywords: aging; gender difference; hypertension; salt; sodium MRI

23Na Magnetic Resonance Imaging of the Lower Leg of Acute Heart Failure Patients during Diuretic Treatment - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Garlichs, Christoph; Janka, Rolf Matthias; Luft, Friedrich C.; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (PLoS ONE, 2015)
Na+ can be stored in muscle and skin without commensurate water accumulation. The aim of this study was to assess Na+ and H2O in muscle and skin with MRI in acute heart failure patients before and after diuretic treatment and in a healthy cohort.Nine patients (mean age 78 years; range 58-87) and nine age and gender-matched controls were studied. They underwent 23Na/1H-MRI at the calf with a custom-made knee coil. Patients were studied before and after diuretic therapy. 23Na-MRI gray-scale measurements of Na+-phantoms served to quantify Na+-concentrations. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na+-levels did not change during therapy. Mean Na+-concentrations in muscle and skin decreased after furosemide therapy (before therapy: 30.7±6.4 and 43.5±14.5 mmol/L; after therapy: 24.2±6.1 and 32.2±12.0 mmol/L; p?0.05 and p?0.01). Water content measurements did not differ significantly before and after furosemide therapy in muscle (p = 0.17) and only tended to be reduced in skin (p = 0.06). Na+-concentrations in calf muscle and skin of patients before and after diuretic therapy were significantly higher than in healthy subjects (18.3±2.5 and 21.1±2.3 mmol/L).23Na-MRI shows accumulation of Na+ in muscle and skin in patients with acute heart failure. Diuretic treatment can mobilize this Na+-deposition; however, contrary to expectations, water and Na+-mobilization are poorly correlated.
EVALuna2:3828

23Na MRI Depicts Early Changes in Ion Homeostasis in Skeletal Muscle Tissue of Patients With Duchenne Muscular Dystrophy - Gerhalter, Teresa; Gast, Lena; Marty, Benjamin; Martin, Jan; Trollmann, Regina; Schüssler, Stephanie; Roemer, Frank; Uder, Michael; Schröder, Rolf; Carlier, Pierre G.; Nagel, Armin Michael; Laun, Frederik Bernd (Journal of Magnetic Resonance Imaging, 2019)
BACKGROUND: Duchenne muscular dystrophy (DMD) is a hereditary neuromuscular disease leading to progressive muscle wasting. Since there is a need for MRI variables that serve as early sensitive indicators of response to treatment, several quantitative MRI methods have been suggested for disease monitoring. PURPOSE: To evaluate the potential of sodium (23 Na) and proton (1 H) MRI methods to assess early pathological changes in skeletal muscle of DMD. STUDY TYPE: Prospective clinical study. POPULATION: 23 Na and 1 H MRI of the right leg were performed in 13 patients with DMD (age 7.8 ± 2.4) and 14 healthy boys (age 9.5 ± 2.2). FIELD STRENGTH/SEQUENCE: 3 T including a multiecho-spin-echo sequence, diffusion-weighted sequences, 1 H spectroscopy, 3-pt Dixon, and 23 Na ultrashort echo time sequences. ASSESSMENT: We obtained water T2 maps, fat fraction (FF), pH, and diffusion properties of the skeletal muscle tissue. Moreover, total tissue sodium concentration (TSC) was calculated from the 23 Na sequence. Intracellular-weighted 23 Na signal (ICwS) was derived from 23 Na inversion-recovery imaging. STATISTICAL TESTS: Results from DMD patients and controls were compared using Wilcoxon rank-sum tests and repeated analysis of variance (ANOVA). Spearman-rank correlations and area under the curve (AUC) were calculated to assess the performance of the different MRI methods to distinguish dystrophic from healthy muscle tissue. RESULTS: FF, water T2 , and pH were higher in DMD patients (0.07 ± 0.03, 39.4 ± 0.8 msec, 7.06 ± 0.03, all P < 0.05) than in controls (0.02 ± 0.01, 36.0 ± 0.4 msec, 7.03 ± 0.02). No difference was observed in diffusion properties. TSC (26.0 ± 1.3 mM, P < 0.05) and ICwS (0.69 ± 0.05 a.u., P < 0.05) were elevated in DMD (controls: 16.5 ± 1.3 mM and 0.47 ± 0.04 a.u.). The ICwS was frequently abnormal in DMD even when water T2 , FF, and pH were in the normal range. 23 Na MRI showed higher AUC values in comparison to the 1 H methods. DATA CONCLUSION: Sodium anomalies were regularly observed in patients with DMD compared with controls, and were present even in absence of fatty degenerative changes and water T2 increases. LEVEL OF EVIDENCE: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1103-1113.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Duchenne muscular dystrophy; proton MRI; skeletal muscle; sodium MRI

23Na MRI of human skeletal muscle using long inversion recovery pulses - Wilferth, Tobias; Gast, Lena; Stobbe, Robert W.; Beaulieu, Christian; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Imaging, 2019)
23Na inversion recovery (IR) imaging allows for a weighting toward intracellular sodium in the human calf muscle and thus enables an improved analysis of pathophysiological changes of the muscular ion homeostasis. However, sodium signal-to-noise ratio (SNR) is low, especially when using IR sequences. 23Na has a nuclear spin of 3/2 and therefore experiences a strong electrical quadrupolar interaction. This results in very short relaxation times as well as in possible residual quadrupolar splitting. Consequently, relaxation effects during a radiofrequency pulse can no longer be neglected and even allow for increasing SNR as has previously been shown for human brain and knee. The aim of this work was to increase the SNR in 23Na IR imaging of the human calf muscle by using long inversion pulses instead of the usually applied short pulses. First, the influence of the inversion pulse length (1 to 20 ms) on the SNR as well as on image contrast was simulated for different model environments and verified by phantom measurements. Depending on the model environment (agarose 4% and 8%, xanthan 2% and 3%), SNR values increased by a factor of 1.15 up to 1.35, while NaCl solution was successfully suppressed. Thus, image contrast between the non-suppressed model compartments changes with IR pulse length. Finally, in vivo measurements of the human calf muscle of ten healthy volunteers were conducted at 3 Tesla. On average, a 1.4-fold increase in SNR could be achieved by increasing the inversion pulse length from 1 ms to 20 ms, leaving all other parameters – including the scan time – constant. This enables 23Na IR MRI with improved spatial resolution or reduced acquisition time.
CRIS-Team Scopus Importer:2019-10-22
Keywords: B; Human skeletal muscle; Intracellular weighting; Inversion recovery; Long inversion pulses; Sodium (

(23)Na MRI reveals persistent sodium accumulation in tumefactive MS lesions - Huhn, Konstantin; Mennecke, Angelika; Linz, Peter; Tschunko, Franz; Kästle, Nicola; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Linker, Ralf; Engelhorn, Tobias (Journal of the Neurological Sciences, 2017)
Chronic inflammatory demyelinating diseases of the CNS typically show a limited lesion size. However, extended lesions may appear with an atypical configuration. Large lesions with a diameter>2cm accompanied by tumor-like edema are entitled "tumefactive" and may occur in multiple sclerosis (MS) and other demyelinating diseases. Historically, differential diagnosis often requires histological analysis. Therefore, advanced imaging techniques are warranted to allow for a precise non-invasive diagnosis. Cerebral sodium ((23)Na) MRI was recently described as a new method to investigate in vivo sodium accumulation. Indicating extended sodium levels in MS lesions, (23)Na MRI is a promising differential diagnostic tool further elucidating the role of sodium in demyelinating lesions.Repetitive (23)Na MRI measurements in a MS patient with a tumefactive demyelinating lesion providing insight into the medium-term course of cerebral sodium levels.(23)Na MRI depicts persistent lesional sodium accumulation after anti-inflammatory treatment and provides the opportunity of a non-invasive, in vivo analysis of sodium levels in inflammatory CNS lesions without need for contrast enhancing media. As a result of the extended dimension, tumefactive lesions may have an appropriate size for the analysis of inflammatory demyelination by (23)Na MRI with sufficient resolution.
EVALuna2:14686

3D Dixon water-fat LGE imaging with image navigator and compressed sensing in cardiac MRI - Zeilinger, Martin Georg; Wiesmüller, Marco; Forman, Christoph; Schmidt, Michaela; Munoz, Camila; Piccini, Davide; Kunze, Karl Philipp; Neji, Radhouene; Botnar, René Michael; Prieto, Claudia; Uder, Michael; May, Matthias; et al. (European Radiology, 2020)
Objectives: To evaluate an image-navigated isotropic high-resolution 3D late gadolinium enhancement (LGE) prototype sequence with compressed sensing and Dixon water-fat separation in a clinical routine setting. Material and methods: Forty consecutive patients scheduled for cardiac MRI were enrolled prospectively and examined with 1.5 T MRI. Overall subjective image quality, LGE pattern and extent, diagnostic confidence for detection of LGE, and scan time were evaluated and compared to standard 2D LGE imaging. Robustness of Dixon fat suppression was evaluated for 3D Dixon LGE imaging. For statistical analysis, the non-parametric Wilcoxon rank sum test was performed. Results: LGE was rated as ischemic in 9 patients and non-ischemic in 11 patients while it was absent in 20 patients. Image quality and diagnostic confidence were comparable between both techniques (p = 0.67 and p = 0.66, respectively). LGE extent with respect to segmental or transmural myocardial enhancement was identical between 2D and 3D (water-only and in-phase). LGE size was comparable (3D 8.4 ± 7.2 g, 2D 8.7 ± 7.3 g, p = 0.19). Good or excellent fat suppression was achieved in 93% of the 3D LGE datasets. In 6 patients with pericarditis, the 3D sequence with Dixon fat suppression allowed for a better detection of pericardial LGE. Scan duration was significantly longer for 3D imaging (2D median 9:32 min vs. 3D median 10:46 min, p = 0.001). Conclusion: The 3D LGE sequence provides comparable LGE detection compared to 2D imaging and seems to be superior in evaluating the extent of pericardial involvement in patients suspected with pericarditis due to the robust Dixon fat suppression. Key Points: • Three-dimensional LGE imaging provides high-resolution detection of myocardial scarring. • Robust Dixon water-fat separation aids in the assessment of pericardial disease. • The 2D image navigator technique enables 100% respiratory scan efficacy and permits predictable scan times.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Cardiac; Magnetic resonance imaging; Myocardium; Pericardium; Three-dimensional imaging

3 Tesla (23)Na Magnetic Resonance Imaging During Acute Kidney Injury - Hammon, Matthias; Großmann, Susan; Linz, Peter; Seuss, Hannes; Hammon, Rebecca; Rosenhauer, Daniela; Janka, Rolf Matthias; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Dahlmann, Anke; Cavallaro, Alexander Josef (Academic Radiology, 2017)
Sodium and proton magnetic resonance imaging ((23)Na/(1)H-MRI) have shown that muscle and skin can store Na(+) without water. In chronic renal failure and in heart failure, Na(+) mobilization occurs, but is variable depending on age, dialysis vintage, and other features. Na(+) storage depots have not been studied in patients with acute kidney injury (AKI).We studied 7 patients with AKI (mean age: 51.7 years; range: 25-84) and 14 age-matched and gender-matched healthy controls. All underwent (23)Na/(1)H-MRI at the calf. Patients were studied before and after acute hemodialysis therapy within 5-6 days. The (23)Na-MRI produced grayscale images containing Na(+) phantoms, which served to quantify Na(+) contents. A fat-suppressed inversion recovery sequence was used to quantify H2O content.Plasma Na(+) levels did not change. Mean Na(+) contents in muscle and skin did not significantly change following four to five cycles of hemodialysis treatment (before therapy: 32.7 ± 6.9 and 44.2 ± 13.5 mmol/L, respectively; after dialysis: 31.7 ± 10.2 and 42.8 ± 11.8 mmol/L, respectively; P > .05). Water content measurements did not differ significantly before and after hemodialysis in muscle and skin (P > .05). Na(+) contents in calf muscle and skin of patients before hemodialysis were significantly higher than in healthy subjects (16.6 ± 2.1 and 17.9 ± 3.2) and remained significantly elevated after hemodialysis.Na(+) in muscle and skin accumulates in patients with AKI and, in contrast to patients receiving chronic hemodialysis and those with acute heart failure, is not mobilized with hemodialysis within 5-6 days.
EVALuna2:14621

3 Tesla (23)Na magnetic resonance imaging during aerobic and anaerobic exercise - Hammon, Matthias; Großmann, Susan; Linz, Peter; Kopp, Christoph; Dahlmann, Anke; Janka, Rolf Matthias; Uder, Michael; Titze, Jens; Cavallaro, Alexander Josef (Academic Radiology, 2015)
The aim of the work described here was to determine the feasibility of monitoring Na(+) concentration and distribution in muscle/skin during aerobic/anaerobic exercise with (23)Na magnetic resonance imaging (MRI).The Na(+) concentration and water content of muscle/skin of the left lower leg of six healthy subjects (mean age, 26 years; range, 22-30 years; three men and three women) were assessed before and after aerobic/anaerobic cycle ergometry and during recovery with 3-T (23)Na/(1)H MRI. (23)Na MRI was performed with a custom-made knee coil. A gradient echo sequence with an acquisition time of 3.25 minutes, echo time of 2.07 ms, repetition time of 100 ms, and spatial resolution of 3 × 3 × 30 mm(3) was applied. Phantoms with increasing sodium concentration served for quantification via linear extrapolation. Blood values were determined by blood gas analysis.The concentration of Na(+) significantly increased during anaerobic exercise in all muscle compartments except the medial gastrocnemius muscle, whereas no significant change was observed in most muscle compartments during aerobic exercise (only the soleus muscle exhibited a significant increase in Na(+) concentration during aerobic exercise: 1.6 ± 1.5 mmol/kg, 4.5%, P = .046). During anaerobic exercise, the mean Na(+) concentration of the triceps surae and the whole leg increased by 9.0% (3.1 ± 2.1 mmol/kg, P = .016) and 6.5% (2.2 ± 1.3 mmol/kg, P < .01). MRI revealed a water-independent increase in Na(+) concentration in most muscle compartments during anaerobic exercise. Na(+) concentration significantly decreased during recovery after anaerobic and aerobic exercise in all muscle compartments except the soleus. The Na(+) concentration of the skin did not significantly change during anaerobic/aerobic exercise.Sodium(23) MRI allows reliable and noninvasive visualization and quantification of Na(+) concentration and distribution in muscle and skin during exercise. (23)Na MRI can be used to gain new insights into Na(+) homeostasis, presumably leading to better comprehension of pathophysiology.
EVALuna2:3827

3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Objective: Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task. Methods: 18 healthy volunteers underwent two resting state and a stimulus driven measurement using a finger tapping motor task at 3 and 7 T, respectively. The SNR for each field strength was adjusted by targeted voxel size variation to minimize the effect of SNR on the field strength specific outcome. Spatial and temporal characteristics of resting state ICA, network graphs, and motor task related activated areas were compared. Finally, a graph theoretical approach was used to detect resting state modulation subsequent to a simple motor task. Results: Spatial extensions of resting state ICA and motor task related activated areas were consistent between field strengths, but temporal characteristics varied, indicating that 7 T achieved a higher functional specificity of the BOLD response than 3 T-fMRI. Following the motor task, only 7 T-fMRI enabled the detection of highly specific connectivity modulations representing an “offline replay” of previous motor activation. Modulated connections of the motor cortex were directly linked to brain regions associated with memory consolidation. Conclusion: These findings reveal how memory processing is initiated even after simple motor tasks, and that it begins earlier than previously shown. Thus, the superior capability of 7 T-fMRI to detect subtle functional dynamics promises to improve diagnostics and therapeutic assessment of neurological diseases.
CRIS-Team Scopus Importer:2023-09-08
Keywords: 7T fMRI; graph theory; memory; motor task; offline replay; resting state

3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task.<br

68Ga-PSMA-11 PET/CT-derived metabolic parameters for determination of whole-body tumor burden and treatment response in prostate cancer - Schmidkonz, Christian; Cordes, Michael; Schmidt, Daniela; Bäuerle, Tobias; Goetz, Theresa Ida; Beck, Michael; Prante, Olaf; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2018)
PURPOSE: We aimed at evaluating the role of 68Ga-PSMA-11 PET/CT-derived metabolic parameters for assessment of whole-body tumor burden and its capability to determine therapeutic response in patients with prostate cancer. METHODS: A total of 142 patients with biochemical recurrence of prostate cancer underwent PET/CT with [68Ga]Ga-PSMA-HBED-CC (68Ga-PSMA-11). Quantitative assessment of all 641 68Ga-PSMA-11-positive lesions in the field of view was performed to calculate PSMA-derived parameters, including whole-body PSMA tumor volume (PSMA-TV) and whole-body total lesion PSMA (TL-PSMA), as well as the established SUVmax and SUVmean values. All PET-derived parameters were tested for correlation with serum PSA levels and for association with Gleason scores. In 23 patients who underwent 68Ga-PSMA-11 PET/CT before and after therapy with either external beam radiation, androgen deprivation, or docetaxel chemotherapy, SUVmax and TL-PSMA were compared to radiographic response assessment of CT images based on RECIST 1.1 criteria and to biochemical response determined by changes of serum PSA levels. RESULTS: PSMA-TV and TL-PSMA demonstrated a significant correlation with serum PSA levels (P < 0.0001) and TL-PSMA was significantly different for different Gleason scores. The agreement rate between TL-PSMA derived from PET and biochemical response was 87% (95% confidence interval, 0.66-0.97; Cohen's κ = 0.78; P < 0.01) and, thus, higher than for SUVmax, which was 74% (95% CI, 0.52-0.90; κ = 0.55; P < 0.01). Furthermore, agreement with PSA was higher for TL-PSMA and SUVmax than for CT-based response evaluation. Discordant findings between PET and CT were most likely due to limitations of CT and RECIST in rating small lymph nodes as metastases, as well as bone involvement, which was sometimes not detectable in CT. CONCLUSION: 68Ga-PSMA-11 PET/CT-derived metabolic tumor parameters showed promising results for evaluation of treatment response. Especially, TL-PSMA demonstrated higher agreement rates with biochemical response compared to SUVmax. Larger, ideally prospective trials are needed to help to reveal the full potential of metabolic parameters derived from PET imaging with 68Ga-PSMA-11.
EVALuna2:34269

68Ga-PSMA-11 PET/CT derived quantitative volumetric tumor parameters for classification and evaluation of therapeutic response of bone metastases in prostate cancer patients - Schmidkonz, Christian; Cordes, Michael; Goetz, Theresa Ida; Prante, Olaf; Kuwert, Torsten; Ritt, Philipp; Uder, Michael; Wullich, Bernd; Goebell, Peter; Bäuerle, Tobias (Annals of Nuclear Medicine, 2019)
Background: To evaluate the role of 68Gallium prostate-specific membrane antigen-positron emission tomography/computed tomography (68Ga-PSMA-11 PET/CT) derived quantitative volumetric tumor parameters in comparison with fully diagnostic conventional CT and serum-PSA levels for classification and evaluation of therapeutic response of bone metastases in patients with metastasized prostate cancer (PC). Methods: A total of 177 men with biochemical recurrence of prostate cancer suffering from bone metastases underwent PET/CT with [68Ga] Ga-PSMA-HBED-CC (68Ga-PSMA-11). To calculate 68Ga-PSMA-11 PET quantitative volumetric tumor parameters including whole-body total-lesion PSMA (TL-PSMA), whole-body PSMA-tumor volume (PSMA-TV), as well as the established maximum standard uptake values (SUVmax) and mean standard uptake values (SUVmean), all 443 68Ga-PSMA-11-positive bone lesions in the field of view were assessed quantitatively. Quantitative volumetric tumor parameters were correlated with CT-derived volume and bone density measurements of metastatic bone lesions, serum prostate-specific antigen (PSA) levels, and Gleason Scores. In the 20 patients suffering from bone metastases who underwent 68Ga-PSMA-11 PET/CT before and after therapy, CT-derived volume and bone density measurements of metastatic lesions were compared to biochemical response determined by serum-PSA levels. Results: In 177 patients, a total of 443 68Ga-PSMA-11 PET-positive bone lesions were detected. Of these, 50 lesions (11%) were only detectable on PET but not on conventional CT. PET-positive/CT-negative bone metastases demonstrated a significantly lower PSMA uptake compared to PET-positive/CT-positive bone lesions (p < 0.05). SUVmax, SUVmean, PSMA-TV, and TL-PSMA of bone metastases were significantly higher (p < 0.05) in patients with Gleason Scores > 7 compared to those with Gleason Scores ≤ 7. In the linear regression analysis, an association was determined between SUVmean, Gleason Scores, lesion classification, and serum-PSA levels but not for CT-derived bone density measurements. No significant correlation could be found between changes of bone density and CT-derived volume measurements of metastatic bone lesions and changes of serum-PSA levels (p > 0.05) before and after therapy, while a highly significant correlation was observed for changes of PSMA-TV, TL-PSMA, and serum-PSA levels (p < 0.001). Conclusion: Our results suggest that 68Ga-PSMA-11 PET/CT might be a valuable tool for the detection and follow-up of bone metastases in patients with metastasized prostate cancer. 68Ga-PSMA-11 PET-derived quantitative volumetric parameters demonstrated a highly significant correlation with changes of serum-PSA levels during the course of therapy. No such correlation could be determined for bone density measurements of metastatic bone lesions. Compared to the fully diagnostic CT scan, a significantly higher proportion of bone metastases was detected on 68Ga-PSMA-11 PET.
CRIS-Team Scopus Importer:2019-08-02
Keywords: 68Ga-PSMA-11 PET/CT; Bone metastases; Quantitative tumor parameters; Treatment response

99m Tc-MIP-1404-SPECT/CT for the detection of PSMA-positive lesions in 225 patients with biochemical recurrence of prostate cancer - Schmidkonz, Christian; Hollweg, Claudia; Beck, Michael; Reinfelder, Julia; Götz, Theresa; Sanders, James Chester; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; et al. (Prostate, 2018)
99m Tc-MIP-1404 (Progenics Pharmaceuticals, Inc., New York, NY) is a novel, SPECT-compatible 99m Tc-labeled PSMA inhibitor for the detection of prostate cancer. We present results of its clinical use in a cohort of 225 men with histologically confirmed prostate cancer referred for workup of biochemical relapse.From April 2013 to April 2017, 99m Tc-MIP1404-scintigraphy was performed in 225 patients for workup of PSA biochemical relapse of prostate cancer. Whole-body planar and SPECT/CT images of the lower abdomen and thorax were obtained 3-4 h p.i. of 710 ± 64 MBq 99m Tc-MIP-1404. Images were visually analyzed for presence and location of abnormal uptake. In addition, quantitative analysis of the SPECT/CT data was carried out on a subset of 125 patients. Follow-up reports of subsequent therapeutic interventions were available for 59% (139) of all patients.Tracer-positive lesions were detected in 77% (174/225) of all patients. Detections occurred at the area of local recurrence in the prostate in 25% of patients (or a total of 56), with metastases in lymph nodes in 47% (105), bone in 27% (60), lung in 5% (12), and other locations in 2% (4) of patients. Detection rates were 90% at PSA levels >=2 ng/mL and 54% below that threshold. Lesional SUVmax values were, on average, 32.2 ± 29.6 (0.8-142.2), and tumor-to-normal ratios 146.6 ± 160.5 (1.9-1482.4). The PSA level correlated significantly with total uptake of MIP-1404 in tumors (P < 0.001). Furthermore, total tumor uptake was significantly higher in patients with Gleason scores >=8 compared to those with Gleason scores <=7 (P < 0.05). In patients with androgen deprivation therapy, the detection rate was significantly higher compared to patients without androgen deprivation therapy (86% vs 71%, P < 0.001). Based on 99m Tc-MIP-1404-imaging and other information, an interdisciplinary tumor board review recommended changes to treatment plans in 74% (104/139) of those patients for whom the necessary documentation was available.SPECT/CT with 99m Tc-labeled MIP-1404 has a high probability in detecting PSMA-positive lesions in patients with elevated PSA. Statistical analysis disclosed significant relationship between quantitative 99m Tc-MIP-1404 uptake, PSA level, and Gleason score.
EVALuna2:13874

Accuracy and Specific Value of Cardiovascular 3D-Models in Pediatric CT-Angiography - Hammon, Matthias; Rompel, Oliver; Seuss, Hannes; Dittrich, Sven; Uder, Michael; Rüffer, Andrè; Cesnjevar, Robert; Ehret, Nicole; Glöckler, Martin (Pediatric Cardiology, 2017)
Computed tomography (CT)-angiography is routinely performed prior to catheter-based and surgical treatment in congenital heart disease. To date, little is known about the accuracy and advantage of different 3D-reconstructions in CT-data. Exact anatomical information is crucial. We analyzed 35 consecutive CT-angiographies of infants with congenital heart disease. All datasets are reconstructed three-dimensionally using volume rendering technique (VRT) and threshold-based segmentation (stereolithographic model, STL). Additionally, the two-dimensional maximum intensity projection (MIP) reconstructs two-dimensional data. In each dataset and resulting image, measurements of vascular diameters for four different vessels were estimated and compared to the reference standard, measured via multiplanar reformation (MPR). The resulting measurements obtained via the STL-images, MIP-images, and the VRT-images were compared with the reference standard. There was a significant difference (p < 0.05) between measurements. The mean difference was 0.0 for STL-images, -0.1 for MIP-images, and -0.3 for VRT-images. The range of the differences was -0.7 to 1.0 mm for STL-images, -0.6 to 0.5 mm for MIP-images and -1.1 to 0.7 mm for VRT-images. There was an excellent correlation between the STL-, MIP-, VRT-measurements, and the reference standard. Inter-reader reliability was excellent (p < 0.01). STL-models of cardiovascular structures are more accurate than the traditional VRT-models. Additionally, they can be standardized and are reproducible.
EVALuna2:14612

Accuracy of automated software-guided detection of significant coronary artery stenosis by CT angiography: Comparison with invasive catheterisation - Anders, Katharina; Achenbach, Stephan; Petit, Isabel; Daniel, Werner; Uder, Michael; Pflederer, Tobias (European Radiology, 2013)
Purpose: True automated detection of coronary artery stenoses might be useful whenever expert evaluation is not available, or as a "second reader" to enhance diagnostic confidence. We evaluated the accuracy of a PC-based stenosis detection tool alone and combined with expert interpretation. Methods: One hundred coronary CT angiography datasets were evaluated with the automated software alone, by manual interpretation (axial images, multiplanar reformations and maximum intensity projections in free double-oblique planes), and by expert interpretation aware of the automated findings. Stenoses ≥ 50 % were noted per-vessel and per-patient, and compared with invasive angiography. Results: Automated post-processing was successful in 90 % of patients (88 % of vessels). When excluding uninterpretable datasets, per-patient sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were 89 %, 79 %, 74 % and 92 % (per-vessel: 82 %, 85 %, 48 % and 96 %). All 100 datasets were evaluable by expert interpretation. Per-patient sensitivity, specificity, PPV and NPV were 95 %, 95 %, 93 % and 97 % (per-vessel: 89 %,98 %, 88 % and 98 %). Knowing the results of automated interpretation did not improve the performance of expert readers. Conclusion: Automated off-line post-processing of coronary CT angiography shows adequate sensitivity, but relatively low specificity in coronary stenosis detection. It does not increase accuracy of expert interpretation. Failure of post-processing in 10 % of all patients necessitates additional manual image work-up. Key Points: • Coronary CT angiography is increasingly used for detection of coronary artery stenosis • Computer assisted diagnosis might facilitate and speed up interpretation • Performance in properly segmented cases compared favourably with manual image interpretation • However, automated segmentation failed in about 10 % of cases • Manual reading is still mandatory; computer assisted diagnosis can provide a useful second read © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computer assisted diagnosis; Coronary angiography; Coronary artery disease; Coronary stenosis; Multidetector computed tomography

Accuracy of MRI-Compatible Contrast Media Injectors - Saake, Marc; Wüst, Wolfgang; Becker, Stefan; Uder, Michael; Janka, Rolf Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To analyze the exactness of MRI-compatible contrast media (CM) injectors in an experimental setup and clinical use. Materials and Methods: Ejected fluid volumes and amounts of CM were quantified for single and double piston injections. The focus was on small volumes, as used in pediatric examination and test-bolus measurements. Samples were collected before and after clinical MRI scans and amounts of CM were measured. Results: For single piston injections the volume differences were minimal (mean difference 0.01 ml). For double piston injections the volume of the first injection was decreased (mean 20.74 ml, target 21.00 ml, p < 0.01). After a position change of the Y-piece of the injection system, the amount of CM differed significantly from the target value (mean 1.23 mmol and 0.83 mmol at 1 ml/s flow rate, target 1.00 mmol, p < 0.01), independently of the wait time. The clinical samples confirmed these findings. Conclusion: The pistons of modern CM injectors work exactly. However, for small CM volumes the injected amount of CM can differ significantly from the target value in both directions. Influence factors are an incomplete elimination of air and exchange processes between the CM and saline chaser in the injection system. Key Points: o?In MRI examinations of children and test-bolus measurements, small amounts of CM are used.o?The accuracy of single piston injections is high.o?In double piston injections the injected amount of CM can differ significantly from the target value. Citation Format: o?Saake M, Wuest W, Becker S et al. Genauigkeit von MRT-kompatiblen Kontrastmittelinjektoren. Fortschr Röntgenstr 2014; 186: 253 - 259.
EVALuna2:14348

Accuracy of radiological tumour size assessment and the risk for re-excision in a cohort of primary breast cancer patients - Meier-Meitinger, Martina; Rauh, Claudia; Adamietz, B.; Fasching, Peter; Schwab, Siegfried; Häberle, Lothar; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; Lux, Michael P.; Hartmann, Arndt; Wachter, David Lukas; et al. (Ejso, 2012)
Background: Re-operations after breast conserving surgery (BCS) are necessary, when specimen margins are not free of breast cancer cells. This study explored the accuracy of preoperative tumour size assessment and its influence on the rate of re-excisions and mastectomies. Methods: The study included 1591 patients with invasive breast cancer, who were planned for BCS. Patient, staging and tumor characteristics were evaluated concerning their influence on re-excision and mastectomy rates. Patient and tumor characteristics comprised histopathological tumour size, HER2 status, multifocality, in situ component, grading (G), nodal status and hormone receptor (HR) status. Staging characteristics included deviation from pathological tumour size as measured by clinical examination, sonography and mammography. Results: In 1316 patients (83%) sufficient treatment was possible with one operation. 275 patients (17%) had to undergo at least one further surgery as a result of positive specimen margins. In 138 patients (9%) mastectomy was ultimately necessary. In patients with a positive HER2 status, a larger tumour size, underestimation by ultrasound, an in situ component and multifocality, the risk for a re-operation was about doubled. Tumour size deviation in the mammogram or the clinical tumour size assessment did not have significant influence to the re-excision rates. Conclusion: Tumour size and accurate presurgical assessment of the tumour size itself are independent predictors for the need of a second surgery or even a mastectomy in patients for whom a primary BCS was planned. © 2011 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Mastectomy; Re-excision; Tumour size; Ultrasound

Achieving high spatial and temporal resolution with perfusion MRI in the head and neck region using golden-angle radial sampling - Tomppert, Andrea; Wüst, Wolfgang; Wiesmüller, Marco; Heiß, Rafael; Kopp, Markus; Nagel, Armin Michael; Tomita, Hayato; Meixner, Christian; Uder, Michael; May, Matthias (European Radiology, 2020)
Objectives: Conventional perfusion-weighted MRI sequences often provide poor spatial or temporal resolution. We aimed to overcome this problem in head and neck protocols using a golden-angle radial sparse parallel (GRASP) sequence. Methods: We prospectively included 58 patients for examination on a 3.0-T MRI using a study protocol. GRASP (A) was applied to a volumetric interpolated breath-hold examination (VIBE) with 135 reconstructed pictures and high temporal (2.5 s) and spatial resolution (0.94 × 0.94 × 3.00 mm). Additional sequences of matching temporal resolution (B: 2.5 s, 1.88 × 1.88 × 3.00 mm), with a compromise between temporal and spatial resolution (C: 7.0 s, 1.30 × 1.30 × 3.00 mm) and with matching spatial resolution (D: 145 s, 0.94 × 0.94 × 3.00 mm), were subsequently without GRASP. Instant inline-image reconstructions (E) provided one additional series of averaged contrast information throughout the entire acquisition duration of A. Overall diagnostic image quality, edge sharpness and contrast of soft tissues, vessels and lesions were subjectively rated using 5-point Likert scales. Objective image quality was measured as contrast-to-noise ratio in D and E. Results: Overall, the anatomic and pathologic image quality was substantially better with the GRASP sequence for the temporally (A/B/C, all p < 0.001) and spatially resolved comparisons (D/E, all p < 0.002 except lesion edge sharpness with p = 0.291). Image artefacts were also less likely to occur with GRASP. Differences in motion, aliasing and truncation were mainly significant, but pulsation and fat suppression were comparable. In addition, the contrast-to-noise ratio of E was significantly better than that of D (pD-E < 0.001). Conclusions: High temporal and spatial resolution can be obtained synchronously using a GRASP-VIBE technique for perfusion evaluation in head and neck MRI. Key Points: • Golden-angle radial sparse parallel (GRASP) sampling allows for temporally resolved dynamic acquisitions with a very high image quality. • Very low-contrast structures in the head and neck region can benefit from using the GRASP sequence. • Inline-image reconstruction of dynamic and static series from one single acquisition can replace the conventional combination of two acquisitions, thereby saving examination time.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Adult; Magnetic resonance imaging; Neck; Perfusion

A COMPARISON BETWEEN 6-POINT DIXON MRI AND MR SPECTROSCOPY TO QUANTIFY MUSCLE FAT IN THE THIGH OF SUBJECTS WITH SARCOPENIA - Grimm, Alexandra; Meyer, H.; Nickel, M. D.; Nittka, M.; Raithel, E.; Chaudry, Oliver; Friedberger, Andreas; Uder, Michael; Kemmler, Wolfgang; Engelke, Klaus; Quick, H. H. (Journal of Frailty & Aging, 2019)
Background: Changes in muscle fat composition as for example observed in sarcopenia, affect physical performance and muscular function, like strength and power. Objectives: The purpose of this study was to compare 6-point Dixon magnetic resonance imaging and multi-echo magnetic resonance spectroscopy sequences to quantify muscle fat. Setting, participants and measurements: Two groups were recruited (G1: 23 healthy young men (28 +/- 4 years), G2: 56 men with sarcopenia (80 +/- 5 years)). Proton density fat fraction was measured with a 6-point product and a 6-point prototype Dixon sequence in the left thigh muscle and with a highspeed multi-echo T2*-corrected H1 magnetic resonance spectroscopy sequence within the semitendinosus muscle of the left thigh. To evaluate the comparability among the different methods, Bland-Altman and linear regression analyses of the proton density fat fraction results were performed. Results: Mean differences +/- 1.96 * standard deviation between spectroscopy and 6pt Dixon sequences were 1.9 +/- 3.3% and 1.5 +/- 3.6% for the product and prototype sequences, respectively. High correlations were measured between the proton density fat fraction results of the 6-point Dixon sequences and spectroscopy (R = 0.95 for the product sequence and R = 0.97 for the prototype sequence). Conclusions: Dixon imaging and spectroscopy sequences show comparable accuracy for fat measurements in the thigh. Spectroscopy is a local measurement, whereas Dixon sequences provide maps of the fat distribution. The high correlations of the 6-point Dixon sequences with spectroscopy support their clinical use. They provide higher spatial resolution than spectroscopy, but are not suitable for a more complicated spectral analysis to separate extra-and intramyocellular lipids.
CRIS-Team WoS Importer:2019-03-06

Acute Effects of Lateral Thigh Foam Rolling on Arterial Tissue Perfusion Determined by Spectral Doppler and Power Doppler Ultrasound - Hotfiel, Thilo; Swoboda, Bernd; Krinner, Sebastian; Grim, Casper; Engelhardt, Martin; Uder, Michael; Heiß, Rafael (Journal of strength and conditioning research, 2017)
Hotfiel, T, Swoboda, B, Krinner, S, Grim, C, Engelhardt, M, Uder, M, and Heiss, R. Acute effects of lateral thigh foam rolling on arterial tissue perfusion determined by spectral Doppler and power Doppler ultrasound. J Strength Cond Res 31(4): 893-900, 2017-Foam rolling has been developed as a popular intervention in training and rehabilitation. However, evidence on its effects on the cellular and physiological level is lacking. The aim of this study was to assess the effect of foam rolling on arterial blood flow of the lateral thigh. Twenty-one healthy participants (age, 25 ± 2 years; height, 177 ± 9 cm; body weight, 74 ± 9 kg) were recruited from the medical and sports faculty. Arterial tissue perfusion was determined by spectral Doppler and power Doppler ultrasound, represented as peak flow (Vmax), time average velocity maximum (TAMx), time average velocity mean (TAMn), and resistive index (RI), and with semiquantitative grading that was assessed by 4 blindfolded investigators. Measurement values were assessed under resting conditions and twice after foam rolling exercises of the lateral thigh (0 and 30 minutes after intervention). The trochanteric region, mid portion, and distal tibial insertion of the lateral thigh were representative for data analysis. Arterial blood flow of the lateral thigh increased significantly after foam rolling exercises compared with baseline (p <= 0.05). We detected a relative increase in Vmax of 73.6% (0 minutes) and 52.7% (30 minutes) (p < 0.001), in TAMx of 53.2% (p < 0.001) and 38.3% (p = 0.002), and in TAMn of 84.4% (p < 0.001) and 68.2% (p < 0.001). Semiquantitative power Doppler scores at all portions revealed increased average grading of 1.96 after intervention and 2.04 after 30 minutes compared with 0.75 at baseline. Our results may contribute to the understanding of local physiological reactions to self-myofascial release.
EVALuna2:10911

Acute-onset migrainous aura mimicking acute stroke: MR perfusion imaging features - Floery, D.; Vosko, M. R.; Fellner, F. A.; Fellner, C.; Ginthoer, C.; Gruber, F.; Ransmayr, G.; Dörfler, Arnd; Uder, Michael; Bradley, W. G. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: In a very limited number of cases, acute migrainous aura may mimic acute brain infarction. The aim of this study was to recognize patterns of MR perfusion abnormalities in this presentation. MATERIALS AND METHODS: One thousand eight hundred fifty MR imaging studies performed for the suspicion of acute brain infarction were analyzed retrospectively to detect patients with acute migrainous aura not from stroke. All patients were examined clinically by 2 neurologists and underwent a standard stroke MR imaging protocol, including PWI. Two radiologists reviewed the perfusion maps visually and quantitatively for the presence, distribution, and grade of perfusion abnormalities. RESULTS: Among 1850 MR imaging studies, 20 (1.08%) patients were found to have acute migrainous aura. Hypoperfusion was found in 14/20 patients (70%) with delayed rMTT and TTP, decreased rCBF, and minimal decrease in rCBV. In contrast to the typical pattern in stroke, perfusion abnormalities were not limited to a single vascular territory but extended to >1. Bilateral hypoperfusion was seen in 3/14 cases. In 11/14 cases, hypoperfusion with a posterior predominance was found. TTP and rMTT were the best maps to depict perfusion changes at visual assessment, but also rCBF maps demonstrated significant hypoperfusion in quantitative analysis. In all patients, clinical and imaging follow-up findings were negative for stroke. CONCLUSIONS: Acute migrainous aura is rare but important in the differential diagnosis among patients with the suspicion of acute brain infarction. Atypical stroke perfusion abnormalities can be seen in these patients.
CRIS-Team Scopus Importer:2022-08-05

Added value of clinical decision rules for the management of enhancing breast MRI lesions: A systematic comparison of the Kaiser score and the Göttingen score - Dietzel, Matthias; Bernathova, Maria; Clauser, Paola; Kapetas, Panagiotis; Uder, Michael; Baltzer, Pascal A.T. (European Journal of Radiology, 2023)
Purpose: We investigated the added value of two internationally used clinical decision rules in the management of enhancing lesions on breast MRI. Methods: This retrospective, institutional review board approved study included consecutive patients from two different populations. Patients received breast MRI according to the recommendations of the European Society of Breast Imaging (EUSOBI). Initially, all examinations were assessed by expert readers without using clinical decision rules. All lesions rated as category 4 or 5 according to the Breast Imaging Reporting and Data System were histologically confirmed. These lesions were re-evaluated by an expert reader blinded to the histology. He assigned each lesion a Göttingen score (GS) and a Kaiser score (KS) on different occasions. To provide an estimate on inter-reader agreement, a second fellowship-trained reader assessed a subset of these lesions. Subgroup analyses based on lesion type (mass vs. non-mass), size (>1 cm vs. ≤ 1 cm), menopausal status, and significant background parenchymal enhancement were conducted. The areas under the ROC curves (AUCs) for the GS and KS were compared, and the potential to avoid unnecessary biopsies was determined according to previously established cutoffs (KS > 4, GS > 3) Results: 527 lesions in 506 patients were included (mean age: 51.8 years, inter-quartile-range: 43.0–61.0 years). 131/527 lesions were malignant (24.9 %; 95 %-confidence-interval: 21.3–28.8). In all subgroups, the AUCs of the KS (median = 0.91) were higher than those of the GS (median = 0.83). Except for “premenopausal patients” (p = 0.057), these differences were statistically significant (p ≤ 0.01). Kappa agreement was higher for the KS (0.922) than for the GS (0.358). Conclusion: Both the KS and the GS provided added value for the management of enhancing lesions on breast MRI. The KS was superior to the GS in terms of avoiding unnecessary biopsies and showed superior inter-reader agreement; therefore, it may be regarded as the clinical decision rule of choice.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Algorithms; Breast Neoplasms; Clinical Decision-Making; Magnetic Resonance Imaging

Additive Effects of Exercise and Vitamin D Supplementation (with and without Calcium) on Bone Mineral Density in Older Adults: A Systematic Review and Meta-Analysis - Fischer, Cecilie; Jakob, Franz; Kohl, Matthias; Kast, Stephanie; von Stengel, Simon; Kerschan-Schindl, Katharina; Lange, Uwe; Thomasius, Friederike; Peters, Stefan; Uder, Michael; Kemmler, Wolfgang (Journal of Osteoporosis, 2023)
Exercise is a recognized component in the prevention and therapy of osteoporosis. The present systematic review and meta-analysis aimed to determine the effect of Vitamin D (Vit-D) added to exercise versus exercise alone on bone mineral density (BMD) at the lumbar spine (LS) or hip in older adults. A systematic review based on six literature databases according to PRISMA included (a) exercise trials, with an exercise (EX) and a combined exercise + Vit-D group (EX + Vit-D), (b) intervention ≥ 6 months, and (c) BMD assessments at LS or hip. Effects sizes (MD) and 95%-confidence intervals (95%-CI) were calculated using a random-effect model that includes the inverse heterogeneity model (IVhet). Five studies with 281 participants in the EX and 279 participants in the EX + Vit-D were included. No significant differences between EX versus EX + Vit-D were observed for BMD-LS (MD: 0.002, 95%-CI: -0.033 to 0.036) or BMD-hip (MD: 0.003, 95%-CI: -0.035 to 0.042). Heterogeneity between the trial results was moderate-substantial for LS (I2 = 0%) and moderate for hip-BMD (I2 = 35%). The funnel plot analysis suggests evidence for a publication/small study bias for BMD-LS and hip results. In summary, this present systematic review and meta-analysis were unable to determine significant positive interaction of exercise and Vit-D on LS- or hip-BMD. We predominately attribute this finding to (1) the less bone-specific exercise protocols of at least two of the five studies and (2) the inclusion criteria of the studies that did not consequently focus on Vit-D deficiency. This issue should be addressed in more detail by adequately powered exercise trials with promising exercise protocols and participants with Vit-D deficiency.
CRIS-Team Scopus Importer:2023-09-29

Adherence to Antihypertensive Medication in Treatment-Resistant Hypertension Undergoing Renal Denervation - Schmieder, Roland; Ott, Christian; Schmid, Andrea; Friedrich, Stefanie; Kistner, Iris; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Toennes, Stefan W. (Journal of the American Heart Association, 2016)
Adherence to medication has been repeatedly proposed to represent a major cause of treatment-resistant hypertension (TRH); however, treatment decisions such as treating TRH with renal denervation depend on accurate judgment of adherence. We carefully analyzed adherence rates to medication before and after renal denervation and its effect on blood pressure (BP) control.Eighty patients with TRH were included in 2 prospective observational studies that assessed the difference of potential antihypertensive and nephroprotective effects of renal denervation. To compare prescribed with actual medication intake (representing a measure of adherence), we analyzed urine samples collected at baseline and at 6 months after renal denervation for antihypertensive compounds or metabolites (by liquid chromatography-mass spectrometry). In addition to office BP, 24-hour ambulatory BP and central hemodynamics (central systolic pressure, central pulse pressure) were assessed. Informed consent for analyses of urine metabolites was obtained from 79 of 80 patients. Actual intake of all antihypertensive drugs was detected at baseline and at 6 months after renal denervation in 44 (56%) and 52 (66%) patients, respectively; 1 drug was missing in 22 (28%) and 17 (22%) patients, respectively, and >=2 drugs were missing in 13 (16%) and 10 (13%) patients, respectively. At baseline, 24-hour ambulatory BP (P=0.049) and central systolic BP (P=0.012) were higher in nonadherent patients. Adherence did not significantly change overall (McNemar-Bowker test, P=0.362). An increase in adherence was observed in 21 patients, and a decrease was observed in 11 patients. The decrease in 24-hour ambulatory BP was not different in those with stable adherence 6 months after renal denervation (n=41, -7±13 mm Hg) compared with those with increased adherence (n=21, -10±13 mm Hg) and decreased adherence (n=11, -7±14 mm Hg) (P>0.20). Our study is limited by the relatively small sample size and potentially by the specific health environment of our university center (Northern Bavaria, Germany).Nonadherence to medication among patients with TRH was relatively low: ?1 of 6 patients with TRH did not take >=2 of the prescribed drugs. Adherence pattern did not change significantly after renal denervation and had no impact on the overall observed BP changes, supporting the concept that renal denervation is an effective treatment in patients with TRH.URL: https://www.clinicaltrials.gov. Unique identifiers: NCT00888433, NCT01442883 and NCT01687725.
EVALuna2:3842

Advanced Modeled Iterative Reconstruction (ADMIRE) Facilitates Radiation Dose Reduction in Abdominal CT - Ellmann, Stephan; Kammerer, Ferdinand; Allmendinger, Thomas; Hammon, Matthias; Janka, Rolf Matthias; Lell, Michael; Uder, Michael; Kramer, Manuel (Academic Radiology, 2018)
RATIONALE AND OBJECTIVES: This study aimed to determine the potential degree of radiation dose reduction achievable using Advanced Modeled Iterative Reconstruction (ADMIRE) in abdominal computed tomography (CT) while maintaining image quality. Moreover, this study compared differences in image noise reduction of this iterative algorithm with radiation dose reduction. METHODS: Eleven consecutive patients scheduled for abdominal CT were scanned according to our institute's standard protocol (100 kV, 289 reference mAs). Using a proprietary reconstruction software, CT images of these patients were reconstructed as either full-dose weighted filtered back projections or with simulated radiation dose reductions down to 10% of the full-dose level and ADMIRE at either strength 3 or strength 5. Images were marked with arrows pointing on anatomic structures of the abdomen, differing in their contrast to the surrounding tissue. Structures were grouped into high-, medium-, and low-contrast subgroups. In addition, the intrinsic noise of these structures was measured. That followed, image pairs were presented to observers, with five readers assessing image quality using two-alternative-forced-choice comparisons. In total, 3000 comparisons were performed that way. RESULTS: Both ADMIRE 3 and 5 decreased noise of the anatomic structures significantly compared to the filtered back projection, with an additional significant difference between ADMIRE 3 and 5. Radiation dose reduction potential for ADMIRE ranged from 29.0% to 53.5%, with no significant differences between ADMIRE 3 and 5 within the contrast subgroups.The potential levels of radiation dose reduction for ADMIRE 3 differed significantly between high-, medium-, and low-contrast structures, whereas for ADMIRE 5, there was only a significant difference between the high- and the medium-contrast subgroups. CONCLUSION: Although ADMIRE 5 permits significantly higher noise reduction potential than ADMIRE 3, it does not facilitate higher levels of radiation dose reduction. ADMIRE nonetheless holds remarkable potential for radiation dose reduction, which features a certain dependency on the contrast of the structure of interest. Applying ADMIRE with a strength of 3 in abdominal CT may permit radiation dose reduction of about 30%.
EVALuna2:34687

Advanced neural networks for classification of MRI in psoriatic arthritis, seronegative, and seropositive rheumatoid arthritis - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Rheumatology, 2022)
Objectives: To evaluate whether neural networks can distinguish between seropositive rheumatoid arthritis (RA), seronegative RA and psoriatic arthritis (PsA) based on inflammatory patterns from hand MRI and to test how psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet neural networks were utilized to compare (i) seropositive RA vs. PsA, (ii) seronegative RA vs. PsA and (iii) seropositive vs. seronegative RA with respect to hand MRI data. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without presentation of demographic and clinical parameters. Additionally, the trained networks were applied to psoriasis patients without clinical arthritis. Results: MRI scans from 649 patients (135 seronegative RA, 190 seropositive RA, 177 PsA, 147 psoriasis) were fed into ResNet neural networks. AUROC was 75% for seropositive RA vs. PsA, 74% for seronegative RA vs. PsA and 67% for seropositive vs. seronegative RA. All MRI sequences were relevant for classification, however, when deleting contrast agent-based sequences the loss of performance was only marginal. The addition of demographic and clinical data to the networks did not provide significant improvements for classification. Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that a PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Neural networks can be successfully trained to distinguish MRI inflammation related to seropositive RA, seronegative RA, and PsA.
Keywords: Rheumatoid arthritis; Psoriatic arthritis; neural networks; deep learning

A hybrid method towards automated nipple detection in 3D breast ultrasound images - Wang, Lei; Böhler, Tobias; Zöhrer, Fabian; Georgii, Joachim; Rauh, Claudia; Fasching, Peter; Brehm, Barbara; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Uder, Michael; Hahn, Horst K. (Proceedings of the Annual International Conference of the IEEE Engineering in Medicine and Biology Society, EMBS, 2014)
In clinical work-up of breast cancer, nipple position is an important marker to locate lesions. Moreover, it serves as an effective landmark to register a 3D automated breast ultrasound (ABUS) images to other imaging modalities, e.g., X-ray mammography, tomosynthesis or magnetic resonance imaging (MRI). However, the presence of speckle noises caused by the interference waves and variant imaging directions poses challenges to automatically identify nipple positions. In this work, a hybrid fully automatic method to detect nipple positions in ABUS images is presented. The method extends the multi-scale Laplacian-based method that we proposed previously, by integrating a specially designed Hessian-based method to locate the shadow area beneath the nipple and areola. Subsequently, the likelihood maps of nipple positions generated by both methods are combined to build a joint-likelihood map, where the final nipple position is extracted. To validate the efficiency and robustness, the extended hybrid method was tested on 926 ABUS images, resulting in a distance error of 7.08±10.96 mm (mean±standard deviation).
EVALuna2:14367

A large cohort of patients with hepatocellular carcinoma in a single European centre: aetiology and prognosis now and in a historical cohort - Ganslmayer, Marion; Hagel, Alexander; Dauth, Wolfgang; Zopf, Steffen; Strobel, Deike; Mueller, Volker; Uder, Michael; Neurath, Markus; Siebler, Jürgen (Swiss Medical Weekly, 2014)
The incidence of hepatocellular carcinoma is rising. However, this is occurring not only in developing nations, but in industrial countries as well. Surveillance programmes, classification systems and therapeutic options have improved, but there is a lack of data regarding their impact on the prognosis of this difficult-to-treat cancer.We evaluated 484 patients and reported on disease stage, therapeutic procedures and survival time. Data were compared with a historical cohort treated in the same centre 10 years before.In this cohort, the main reason for liver disease was alcoholism, although hepatitis B remains the leading cause of hepatocellular carcinoma worldwide. Now, most patients have compensated liver function and hepatocellular carcinoma is diagnosed in the early tumour stages (it was diagnosed in the advanced disease stages in the previous cohort). Overall, median survival time was 62.4 weeks, 1-year survival was 58.6% and 3-year survival was 23.2%. Survival time correlated with the stage of liver disease, tumour stage and with therapeutic options.Surveillance programmes lead to diagnosis in earlier tumour stages. Differentiated classification systems allow individualised therapeutic approaches. Earlier cancer stage and compensated liver function allow combination or sequential therapy, which was nearly impossible some years ago but is an option for most now. Primary liver cancer remains a difficult-to-treat malignancy, but the prognosis has improved remarkably, at least in the western world.
EVALuna2:1851

A mixed waveform protocol for reduction of the cardiac motion artifact in black-blood diffusion-weighted imaging of the liver - Rauh, Susanne S.; Riexinger, Andreas; Ohlmeyer, Sabine; Hammon, Matthias; Saake, Marc; Stemmer, Alto; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance Imaging, 2020)
Objective: Diffusion-weighted imaging (DWI) in the liver suffers from signal loss due to the cardiac motion artifact, especially in the left liver lobe. The purpose of this work was to improve the image quality of liver DWI in terms of cardiac motion artifact reduction and achievement of black-blood images in low b-value images. Material and methods: Ten healthy volunteers (age 20–31 years) underwent MRI examinations at 1.5 T with a prototype DWI sequence provided by the vendor. Two diffusion encodings (i.e. waveforms), monopolar and flow-compensated, and the b-values 0, 20, 50, 100, 150, 600 and 800 s/mm2 were used. Two Likert scales describing the severity of the pulsation artifact and the quality of the black-blood state were defined and evaluated by two experienced radiologists. Regions of interest (ROIs) were manually drawn in the right and left liver lobe in each slice and combined to a volume of interest (VOI). The mean and coefficient of variation were calculated for each normalized VOI-averaged signal to assess the severity of the cardiac motion artifact. The ADC was calculated using two b-values once for the monopolar data and once with mixed data, using the monopolar data for the small and the flow-compensated data for the high b-value. A Wilcoxon rank sum test was used to compare the Likert scores obtained for monopolar and flow-compensated data. Results: At b-values from 20 to 150 s/mm2, unlike the flow-compensated diffusion encoding, the monopolar encoding yielded black blood in all images with a negligible signal loss due to the cardiac motion artifact. At the b-values 600 and 800 s/mm2, the flow-compensated encoding resulted in a significantly reduced cardiac motion artifact, especially in the left liver lobe, and in a black-blood state. The ADC calculated with monopolar data was significantly higher in the left than in the right liver lobe. Conclusion: It is recommendable to use the following mixed waveform protocol: Monopolar diffusion encodings at small b-values and flow-compensated diffusion encodings at high b-values.
CRIS-Team Scopus Importer:2020-01-21

A model of chronic enthesitis and new bone formation characterized by multimodal imaging - Czegley, Christine; Gillmann, Clarissa; Schauer, Christine; Seyler, Lisa; Reinwald, Christiane; Hahn, Madelaine; Uder, Michael; Jochmann, Katja; Naschberger, Elisabeth; Stock, Michael; Schett, Georg; Bäuerle, Tobias; et al. (Disease Models & Mechanisms, 2018)
Enthesitis is a key feature of several different rheumatic diseases. Its pathophysiology is only partially known due to the lack of access to human tissue and the shortage of solid animal models for enthesitis. Here we aimed to develop a model, which mimics the effector phase of enthesitis and reliably leads to inflammation and new bone formation.Enthesitis was induced by local injection of monosodium urate crystals (MSU) into the metatarsal entheses of wild type (WT) or oxidative burst-deficient Ncf1** mice. Quantitative variables of inflammation (edema, swelling) and vascularization (tissue perfusion) were assessed by MRI, bone forming-activity by [18F]-fluoride-PET and destruction of cortical bone and new bone formation by CT. Non-invasive imaging was validated by histochemical and histomorphometric analysis.While injection of MSU crystals into WT mice triggered transient mild enthesitis with no new bone formation, Ncf1** mice developed chronic enthesitis accompanied by massive enthesiophytes. In MRI, inflammation and blood flow in the entheses were chronically increased while PET/CT showed osteoproliferation with enthesiophyte formation. Histochemical analyses showed chronic inflammation, increased vascularization, osteoclast differentiation and bone deposition in the affected entheseal sites.Herein we describe a fast and reliable effector model of chronic enthesitis, which is characterized by a combination of inflammation, vascularization and new bone formation. This model will help to disentangle the molecular pathways involved in the effector phase of enthesitis.
EVALuna2:34481

A Multicentric Comparison of Apparent Diffusion Coefficient Mapping and the Kaiser Score in the Assessment of Breast Lesions - Dietzel, Matthias; Krug, Barbara; Clauser, Paola; Burke, Christina; Hellmich, Martin; Maintz, David; Uder, Michael; Bickel, Hubert; Helbich, Thomas; Baltzer, Pascal A.T. (Investigative Radiology, 2021)
MATERIALS AND METHODS: In this multicentric study, individual patient data from 3 different centers were analyzed. Consecutive patients receiving standardized multiparametric breast magnetic resonance imaging for standard nonscreening indications were included. At each center, 2 experienced radiologists with more than 5 years of experience retrospectively interpreted the examinations in consensus and applied the KS to every histologically verified lesion. The corresponding mean ADC of each lesion was measured using a Wielema type 4 region of interest. According to established methods, the KS and ADC were combined, yielding the KS+ score. Diagnostic accuracy was evaluated by the area under the receiver operating characteristics curve (AUROC) and compared between the KS, ADC, and KS+ (DeLong test). Likewise, the potential to help avoid unnecessary biopsies was compared between the KS, ADC, and KS+ based on established high sensitivity thresholds (McNemar test). RESULTS: A total of 450 lesions in 414 patients (mean age, 51.5 years; interquartile range, 42-60.8 years) were included, with 219 lesions being malignant (48.7%; 95% confidence interval [CI], 44%-53.4%). The performance of the KS (AUROC, 0.915; CI, 0.886-0.939) was significantly better than that of the ADC (AUROC, 0.848; CI, 0.811-0.880; P < 0.001). The largest difference between these parameters was observed when assessing subcentimeter lesions (AUROC, 0.909 for KS; CI, 0.849-0.950 vs 0.811 for ADC; CI, 0.737-0.871; P = 0.02).The use of the KS+ (AUROC, 0.918; CI, 0.889-0.942) improved the performance slightly, but without any significant difference relative to a single KS or ADC reading (P = 0.64).When applying high sensitivity thresholds for avoiding unnecessary biopsies, the KS and ADC achieved equal sensitivity (97.7% for both; cutoff values, >4 for KS and ≤1.4 × 10-3 mm2/s for ADC). However, the rate of potentially avoidable biopsies was higher when using the KS (specificity: 65.4% for KS vs 32.9% for ADC; P < 0.0001). The KS was superior to the KS+ in avoiding unnecessary biopsies. CONCLUSIONS: Both the KS and ADC may be used to distinguish benign from malignant breast lesions. However, KS proved superior in this task including, most of all, when assessing small lesions less than 1 cm. Using the KS may avoid twice as many unnecessary biopsies, and the combination of both the KS and ADS does not improve diagnostic performance.
CRIS-Team Scopus Importer:2021-04-19

An AI classifier derived from 4D radiomics of dynamic contrast-enhanced breast MRI data: potential to avoid unnecessary breast biopsies - Poetsch, Nina; Dietzel, Matthias; Kapetas, Panagiotis; Clauser, Paola; Pinker, Katja; Ellmann, Stephan; Uder, Michael; Helbich, Thomas; Baltzer, Pascal A. T. (European Radiology, 2021)
Objectives Due to its high sensitivity, DCE MRI of the breast (bMRI) is increasingly used for both screening and assessment purposes. The high number of detected lesions poses a significant logistic challenge in clinical practice. The aim was to evaluate a temporally and spatially resolved (4D) radiomics approach to distinguish benign from malignant enhancing breast lesions and thereby avoid unnecessary biopsies. Methods This retrospective study included consecutive patients with MRI-suspicious findings (BI-RADS 4/5). Two blinded readers analyzed DCE images using a commercially available software, automatically extracting BI-RADS curve types and pharmacokinetic enhancement features. After principal component analysis (PCA), a neural network-derived A.I. classifier to discriminate benign from malignant lesions was constructed and tested using a random split simple approach. The rate of avoidable biopsies was evaluated at exploratory cutoffs (C-1, 100%, and C-2, >= 95% sensitivity). Results Four hundred seventy (295 malignant) lesions in 329 female patients (mean age 55.1 years, range 18-85 years) were examined. Eighty-six DCE features were extracted based on automated volumetric lesion analysis. Five independent component features were extracted using PCA. The A.I. classifier achieved a significant (p < .001) accuracy to distinguish benign from malignant lesion within the test sample (AUC: 83.5%; 95% CI: 76.8-89.0%). Applying identified cutoffs on testing data not included in training dataset showed the potential to lower the number of unnecessary biopsies of benign lesions by 14.5% (C-1) and 36.2% (C-2). Conclusion The investigated automated 4D radiomics approach resulted in an accurate A.I. classifier able to distinguish between benign and malignant lesions. Its application could have avoided unnecessary biopsies.
CRIS-Team WoS Importer:2021-04-02

Anatomical accuracy of abdominal lesion localization: Retrospective automatic rigid image registration between FDG-PET and MRI - Kiefer, Alexander; Kuwert, Torsten; Hahn, Dieter; Hornegger, Joachim; Uder, Michael; Ritt, Philipp (Nuklearmedizin-Nuclear Medicine, 2011)
Software-based image registration can improve the diagnostic value of imaging procedures and is an alternative to hybrid scanners. The aim of this study was to evaluate the anatomical accuracy of automatic rigid image registration of independently acquired datasets of positron emission tomography with F-deoxyglucose and abdominal magnetic resonance imaging. Patients, methods: Analyses were performed on 28 abdominal lesions from 20 patients. The PET data were obtained using a stand-alone PET camera in 14 cases and a hybrid PET/CT scanner in 9 cases. The abdominal T1- and T2-weighted MRI scans were acquired on 1.5 T MRI scanners. The mean time interval between MRI and PET was 7.3 days (0-28 days). Automatic rigid registration was carried out using a self-developed registration tool integrated into commercial available software (InSpace for Siemens Syngo). Distances between the centres of gravity of 28 manually delineated neoplastic lesions represented in PET and MRI were measured in X-, Y-, and Z-direction. The intra- (intraclass correlation 0.94) and inter- (intraclass correlation 0.86) Positronenemissionsobserver repeatability were high. Results: The average distance in all MRI sequences was 5.2 ± 7.6 mm in X-direction, 4. ± 3.7 mm in Y-direction and 6.1 ± 5.1 mm in Z-direction. There was a significantly higher misalignment in Z-direction (p < 0.05). The misalignment was not significantly different for the registration of T1- and T2- weighted sequences (p = 0.7). Conclusion: The misalignment between FDG-PET and abdominal MRI registered using an automated rigid registration tool was comparable to data reported for software-based fusion between PET and CT. Although this imprecision may not affect diagnostic accuracy, it is not sufficient to allow for pixel-wise integration of MRI and PET information. © Schattauer 2011.

A New Analysis of Resting State Connectivity and Graph Theory Reveals Distinctive Short-Term Modulations due to Whisker Stimulation in Rats - Kreitz, Silke; De Celis Alonso, Benito; Uder, Michael; Heß, Andreas (Frontiers in Neuroscience, 2018)
Resting state (RS) connectivity has been increasingly studied in healthy and diseased brains in humans and animals. This paper presents a new method to analyze RS data from fMRI that combines multiple seed correlation analysis with graph-theory (MSRA). We characterize and evaluate this new method in relation to two other graph-theoretical methods and ICA. The graph-theoretical methods calculate cross-correlations of regional average time-courses, one using seed regions of the same size (SRCC) and the other using whole brain structure regions (RCCA). We evaluated the reproducibility, power, and capacity of these methods to characterize short-term RS modulation to unilateral physiological whisker stimulation in rats. Graph-theoretical networks found with the MSRA approach were highly reproducible, and their communities showed large overlaps with ICA components. Additionally, MSRA was the only one of all tested methods that had the power to detect significant RS modulations induced by whisker stimulation that are controlled by family-wise error rate (FWE). Compared to the reduced resting state network connectivity during task performance, these modulations implied decreased connectivity strength in the bilateral sensorimotor and entorhinal cortex. Additionally, the contralateral ventromedial thalamus (part of the barrel field related lemniscal pathway) and the hypothalamus showed reduced connectivity. Enhanced connectivity was observed in the amygdala, especially the contralateral basolateral amygdala (involved in emotional learning processes). In conclusion, MSRA is a powerful analytical approach that can reliably detect tiny modulations of RS connectivity. It shows a great promise as a method for studying RS dynamics in healthy and pathological conditions.
EVALuna2:34696

A new approach of three-dimensional guidance in paediatric cath lab: segmented and tessellated heart models for cardiovascular interventions in CHD - Ehret, Nicole; Alkassar, Muhannad; Dittrich, Sven; Cesnjevar, Robert; Ruffer, Andre; Uder, Michael; Rompel, Oliver; Hammon, Matthias; Glöckler, Martin (Cardiology in the Young, 2018)
BACKGROUND: Optimal imaging is essential for catheter-based interventions in CHD. The three-dimensional models in volume-rendering technique currently in use are not standardised. This paper investigates the feasibility and impact of novel three-dimensional guidance with segmented and tessellated three-dimensional heart models in catheterisation of CHD. In addition, a nearly radiation-free two- to three-dimensional registration and a biplane overlay were used.Methods and resultsWe analysed 60 consecutive cases in which segmented tessellated three-dimensional heart models were merged with live fluoroscopy images and aligned using the tracheal bifurcation as a fiducial mark. The models were generated from previous MRI or CT by dedicated medical software. We chose the stereo-lithography format, as this promises advantage over volume-rendering-technique models regarding visualisation. Prospects, potential benefits, and accuracy of the two- to three-dimensional registration were rated separately by two paediatric interventionalists on a five-point Likert scale. Fluoroscopy time, radiation dose, and contrast dye consumption were evaluated. Over a 10-month study period, two- to three-dimensional image fusion was applied to 60 out of 354 cases. Of the 60 catheterisations, 73.3% were performed in the context of interventions. The accuracy of two- to three-dimensional registration was sufficient in all cases. Three-dimensional guidance was rated superior to conventional biplane imaging in all 60 cases. We registered significantly smaller amounts of used contrast dye (p<0.01), lower levels of radiation dose (p<0.02), and less fluoroscopy time (p<0.01) during interventions concerning the aortic arch compared with a control group. CONCLUSIONS: Two- to three-dimensional image fusion can be applied successfully in most catheter-based interventions of CHD. Meshes in stereo-lithography format are accurate and base for standardised and reproducible three-dimensional models.
EVALuna2:34698

An optimized b-value distribution for triexponential intravoxel incoherent motion (IVIM) in the liver - Riexinger, Andreas; Martin, Jan; Wetscherek, Andreas; Kuder, Tristan Anselm; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2020)
Purpose: To find an optimized b-value distribution for reproducible triexponential intravoxel incoherent motion (IVIM) exams in the liver. Methods: A numeric optimization of b-value distributions was performed using the triexponential IVIM equation and 27 different IVIM parameter sets. Starting with an initially optimized distribution of 6 b-values, the number of b-values was increased stepwise. Each new b-value was chosen from a set of 64 predefined b-values based on the computed summed relative mean error of the fitted triexponential IVIM parameters. This process was repeated for up to 100 b-values. In simulations and in vivo measurements, optimized b-value distributions were compared to 4 representative distributions found in literature. Results: The first 16 optimized b-values were 0, 0.3, 0.3, 70, 200, 800, 70, 1, 3.5, 5, 70, 1.2, 6, 45, 1.5, and 60 in units of s/mm2. Low b-values were much more frequent than high b-values. The optimized b-value distribution resulted in a higher fit stability compared to distributions used in literature in both, simulation and in vivo measurements. Using more than 6 b-values, ideally 16 or more, increased the fit stability considerably. Conclusion: Using optimized b-values, the fit uncertainty in triexponential IVIM can be largely reduced. Ideally, 16 or more b-values should be acquired.
CRIS-Team Scopus Importer:2020-12-04
Keywords: diffusion; intravoxel incoherent motion; liver; MRI; optimization; triexponential

A Novel Pairwise Comparison-Based Method to Determine Radiation Dose Reduction Potentials of Iterative Reconstruction Algorithms, Exemplified Through Circle of Willis Computed Tomography Angiography - Ellmann, Stephan; Kammerer, Ferdinand; Brand, Michael; Allmendinger, Thomas; May, Matthias; Uder, Michael; Lell, Michael; Kramer, Manuel (Investigative Radiology, 2016)
The aim of this study was to determine the dose reduction potential of iterative reconstruction (IR) algorithms in computed tomography angiography (CTA) of the circle of Willis using a novel method of evaluating the quality of radiation dose-reduced images.This study relied on ReconCT, a proprietary reconstruction software that allows simulating CT scans acquired with reduced radiation dose based on the raw data of true scans. To evaluate the performance of ReconCT in this regard, a phantom study was performed to compare the image noise of true and simulated scans within simulated vessels of a head phantom. That followed, 10 patients scheduled for CTA of the circle of Willis were scanned according to our institute's standard protocol (100 kV, 145 reference mAs). Subsequently, CTA images of these patients were reconstructed as either a full-dose weighted filtered back projection or with radiation dose reductions down to 10% of the full-dose level and Sinogram-Affirmed Iterative Reconstruction (SAFIRE) with either strength 3 or 5. Images were marked with arrows pointing on vessels of different sizes, and image pairs were presented to observers. Five readers assessed image quality with 2-alternative forced choice comparisons.In the phantom study, no significant differences were observed between the noise levels of simulated and true scans in filtered back projection, SAFIRE 3, and SAFIRE 5 reconstructions.The dose reduction potential for patient scans showed a strong dependence on IR strength as well as on the size of the vessel of interest. Thus, the potential radiation dose reductions ranged from 84.4% for the evaluation of great vessels reconstructed with SAFIRE 5 to 40.9% for the evaluation of small vessels reconstructed with SAFIRE 3.This study provides a novel image quality evaluation method based on 2-alternative forced choice comparisons. In CTA of the circle of Willis, higher IR strengths and greater vessel sizes allowed higher degrees of radiation dose reduction.
EVALuna2:14492

Anti-citrullinated protein antibody positivity correlates with cartilage damage and proteoglycan levels in patients with rheumatoid arthritis in the hand joints - Renner, Nina; Krönke, Gerhard; Rech, Jürgen; Uder, Michael; Janka, Rolf Matthias; Lauer, Lars; Paul, Dominik; Herz, Barbara; Schlechtweg, Philipp; Hennig, Friedrich; Schett, Georg; Welsch, Götz (Arthritis and Rheumatology, 2014)
Objective: To investigate the factors associated with cartilage proteoglycan content in patients with rheumatoid arthritis (RA) Methods: 32 RA patients received high-field 3 Tesla Gadolinium-Enhanced MRI of Cartilage (dGEMRIC) for determining cartilage proteoglycan content. Measurements were performed in three individual cartilage regions (medial, central, lateral) of the metacarpophalangeal joints 2 and 3. dGEMRIC values were then related to disease duration, disease activity, anti-citrullinated protein antibody (ACPA) status, rheumatoid factor status and C-reactive protein level. Results: dGEMRIC values were not significantly different between the MCP2 and MCP3 joint. Inter-class correlations were high (>0.92) for all three (medial, central and lateral) cartilage compartments. dGEMRIC values were significantly lower in RA patients with longer disease duration (>=3 years) and those with ACPA positivity than those with a short disease duration (<3 years)(p=0.034) or negative ACPA (p=0.0002), respectively. In contrast, no association between cartilage proteoglycan content and disease activity, C-reactive protein level and rheumatoid factor status was found. Conclusion: Decreased cartilage proteoglycan content in RA patients is associated with disease duration and ACPA positivity but not with the actual disease activity, CRP level or rheumatoid factor status. These data suggest that the cumulative burden of inflammation as well as ACPA are the determinants for cartilage damage in RA.
EVALuna2:12983

Aortic annulus eccentricity before and after transcatheter aortic valve implantation: Comparison of balloon-expandable and self-expanding prostheses - Schuhbaeck, Annika; Weingartner, Christina; Schmid, Jasmin; Pflederer, Tobias; Rixe, Johannes; Nef, Holger; Schneider, Christian; Lell, Michael; Uder, Michael; Ensminger, Stephan; Feyrer, Richard; Weyand, Michael; et al. (European Journal of Radiology, 2015)
The geometry of the aortic annulus and implanted transcatheter aortic valve prosthesis might influence valve function. We investigated the influence of valve type and aortic valve calcification on post-implant geometry of catheter-based aortic valve prostheses.Eighty consecutive patients with severe aortic valve stenosis (mean age 82 ± 6 years) underwent computed tomography before and after TAVI. Aortic annulus diameters were determined. Influence of prosthesis type and degree of aortic valve calcification on post-implant eccentricity were analysed.Aortic annulus eccentricity was reduced in patients after TAVI (0.21 ± 0.06 vs. 0.08 ± 0.06, p<0.0001). Post-TAVI eccentricity was significantly lower in 65 patients following implantation of a balloon-expandable prosthesis as compared to 15 patients who received a self-expanding prosthesis (0.06 ± 0.05 vs. 0.15 ± 0.07, p<0.0001), even though the extent of aortic valve calcification was not different. After TAVI, patients with a higher calcium amount retained a significantly higher eccentricity compared to patients with lower amounts of calcium.Patients undergoing TAVI with a balloon-expandable prosthesis show a more circular shape of the implanted prosthesis as compared to patients with a self-expanding prosthesis. Eccentricity of the deployed prosthesis is affected by the extent of aortic valve calcification.
EVALuna2:12030

A Possible Distinct Molecular Subtype (Quintuple-Wildtype) of Metastatic Colorectal Cancer in First-Line Anti-EGFR Therapy with Cetuximab Plus FOLFIRI - Palliative Precision Therapy and a Multidisciplinary Treatment Approach: Interim Analysis of the IVOPAK II Trial with Early Results - Wein, Axel; Stöhr, Robert; Kersting, Stephan; Siebler, Jürgen; Merkel, Susanne; Busse, Daniel; Wolff, Kerstin; Ostermeier, Nicola; Neufert, Clemens; Vitali, Francesco; Eckstein, Markus; Roth, Jan-Peter; et al. (Oncology, 2021)
Objective: The study aimed to prospectively evaluate a new molecular biomarker panel (KRAS, NRAS, BRAF, PIK3CA, and ERBB2) for palliative first-line treatment of colorectal cancer (CRC), including a multidisciplinary treatment approach. The rate of secondary metastasis resections was assessed. Patients and Methods: A total of 40 patients with definitively nonresectable metastatic CRC were enrolled from 10 centers before the interim analysis (June 2019) of the IVOPAK II trial (Interdisciplinary Care with Quality Control in Palliative Treatment of Colorectal Cancer). After determination of 5 molecular biomarkers in the tumor (KRAS, exons 2-4; NRAS, exons 2-4; BRAF V600E; PIK3CA; and ERBB2), patients in the IVOPAK II study received FOLFIRI plus cetuximab for all-RAS/quintuple-wildtype disease and FOLFIRI plus bevacizumab in the case of RAS mutations. The current article presents the early description of the clinical outcome of the interim analysis of IVOPAK II comparing the all-RAS/quintuple-wildtype and RAS-mutations populations, including a multidisciplinary-treated case report of a quintuple-wildtype patient. Results: The quintuple-wildtype population treated with FOLFIRI plus cetuximab in first-line exhibited a significantly higher response rate and enhanced early tumor shrinkage in the interim analysis than the RAS-mutations population, as well as a high rate of secondary metastatic resections. Conclusion: Initial results of this new biomarker panel (quintuple-wildtype) are promising for anti-EGFR therapy with cetuximab plus doublet chemotherapy (FOLFIRI) in first-line treatment of metastatic CRC. These results warrant confirmation with higher case numbers in the IVOPAK II trial.
CRIS-Team WoS Importer:2021-11-05

Apparent Diffusion Coefficient (ADC) Histogram Analysis in Parotid Gland Tumors: Evaluating a Novel Approach for Differentiation between Benign and Malignant Parotid Lesions Based on Full Histogram Distributions. - Hepp, Tobias; Wüst, Wolfgang; Heiß, Rafael; May, Matthias; Kopp, Markus; Wetzl, Matthias; Treutlein, Christoph; Uder, Michael; Wiesmüller, Marco (Diagnostics, 2022)
The aim of this study was to assess the diagnostic value of ADC distribution curves for differentiation between benign and malignant parotid gland tumors and to compare with mean ADC values. 73 patients with parotid gland tumors underwent head-and-neck MRI on a 1.5 Tesla scanner prior to surgery and histograms of ADC values were extracted. Histopathological results served as a reference standard for further analysis. ADC histograms were evaluated by comparing their similarity to a reference distribution using Chi2-test-statistics. The assumed reference distribution for benign and malignant parotid gland lesions was calculated after pooling the entire ADC data. In addition, mean ADC values were determined. For both methods, we calculated and compared the sensitivity and specificity between benign and malignant parotid gland tumors and three subgroups (pleomorphic adenoma, Warthin tumor, and malignant lesions), respectively. Moreover, we performed cross-validation (CV) techniques to estimate the predictive performance between ADC distributions and mean values. Histopathological results revealed 30 pleomorphic adenomas, 22 Warthin tumors, and 21 malignant tumors. ADC histogram distribution yielded a better specificity for detection of benign parotid gland lesions (ADChistogram: 75.0% vs. ADCmean: 71.2%), but mean ADC values provided a higher sensitivity (ADCmean: 71.4% vs. ADChistogram: 61.9%). The discrepancies are most pronounced in the differentiation between malignant and Warthin tumors (sensitivity ADCmean: 76.2% vs. ADChistogram: 61.9%; specificity ADChistogram: 81.8% vs. ADCmean: 68.2%). Using CV techniques, ADC distribution revealed consistently better accuracy to differentiate benign from malignant lesions ("leave-one-out CV" accuracy ADChistogram: 71.2% vs. ADCmean: 67.1%). ADC histogram analysis using full distribution curves is a promising new approach for differentiation between primary benign and malignant parotid gland tumors, especially with respect to the advantage in predictive performance based on CV techniques.
EVALuna2:506315

Application of Acoustic Radiation Force Impulse (ARFI) Elastography in Imaging of Delayed Onset Muscle Soreness (DOMS): A Comparative Analysis With 3T MRI - Hotfiel, Thilo; Kellermann, Marion; Swoboda, Bernd; Wildner, Dane; Golditz, Tobias; Grim, Casper; Raithel, Martin; Uder, Michael; Heiß, Rafael (Journal of Sport Rehabilitation, 2017)
DOMS is one of the most common reasons for impaired muscle performance in sports and is associated with reduced muscle strength and frequently observed both in professional and recreational athletes.To emphasize the diagnostic value of Acoustic Radiation Force Impulse (ARFI) in imaging of Delayed Onset Muscle Soreness by comparing findings to high-resolution 3T MRI T2 weighted sequences.Case series.Laboratory environment.Fifteen healthy students (7 female, 8 male, age 24 ± 4 years, height 178 ± 10 cm, body weight 67 ± 12 kg).ARFI values, represented as shear wave velocities (SWV) of the gastrocnemius muscle (GM) and soleus muscle (SM), as well as conventional ultrasound, high-resolution 3T MRI, creatine kinase activity, extension range of the ankle joint, calf circumference and muscle soreness were assessed before (baseline) and 60 hours after (post-intervention, PI) a standardized eccentric exercise.ARFI SWV values of the GM revealed a statistically significant decrease of 19.1% between baseline (2.2 ± 0.26 m/s) and PI (1.78 ± 0.24 m/s); p=0.008. At follow-up, the MRI investigations showed intramuscular oedema for the GM in all participants corresponding to a significant raise in T2 signal intensity (p=0.001) and in T2-time values (p=0.004).ARFI elastography seems to be an additional sensitive diagnostic modality in the diagnostic work up of DOMS. Intramuscular SWV could represent an additional imaging marker for the assessment and monitoring of ultrastructural muscle injuries and therefore be helpful for individual training composition in elite sports.
EVALuna2:10902

Application of Dual-Source-Computed Tomography in Pediatric Cardiology in Children Within the First Year of Life - Hausmann, P.; Stenger, Anna; Dittrich, Sven; Cesnjevar, Robert; Rueffer, A.; Hammon, Matthias; Uder, Michael; Rompel, O.; Glöckler, Martin (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
To assess fields of application and value of dual source computed tomography (DSCT) for diagnostics and therapy in patients with congenital heart disease during their first year of life. Evaluation of image quality, surgical use and radiation exposure of 2nd and 3 rd generation DSCT.DSCT was applied in 118 cases between January 2012 and October 2014 for diagnostics of congenital heart defects. 2nd generation was used in 91 cases until April 2014 and 3 rd generation in 27 cases during the period thereafter. 3 D reconstructions of the image data were created for clinical diagnostics and planning of interventions. Image quality was assessed using a 4-point-scale. The visibility of the mammary arteries was analyzed, and signal-to-noise-ratio (SNR) and contrast-to-noise-ratio (CNR) were calculated. The usefulness of 3D-reconstructions for surgical planning was rated using a 5-point-scale. Radiation exposure and contrast dye consumption were determined. All cases were analyzed retrospectively.DSCT was successfully used in 118 cases. All image data obtained were interpretable. More than 60 percent of cases did not show any artifacts. The mammary arteries were visible down to the diaphragmatic arch in more than 80 percent of cases. Diagnostic value and surgical benefit were evaluated as "useful" or as "essential" in all cases. Median radiation dose was 0.4 mSv and 0.27 mSv for the 2nd and 3 rd generation DSCT, respectively. Consumption of contrast dye was 2 ml/kg in all cases.DSCT is a modern and extremely helpful technique for diagnostics and planning of interventions in patients with complex congenital heart defects. Extracardiac vascular structures in particular can be depicted three-dimensionally at high resolution. The use of iterative reconstruction with 3 rd generation DSCT yielded image quality similar to that of 2nd generation DSCT at considerably reduced radiation exposure level compared to 2nd generation DSCT. 3 rd generation DSCT is a low risk, accurate and extremely fast technique for diagnosing unstable patients with CHD.Expanded scope of indications for DSCT in diagnosing critically ill infants. Effective radiation dose is considerably lower than 0.5 mSv. Extremely rapid image acquisitions with high image quality. Possibility of optimized 3D-based surgical planning
EVALuna2:14590

Application of machine learning algorithms for multiparametric MRI-based evaluation of murine colitis - Ellmann, Stephan; Langer, Victoria; Britzen-Laurent, Nathalie; Hildner, Kai; Huber, Carina; Tripal, Philipp; Seyler, Lisa; Waldner, Maximilian; Uder, Michael; Stürzl, Michael; Bäuerle, Tobias (PLoS ONE, 2018)
Magnetic resonance imaging (MRI) allows non-invasive evaluation of inflammatory bowel disease (IBD) by assessing pathologically altered gut. Besides morphological changes, relaxation times and diffusion capacity of involved bowel segments can be obtained by MRI. The aim of this study was to assess the use of multiparametric MRI in the diagnosis of experimentally induced colitis in mice, and evaluate the diagnostic benefit of parameter combinations using machine learning. This study relied on colitis induction by Dextran Sodium Sulfate (DSS) and investigated the colon of mice in vivo as well as ex vivo. Receiver Operating Characteristics were used to calculate sensitivity, specificity, positive- and negative-predictive values (PPV and NPV) of these single values in detecting DSS-treatment as a reference condition. A Model Averaged Neural Network (avNNet) was trained on the multiparametric combination of the measured values, and its predictive capacity was compared to those of the single parameters using exact binomial tests. Within the in vivo subgroup (n = 19), the avNNet featured a sensitivity of 91.3% (95% CI: 86.6-96.0%), specificity of 92.3% (95% CI: 85.1-99.6%), PPV of 96.9% (94.0-99.9%) and NPV of 80.0% (95% CI: 69.9-90.1%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.003) and performing significantly worse compared to none of the single values. Within the ex vivo subgroup (n = 30), the avNNet featured a sensitivity of 87.4% (95% CI: 82.6-92.2%), specificity of 82.9% (95% CI: 76.1-89.7%), PPV of 88.9% (84.3-93.5%) and NPV of 80.8% (95% CI: 73.8-87.9%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.015), exceeded by none of the single parameters. In experimental mouse colitis, multiparametric MRI and the combination of several single measured values to an avNNet can significantly increase diagnostic accuracy compared to the single parameters alone. This pilot study will provide new avenues for the development of an MR-derived colitis score for optimized diagnosis and surveillance of inflammatory bowel disease.
EVALuna2:35135

A Retrieval-Based Computer-Aided Diagnosis System for theCharacterization of Liver Lesions in CT Scans - Dankerl, Peter; Cavallaro, Alexander Josef; Tsymbal, Alexey; Costa, Maria Jimena; Suehling, Michael; Janka, Rolf Matthias; Uder, Michael; Hammon, Matthias (Academic Radiology, 2013)
Rationale and Objectives: To evaluate a computer-aided diagnosis (CADx) system for the characterization of liver lesions in computed tomography (CT) scans. The stand-alone predictive performance of the CADx system was assessed and compared to that of three radiologists who were provided with the same amount of image information to which the CADx system had access. Materials and Methods: The CADx system operates as an image search engine exploiting texture analysis of liver lesion image data forthe lesion in question and lesions from a database. A region of interest drawn around an indeterminate liver lesion is used as input query. The CADx system retrieves lesions of similar histology (benign/malignant), density (hypodense/hyperdense), or type (cyst/hemangioma/metastasis). The system's performance was evaluated with leave-one-patient-out receiver operating characteristic area under the curve on 685 CT scans from 372 patients that contained 2325 liver lesions (193<1cm3). Sensitivity, specificity, and positive and negative predictive values were evaluated separately for subcentimeter lesions. Results were compared to those of three radiologists who rated 83 liver lesions (20 hemangiomas, 20 metastases, 20 cysts, 20 hepatocellular carcinomas, and 3 focal nodular hyperplasias) displaying only the liver. Results: The CADx system's leave-one-patient-out receiver operating characteristic area under the curve was 97.1% for density, 91.4% for histology, and 95.5% for lesion type. For subcentimeter lesions, input of additional semantic information improved the system's performance. The CADx system has been proved to significantly outperform radiologists in discriminating lesion histology and type, provided the radiologists have no access to information other than the image. The radiologists were most reliable in diagnosing hemangioma given the limited image data. Conclusions: The CADx system under study discriminated reliably between various liver lesions, even outperforming radiologists whenaccessing the same image information and demonstrated promising performance in classifying subcentimeter lesions in particular. © 2013 AUR.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computer-assisted diagnosis; Hepatobiliary; Imaging technology; Special interest

Assessing muscle-specific potassium concentrations in human lower leg using potassium magnetic resonance imaging - Gast, Lena; Baier, Laura-Marie; Chaudry, Oliver; Meixner, Christian; Müller, Max; Engelke, Klaus; Uder, Michael; Heiß, Rafael; Nagel, Armin Michael (NMR in Biomedicine, 2022)
Noninvasively assessing tissue potassium concentrations (TPCs) using potassium magnetic resonance imaging (39K MRI) could give valuable information on physiological processes connected to various pathologies. However, because of inherently low 39K MR image resolution and strong signal blurring, a reliable measurement of the TPC is challenging. The aim of this work was to investigate the feasibility of a muscle-specific TPC determination with a focus on the influence of a varying residual quadrupolar interaction in human lower leg muscles. The quantification accuracy of a muscle-specific TPC determination was first assessed using simulated 39K MRI data. In vivo 39K and corresponding sodium (23Na) MRI data of healthy lower leg muscles (n = 14, seven females) were acquired on a 7-T MR system using a double-resonant 23Na/39K birdcage Tx/Rx RF coil. Additional 1H MR images were acquired on a 3-T MR system and used for tissue segmentation. Quantification of TPC was performed after a region-based partial volume correction (PVC) using five external reference phantoms. Simulations not only underlined the importance of PVC for correctly assessing muscle-specific TPC values, but also revealed the strong impact of a varying residual quadrupolar interaction between different muscle regions on the measured TPC. Using 39K T2* decay curves, we found significantly higher residual quadrupolar interaction in tibialis anterior muscle (TA; ωq = 194 ± 28 Hz) compared with gastrocnemius muscle (medial/lateral head, GM/GL; ωq = 151 ± 25 Hz) and soleus muscle (SOL; ωq = 102 ± 32 Hz). If considered in the PVC, TPC in individual muscles was similar (TPC = 98 ± 11/96 ± 14/99 ± 8/100 ± 12 mM in GM/GL/SOL/TA). Comparison with tissue sodium concentrations suggested that residual quadrupolar interactions might also influence the 23Na MRI signal of lower leg muscles. A TPC determination of individual lower leg muscles is feasible and can therefore be applied in future studies. Considering a varying residual quadrupolar interaction for PVC of 39K MRI data is essential to reliably assess potassium concentrations in individual muscles.
CRIS-Team Scopus Importer:2022-09-16
Keywords: 7 T; muscle MRI; potassium (; sodium (; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Assessing the variability of 23Na MRI in skeletal muscle tissue: Reproducibility and repeatability of tissue sodium concentration measurements in the lower leg at 3 T - Gerhalter, Teresa; Gast, Lena; Marty, Benjamin; Uder, Michael; Carlier, Pierre G.; Nagel, Armin Michael (NMR in Biomedicine, 2020)
The goal of this study was to evaluate the reproducibility and repeatability of tissue sodium concentration (TSC) measurements using 23Na MRI in skeletal muscle tissue. 23Na MRI was performed at 3 T on the right lower leg of eight healthy volunteers (aged 28 ± 4 years). The examinations were repeated at the same site after 22 weeks to assess the variability over a medium-term period. Additionally, they were scanned at a second site shortly before or shortly after the first visit (within 3 weeks) to evaluate the inter-site reproducibility. Moreover, we analysed the effect of B0 correction on the variability. Coefficients of variations (CVs) from mean TSC values as well as Bland–Altman plots were used to assess intra-site repeatability and inter-site reproducibility. In phantom measurements, the B0 correction improved the quantitative accuracy. We observed differences of up to 4.9 mmol/L between the first and second visit and a difference of up to 3.7 mmol/L between the two different sites. The CV for the medium-term repeatability was 15% and the reproducibility CV was 9%. The Bland–Altman plots indicated high agreement between the visits in all muscle regions. The systematic bias of −0.68 mmol/L between site X and Y (P = 0.03) was slightly reduced to −0.64 mmol/L after B0 correction (P = 0.04). This work shows that TSC measurements in healthy skeletal muscle tissue can be performed with good repeatability and reproducibility, which is of importance for future longitudinal or multicentre studies.
CRIS-Team Scopus Importer:2020-03-17
Keywords: quantification; repeatability; reproducibility; skeletal muscle tissue; sodium MRI; total tissue sodium content

ASSESSMENT OF KNEE JOINT SYNOVITIS AT ULTRA-HIGH FIELD (7T) MRI: A MULTI-DIMENSIONAL APPROACH USING CONTRAST-ENHANCED AND NON-ENHANCED SEQUENCES - Roemer, Frank; Treutlein, Christoph; Guermazi, A.; Nagel, Armin Michael; Schett, Georg; Uder, Michael; Bäuerle, Tobias (OSTEOARTHRITIS AND CARTILAGE, 2020)
CRIS-Team WoS Importer:2020-05-29

Assessment of myocardial fibrosis in patients with systemic sclerosis using [Ga-68]Ga-FAPI-04-PET-CT - Treutlein, Christoph; Distler, Jörg; Tascilar, Koray; Chenguiti Fakhouri, Sara; Györfi, Andrea-Hermina; Atzinger, Armin; Matei, Alexandru-Emil; Dees, Clara; Büttner-Herold, Maike; Kuwert, Torsten; Prante, Olaf; Bäuerle, Tobias; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2022)
Purpose Myocardial fibrosis (MF) is a factor of poor prognosis in systemic sclerosis (SSc). Direct in-vivo visualization of fibroblast activation as early readout of MF has not been feasible to date. Here, we characterize (68)Gallium-labeled-Fibroblast-Activation-Inhibitor-04 ([Ga-68]Ga-FAPI-04)-PET-CT as a diagnostic tool in SSc-related MF.Methods In this proof-of-concept trial, six SSc patients with and eight without MF of the EUSTAR cohort Erlangen underwent [Ga-68]Ga-FAPI-04-PET-CT and cardiac MRI (cMRI) and clinical and serologic investigations just before baseline and during follow-up between January 2020 and December 2020. Myocardial biopsy was performed as clinically indicated.Results [Ga-68]Ga-FAPI-04 tracer uptake was increased in SSc-related MF with higher uptake in SSc patients with arrhythmias, elevated serum-NT-pro-BNP, and increased late gadolinium enhancement (LGE) in cMRI. Histologically, myocardial biopsies from cMRI- and [Ga-68]Ga-FAPI-04-positive regions confirmed the accumulation of FAP(+) fibroblasts surrounded by collagen deposits. We observed similar but not equal spatial distributions of [Ga-68]Ga-FAPI-04 uptake and quantitative cMRI-based techniques. Using sequential [Ga-68]Ga-FAPI-04-PET-CTs, we observed dynamic changes of [Ga-68]Ga-FAPI-04 uptake associated with changes in the activity of SSc-related MF, while cMRI parameters remained stable after regression of molecular activity and rather indicated tissue damage.Conclusions We present first in-human evidence that [Ga-68]Ga-FAPI-04 uptake visualizes fibroblast activation in SSc-related MF and may be a diagnostic option to monitor cardiac fibroblast activity in situ.
CRIS-Team WoS Importer:2023-02-10

ASSESSMENT OF SYSTEMIC SCLEROSIS RELATED MYOCARDIAL FIBROSIS BY 68GA-FAPI-04 PET/CT - Treutlein, Christoph; Schmidkonz, Christian; Tascilar, Koray; Chenguiti Fakhouri, Sara; Dees, Clara; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Bäuerle, Tobias; Kuwert, Torsten; Uder, Michael; Schett, Georg; Distler, Jörg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, J.; Fasching, Peter; Wunderle, M.; Heindl, F.; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, M.; Polifka, Iris; Wachter, David Lukas; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, Julius; Fasching, Peter; Wunderle, Marius; Heindl, Felix; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, Marcus; Polifka, Iris; Wachter, David; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: Mammography can identify calcifications up to 50–100 μm in size as a surrogate parameter for breast cancer or ductal carcinoma in situ (DCIS). Microcalcifications measuring <50 µm are also associated with breast cancer or DCIS and are frequently not detected on mammography, although they can be detected with dark-field imaging. This study examined whether additional breast examination using X-ray dark-field imaging can increase the detection rate of calcifications. Advances in knowledge: (1) evaluation of additional modality of breast imaging; (2) specific evaluation of breast calcifications. Implications for patient care: the addition of X-ray dark-field imaging to conventional mammography could detect additional calcifications. Methods: Talbot–Lau X-ray phase–contrast imaging and X-ray dark-field imaging were used to acquire images of breast specimens. The radiation dosage with the technique is comparable with conventional mammography. Three X-ray gratings with periods of 5–10 µm between the X-ray tube and the flat-panel detector provide three different images in a single sequence: the conventional attenuation image, differential phase image, and dark-field image. The images were read by radiologists. Radiological findings were marked and examined pathologically. The results were described in a descriptive manner. Results: A total of 81 breast specimens were investigated with the two methods; 199 significant structures were processed pathologically, consisting of 123 benign and 76 malignant lesions (DCIS or invasive breast cancer). X-ray dark-field imaging identified 15 additional histologically confirmed carcinoma lesions that were visible but not declared suspicious on digital mammography alone. Another four malignant lesions that were not visible on mammography were exclusively detected with X-ray dark-field imaging. Conclusions: Adding X-ray dark-field imaging to digital mammography increases the detection rate for breast cancer and DCIS associated lesions with micrometer-sized calcifications. The use of X-ray dark-field imaging may be able to provide more accurate and detailed radiological classification of suspicious breast lesions. Adding X-ray dark-field imaging to mammography may be able to increase the detection rate and improve preoperative planning in deciding between mastectomy or breast-conserving therapy, particularly in patients with invasive lobular breast cancer.
CRIS-Team Scopus Importer:2020-09-25
Keywords: breast cancer; interferometry; mammography; microcalcifications

Assessment of Treatment Response by 99mTc-MIP-1404 SPECT/CT: A Pilot Study in Patients With Metastatic Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp; et al. (Clinical Nuclear Medicine, 2018)
BACKGROUND: We investigated the role of Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) SPECT/CT of PSMA expression in the assessment of treatment response in patients with metastatic prostate cancer. METHODS: We retrospectively analyzed Tc-MIP-1404 SPECT/CT scans from 28 patients with metastatic prostate cancer examined before initiation and after completion of therapy. Eight of these patients had been treated with androgen deprivation therapy, 10 with docetaxel, and another 10 with external beam radiotherapy. On the CT images from SPECT/CT, treatment response was assessed according to RECIST 1.1 criteria; independently from that analysis, maximal standardized uptake values (SUVmax) were quantified in representative tumor lesions and treatment response assumed at differences in SUVmax greater than 30%. Radiographic response assessment was correlated to biochemical response (BR) based on prostate-specific antigen serum levels. RESULTS: The concordance rate between SPECT and BR was 75% (95% confidence interval [CI], 0.55-0.89) (Cohen κ = 0.57; 95% CI, 0.29-0.85; P ≤ 0.01), higher than for that between SPECT and CT with 57% (95% CI, 0.37-0.76) (κ = 0.40; 95% CI, 0.14-0.65; P ≤ 0.01), as well as that between CT and BR with 50% (95% CI, 0.31-0.69) (κ = 0.31; 95% CI, 0.06-0.57, P ≤ 0.05). Discordant findings between SPECT and CT were most likely due to limitations of CT in assessing metastases in lymph nodes, as well as bone involvement, which was sometimes not detectable on CT scans. CONCLUSIONS: The high agreement between treatment response, as assessed by Tc-MIP-1404 SPECT/CT and BR, suggests a possible role of that imaging tool for monitoring treatment in metastatic prostate cancer. Larger, ideally prospective trials are needed to help to reveal the full potential of SPECT imaging of PSMA expression in that regard.
EVALuna2:34693

Association between mammographic density and pregnancies relative to age and BMI: a breast cancer case-only analysis - Hack, Carolin; Emons, Julius; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Gaß, Paul; Haeberle, Lothar; Heindl, Felix; Hein, Alexander; Schulz-Wendtland, Rüdiger; Uder, Michael; Hartmann, Arndt; et al. (Breast Cancer Research and Treatment, 2017)
Percentage mammographic density (PMD) is a major risk factor for breast cancer (BC). It is strongly associated with body mass index (BMI) and age, which are themselves risk factors for breast cancer. This analysis investigated the association between the number of full-term pregnancies and PMD in different subgroups relative to age and BMI.Patients were identified in the breast cancer database of the University Breast Center for Franconia. A total of 2410 patients were identified, for whom information on parity, age, and BMI, and a mammogram from the time of first diagnosis were available for assessing PMD. Linear regression analyses were conducted to investigate the influence on PMD of the number of full-term pregnancies (FTPs), age, BMI, and interaction terms between them.As in previous studies, age, number of FTPs, and BMI were found to be associated with PMD in the expected direction. However, including the respective interaction terms improved the prediction of PMD even further. Specifically, the association between PMD and the number of FTPs differed in young patients under the age of 45 (mean decrease of 0.37 PMD units per pregnancy) from the association in older age groups (mean decrease between 2.29 and 2.39 PMD units). BMI did not alter the association between PMD and the number of FTPs.The effect of pregnancies on mammographic density does not appear to become apparent before the age of menopause. The mechanism that drives the effect of pregnancies on mammographic density appears to be counter-regulated by other influences on mammographic density in younger patients.
EVALuna2:14710

A Standard Mammography Unit - Standard 3D Ultrasound Probe Fusion Prototype: First Results - Schulz-Wendtland, Rüdiger; Jud, Sebastian; Fasching, Peter; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Wunderle, Marius; Gaß, Paul; Langemann, Hanna; Beckmann, Matthias; Emons, Julius (Geburtshilfe und Frauenheilkunde, 2017)
The combination of different imaging modalities through the use of fusion devices promises significant diagnostic improvement for breast pathology. The aim of this study was to evaluate image quality and clinical feasibility of a prototype fusion device (fusion prototype) constructed from a standard tomosynthesis mammography unit and a standard 3D ultrasound probe using a new method of breast compression.Imaging was performed on 5 mastectomy specimens from patients with confirmed DCIS or invasive carcinoma (BI-RADS ((TM)) 6). For the preclinical fusion prototype an ABVS system ultrasound probe from an Acuson S2000 was integrated into a MAMMOMAT Inspiration (both Siemens Healthcare Ltd) and, with the aid of a newly developed compression plate, digital mammogram and automated 3D ultrasound images were obtained.The quality of digital mammogram images produced by the fusion prototype was comparable to those produced using conventional compression. The newly developed compression plate did not influence the applied x-ray dose. The method was not more labour intensive or time-consuming than conventional mammography. From the technical perspective, fusion of the two modalities was achievable.In this study, using only a few mastectomy specimens, the fusion of an automated 3D ultrasound machine with a standard mammography unit delivered images of comparable quality to conventional mammography. The device allows simultaneous ultrasound - the second important imaging modality in complementary breast diagnostics - without increasing examination time or requiring additional staff.
EVALuna2:6849

Attenuation-based automatic kilovolt (kV)-selection in computedtomography of the chest: Effects on radiation exposure and imagequality - Eller, Achim; Wüst, Wolfgang; Scharf, Michael; Brand, Michael; Achenbach, Stephan; Uder, Michael; Lell, Michael (European Journal of Radiology, 2013)
Objectives: To evaluate an automated attenuation-based kV-selection in computed tomography of thechest in respect to radiation dose and image quality, compared to a standard 120 kV protocol.Materials and methods: 104 patients were examined using a 128-slice scanner. Fifty examinations (58 ± 15years, study group) were performed using the automated adaption of tube potential (100-140 kV), basedon the attenuation profile of the scout scan, 54 examinations (62 ± 14 years, control group) with fixed120 kV. Estimated CT dose index (CTDI) of the software-proposed setting was compared with a 120 kVprotocol. After the scan CTDI volume (CTDIvol) and dose length product (DLP) were recorded. Imagequality was assessed by region of interest (ROI) measurements, subjective image quality by two observerswith a 4-point scale (3 - excellent, 0 - not diagnostic).Results: The algorithm selected 100 kV in 78% and 120 kV in 22%. Overall CTDIvol reduction was 26.6%(34% in 100 kV) overall DLP reduction was 22.8% (32.1% in 100 kV) (all p < 0.001). Subjective image qualitywas excellent in both groups.Conclusion: The attenuation based kV-selection algorithm enables relevant dose reduction (?27%) inchest-CT while keeping image quality parameters at high levels. © 2013 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Chest; Computed tomography; Dose reduction; Tube potentialImage quality

Automated artifact detection in abbreviated dynamic contrast-enhanced (DCE) MRI-derived maximum intensity projections (MIPs) of the breast - Kapsner, Lorenz; Ohlmeyer, Sabine; Folle, Lukas; Laun, Frederik Bernd; Nagel, Armin Michael; Liebert, Andrzej; Schreiter, Hannes; Beckmann, Matthias; Uder, Michael; Wenkel, Evelyn; Bickelhaupt, Sebastian (European Radiology, 2022)
Objectives To automatically detect MRI artifacts on dynamic contrast-enhanced (DCE) maximum intensity projections (MIPs) of the breast using deep learning. Methods Women who underwent clinically indicated breast MRI between October 2015 and December 2019 were included in this IRB-approved retrospective study. We employed two convolutional neural network architectures (ResNet and DenseNet) to detect the presence of artifacts on DCE MIPs of the left and right breasts. Networks were trained on images acquired up to and including the year 2018 using a 5-fold cross-validation (CV). Ensemble classifiers were built with the resulting CV models and applied to an independent holdout test dataset, which was formed by images acquired in 2019. Results Our study sample contained 2265 examinations from 1794 patients (median age at first acquisition: 50 years [IQR: 17 years]), corresponding to 1827 examinations of 1378 individuals in the training dataset and 438 examinations of 416 individuals in the holdout test dataset with a prevalence of image-level artifacts of 53% (1951/3654 images) and 43% (381/876 images), respectively. On the holdout test dataset, the ResNet and DenseNet ensembles demonstrated an area under the ROC curve of 0.92 and 0.94, respectively. Conclusion Neural networks are able to reliably detect artifacts that may impede the diagnostic assessment of MIPs derived from DCE subtraction series in breast MRI. Future studies need to further explore the potential of such neural networks to complement quality assurance and improve the application of DCE MIPs in a clinical setting, such as abbreviated protocol
Keywords: Artifacts; Magnetic resonance imaging; Breast; Contrast agent; Neural network

Automated Semi-Quantitative Analysis of Breast MRI: Potential Imaging Biomarker for the Prediction of Tissue Response to Neoadjuvant Chemotherapy - Dietzel, Matthias; Kaiser, Clemens; Pinker, Katja; Wenkel, Evelyn; Hammon, Matthias; Uder, Michael; Baiti, Barbara Bennani; Clauser, Paola; Schulz-Wendtland, Rüdiger; Baltzer, Pascal (Breast Care, 2017)
We aimed to investigate an automated semi-quantitative software as an imaging biomarker for the prediction of tissue response (TR) after completion of neoadjuvant chemotherapy (NAC).Breast magnetic resonance imaging (MRI) (1.5T, protocol according to international recommendations) of 67 patients with biopsy-proven invasive breast cancer were examined before and after NAC. After completion of NAC, histopathologic assessments of TR were classified according to the Chevallier grading system (CG1/4: full/non-responder; CG2/C3: partial responder). A commercially available fully automatic software (CADstream) extracted MRI parameters of tumor extension (tumor diameter/volume: TD/TV). Pre- versus post-NAC values were compared (?TV and ?TD). Additionally, the software performed volumetric analyses of vascularization (VAV) after NAC. Accuracy of MRI parameters to predict TR were identified (cross-tabs, ROC, AUC, Kruskal-Wallis).There were 37 (34.3%) CG1, 7 (6.5%) CG2, 53 (49.1%) CG3, and 11 (10.2%) CG4 lesions. The software reached area under the curve levels of 79.5% (CG1/complete response: ?TD), 68.6% (CG2, CG3/partial response: VAV), and 88.8% to predict TR (CG4/non-response: ?TV).Semi-quantitative automated analysis of breast MRI data enabled the prediction of tissue response to NAC.
EVALuna2:14712

Automated tube voltage adaptation in head and neck computed tomography between 120 and 100 kV: effects on image quality and radiation dose - May, Matthias; Kramer, Manuel; Eller, Achim; Wüst, Wolfgang; Scharf, Michael; Brand, Michael; Saake, Marc; Schmidt, Bernhard; Uder, Michael; Lell, Michael (Neuroradiology, 2014)
Low tube voltage allows for computed tomography (CT) imaging with increased iodine contrast at reduced radiation dose. We sought to evaluate the image quality and potential dose reduction using a combination of attenuation based tube current modulation (TCM) and automated tube voltage adaptation (TVA) between 100 and 120 kV in CT of the head and neck.One hundred thirty consecutive patients with indication for head and neck CT were examined with a 128-slice system capable of TCM and TVA. Reference protocol was set at 120 kV. Tube voltage was reduced to 100 kV whenever proposed by automated analysis of the localizer. An additional small scan aligned to the jaw was performed at a fixed 120 kV setting. Image quality was assessed by two radiologists on a standardized Likert-scale and measurements of signal- (SNR) and contrast-to-noise ratio (CNR). Radiation dose was assessed as CTDIvol.Diagnostic image quality was excellent in both groups and did not differ significantly (p = 0.34). Image noise in the 100 kV data was increased and SNR decreased (17.8/9.6) in the jugular veins and the sternocleidomastoid muscle when compared to 120 kV (SNR 24.4/10.3), but not in fatty tissue and air. However, CNR did not differ statistically significant between 100 (23.5/14.4/9.4) and 120 kV data (24.2/15.3/8.6) while radiation dose was decreased by 7-8%.TVA between 100 and 120 kV in combination with TCM led to a radiation dose reduction compared to TCM alone, while keeping CNR constant though maintaining diagnostic image quality.
EVALuna2:14375

Automated tube voltage selection in thoracoabdominal computed tomography at high pitch using a third-generation dual-source scanner: image quality and radiation dose performance - Lurz, Markus; Lell, Michael; Wüst, Wolfgang; Eller, Achim; Scharf, Michael; Uder, Michael; May, Matthias (Investigative Radiology, 2015)
The objective of this study was to evaluate the radiation dose and image quality performance of thoracoabdominal examinations with an automated tube voltage selection (tube voltage adaptation), tube current modulation, and high pitch using a third-generation dual-source computed tomography (CT) compared intraindividually with 120-kV examinations with tube current modulation with special attention on clinically relevant lesions in the liver, the lungs, and extrahepatic soft tissues.This study was approved by the institutional review board. Computed tomography of the body was performed using a third-generation dual-source system in 95 patients (mean body mass index, 25 kg/m²; range, 18-35 kg/m²). For 49 of these patients, all calculated tube settings and resulting dose values were recorded for each of the 12 gradual contrast weightings of the tube voltage adaptation algorithm. Spiral CT was performed for all patients with an intermediate weighting (grade 7) in a portal venous phase at 120 reference kV, 180 reference mAs, and pitch of 1.55. Objective image quality was assessed on the basis of contrast-to-noise ratio. Subjective image quality was assessed on the basis of clarity and sharpness of anatomical and pathological structures as well as interfering beam hardening and spiral and motion artifacts (heart, lungs, diaphragm). Previous examinations on a 64-slice scanner served as reference.All examinations were rated good or excellent for clinical diagnosis. Automated tube voltage selection resulted in significantly lower effective radiation dose (9.5 mSv) compared with the reference (12.0 mSv; P < 0.01). Contrast-to-noise ratio and image quality of soft tissue lesions were significantly increased (P < 0.01). Motion artifacts were significantly reduced (P < 0.01).Automated tube voltage adaptation combined with high-pitch protocols allows for a substantial radiation dose reduction while substantially increasing the image quality, even at large-volume exposure.
EVALuna2:14497

Automated volumetric radiomic analysis of breast cancer vascularization improves survival prediction in primary breast cancer - Dietzel, Matthias; Schulz-Wendtland, Rüdiger; Ellmann, Stephan; Zoubi, Ramy; Wenkel, Evelyn; Hammon, Matthias; Clauser, Paola; Uder, Michael; Runnebaum, Ingo B.; Baltzer, Pascal A.T. (Scientific Reports, 2020)
To investigate whether automated volumetric radiomic analysis of breast cancer vascularization (VAV) can improve survival prediction in primary breast cancer. 314 consecutive patients with primary invasive breast cancer received standard clinical MRI before the initiation of treatment according to international recommendations. Diagnostic work-up, treatment, and follow-up was done at one tertiary care, academic breast-center (outcome: disease specific survival/DSS vs. disease specific death/DSD). The Nottingham Prognostic Index (NPI) was used as the reference method with which to predict survival of breast cancer. Based on the MRI scans, VAV was accomplished by commercially available, FDA-cleared software. DSD served as endpoint. Integration of VAV into the NPI gave NPIVAV. Prediction of DSD by NPIVAV compared to standard NPI alone was investigated (Cox regression, likelihood-test, predictive accuracy: Harrell’s C, Kaplan Meier statistics and corresponding hazard ratios/HR, confidence intervals/CI). DSD occurred in 35 and DSS in 279 patients. Prognostication of the survival outcome by NPI (Harrell’s C = 75.3%) was enhanced by VAV (NPIVAV: Harrell’s C = 81.0%). Most of all, the NPIVAV identified patients with unfavourable outcome more reliably than NPI alone (hazard ratio/HR = 4.5; confidence interval/CI = 2.14-9.58; P = 0.0001). Automated volumetric radiomic analysis of breast cancer vascularization improved survival prediction in primary breast cancer. Most of all, it optimized the identification of patients at higher risk of an unfavorable outcome. Future studies should integrate MRI as a “gate keeper” in the management of breast cancer patients. Such a “gate keeper” could assist in selecting patients benefitting from more advanced diagnostic procedures (genetic profiling etc.) in order to decide whether are a more aggressive therapy (chemotherapy) is warranted.
CRIS-Team Scopus Importer:2020-03-17

Automatic segmentation and annotation in radiology - Dankerl, Peter; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Radiologe, 2014)
The technical progress and broader indications for cross-sectional imaging continuously increase the number of radiological images to be assessed. However, as the amount of image information and available resources (radiologists) do not increase at the same pace and the standards of radiological interpretation and reporting remain consistently high, radiologists have to rely on computer-based support systems. Novel semantic technologies and software relying on structured ontological knowledge are able to "understand" text and image information and interconnect both. This allows complex database queries with both the input of text and image information to be accomplished. Furthermore, semantic software in combination with automatic detection and segmentation of organs and body regions facilitates personalized supportive information in topographical accordance and generates additional information, such as organ volumes. These technologies promise improvements in workflow; however, great efforts and close cooperation between developers and users still lie ahead.
EVALuna2:14374

A web based cross-platform application for teleconsultation in radiology - Kammerer, Ferdinand J.; Hammon, Matthias; Schlechtweg, Philipp; Uder, Michael; Schwab, Siegfried (Journal of Telemedicine and Telecare, 2015)
The growing complexity of radiologic examinations and interventional procedures requires frequent exchange of knowledge. Consequently a simple way to share and discuss patient images between radiology experts and with colleagues from other medical disciplines is needed. Aims of this work were the development and initial performance evaluation of a fast and user friendly, platform independent teleconsultation system for medical imaging. A local back end system receives DICOM images and generates anonymized JPEG files that are uploaded to an internet webserver. The front end running on that webserver comprises an image viewer with a specially developed pointer element for indicating findings to collaborative partners. The front end that uses only standard web technologies works on a variety of different platforms, mobile devices and desktop computers. Images can be accessed by simply calling up a special internet address in a web browser that may be exchanged between users (e.g. via email). A speed evaluation of the system showed good results: For example the preparation and upload of a standard head CT took less than 21 seconds. The data volume of the same series and the viewer application could be transferred to a mobile phone in less than 42 seconds via a UMTS network or in less than 3 seconds via a HSPA network. The presented system with its minimal hard- and software requirements, its simplicity and platform independence might be a promising tool in the increasingly important area of teleconsultation.
EVALuna2:14496

Benefits of Long Versus Short Thrombolysis Times for Acutely Thrombosed Hemodialysis Native Fistulas - Regus, Susanne; Lang, Werner; Heinz, Marco; Uder, Michael; Schmid, Axel (Vascular and Endovascular Surgery, 2017)
Local thrombolysis with a time of exposure to recombinant tissue plasminogen activator of 15 to 150 minutes is commonly used to declot acutely thrombosed hemodialysis fistulas. The duration of thrombolysis for the restoration of arteriovenous blood flow remains controversial. The aim of this study was to investigate the outcomes of long thrombolysis treatment (LTT, 3 hours or more) and short thrombolysis treatment (STT, less than 3 hours) in our institution.We retrospectively analyzed 86 interventional declotting procedures (28 STT and 58 LTT) applied to 86 acutely thrombosed hemodialysis fistulas. The intervention time (IT) following thrombolysis (from the initial fistulography to the end of the angioplasty maneuvers), the time of day of the intervention (ie, during working hours vs off-hours), and the need for temporary catheter placement (TCP) were assessed. Success was defined as complete access recanalization, and major adverse events were defined as ischemia, bleeding, and access rupture.The ITs were reduced after LTT (63.3 [9.3] minutes) compared to STT (106.7 [24.7], P = .01), but there was no difference in success rate (85.7% STT, 89.7% LTT, P = .722). While all (100%, 58/58) of the angioplasty maneuvers after LTT were performed during regular working hours, 75% (21/28) of those following STT were managed during off-hours ( P < .001). Despite the longer treatment, the need for TCP was not increased after LTT (10.7%) compared to STT (12.1%, P = .515), and the major complication rate was reduced (3.4% after LTT and 28.6% after STT, P = .004).Long thrombolysis treatment results in shorter and less complicated percutaneous stenosis treatments during regular working hours. Despite the LTT of up to 25 hours until access for dialysis was achieved, no increase in the risks of TCP or major adverse events were observed following LTT.
EVALuna2:14643

Bioabsorbable Unsintered Hydroxyapatite/Poly-l-Lactic Acid Pin Fixation of Osteochondritis Dissecans in Adolescents: Initial Experiences - Zeilinger, Martin Georg; Autenrieth, Christian; Remmel, Kerstin; Schuh, Alexander; Hammon, Matthias; Schraml, Annemarie; Uder, Michael; Rompel, Oliver (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Background This study sought to retrospectively evaluate the clinical and magnetic resonance imaging (MRI) outcomes of u-HA/PLLA pin (u-HA/PLLA: hydroxyapatite/poly-L-lactic acid) pin fixation of unstable osteochondritis dissecans (OCD) lesions of the knee. Methods Seven adolescent patients (four females and three males) with arthroscopically unstable OCD lesions of the knee were included. The mean age at diagnosis was 13.1 years. Clinical results were evaluated preoperatively and during follow-up using the Ogilvie-Harris score (0-15 points). MRI scans were performed preoperatively and during follow-up, with results evaluated using the Dipaola classification (grades 1-4). Mean follow-up time was 29 months. Results The median Ogilvie-Harris score improved from 13 points (range: 10-14 points) to 15 points (range: 13-15 points). Separately, the median Dipaola score improved from 3 points (range: 2-4 points) to 1 point (range: 1-4 points). No complications such as infection, synovitis, or intra-articular adhesion were observed. Conclusions Initial experiences using bioabsorbable u-HA/PLLA pins for the refixation of unstable OCD lesions in adolescents in the knee are promising, and MRI provides excellent monitoring of healing.
CRIS-Team Scopus Importer:2020-12-25
Keywords: bioabsorbable pins; juvenile; Osteochondritis dissecans; u-HA/PLLA

Biomechanical knee cartilage analysis in young professional soccer players by a T2 mapping unloading algorithm - Welsch, Götz; Waldenmeier, L; Evers, C; Janka, Rolf Matthias; Uder, Michael; Hennig, Friedrich; Lochmann, Matthias (Osteoarthritis and Cartilage, 2014)

Blood Pressure Pattern and Target Organ Damage in Patients With Chronic Kidney Disease - Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; Janka, Rolf Matthias; et al. (Hypertension, 2018)
In patients with chronic kidney disease, data on blood pressure (BP) pattern and its association with target organ damage, which indicates elevated cardiovascular risk, are sparse. In 305 treated hypertensive chronic kidney disease patients, we assessed BP pattern, left ventricular mass (magnetic resonance imaging), intima-media thickness (ultrasound), 24-hour-pulse wave velocity and 24-hour-central augmentation index (Mobil-O-Graph). Controlled hypertension (normal office and ambulatory BP) was found in 41% and sustained uncontrolled hypertension (elevated office and ambulatory BP) in 30% of patients. Misclassification of BP status occurred in 29%: white coat uncontrolled hypertension (elevated office but normal ambulatory BP) was detected in 11% and masked uncontrolled hypertension (normal office but elevated ambulatory BP) in 18% of patients. Left ventricular mass was increased in white coat uncontrolled hypertension (+11.2 g), masked uncontrolled hypertension (+9.4 g), and sustained uncontrolled hypertension (+16.6 g) compared with controlled hypertension. Intima-media thickness was similar across all 4 BP groups. Twenty-four hour-pulse wave velocity and 24-hour-central augmentation index were increased in masked uncontrolled hypertension (+0.5 m/sec and +2.5%) and sustained uncontrolled hypertension (+0.5 m/sec and +2.9%) compared with controlled hypertension. In conclusion, based on office BP measurements, misclassification of true BP status occurred in almost one-third of chronic kidney disease patients. Both types of misclassification (white coat uncontrolled hypertension and masked uncontrolled hypertension) were associated with parameters of target organ damage. Ambulatory BP monitoring should be used routinely to identify chronic kidney disease patients at high cardiovascular risk.
EVALuna2:34688

Blood pressure reduction after renal denervation in patients with or without chronic kidney disease - Günes-Altan, Merve; Schmid, Axel; Ott, Christian; Bosch, Agnes; Pietschner, Robert; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (Clinical Kidney Journal, 2024)
Background. Renal denervation (RDN) has emerged as an adjacent option for the treatment of hypertension. This analysis of the Erlanger registry aimed to compare the blood pressure (BP)-lowering effects and safety of RDN in patients with and without chronic kidney disease (CKD). Methods. In this single-center retrospective analysis, 47 patients with and 127 without CKD underwent radiofrequency-, ultrasound- or alcohol-infusion-based RDN. Office and 24-h ambulatory BP and estimated glomerular filtration rate (eGFR) were measured at baseline, and after 6 and 12 months. Results. A total of 174 patients with a mean age of 59.0 ± 10 years were followed up for 12 months. At baseline, mean eGFR was 55.8 ± 21 mL/min/1.73 m2 in patients with CKD and 87.3 ± 13 mL/min/1.73 m2 in patients without CKD. There was no significant eGFR decline in either of the groups during 12 months of follow-up. In patients without CKD, office systolic and diastolic BP were reduced by –15.3 ± 17.5/–7.9 ± 10.8 mmHg 6 months after RDN and by –16.1 ± 18.2/–7.7 ± 9.6 mmHg 12 months after RDN. In patients with CKD, office systolic and diastolic BP were reduced by –10.7 ± 24.0/–5.8 ± 13.2 mmHg 6 months after RDN and by –15.1 ± 24.9/–5.9 ± 12.9 mmHg 12 months after RDN. Accordingly, in patients without CKD, 24-h ambulatory systolic and diastolic BP were reduced by –7.2 ± 15.8/–4.9 ± 8.8 mmHg 6 months after RDN and by –9.0 ± 17.0/–6.2 ± 9.8 mmHg 12 months after RDN. In patients with CKD, 24-h systolic and diastolic BP were reduced by –7.4 ± 12.9/–4.2 ± 9.9 mmHg 6 months after RDN and by –8.0 ± 14.0/–3.6 ± 9.6 mmHg 12 months after RDN. There was no difference in the reduction of office and 24-h ambulatory BP between the two groups at any time point (all P > .2). Similar results have been found for the 6 months data. With exception of rare local adverse events, we did not observe any safety signals. Conclusion. According to our single-center experience, we observed a similar reduction in 24-h, day and night-time ambulatory BP as well as in-office BP in patients with and without CKD at any time point up to 12 months. We conclude that RDN is an effective and safe treatment option for patients with hypertension and CKD.
CRIS-Team Scopus Importer:2024-01-26
Keywords: blood pressure; chronic kidney disease; hypertension; post-hoc analysis; renal denervation

BLOOD PRESSURE REDUCTION AFTER RENAL DENERVATION IN PATIENTS WITH OR WITHOUT CHRONIC KIDNEY DISEASE: THE ERLANGER EXPERIENCE - Schmid, Axel; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland; Kannenkeril, Dennis (JOURNAL OF HYPERTENSION, 2023)
CRIS-Team WoS Importer:2023-03-17

BMD ACCURACY ERRORS IN PHANTOMLESS CALIBRATION OF CT SCANS: A SIMULATION STUDY - Bartenschlager, Stefan; Chaudry, Oliver; Dankerl, Peter; Uder, Michael; Engelke, Klaus (OSTEOPOROSIS INTERNATIONAL, 2021)
Opportunistic screening using existing CT images may be a new strategy to identify subjects at increased risk for osteoporotic fracture. Low bone mineral density (BMD) is a key parameter but routine clinical CT scans do not include a calibration phantom to calculate BMD from the measured CT values. An alternative is internal or phantomless calibration, which is based on the CT values of air and of internal tissues of the subject such as blood, muscle or adipose tissue. However, the composition and as a consequence the CT values of these so-called internal calibration materials vary among subjects, which introduces additional BMD accuracy errors compared to phantom based calibration. The objective of this study was to quantify these accuracy errors and to identify optimum combinations of internal calibration materials (IM) for BMD assessments in opportunistic screening. Based on the base material decomposition theory we demonstrate how BMD can be derived from the CT values of the internal calibration materials. 121 CT datasets of the lumbar spine form postmenopausal women were used to determine the population variance of blood assessed in the aorta or the inferior vena cava, skeletal muscle of the erector spinae or psoas, subcutaneous adipose tissue (SAT) and air. The corresponding standard deviations were used for error propagation to determine phantomless calibration related BMD accuracy errors. Using a CT value of 150 HU, a typical value of trabecular bone, simulated BMD accuracy errors for most IM combinations containing air as one of the two base materials were below 5% or 6 mg/cm3. The lowest errors were determined for the combination of blood and air (<2 mg/cm3). The combination of blood and skeletal muscle resulted in higher errors (>10.5% or >12 mg/cm3) and is not recommended. Due to possible age-related differences in tissue composition, the selection of IMs is suggested to be adapted according to the measured subject. In younger subjects without significant aortic calcifications, air and blood of the aorta may be the best combination whereas in elderly subjects, air and SAT (error of 4%) may be preferable. The use of skeletal muscle as one of the two IMs is discouraged, in particular in elderly subjects because of varying fatty infiltration. A practical implementation of the internal calibration with different IM pairs confirmed the theoretical results. In summary, compared to a phantom based calibration the phantomless approach used for opportunistic screening creates additional BMD accuracy errors of 2% or more, dependent on the used internal reference tissues. The impact on fracture prediction still must be evaluate
CRIS-Team WoS Importer:2022-03-04
Keywords: Opportunistic screening; BMD; Phantomless calibration; QCT; Accuracy errors; Base material decomposition

BMD accuracy errors specific to phantomless calibration of CT scans of the lumbar spine - Bartenschlager, Stefan; Dankerl, Peter; Chaudry, Oliver; Uder, Michael; Engelke, Klaus (Bone, 2022)
Opportunistic screening using existing CT images may be a new strategy to identify subjects at increased risk for osteoporotic fracture. Low bone mineral density (BMD) is a key parameter but routine clinical CT scans do not include a calibration phantom to calculate BMD from the measured CT values. An alternative is internal or phantomless calibration, which is based on the CT values of air and of internal tissues of the subject such as blood, muscle or adipose tissue. However, the composition and as a consequence the CT values of these so-called internal calibration materials vary among subjects, which introduces additional BMD accuracy errors compared to phantom based calibration. The objective of this study was to quantify these accuracy errors and to identify optimum combinations of internal calibration materials (IM) for BMD assessments in opportunistic screening. Based on the base material decomposition theory we demonstrate how BMD can be derived from the CT values of the internal calibration materials. 121 CT datasets of the lumbar spine form postmenopausal women were used to determine the population variance of blood assessed in the aorta or the inferior vena cava, skeletal muscle of the erector spinae or psoas, subcutaneous adipose tissue (SAT) and air. The corresponding standard deviations were used for error propagation to determine phantomless calibration related BMD accuracy errors. Using a CT value of 150 HU, a typical value of trabecular bone, simulated BMD accuracy errors for most IM combinations containing air as one of the two base materials were below 5% or 6 mg/cm3. The lowest errors were determined for the combination of blood and air (<2 mg/cm3). The combination of blood and skeletal muscle resulted in higher errors (>10.5% or >12 mg/cm3) and is not recommended. Due to possible age-related differences in tissue composition, the selection of IMs is suggested to be adapted according to the measured subject. In younger subjects without significant aortic calcifications, air and blood of the aorta may be the best combination whereas in elderly subjects, air and SAT (error of 4%) may be preferable. The use of skeletal muscle as one of the two IMs is discouraged, in particular in elderly subjects because of varying fatty infiltration. A practical implementation of the internal calibration with different IM pairs confirmed the theoretical results. In summary, compared to a phantom based calibration the phantomless approach used for opportunistic screening creates additional BMD accuracy errors of 2% or more, dependent on the used internal reference tissues. The impact on fracture prediction still must be evaluated.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Accuracy errors; Base material decomposition; BMD; Opportunistic screening; Phantomless calibration; QCT

Bone Structure Analysis of the Radius Using Ultrahigh Field (7T) MRI: Relevance of Technical Parameters and Comparison with 3T MRI and Radiography - Jarraya, Mohamed; Heiß, Rafael; Duryea, Jeffrey; Nagel, Armin Michael; Lynch, John A.; Guermazi, Ali; Weber, Marc-Andre; Arkudas, Andreas; Horch, Raymund E.; Uder, Michael; Roemer, Frank (Diagnostics, 2021)
Bone fractal signature analysis (FSA-also termed bone texture analysis) is a tool that assesses structural changes that may relate to clinical outcomes and functions. Our aim was to compare bone texture analysis of the distal radius in patients and volunteers using radiography and 3T and 7T magnetic resonance imaging (MRI)-a patient group (n = 25) and a volunteer group (n = 25) were included. Participants in the patient group had a history of chronic wrist pain with suspected or confirmed osteoarthritis and/or ligament instability. All participants had 3T and 7T MRI including T1-weighted turbo spin echo (TSE) sequences. The 7T MRI examination included an additional high-resolution (HR) T1 TSE sequence. Radiographs of the wrist were acquired for the patient group. When comparing patients and volunteers (unadjusted for gender and age), we found a statistically significant difference of horizontal and vertical fractal dimensions (FDs) using 7T T1 TSE-HR images in low-resolution mode (horizontal: p = 0.04, vertical: p = 0.01). When comparing radiography to the different MRI sequences, we found a statistically significant difference for low- and high-resolution horizontal FDs between radiography and 3T T1 TSE and 7T T1 TSE-HR. Vertical FDs were significantly different only between radiographs and 3T T1 TSE in the high-resolution mode; FSA measures obtained from 3T and 7T MRI are highly dependent on the sequence and reconstruction resolution used, and thus are not easily comparable between MRI systems and applied sequences.
CRIS-Team WoS Importer:2021-02-12

Brain tissues have single-voxel signatures in multi-spectral MRI - German, Alexander; Mennecke, Angelika; Martin, Jan; Hanspach, Jannis; Liebert, Andrzej; Herrler, Jürgen; Kuder, Tristan Anselm; Schmidt, Manuel; Nagel, Armin Michael; Uder, Michael; Dörfler, Arnd; Winkler, Jürgen; et al. (NeuroImage, 2021)
Since the seminal works by Brodmann and contemporaries, it is well-known that different brain regions exhibit unique cytoarchitectonic and myeloarchitectonic features. Transferring the approach of classifying brain tissues – and other tissues – based on their intrinsic features to the realm of magnetic resonance (MR) is a longstanding endeavor. In the 1990s, atlas-based segmentation replaced earlier multi-spectral classification approaches because of the large overlap between the class distributions. Here, we explored the feasibility of performing global brain classification based on intrinsic MR features, and used several technological advances: ultra-high field MRI, q-space trajectory diffusion imaging revealing voxel-intrinsic diffusion properties, chemical exchange saturation transfer and semi-solid magnetization transfer imaging as a marker of myelination and neurochemistry, and current neural network architectures to analyze the data. In particular, we used the raw image data as well to increase the number of input features. We found that a global brain classification of roughly 97 brain regions was feasible with gross classification accuracy of 60%; and that mapping from voxel-intrinsic MR data to the brain region to which the data belongs is possible. This indicates the presence of unique MR signals of different brain regions, similar to their cytoarchitectonic and myeloarchitectonic fingerprints.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Brain; Data Analysis; High-Field Imaging; Machine Learning; MRI; Segmentation

Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images - Wenkel, Evelyn; Janka, Rolf Matthias; Geppert, Christian; Kämmerer, Nadine; Hartmann, Arndt; Uder, Michael; Hammon, Matthias; Brand, Michael (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The aim was to evaluate a minimum echo time (minTE) protocol for breast magnetic resonance imaging (MRI) in patients with breast lesions compared to a standard TE (nTE) time protocol. Methods Breasts of 144 women were examined with a 1.5 Tesla MRI scanner. Additionally to the standard gradient-echo sequence with nTE (4.8 ms), a variant with minimum TE (1.2 ms) was used in an interleaved fashion which leads to a better temporal resolution and should reduce the scan time by approximately 50 %. Lesion sizes were measured and the signal-to-noise ratio (SNR) as well as the contrast-to-noise ratio (CNR) were calculated. Subjective confidence was evaluated using a 3-point scale before looking at the nTE sequences (1 = very sure that I can identify a lesion and classify it, 2 = quite sure that I can identify a lesion and classify it, 3 = definitely want to see nTE for final assessment) and the subjective image quality of all examinations was evaluated using a four-grade scale (1 = sharp, 2 = slight blur, 3 = moderate blur and 4 = severe blur/not evaluable) for lesion and skin sharpness. Lesion morphology and contrast enhancement were also evaluated. Results With minTE sequences, no lesion was rated with "definitely want to see nTE sequences for final assessment". The difference of the longitudinal and transverse diameter did not differ significantly (p > 0.05). With minTE, lesions and skin were rated to be significantly more blurry (p < 0.01 for lesions and p < 0.05 for skin). There was no difference between both sequences with respect to SNR, CNR, lesion morphology, contrast enhancement and detection of multifocal disease. Conclusion Dynamic breast MRI with a minTE protocol is feasible without a major loss of information (SNR, CNR, lesion morphology, contrast enhancement and lesion sizes) and the temporal resolution can be increased by a factor of 2 using minTE sequences. Key points · Increase of temporal resolution for a better in-flow curve.. · Dynamic breast MRI with a shorter TE time is possible without relevant loss of information.. · Possible decrease of the overall scan time.. Citation Format · Wenkel E, Janka R, Geppert C et al. Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images. Fortschr Röntgenstr 2017; 189: 137 - 145.
EVALuna2:6843

Breast MRI in the era of diffusion weighted imaging: do we still need signal-intensity time curves? - Dietzel, Matthias; Ellmann, Stephan; Schulz-Wendtland, Rüdiger; Clauser, Paola; Wenkel, Evelyn; Uder, Michael; Baltzer, Pascal A.T. (European Radiology, 2019)
Objective: Dynamic contrast-enhanced imaging of the initial (IP) and delayed phase (DP) is an integral part of any clinical breast MRI protocol. Furthermore, DWI is increasingly used as an add-on sequence by the breast-imaging community. We investigated whether DWI could be used as a substitute DP. Material and methods: One hundred thirty-two consecutive patients with equivocal or suspicious findings at ultrasound and/or mammography received a full diagnostic breast MRI according to international recommendations. Histopathological verification served as reference standard. We evaluated three sections of the MRI protocol: IP, DP, and apparent diffusion coefficient (ADC) maps derived from DWI. Circular ROIs (regions of interest, mean size 5–10 mm2) were drawn into the enhancing parts of the lesion (first postcontrast). ROIs were transferred to the corresponding location on ADC maps and IP and DP images. Mean ROI values were investigated signal intensity (SI): (1) Initial-phase enhancement = (SI(IP) − SI(precontrast))/SI(precontrast); (2) Delayed-phase enhancement = (SI(DP) − SI(IP))/SI(IP); (3) ADC. Multiparametric combinations were computed using logistic regression analysis: (1) IP+: Initial-phase enhancement and ADC; (2) Curve: Initial-phase enhancement and delayed-phase enhancement; (3) Curve+: Curve and ADC. The diagnostic performances of these feature combinations to diagnose malignancy were compared by the area under the receiver-operating characteristics curve (AUC). Results: One hundred thirty-two patients (age: mean = 57.1 years, range 23–83 years) with 145 lesions were included (malignant/benign 101/44). IP+ (AUC = 0.877) outperformed Curve (AUC = 0.788, p = 0.03). Curve+ was not superior to IP+ (p = 1). Conclusion: DWI could substitute DP. Because DWI is typically used as an add-on to IP and DP, our results might help to abbreviate and to simplify current practice of breast MRI. Key Points: • DWI provides similar but superior diagnostic information for diagnosis of malignancy in enhancing breast lesions compared to DP. • Adding DP to DWI does not provide incremental information to distinguish benign from malignant lesions. • DWI could substitute DP. As DWI is typically used as an add-on to IP and DP, our findings might help to abbreviate and to simplify current breast MRI practice.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Breast neoplasms; Diagnostic techniques and procedures; Differential diagnosis; Diffusion magnetic resonance imaging; Magnetic resonance imaging

Breast MRI in the era of diffusion weighted imaging: do we still need signal-intensity time curves? - Dietzel, Matthias; Ellmann, Stephan; Schulz-Wendtland, Rüdiger; Clauser, Paola; Wenkel, Evelyn; Uder, Michael; Baltzer, Pascal A. T. (European Radiology, 2020)
OBJECTIVE: Dynamic contrast-enhanced imaging of the initial (IP) and delayed phase (DP) is an integral part of any clinical breast MRI protocol. Furthermore, DWI is increasingly used as an add-on sequence by the breast-imaging community. We investigated whether DWI could be used as a substitute DP. MATERIAL AND METHODS: One hundred thirty-two consecutive patients with equivocal or suspicious findings at ultrasound and/or mammography received a full diagnostic breast MRI according to international recommendations. Histopathological verification served as reference standard. We evaluated three sections of the MRI protocol: IP, DP, and apparent diffusion coefficient (ADC) maps derived from DWI. Circular ROIs (regions of interest, mean size 5-10 mm2) were drawn into the enhancing parts of the lesion (first postcontrast). ROIs were transferred to the corresponding location on ADC maps and IP and DP images. Mean ROI values were investigated signal intensity (SI): (1) Initial-phase enhancement = (SI(IP) - SI(precontrast))/SI(precontrast); (2) Delayed-phase enhancement = (SI(DP) - SI(IP))/SI(IP); (3) ADC. Multiparametric combinations were computed using logistic regression analysis: (1) IP+: Initial-phase enhancement and ADC; (2) Curve: Initial-phase enhancement and delayed-phase enhancement; (3) Curve+: Curve and ADC. The diagnostic performances of these feature combinations to diagnose malignancy were compared by the area under the receiver-operating characteristics curve (AUC). RESULTS: One hundred thirty-two patients (age: mean = 57.1 years, range 23-83 years) with 145 lesions were included (malignant/benign 101/44). IP+ (AUC = 0.877) outperformed Curve (AUC = 0.788, p = 0.03). Curve+ was not superior to IP+ (p = 1). CONCLUSION: DWI could substitute DP. Because DWI is typically used as an add-on to IP and DP, our results might help to abbreviate and to simplify current practice of breast MRI. KEY POINTS: • DWI provides similar but superior diagnostic information for diagnosis of malignancy in enhancing breast lesions compared to DP. • Adding DP to DWI does not provide incremental information to distinguish benign from malignant lesions. • DWI could substitute DP. As DWI is typically used as an add-on to IP and DP, our findings might help to abbreviate and to simplify current breast MRI practice.
EVALuna2:210908

Breast MRI texture analysis for prediction of BRCA-associated genetic risk - Vasileiou, Georgia; Costa, Maria J.; Long, Christopher; Wetzler, Iris; Hoyer, Juliane; Kraus, Cornelia; Popp, Bernt; Emons, Julius; Wunderle, Marius; Wenkel, Evelyn; Uder, Michael; Beckmann, Matthias; et al. (BMC Medical Imaging, 2020)
BACKGROUND: BRCA1/2 deleterious variants account for most of the hereditary breast and ovarian cancer cases. Prediction models and guidelines for the assessment of genetic risk rely heavily on criteria with high variability such as family cancer history. Here we investigated the efficacy of MRI (magnetic resonance imaging) texture features as a predictor for BRCA mutation status. METHODS: A total of 41 female breast cancer individuals at high genetic risk, sixteen with a BRCA1/2 pathogenic variant and twenty five controls were included. From each MRI 4225 computer-extracted voxels were analyzed. Non-imaging features including clinical, family cancer history variables and triple negative receptor status (TNBC) were complementarily used. Lasso-principal component regression (L-PCR) analysis was implemented to compare the predictive performance, assessed as area under the curve (AUC), when imaging features were used, and lasso logistic regression or conventional logistic regression for the remaining analyses. RESULTS: Lasso-selected imaging principal components showed the highest predictive value (AUC 0.86), surpassing family cancer history. Clinical variables comprising age at disease onset and bilateral breast cancer yielded a relatively poor AUC ( 0.56). Combination of imaging with the non-imaging variables led to an improvement of predictive performance in all analyses, with TNBC along with the imaging components yielding the highest AUC (0.94). Replacing family history variables with imaging components yielded an improvement of classification performance of 4%, suggesting that imaging compensates the predictive information arising from family cancer structure. CONCLUSIONS: The L-PCR model uncovered evidence for the utility of MRI texture features in distinguishing between BRCA1/2 positive and negative high-risk breast cancer individuals, which may suggest value to diagnostic routine. Integration of computer-extracted texture analysis from MRI modalities in prediction models and inclusion criteria might play a role in reducing false positives or missed cases especially when established risk variables such as family history are missing.
CRIS-Team Scopus Importer:2020-08-07
Keywords: BRCA1/2; Breast cancer; HBOC; L-PCR; MRI; Texture analysis

Breast volume assessment with a smart phone device compared to MRI - Behrens, Annika; Wunderle, Marius; Häberle, Lothar; Stamminger, Marc; Zint, Daniel; Emons, Julius; Heindl, Felix; Hack, Caroline; Ohlmeyer, Sabine; Uder, Michael; Beckmann, Matthias; Fasching, Peter (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Can the documented patient briefing be carried out with an iPad App? - Schlechtweg, Philipp; Hammon, Matthias; Heberlein, Christian; Giese, David Andreas; Uder, Michael; Schwab, Siegfried (Journal of Digital Imaging, 2013)
To evaluate the feasibility of an iPad-based documented patient briefing for Magnetic Resonance Imaging (MRI) examinations. A standard briefing sheet and questionnaire for a MRI scan was converted from paper form into an iPad application. Twenty patients, who had been referred for an MRI scan, were briefed about the examination in paper form as well as via the iPad application before performing the MRI scan. Time each patient needed for the briefing and the number of questions that came up were documented. Patients' acceptance of the electronic briefing was assessed using a questionnaire. The mean processing time was 2.36 min (range 0.58 to 09.35 min., standard deviation ±2.05 min) for the paper-based briefing and 4.15 min (range 1.56 to 13.48 min, SD ± 2.36 min) for the app-based briefing. Concerning technical aspects, patients asked two questions during the app-based briefing; no questions arose during the paper-based briefing. Six patients preferred electronic briefing and four patients, the paper-based form. No patient preferred the electronic form with additional multimedial information. Eight participants did not mind which briefing version was used; two participants did not express their preference at all. Our experiences showed that electronic briefing using an iPad is feasible and has the potential to become a user-friendly alternative to the conventional paper-based approach. Owing to the broad range of the results, a follow-up study will seek to determine the influencing factors on processing time and other potential questions. © 2012 Society for Imaging Informatics in Medicine.
CRIS-Team Scopus Importer:2023-03-08
Keywords: App; Apple; Electronic patient consent; Feasibility; iPad; Tablet PC

Cardiac MRI: An Alternative Method to Determine the Left Ventricular Function - Michler, Kerstin; Hessman, Christopher; Prümmer, Marcus; Achenbach, Stephan; Uder, Michael; Janka, Rolf Matthias (Diagnostics, 2023)
(1) Background: With the conventional contour surface method (KfM) for the evaluation of cardiac function parameters, the papillary muscle is considered to be part of the left ventricular volume. This systematic error can be avoided with a relatively easy-to-implement pixel-based evaluation method (PbM). The objective of this thesis is to compare the KfM and the PbM with regard to their difference due to papillary muscle volume exclusion. (2) Material and Methods: In the retrospective study, 191 cardiac-MR image data sets (126 male, 65 female; median age 51 years; age distribution 20–75 years) were analysed. The left ventricular function parameters: end-systolic volume (ESV), end-diastolic volume (EDV), ejection fraction (EF) and stroke volume (SV) were determined using classical KfW (syngo.via and cvi42 = gold standard) and PbM. Papillary muscle volume was calculated and segmented automatically via cvi42. The time required for evaluation with the PbM was collected. (3) Results: The size of EDV was 177 mL (69–444.5 mL) [average, [minimum–maximum]], ESV was 87 mL (20–361.4 mL), SV was 88 mL and EF was 50% (13–80%) in the pixel-based evaluation. The corresponding values with cvi42 were EDV 193 mL (89–476 mL), ESV 101 mL (34–411 mL), SV 90 mL and EF 45% (12–73%) and syngo.via: EDV 188 mL (74–447 mL), ESV 99 mL (29–358 mL), SV 89 mL (27–176 mL) and EF 47% (13–84%). The comparison between the PbM and KfM showed a negative difference for end-diastolic volume, a negative difference for end-systolic volume and a positive difference for ejection fraction. No difference was seen in stroke volume. The mean papillary muscle volume was calculated to be 14.2 mL. The evaluation with PbM took an average of 2:02 min. (4) Conclusion: PbM is easy and fast to perform for the determination of left ventricular cardiac function. It provides comparable results to the established disc/contour area method in terms of stroke volume and measures “true” left ventricular cardiac function while omitting the papillary muscles. This results in an average 6% higher ejection fraction, which can have a significant influence on therapy decisions.
CRIS-Team Scopus Importer:2023-05-05
Keywords: cardiac MRI; cine MRI; ejection fraction; left ventricular function; MRI

Cardiac MRI in Children and Adolescents Who Have Undergone Surgical Repair of Right-Sided Congenital Heart Disease: Automated Left Ventricular Volumes and Function Analysis and Effects of Different Manual Adjustments - Rompel, O.; Janka, Rolf Matthias; May, Matthias; Glöckler, Martin; Cesnjevar, Robert; Dittrich, Sven; Lell, Michael; Uder, Michael; Hammon, Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To evaluate automated segmentation and the effects of different manual adjustments regarding left ventricular parameter quantification in cardiac magnetic resonance (MR) data on children and adolescents who have undergone surgical repair of right-sided congenital heart disease (CHD). Materials and Methods: Dedicated software (syngo.via, Siemens AG) was used to automatically segment and/or manually adjust the end-diastolic volume (EDV), end-systolic volume (ESV), stroke volume (SV), myocardial mass (MM) and ejection fraction (EF) before/after manual apex/base adjustment (ADJ-step 1) and after manual apex/base/myocardial contour adjustment (ADJ-step 2; reference standard). MR data of 40 patients (13.1 ± 3.1y, 4 - 17y) with repaired CHD with decreased pulmonary blood flow (CHD-DPBF) were evaluated. Intra- and inter-rater reliability was determined for 10 randomly selected patients. Results: The software correctly detected the left ventricle in 38/40 (95 %) patients. EDV after automated segmentation: 119.1 ± 44.0ml; after ADJ-step 1: 115.8 ± 39.5ml; after ADJ-step 2: 116.2 ± 39.4 ml. The corresponding results for ESV were 52.0 ± 18.5/49.6 ± 16.9/49.7 ± 16.4ml; for SV 67.1 ± 28.5/66.2 ± 25.4/66.5 ± 25.5ml; for EF 55.5 ± 7.3/56.7 ± 6.6/56.7 ± 6.3 %; for MM 83.7 ± 35.9/76.2 ± 28.3/74.6 ± 27.2 g. Significant differences were found for ESV/MM/EF comparing the automated segmentation results with these after ADJ-step 1 and ADJ-step 2. No significant differences were found when comparing all results of ADJ-step 1 and ADJ-step 2 or when comparing EDV/SV results. Intra- and inter-rater reliability was excellent. The mean time effort was 63.4 ± 6.9 s for the automated segmentation, 74.2 ± 8.9 s for ADJ-step 1 and 269.5 ± 39.4 s for ADJ-step 2. Conclusion: Automated left ventricular volumes and function analysis in children and adolescents with surgically treated CHD proved to be feasible with excellent intra- and inter-rater reliability. Automated segmentation with manual apex/base adjustment provided clinically acceptable results. Key Points: o?Automated left ventricular volume and function analysis in children and adolescents with surgically treated right-sided heart disease is feasible with excellent intra- and inter-rater reliability.o?Automated segmentation with manual apex/base adjustment provides clinically acceptable results.o?Additional manual myocardial contour adjustment does not significantly improve the results. Citation Format: o?Rompel O, Janka R, May MS et al. Cardiac MRI in Children and Adolescents Who Have Undergone Surgical Repair of Right-Sided Congenital Heart Disease: Automated Left Ventricular Volumes and Function Analysis and Effects of Different Manual Adjustments. Fortschr Röntgenstr 2015; 187: 1099 - 1107.
EVALuna2:14516

Cardiac T2 mapping: Robustness and homogeneity of standardized in-line analysis - Wiesmüller, Marco; Wüst, Wolfgang; Heiß, Rafael; Treutlein, Christoph; Uder, Michael; May, Matthias (Journal of Cardiovascular Magnetic Resonance, 2020)
Background and purpose: Interpretation of T2 values remains difficult due to limited comparability across hardware and software systems and the lack of validated measurement recommendations for the number and orientation of mandatory slices. Our aims were to provide a standardized comparison of intra- and inter-individual T2 values in the short and long axes and to investigate inter-scanner reproducibility. Method and materials: Ninety cardiovascular magnetic resonance (CMR) studies in 30 healthy subjects were performed with three identical 1.5 T CMR scanners (same hardware and software) using a balanced steady-state free precession (bSSFP) gradient echo sequence in three short axis (SAx) and three long axis (LAx) views. A commercially available T2 mapping software package of the latest generation with automatic in-line motion correction was used for acquisition. Regions of interest were manually drawn in each of the 16 myocardial segments according to the American Heart Association (AHA) model in three SAx and three LAx acquisitions. Analysis of inter-scanner, inter-segmental, intra-segmental, inter-regional and inter-level differences was performed. Results: Inter-scanner reproducibility was high and the mean myocardial T2 value for all evaluated segments was 45.7 ± 3.4 ms. Significant inter-segmental variations of mean T2 values were found. Mean intra-segmental T2 values were comparable between LAx and SAx acquisitions in 72%. Significantly higher T2 values were found in apical segments and a significant disparity among different regions was found for SAx and LAx orientations. Conclusion: Standardized cardiac T2 mapping is highly reproducible on identical CMR systems. T2 values vary significantly between single heart segments, regions, levels, and axes in young, healthy subjects.
CRIS-Team Scopus Importer:2020-06-09
Keywords: Cardiovascular imaging; cardiovascular magnetic resonance; MRI; T2 mapping

Cardiac T2 star mapping: standardized inline analysis of long and short axis at three identical 1.5 T MRI scanners - Heiß, Rafael; Wiesmüller, Marco; Treutlein, Christoph; Seuß, Hannes; Uder, Michael; May, Matthias; Wüst, Wolfgang (International Journal of Cardiovascular Imaging, 2019)
T2 star mapping can be applied for in vivo cardiac iron quantification. Current recommendations of imaging acquisition, post-processing and interpretation of normal values are based on old scanner types and in house software packages. A standardized comparison of short (SAX) and long axis (LAX) segments using commercially available software packages and modern scanners is lacking. To provide a standardized comparison of T2 star time values in SAX and LAX and to investigate intersegmental, interregional and inter-level comparison and the interscanner reproducibility. 84 cardiac MRIs in 28 healthy volunteers were performed with three structurally identical 1.5 T MRI scanners. A commercially available software package for T2 star mapping with automatic in-line motion correction was used for analysis. Regions of interest were manually placed in each of the 16 myocardial segments according to the AHA model in three SAX and three LAX. A total of 2856 ROIs were drawn and 102 segments per volunteer were analysed. Interscanner reproducibility was high (91%) and the mean myocardial T2 star time value for all evaluated segments was 34 ± 5.7 ms. No significant difference was found between all measurements in SAX (35 ± 5.5 ms) and LAX (34 ± 5.8 ms). T2 star time values varied significantly between heart segments in the same axis and in 44% between corresponding SAX and LAX segments. T2 star time values in SAX and LAX have a high interscanner reproducibility but can vary significantly between heart segments in the same axis. Comparability between corresponding SAX and LAX segments is limited. To get representative results T2 star time values should be obtained in more than one heart segment and for follow-up studies identical segments should be used to avoid a systematic bias.
EVALuna2:210886

Carotid CTA at the Lowest Tube Voltage (70 kV) in Comparison with Automated Tube Voltage Adaption - Eller, A.; Wiesmüller, Marco; Wüst, Wolfgang; Heiß, Rafael; Kopp, Markus; Saake, Marc; Brand, Michael; Uder, Michael; May, Matthias (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: CTA is the imaging modality of choice in many institutions for the evaluation of the supraaortic vessels, but radiation exposure remains a matter of concern. Our aim was to evaluate a 70-kV protocol for CT angiography of the carotid arteries with respect to image quality and radiation exposure compared with automated tube voltage adaption. MATERIALS AND METHODS: A total of 90 consecutive patients were included in this prospective study and randomized to the study group (n = 45, 70 kV) or control group (n = 45, automated tube voltage adaptation). Volume CT dose indices and dose-length products were recorded in the examination protocol. Image quality was assessed as arterial vessel contrast, signal-to-noise ratio, contrast-to-noise ratio, and contrast-to-noise ratio in reference to the radiation dose. Subjective overall image-quality analysis, image-artifact analysis, and diagnostic evaluation were performed by 2 observers by using a 4-point Likert scale. RESULTS: Radiation exposure was significantly lower in the study group (volume CT dose index reduced by 22%, dose-length product reduction by 20%; each P < .001). Contrast (P = .15), SNR (P = .4), and contrast-to-noise ratio (P = .5) did not show significant differences between the groups. The contrast-to-noise ratio in reference to the radiation dose was not significantly increased using the study protocol (P = .2). Subjective image quality and visualization of pathologic findings did not differ significantly between the groups. CONCLUSIONS: Carotid CTA using the lowest available voltage (70 kV) is feasible at very-low-dose levels, while overall image quality is comparable with protocols using automated tube voltage selection.
CRIS-Team Scopus Importer:2019-09-03

Carotid CTA: Radiation Exposure and Image Quality with the Use of Attenuation-Based, Automated Kilovolt Selection - Eller, A.; Wüst, Wolfgang; Kramer, Manuel; May, Matthias; Schmid, A.; Uder, Michael; Lell, Michael (American Journal of Neuroradiology, 2014)
CTA is considered the imaging modality of choice in evaluating the supraaortic vessels in many institutions, but radiation exposure remains a matter of concern. The objective of the study was to evaluate a fully automated, attenuation-based kilovolt selection algorithm in carotid CTA in respect to radiation dose and image quality compared with a standard 120-kV protocol.Ninety-eight patients were included: 53 examinations (patient age, 66 ± 12 years) were performed by use of automated adaption of tube potential (80-140 kV) on the basis of the attenuation profile of the scout scan (study group), and 45 examinations (patient age, 67 ± 11 years) were performed by use of a standard 120-kV protocol (control group). CT dose index volume and dose-length product were recorded from the examination protocol. Image quality was assessed by ROI measurements and calculations of SNR and contrast-to-noise ratio. Subjective image quality was evaluated by 2 observers with the use of a 4-point scale (3, excellent; 0, not diagnostic).Subjective image quality was rated as "excellent" or "good" in all examinations (study group, 2.8; control group, 2.8). The algorithm automatically selected 100 kV in 47% and 80 kV in 34%; 120 kV was retained in 19%. An elevation to 140 kV did not occur. Compared with the control group, overall CT dose index volume reduction was 33.7%; overall dose-length product reduction was 31.5%. In the low-kilovolt scans, image noise and mean attenuation of ROIs inside the carotid arteries were significantly higher than in 120-kV scans, resulting in a constant or increased (80-kV group) contrast-to-noise ratio.The attenuation-based, kilovolt selection algorithm enables a dose reduction of >30% in carotid artery CTA while maintaining contrast-to-noise ratio and subjective image quality at adequate levels.
EVALuna2:14326

CD19-targeted CAR T cells in refractory antisynthetase syndrome - Müller, Fabian; Böltz, Sebastian; Knitza, Johannes; Aigner, Michael; Völkl, Simon; Kharboutli, Soraya; Reimann, Hannah; Taubmann, Jule; Kretschmann, Sascha; Rösler, Wolf; Manger, Bernhard; Wacker, Jochen; et al. (Lancet, 2023)
CRIS-Team Scopus Importer:2023-03-24

Central pulse pressure predicts BP reduction after renal denervation in patients with treatment-resistant hypertension - Ott, Christian; Schmid, Axel; Toennes, Stefan W.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (EuroIntervention, 2015)
Enhanced vascular ageing is associated with elevated central pulse pressure (cPP), an independent predictor of cardiovascular (CV) events. Although antihypertensive treatment strategies are effective, high residual CV risk remains indicative of advanced and largely irreversible vascular damage. Renal denervation (RDN) has been shown to reduce blood pressure (BP) to various extents in patients with treatment-resistant hypertension (TRH). We hypothesised that cPP predicts BP reduction after RDN.Sixty-three patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter and were followed for six months. At baseline, cPP was assessed by pulse wave analysis (SphygmoCor(TM)). Patients were stratified according to their median cPP (55 mmHg), and called "low cPP" (below the median) or "high cPP" (above the median). Office BP reduction six months after RDN was greater (-22±19/-13±11 vs. -12±20/-5±13 mmHg, p=0.038/0.014) and 24-hr ambulatory blood pressure (ABP) reduction tended to be greater (-11±13/-8±10 vs. -3±18/-4±10 mmHg, p=0.070/0.112) in patients with low cPP compared to those with high cPP. Only cPP (?=0.687, p=0.001) and baseline systolic BP (?=-0.564, p<0.001) were independent determinants of office systolic BP reduction after RDN.Our data suggest that cPP, indicative of the degree of large arterial stiffening, may be helpful to identify responders to RDN.
EVALuna2:3764

Change in the radio-oncological Treatment Concept for Brain Metastases through a dedicated Radiotherapy Planning MRI - Voigt, R.; Masitho, Siti; Grigo, Johanna; Reissig, L.; Uder, Michael; Semrau, Sabine; Fietkau, Rainer; Bert, Christoph; Putz, Florian (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Changes in T2 Relaxation Time Mapping of Intervertebral Discs Adjacent to Vertebrae after Kyphoplasty Correlate with the Physical Clinical Outcome of Patients - Wegener, Lisa; Werner, Felix; Kleyer, Arnd; Simon, David; Uder, Michael; Janka, Rolf Matthias; Trattnig, Siegfried; Welsch, Goetz H.; Pachowsky, Milena (Diagnostics, 2022)
(1) Background: To assess whether clinical outcomes correlate with tissue changes in the intervertebral discs (IVDs) after kyphoplasty as treatment for vertebral fractures, quantitative MRI was applied. (2) Methods: Quantitative T2 mapping acquired in a 3 T MRI scanner of the thoracolumbar spine was performed in 20 patients two years after kyphoplasty. The IVDs adjacent and nonadjacent to the treated vertebrae were divided into six regions of interest (ROI), which were further categorised into inner (ROI 2–5) and outer (ROI 1 and 6) parts of the IVDs, and the T2 values were analysed. T2 values of adjacent discs were correlated with the items of questionnaires evaluating the clinical outcome (i.e., 36-Item Short Form Survey). (3) Results: Lower T2 values in adjacent IVDs correlated with poorer physical outcome two years after kyphoplasty. The inner part of the IVDs adjacent to treated vertebrae showed statistically significant lower T2 values in segments L2/L3 and L3/L4 compared to nonadjacent ones. Patients with lower T2 values showed more pain and physical limitations in everyday life. (4) Conclusions: Quantitative T2 mapping can detect IVD degeneration in patients after kyphoplasty and correlates with the physical outcome. This technique could help to gain better insights into alterations in tissue composition following kyphoplasty and the consequences for the patients’ quality of life.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Clinical outcome; Intervertebral disc; Kyphoplasty; MRI; T2 mapping

Characterization of the murine orthotopic adamantinomatous craniopharyngioma PDX model by MRI in correlation with histology - Hoelsken, Annett; Schwarz, Marc; Gillmann, Clarissa; Pfister, Christina; Uder, Michael; Dörfler, Arnd; Buchfelder, Michael; Schlaffer, Sven-Martin; Fahlbusch, Rudolf; Buslei, Rolf; Bäuerle, Tobias (PLoS ONE, 2018)
PURPOSE: Adamantinomatous craniopharyngiomas (ACP) as benign sellar brain tumors are challenging to treat. In order to develop robust in vivo drug testing methodology, the murine orthotopic craniopharyngioma model (PDX) was characterized by magnetic resonance imaging (MRI) and histology in xenografts from three patients (ACP1-3). METHODS: In ACP PDX, multiparametric MRI was conducted to assess morphologic characteristics such as contrast-enhancing tumor volume (CETV) as well as functional parameters from dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI) including area-under-the-curve (AUC), peak enhancement (PE), time-to-peak (TTP) and apparent diffusion coefficient (ADC). These MRI parameters evaluated in 27 ACP PDX were correlated to histological features and percentage of vital tumor cell content. RESULTS: Qualitative analysis of MRI and histology from PDX revealed a similar phenotype as seen in patients, although the MRI appearance in mice resulted in a more solid tumor growth than in humans. CETV were significantly higher in ACP2 xenografts relative to ACP1 and ACP3 which correspond to respective average vitality of 41%, <10% and 26% determined histologically. Importantly, CETV prove tumor growth of ACP2 PDX as it significantly increases in longitudinal follow-up of 110 days. Furthermore, xenografts from ACP2 revealed a significantly higher AUC, PE and TTP in comparison to ACP3, and significantly increased ADC relative to ACP1 and ACP3 respectively. Overall, DCE-MRI and DWI can be used to distinguish vital from non-vital grafts, when using a cut off value of 15% for vital tumor cell content. CONCLUSIONS: MRI enables the assessment of craniopharyngioma PDX vitality in vivo as validated histologically.
EVALuna2:34588

Characterizing mammographic images by using generic texture features - Häberle, Lothar; Wagner, Florian; Fasching, Peter; Jud, Sebastian; Heusinger, Katharina; Löhberg, Christian; Hein, Alexander; Bayer, Christian M.; Hack, Carolin; Lux, Michael P.; Binder, Katja; Elter, Matthias; et al. (Breast Cancer Research, 2012)
Introduction: Although mammographic density is an established risk factor for breast cancer, its use is limited in clinical practice because of a lack of automated and standardized measurement methods. The aims of this study were to evaluate a variety of automated texture features in mammograms as risk factors for breast cancer and to compare them with the percentage mammographic density (PMD) by using a case-control study design.Methods: A case-control study including 864 cases and 418 controls was analyzed automatically. Four hundred seventy features were explored as possible risk factors for breast cancer. These included statistical features, moment-based features, spectral-energy features, and form-based features. An elaborate variable selection process using logistic regression analyses was performed to identify those features that were associated with case-control status. In addition, PMD was assessed and included in the regression model.Results: Of the 470 image-analysis features explored, 46 remained in the final logistic regression model. An area under the curve of 0.79, with an odds ratio per standard deviation change of 2.88 (95% CI, 2.28 to 3.65), was obtained with validation data. Adding the PMD did not improve the final model.Conclusions: Using texture features to predict the risk of breast cancer appears feasible. PMD did not show any additional value in this study. With regard to the features assessed, most of the analysis tools appeared to reflect mammographic density, although some features did not correlate with PMD. It remains to be investigated in larger case-control studies whether these features can contribute to increased prediction accuracy. © 2012 Fasching et al.; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-07-19

Chemoprevention of Radiation-Induced DNA Double-Strand Breaks with Antioxidants - Kuefner, Michael Andreas; Brand, Michael; Andreassi, Maria Grazia; Braga, Larissa; Uder, Michael (Current Radiology Reports, 2015)
Double-strand breaks (DSB) are considered to be the most relevant X-ray-induced DNA damages. γ-H2AX immunofluorescence microscopy is a sensitive and reliable method for the quantification of distinct DSB. The detectable amount of these DNA damages correlates well with the dose received. A protective effect of different antioxidants has been postulated. This review explains the principle of the γ-H2AX technique, describes important results concerning DSB in radiologic examinations, and provides an overview on studies evaluating the effect of antioxidants on radiation-induced DNA damages with a special focus on recent studies using the γ-H2AX method.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Antioxidants; Chemoprevention; DNA double-strand breaks; Radiation; γ-H2AX

Cinematic Rendering in Anatomy: A Crossover Study Comparing a Novel 3D Reconstruction Technique to Conventional Computed Tomography - Binder, Johannes; Scholz, Michael; Ellmann, Stephan; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (Anatomical Sciences Education, 2020)
Integration of medical imaging into preclinical anatomy courses is already underway in many medical schools. However, interpretation of two-dimensional grayscale images is difficult and conventional volume rendering techniques provide only images of limited quality. In this regard, a more photorealistic visualization provided by Cinematic Rendering (CR) may be more suitable for anatomical education. A randomized, two-period crossover study was conducted from July to December 2018, at the University Hospital of Erlangen, Germany to compare CR and conventional computed tomography (CT) imaging for speed and comprehension of anatomy. Sixteen students were randomized into two assessment sequences. During each assessment period, participants had to answer 15 anatomy-related questions that were divided into three categories: parenchymal, musculoskeletal, and vascular anatomy. After a washout period of 14 days, assessments were crossed over to the respective second reconstruction technique. The mean interperiod differences for the time to answer differed significantly between the CR-CT sequence (-204.21 +/- 156.0 seconds) and the CT-CR sequence (243.33 +/- 113.83 seconds;P < 0.001). Overall time reduction by CR was 65.56%. Cinematic Rendering visualization of musculoskeletal and vascular anatomy was higher rated compared to CT visualization (P P = 0.003), whereas CT visualization of parenchymal anatomy received a higher scoring than CR visualization (P < 0.001). No carryover effects were observed. A questionnaire revealed that students consider CR to be beneficial for medical education. These results suggest that CR has a potential to enhance knowledge acquisition and transfer from medical imaging data in medical education.
CRIS-Team WoS Importer:2020-07-17

Cinematic Rendering in Mixed-Reality Holograms: A New 3D Preoperative Planning Tool in Pediatric Heart Surgery - Gehrsitz, Pia; Rompel, Oliver; Schoeber, Martin; Cesnjevar, Robert; Purbojo, Ariawan; Uder, Michael; Dittrich, Sven; Alkassar, Muhannad (Frontiers in Cardiovascular Medicine, 2021)
Cinematic rendering (CR) is based on a new algorithm that creates a photo-realistic three-dimensional (3D) picture from cross-sectional images. Previous studies have shown its positive impact on preoperative planning. To date, CR presentation has only been possible on 2D screens which limited natural 3D perception. To depict CR-hearts spatially, we used mixed-reality technology and mapped corresponding hearts as holograms in 3D space. Our aim was to assess the benefits of CR-holograms in the preoperative planning of cardiac surgery. Including 3D prints allowed a direct comparison of two spatially resolved display methods. Twenty-six patients were recruited between February and September 2019. CT or MRI was used to visualize the patient's heart preoperatively. The surgeon was shown the anatomy in cross-sections on a 2D screen, followed by spatial representations as a 3D print and as a high-resolution hologram. The holographic representation was carried out using mixed-reality glasses (HoloLens (R)). To create the 3D prints, corresponding structures were segmented to create STL files which were printed out of resin. In 22 questions, divided in 5 categories (3D-imaging effect, representation of pathology, structure resolution, cost/benefit ratio, influence on surgery), the surgeons compared each spatial representation with the 2D method, using a five-level Likert scale. The surgical preparation time was assessed by comparing retrospectively matched patient pairs, using a paired t-test. CR-holograms surpassed 2D-monitor imaging in all categories. CR-holograms were superior to 3D prints in all categories (mean Likert scale 4.4 +/- 1.0 vs. 3.7 +/- 1.3, P < 0.05). Compared to 3D prints it especially improved the depth perception (4.7 +/- 0.7 vs. 3.7 +/- 1.2) and the representation of the pathology (4.4 +/- 0.9 vs. 3.6 +/- 1.2). 3D imaging reduced the intraoperative preparation time (n = 24, 59 +/- 23 min vs. 73 +/- 43 min, P < 0.05). In conclusion, the combination of an extremely photo-realistic presentation via cinematic rendering and the spatial presentation in 3D space via mixed-reality technology allows a previously unattained level of comprehension of anatomy and pathology in preoperative planning.
CRIS-Team WoS Importer:2021-03-12

Cinematic rendering in rheumatic diseases-Photorealistic depiction of pathologies improves disease understanding for patients - Pachowsky, Milena; Morf, Harriet; Simon, David; Schönau, Verena; Valor-Mendez, Larissa; Knitza, Johannes; Fagni, Filippo; Engel, Klaus; Uder, Michael; Hueber, Axel; Schmidkonz, Christian; Schett, Georg; et al. (Frontiers in Medicine, 2022)
BackgroundPatient education is crucial for successful chronic disease management. Current education material for rheumatic patients however rarely includes images of disease pathologies, limiting patients' disease understanding. Cinematic rendering (CR) is a new tool that allows segmentation of standard medical images (DICOMs) into pictures that illustrate disease pathologies in a photorealistic way. Thus CR has the potential to simplify and improve the explanation of disease pathologies, disease activity and disease consequences and could therefore be a valuable tool to effectively educate and inform patients about their rheumatic and musculoskeletal disease (RMD). ObjectivesTo examine the feasibility of creating photorealistic images using CR from RMD patients depicting typical rheumatic disease pathologies and, in a second step to investigate the patient-perceived educational potential of these photorealistic images in clinical routine. MethodsWe selected conventional, high-resolution (HR) and positron emission tomography (PET) computed tomography (CT) images of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), axial spondyloarthritis (axSpA), and giant cell arteritis (GCA) that showed typical respective disease pathologies. These images were segmented using CR technique. In a prospective study, physicians used CR-enhanced and conventional original images to explain the depicted pathognomonic pathologies to patients with the respective rheumatic disease. Patients were then asked to complete a questionnaire evaluating the perceived usefulness of being presented with CR-enhanced images to better understand their underlying disease. ResultsCR images were successfully generated from above mentioned CT methods. Pathologies such as bone erosions, bony spurs, bone loss, ankylosis, and PET-based inflammation could be visualized in photorealistic detail. A total of 79 patients (61% females) with rheumatic diseases (RA 29%, PsA 29%, axSpA 24%, GCA 18%) were interviewed and answered the quantitative questionnaire. Mean age was 55.4 +/- 12.6 years. Irrespective of disease, all patients agreed or highly agreed that CR-based images help to improve disease understanding, should be shown at disease onset, provide a rationale to regularly take medication and would like to have access to their own CR-enhanced images. ConclusionConventional disease images can successfully be turned into photorealistic disease depictions using CR. Patients perceived CR images as a valuable addition to current patient education, enabling personalized disease education and potentially increased medication adherence.
CRIS-Team WoS Importer:2022-08-26

CLASSIFICATION OF PSORIATIC ARTHRITIS, SERONEGATIVE RHEUMATOID ARTHRITIS, AND SEROPOSITIVE RHEUMATOID ARTHRITIS USING DEEP LEARNING ON MAGNETIC RESONANCE IMAGING - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Supplement 1, 2022)
Background: While MRI evaluation of joints has been primarily used to quantify inflammation at a cross-sectional and longitudinal level, less is known about the potential of MRI in distinguishing different patterns of inflammation in the various forms of arthritis. Objectives: To evaluate (i) whether deep learning using neural networks can be trained to distinguish between seropositive rheumatoid arthritis (RA+), seronegative RA (RA-), and psoriatic arthritis (PsA) based on structural inflammatory patterns on hand magnetic resonance imaging and (ii) to assess if psoriasis patients with subclinical inflammation fit into such patterns. Methods: ResNet 3D [1] neural networks were trained to distinguish (i) RA+ vs. PsA, (ii) RA- vs. PsA and (iii) RA+ vs. RA- with respect to hand MRI data. Diagnosis of patients was determined using the following guidelines: ACR/EULAR 2010 [2] for RA and CASPAR [3] for PsA. Results from T1 coronal, T2 coronal, T1 coronal and axial fat suppressed contrast-enhanced (CE) and T2 fat suppressed axial sequences were used. The performance of such trained networks was analyzed by the area-under-the-receiver-operating-characteristic curve (AUROC) with and without imputation of demographic and clinical parameters ( Figure 1A ). Additionally, the trained networks were applied to psoriasis patients without clinical signs of PsA. Results: MRI scans from 649 patients (135 RA-, 190 RA+, 177 PsA, 147 psoriasis) were included ( Table 1 ). The AUROC for differentiation between disease entities was 75% (SD 3%) for RA+ vs. PsA, 74% (SD 8%) for RA- vs. PsA, and 67% (6%) for RA+ vs. RA-. All MRI sequences were relevant for classification, however, when deleting CE sequences, the loss of performance was only marginal. The addition of patient-specific data to the networks did not provide significant improvements. Increasing amounts of training data demonstrated improved performance of the networks ( Figure 1B ). Psoriasis patients were mostly assigned to PsA by the neural networks, suggesting that PsA-like MRI pattern may be present early in the course of psoriatic disease. Conclusion: Deep learning can be successfully applied to differentiate MRI inflammatory patterns related to RA+, RA-, and PsA. Early changes in psoriasis patients can be recognized by neural networks and are characterized by a pattern that allowed the networks to classify them as PsA. <
Keywords: Rheumatoid arthritis; deep learning; neural networks

Clinical Application of Ultrahigh-Field-Strength Wrist MRI: A Multireader 3-T and 7-T Comparison Study - Heiß, Rafael; Weber, Marc-Andre; Balbach, Eva; Schmitt, Rainer; Rehnitz, Christoph; Laqmani, Azien; Sternberg, Andreas; Ellermann, Jutta J.; Nagel, Armin Michael; Ladd, Mark E.; Englbrecht, Matthias; Arkudas, Andreas; et al. (Radiology, 2023)
Background Ultrahigh-field-strength MRI at 7 T may permit superior visualization of noninflammatory wrist pathologic conditions, particularly due to its high signal-to-noise ratio compared with the clinical standard of 3 T, but direct comparison studies are lacking. Purpose To compare the subjective image quality of 3-T and 7-T ultrahigh-field-strength wrist MRI through semiquantitative scoring of multiple joint tissues in a multireader study. Materials and Methods In this prospective study, healthy controls and participants with chronic wrist pain underwent 3-T and 7-T MRI (coronal T1-weighted turbo spin-echo [TSE], coronal fat-suppressed proton-density [PD]-weighted TSE, transversal T2-weighted TSE) on the same day, from July 2018 to June 2019. Images were scored by seven musculoskeletal radiologists. The overall image quality, presence of artifacts, homogeneity of fat suppression, and visualization of cartilage, the triangular fibrocartilage complex (TFCC), and scapholunate and lunotriquetral ligaments were semiquantitatively assessed. Pairwise differences between 3 T and 7 T were assessed using the Wilcoxon signed-rank test. Interreader reliability was determined using the Fleiss kappa. Results In total, 25 healthy controls (mean age, 25 years ± 4 [SD]; 13 women) and 25 participants with chronic wrist pain (mean age, 39 years ± 16; 14 men) were included. Overall image quality (P = .002) and less presence of artifacts at PD-weighted fat-suppressed MRI were superior at 7 T. T1- and T2-weighted MRI were superior at 3 T (both P < .001), as was fat suppression (P < .001). Visualization of cartilage was superior at 7 T (P < .001), while visualization of the TFCC (P < .001) and scapholunate (P = .048) and lunotriquetral (P = .04) ligaments was superior at 3 T. Interreader reliability showed slight to substantial agreement for the detected pathologic conditions (κ = 0.20-0.64). Conclusion A 7-T MRI of the wrist had potential advantages over 3-T MRI, particularly in cartilage assessment. However, superiority was not shown for all parameters; for example, visualization of the triangular fibrocartilage complex and wrist ligaments was superior at 3 T. © RSNA, 2023 Supplemental material is available for this article.
CRIS-Team Scopus Importer:2023-04-21

Clinical evaluation of semi-automatic landmark-based lesion tracking software for CT-scans - Dankerl, Peter; Dietzel, Matthias; Tsymbal, Alexey; Kramer, Martin; Seifert, Sascha; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Cancer Imaging, 2014)
To evaluate a semi-automatic landmark-based lesion tracking software enabling navigation between RECIST lesions in baseline and follow-up CT-scans.The software automatically detects 44 stable anatomical landmarks in each thoraco/abdominal/pelvic CT-scan, sets up a patient specific coordinate-system and cross-links the coordinate-systems of consecutive CT-scans. Accuracy of the software was evaluated on 96 RECIST lesions (target- and non-target lesions) in baseline and follow-up CT-scans of 32 oncologic patients (64 CT-scans). Patients had to present at least one thoracic, one abdominal and one pelvic RECIST lesion. Three radiologists determined the deviation between lesions' centre and the software's navigation result in consensus.The initial mean runtime of the system to synchronize baseline and follow-up examinations was 19.4 ± 1.2 seconds, with subsequent navigation to corresponding RECIST lesions facilitating in real-time. Mean vector length of the deviations between lesions' centre and the semi-automatic navigation result was 10.2 ± 5.1 mm without a substantial systematic error in any direction. Mean deviation in the cranio-caudal dimension was 5.4 ± 4.0 mm, in the lateral dimension 5.2 ± 3.9 mm and in the ventro-dorsal dimension 5.3 ± 4.0 mm.The investigated software accurately and reliably navigates between lesions in consecutive CT-scans in real-time, potentially accelerating and facilitating cancer staging.
EVALuna2:14438

Clinically compatible subject-specific dynamic parallel transmit pulse design for homogeneous fat saturation and water-excitation at 141657T: Proof-of-concept for 14165CEST MRI of the brain - Levy, Simon; Herrler, Jürgen; Liebert, Andrzej; Tkotz, Katharina; Fabian, Moritz; Eisen, Christian; Grodzki, David; Uder, Michael; Dörfler, Arnd; Zaiß, Moritz; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose To evaluate the benefits and challenges of dynamic parallel transmit (pTx) pulses for fat saturation (FS) and water-excitation (WE), in the context of CEST MRI. Methods "Universal" k(T)-points (for FS) and spiral non-selective (for WE) trajectories were optimized offline for flip angle (FA) homogeneity. Routines to optimize the pulse shape online, based on the subject's fields maps, were implemented (target FA of 110 degrees/0 degrees for FS, 0 degrees/5 degrees for WE at fat/water frequencies). The pulses were inserted in a CEST sequence with a pTx readout. The different fat suppression schemes and their effects on CEST contrasts were compared in 12 volunteers at 7T. Results With a 25%-shorter pulse duration, pTx FS largely improved the FA homogeneity (root-mean-square-error (RMSE) = 12.3 degrees vs. 53.4 degrees with circularly-polarized mode, at the fat frequency). However, the spectral selectivity was degraded mainly in the cerebellum and close to the sinuses (RMSE = 5.8 degrees vs. 0.2 degrees at the water frequency). Similarly, pTx WE showed a trade-off between FA homogeneity and spectral selectivity compared to pTx non-selective pulses (RMSE = 0.9 degrees and 1.1 degrees at the fat and water frequencies, vs. 4.6 degrees and 0.5 degrees). In the brain, CEST metrics were reduced by up to 31.9% at -3.3 ppm with pTx FS, suggesting a mitigated lipid-induced bias. Conclusion This clinically compatible implementation of dynamic pTx pulses improved the fat suppression homogeneity at 7T taking into account the subject-specific B-0 heterogeneities online. This study highlights the lipid-induced biases on the CEST z-spectrum. The results are promising for body applications where B-0 heterogeneities and fat are more substantial.
CRIS-Team WoS Importer:2022-09-30

Combination of an ultrafast TWIST-VIBE Dixon sequence protocol and diffusion-weighted imaging into an accurate easily applicable classification tool for masses in breast MRI - Peter, Sandra C.; Wenkel, Evelyn; Weiland, Elisabeth; Dietzel, Matthias; Janka, Rolf Matthias; Hartmann, Arndt; Emons, Julius; Uder, Michael; Ellmann, Stephan (European Radiology, 2020)
Objectives: This study aimed to develop a tool for the classification of masses in breast MRI, based on ultrafast TWIST-VIBE Dixon (TVD) dynamic sequences combined with DWI. TVD sequences allow to abbreviate breast MRI protocols, but provide kinetic information only on the contrast wash-in, and because of the lack of the wash-out kinetics, their diagnostic value might be hampered. A special focus of this study was thus to maintain high diagnostic accuracy in lesion classification. Materials and methods: Sixty-one patients who received breast MRI between 02/2014 and 04/2015 were included, with 83 reported lesions (60 malignant). Our institute’s standard breast MRI protocol was complemented by an ultrafast TVD sequence. ADC and peak enhancement of the TVD sequences were integrated into a generalised linear model (GLM) for malignancy prediction. For comparison, a second GLM was calculated using ADC and conventional DCE curve type. The resulting GLMs were evaluated for standard diagnostic parameters. For easy application of the GLMs, nomograms were created. Results: The GLM based on peak enhancement of the TVD and ADC was as equally accurate as the GLM based on conventional DCE and ADC, with no significant differences (sensitivity, 93.3%/93.3%; specificity, 91.3%/87.0%; PPV, 96.6%/94.9%; NPV, 84.0%/83.3%; all, p ≥ 0.315). Conclusions: This study presents a method to integrate ultrafast TVD sequences into a breast MRI protocol, allowing a reduction of the examination time while maintaining diagnostic accuracy. A GLM based on the combination of TVD-derived peak enhancement and ADC provides high diagnostic accuracy, and can be easily applied using a nomogram. Key Points: • Ultrafast TWIST-VIBE Dixon sequence protocols in combination with diffusion-weighted imaging allow to shorten breast MRI examinations, while diagnostic accuracy is maintained. • Integrating peak enhancement from the TWIST-VIBE Dixon sequence and the apparent diffusion coefficient into a generalised linear model provides a comprehensible image evaluation approach. • This approach is further facilitated by nomograms.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Breast cancer; Diagnostic imaging; Diffusion magnetic resonance imaging; Magnetic resonance imaging; Statistical model

Combined imaging of potassium and sodium in human skeletal muscle tissue at 7 T - Gast, Lena; Volker, Stefanie; Utzschneider, Matthias; Linz, Peter; Wilferth, Tobias; Müller, Max; Kopp, Christoph; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2020)
Purpose: To validate the feasibility of quantitative combined potassium (39K) and sodium (23Na) MRI in human calf muscle tissue, as well as to evaluate the reproducibility of the apparent tissue potassium concentration (aTPC) and apparent tissue sodium concentration (aTSC) determination in healthy muscle tissue. Methods: Quantitative 23Na and 39K MRI acquisition protocols were implemented on a 7 T MR system. A double-resonant 23Na/39K birdcage RF coil was used. Measurements of human lower leg were performed in a total acquisition time of TANa = 10:54 min/TAK = 8:06 min and using a nominal spatial resolution of 2.5 × 2.5 × 15 mm3/7.5 × 7.5 × 30 mm3 for 23Na/39K MRI. Two aTSC and aTPC examinations in muscle tissue were performed during the same day on 10 healthy subjects. Results: The proposed acquisition and postprocessing workflow for 23Na and 39K MRI data sets provided reproducible aTSC and aTPC measurements. In human calf muscle tissue, the coefficient of variation between scan and re-scan was 5.7% for both aTSC and aTPC determination. Overall, mean values of aTSC = (17 ± 1) mM and aTPC = (85 ± 5) mM were measured. Moreover, for 39K in calf muscle tissue, (Formula presented.) components of (Formula presented.) = (1.2 ± 0.2) ms and (Formula presented.) = (7.9 ± 0.9) ms, as well as a residual quadrupolar interaction of (Formula presented.) = (143 ± 17) Hz, were determined. The fraction of the fast component was f = (58 ± 4)%. Conclusion: Using the presented measurement and postprocessing approach, a reproducible aTSC and aTPC determination using 23Na and 39K MRI at 7 T in human skeletal muscle tissue is feasible in clinically acceptable acquisition durations.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 7 T; potassium MRI; sodium MRI; tissue potassium concentration; tissue sodium concentration; ultrahigh field strengths

Comparison between open and pharmacomechanical repair of acutely thrombosed arteriovenous hemodialysis fistulae within a decade - Regus, Susanne; Almási-Sperling, Veronika; Rother, Ulrich; Meyer, Alexander; Schmid, Axel; Uder, Michael; Lang, Werner (Hemodialysis International, 2018)
INTRODUCTION: Different declotting techniques are available for acutely thrombosed arteriovenous hemodialysis fistulae (AVF). The aim of this single-center study was to compare immediate and follow-up results between surgical repair and a modified interventional lyse-and-wait technique characterized by prolonged local reaction times of recombinant tissue-plasminogen activator (rtPA). MATERIALS AND METHODS: We retrospectively analyzed medical records of 110 consecutively treated patients between the years 2003 and 2013. All patients were on hemodialysis (HD) and suffered from an acutely thrombosed AVF. The treatment standards changed in the course of time, wherefore we compared 2 groups: the open repair (OR) (N = 50) and the endovascular repair (ER) group (N = 60). FINDINGS: We found no significant differences in success rates (OR 92%/ER 96.7%; P = 0.28), immediate failures (IFs) (OR 8%/ER 10%; P = 0.71), and temporary catheter placements (TCPs) (OR 10%/ER 6.7%; P = 0.52). Furthermore, there were no differences in cumulative primary patency rates (P = 0.42) and secondary patency rates (P = 0.97).The infection rate was significantly increased after OR (8%) compared to ER (0%); P = 0.026. The hospital stay in days was shorter after ER (5.2 ±2.8) vs. OR (9.0 ± 3.5); P < 0.001. CONCLUSION: The modified lyse-and-wait technique with prolonged local reaction times is a successful alternative to surgical repair for acutely thrombosed AVF. Clear benefits are less infections and significant shorter hospital stays after ER. However, OR remains the preferred treatment for aneurysms and anastomotic stenoses.
EVALuna2:36234

Comparison of Cinematic Rendering and Computed Tomography for Speed and Comprehension of Surgical Anatomy - Elshafei, Moustafa; Binder, Johannes; Baecker, Justus; Brunner, Maximilian; Uder, Michael; Grützmann, Robert; Krautz, Christian; Weber, Georg (JAMA Surgery, 2019)
Importance: Three-dimensional (3-D) volume rendering has been shown to improve visualization in general surgery. Cinematic rendering (CR), a novel 3-D visualization technology for postprocessing of computed tomographaphy (CT) images, provides photorealistic images with the potential to improve visualization of anatomic details. Objective: To determine the value of CR for the comprehension of the surgical anatomy. Design, Setting, and Participants: This preclinical, randomized, 2-sequence crossover study was conducted from February to November 1, 2018, at University Hospital of Erlangen, Germany. The 40 patient cases were evaluated by 18 resident and attending surgeons using a prepared set of CT and CR images. The patient cases were randomized to 2 assessment sequences (CR-CT and CT-CR). During each assessment period, participants answered 1 question per case that addressed crucial issues of anatomic understanding, preoperative planning, and intraoperative strategies. After a washout period of 2 weeks, case evaluations were crossed over to the respective second image modality. Main Outcomes and Measures: The primary outcome measure was the correctness of answers. Secondary outcome was the time needed to answer. Results: The mean (SD) interperiod differences for the percentage of correct answers in the CR-CT sequence (8.5% [7.0%]) differed significantly from those in the CT-CR sequence (-13.1% [6.3%]) (P <.001). The mean (SD) interperiod differences for the time spent to answer the questions in the CR-CT sequence (-18.3 [76.9] seconds) also differed significantly from those in the CT-CR sequence (52.4 [88.5] seconds) (P <.001). Subgroup analysis revealed that residents as well as attending physicians benefitted from CR visualization. Analysis of the case assessment questionnaire showed that CR added significant value to the comprehension of the surgical anatomy (overall mean [SD] score, 4.53 [0.75]). No carryover or period effects were observed. Conclusions and Relevance: The visualization with CR allowed a more correct and faster comprehension of the surgical anatomy compared with conventional CT imaging, independent of level of surgeon experience. Therefore, CR may assist general surgeons with preoperative preparation and intraoperative guidance..
CRIS-Team Scopus Importer:2019-06-18

Comparison of Diagnostic Performance and Image Quality between Topup-Corrected and Standard Readout-Segmented Echo-Planar Diffusion-Weighted Imaging for Cholesteatoma Diagnostics - Wiesmüller, Marco; Wüst, Wolfgang; Mennecke, Angelika; May, Matthias; Heiß, Rafael; Führes, Tobit; Janka, Rolf Matthias; Uder, Michael; Dörfler, Arnd; Laun, Frederik Bernd (Diagnostics, 2023)
This study compares the diagnostic performance and image quality of single-shot turbo spin-echo DWI (tseDWI), standard readout-segmented DWI (rsDWI), and a modified rsDWI version (topupDWI) for cholesteatoma diagnostics. Thirty-four patients with newly suspected unilateral cholesteatoma were examined on a 1.5 Tesla MRI scanner. Diagnostic performance was evaluated by calculating and comparing the sensitivity and specificity using histopathological results as the standard of reference. Image quality was independently reviewed by two readers using a 5-point Likert scale evaluating image distortions, susceptibility artifacts, image resolution, lesion conspicuity, and diagnostic confidence. Twenty-five cholesteatomas were histologically confirmed after surgery and originated in the study group. TseDWI showed the highest sensitivity with 96% (95% confidence interval (CI): 88–100%), followed by topupDWI with 92% (95% CI: 81–100%) for both readers. The sensitivity for rsDWI was 76% (95% CI: 59–93%) for reader 1 and 84% (95% CI: 70–98%) for reader 2, respectively. Both tseDWI and topupDWI revealed a specificity of 100% (95% CI: 66–100%) and rsDWI of 89% (95% CI: 52–100%). Both tseDWI and topupDWI showed fewer image distortions and susceptibility artifacts compared to rsDWI. Image resolution was consistently rated best for topupDWI, followed by rsDWI, which both outperformed tseDWI. TopupDWI and tseDWI showed comparable results for lesions’ conspicuity and diagnostic confidence, both outperforming rsDWI. Modified readout-segmented DWI using the topup-correction method is preferable to standard rsDWI and may be regarded as an accurate alternative to single-shot turbo spin-echo DWI in cholesteatoma diagnostics.
CRIS-Team Scopus Importer:2023-04-28
Keywords: cholesteatoma; diffusion-weighted imaging; DWI; echo-planar imaging; EPI; readout-segmented; reduced susceptibility-induced distortions; topup correction; TSE; turbo spin-echo

Comparison of dual- and single-source dual-energy CT in head and neck imaging - May, Matthias; Wiesmüller, Marco; Heiß, Rafael; Brand, Michael; Brügel, Joscha; Uder, Michael; Wüst, Wolfgang (European Radiology, 2019)
Objectives: The aim of this study was to compare image quality of single-source dual-energy CT (SS-DECT) with third-generation dual-source dual-energy CT (DS-DECT) in head and neck cancer. Materials and methods: One hundred two patients with histologically proven head and neck cancer were prospectively randomized to undergo radiation dose-matched SS-DECT (n = 51, 120 kV, split-filter technique, 384 ref. mAs) or DS-DECT (n = 51, 80/Sn150 kV, tube A 100/tube B 67 ref. mAs). Inline default images (DI) and virtual monoenergetic images (VMI) for two different low energies (40 and 60 keV) were reconstructed. Objective image quality was evaluated as dose-normalized contrast to noise ratio (CNRD), and subjective image quality was rated on a 5-point Likert scale. Results: In both groups, highest CNRD values for vessel and tumor attenuation were obtained at 40 keV. DS-DECT was significantly better than SS-DECT regarding vessel and tumor attenuation. Overall subjective image quality in the SS-DECT group was highest on the DI followed by 40 keV and 60 keV. In the DS-DECT group, subjective image quality was highest at 40 keV followed by 60 keV and the DI. Forty kiloelectron volts and 60 keV were significantly better in the DS-DECT compared to the SS-DECT group (both p < 0.01). Conclusions: In split-filter SS-DECT as well as in DS-DECT, highest overall image quality in head and neck imaging can be obtained with a combination of DI and low keV reconstructions. DS-DECT is superior to split-filter SS-DECT in terms of subjective image quality and vessel and tumor attenuation. Key Points: • Image quality was diagnostic with both dual-energy techniques; however, the dual-source technique delivered significantly better results. • Highest overall image quality in head and neck imaging can be obtained with a combination of default images and low keV reconstructions with both dual-energy techniques. • The results of this study may have relevance for the decision-making process regarding replacement of CT scanners and focused patient examination considering image quality and subsequent therapeutic decision-making.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Diagnostic imaging; Head and neck neoplasms; Image enhancement

Comparison of optimized intensity correction methods for 23Na MRI of the human brain using a 32-channel phased array coil at 7 Tesla - Lachner, Sebastian; Ruck, Laurent; Niesporek, Sebastian C.; Utzschneider, Matthias; Lott, Johanna; Hensel, Bernhard; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Zeitschrift für Medizinische Physik, 2019)
Purpose: To correct for the non-homogeneous receive profile of a phased array head coil in sodium magnetic resonance imaging (23Na MRI). Methods: 23Na MRI of the human brain (n = 8) was conducted on a 7T MR system using a dual-tuned quadrature 1H/23Na transmit/receive birdcage coil, equipped with a 32-channel receive-only array. To correct the inhomogeneous receive profile four different methods were applied: (1) the uncorrected phased array image and an additionally acquired birdcage image as reference image were low-pass filtered and divided by each other. (2) The second method substituted the reference image by a support region. (3) By averaging the individually calculated receive profiles, a universal sensitivity map was obtained and applied. (4) The receive profile was determined by a pre-scanned large uniform phantom. The calculation of the sensitivity maps was optimized in a simulation study using the normalized root-mean-square error (NRMSE). All methods were evaluated in phantom measurements and finally applied to in vivo 23Na MRI data sets. The in vivo measurements were partial volume corrected and for further evaluation the signal ratio between the outer and inner cerebrospinal fluid compartments (CSFout:CSFin) was calculated. Results: Phantom measurements show the correction of the intensity profile applying the given methods. Compared to the uncorrected phased array image (NRMSE = 0.46, CSFout:CSFin = 1.71), the quantitative evaluation of simulated and measured intensity corrected human brain data sets indicates the best performance utilizing the birdcage image (NRMSE = 0.39, CSFout:CSFin = 1.00). However, employing a support region (NRMSE = 0.40, CSFout:CSFin = 1.17), a universal sensitivity map (NRMSE = 0.41, CSFout:CSFin = 1.05) or a pre-scanned sensitivity map (NRMSE = 0.42, CSFout:CSFin = 1.07) shows only slightly worse results. Conclusion: Acquiring a birdcage image as reference image to correct for the receive profile demonstrates the best performance. However, when aiming to reduce acquisition time or for measurements without existing birdcage coil, methods that use a support region as reference image, a universal or a pre-scanned sensitivity map provide good alternatives for correction of the receive profile.
CRIS-Team Scopus Importer:2019-12-31
Keywords: 7 Tesla; Intensity correction; Multi-channel array coil; Phased array coil; Receive profile; Sodium MRI

COMPARISON OF RADIOGRAPHY, 3T AND 7T MAGNETIC RESONANCE IMAGING FOR ANALYSIS OF DISTAL RADIUS TRABECULAR BONE IN PATIENTS WITH ESTABLISHED OR SUSPECTED WRIST OSTEOARTHRITIS USING FRACTAL SIGNATURE ANALYSIS - Jarraya, M.; Heiß, Rafael; Duryea, J.; Lynch, J.; Weber, M. -A.; Guermazi, A.; Uder, Michael; Roemer, Frank (OSTEOARTHRITIS AND CARTILAGE, 2020)
CRIS-Team WoS Importer:2020-06-02

Comparison of Readout-Segmented Echo-Planar Imaging and Single-Shot TSE DWI for Cholesteatoma Diagnostics - Wiesmüller, Marco; Wüst, Wolfgang; May, Matthias; Ellmann, Stephan; Heiß, Rafael; Saake, Marc; Janka, Rolf Matthias; Uder, Michael; Laun, Frederik Bernd (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The high diagnostic value of DWI for cholesteatoma diagnostics is undisputed. This study compares the diagnostic value of readout-segmented echo-planar DWI and single-shot TSE DWI for cholesteatoma diagnostics.
CRIS-Team WoS Importer:2021-06-04

Comparison of Sonography versus Digital Breast Tomosynthesis to Locate Intramammary Marker Clips - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, C.; Bayer, C. M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: This study aimed to compare the accuracy of sonography versus digital breast tomosynthesis to locate intramammary marker clips placed under ultrasound guidance. Patients and Methods: Fifty patients with suspicion of breast cancer (lesion diameter less than 2 cm [cT1]) had ultrasound-guided core needle biopsy with placement of a marker clip in the center of the tumor. Intramammary marker clips were subsequently located with both sonography and digital breast tomosynthesis. Results: Sonography detected no dislocation of intrammammary marker clips in 42 of 50 patients (84 %); dislocation was reported in 8 patients (16 %) with a maximum dislocation of 7 mm along the x-, y- or z-axis. Digital breast tomosynthesis showed accurate placement without dislocation of the intramammary marker clip in 48 patients (96 %); 2 patients (4 %) had a maximum clip dislocation of 3 mm along the x-, y- or z-axis (p < 0.05). Conclusion: The use of digital breast tomosynthesis could improve the accuracy when locating intramammary marker clips compared to sonography and could, in future, be used to complement or even completely replace sonography.
EVALuna2:6724

Comparison of vestibular schwannoma visualization between 0.55 T and 1.5 T MRI - Wiesmüller, Marco; Kopp, Markus; Sievert, Matti; May, Matthias; Nagel, Armin Michael; Iro, Heinrich; Uder, Michael; Heiß, Rafael (European Journal of Radiology, 2023)
Objectives: Vestibular schwannoma (VS) is the most common mass of the internal auditory canal (IAC) and is responsible for unilateral sensorineural hearing loss. Magnetic resonance imaging (MRI) at 1.5 T and 3 T is the standard of care for the evaluation of VS, and the feasibility of using modern low-field MRI for imaging of the IAC has not yet been elucidated. Hence, the purpose of this prospective study was to assess image quality and diagnostic performance of a modern 0.55 T MRI. Materials and Methods: Fifty-six patients with known unilateral VS underwent routine MRI of the IAC at 1.5 T, followed immediately by 0.55 T MRI. Two radiologists independently evaluated the image quality, conspicuity of VS, diagnostic confidence, and image artifacts separately for isotropic T2-weighted SPACE images and for transversal and coronal T1-weighted fat-saturated contrast-enhanced images at 1.5 T and 0.55 T using 5-point Likert scales. In a second independent reading, both readers assessed lesion conspicuity and subjective diagnostic confidence in a direct comparison of 1.5 T and 0.55 T images. Results: Image quality of transversal T1-weighted images (p = 0.13 and p = 0.16 for Reader 1 and Reader 2, respectively) and T2-weighted SPACE images (p = 0.39 and p = 0.58) were rated equally at 1.5 T and 0.55 T by both readers, whereas image quality of coronal T1-weighted images was superior at 1.5 T (p = 0.009 and p = 0.001). Analysis of the conspicuity of VS, diagnostic confidence, and image artifacts of all sequences revealed no significant differences between 1.5 T and 0.55 T. In the direct comparison of 1.5 T with 0.55 T images, there were no significant differences in lesion conspicuity or diagnostic confidence for any sequence (p = 0.60–0.73). Conclusions: Modern low-field MRI at 0.55 T provided a sufficient diagnostic image quality and seems feasible for the evaluation of VS of the IAC.
CRIS-Team Scopus Importer:2023-07-28
Keywords: 0.55T MRI; Acoustic neuroma; Image quality; Inner auditory canal; low-field MRI; Vestibular schwannoma

Complete Free-breathing Adenosine Stress Cardiac MRI Using Compressed Sensing and Motion Correction: Comparison of Functional Parameters, Perfusion, and Late Enhancement with the Standard Breath-holding Examination. - Treutlein, Christoph; Wiesmüller, Marco; May, Matthias; Heiß, Rafael; Hepp, Tobias; Uder, Michael; Wüst, Wolfgang (Radiology: Cardiothoracic Imaging, 2019)
Purpose: To compare free-breathing (FB) stress cardiac MRI examinations with the reference standard breath-holding (BH) examination. Materials and Methods: A total of 40 consecutive patients were enrolled prospectively and were examined with 3-T MRI. Functional imaging, perfusion, and late gadolinium enhancement (LGE) sequences were performed in BH and FB by using compressed sensing and in-line motion correction. Left ventricle (LV) and right ventricle (RV) functional parameters in BH and FB examinations were compared by using Bland-Altman plots and linear mixed models. Subjective image quality was assessed with a five-point scale (1 = nondiagnostic, 5 = very good). For perfusion and LGE imaging, diagnostic confidence was rated with a three-point scale (1 = low, 3 = high), and image quality was rated with a five-point scale (1 = nondiagnostic, 5 = very good). The Wilcoxon test was used to compare image quality and diagnostic confidence. Results: Bland-Altman plots showed good agreement for LV and RV functional parameters in BH and FB sequences. Subjective image quality was significantly better with the BH sequences in the LV (P < .01) but was comparable in the RV (P > .99). Scanning time was 218 seconds (range, 130-385 seconds) for cine BH and 16 seconds (range, 11-27 seconds) for cine FB. Extent of perfusion defects, LGE, and diagnostic confidence was comparable between groups. Scanning time was 371 seconds (range, 239-502 seconds) for the LGE BH sequence and 189 seconds (range, 122-286 seconds) for the LGE FB sequence. Conclusion: FB adenosine stress cardiac MRI delivers diagnostic image quality and could represent an alternative for use in patients who are unable to meet the demands of multiple BHs and long examination times.© RSNA, 2019.
EVALuna2:469014

Comprehensive assessment of knee joint synovitis at 7 T MRI using contrast-enhanced and non-enhanced sequences - Treutlein, Christoph; Bäuerle, Tobias; Nagel, Armin Michael; Guermazi, Ali; Kleyer, Arnd; Simon, David; Schett, Georg; Hepp, Tobias; Uder, Michael; Roemer, Frank (BMC Musculoskeletal Disorders, 2020)
BACKGROUND: Seven T ultra-high field MRI systems have recently been approved for clinical use by the U.S. and European regulatory agencies. These systems are now being used clinically and will likely be more widely available in the near future. One of the applications of 7 T systems is musculoskeletal disease and particularly peripheral arthritis imaging. Since the introduction of potent anti-rheumatic therapies over the last two decades MRI has gained increasing importance particularly for assessment of disease activity in early stages of several rheumatic disorders. Commonly gadolinium-based contrast agents are used for assessment of synovitis. Due to potential side-effects of gadolinium non-enhanced techniques are desirable that enable visualization of inflammatory disease manifestations. The feasibility of 7 T MRI for evaluation of peripheral arthritis has not been shown up to now. Aim of our study was to evaluate the feasibility of contrast-enhanced (CE) and non-enhanced MRI at 7 T for the assessment of knee joint synovitis. METHOD: Seven T MRI was acquired for 10 patients with an established diagnosis of psoriatic or rheumatoid arthritis. The study pulse sequence protocol was comprised of a sagittal intermediate-weighted fat-suppressed (FS), axial fluid-attenuated inversion recovery (FLAIR) FS, sagittal 3D T1-weighted dynamic contrast enhanced (DCE) and an axial static 2D T1-weighted FS contrast-enhanced sequence (T1-FS CE). Ordinal scoring on non-enhanced (Hoffa- and effusion-synovitis) and enhanced MRI (11-point synovitis score), and comparison of FLAIR-FS with static T1-FS CE MRI using semiquantitative (SQ) grading and volume assessment was performed. For inter- and intra-reader reliability assessment weighted kappa statistics for ordinal scores and intraclass correlation coefficients (ICC) for continuous variables were used. RESULTS: The total length of study protocol was 15 min 38 s. Different amounts of synovitis were observed in all patients (mild: n = 3; moderate: n = 5; severe: n = 2). Consistently, SQ assessment yielded significantly lower peripatellar summed synovitis scores for the FLAIR-FS sequence compared to the CE T1-FS sequence (p < 0.01). FLAIR-FS showed significantly lower peripatellar synovial volumes (p < 0.01) compared to CE T1-FS imaging with an average percentage difference of 18.6 ± 9.5%. Inter- and intra-reader reliability for ordinal SQ scoring ranged from 0.21 (inter-reader Hoffa-synovitis) to 1.00 (inter-reader effusion-synovitis). Inter- and intra-observer reliability of SQ 3D-DCE parameters ranged from 0.86 to 0.99. CONCLUSIONS: Seven T FLAIR-FS ultra-high field MRI is a potential non-enhanced imaging method able to visualize synovial inflammation with high conspicuity and holds promise for further application in research endeavors and clinical routine by trained readers.
EVALuna2:212706

Compressed sensing and the use of phased array coils in 23Na MRI: a comparison of a SENSE-based and an individually combined multi-channel reconstruction - Lachner, Sebastian; Utzschneider, Matthias; Zaric, Olgica; Minarikova, Lenka; Ruck, Laurent; Zbýň, Štefan; Hensel, Bernhard; Trattnig, Siegfried; Uder, Michael; Nagel, Armin Michael (Zeitschrift für Medizinische Physik, 2020)
Purpose: To implement and to evaluate a compressed sensing (CS) reconstruction algorithm based on the sensitivity encoding (SENSE) combination scheme (CS-SENSE), used to reconstruct sodium magnetic resonance imaging (23Na MRI) multi-channel breast data sets. Methods: In a simulation study, the CS-SENSE algorithm was tested and optimized by evaluating the structural similarity (SSIM) and the normalized root-mean-square error (NRMSE) for different regularizations and different undersampling factors (USF = 1.8/3.6/7.2/14.4). Subsequently, the algorithm was applied to data from in vivo measurements of the healthy female breast (n = 3) acquired at 7 T. Moreover, the proposed CS-SENSE algorithm was compared to a previously published CS algorithm (CS-IND). Results: The CS-SENSE reconstruction leads to an increased image quality for all undersampling factors and employed regularizations. Especially if a simple 2nd order total variation is chosen as sparsity transformation, the CS-SENSE reconstruction increases the image quality of highly undersampled data sets (CS-SENSE: SSIMUSF=7.2 = 0.234, NRMSEUSF=7.2 = 0.491 vs. CS-IND: SSIMUSF=7.2 = 0.201, NRMSEUSF=7.2 = 0.506). Conclusion: The CS-SENSE reconstruction supersedes the need of CS weighting factors for each channel as well as a method to combine single channel data. The CS-SENSE algorithm can be used to reconstruct undersampled data sets with increased image quality. This can be exploited to reduce total acquisition times in 23Na MRI.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Compressed sensing; Iterative reconstruction; Multi-channel; Prior knowledge; Sensitivity encoding; Sodium MRI

Compressed sensing reconstruction of 7 Tesla23Na multi-channel breast data using 1H MRI constraint - Lachner, Sebastian; Zaric, Olgica; Utzschneider, Matthias; Minarikova, Lenka; Zbýň, Štefan; Hensel, Bernhard; Trattnig, Siegfried; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Imaging, 2019)
Purpose: To reduce acquisition time and to improve image quality in sodium magnetic resonance imaging ( 23 Na MRI)using an iterative reconstruction algorithm for multi-channel data sets based on compressed sensing (CS)with anatomical 1 H prior knowledge. Methods: An iterative reconstruction for 23 Na MRI with multi-channel receiver coils is presented. Based on CS it utilizes a second order total variation (TV (2) ), adopted by anatomical weighting factors (AnaWeTV (2) )obtained from a high-resolution 1 H image. A support region is included as additional regularization. Simulated and measured 23 Na multi-channel data sets (n = 3)of the female breast acquired at 7 T with different undersampling factors (USF = 1.8/3.6/7.2/14.4)were reconstructed and compared to a conventional gridding reconstruction. The structural similarity was used to assess image quality of the reconstructed simulated data sets and to optimize the weighting factors for the CS reconstruction. Results: Compared with a conventional TV (2) , the AnaWeTV (2) reconstruction leads to an improved image quality due to preserving of known structure and reduced partial volume effects. An additional incorporated support region shows further improvements for high USFs. Since the decrease in image quality with higher USFs is less pronounced compared to a conventional gridding reconstruction, proposed algorithm is beneficial especially for higher USFs. Acquisition time can be reduced by a factor of 4 (USF = 7.2), while image quality is still similar to a nearly fully sampled (USF = 1.8)gridding reconstructed data set. Conclusion: Especially for high USFs, the proposed algorithm allows improved image quality for multi-channel 23 Na MRI data sets.
CRIS-Team Scopus Importer:2019-05-14
Keywords: 7 Tesla; Compressed sensing (CS); Iterative reconstruction; Multi-channel; Prior knowledge; Sodium (

Computed Tomography Angiography of Carotid Arteries and Vertebrobasilar System: A Simulation Study for Radiation Dose Reduction - Kramer, Manuel; Ellmann, Stephan; Allmendinger, Thomas; Eller, Achim; Kammerer, Ferdinand; May, Matthias; Baigger, Joao F.; Uder, Michael; Lell, Michael (Medicine, 2015)
Computed tomography angiography (CTA) of carotid arteries and vertebrobasilar system is a standardized procedure with excellent image quality, but radiation exposure remains a matter of concern. The aim of this study is to examine to what extent radiation dose can be lowered in relation to a standard protocol by simulating examinations with lower tube currents applying a dedicated software.Lower tube current was simulated by a dedicated noise insertion and reconstruction software (ReconCT). In a phantom study, true scans were performed with different dose protocols and compared to the results of simulated dose reductions of the same degree, respectively. In a patient study, 30 CTAs of supra-aortic vessels were reconstructed at a level of 100%, 75%, 50%, and 25% of the initial dose. Objective and subjective image analyses were performed.No significant noise differences between true scans and simulated scans of mimicked contrasted vessels were found. In the patient study, the quality scores of the 4 dose groups differed statistically significant; this difference vanished for the comparison of the 100% and 75% datasets after dichotomization into the categories of diagnostic and nondiagnostic image quality (P = .50).This study suggests an easy-to-implement method of simulating CTAs of carotid arteries and vertebrobasilar system with lower tube current for dose reduction by artificially adding noise to the original raw data. Lowering the radiation dose in a moderate extent to 75% of the original dose levels does not significantly alter the diagnostic image quality.
EVALuna2:14495

Computed Tomography of the Head and Neck Region for Tumor Staging-Comparison of Dual-Source, Dual-Energy and Low-Kilovolt, Single-Energy Acquisitions - May, Matthias; Brügel, Joscha; Brand, Michael; Wiesmüller, Marco; Krauss, Bernhard; Allmendinger, Thomas; Uder, Michael; Wüst, Wolfgang (Investigative Radiology, 2017)
The aim of this study was to intra-individually compare the image quality obtained by dual-source, dual-energy (DSDE) computed tomography (CT) examinations and different virtual monoenergetic reconstructions to a low single-energy (SE) scan.Third-generation DSDE-CT was performed in 49 patients with histologically proven malignant disease of the head and neck region. Weighted average images (WAIs) and virtual monoenergetic images (VMIs) for low (40 and 60 keV) and high (120 and 190 keV) energies were reconstructed. A second scan aligned to the jaw, covering the oral cavity, was performed for every patient to reduce artifacts caused by dental hardware using a SE-CT protocol with 70-kV tube voltages and matching radiation dose settings. Objective image quality was evaluated by calculating contrast-to-noise ratios. Subjective image quality was evaluated by experienced radiologists.Highest contrast-to-noise ratios for vessel and tumor attenuation were obtained in 40-keV VMI (all P < 0.05). Comparable objective results were found in 60-keV VMI, WAI, and the 70-kV SE examinations. Overall subjective image quality was also highest for 40-keV, but differences to 60-keV VMI, WAI, and 70-kV SE were nonsignificant (all P > 0.05). High kiloelectron volt VMIs reduce metal artifacts with only limited diagnostic impact because of insufficiency in case of severe dental hardware. CTDIvol did not differ significantly between both examination protocols (DSDE: 18.6 mGy; 70-kV SE: 19.4 mGy; P = 0.10).High overall image quality for tumor delineation in head and neck imaging were obtained with 40-keV VMI. However, 70-kV SE examinations are an alternative and modified projections aligned to the jaw are recommended in case of severe artifacts caused by dental hardware.
EVALuna2:14672

Computer-aided diagnosis in multiparametric mri of the prostate: An open-access online tool for lesion classification with high accuracy - Ellmann, Stephan; Schlicht, Michael; Dietzel, Matthias; Janka, Rolf Matthias; Hammon, Matthias; Saake, Marc; Ganslandt, Thomas; Hartmann, Arndt; Kunath, Frank; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (Cancers, 2020)
Computer-aided diagnosis (CADx) approaches could help to objectify reporting on prostate mpMRI, but their use in many cases is hampered due to common-built algorithms that are not publicly available. The aim of this study was to develop an open-access CADx algorithm with high accuracy for classification of suspicious lesions in mpMRI of the prostate. This retrospective study was approved by the local ethics commission, with waiver of informed consent. A total of 124 patients with 195 reported lesions were included. All patients received mpMRI of the prostate between 2014 and 2017, and transrectal ultrasound (TRUS)-guided and targeted biopsy within a time period of 30 days. Histopathology of the biopsy cores served as a standard of reference. Acquired imaging parameters included the size of the lesion, signal intensity (T2w images), diffusion restriction, prostate volume, and several dynamic parameters along with the clinical parameters patient age and serum PSA level. Inter-reader agreement of the imaging parameters was assessed by calculating intraclass correlation coefficients. The dataset was stratified into a train set and test set (156 and 39 lesions in 100 and 24 patients, respectively). Using the above parameters, a CADx based on an Extreme Gradient Boosting algorithm was developed on the train set, and tested on the test set. Performance optimization was focused on maximizing the area under the Receiver Operating Characteristic curve (ROCAUC). The algorithm was made publicly available on the internet. The CADx reached an ROCAUC of 0.908 during training, and 0.913 during testing (p = 0.93). Additionally, established rule-in and rule-out criteria allowed classifying 35.8% of the malignant and 49.4% of the benign lesions with error rates of <2%. All imaging parameters featured excellent inter-reader agreement. This study presents an open-access CADx for classification of suspicious lesions in mpMRI of the prostate with high accuracy. Applying the provided rule-in and rule-out criteria might facilitate to further stratify the management of patients at risk.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Artificial intelligence; Computer-aided diagnosis; Machine learning; Prostate cancer; Prostate mpMRI

Computer-aided evaluation of low-dose and low-contrast agent third-generation dual-source CT angiography prior to transcatheter aortic valve implantation (TAVI) - Dankerl, Peter; Hammon, Matthias; Seuß, Hannes; Tröbs, Monique; Schuhbaeck, Annika; Hell, Michaela M.; Achenbach, Stephan; Uder, Michael; Marwan, Mohamed; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2016)
To evaluate the performance of computer-aided evaluation software for a comprehensive workup of patients prior to transcatheter aortic valve implantation (TAVI) using low-contrast agent and low radiation dose third-generation dual-source CT angiography.We evaluated 30 consecutive patients scheduled for TAVI. All patients underwent ECG-triggered high-pitch dual-source CT angiography of the aortic root and aorta with a standardized contrast agent volume (30 ml Imeron350, flow rate 4 ml/s) and low-dose (100 kv/350 mAs) protocol. An expert (10 years of experience) manually evaluated aortic root and iliac access dimensions (distance between coronary ostia and aortic annulus, minimal/maximal diameters and area-derived diameter of the aortic annulus) and best CT-predicted fluoroscopic projection angle as the reference standard. Utilizing computer-aided software (syngo.via), the same pre-TAVI workup was performed and compared to the reference standard.Mean CTDI[Formula: see text] was 3.46 mGy and mean DLP 217.6 ± 12.1 mGy cm, corresponding to a mean effective dose of 3.7 ± 0.2 mSv. Computer-aided evaluation was successful in all but one patient. Compared to the reference standard, Bland-Altman analysis indicated very good agreement for the distances between aortic annulus and coronary ostia (RCA: mean difference 0.8 mm; 95 % CI 0.4-1.2 mm; LM: mean difference 0.9 mm; 95 % CI 0.5-1.3 mm); however, we demonstrated a systematic overestimation of annulus- derived diameter using the software (mean difference 44.4 mm[Formula: see text]; 95 % CI 30.4-58.3 mm[Formula: see text]). Based on respective annulus dimensions, the recommended prosthesis size (Edwards SAPIEN 3) matched in 26 out of the 29 patients (90 %). CT-derived fluoroscopic projection angles showed an excellent agreement for both methods. Out of 58 iliac arteries, 15 (25 %) arteries could not be segmented by the software. Preprocessing time of the software was 71 ± 11 s (range 51-96 s), and reading time with the software was 118 ± 31 s (range 68-201 s).In the workup of pre-TAVI CT angiography, computer-aided evaluation of low-contrast, low-dose examinations is feasible with good agreement and quick reading time. However, a systematic overestimation of the aortic annulus area is observed.
EVALuna2:14602

Computer-aided evaluation of the anatomical accuracy of hybrid SPECT/spiral-CT imaging of lesions localized in the neck and upper abdomen - Hahn, Dieter; Bennewitz, Christian; Kuwert, Torsten; Han, Jingfeng; Ritt, Philipp; Hahn, Dieter; Thimister, Willie; Hornegger, Joachim; Uder, Michael; Schmidt, Daniela (Nuclear Medicine Communications, 2012)
OBJECTIVE: The purpose of this study was to investigate the anatomical accuracy of hardware-based single-photon emission computed tomography/computed tomography (SPECT/CT) registration in the upper abdomen and neck. METHODS: The database consisted of 90 patients referred for SPECT/CT for diagnostic workup of either thyroid/parathyroid disease (n=46) or abdominal neuroendocrine tumours (n=44). In the first group, Tc-MIBI was used as the tracer and in the second I-metaiodobenzylguanidine (n=13), In-octreotide (n=28) or Tc-octreotide (n=3). For predefined structures represented by both modalities, the distances between the centres of gravity of their CT and SPECT representation were determined in a semiautomated manner. In cervical data sets, this analysis was performed for the submandibular salivary glands (n=92) and in abdominal data sets for 69 neoplastic foci. RESULTS: The mean distances were 5.7±2.0 mm (range: 1.84-9.67 mm) in the neck and 6.8±3.3 mm (range: 1.4-19.7 mm) in the abdomen. In 42 out of 92 of the cervical and 40 out of 69 of the abdominal data sets at least one of the X-direction-determined, Y-direction-determined, and Z-direction-determined distances was greater than the SPECT pixel width of 4.6 mm. CONCLUSION: The anatomical accuracy of hardware-based SPECT/CT fusion depends also on the region of the body studied. For example, in the neck and upper abdomen the accuracy is lower than in the lower lumbar spine. In clinical routine, SPECT/CT data sets acquired for the neck and upper abdomen should be regularly checked and corrected for SPECT/CT misalignment. This is, in particular, important when CT-based corrections of SPECT involving pixelwise data integration such as for attenuation correction are made. © 2012 Wolters Kluwer Health | Lippincott Williams & Wilkins.

Cone beam CT imaging of the paranasal region with a multipurpose X-ray system-image quality and radiation exposure - Ohlmeyer, Sabine; Saake, Marc; Buder, Thomas; May, Matthias; Uder, Michael; Wüst, Wolfgang (Applied Sciences, 2020)
Besides X-ray and fluoroscopy, a previously introduced X-ray scanner offers a 3D cone beam option (Multitom Rax, Siemens Healthcare). The aim of this study was to evaluate various scan parameters and post-processing steps to optimize image quality and radiation exposure for imaging of the parasinus region. Four human cadaver heads were examined with different tube voltages (90-121 kV), dose levels (DLs) (278-2180 nGy) and pre-filtration methods (none, Cu 0.2 mm, Cu 0.3 mm and Sn 0.4 mm). All images were reconstructed in 2 mm slice thickness with and without a metal artifact reduction algorithm in three different kernels. In total, 80 different scan protocols and 480 datasets were evaluated. Image quality was rated on a 5-point Likert scale. Radiation exposure (mean computed tomography volume index (CTDIvol) and effective dose) was calculated for each scan. The most dose-effective combination for the diagnosis of sinusitis was 121 kV/DL of 278/0.3 mm copper (CTDIvol 1.70 mGy, effective dose 77 μSv). Scan protocols with 121 kV/DL1090/0.3 mm copper were rated sufficient for preoperative sinus surgery planning (CTDIvol 4.66 mGy, effective dose 212 μSv). Therefore, sinusitis and preoperative sinus surgery planning can be performed in diagnostic image quality at low radiation dose levels with a multipurpose X-ray system.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Computed tomography; DVT; Medical imaging; Parasinus region; Sinusitis; Three-dimensional; X-ray

Contrast-Enhanced µCT for Visualizing and Evaluating Murine Intestinal Inflammation - Jung, Dennis; Heiß, Rafael; Kramer, Viktoria; Thoma, Oana-Maria; Regensburger, Adrian; Rascher, Wolfgang; Uder, Michael; Neurath, Markus; Knieling, Ferdinand; Waldner, Maximilian (Theranostics, 2018)
Rationale: To develop a simple and fast protocol for the assessment of acute and chronic experimental intestinal inflammation using contrast-enhanced µCT. Methods: For the imaging studies, an acute 2% and 3% dextran sodium sulfate (n = 15, female, 8-12 weeks) and a chronic adoptive transfer colitis model (n = 10, female, 8-9 weeks) were established over 9 days or 6 weeks, respectively. Throughout the experiments, longitudinal measurement of murine intestinal wall thickness and time dependent perfusion was performed on a small animal µCT system (90 kV, 160 μA, FOV: 60 mm, scan time: 17 s, image size: 512x512, layer thickness: 118 µm) between 0.5 and 30 min after intravenous bolus injection of an iodine contrast agent. Weight development, small animal endoscopy, and histological ex vivo analysis were compared to contrast-enhanced µCT imaging findings. Results: Murine intestinal wall thickness was significantly increased in inflamed colons of acute colitis at day 9 in comparison to pre-inflamed state. Perfusion analysis revealed a late contrast enhancement in acute inflamed colons and the renal medulla at day 9 compared to control mice. An increasing intestinal wall thickness was monitored 3, 5 and 6 weeks after on-set of chronic colitis in comparison to controls. A good correlation with endoscopic (r = 0.75, p < 0.0001) and histologic degree of inflammation (r = 0.83, p = 0.04) was found. Conclusion: Contrast-enhanced µCT is a simple and fast method to assess acute intestinal inflammation and to monitor disease progression in experimental models of chronic colitis. According to our findings, one single contrast-enhanced µCT-scan is a valid non-invasive modality to quantify the degree of inflammation in the entire digestive tract in murine inflammatory models.
EVALuna2:35195

Contrast medium application in pediatric high-pitch cardiovascular CT angiography: manual or power injection? - Saake, Marc; Lell, Michael; Rompel, Oliver; Glöckler, Martin; May, Matthias; Eller, Achim; Achenbach, Stephan; Uder, Michael; Wüst, Wolfgang (Journal of Cardiovascular Computed Tomography, 2014)
Dual-source CT offers accurate depiction of cardiac structures in children with congenital heart disease. For cardiac CT, optimal enhancement of the cardiovascular structures is essential. There is considerable controversy about the administration of contrast medium (CM) in infants and small children, with either a power injector or a manual (hand) injection.The aim of this study was to compare image quality with power injection of CM (study group) and manual injection (control group).Thirty-four patients (study group, 6.8 ± 9.6 months and control group, 4.6 ± 8.9 months, nonrandomized) underwent dual-source CT angiography of the chest using a prospective electrocardiography-triggered high-pitch spiral mode (pitch, 3.4; 80 kV). In the study group (17 patients), a power injector was used, and in the control group (17 patients, historical group), manual CM injection had been performed. To assess image quality, both subjective and objective parameters were evaluated independently by 2 experienced radiologists.Subjective overall image quality, signal-to-noise ratio, and contrast-to-noise ratio were significantly higher using power injection compared with manual injection (P < .05). However, depiction of cardiovascular structures did not differ significantly between both groups in all evaluated regions except the superior vena cava and the coronary arteries.In infants and small children with congenital heart disease, both manual and power injector protocols allowed for diagnostic imaging of cardiac and extracardiac structures. However, image quality and vascular attenuation were superior using a power injector.
EVALuna2:11950

Contrast-to-noise ratio analysis of microscopic diffusion anisotropy indices in q-space trajectory imaging - Martin, Jan; Endt, Sebastian; Wetscherek, Andreas; Kuder, Tristan Anselm; Dörfler, Arnd; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Zeitschrift für Medizinische Physik, 2019)
Diffusion anisotropy in diffusion tensor imaging (DTI) is commonly quantified with normalized diffusion anisotropy indices (DAIs). Most often, the fractional anisotropy (FA) is used, but several alternative DAIs have been introduced in attempts to maximize the contrast-to-noise ratio (CNR) in diffusion anisotropy maps. Examples include the scaled relative anisotropy (sRA), the gamma variate anisotropy index (GV), the surface anisotropy (UA surf ), and the lattice index (LI). With the advent of multidimensional diffusion encoding it became possible to determine the presence of microscopic diffusion anisotropy in a voxel, which is theoretically independent of orientation coherence. In accordance with DTI, the microscopic anisotropy is typically quantified by the microscopic fractional anisotropy (μFA). In this work, in addition to the μFA, the four microscopic diffusion anisotropy indices (μDAIs) μsRA, μGV, μUA surf , and μLI are defined in analogy to the respective DAIs by means of the average diffusion tensor and the covariance tensor. Simulations with three representative distributions of microscopic diffusion tensors revealed distinct CNR differences when differentiating between isotropic and microscopically anisotropic diffusion. q-Space trajectory imaging (QTI) was employed to acquire brain in-vivo maps of all indices. For this purpose, a 15 min protocol featuring linear, planar, and spherical tensor encoding was used. The resulting maps were of good quality and exhibited different contrasts, e.g. between gray and white matter. This indicates that it may be beneficial to use more than one μDAI in future investigational studies.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Contrast-to-noise ratio; Diffusion; Microstructure; Multidimensional; q-Space trajectory

Contrast volume reduction using third generation dual source computed tomography for the evaluation of patients prior to transcatheter aortic valve implantation - Bittner, Daniel O.; Klinghammer, Lutz; Schuhbaeck, Annika; Hell, Michaela M.; Muschiol, Gerd; Gauss, Soeren; Lell, Michael; Uder, Michael; Hoffmann, Udo; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (European Radiology, 2016)
Chronic renal failure is common in patients referred for transcatheter aortic valve implantation (TAVI). CT angiography is recommended and provides crucial information prior to TAVI. We evaluated the feasibility of a reduced contrast volume protocol for pre-procedural CT imaging.Forty consecutive patients were examined with prospectively ECG-triggered high-pitch spiral acquisition using a novel third-generation dual-source CT system; 38 ml contrast agent was used. Image quality was graded on a visual scale (1-4). Contrast attenuation was measured at the level of the aortic root and at the iliac bifurcation.Mean patient age was 82 ± 6 years (23 males; 58 %). Mean attenuation/average image quality was 285 ± 60 HU/1.5 at the aortic annulus compared to 289 ± 74 HU/1.8 at the iliac bifurcation (p = 0.77/p = 0.29). Mean estimated effective radiation dose was 2.9 ± 0.3 mSv. A repeat acquisition was necessary in one patient due to image quality. Out of the 35 patients who underwent TAVI, 31 (89 %) patients had no or mild aortic regurgitation. Thirty-two (91 %) patients were discharged successfully.Pre-procedural CTA with a total of 38 ml contrast volume is feasible and clinically useful, using third-generation dual-source CT, allowing comprehensive imaging for procedural success.o Reduction of contrast agent volume is crucial in patients with chronic renal failure. o Novel third-generation computed tomography helps to reduce contrast agent volume. o Pre-procedural CT allows comprehensive imaging for procedural success before heart valve implantation. o A low-contrast CT protocol is feasible for pre-procedural TAVI planning.
EVALuna2:14600

COPEPTIN AS A RESEARCH MARKER IN CARDIOVASCULAR DISEASE - Bosch, Agnes; Ott, C.; Schmid, Andrea; Kannenkeril, D.; Karg, M.; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2018)
EVALuna2:202963

COPEPTIN LEVELS IN PATIENTS WITH TREATMENT RESISTANT HYPERTENSION BEFORE AND AFTER RENAL DENERVATION - Jumar, A.; Ott, Christian; Schmid, Axel; Kannenkeril, D.; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36267

Copeptin levels in patients with treatment resistant hypertension before and six months after renal denervation - Bosch, Agnes; Schmid, Axel; Ott, Christian; Kannenkeril, Dennis; Karg, Marina V.; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (American Journal of Hypertension, 2019)
BACKGROUND: Copeptin, the C-terminal peptide of pro-vasopressin, is released from the neurohypophysis and reflects the activity of the hormone arginine vasopressin in patients with hypertension. Elevated copeptin levels are associated with increased cardiovascular and all-cause mortality. The aim of this study is to compare copeptin levels in patients with treatment resistant hypertension (TRH) before and 6 months after renal denervation (RDN). METHODS: Copeptin was measured in 34 patients with TRH and 30 patients with primary hypertension stage 1 or 2 (HT). In addition, copeptin levels were measured in patients with TRH at 6 month follow-up visit after RDN. RDN was performed by an experienced interventionalist applying at least four ablations longitudinally and rotationally within the lengths of each renal artery to cover a full four quadrant ablation. RESULTS: In patients with TRH 24h ambulatory blood pressure (BP) decreased from 154±15/ 87±12 mmHg to 146±13/ 83±7.9 mmHg after RDN (systolic: p=0.001, diastolic: p=0.034). There was no significant change in copeptin levels in these 34 patients with TRH before versus six months after RDN (median 8.4 [interquartile range 3.6-14] vs 8.5 [4.5-13] pmol/l, p=0.334). Patients with TRH had higher copeptin levels (p=0.024) than patients with HT (24h ambulatory BP: 142±11/ 91±8.3 mmHg, copeptin: 4.2 [2.8-6.3] pmol/l). CONCLUSION: Patients with TRH showed 2 fold higher copeptin levels than patients with HT. RDN did not lead to any change of copeptin levels in patients with TRH 6 months after procedure despite significant fall in BP.
EVALuna2:210911

Coronary CT angiography in patients with atrial fibrillation: Standard-dose and low-dose imaging with a high-resolution whole-heart CT scanner - Matveeva, Anna; Schmitt, Rainer R.; Edtinger, Karoline; Wagner, Matthias; Kerber, Sebastian; Deneke, Thomas; Uder, Michael; Barth, Sebastian (European Radiology, 2018)
OBJECTIVE: To compare image quality, observer confidence, radiation exposure in the standard-dose (SD-CCTA) and low-dose (LD-CCTA) protocols of coronary CT angiography (CCTA) in patients with atrial fibrillation (AF). MATERIAL AND METHODS: CCTA was performed in 303 patients using a CT scanner with 16-cm coverage (111 scans during sinus rhythm (SR); 192 during AF). LD-CCTA was used in 218 patients; SD-CCTA in 85 patients suspected of having coronary artery disease (CAD). Image quality and observer confidence were evaluated on 5-point scales. Radiation doses were recorded. RESULTS: Image quality was superior in the SD-CCTA compared to the LD-CCTA (SR 1.45±0.40; AF 1.72±0.46; vs. SR 1.83±0.48; AF 1.92±0.50; p < 0.001). Observers were more confident with SD-CCTA than with LD-CCTA (SR 1.38±0.33; AF 1.61±0.43; vs. SR 1.70±0.45; AF 1.82±0.50; p < 0.001). Radiation doses in AF were significantly higher than in the SR (LD-CCTA, 1.68±0.71 mSv; SD-CCTA, 3.72±1.95 mSv; vs. LD-CCTA, 1.3 ±0.52 mSv; SD-CCTA, 2.67±1.47 mSv; p < 0.001). CONCLUSION: Using a low-dose protocol in AF, radiation exposure can be decreased by 50 % at the expense of 20 % impaired image quality. A low-dose CCTA protocol can be considered in young patients, whereas the standard-dose protocol is recommended for older patients and those suspected of having CAD. KEY POINTS: • Whole-heart CT allows visualization of the coronary arteries in atrial fibrillation. • Low-dose CT decreases radiation exposure by 50%, image quality by 20%. • Standard-dose CT seems advantageous when concomitant coronary artery disease is suspected.
EVALuna2:34694

Correction to: Accelerated quantification of tissue sodium concentration in skeletal muscle tissue: quantitative capability of dictionary learning compressed sensing (Magnetic Resonance Materials in Physics, Biology and Medicine, (2020), 10.1007/s10334-019-00819-2) - Utzschneider, Matthias; Behl, Nicolas G.R.; Lachner, Sebastian; Gast, Lena; Maier, Andreas; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Materials in Physics Biology and Medicine, 2020)
The original version of this article unfortunately contained a mistake. Title was incorrect. The corrected title is given below. Accelerated quantification of tissue sodium concentration in skeletal muscle tissue: quantitative capability of dictionary learning compressed sensing. The original article has been corrected.
CRIS-Team Scopus Importer:2020-02-25

Correction to: Effect of long term CPAP therapy on cardiac parameters assessed with cardiac MRI (The International Journal of Cardiovascular Imaging, (2021), 37, 2, (613-621), 10.1007/s10554-020-02024-y) - Wüst, Wolfgang; May, Matthias; Wiesmüller, Marco; Uder, Michael; Schmid, Andrea (International Journal of Cardiovascular Imaging, 2022)
parameters assessed with cardiac MRI written by W. Wuest, M. S. May, M. Wiesmueller, M. Uder and A. Schmid”, was originally published Online First without Open Access. After publication in volume 37, issue 2, page 613–621 the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © The Author(s) 2021 and the article is forthwith distributed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit https:// creat iveco mmons. org/ licen ses/ by/4.0. Open Access funding enabled and organized by Projekt DEAL. The original article has been corrected.
CRIS-Team Scopus Importer:2022-02-11

Correction to: Variation in cartilage T2 and T2* mapping of the wrist: a comparison between 3- and 7-T MRI (European Radiology Experimental, (2023), 7, 1, (80), 10.1186/s41747-023-00394-1) - Heiß, Rafael; Weber, Marc André; Balbach, Eva; Hinsen, Maximilian; Geißler, Frederik; Nagel, Armin Michael; Ladd, Mark E.; Arkudas, Andreas; Horch, Raymund E.; Gall, Christine; Uder, Michael; Roemer, Frank (European Radiology Experimental, 2024)
The original article [1] omits the following funding information that the authors would like to note in this correction article: “We acknowledge financial support by Deutsche Forschungsgemeinschaft and Friedrich-Alexander-Universität Erlangen-Nürnberg within the funding programme "Open Access Publication Funding".”.
CRIS-Team Scopus Importer:2024-03-22

Correlation of mammographic density and serum calcium levels in patients with primary breast cancer - Hack, Carolin; Stoll, Martin; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Haeberle, Lothar; Ganslandt, Thomas; Heindl, Felix; Schulz-Wendtland, Rüdiger; Uder, Michael; Beckmann, Matthias; Fasching, Peter; et al. (Cancer Medicine, 2017)
Percentage mammographic breast density (PMD) is one of the most important risk factors for breast cancer (BC). Calcium, vitamin D, bisphosphonates, and denosumab have been considered and partly confirmed as factors potentially influencing the risk of BC. This retrospective observational study investigated the association between serum calcium level and PMD. A total of 982 BC patients identified in the research database at the University Breast Center for Franconia with unilateral BC, calcium and albumin values, and mammogram at the time of first diagnosis were included. PMD was assessed, using a semiautomated method by two readers. Linear regression analyses were conducted to investigate the impact on PMD of the parameters of serum calcium level adjusted for albumin level, and well-known clinical predictors such as age, body mass index (BMI), menopausal status and confounder for serum calcium like season in which the BC was diagnosed. Increased calcium levels were associated with reduced PMD (P = 0.024). Furthermore, PMD was inversely associated with BMI (P < 0.001) and age (P < 0.001). There was also an association between PMD and menopausal status (P < 0.001). The goodness-of-fit of the regression model was moderate. This is the first study assessing the association between serum calcium level and PMD. An inverse association with adjusted serum calcium levels was observed. These findings add to previously published data relating to vitamin D, bisphosphonates, denosumab, and the RANK/RANKL signaling pathway in breast cancer risk and prevention.
EVALuna2:175

Current situation of experimental radiology in Germany - Bäuerle, Tobias; Uder, Michael (Radiologe, 2016)
EVALuna2:14608

Cutting Staff Radiation Exposure and Improving Freedom of Motion during CT Interventions: Comparison of a Novel Workflow Utilizing a Radiation Protection Cabin versus Two Conventional Workflows - Dankerl, Peter; May, Matthias; Canstein, Christian; Uder, Michael; Saake, Marc (Diagnostics, 2021)
This study aimed to evaluate the radiation exposure to the radiologist and the procedure time of prospectively matched CT interventions implementing three different workflows-the radiologist-(I) leaving the CT room during scanning; (II) wearing a lead apron and staying in the CT room; (III) staying in the CT room in a prototype radiation protection cabin without lead apron while utilizing a wireless remote control and a tablet. We prospectively evaluated the radiologist's radiation exposure utilizing an electronic personal dosimeter, the intervention time, and success in CT interventions matched to the three different workflows. We compared the interventional success, the patient's dose of the interventional scans in each workflow (total mAs and total DLP), the radiologist's personal dose (in mu SV), and interventional time. To perform workflow III, a prototype of a radiation protection cabin, with 3 mm lead equivalent walls and a foot switch to operate the doors, was built in the CT examination room. Radiation exposure during the maximum tube output at 120 kV was measured by the local admission officials inside the cabin at the same level as in the technician's control room (below 0.5 mu Sv/h and 1 mSv/y). Further, to utilize the full potential of this novel workflow, a sterile packed remote control (to move the CT table and to trigger the radiation) and a sterile packed tablet anchored on the CT table (to plan and navigate during the CT intervention) were operated by the radiologist. There were 18 interventions performed in workflow I, 16 in workflow II, and 27 in workflow III. There were no significant differences in the intervention time (workflow I: 23 min +/- 12, workflow II: 20 min +/- 8, and workflow III: 21 min +/- 10, p = 0.71) and the patient's dose (total DLP, p = 0.14). However, the personal dosimeter registered 0.17 +/- 0.22 mu Sv for workflow II, while I and III both documented 0 mu Sv, displaying significant difference (p < 0.001). All workflows were performed completely and successfully in all cases. The new workflow has the potential to reduce interventional CT radiologists' radiation dose to zero while relieving them from working in a lead apron all day.
CRIS-Team WoS Importer:2021-07-09

Deep learning–based quantitative susceptibility mapping (QSM) in the presence of fat using synthetically generated multi-echo phase training data - Hanspach, Jannis; Bollmann, Steffen; Grigo, Johanna; Karius, Andre; Uder, Michael; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2022)
Purpose: To enable a fast and automatic deep learning–based QSM reconstruction of tissues with diverse chemical shifts, relevant to most regions outside the brain. Methods: A UNET was trained to reconstruct susceptibility maps using synthetically generated, unwrapped, multi-echo phase data as input. The RMS error with respect to synthetic validation data was computed. The method was tested on two in vivo knee and two pelvis data sets. Comparisons were made to a conventional fat–water separation pipeline by applying a commonly used graph-cut algorithm, both without and with an extended mask for background field removal (FWS-CONV-QSM and FWS-MASK-CONV-QSM, respectively). Several regions of interest were segmented and compared. Furthermore, the approach was tested on a prostate cancer patient receiving low-dose-rate brachytherapy, to detect and localize the seeds by MRI. Results: The RMS error was 0.292 ppm with FWS-CONV-QSM and 0.123 ppm for the UNET approach. Susceptibility maps were reconstructed much faster (< 10 s) and completely automatically (no background masking needed) by the UNET compared with the other applied techniques (5 min 51 s and 22 min 44 s for CONV-QSM and FWS-MASK-CONV-QSM, respectively. Background artifacts, fat–water swaps, and hypointense artifacts between I-125 seeds of a patient receiving low-dose brachytherapy in the prostate were largely reduced in the UNET approach. Conclusions: Deep learning–based QSM reconstruction, trained solely with synthetic data, is well-suited to rapidly reconstructing high-quality susceptibility maps in the presence of fat without needing masking for background field removal.
CRIS-Team Scopus Importer:2022-06-24
Keywords: deep learning; dipole inversion; fat–water separation; magnetic resonance imaging (MRI); prostate seed detection; quantitative susceptibility mapping (QSM)

Deep learning for brain metastasis detection and segmentation in longitudinal MRI data - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Medical Physics, 2022)
Keywords: Deep learning; brain metastasis; MRI; loss function; sensitivity specificity

Detection and prediction of background parenchymal enhancement on breast MRI using deep learning - Das, Badhan Kumar; Kapsner, Lorenz; Ohlmeyer, Sabine; Laun, Frederik Bernd; Maier, Andreas; Uder, Michael; Wenkel, Evelyn; Bickelhaupt, Sebastian; Liebert, Andrzej (Joint Annual Meeting ISMRM-ESMRMB & ISMRT 31st Annual Meeting, 2023)
The purpose of this work was to automatically classify BPE using T1-weighted subtraction volumes and diffusion-weighted imaging volumes in breast MRI. The dataset consisted of 621 routine breast MRI examination acquired at University Hospital Erlangen. 2D MIP and 3D T1-subtraction volumes were used for the automatic detection of BPE classes. Multi-b-value DWI (up to1500s/mm2) DWI images were used for automatic prediction. ResNet and DenseNet models were used for 2D and 3D data respectively. The study demonstrated an AUROC of 0.8107 on the test set using the T1-subtraction volumes. With DWI volumes, a slightly decreased AuROC of 0.78 was achieved.<br

Detection of Changes in Renal Blood Flow Using Arterial Spin Labeling MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (American Journal of Nephrology, 2021)
Background: Alteration in kidney perfusion is an early marker of renal damage. The purpose of this study was to evaluate if changes in renal blood flow (RBF) could be detected using MRI with arterial spin labeling (ASL) technique. Methods: RBF as assessed by cortical (CRBF), medullary, and total renal blood flow (TRBF) were measured by MRI with arterial spin labeling (ASL-MRI) using flow-sensitive alternating inversion recovery true fast imaging with steady-state precession sequence. In 11 normotensive healthy individuals (NT) and 11 hypertensive patients (HT), RBF was measured at baseline and after both feet were covered with cold ice packs (cold pressor test) that activates the sympathetic nervous system. In another experiment, RBF was measured in 10 patients with CKD before and after a pharmacological intervention. We compared RBF measurements between the 3 study populations. Results: A significant reduction in CRBF (p = 0.042) and a trend in TRBF (p = 0.053) were observed in response to the activation of the sympathetic nervous system. A trend toward reduction of CRBF (p = 0.051) and TRBF (p = 0.059) has been detected after pharmacological intervention. TRBF was significantly lower in patients with HT and CKD patients compared to NT individuals (NT vs. HT, p = 0.014; NT vs. CKD, p = 0.004). TRBF was lower in patients with CKD compared to HT (p = 0.047). Conclusion: Our data indicate that both acute and short-term changes in RBF could be detected using ASL-MRI. We were able to detect differences in RBF between healthy and diseased individuals by needing only small sample size per group. Thus, ASL-MRI offers an advantage in conducting clinical trials compared to other technologies.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ASL-MRI; Cold pressor test; Renal blood flow

DETECTION OF CHANGES IN RENAL BLOOD FLOW USING ARTERIAL SPIN LABELING MRI - Kannenkeril, Dennis; Janka, Rolf Matthias; Bosch, Agnes; Jung, Susanne; Kolwelter, Julie; Striepe, Kristina; Ott, Christian; Martirosian, Petros; Schiffer, Mario; Uder, Michael; Schmieder, Roland (JOURNAL OF HYPERTENSION, 2021)
CRIS-Team WoS Importer:2021-07-30

Detection of collagens by multispectral optoacoustic tomography as an imaging biomarker for Duchenne muscular dystrophy - Regensburger, Adrian; Fonteyne, Lina M.; Jüngert, Jörg; Wagner, Anna; Gerhalter, Teresa; Nagel, Armin Michael; Heiß, Rafael; Flenkenthaler, Florian; Qurashi, Matthias; Neurath, Markus; Klymiuk, Nikolai; Kemter, Elisabeth; et al. (Nature Medicine, 2019)
Biomarkers for monitoring of disease progression and response to therapy are lacking for muscle diseases such as Duchenne muscular dystrophy. Noninvasive in vivo molecular imaging with multispectral optoacoustic tomography (MSOT) uses pulsed laser light to induce acoustic pressure waves, enabling the visualization of endogenous chromophores. Here we describe an application of MSOT, in which illumination in the near- and extended near-infrared ranges from 680–1,100 nm enables the visualization and quantification of collagen content. We first demonstrated the feasibility of this approach to noninvasive quantification of tissue fibrosis in longitudinal studies in a large-animal Duchenne muscular dystrophy model in pigs, and then applied this approach to pediatric patients. MSOT-derived collagen content measurements in skeletal muscle were highly correlated to the functional status of the patients and provided additional information on molecular features as compared to magnetic resonance imaging. This study highlights the potential of MSOT imaging as a noninvasive, age-independent biomarker for the implementation and monitoring of newly developed therapies in muscular diseases.
CRIS-Team Scopus Importer:2019-12-17

Detection of microcalcifications in spiral breast computed tomography with photon-counting detector is feasible: A specimen study - Wetzl, Matthias; Wenkel, Evelyn; Balbach, Eva; Dethlefsen, Ebba; Hartmann, Arndt; Emons, Julius; Kuhl, Christiane; Beckmann, Matthias; Uder, Michael; Ohlmeyer, Sabine (Diagnostics, 2021)
The primary objective of the study was to compare a spiral breast computed tomography system (SBCT) to digital breast tomosynthesis (DBT) for the detection of microcalcifications (MCs) in breast specimens. The secondary objective was to compare various reconstruction modes in SBCT. In total, 54 breast biopsy specimens were examined with mammography as a standard reference, with DBT, and with a dedicated SBCT containing a photon-counting detector. Three different reconstruction modes were applied for SBCT datasets (Recon1 = voxel size (0.15 mm)3, smooth kernel; Recon2 = voxel size (0.05 mm)3, smooth kernel; Recon3 = voxel size (0.05 mm)3, sharp kernel). Sensitivity and specificity of DBT and SBCT for the detection of suspicious MCs were analyzed, and the McNemar test was used for comparisons. Diagnostic confidence of the two readers (Likert Scale 1 = not confident; 5 = completely confident) was analyzed with ANOVA. Regarding detection of MCs, reader 1 had a higher sensitivity for DBT (94.3%) and Recon2 (94.9%) compared to Recon1 (88.5%; p < 0.05), while sensitivity for Recon3 was 92.4%. Respectively, reader 2 had a higher sensitivity for DBT (93.0%), Recon2 (92.4%), and Recon3 (93.0%) compared to Recon1 (86.0%; p < 0.05). Specificities ranged from 84.7–94.9% for both readers (p > 0.05). The diagnostic confidence of reader 1 was better with SBCT than with DBT (DBT 4.48 ± 0.88, Recon1 4.77 ± 0.66, Recon2 4.89 ± 0.44, and Recon3 4.75 ± 0.72; DBT vs. Recon1/2/3: p < 0.05), while reader 2 found no differences. Sensitivity and specificity for the detection of MCs in breast specimens is equal for DBT and SBCT when a small voxel size of (0.05 mm)3 is used with an equal or better diagnostic confidence for SBCT compared to DBT.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Breast cancer; Microcalcifications; Reconstruction modes; Spiral breast CT

Determining microvascular obstruction and infarct size with steady-state free precession imaging cardiac MRI - Wüst, Wolfgang; Lell, Michael; May, Matthias; Scharf, Michael; Schlundt, Christian; Achenbach, Stephan; Uder, Michael; Schmid, Andrea (PLoS ONE, 2015)
In cardiac MRI (cMRI) injection of contrast medium may be performed prior to the acquisition of cine steady-state free precession (SSFP) imaging to speed up the protocol and avoid delay before late Gadolinium enhancement (LGE) imaging. Aim of this study was to evaluate whether a condensed clinical protocol with contrast cine SSFP imaging is able to detect early microvascular obstruction (MO) and determine the infarct size compared to the findings of LGE inversion recovery sequences.The study complies with the Declaration of Helsinki and was performed following approval by the ethic committee of the University of Erlangen-Nuremberg. Written informed consent was obtained from every patient. 68 consecutive patients (14 females/54 males) with acute ST-elevation myocardial infarction (STEMI) treated by percutaneous coronary revascularization were included in this study. CMRI was performed 6.6±2 days after symptom onset and MO and infarct size in early contrast SSFP cine imaging were compared to LGE imaging.MO was detected in 47/68 (69%) patients on cine SSFP and in 41/68 (60%) patients on LGE imaging. In 6 patients MO was found on cine SSFP imaging but was not detectable on LGE imaging. Infarct size on cine SSFP showed a strong agreement to LGE imaging (intraclass correlation coefficient [ICC] of 0.96 for enddiastolic, p<0.001 and 0.96 for endsystolic, p<0.001 respectively). Significant interobserver agreement was found measuring enddiastolic and endsystolic infarct size on cine SSFP imaging (p<0.01).In patients after STEMI infarct size and presence of MO can be detected with contrast cine SSFP imaging. This could be an option in patients who are limited in their ability to comply with the demands of a cMRI protocol.
EVALuna2:12029

Development and Evaluation of a Semi-automated Segmentation Tool and a Modified Ellipsoid Formula for Volumetric Analysis of the Kidney in Non-contrast T2-Weighted MR Images - Seuß, Hannes; Janka, Rolf Matthias; Pruemmer, Marcus; Hammon, Rebecca; Theis, Ragnar; Sandmair, Martin; Amann, Kerstin Ute; Bäuerle, Tobias; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Journal of Digital Imaging, 2017)
Volumetric analysis of the kidney parenchyma provides additional information for the detection and monitoring of various renal diseases. Therefore the purposes of the study were to develop and evaluate a semi-automated segmentation tool and a modified ellipsoid formula for volumetric analysis of the kidney in non-contrast T2-weighted magnetic resonance (MR)-images. Three readers performed semi-automated segmentation of the total kidney volume (TKV) in axial, non-contrast-enhanced T2-weighted MR-images of 24 healthy volunteers (48 kidneys) twice. A semi-automated threshold-based segmentation tool was developed to segment the kidney parenchyma. Furthermore, the three readers measured renal dimensions (length, width, depth) and applied different formulas to calculate the TKV. Manual segmentation served as a reference volume. Volumes of the different methods were compared and time required was recorded. There was no significant difference between the semi-automatically and manually segmented TKV (p = 0.31). The difference in mean volumes was 0.3 ml (95% confidence interval (CI), -10.1 to 10.7 ml). Semi-automated segmentation was significantly faster than manual segmentation, with a mean difference = 188 s (220 vs. 408 s); p < 0.05. Volumes did not differ significantly comparing the results of different readers. Calculation of TKV with a modified ellipsoid formula (ellipsoid volume × 0.85) did not differ significantly from the reference volume; however, the mean error was three times higher (difference of mean volumes -0.1 ml; CI -31.1 to 30.9 ml; p = 0.95). Applying the modified ellipsoid formula was the fastest way to get an estimation of the renal volume (41 s). Semi-automated segmentation and volumetric analysis of the kidney in native T2-weighted MR data delivers accurate and reproducible results and was significantly faster than manual segmentation. Applying a modified ellipsoid formula quickly provides an accurate kidney volume.
EVALuna2:14622

Diagnostic Accuracy and Performance Analysis of a Scanner-Integrated Artificial Intelligence Model for the Detection of Intracranial Hemorrhages in a Traumatology Emergency Department. - Kiefer, Jonas; Kopp, Markus; Rüttinger, Theresa; Heiß, Rafael; Wuest, Wolfgang; Amarteifio, Patrick; Ströbel, Armin; Uder, Michael; May, Matthias (Bioengineering, 2023)
Intracranial hemorrhages require an immediate diagnosis to optimize patient management and outcomes, and CT is the modality of choice in the emergency setting. We aimed to evaluate the performance of the first scanner-integrated artificial intelligence algorithm to detect brain hemorrhages in a routine clinical setting. This retrospective study includes 435 consecutive non-contrast head CT scans. Automatic brain hemorrhage detection was calculated as a separate reconstruction job in all cases. The radiological report (RR) was always conducted by a radiology resident and finalized by a senior radiologist. Additionally, a team of two radiologists reviewed the datasets retrospectively, taking additional information like the clinical record, course, and final diagnosis into account. This consensus reading served as a reference. Statistics were carried out for diagnostic accuracy. Brain hemorrhage detection was executed successfully in 432/435 (99%) of patient cases. The AI algorithm and reference standard were consistent in 392 (90.7%) cases. One false-negative case was identified within the 52 positive cases. However, 39 positive detections turned out to be false positives. The diagnostic performance was calculated as a sensitivity of 98.1%, specificity of 89.7%, positive predictive value of 56.7%, and negative predictive value (NPV) of 99.7%. The execution of scanner-integrated AI detection of brain hemorrhages is feasible and robust. The diagnostic accuracy has a high specificity and a very high negative predictive value and sensitivity. However, many false-positive findings resulted in a relatively moderate positive predictive value.
EVALuna2:549632

Diagnostic Accuracy of an MRI Protocol of the Knee Accelerated Through Parallel Imaging in Correlation to Arthroscopy - Schnaiter, Johannes Walter; Roemer, Frank; Mckenna-Kuettner, Axel; Patzak, Hans-Joachim; May, Matthias; Janka, Rolf Matthias; Uder, Michael; Wüst, Wolfgang (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
PURPOSE: Parallel imaging allows for a considerable shortening of examination times. Limited data is available about the diagnostic accuracy of an accelerated knee MRI protocol based on parallel imaging evaluating all knee joint compartments in a large patient population compared to arthroscopy. MATERIALS AND METHODS: 162 consecutive patients with a knee MRI (1.5 T, Siemens Aera) and arthroscopy were included. The total MRI scan time was less than 9 minutes. Meniscus and cartilage injuries, cruciate ligament lesions, loose joint bodies and medial patellar plicae were evaluated. Sensitivity (SE), specificity (SP), positive predictive value (PPV), and negative predictive value (NPV), as well as diagnostic accuracy were determined. RESULTS: For the medial meniscus, the values were: SE 97 %, SP 88 %, PPV 94 %, and NPV 94 %. For the lateral meniscus the values were: SE 77 %, SP 99 %, PPV 98 %, and NPV 89 %. For cartilage injuries the values were: SE 72 %, SP 80 %, PPV 86 %, and NPV 61 %. For the anterior cruciate ligament the values were: SE 90 %, SP 94 %, PPV 77 %, and NPV 98 %, while all values were 100 % for the posterior cruciate ligament. For loose bodies the values were: SE 48 %, SP 96 %, PPV 62 %, and NPV 93 %, and for the medial patellar plicae the values were: SE 57 %, SP 88 %, PPV 18 %, and NPV 98 %. CONCLUSION: A knee MRI examination with parallel imaging and a scan time of less than 9 minutes delivers reliable results with high diagnostic accuracy. KEY POINTS: · An accelerated knee MRI protocol with parallel imaging allows for high diagnostic accuracy.. · Especially meniscal and cruciate ligament injuries are well depicted.. · Cartilage injuries seem to be overestimated.. CITATION FORMAT: · Schnaiter JW, Roemer F, McKenna-Kuettner A et al. Diagnostic Accuracy of an MRI Protocol of the Knee Accelerated Through Parallel Imaging in Correlation to Arthroscopy. Fortschr Röntgenstr 2018; 190: 265 - 272.
EVALuna2:34702

Diagnostic Performance of 0.55 T MRI for Intracranial Aneurysm Detection - Osmanodja, Filiz; Rösch, Julie; Knott, Michael; Dörfler, Arnd; Grodzki, David; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: Intracranial aneurysm (IA) is the main cause of subarachnoid hemorrhages. Time-of-flight (TOF) magnetic resonance angiography (MRA) at 1.5 T or 3 T magnetic resonance imaging (MRI) is a well-established method for the diagnosis of IA. The aim of this prospective study was to evaluate the performance of a modern 0.55 T MRI in the diagnosis of IAs in comparison to digital subtraction angiography (DSA) as a standard of reference. MATERIALS AND METHODS: Seventeen patients with suspicion of single or multiple IAs underwent TOF MRA at 0.55 T MRI 1 day before DSA. Two neuroradiologists independently measured the aneurysm neck, width, and height on 0.55 T, 1.5 T, and 3 T 3D-TOF MRA source images and 2D/3D rotational angiography. The main analysis assessed the intermodality agreement between 0.55 T TOF MRA and DSA using Bland-Altman plots, a Wilcoxon test, and the intraclass correlation coefficient (ICC). In a secondary analysis, aneurysm dimensions were compared between 0.55 T TOF MRA and 1.5/3 T TOF MRA. Interreader agreement was evaluated by ICC. A third neuroradiologist blinded to patient history screened 0.55 T TOF MRA data sets of the aforementioned 17 patients and 15 additional healthy patients for the presence and location of aneurysms. RESULTS: A total of 19 aneurysms in 16 patients were identified in both 0.55 T MRA and DSA. Measurements of the 2 nonblinded readers showed no significant differences between 0.55 T TOF MRA and DSA in the overall aneurysm size (calculated as the mean from height/width/neck) ( P = 0.178), as well as in the mean width ( P = 0.778) and neck values ( P = 0.190). The mean height was significantly larger in 0.55 T TOF MRA in comparison to DSA ( P = 0.020). Intermodality (1.5/3 T TOF MRA) and interrater agreement were excellent (ICC > 0.94). Of the 32 data sets of patients with and without IA, the blinded reader detected all aneurysms correctly by using 0.55 T images. CONCLUSIONS: TOF-MRA acquired with a modern 0.55 T MRI is a reliable tool for the detection and initial assessment of IAs.
CRIS-Team Scopus Importer:2023-01-20

Diagnostic value of 3D dynamic contrast-enhanced magnetic resonance imaging in lymph node metastases of head and neck tumors: a correlation study with histology - Treutlein, Christoph; Stollberg, Adrian; Scherl, Claudia; Agaimy, Abbas; Ellmann, Stephan; Iro, Heinrich; Lell, Michael; Uder, Michael; Bäuerle, Tobias (Acta Radiologica Open, 2020)
Background: Accurate staging of cervical lymph nodes (LN) is pivotal for further clinical management of patients with head and neck cancer. Functional magnetic resonance imaging (MRI) such as three-dimensional (3D) dynamic contrast-enhanced (DCE) acquisition might improve the diagnosis of cervical LN metastases.
CRIS-Team WoS Importer:2020-09-25

Diagnostic value of a 3D-SPACE-sequence with compressed sensing technology for the knee joint - Pfeifer, Corina; Attenberger, Ulrike; Schoenberg, Stefan O.; Riffel, P.; Uder, Michael; Hinterwimmer, Stefan; Strecker, Ralph; Adamietz, Boris (Radiologe, 2020)
Backround SPACE (3D fast spin echo acquisition) sequences require long scan times for three-dimensional assessment of acute injury of the knee joint and are flawed due to geometric blurring. Their implementation into routine diagnostic imaging was not feasible until recently. Objectives By comparing conventional MRI (magnetic resonance imaging) sequences to 3D (three-dimensional) sequences, it was investigated whether the compressed sensing (CS) technique is inferior to the established 2D sequences with shorter examination times. Materials and methods A total of 109 patients (age range 18-50 years) with knee injury were examined by MRI between April 2017 and May 2018. The inter- and intraobserver concordance of two blinded readers were assessed. Consensus was achieved in case of discrepancies. Descriptive analyses of absolute and relative frequency and distribution were tested by Fisher's exact test concerning differences between CS-SPACE and standard proton density fat suppressed imaging. Results Interoberserver concordance (IC) of conventional sequences before/after consensus amounted to 58.8/68.1% (medial meniscus, MM), 68.8/88.7% (lateral meniscus, LM) 88.9/97.2% (anterior cruciate ligament, ACL), 99/100% (posterior cruciate ligament, PCL), 88.9/97.2% (collateral ligament, CL) and chondral injury (CI) 1-2: 64.2%, CI-3: 77% and CI-4: 76%. The IC of CS-SPACE amounted before/after consensus of MM to 50.4/77%, LM 68.8/88%, ACL 89.9/94.5%, PCL 97.2/99.0%, CL 92.6/96.3%. IC of CI was evaluated without consensus and amounted to 65.1% (CI 1-2), 66% (CI 3) and 81.6% (CI 4). Conclusions Injuries of ACL, PCL and CL have excellent IC between 3D and 2D sequences. Excellent IC could be found in CI grade 3 and 4 when using 2D sequences and CI grade 4 utilizing CS-SPACE. Our results indicate that CS-SPACE is useful in diagnosing acute knee injuries.
CRIS-Team WoS Importer:2021-01-15

Difference in renal parenchymal perfusion after renal denervation comparing treated vs. non-treated arteries - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Schmieder, Roland; Ott, Christian; Uder, Michael (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Mueller, Sarina K.; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Differential diagnostic ultrasound criteria of papillary and follicular carcinomas: a multivariate analysis - Cordes, M.; Kondrat, P.; Uder, Michael; Kuwert, Torsten; Sasiadek, M. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The purpose of the study was to test the hypothesis that papillary thyroid carcinomas (PTCs) and follicular thyroid carcinomas (FTCs) appear with different ultrasound characteristics.90 patients (70 females, 20 males) were included in the study in whom after thyroidectomy the diagnoses of PTCs or FTCs were established. 33 patients (25 females, 8 males) with the diagnosis of follicular adenoma were included in the study as controls (KONs). All patients had ultrasound examinations of the thyroid preoperatively. These ultrasound examinations were evaluated retrospectively with respect to the ultrasound characteristics: "size", "shape", "contour", "structure", "echogenicity" and "calcifications".In PTCs, FTCs and KONs "size" was significantly different (PTCs: MW = 12.5 mm, SD = 8. mm - FTCs: MW = 35.4 mm, SD = 19.6 mm - KONs: MW = 22.7 mm, SD = 14.5 mm; p < 0.001 for PTCs vs. FTCs, p < 0.001 for PTCs vs. KONs, p = 0.013 for FTCs vs. KONs). Differences were also found with respect to "contour" and "echogenicity" among PTCs, FTCs and KONs (p <= 0.035). The parameters "size", "contour", "echogenicity" and "calcifications" correlated for PTCs, FTCs and KONs with a correlation coefficient r = 0.57 (p < 0.05, multivariate regressionanalysis).PTCs and FTCs appear with different sonographic characteristics. Although there is some overlapping of the sonographic appearances of PTCs and FTCs, the knowledge of these differences should have some impact of the risk adapted further work up.
EVALuna2:13825

Differentiating Benign and Malignant Breast Lesions in Diffusion Kurtosis MRI: Does the Averaging Procedure Matter? - Pistel, Mona; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Dada, Anes; Weiland, Elisabeth; Niederdränk, Torsten; Uder, Michael; Janka, Rolf Matthias; Wenkel, Evelyn; Ohlmeyer, Sabine (Journal of Magnetic Resonance Imaging, 2022)
Background: Diffusion kurtosis imaging (DKI) is used to differentiate between benign and malignant breast lesions. DKI fits are performed either on voxel-by-voxel basis or using volume-averaged signal. Purpose: Investigate and compare DKI parameters' diagnostic performance using voxel-by-voxel and volume-averaged signal fit approach. Study type: Retrospective. Study population: A total of 104 patients, aged 24.1–86.4 years. Field Strength/Sequence: A 3 T Spin-echo planar diffusion-weighted sequence with b-values: 50 s/mm2, 750 s/mm2, and 1500 s/mm2. Dynamic contrast enhanced (DCE) sequence. Assessment: Lesions were manually segmented by M.P. under supervision of S.O. (2 and 5 years of experience in breast MRI). DKI fits were performed on voxel-by-voxel basis and with volume-averaged signal. Diagnostic performance of DKI parameters (Formula presented.) (kurtosis corrected diffusion coefficient) and kurtosis (Formula presented.) was compared between both approaches. Statistical Tests: Receiver operating characteristics analysis and area under the curve (AUC) values were computed. Wilcoxon rank sum and Students t-test tested DKI parameters for significant (P <0.05) difference between benign and malignant lesions. DeLong test was used to test the DKI parameter performance for significant fit approach dependency. Correlation between parameters of the two approaches was determined by Pearson correlation coefficient. Results: DKI parameters were significantly different between benign and malignant lesions for both fit approaches. Median benign vs. malignant values for voxel-by-voxel and volume-averaged approach were 2.00 vs. 1.28 ((Formula presented.) in μm2/msec), 2.03 vs. 1.26 ((Formula presented.) in μm2/msec), 0.54 vs. 0.90 ((Formula presented.)), 0.55 vs. 0.99 ((Formula presented.)). AUC for voxel-by-voxel and volume-averaged fit were 0.9494 and 0.9508 ((Formula presented.)); 0.9175 and 0.9298 ((Formula presented.)). For both, AUC did not differ significantly (P = 0.20). Correlation of values between the two approaches was very high (r = 0.99 for (Formula presented.) and r = 0.97 for (Formula presented.)). Data Conclusion: Voxel-by-voxel and volume-averaged signal fit approach are equally well suited for differentiating between benign and malignant breast lesions in DKI. Evidence Level: 3. Technical Efficacy: Stage 3.
CRIS-Team Scopus Importer:2022-03-25
Keywords: breast lesions; diffusion kurtosis fitting; diffusion magnetic resonance imaging

Differentiation of ductal carcinoma in situ versus fibrocystic changes by magnetic resonance imaging: are there pathognomonic imaging features? - Dietzel, Matthias; Kaiser, Clemens G.; Wenkel, Evelyn; Clauser, Paola; Uder, Michael; Schulz-Wendtland, Rüdiger; Baltzer, Pascal A. T. (Acta Radiologica, 2017)
Background In breast magnetic resonance imaging (MRI), the diagnosis of ductal carcinoma in situ (DCIS) remains controversial; the most challenging cause of false-positive DCIS diagnosis is fibrocystic changes (FC). Purpose To search for typical and pathognomonic patterns of DCIS and FC using a standard clinical MRI protocol. Material and Methods Consecutive patients scheduled for breast MRI (standardized protocols @ 1.5T: dynamic-T1-GRE before/after Gd-DTPA [0.1 mmol/kg body weight (BW)]; T1-TSE), with subsequent pathological sampling, were investigated. Sixteen MRI descriptors were prospectively assessed by two experienced radiologists in consensus (blinded to pathology) and explored in patients with DCIS (n = 77) or FC (n = 219). Univariate and multivariate statistics were performed to identify the accuracy of descriptors (alone, combined). Furthermore, pathognomonic descriptor-combinations with an accuracy of 100% were explored (?(2) statistics; decision trees). Results Six breast MRI descriptors significantly differentiated DCIS from FC ( Pcorrected < 0.05; odds ratio < 7.9). Pathognomonic imaging features were present in 33.8% (n = 100) of all cases allowing the identification of 42.9% of FC (n = 94). Conclusion Pathognomonic patterns of DCIS and FC were frequently observed in a standard clinical MRI protocol. Such imaging patterns could decrease the false-positive rate of breast MRI and hence might help to decrease the number of unnecessary biopsies in this clinically challenging subgroup.
EVALuna2:14614

Diffuse Encephalopathy Associated with Isolated Cerebral Langerhans Cell Histiocytosis - Rompel, Oliver; Buslei, Rolf; Hammon, Matthias; Dörr, Helmuth-Günther; Chada, Martin; Nikkhah, Guido; Uder, Michael; Trollmann, Regina (Pediatric Neurology, 2016)
Langerhans cell histiocytosis is a rare disease of the monocyte-macrophage system. Abnormalities of the hypothalamic-pituitary region are common in individuals with central nervous system involvement.This six-year-old boy developed rapidly progressive aggressive behavior, central diabetes insipidus, and repeated complex partial seizures. Magnetic resonance imaging revealed a diffuse leukoencephalopathy-like pattern and numerous infratentorial and supratentorial granulomatous nodules in the brain parenchyma along with infundibular and hypothalamic mass lesions. Stereotactic serial biopsies enabled histopathologic and immunohistochemical diagnosis of Langerhans cell histiocytosis.Similar MRI findings have rarely been described in the literature. These findings represent part of the broad neuroradiological spectrum of Langerhans cell histiocytosis of the nervous system in children.
EVALuna2:7341

Diffusion kurtosis imaging does not improve differentiation performance of breast lesions in a short clinical protocol - Palm, Theresa; Wenkel, Evelyn; Ohlmeyer, Sabine; Janka, Rolf Matthias; Uder, Michael; Weiland, Elisabeth; Bickelhaupt, Sebastian; Ladd, Mark E.; Zaitsev, Maxim; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance Imaging, 2019)
Background: Diffusion weighted magnetic resonance imaging (DWI) is known to differentiate between malignant and benign lesions via the apparent diffusion coefficient (ADC). Here, the value of diffusion kurtosis imaging (DKI) for differentiation and further characterization of benign and malignant breast lesions and their subtypes in a clinically feasible protocol is investigated. Material and methods: This study included 85 patients (with 68 malignant and 73 benign lesions) who underwent 3 T breast DWI using three b values (50, 750, 1500 s/mm2), with a total measurement time < 5 min. ADC maps were calculated from b values 50, 750 s/mm2. The diffusion kurtosis model was fitted to the diffusion weighted images, yielding in each lesion the average kurtosis-corrected diffusion coefficient DK and mean kurtosis K. Histopathology was obtained of radiologically suspicious lesions; follow-up scans were used as a standard of reference for benign appearing lesions. Receiver operating characteristic curves were used to evaluate the parameters' diagnostic performance for differentiation of lesion types and grades. The difference in diffusion parameters between subgroups was analysed statistically using the Wilcoxon rank sum test and Kruskal-Wallis test, applying a Bonferroni correction for multiple testing where necessary. Results: ADC, DK and K showed significant differences between malignant and benign lesions (p < 10−5). All parameters had similar areas under the curve (AUC) (ADC: 0.92, DK: 0.91, K: 0.89) for differentiation of malignant and benign lesions. Sensitivity was highest for ADC (ADC: 0.96, DK: 0.94, K: 0.93), as well as specificity (ADC: 0.85, DK: 0.82, K: 0.82). ADC and DK showed significant differences between tumor histologic grades (p = 6.8⋅10−4, p = 6.6 · 10−5, respectively), whereas K did not (p = 0.99). All three parameters differed significantly between subtypes of benign lesions (ADC: p < 10−5, DK: p< 10−5, K: p = 4.1·10−4), but not between subtypes of malignant lesions (ADC: p = 0.21, DK: p = 0.25, K: p = 0.08). Conclusion: DKI parameters and conventional ADC can differentiate between malignant and benign lesions. Differentiation performance was best for ADC. Different tumor grades were significantly different in ADC and DK, which may have an impact on therapy planning and monitoring. In our study, K did not add value to the diagnostic performance of DWI in a clinical setting.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Breast neoplasms; Diagnostic imaging; Diffusion kurtosis imaging; Diffusion magnetic resonance imaging; Neoplasms by histologic type

Diffusion-weighted breast imaging. Clinical implementation procedure - Wenkel, Evelyn; Uder, Michael; Janka, Rolf Matthias (Radiologe, 2014)
Diffusion-weighted imaging (DWI) of the breast provides additional contrast information in breast magnetic resonance imaging (MRI). The DWI procedure can easily be implemented in the routine breast MRI protocol with little time expenditure regarding image acquisition and evaluation. Evaluation of the DW images can be performed with or without the routine breast MRI sequences (T2w and T1w with contrast material) but evaluation in combination with the routine program is highly recommended. Objective analysis of the tissue diffusion can be achieved by calculating the apparent diffusion coefficient (ADC) value with the scanner software. The choice of the DW sequence, evaluation and determination of the ADC threshold to differentiate between benign and malignant lesions should be scanner adapted. The use of DW imaging qualifies for routine use regarding the differentiation between malignant and benign breast lesions. Non-mass-like lesions and monitoring neoadjuvant chemotherapy can also be evaluated with DW sequences. The benefit of the additional information from DW-MR mammography to characterize non-mass-like lesions and in the course of neoadjuvant chemotherapy remains unclear to date.
EVALuna2:14377

Diffusion-weighted MR imaging of benign and malignant breast lesions before and after contrast enhancement - Janka, Rolf Matthias; Hammon, Matthias; Geppert, C.; Nothhelfer, A.; Uder, Michael; Wenkel, Evelyn (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Many publications describe the use of diffusion-weighted imaging (DWI) in breast MRI. This article addresses the question of when to apply the DWI sequence in the course of the scan protocol. The effect of T1-shortening contrast media (CM) on the ADC values of breast lesions is investigated.Data were acquired on a 1.5 T scanner. 60 patients with 79 lesions (20 benign, 59 malignant) were included. The DWI sequence (4 mm slice thickness, b-values: 50, 400, 800) was applied before and after CM administration. Before calculating the ADC map, the b50, b400 and b800 series were analyzed concerning lesion displacement. ADC values before and after CM application were compared.The mean lesion size was 1.5 ± 0.8 cm. On the basis of the b50 and b400 measurements, the mean ADC value of benign lesions was 1.89 ± 0.30 × 10-3 mm2/s before and 1.85 ± 0.28 ×10-3 mm2/s after CM administration. The consecutive values for two pure mucinous carcinomas were 1.88 × 10-3 mm2/s and 1.81 × 103 mm2/s and for the remaining malignant lesions 1.00 ± 0.18 × 10-3 mm2/s and 0.88 ± 0.21 × 10-3 mm2. On the basis of the b50, b400 and b800 measurements, the mean ADC value of benign lesions was 1.99 ± 0.37 × 10-3 mm2/s before and 1.97 ± 0.30 × 10-3 mm2/s after CM application, whereas the mean ADC value of the malignant lesions was 0.90 ± 0.14 × 10-3 mm2/s before and 0.80 ± 0.14 × 10-3 mm2/s after CM application. While there was no significant change for benign lesions, the ADC value decrease in post-contrast malignant lesions was highly significant.DWI after CM is possible and even leads to slightly better lesion discrimination between benign and malignant. However, further studies need to be performed to verify this. Citation Format: o?Janka R, Hammon M, Geppert C et al. Diffusion-Weighted MR Imaging of Benign and Malignant Breast Lesions Before and After Contrast Enhancement. Fortschr Röntgenstr 2014; 186: 130 - 135.
EVALuna2:14329

Digitized and structured informed patient consent before contrast-enhanced computed tomography: feasibility and benefits in clinical routine - Kopp, Markus; Roth, Jessica; Geißler, Frederik; Daniel, Sascha; Rüttinger, Theresa; Treutlein, Christoph; Balbach, Eva; Heiß, Rafael; Wetzl, Matthias; El Amrani, Nouhayla; Cavallaro, Alexander Josef; Uder, Michael; et al. (Insights into Imaging, 2022)
Background: To evaluate the feasibility and benefits of digitized informed patient consent (D-IPC) for contrast-enhanced CT and compare digitized documentation with paper-based, conventional patient records (C-PR). Methods: We offered D-IPC to 2016 patients scheduled for a CT. We assessed patient history (e.g., CT examinations, malignant or cardiovascular diseases) and contraindications (red flags) for a CT (e.g., thyroid hyperfunction, allergies) using a tablet device. We evaluated the success rate of D-IPC and compared patient age between the subgroups of patients who were able or unable to complete D-IPC. We analyzed the prevalence of marked questions and red flags (RF). RF were compared with the documentation from C-PR. We estimated greenhouse gas (GHG) emissions for paperless workflow and provide a cost–benefit analysis. Results: Overall, 84.4% of patients completed D-IPC. They were younger (median 61 years) than unsuccessful patients (65 years; p < 0.001). Patients who marked questions (21.7%) were older than patients without inquiries (median 63.9 vs 59.5 years; p < 0.001). The most prevalent RF was thyroid disease (23.8%). RF were considered critical for contrast-agent injection in 13.7%, requiring personalized preparation. The detection rate for RF documented with D-IPC was higher than for C-PR (n = 385 vs. 43). GHG emissions for tablet production are 80–90 times higher than for paper production. The estimated costs were slightly higher for D-IPC (+ 8.7%). Conclusion: D-IPC is feasible, but patient age is a relevant factor. Marked questions and RF help personalize IPC. The availability of patient history by D-IPC was superior compared to C-PR.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Electronic medical records; Greenhouse gases; Helical computed tomography; Informed consent document; Personalized medicine

Direct imaging of white matter ultrashort T2∗ components at 7 Tesla - Müller, Max; Egger, Nico; Sommer, Stefan; Wilferth, Tobias; Meixner, Christian; Laun, Frederik Bernd; Mennecke, Angelika; Schmidt, Manuel; Huhn, Konstantin; Rothhammer, Veit; Uder, Michael; Dörfler, Arnd; et al. (Magnetic Resonance Imaging, 2022)
Purpose: To demonstrate direct imaging of the white matter ultrashort T2∗ components at 7 Tesla using inversion recovery (IR)-enhanced ultrashort echo time (UTE) MRI. To investigate its characteristics, potentials and limitations, and to establish a clinical protocol. Material and methods: The IR UTE technique suppresses long T2∗ signals within white matter by using adiabatic inversion in combination with dual-echo difference imaging. Artifacts arising at 7 T from long T2∗ scalp fat components were reduced by frequency shifting the IR pulse such that those frequencies were inverted likewise. For 8 healthy volunteers, the T2∗ relaxation times of white matter were then quantified. In 20 healthy volunteers, the UTE difference and fraction contrast were evaluated. Finally, in 6 patients with multiple sclerosis (MS), the performance of the technique was assessed. Results: A frequency shift of −1.2 ppm of the IR pulse (i.e. towards the fat frequency) provided a good suppression of artifacts. With this, an ultrashort compartment of (68 ± 6) % with a T2∗ time of (147 ± 58) μs was quantified with a chemical shift of (−3.6 ± 0.5) ppm from water. Within healthy volunteers' white matter, a stable ultrashort T2∗ fraction contrast was calculated. For the MS patients, a significant fraction reduction in the identified lesions as well as in the normal-appearing white matter was observed. Conclusions: The quantification results indicate that the observed ultrashort components arise primarily from myelin tissue. Direct IR UTE imaging of the white matter ultrashort T2∗ components is thus feasible at 7 T with high quantitative inter-subject repeatability and good detection of signal loss in MS.
Created from Fastlane, Scopus look-up
Keywords: 7 Tesla; Multiple sclerosis; Myelin; Relaxometry; Ultrashort echo time (UTE); White matter

Dissimilar DNA Damage to Blood Lymphocytes After 177Lu-Labeled DOTATOC or Prostate-Specific Membrane Antigen Therapy - Ritt, Philipp; Jobic, Camille; Beck, Michael; Schmidkonz, Christian; Kuwert, Torsten; Uder, Michael; Brand, Michael (Journal of Nuclear Medicine, 2021)
DNA double-strand breaks in cells of radionuclide-treated patients are quantifiable by immunofluorescence microscopy, using phosphorylation of histone-variant H2AX (γ-H2AX) to mark radiation-induced foci (RIFs). Using this method, we compared excess RIFs side by side in recipients of 177Lu-DOTATOC or 177Lu-prostate specific membrane antigen-617 (PSMA) radioligands. We also examined relations between blood dose and dose rate, RIFs, and platelet counts. Methods: Venous blood samples were obtained from 48 patients subjected to 177Lu-labeled radioligand therapy (177Lu-DOTATOC, 26; 177Lu-PSMA, 22) to quantify blood lymphocyte RIFs and blood activity concentrations at various time points, including baseline (before injection) and postinjection readings (5 min, 30 min, 4 h, 24 h, 48 h, and 72 h). Absorbed doses and dose rates to blood were derived from sequentially assessed blood activity concentrations and γ-camera imaging. Platelet levels in routine blood tests were monitored for 3 d after injection to assess responses. Results: RIF counts averaged 0.25 ± 0.15 at baseline. Postinjection RIF counts were significantly higher than baseline values, peaking at 5 min (average, 3.93 ± 2.51 min) and declining thereafter. Compared with RIF counts of 177Lu-DOTATOC, those of 177Lu-PSMA were significantly higher at 5 min after injection and significantly lower at 72 h after injection. These differences could not be fully explained by blood doses and dose rates, which were significantly higher for 177Lu-PSMA than for 177Lu-DOTATOC treatment at every time point. RIF counts overall correlated with dose rates across all time points (Pearson r = 0.78; P < 0.01) and with absorbed dose until 4 h after injection only (Pearson r = 0.42; P < 0.01). Declines in platelet concentration correlated significantly with RIFs at 72 h after injection (Pearson r = -0.34; P < 0.05). Conclusion: Although values generated by the currently used blood dosimetry model correlated with RIF counts, the difference observed in 177Lu-DOTATOC and 177Lu-PSMA treatment groups was unexplained. Significantly more RIFs were found in 177Lu-DOTATOC recipients by comparison, despite lower dose rates and blood doses, exposing a potential limitation.
CRIS-Team Scopus Importer:2021-03-19
Keywords: 177Lu-labeled therapy; DOTATOC; PSMA; radiation-induced foci; γ-H2AX

Does higher field strength translate into better diagnostic accuracy? A prospective comparison of breast MRI at 3 and 1.5 Tesla - Dietzel, Matthias; Wenkel, Evelyn; Hammon, Matthias; Clauser, Paola; Uder, Michael; Schulz-Wendtland, Rüdiger; Baltzer, Pascal A. T. (European Journal of Radiology, 2019)
Objective: We performed a prospective monocentric study to inter-individually compare the diagnostic accuracy of breast MRI at 1.5 T and 3 T.
CRIS-Team WoS Importer:2019-05-03

Does renal artery supply indicate treatment success of renal denervation? - Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2013)
Purpose: Renal denervation (RDN) emerged as an innovative interventional antihypertensive therapy. With the exception of pretreatment blood pressure (BP) level, no other clear predictor for treatment efficacy is yet known. We analyzed whether the presence of multiple renal arteries has an impact on BP reduction after RDN. Methods: Fifty-three patients with treatment-resistant hypertension (office BP ≥ 140/90 mmHg and 24-h ambulatory BP monitoring (≥130/80 mmHg) underwent bilateral catheter-based RDN. Patients were stratified into one-vessel (OV) (both sides) and at least multivessel (MV) supply at one side. Both groups were treated on one vessel at each side; in case of multiple arteries, only the dominant artery was treated on each side. Results: Baseline clinical characteristics (including BP, age, and estimated glomerular filtration rate) did not differ between patients with OV (n = 32) and MV (n = 21). Office BP was significantly reduced in both groups at 3 months (systolic: OV -15 ± 23 vs. MV -16 ± 20 mmHg; diastolic: OV -10 ± 12 vs. MV -8 ± 11 mmHg, both p = NS) as well as 6 months (systolic: OV -18 ± 18 vs. MV -17 ± 22 mmHg; diastolic: OV -10 ± 10 vs. -10 ± 12 mmHg, both p = NS) after RDN. There was no difference in responder rate (rate of patients with office systolic BP reduction of at least 10 mmHg after 6 months) between the groups. Conclusion: In patients with multiple renal arteries, RDN of one renal artery - namely, the dominant one - is sufficient to induce BP reduction in treatment-resistant hypertension. © 2013 Springer Science+Business Media New York and the Cardiovascular and Interventional Radiological Society of Europe (CIRSE).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Ablation; Artery; Endovascular treatment; Hypertension; Kidney/renal; Radiofrequency ablation

Dose reduction in computed tomography of the chest: image quality of iterative reconstructions at a 50% radiation dose compared to filtered back projection at a 100% radiation dose - May, Matthias; Eller, A.; Stahl, Christian; Wuest, W.; Scharf, M.; Hammon, Matthias; Dankerl, P.; Schlechtweg, Philipp; Allmendinger, T.; Sedlmair, M.; Schmidt, B.; Uder, Michael; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
The aim of this study was to evaluate the potential of iterative reconstruction (IR) in chest computed tomography (CT) to reduce radiation exposure. The qualitative and quantitative image quality of standard reconstructions with filtered back projection (FBP) and half dose (HD) chest CT data reconstructed with FBP and IR was assessed.52 consecutive patients underwent contrast-enhanced chest CT on a dual-source CT system at 120 kV and automatic exposure control. The tube current was equally split on both tube detector systems. For the HD datasets, only data from one tube detector system was utilized. Thus, FD and HD data was available for each patient with a single scan. Three datasets were reconstructed from the raw data: standard full dose (FD) images applying FBP which served as a reference, HD images applying FBP and IR. Objective image quality analysis was performed by measuring the image noise in tissue and air. The subjective image quality was evaluated by 2 radiologists according to European guidelines. Additional assessment of artifacts, lesion conspicuity and edge sharpness was performed.Image noise did not differ significantly between HD-IR and FD-FBP (p = 0.254) but increased substantially in HD-FBP (p < 0.001). No statistically significant differences were found for the reproduction of anatomical and pathological structures between HD-IR and FD-FBP, subsegmental bronchi and bronchioli. The image quality of HD-FBP was rated inferior because of increased noise.A 50 % dose reduction in contrast-enhanced chest CT is feasible without a loss of diagnostic confidence if IR is used for image data reconstruction. Iterative reconstruction is another powerful tool to reduce radiation exposure and can be combined with other dose-saving techniques.o?Iterative reconstructions allow for image noise and artifact reduction.o?Comparable image data can thus be attained even at 50 % radiation dose.o?Diagnostic confidence remains unaffected.
EVALuna2:14376

Dose reduction of the female breast in chest CT - Seidenfuß, Anna; Mayr, Andreas; Schmid, Matthias; Uder, Michael; Lell, Michael (American Journal of Roentgenology, 2014)
Organ-based tube current modulation has been shown to significantly reduce the radiation dose to the female breast in phantom studies. We sought to assess the proportions of female breast and glandular tissues that are within the range of organ-based tube current modulation in different age groups and whether these proportions could be optimized by clothing. The secondary objective of our study was to determine whether metal parts of brassieres cause artifacts that impair the diagnostic value.Five hundred seventy-eight female patients undergoing chest CT were included in this study. Two hundred nine patients were prospectively examined wearing a brassiere (group A), and the control patients (group B; n = 369) were scanned according to our previous standard without wearing a brassiere during CT. The two groups were subdivided according to cup size (A-E). For CT data acquisition, an angle-dependent tube current modulation, which reduces the tube current for anterior tube position to minimize direct exposure to anteriorly located organs, was used. The proportion of breast tissue and glandular tissue located within and outside the region of tube current reduction was assessed.The results showed that 60.4% of total breast tissue and 67.1% of glandular tissue was inside the region of tube current reduction in group B; the proportions were significantly improved, to an average of 91.3% and 96%, respectively, in group A. Diagnostically relevant artifacts were introduced in none of the patients. Patients' age correlated with this effect, with higher rates of improvement in the older patient group. Angle-dependent tube current modulation was most effective in patients with cup size A while wearing a brassiere. In this group, 97.5% of breast tissue and 98.1% of glandular tissue was inside the region of tube current reduction. Women with a cup size of E had the largest effect of wearing a brassiere, increasing the rate of breast tissue that was affected by angle-dependent tube current modulation from 30.0% to 83.3% and that of glandular tissue from 31.8% to 90.0%.We show that wearing a brassiere increases the percentage of breast tissue within the region of reduced tube current and, therefore, improves the performance of angle-dependent tube current modulation technique.
EVALuna2:5472

Dose reduction potential of iterative reconstruction algorithms in neck CTA-a simulation study - Ellmann, Stephan; Kammerer, Ferdinand; Allmendinger, Thomas; Brand, Michael; Janka, Rolf Matthias; Hammon, Matthias; Lell, Michael M.; Uder, Michael; Kramer, Manuel (Dentomaxillofacial Radiology, 2016)
This study aimed to determine the degree of radiation dose reduction in neck CT angiography (CTA) achievable with Sinogram-affirmed iterative reconstruction (SAFIRE) algorithms.10 consecutive patients scheduled for neck CTA were included in this study. CTA images of the external carotid arteries either were reconstructed with filtered back projection (FBP) at full radiation dose level or underwent simulated dose reduction by proprietary reconstruction software. The dose-reduced images were reconstructed using either SAFIRE 3 or SAFIRE 5 and compared with full-dose FBP images in terms of vessel definition. 5 observers performed a total of 3000 pairwise comparisons.SAFIRE allowed substantial radiation dose reductions in neck CTA while maintaining vessel definition. The possible levels of radiation dose reduction ranged from approximately 34 to approximately 90% and depended on the SAFIRE algorithm strength and the size of the vessel of interest. In general, larger vessels permitted higher degrees of radiation dose reduction, especially with higher SAFIRE strength levels. With small vessels, the superiority of SAFIRE 5 over SAFIRE 3 was lost.Neck CTA can be performed with substantially less radiation dose when SAFIRE is applied. The exact degree of radiation dose reduction should be adapted to the clinical question, in particular to the smallest vessel needing excellent definition.
EVALuna2:14595

Double quantum filtered 23 Na MRI with magic angle excitation of human skeletal muscle in the presence of B0 and B1 inhomogeneities - Gast, Lena; Gerhalter, Teresa; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (NMR in Biomedicine, 2018)
Double quantum filtered 23 Na MRI with magic angle excitation (DQF-MA) can be used to selectively detect sodium ions located within anisotropic structures such as muscle fibers. It might therefore be a promising tool to analyze the microscopic environment of sodium ions, for example in the context of osmotically neutral sodium retention. However, DQF-MA imaging is challenging due to various signal dependences, on both measurement parameters and external influences. The aim of this work was to examine how B0 in combination with B1 inhomogeneities alter the DQF-MA signal intensity. We showed that, in the presence of B0 inhomogeneities, flip angle schemes with only one 54.7° pulse can be favorable compared with the classical 90°-54.7°-54.7° scheme. DQF-MA images of the human lower leg were acquired at B0 = 3 T with a nominal spatial resolution of 12 × 12 × 36 mm3 within an acquisition time of TAcq < 10 min, and compared with spin density weighted (DW), as well as triple quantum filtration (TQF) 23 Na images. We found mean normalized signal-to-noise ratios of TQF/DW = 13.7 ± 2.3% (tibialis anterior), 11.9 ± 2.3% (soleus) and 11.4 ± 2.2% (gastrocnemius medialis), as well as DQF-MA/DW = 4.7 ± 1.1% (tibialis anterior), 3.3 ± 0.73% (soleus) and 3.4 ± 0.6% (gastrocnemius medialis). These ratios might serve as additional measures in future clinical studies of sodium retention within human skeletal muscle. However, the influence of B0 and B1 inhomogeneities should be considered when interpreting DQF-MA images.
EVALuna2:36106

Dual-Energy Computed Tomography Angiography of the Head and Neck With Single-Source Computed Tomography: A New Technical (Split Filter) Approach for Bone Removal - Kämmerer, Nadine; Brand, Michael; Hammon, Matthias; May, Matthias; Wuest, Wolfgang; Krauss, Bernhard; Uder, Michael; Lell, Michael (Investigative Radiology, 2016)
Dual-energy computed tomographic angiography (DE-CTA) has been demonstrated to improve the visualization of the head and neck vessels. The aim of this study was to test the potential of split-filter single-source dual-energy CT to automatically remove bone from the final CTA data set.Dual-energy CTA was performed in 50 consecutive patients to evaluate the supra-aortic arteries, either to grade carotid artery stenosis or to rule out traumatic dissections. Dual-energy CTA was performed on a 128-slice single-source CT system equipped with a special filter array to separate the 120-kV spectrum into a high- and a low-energy spectrum for DE-based automated bone removal. Image quality of fully automated bone suppression and subsequent manual optimization was evaluated by 2 radiologists on maximum intensity projections using a 4-grade scoring system. The effect of image reconstruction with an iterative metal artifact reduction algorithm on DE postprocessing was tested using a 3-grade scoring system, and the time demand for each postprocessing step was measured.Two patients were excluded due to insufficient arterial contrast enhancement; in the remaining 48 patients, automated bone removal could be performed successfully. The addition of iterative metal artifact reduction algorithm improved image quality in 58.3% of the cases. After manual optimization, DE-CTA image quality was rated excellent in 7, good in 29, and moderate in 10 patients. Interobserver agreement was high (? = 0.85). Stenosis grading was not influenced using DE-CTA with bone removal as compared with the original CTA. The time demand for DE image reconstruction was significantly higher than for single-energy reconstruction (42.1 vs 20.9 seconds).Our results suggest that bone removal in DE-CTA of the head and neck vessels with a single-source CT is feasible and can be performed within acceptable time and moderate user interaction.
EVALuna2:14603

Dual-energy lung perfusion in portal venous phase CT—A comparison with the pulmonary arterial phase - Praël, Isabelle; Wuest, Wolfgang; Heiß, Rafael; Wiesmüller, Marco; Kopp, Markus; Uder, Michael; May, Matthias (Diagnostics, 2021)
Pulmonary arterial dual-energy (aDE) CT is an established technique for evaluating pulmonary perfusion blood volume (PBV). As DECT protocols are increasingly used for thoracoabdominal CT, this study assessed image quality and clinical findings in portal–venous phase dual-energy (vDE) CT and compared it to aDE. In 95 patients, vDE-CT was performed using a dual-source scanner (70/Sn150 kV, 560/140 ref.mAs). Pulmonary triggered aDE-CT served as reference (n = 94). PBV was reconstructed using a dedicated algorithm. Mean relative attenuation was measured in the pulmonary trunk, aorta, and segmented lung parenchyma. A distribution ratio (DL) between vessels and parenchyma was calculated to assess the iodine uptake of the lung parenchyma. Subjective overall diagnostic image quality was assessed for PBV images on a five-point Likert scale. Image artifacts were classified into five groups based on scale rating and compared between vDE and aDE. Pathological findings were correlated with the anatomical image datasets. Mean relative attenuation of the lung parenchyma was comparable in both groups (vDE: 23 ± 6 HU and aDE: 22 ± 7 HU), but significantly lower in the vessels of vDE. Therefore, iodine uptake of the lung parenchyma was significantly higher in vDE (DL: 10% vs. 8%, p < 0.01). The subjective overall image quality of the PBV images was comparable (p = 0.5). Rotation and streak artifacts were found in most of the patients (>86%, both p > 0.6). Dual-source artifacts were found in only a few patients in both groups (vDE 5%, aDE 7%, p = 0.5). Recess and subpleural artifacts were increased in vDE (vDE 53/27%, aDE 24/7%, both p < 0.001). Pathological findings were found in 19% of the vDE patients and 59% of the aDE patients. Comparable objective and subjective image quality of lung perfusion can be obtained in vDE and aDE. Iodine uptake of the lung parenchyma is increased in vDE compared to aDE, suggesting an interstitial pooling effect. Knowledge of the different appearances of artifacts will aid in the interpretation of the images. Additional clinical information about the lung parenchyma can be provided by PBV evaluation in vDE.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Dual-energy computed tomography; Lung perfusion; Portal venous

Dual-source computed tomography of the lung with spectral shaping and advanced iterative reconstruction: potential for maximum radiation dose reduction - Wetzl, Matthias; May, Matthias; Weinmann, Daniel; Hammon, Matthias; Treutlein, Christoph; Zeilinger, Martin; Kiefer, Alexander; Trollmann, Regina; Wölfle, Joachim; Uder, Michael; Rompel, Oliver (Pediatric Radiology, 2020)
Background: Radiation dose at CT should be as low as possible without compromising diagnostic quality. Objective: To assess the potential for maximum dose reduction of pediatric lung dual-source CT with spectral shaping and advanced iterative reconstruction (ADMIRE). Materials and methods: We retrospectively analyzed dual-source CT acquisitions in a full-dose group (FD: 100 kV, 64 reference mAs) and in three groups with spectral shaping and differing reference mAs values (Sn: 100 kV, 96/64/32 reference mAs), each group consisting of 16 patients (age mean 11.5 years, standard deviation 4.8 years, median 12.8 years, range 1.3–18 years). Advanced iterative reconstruction of images was performed with different strengths (FD: ADMIRE Level 2; Sn: ADMIRE Levels 2, 3 and 4). We analyzed dose parameters and measured noise. Diagnostic confidence and detectability of lung lesions as well as anatomical structures were assessed using a Likert scale (from 1 [unacceptable] to 4 [fully acceptable]). Results: Compared to full dose, effective dose was reduced to 16.7% in the Sn 96 group, 11.1% in Sn64, and 5.5% in Sn32 (P<0.001). Noise values of Sn64ADM4 did not statistically differ from those in FDADM2 (45.7 vs. 38.9 Hounsfield units [HU]; P=0.132), whereas noise was significantly higher in Sn32ADM4 compared to Sn64ADM4 (61.5 HU; P<0.001). A Likert score >3 was reached in Sn64ADM4 regarding diagnostic confidence (3.2) and detectability of lung lesions (3.3). For detectability of most anatomical structures, no significant differences were found between FDAM2 and Sn64ADM4 (P≥0.05). Conclusion: In pediatric lung dual-source CT, spectral shaping together with ADMIRE 4 enable radiation dose reduction to about 10% of a full-dose protocol while maintaining an acceptable diagnostic quality.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Adolescents; Advanced iterative reconstruction; Children; Dual-source computed tomography; Lung; Radiation dose reduction; Spectral shaping; Tin prefiltration

Dynamic CT angiography for therapy evaluation after transarterial chemoembolization of hepatocellular carcinoma - Saake, Marc; Seuß, Hannes; Hammon, Matthias; Ellmann, Stephan; May, Matthias; Uder, Michael; Schmid, Axel (Acta Radiologica, 2019)
Background: Liver dynamic computed tomography (CT) is an established method for pre- and post-interventional evaluation of hepatocellular carcinoma. To date only the liver parenchyma and perfusion information of dynamic CT has been evaluated widely. Purpose: To evaluate the vascular information contained in dynamic CT datasets. Material and Methods: Dynamic CT performed one day after transarterial chemoembolization (60 mL of contrast medium, 6 mL/s, 40 s scan duration) were retrospectively evaluated. Conventional slice and angiographic maximum-intensity-projection reconstructions were calculated on a multi-modality post-processing platform. Datasets were evaluated for viable tumor, anatomy of the vasculature, and potential tumor-feeding vessels. The results were compared to digital subtraction angiography images. Results: In total, 94 treated hepatocellular carcinoma nodules were evaluated (62 dynamic CT scans, 46 patients [34 men; mean age = 69 years]). Forty-six partially viable tumors were diagnosed after transarterial chemoembolization. In all of these, tumor-feeding vessels were found in dynamic CT. Seventeen suspected extra-hepatic tumor feeders were reported, of which 14 had not been found during previous transarterial chemoembolization. Conclusion: Dynamic CT is useful in post-interventional imaging of hepatocellular carcinoma after transarterial chemoembolization due to its ability to detect residual viable tumor parts and to show previously unknown intra- and extra-hepatic tumor-feeding vessels.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Abdomen; chemoembolization; computed tomography angiography; interventional; liver

Dynamic study of the finger interphalangeal joint volar plate—motion analysis with magnetic resonance cinematography and histologic comparison - Lutter, Christoph; Kürten, Stefanie; Geppert, Carol-Immanuel; Mittelmeier, Wolfram; Klinder, Annett; Söder, Stephan; Roemer, Frank; Uder, Michael; Janka, Rolf Matthias; Bayer, Thomas (Skeletal Radiology, 2023)
Objective: We aimed to further improve knowledge about volar plate (VP) motion of the finger proximal interphalangeal joint (PIP), by analyzing the dynamic VP shape during a full range of finger flexion using magnetic resonance cinematography of the fingers (MRCF), and to compare the results with anatomical cross sections from cadaver specimens. Materials and methods: The dynamic sagittal VP shape was visualized with MRCF in a total number of 23 healthy volunteers. The length, angle, and thickness as well as the contact length of the VP to the PIP joint base were measured. Statistical analysis included t-test or rank-sum testing. Anatomical cross sections with differing degrees of PIP joint flexion were obtained from 12 cadaver specimens (fingers) for comparison. Results: Significant positive correlations between PIP joint flexion angle and VP area, length, depth and the VP contact length were found. This matched histologically to fiber rearrangements especially within the loose third VP layer. Conclusion: Our study analyzed the full range of motion dynamic VP shape of the PIP joint using MRCF. This contributes to a more precise understanding of the complex interaction of the VP with the PIP joint and may facilitate evaluation of clinical cases such as VP avulsion or pulley rupture.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Dislocation; Injury; Microsurgery; MRI; Ultrasound

Early functional and morphological changes of calf muscles in delayed onset muscle soreness (DOMS) assessed with 7T MRI - Heiß, Rafael; Höger, Svenja; Uder, Michael; Hotfiel, Thilo; Hanspach, Jannis; Laun, Frederik Bernd; Nagel, Armin Michael; Roemer, Frank (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Background: To assess morphological and functional alterations of the skeletal muscle in exercise-induced delayed onset muscle soreness (DOMS) using 7 Tesla (T) magnetic resonance imaging (MRI). Methods: DOMS was induced in 16 volunteers performing an eccentric exercise protocol of the calf muscles of one randomized leg. 7 T MRI including T1w- (0.18×0.18×1mm3), T2w-images (0.2×0.2×2mm3), T2-maps (0.5×0.5×5mm3), and susceptibility weighted imaging (SWI, 0.7×0.7×0.7 mm3) were acquired at baseline, directly (t1) and 60 hours (t2) after the exercise. T2 signal intensity (SI), T2 values [ms], T1 SI and SWI were assessed in the medial (MG) and lateral gastrocnemius muscle (LG) and in the soleus muscle (SM). In addition, the serum creatine kinase (CK) activity, range of motion (ROM) of the ankle, calf circumference, and muscle soreness were assessed at each time point. Results: Directly after exercise (t1), T2 SI (p=0.04) and T2 values (p=0.03) increased significantly in the LG. No changes of SI and T2 values for MG and SM were present at t1. At t2, T2 SI and T2 values of LG (p=0.001, p=0.02) and MG (p=0.04, p=0.03) increased significantly compared to baseline. T1 SI did not change in any muscle at any time point. In SWI, no signs of intramuscular signal drop could be detected. Clinical parameters confirmed the induction of DOMS, with a significant increase of CK (p=0.03), muscle soreness (p<0.001), calf circumference (p=0.001), and respective a decrease of ROM (p=0.04). Conclusions: 7 T MRI has the potential to visualize microstructural muscle damage immediately after an exercise that induces DOMS. No changes in susceptibility which could, for example, reflect micro-hemorrhage, could be detected with SWI immediately after exercise or in DOMS. Ultra-high field MRI may potentially be used in sports medicine to monitor intramuscular structural changes, allowing for modification of training intensity or to implement appropriate therapeutic strategies.
CRIS-Team Scopus Importer:2023-12-01
Keywords: DOMS; Magnetic resonance imaging; Multiparametric magnetic resonance imaging; Muscle injury

Echo time dependence of biexponential and triexponential intravoxel incoherent motion parameters in the liver - Führes, Tobit; Riexinger, Andreas; Loh, Martin; Martin, Jan; Wetscherek, Andreas; Kuder, Tristan Anselm; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2021)
Purpose Intravoxel incoherent motion (IVIM) studies are performed with different acquisition protocols. Comparing them requires knowledge of echo time (TE) dependencies. The TE-dependence of the biexponential perfusion fraction f is well-documented, unlike that of its triexponential counterparts f(1) and f(2) and the biexponential and triexponential pseudodiffusion coefficients D*, D1*, and D2*. The purpose was to investigate the TE-dependence of these parameters and to check whether the triexponential pseudodiffusion compartments are associated with arterial and venous blood. Methods Fifteen healthy volunteers (19-58 y; mean: 24.7 y) underwent diffusion-weighted imaging of the abdomen with 24 b-values (0.2-800 s/mm(2)) at TEs of 45, 60, 75, and 90 ms. Regions of interest (ROIs) were manually drawn in the liver. One set of bi- and triexponential IVIM parameters per volunteer and TE was determined. The TE-dependence was assessed with the Kruskal-Wallis test. Results TE-dependence was observed for f (P < .001), f(1) (P = .001), and f(2) (P < .001). Their median values at the four measured TEs were: f: 0.198/0.240/0.274/0.359, f(1): 0.113/0.139/0.146/0.205, f(2): 0.115/0.155/0.182/0.194. D, D*, D1*, and D2* showed no significant TE-dependence. Their values were: diffusion coefficient D (10(-4) mm(2)/s): 9.45/9.63/9.75/9.41, biexponential D* (10(-2) mm(2)/s): 5.26/5.52/6.13/5.82, triexponential D1* (10(-2) mm(2)/s): 1.73/2.91/2.25/2.51, triexponential D2* (mm(2)/s): 0.478/1.385/0.616/0.846. Conclusion f(1) and f(2) show similar TE-dependence as f, ie, increase with rising TE; an effect that must be accounted for when comparing different studies. The diffusion and pseudodiffusion coefficients might be compared without TE correction. Because of the similar TE-dependence of f(1) and f(2), the triexponential pseudodiffusion compartments are most probably not associated to venous and arterial blood.
CRIS-Team WoS Importer:2021-09-10

EFFECT OF AGEING ON FAT INFILTRATION OF THIGH AND PARASPINAL MUSCLES IN MEN - Engelke, Klaus; Ghasemikaram, Mansour; Chaurdy, O.; Uder, Michael; Nagel, Armin Michael; Jacob, F.; Kemmler, Wolfgang (AGING CLINICAL AND EXPERIMENTAL RESEARCH, 2022)
CRIS-Team WoS Importer:2022-10-14

Effect of compression garments on muscle perfusion in delayed-onset muscle soreness: A quantitative analysis using intravoxel incoherent motion MR perfusion imaging - Riexinger, Andreas; Laun, Frederik Bernd; Hoeger, Svenja Alina; Wiesmüller, Marco; Uder, Michael; Hensel, Bernhard; Forst, Raimund; Hotfiel, Thilo; Heiß, Rafael (NMR in Biomedicine, 2021)
The aim of this prospective cohort study was to evaluate the effect of compression garments under resting conditions and after the induction of delayed-onset muscle soreness (DOMS) by MR perfusion imaging using intravoxel incoherent motion (IVIM). Magnetic resonance imaging of both lower legs of 16 volunteers was performed before and after standardized eccentric exercises that induced DOMS. A compression garment (21–22 mmHg) was worn during and for 6 h after exercise on one randomly selected leg. IVIM MR imaging, represented as total muscle perfusion D*f, perfusion fraction f and tissue diffusivity D, were compared between baseline and directly, 30 min, 6 h and 48 h after exhausting exercise with and without compression. Creatine kinase levels and T2-weighted images were acquired at baseline and after 48 h. DOMS was induced in the medial head of the gastrocnemius muscle (MGM) in all volunteers. Compression garments did not show any significant effect on IVIM perfusion parameters at any time point in the MGM or the tibialis anterior muscle (p > 0.05). Microvascular perfusion in the MGM increased significantly in both the compressed and noncompressed leg between baseline measurements and those taken directly after and 30 min after the exercise: the relative median f increased by 31.5% and 24.7% in the compressed and noncompressed leg, respectively, directly after the exercise compared with the baseline value. No significant change in tissue perfusion occurred 48 h after the induction of DOMS compared with baseline. It was concluded that compression garments (21–22 mmHg) do not alter microvascular muscle perfusion at rest, nor do they have any significant effect during the regeneration phase of DOMS. In DOMS, only a short-term effect of increased muscle perfusion (30 min after exercise) was observed, with normalization occurring during regeneration after 6–48 h. The normalization of perfusion independently of compression after 6 h may have implications for diagnostic and therapeutic strategies and for the better understanding of pathophysiological pathways in DOMS.
CRIS-Team Scopus Importer:2021-03-05
Keywords: calf; exercise; intravoxel incoherent motion; magnetic resonance imaging; muscle injury

Effect of Compression Garments on the Development of Delayed-Onset Muscle Soreness: A Multimodal Approach Using Contrast-Enhanced Ultrasound and Acoustic Radiation Force Impulse Elastography - Heiß, Rafael; Kellermann, Marion; Swoboda, Bernd; Grim, Casper; Lutter, Christoph; May, Matthias; Wüst, Wolfgang; Uder, Michael; Nagel, Armin Michael; Hotfiel, Thilo (Journal of Orthopaedic & Sports Physical Therapy, 2018)
BACKGROUND: Delayed-onset muscle soreness (DOMS) is one of the most common reasons for impaired muscle performance in sports. However, little consensus exists regarding which treatments may be most effective, and the underlying mechanisms are poorly understood. OBJECTIVES: To investigate the influence of compression garments on the development of DOMS, focusing on changes in muscle perfusion and muscle stiffness. METHODS: In this controlled laboratory study with repeated measures, muscle perfusion and stiffness, calf circumference, muscle soreness, passive ankle dorsiflexion, and creatine kinase levels were assessed in participants before (baseline) a DOMS-inducing eccentric calf exercise intervention and 60 hours later (follow-up). After DOMS induction, a sports compression garment (18-21 mmHg) was worn on 1 randomly selected calf until follow-up, while the contralateral calf served as an internal control. Muscle perfusion was assessed using contrast-enhanced ultrasound (peak enhancement and wash-in area under the curve), while muscle stiffness was assessed using acoustic radiation force impulse (shear-wave velocities). A magnetic resonance imaging scan of both lower legs was also performed during the follow-up testing session to characterize the extent of exercise-induced muscle damage. Comparisons were made between limbs and over time. RESULTS: Shear-wave velocity values of the medial gastrocnemius showed a significant interaction between time and treatment (P = .006), with the noncompressed muscle demonstrating lower muscle stiffness values at follow-up compared to baseline or to the compressed muscle. No significant differences in soleus muscle stiffness were noted between limbs or over time, as was the case for muscle perfusion metrics (peak enhancement and wash-in area under the curve) for the medial gastrocnemius and soleus muscles. Further, compression had no significant effect on passive ankle dorsiflexion, muscle soreness, calf circumference, or injury severity, per magnetic resonance imaging. CONCLUSION: Continuous wearing of compression garments during the inflammation phase of DOMS may play an important role in regulating muscle stiffness; however, compression garments have no significant effects on intramuscular perfusion or other common clinical assessments. J Orthop Sports Phys Ther 2018;48(11):887-894. Epub12 Jun 2018. doi:10.2519/jospt.2018.8038.
EVALuna2:36098

Effect of Compression Garments on the Development of Edema and Soreness in Delayed-Onset Muscle Soreness (DOMS) - Heiß, Rafael; Hotfiel, Thilo; Kellermann, Marion; May, Matthias; Wüst, Wolfgang; Janka, Rolf Matthias; Nagel, Armin M.; Uder, Michael; Hammon, Matthias (Journal of Sports Science and Medicine, 2018)
Delayed-onset muscle soreness (DOMS), an ultrastructural muscle injury, is one of the most common reasons for impaired muscle performance. The purpose of this study was to investigate the influence of sport compression garments on the development of exercise-induced intramuscular edema in the context of DOMS. DOMS was induced in 15 healthy participants. The participants performed a standardized eccentric exercise of the calf muscles. Magnetic resonance imaging (MRI) was performed at baseline and 60h after exercise (T2-weighted signal intensity and T2 relaxation time was evaluated in each compartment and the intramuscular edema in the medial head of the gastrocnemius muscle was segmented). After the exercise, a conventional compression garment (18-21 mmHg) was placed on one randomized calf for 60h. The level of muscle soreness was evaluated using a visual analogue pain scale. T2-weighted signal intensity, T2 relaxation time and intramuscular edema showed a significant interaction for time with increased signal intensities/intramuscular edema in the medial head of the gastrocnemius muscle at follow-up compared to baseline. No significant main effect for compression or interaction between time and limb occurred. Further, no significant differences in the soleus muscle and the lateral head of the gastrocnemius muscle were noted between limbs or over time. After exercise, there was significantly increased muscle soreness in both lower legs in resting condition and when going downstairs and a decreased range of motion in the ankle joint. No significant difference was observed between the compressed and the non-compressed calf. Our results indicate that wearing conventional compression garments after DOMS has been induced has no significant effect on the development of muscle edema, muscle soreness, range of motion and calf circumference.
EVALuna2:34690

Effect of Flat-Knitted Medical Compression Stockings on Venous Malformations - Li, Yi; Muekke, Antje; Rother, Ulrich; Janka, Rolf Matthias; Uder, Michael; Lang, Werner; Heiß, Rafael (Journal of Clinical Medicine, 2023)
Venous malformations are one of the most common vascular anomalies. Our study aimed to investigate the effect of medical compression stockings of class I and II on the volume of venous malformations. Patients with venous malformations on upper or lower extremities were enrolled. They wore flat-knitted medical compression stockings of class I and II in a randomized order for four weeks each. Magnetic resonance imaging (MRI) and perometry were performed with and without wearing compression stockings. The 12-Item Short Form Survey (SF-12) questionnaire was performed before and after wearing compression stockings for four weeks each. A total of 18 patients completed the evaluations. Both compression classes showed a significant reduction of the volume of the venous malformations in the lesion itself based on MRI in comparison with baseline (both p < 0.001). Measurements taken with perometry did not reveal a significant difference in comparison to baseline (p = 0.09 and p = 0.22). The results of the SF-12 questionnaire demonstrated no significant differences before and after wearing the compression stockings of class I or class II for four weeks or between the two classes of compression therapy. Our results indicate that wearing medical compression stockings of both class I and class II significantly reduces the volume of venous malformation, without compromising the quality of life, while the effect of class II compression stockings on volume reduction was significantly better than that of class I.
CRIS-Team Scopus Importer:2023-04-28
Keywords: compression stockings; magnetic resonance imaging; perometry; quality of life; T2-weighted imaging; venous malformation

Effect of long term CPAP therapy on cardiac parameters assessed with cardiac MRI - Wüst, Wolfgang; May, Matthias; Wiesmüller, Marco; Uder, Michael; Schmid, Andrea (International Journal of Cardiovascular Imaging, 2020)
The obstructive sleep apnoea syndrome (OSAS) is a disorder with a high prevalence and is associated with an elevated cardiovascular risk and increased morbidity and mortality. For longitudinal studies and functional analysis cardiac MRI is regarded as the gold standard. Aim of this study was to evaluate the long-term effect of continuous positive airway pressure (CPAP) therapy on cardiac functional parameters with cardiac Magnetic Resonance Imaging (cMRI). 54 patients with OSAS (mean apnea hypopnea index-AHI: 31) were prospectively enrolled in this study and cMRI was performed before and after 7 months of CPAP therapy. Data were acquired on a 1.5 T MRI and right and left ventricular cardiac function were analysed. CPAP treatment was considered compliant when used ≥ 4 h per night. 24-h blood pressure was measured at baseline and follow up. 33 patients could be assigned to the compliance group. Left ventricular stroke volume (LV SV) and right ventricular ejection fraction (RV EF) improved significantly with CPAP therapy (LV SV from 93 ± 19 to 99 ± 20 ml, p = 0.02; RV EF from 50 ± 6 to 52 ± 6%, p = 0.04). All other cardiac parameters did not change significantly while mean systolic and diastolic blood pressure improved significantly (p < 0.01). 21 patients were assigned to the non-compliance group and were considered as a control group. There were no relevant differences in cardiac parameters between baseline and follow up examination in these patients. CPAP therapy seems to improve LV SV, RV EF, systolic and diastolic blood pressure in OSAS patients, but reproducibility of our results need to be confirmed in a larger patient population.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Cardiac MRI; CPAP therapy; Follow up; Sleep apnea

Effects of 16 months of high intensity resistance training on thigh muscle fat infiltration in elderly men with osteosarcopenia - Ghasemikaram, Mansour; Chaudry, Oliver; Nagel, Armin Michael; Uder, Michael; Jakob, Franz; Kemmler, Wolfgang; Kohl, Matthias; Engelke, Klaus (GeroScience, 2021)
Osteosarcopenia is characterized by a progressive decline in muscle function and bone strength and associated with muscle fat accumulation. This study aimed to determine the effect of long-term high intensity resistance training (HIRT) on thigh muscle fat infiltration in older men with osteosarcopenia. Forty-three community-dwelling men (72 years and older) were randomly assigned to either an exercise group (EG, n = 21) or an inactive control group (CG, n = 22). EG participants performed a supervised single-set exercise training with high effort two times per week. Participants of both groups were individually provided with dietary protein to reach a cumulative intake of 1.5-1.6 g/kg/day or 1.2-1.3 g/kg/day (EG/CG), respectively, and Up to 10,000 IE/week of Vitamin-D were supplemented in participants with 25 OH Vitamin-D 3 levels below 100 nmol/l. Magnetic resonance (MR) imaging was performed to determine muscle and adipose tissue volume and fat fraction of the thigh. At baseline, there were no significant differences between the two groups. After 16 month,, there were significant training effects of 15% (p = 0.004) on intermuscular adipose tissue (IMAT) volume, which increased in the CG (p = 0.012) and was stable in the EG. In parallel, fat fraction within the deep fascia of the thigh (Baseline, EG: 18.2 vs CG: 15.5, p = 0.16) significantly differed between the groups (Changes, EG: 0.77% vs. CG: 7.7%, p = 0.009). The study confirms the role of fat infiltration of the muscles as an advanced imaging marker in osteosarcopenia and the favorable effects of HIRT on adipose tissue volume of the thigh, in men with osteosarcopenia.
CRIS-Team WoS Importer:2021-02-05

Effects of different exercise intensity on bone mineral density in adults: a comparative systematic review and meta-analysis - Kast, Stephanie; Shojaa, Mahdieh; Kohl, M.; von Stengel, S.; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Klöckner, N.; Lange, U.; Middeldorf, S.; Peters, S.; et al. (Osteoporosis international, 2022)
Purpose: The primary objective of the present systematic review and meta-analysis was to determine the effect of differing exercise intensity on (areal) bone mineral density (BMD) at lumbar spine and hip in adults by a comparative meta-analysis. Methods: A systematic review of the literature according to the PRISMA statement included: (a) exercise trials, (b) with ≥two study arms that compared different exercise intensities, (c) intervention ≥6 months, (d) BMD assessments at lumbar spine (LS) or hip. Five electronic databases were scanned without language restrictions up to July 2021. The present analysis of exercise intensity was conducted as a mixed-effect meta-analysis and applied “type of exercise” and “study duration” as moderator in subgroup analyses. Outcome measures were standardized mean differences (SMD) for BMD changes at the LS, and hip. Results: Eleven exercise studies with 26 study arms were included. Although the effect of high-intensity exercise was more pronounced on LS-BMD (SMD: 0.19, 95%-CI: 0.61 to -0.23) and hip-ROI (0.17, 0.38 to -0.04), we did not observe significant differences between the groups (LS-BMD: p=0.373 and hip-BMD: p=0.109). We observed a substantial level of heterogeneity between the trials for LS- but not for hip-BMD. Applying “type of exercise” and “study duration” as moderators did not significantly modify the differences between low and high exercise intensity on BMD at LS or hip. Conclusion: There is insufficient evidence for a superior effect of high-intensity exercise on areal BMD at lumbar spine and hip in people aged 50 years and older. Varying exercise intensity with periods of lower exercise intensity intermitted by higher intensity might be a promising option to address the issue of exercise intensities in intervention studies.
CRIS-Team Scopus Importer:2022-03-25
Keywords: BMD; Exercise; Intensity; Meta-analysis; Type of exercise

Effects of High-Intensity Resistance Training on Visceral Adipose Tissue and Abdominal Aortic Calcifications in Older Men with Osteosarcopenia – Results from the FrOST Study - Knauer, Kira; Chaudry, Oliver; Uder, Michael; Kohl, Matthias; Kemmler, Wolfgang; Bickelhaupt, Sebastian; Engelke, Klaus (Clinical Interventions in Aging, 2023)
Purpose: To evaluate the effect of a high-intensity resistance training (HIT-RT) on visceral adipose tissue (VAT) and abdominal aortic calcifications (AAC). Patients and Methods: We conducted a post hoc analysis of the Franconian Osteopenia and Sarcopenia Trial (FrOST). 43 community-dwelling men with osteosarcopenia aged 72 years and older were randomly allocated to a supervised high-intensity resistance training (HIT-RT) twice weekly for 18 months (EG; n=21) and a non-training control group (CG; n=22). Non-contrast enhanced 2-point Dixon MRI scans covering mid L2 to mid L3 were acquired to measure VAT volume inside the abdominal cavity. Volume of AAC and hard plaques in renal arteries, truncus celiacus and superior mesenteric artery was measured by computed tomography (CT) scans covering mid T12 to mid L3. Intention-to-treat analysis with imputation for missing data was used to determine longitudinal changes in VAT and AAC volume. Correlations were used to determine associations between VAT and AAC. Results: Significant reduction of VAT volume in the EG (−7.7%; p<0.001) combined with no change in the CG (−1.3%; p=0.46) resulted in a significant 6.4% between group effect (p=0.022). We observed a significant increase of AAC volume in EG (+10.3%; p<0.001) and CG (12.0%; p<0.001). AAC differences between groups were not significant (p=0.57). In vascular outlets increases in volume of the hard plaques were observed in both groups, however, not all of them were significant. There was no significant correlation between changes in VAT and AAC volumes. Conclusion: The study confirmed a positive impact of HIT-RT on the metabolic and cardiovascular risk profile with respect to reduction of VAT volume. No positive exercise effect on AAC was observed. However, there was a further progression of AAC volume independent of group affiliation. Whether different exercise regimen may show a positive effect on AAC remains subject to further studies.
CRIS-Team Scopus Importer:2023-02-03
Keywords: AAC; HIT-RT; osteopenia; sarcopenia; VAT

Effects of high-intensity training on fatty infiltration in paraspinal muscles in elderly males with osteosarcopenia – the randomized controlled FrOST study - Kircher, Kaja; Chaudry, Oliver; Nagel, Armin Michael; Ghasemikaram, Mansour; Uder, Michael; Jakob, Franz; Kohl, Matthias; Kemmler, Wolfgang; Engelke, Klaus (BMC Geriatrics, 2024)
Background: Osteosarcopenia is a common geriatric syndrome with an increasing prevalence with age, leading to secondary diseases and complex consequences such as falls and fractures, as well as higher mortality and frailty rates. There is a great need for prevention and treatment strategies. Methods: In this analysis, we used magnetic resonance imaging (MRI) data from the randomised controlled FrOST trial, which enrolled community-dwelling osteosarcopenic men aged > 72 years randomly allocated to 16 months of twice-weekly high-intensity resistance training (HIRT) or a non-training control group. MR Dixon imaging was used to quantify the effects of HIRT on muscle fat infiltration in the paraspinal muscles, determined as changes in muscle tissue, fat faction and intermuscular adipose tissue (IMAT) in the erector spinae and psoas major muscles. Intention-to-treat analysis with multiple imputation was used to analyse the data set. Results: After 16 months of intervention, 15 men from the HIRT and 16 men from the CG were included in the MRI analysis. In summary, no positive effects on the fat infiltration of the erector spinae and psoas major muscles were observed. Conclusions: The previously reported positive effects on lumbar spine bone mineral density (BMD) suggest that mechanotransduction induces tropic effects on bone, but that fat infiltration of the erector spinae and psoas major muscles are either irreversible or, for some unknown reason, resistant to exercise. Because of the beneficial effects on spinal BMD, HIRT is still recommended in osteosarcopenic older men, but further research is needed to confirm appropriate age-specific training exercises for the paraspinal muscles. The potential of different MRI sequences to quantify degenerative and metabolic changes in various muscle groups must be better characterized. Trial registrations: FrOST was approved by the University Ethics Committee of the Friedrich-Alexander University of Erlangen-Nürnberg (number 67_15b and 4464b) and the Federal Office for Radiation Projection (BfS, number Z 5–2,246,212 – 2017–002). Furthermore, it fully complies with the Declaration of Helsinki and is registered at ClinicalTrials.gov: NCT03453463 (05/03/2018). JAMA 310:2191–2194, 2013.
CRIS-Team Scopus Importer:2024-02-23
Keywords: BMD; Dixon imaging; HIRT; IMAT; MRI; Osteosarcopenia

Effects of renal denervation on blood pressure in hypertensive patients with end-stage renal disease: a single centre experience - Ott, Christian; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical and Experimental Nephrology, 2019)
Background: Sympathetic nerve activity is a hallmark of hypertension in end-stage renal disease (ESRD). An initial proof-of-concept study implies that renal denervation (RDN) is feasible and safe in RDN, but overall data are limited. Methods: In this single-centre prospective pilot study six patients with ESRD and treatment resistant hypertension were consecutively included. Ambulatory blood pressure (ABP) was measured before and 6 months after RDN (Symplictiy Flex™, Medtronic Inc., Santa Rosa, CA). Moreover, haemodialysis parameters which may affect BP reduction were monitored closely. Results: In all patients bilateral RDN was successful done, without documentation of peri- or postprocedural complications. There was a significant reduction in 24-h ABP by 20 ± 17/15 ± 12 mmHg 6 months after RDN (systolic: 163 ± 16 versus 143 ± 9 mmHg, p = 0.043; diastolic: 96 ± 9 versus 81 ± 15 mmHg, p = 0.043), with similar results for day-, and nighttime values, respectively. Antihypertensive medication was kept stable as well as there was no change in haemodialysis parameters during follow-up. In addition, ultrafiltration/week (1.4 ± 1.4 versus 2.2 ± 1.4 l, p = 0.08) as well as hematocrit (measured at baseline and 6 months after RDN) (33.7 ± 4.3 versus 33.1 ± 3.9%, p = 0.715) revealed no change in volume status. Conclusion: Our single-centre pilot study not only supports current data on renal safety of RDN even in small arteries of patients with ESRD, but also enhances the knowledge towards an effective ABP reduction in this type of hypertensive patients.
CRIS-Team Scopus Importer:2019-05-07
Keywords: End-stage renal disease; Renal denervation; Treatment resistant hypertension

EFFECTS OF RENAL DENERVATION ON BLOOD PRESSURE IN PATIENTS WITH END-STAGE RENAL DISEASE: A SINGLE CENTER EXPERIENCE - Ott, C.; Schmid, Axel; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland (2018)
EVALuna2:202966

EFFECTS OF THE SGLT2 INHIBITOR EMPAGLIFLOZIN ON VASCULAR FUNCTION IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Bosch, Agnes; Jung, Susanne; Linz, Peter; Kannenkeril, Dennis; Nagel, Armin Michael; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

Effects of whole-body electromyostimulation with different impulse intensity on blood pressure changes in hyper- and normotensive overweight people. A pilot study - Kemmler, Wolfgang; Kohl, Matthias; von Stengel, Simon; Willert, Sebastian; Kast, Stephanie; Uder, Michael (Frontiers in Physiology, 2024)
Hypertension is a frequent condition in untrained middle-aged to older adults, who form the core group of whole-body electromyostimulation (WB-EMS) applicants. So far, the acute effects of varying impulse intensities on blood pressure responses have not been evaluated in normo- and hypertensive people. Thirteen hypertensive and twelve normotensive overweight WB-EMS novices, 40–70 years old, conducted the same WB-EMS protocol (20 min, bipolar, 85 Hz, 350 µs, 4 s impulse-4 s rest; combined with easy movements) with increasing impulse intensity (low, moderate, advanced) per session. Mean arterial blood pressure (MAP) as determined by automatic sphygmomanometry rose significantly (p <.001) from rest, 5 min pre-WB-EMS to immediately pre-WB-EMS assessment. Of importance, a 20-min WB-EMS application does not increase MAP further. In detail, maximum individual MAP does not exceed 128 mmHg (177 mmHg systolic or 110 mmHg diastolic) in any case. Two-min post-WB-EMS, MAP was significantly lower (p =.016) compared to immediately pre-WB-EMS. In contrast, heart rate increased significantly from immediately pre to immediately post-exercise (p <.001), though individual peak values did not exceed 140 beats/min−1 and heart rate decreased rapidly (p <.001) post-exercise. No significant differences in MAP and HR kinetics were observed for impulse intensity categories or hypertensive status. In summary, largely independently of impulse intensity and status, the acute effect of WB-EMS on MAP in novice applicants seem to be largely negligible. Although definite evidence might not have been provided by the present study, we conclude that hypertension, at least under treatment, should not be considered as a barrier for WB-EMS application in moderately old or older cohorts.
CRIS-Team Scopus Importer:2024-03-22
Keywords: blood pressure; cardiovascular; hypertension; impulse intensity; neuromuscular electrical stimulation; stimulus intensity; whole-body electromyostimulation

Effects on posture by different neuromuscular afferent stimulations and proprioceptive insoles: Rasterstereographic evaluation - Dankerl, Peter; Keller, Andrea; Häberle, Lothar; Stumptner, Thomas; Pfaff, Gregor; Uder, Michael; Forst, Raimund (Prosthetics and Orthotics International, 2014)
Proprioceptive neuromuscular stimulating insoles are increasingly applied in treating functional complaints, chronic pain, foot disorders and so on.To evaluate rasterstereography as a tool in objectifying postural changes resulting from neuromuscular afferent stimulation and proprioceptive neuromuscular stimulating insoles and to compare the respective effects on posture.This is a prospective experimental study.A total of 27 healthy volunteers were consecutively exposed to six different varying intense neuromuscular afferent stimulating test conditions at three different times. One test condition featured proprioceptive neuromuscular stimulating insoles. In each test condition, a sequence of 12 rasterstereographic recordings of back shape was documented. Changes between six different test conditions and over time for 14 posture characterising parameters were investigated, for example, trunk inclination, pelvic torsion, lateral deviation of the spine's amplitude or sagittal spinal curve.Standard deviation of our rasterstereographic measurements (±2.67 mm) was better than in most comparable reference values. Different neuromuscular stimuli were found to provoke significant changes to various posture parameters, including trunk inclination, pelvic torsion and so on ( each p < 0.001, F-tests). Proprioceptive neuromuscular stimulating insoles induced significant changes for parameter lateral deviation of the spine's amplitude (p = 0.03).Neuromuscular afferent stimulation and proprioceptive neuromuscular stimulating insoles induce postural changes, which can be detected reliably by rasterstereography.We demonstrated that rasterstereography - a radiation-free imaging modality - enables visualisation and documentation of subtle postural changes induced by varying intense neuromuscular afferent stimulation and the application of proprioceptive neuromuscular stimulating insoles.
EVALuna2:5494

Effekt von additivem körperlichem Training zur Bisphosphonat-Therapie auf die Knochendichte: Eine systematische Übersichtsarbeit und Meta-Analyse - Klotz, Christopher; Jakob, Franz; Kohl, Matthias; von Stengel, Simon; Lange, Uwe; Thomasius, Friederike; Kerschan-Schindl, Katharina; Uder, Michael; Kemmler, Wolfgang (Osteologie, 2022)
Background Physical exercise and antiresorptive pharmacological therapy affect bone metabolism through different mechanisms. The present study addresses the question of whether bisphosphonate treatment with additional exercise training has additive effects on bone density (BMD) at the lumbar spine (LS) and/or femoral neck (SH). Methods Our systematic literature search of five electronic databases according to PRISMA included controlled trials with a duration of≥6 months with at least two study arms: (a) bisphosphonates (B), (b) bisphosphonates and exercise (B+E) published up to 26 August 2021. Studies including other pharmaceutical therapies or diseases with relevant effects on bone metabolism were excluded. The analysis was conducted as a random-effects meta-analysis. Outcome measures were standardized mean differences (SMD) for BMD changes at LS and SH. Results Our search identified four eligible studies with a total of 247 participants. In summary, compared with bisphosphonate therapy alone, the combined intervention did not demonstrate significantly higher effect sizes at LS- (SMD: 0.66, 95%-CI: - 0.63 to 1.94) or SH-BMD (0.49, - 0.42 to 1.40). We observed very high heterogeneity among the results of the included studies for both, BMD-LWS and BMD-SH (I 2: 89 and 92%, respectively). The evidence for a small study or publication bias is also quite high for both outcomes. Conclusion We could not detect a significantly superior effect of a combined intervention (B+E) compared to isolated bisphosphonate therapy on BMD at LS and/or SH. However, the eligible studies indicate a high heterogeneity, which we primarily refer to the different training protocols of the trials.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bisphosphonate; Knochendichte; körperliches Training; Meta-Analyse

Efficacy and Safety of Angioplasty Balloon Interposition in CT-Guided Percutaneous Thermal Ablation of Hepatic Malignancies to Protect Adjacent Organs - Schlappa, Michael; Wuest, Wolfgang; Siebler, Jürgen; Grützmann, Robert; Uder, Michael; Schmid, Axel (Cardiovascular and Interventional Radiology, 2022)
Purpose To evaluate the feasibility and safety of placing angioplasty balloons between the liver surface and adjacent organs in CT-guided thermal ablation of subcapsular liver malignancies in case of inadequate success of conventional dissection techniques. Materials and Methods A retrospective, single-centre database query identified 327 hepatic malignancies in 153 patients treated in 215 sessions from 2016 to 2018 by thermal ablation. Demographic data, tumour size, distance to adjacent structures, complications and long-term outcomes were assessed when ancillary procedures were performed to protect adjacent organs. Results In 21 of 327 (6.4%) ablations, thermal protection was necessary. Balloon interposition was successfully performed in 9 cases in 8 patients after hydrodissection or gas insufflation failed to separate adherent organs. Median pre- and post-balloon insertion distance was 0 mm [0-2 mm] and 17 mm [8-20 mm]. No balloons were damaged, ruptured or slid away from their initial position. Technical success of MWA and protection of adherent structures were achieved in all procedures. In a median follow-up of 11.5 months [0-49 months], the local control rate was 88.9% as 1 patient was treated twice with an interval of 3 months for local recurrence. Three non-process-related major complications and 1 minor complication occurred. Conclusion Balloon interposition is a safe and feasible method to enable thermal ablation to a greater number of patients, even after established thermo-protective techniques fail to separate the colon or stomach from the liver surface.
CRIS-Team WoS Importer:2022-07-22

Einfluss neuer Techniken in der Bildgebung der Niere - Uder, Michael; Heinrich, Marc Christopher; Jäger, Florian; Hornegger, Joachim; Schmieder, Roland; Janka, Rolf Matthias (Nephrologe, 2009)
Computed tomography and magnetic resonance imaging have developed very rapidly in recent years. Today these methods are capable not only of morphological assessment of the kidneys but also provide data of a functional nature. Urography by MRI and CT have long been established in clinical routine. Other techniques such as blood level oxygenation-dependent (BOLD), diffusion-weighted, and renal perfusion imaging using MRI or CT are used almost exclusively for research purposes, but they also have many possibilities for renal applications under study conditions in diagnostics and for monitoring vascular and parenchymatous disorders. © 2009 Springer-Verlag.

Ein klinisch anwendbares Neuronales Netzwerk zur Klassifikation suspekter Läsionen in der Mamma-MRT - Ellmann, Stephan; Bielowski, Christian; Wenkel, Evelyn; Vesal, Sulaiman; Maier, Andreas; Uder, Michael; Bäuerle, Tobias (Fortschritte auf dem Gebiete der Röntgenstrahlen, 2018)
UnivIS-Import:2018-09-05:Pub.2018.tech.IMMD.IMMD5.einkli

Elevated tissue sodium deposition in patients with type 2 diabetes on hemodialysis detected by 23Na magnetic resonance imaging - Kopp, Christoph; Linz, Peter; Maier, Carolin; Wabel, Peter; Hammon, Matthias; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Uder, Michael; Luft, Friedrich C.; Titze, Jens; Dahlmann, Anke (Kidney International, 2018)
Long-term elevated blood sugar levels result in tissue matrix compositional changes in patients with diabetes mellitus type 2 (T2DM). We hypothesized that hemodialysis patients with T2DM might accumulate more tissue sodium than control hemodialysis patients. To test this, 23Na magnetic resonance imaging (23Na MRI) was used to estimate sodium in skin and muscle tissue in hemodialysis patients with or without T2DM. Muscle fat content was estimated by 1H MRI and tissue sodium content by 23Na MRI pre- and post-hemodialysis in ten hemodialysis patients with T2DM and in 30 matched control hemodialysis patients. We also assessed body fluid distribution with the Body Composition Monitor. 1H MRI indicated a tendency to higher muscle fat content in hemodialysis patients with T2DM compared to non-diabetic hemodialysis patients. 23Na MRI indicated increased sodium content in muscle and skin tissue of hemodialysis patients with T2DM compared to control hemodialysis patients. Multi-frequency bioimpedance was used to estimate extracellular water (ECW), and excess ECW in T2DM hemodialysis patients correlated with HbA1c levels. Sodium mobilization during hemodialysis lowered muscle sodium content post-dialysis to a greater degree in T2DM hemodialysis patients than in control hemodialysis patients. Thus, our findings provide evidence that increased sodium accumulation occurs in hemodialysis patients with T2DM and that impaired serum glucose metabolism is associated with disturbances in tissue sodium and water content.
EVALuna2:34700

Endovascular stenting of an HVAD (TM) outflow graft pseudoaneurysm that exerts compression and kinking stenosis on the soft portion of the prosthesis - Elbayomi, Mohamed; Weyand, Michael; Uder, Michael; May, Matthias; Steger, Katrin; Roth, Jan-Peter; Tandler, Rene (Clinical Case Reports, 2023)
Key Clinical MessageComplex presentations of MCS patients may necessitate a multidisciplinary approach involving HF cardiologists, CT surgeons, advanced cardiac imagers, and interventional cardiologists in order to define the optimal management strategy. Left ventricle assist devices (LVADs) provide life-sustaining treatment for patients with terminal heart failure, but their intricacy allows for complications. One complication is LVAD outflow graft obstruction due to the graft's intraluminal thrombus or extraluminal compression. It may be treated endovascularly with stenting. We report an endovascular stenting of an outflow tract in HVAD (TM) (HeartWare Inc.) due to a pseudoaneurysm causing compression and kinking stenosis.
CRIS-Team WoS Importer:2023-06-02

Evaluation of 2-point, 3-point, and 6-point Dixon magnetic resonance imaging with flexible echo timing for muscle fat quantification - Grimm, Alexandra; Meyer, Heiko; Nickel, Marcel D.; Nittka, Mathias; Raithel, Esther; Chaudry, Oliver; Friedberger, Andreas; Uder, Michael; Kemmler, Wolfgang; Quick, Harald H.; Engelke, Klaus (European Journal of Radiology, 2018)
The purpose of this study is to evaluate and compare 2-point (2pt), 3-point (3pt), and 6-point (6pt) Dixon magnetic resonance imaging (MRI) sequences with flexible echo times (TE) to measure proton density fat fraction (PDFF) within muscles. Two subject groups were recruited (G1: 23 young and healthy men, 31 ± 6 years; G2: 50 elderly men, sarcopenic, 77 ± 5 years). A 3-T MRI system was used to perform Dixon imaging on the left thigh. PDFF was measured with six Dixon prototype sequences: 2pt, 3pt, and 6pt sequences once with optimal TEs (in- and opposed-phase echo times), lower resolution, and higher bandwidth (optTE sequences) and once with higher image resolution (highRes sequences) and shortest possible TE, respectively. Intra-fascia PDFF content was determined. To evaluate the comparability among the sequences, Bland-Altman analysis was performed. The highRes 6pt Dixon sequences served as reference as a high correlation of this sequence to magnetic resonance spectroscopy has been shown before. The PDFF difference between the highRes 6pt Dixon sequence and the optTE 6pt, both 3pt, and the optTE 2pt was low (between 2.2% and 4.4%), however, not to the highRes 2pt Dixon sequence (33%). For the optTE sequences, difference decreased with the number of echoes used. In conclusion, for Dixon sequences with more than two echoes, the fat fraction measurement was reliable with arbitrary echo times, while for 2pt Dixon sequences, it was reliable with dedicated in- and opposed-phase echo timing.
EVALuna2:34695

Evaluation of a novel content-based image retrieval system for the differentiation of interstitial lung diseases in CT examinations - Pogarell, Tobias; Bayerl, Nadine; Wetzl, Matthias; Roth, Jessica; Speier, Christoph; Uder, Michael; Dankerl, Peter; Cavallaro, Alexander Josef (Diagnostics, 2021)
To evaluate the reader’s diagnostic performance against the ground truth with and without the help of a novel content-based image retrieval system (CBIR) that retrieves images with similar CT patterns from a database of 79 different interstitial lung diseases. We evaluated three novice readers’ and three resident physicians‘ (with at least three years of experience) diagnostic performance evaluating 50 different CTs featuring 10 different patterns (e.g., honeycombing, tree-in bud, ground glass, bronchiectasis, etc.) and 24 different diseases (sarcoidosis, UIP, NSIP, Aspergillosis, COVID-19 pneumonia etc.). The participants read the cases first without assistance (and without feedback regarding correctness), and with a 2-month interval in a random order with the assistance of the novel CBIR. To invoke the CBIR, a ROI is placed into the pathologic pattern by the reader and the system retrieves diseases with similar patterns. To further narrow the differential diagnosis, the readers can consult an integrated textbook and have the possibility of selecting high-level semantic features representing clinical information (chronic, infectious, smoking status, etc.). We analyzed readers’ accuracy without and with CBIR assistance and further tested the hypothesis that the CBIR would help to improve diagnostic performance utilizing Wilcoxon signed rank test. The novice readers demonstrated an unassisted accuracy of 18/28/44%, and an assisted accuracy of 84/82/90%, respectively. The resident physicians demonstrated an unassisted accuracy of 56/56/70%, and an assisted accuracy of 94/90/96%, respectively. For each reader, as well as overall, Sign test demonstrated statistically significant (p < 0.01) difference between the unassisted and the assisted reads. For students and physicians, Chi2-test and Mann-Whitney-U test demonstrated statistically significant (p < 0.01) difference for unassisted reads and statistically insignificant (p > 0.01) difference for assisted reads. The evaluated CBIR relying on pattern analysis and featuring the option to filter the results of the CBIR by predominant characteristics of the diseases via selecting high-level semantic features helped to drastically improve novices’ and resident physicians’ accuracy in diagnosing interstitial lung diseases in CT.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Computed tomography; Computer-aided diagnosis; Content-based image retrieval; Interstitial lung disease

Evaluation of ct-guided ultra-low-dose protocol for injection guidance in preparation of mr-arthrography of the shoulder and hip joints in comparison to conventional and low-dose protocols - Goeller, Anja; Pogarell, Tobias; May, Matthias; Uder, Michael; Dankerl, Peter (Diagnostics, 2021)
To evaluate patients’ radiation exposure undergoing CT-guided joint injection in preparation of MR-arthrography. We developed a novel ultra-low-dose protocol utilizing tin-filtration, performed it in 60 patients and compared the radiation exposure (DLP) and success rate to conventional protocol (26 cases) and low-dose protocol (37 cases). We evaluated 123 patients’ radiation exposure undergoing CT-guided joint injection from 16 January–21 March. A total of 55 patients received CT-guided joint injections with various other examination protocols and were excluded from further investigation. In total, 56 patients received shoulder injection and 67 received hip injection with consecutive MR arthrography. The ultra-low-dose protocol was performed in 60 pa-tients, the low-dose protocol in 37 patients and the conventional protocol in 26 patients. We compared the dose of the interventional scans for each protocol (DLP) and then evaluated success rate with MR-arthrography images as gold standard of intraarticular or extracapsular contrast injection. There were significant differences when comparing the DLP of the ultra-low-dose protocol (DLP 1.1 ± 0.39; p < 0.01) to the low dose protocol (DLP 5.3 ± 3.24; p < 0.01) as well as against the conventional protocol (DLP 22.9 ± 8.66; p < 0.01). The ultra-low-dose protocol exposed the patients to an average effective dose of 0.016 millisievert and resulted in a successful joint injection in all 60 pa-tients. The low dose protocol as well as the conventional protocol were also successful in all patients. The presented ultra-low-dose CT-guided joint injection protocol for the preparation of MR-arthrog-raphy demonstrated to reduce patients’ radiation dose in a way that it was less than the equivalent of the natural radiation exposure in Germany over 3 days—and thereby, negligible to the patient.
CRIS-Team Scopus Importer:2021-10-22
Keywords: CT intervention; Joint injection; MR-arthrography; Radiation exposure; Radiation protection; Tin-filtration

Evaluation of finger A3 pulley rupture in the crimp grip position-a magnetic resonance imaging cadaver study - Bayer, Thomas; Adler, Werner; Schweizer, Andreas; Schoeffl, Isabelle; Uder, Michael; Janka, Rolf Matthias (Skeletal Radiology, 2015)
The correct diagnosis of an A3 pulley rupture is challenging for musculoskeletal radiologists. An A3 pulley rupture should in theory influence the shape of the proximal interphalangeal joint volar plate (VP) and the amount of bowstringing at level of the VP during finger flexion. The purpose of this study was to perform MRI with metric analysis of the VP configuration and VP bowstringing in cadaver fingers in the crimp grip position and to determine cut points for A3 pulley rupture.MRI in the crimp grip position was performed in 21 cadaver fingers with artificially created flexor tendon pulley tears (fingers with A3 pulley rupture n = 16, fingers without A3 pulley rupture n = 5). The distances of the translation of the VP relative to the middle phalanx base, the distances between the flexor tendons and the VP body, and the distances between the flexor tendon and bone (TB) were measured.Statistical analysis showed significantly lower VP translation distances and significantly higher VP tendon distances if the A3 pulley was ruptured. A2 TB and A4 TB distances did not differ significantly in specimens with and without A3 pulley rupture. The optimal cut points for A3 pulley rupture were a VP translation distance <2.8 mm and a VP tendon distance >1.4 mm.Reduction of the VP translation distance and augmentation of the VP tendon distance are suitable indirect signs of A3 pulley rupture.
EVALuna2:5492

Evaluation of finger cartilage composition in recreational climbers with 7 Tesla T2 mapping magnetic resonance imaging - Bayer, Thomas; Brockhoff, Marie-Jo; Nagel, Armin Michael; Adler, Werner; Lutter, Christoph; Janka, Rolf Matthias; Heiß, Rafael; Uder, Michael; Roemer, Frank (Frontiers in Sports and Active Living, 2023)
Purpose: Sport climbing may lead to tissue adaptation including finger cartilage before apparent surface damage is detectable. The main aim was to assess finger cartilage composition with T2 mapping in young, active climbers and to compare the results to a non-climbers' collective. A secondary aim was to compare whether differences in cartilage T2 times are observed between older vs. younger volunteers. Methods and materials: 7 Tesla MRI of the fingers Dig.2–4 was performed using a multi-echo spin echo sequence. Manual segmentation of 3 ROIs at the metacarpal heads, 1 ROI at the base phalanx and 1 ROI at the proximal interphalangeal joint was performed. Included were 13 volunteers without history of trauma who are regularly performing climbing activities as a recreational sport (>20 h/month). These were age-matched with 10 control subjects not performing climbing activities. Results: Mean age was 32.4 years for the climbing group and 25.8 years for the controls. Mean T2 values for the 5 different ROIs were 42.2 ± 7.8 msec for climbers and 41.4 ± 6.8 msec for non-climbers. No significant differences were observed for T2 values between both groups. However, higher age had a significant impact on T2 values for all assessed ROIs (higher age 44.2 ± 9.5, younger age 32.9 ± 5.7, p = 0.001). Discussion: This study evaluated the cartilage composition of young, engaged climbers with a T2 mapping MRI technique with the purpose to depict early onset joint changes. No negative impact on cartilage composition due to the sport activity was found, whereas age-related effects on the cartilage seemed to be more prominent.
CRIS-Team Scopus Importer:2023-10-20
Keywords: cartilage; climbing; finger; magenetic resonance imaging; mapping

Evaluation of newly adapted clip marker system in ultrasound-guided core needle biopsy for suspicion of breast cancer - Schulz-Wendtland, Rüdiger; Dankerl, Peter; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Jud, Sebastian; Rauh, Claudia; Bayer, Christian M.; Beckmann, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: A newly adapted clip system for intramammary marking during ultrasound-guided core needle biopsy for suspicion of breast cancer is described and evaluated here. Material and Method: Fifty patients with suspicion of breast cancer (cT2) had ultrasound-guided core needle biopsy using a newly adapted clip marker system (HistoCore™ and O-Twist Marker™). Subsequently, ultrasound follow-up and tomosynthesis scans were done to determine the location of the marker clips. Results: No dislocation of the marker clip was detected on ultrasound in 45 of 50 patients (90%), and 5 patients (10%) had a maximum dislocation of 5 mm along the x-, y- or z-axis. Tomosynthesis scans demonstrated precise placement without dislocation of the clip markers in 48 patients (96%); 2 patients (4%) had a maximum dislocation of 3 mm along the x-, y- or z-axis. Conclusion: The newly developed clip marker system, a combination of a single-use breast biopsy needle and a precise, length-adapted intramammary marker clip, represents a further improvement in oncological therapy. This is of particular importance for patients requiring subsequent neoadjuvant chemotherapy, as in cases with complete tumour remission, there is no target point for preoperative, ultrasound-guided wire marking. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: biopsy; breast; breast cancer; ultrasound

Evaluation of novice reader diagnostic performance in coronary CT angiography using an advanced cardiac software package - Dankerl, Peter; Hammon, Matthias; Tsymbal, Alexey; Achenbach, Stephan; Uder, Michael; Janka, Rolf Matthias; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2014)
The purpose of this research was to evaluate whether a commercially available advanced cardiac software package for coronary CT angiography (CTA) interpretation may reliably assist inexperienced readers to screen for significant coronary artery stenoses.Coronary CTA data sets of 61 consecutive patients with suspected coronary artery disease were evaluated by three novice readers with no experience in cardiac CT interpretation. In the first 15 patients, the novice readers were trained to use the advanced cardiac software package (includes automatic detection of coronary vessels, curved MPR and VRT reconstructions and a measurement too) knowing the results of an expert read. In the next 46 patients, the novice readers had to state whether there is a significant coronary artery stenosis ([Formula: see text]50 %) and if they are confident with their diagnosis. The results of the novice readers were compared to the expert read.The 46 coronary CTA data sets contained 184 vessels with 15 stenoses in 9 patients. On a per-vessel analysis, novice reader 1/2/3 demonstrated 60 %/100 %/ 93% sensitivity, and 98 %/90 %/86 % specificity. Per patient, the readers diagnosed 36/28/29 cases correctly as free of stenoses, 6/9/8 correctly as having at least one stenosis, missed 3/0/1 cases with a stenosis and overdiagnosed 1/9/8 patients. Cohen's kappa values for the three readers versus the expert were 0.60, 0.61 and 0.54. The three novice readers felt confident in the diagnosis of 36/33/30 patients. In these patients, they missed one significant stenosis, showed a sensitivity of 100 %/100 %/75 % and a specificity of 100 %/92 %/88 %.The evaluated advanced cardiac software package successfully assists novice readers in interpreting coronary CTA data sets especially in ruling out significant coronary artery stenosis.
EVALuna2:11866

Evaluation of Rib Fractures on a Single-in-plane Image Reformation of the Rib Cage in CT Examinations - Dankerl, Peter; Seuß, Hannes; Ellmann, Stephan; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (Academic Radiology, 2016)
This study aimed to evaluate the diagnostic performance of using a reformatted single-in-plane image reformation of the rib cage for the detection of rib fractures in computed tomography (CT) examinations, employing different levels of radiological experience.We retrospectively evaluated 10 consecutive patients with and 10 patients without rib fractures, whose CT scans were reformatted to a single-in-plane image reformation of the rib cage. Eight readers (two radiologists, two residents in radiology, and four interns) independently evaluated the images for the presence of rib fractures using a reformatted single-in-plane image and a multi-planar image reformation. The time limit was 30 seconds for each read. A consensus of two radiologist readings was considered as the reference standard. Diagnostic performance (sensitivity, specificity, positive predictive value [PPV], and negative predictive value [NPV]) was assessed and evaluated per rib and per location (anterior, lateral, posterior). To determine the time limit, we prospectively analyzed the average time it took radiologists to assess the rib cage, in a bone window setting, in 50 routine CT examinations. McNemar test was used to compare the diagnostic performances.Single image reformation was successful in all 20 patients. The sensitivity, specificity, PPV, and NPV for the detection of rib fractures using the conventional multi-planar read were 77.5%, 99.2%, 89.9%, and 98.0% for radiologists; 46.3%, 99.7%, 92.5%, and 95.3% for residents; and 29.4%, 99.4%, 82.5%, and 93.9% for interns, respectively. Sensitivity, PPV, and NPV increased across all three groups of experience, using the reformatted single-in-plane image of the rib cage (radiologists: 85.0%, 98.6%, and 98.7%; residents: 80.0%, 92.8%, and 98.2%; interns: 66.9%, 89.9%, and 97.1%), whereas specificity did not change significantly (99.9%, 99.4%, and 99.3%). The diagnostic performance of the interns and residents was significantly better when evaluating the single-in-plane image reformations (P < .01). The diagnostic performance of the radiologists was better when evaluating the single-in-plane image reformations; however, there was no significant difference (statistical power: 0.32).The diagnostic performance for the detection of rib fractures, using CT images that have been reformatted to a single-in-plane image, improves for readers from different educational levels when the evaluation time is restricted to 30 seconds or less.
EVALuna2:14593

Evaluation of ventricular septal defects using high pitch computed tomography angiography of the chest in children with complex congenital heart defects below one year of age - Nau, David; Wüst, Wolfgang; Rompel, Oliver; Hammon, Matthias; Glöckler, Martin; Toka, Okan; Dittrich, Sven; Rueffer, André; Cesnjevar, Robert; Lell, Michael M.; Uder, Michael; May, Matthias (Journal of Cardiovascular Computed Tomography, 2019)
Background: Aim of this study was to assess the accuracy of ventricular septal defects (VSD) using high pitch computed tomography angiography (CTA) of the chest in children below 1 year of age, compared to the intraoperative findings and echocardiography. Methods: Out of 154 patients that underwent Dual-Source CTA of the chest using a high-pitch protocol at low tube voltages (70–80 kV), 55 underwent surgical repair of a VSD (median age 8 days, range 1–348 days). The margins of the VSDs and their relation to the surrounding structures were reproduced by en-face views using multiplanar reformations (MPR). Absolute diameter, normalized area and relative area compared to the aortic valve annulus were used for discrimination between restrictive and non-restrictive defects. Localization was classified into four subtypes. The results were compared to two-dimensional echocardiography and intraoperative findings. Results: Median absolute size of VSDs did not differ significantly between CTA-measurements (10.8 mm, range 2.8–18.1 mm) and intraoperative findings (12.0 mm, 3.0–25.0 mm, p = 0.09). Echocardiographic values were significantly lower (9.6 mm, 3.0–18.5 mm, both p < 0.01). The classification of the location and orientation matched the intraoperative situs in 96.4% of all cases using CT and in 87.3% using echocardiography. Echocardiography missed the relation to valves in 11% of all cases. Pre-interventional sensitivity and specificity for detection of a VSD were 97.2/98.9% compared to echocardiography. Median radiation dose was 0.32 mSv (range 0.12–2.00 mSv) and differed significantly between second and third generation Dual-Source CT (0.43 vs. 0.22 mSv, p = 0.003). Conclusion: Size and subtype of VSDs can be accurately assessed by CTA of the chest in patients with complex congenital heart defects at a very low radiation dose.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Computed tomography angiography; Congenital heart defect; Dual-source; High pitch; Ventricular septal defect

Exercise and the prevention of major osteoporotic fractures in adults: a systematic review and meta-analysis with special emphasis on intensity progression and study duration - Hoffmann, Isabelle; Kohl, Matthias; von Stengel, Simon; Jakob, Franz; Kerschan-Schindl, Katharina; Lange, Uwe; Peters, Stefan; Schöne, Daniel; Sieber, Cornel; Thomasius, Friederike; Bischoff-Ferrari, Heike A.; Uder, Michael; et al. (Osteoporosis international, 2022)
The role of exercise in preventing osteoporotic fractures is vague, and further recommendations for optimized exercise protocols are very rare. In the present work, we provided positive evidence for exercise effects on the number of osteoporotic fractures in adults, albeit without observing any significant relevance of intensity progression or study duration. Introduction Osteoporotic fractures are a major challenge confronting our aging society. Exercise might be an efficient agent for reducing osteoporotic fractures in older adults, but the most promising exercise protocol for that purpose has yet to be identified. The present meta-analysis thus aimed to identify important predictors of the exercise effect on osteoporotic fractures in adults. Methods We conducted a systematic search of six literature databases according to the PRISMA guideline that included controlled exercise studies and reported the number of low-trauma major osteoporotic fractures separately for exercise (EG) and control (CG) groups. Primary study outcome was incidence ratio (IR) for major osteoporotic fractures. Sub-analyses were conducted for progression of intensity (yes vs. no) during the trial and the study duration (<= 12 months vs. > 12 months). Results In summary, 11 studies with a pooled number of 9715 participant-years in the EG and 9592 in the CG were included. The mixed-effects conditional Poisson regression revealed positive exercise effects on major osteoporotic fractures (RR: 0.75, 95% CI: 0.54-0.94, p = .006). Although studies with intensity progression were more favorable, our subgroup analysis did not determine significant differences for diverging intensity progression (p = .133) or study duration (p = .883). Heterogeneity among the trials of the subgroups (I-2 <= 0-7.1%) was negligible. Conclusion The present systematic review and meta-analysis provided significant evidence for the favorable effect of exercise on major osteoporotic fractures. However, diverging study and exercise characteristics along with the close interaction of exercise parameters prevented the derivation of reliable recommendations for exercise protocols for fracture reductions. PROSPERO ID: CRD42021250467.
CRIS-Team WoS Importer:2022-12-02

Exercise effects on bone mineral density in men - Mages, Michelle; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Klöckner, Nicole; Lange, Uwe; Middeldorf, Stefan; et al. (Nutrients, 2021)
In contrast to postmenopausal women, evidence for a favorable effect of exercise on Bone Mineral Density (BMD) is still limited for men. This might be due to the paucity of studies, but also to the great variety of participants and study characteristics that may dilute study results. The aim of the present systematic review and meta-analysis was to evaluate the effect of exercise on BMD changes with rational eligibility criteria. A comprehensive search of six electronic databases up to 15 March 2021 was conducted. Briefly, controlled trials ≥6 months that determined changes in areal BMD in men >18 years old, with no apparent diseases or pharmacological therapy that relevantly affect bone metabolism, were included. BMD changes (standardized mean differences: SMD) of the lumbar spine (LS) and femoral neck (FN) were considered as outcomes. Twelve studies with 16 exercise and 12 control groups were identified. The pooled estimate of random-effect analysis was SMD = 0.38, 95%-CI: 0.14–0.61 and SMD = 0.25, 95%-CI: 0.00–0.49, for LS and FN, respectively. Heterogeneity between the trials was low–moderate. Funnel plots and rank and regression correlation tests indicate evidence for small study publication bias for LS but not FN-BMD. Subgroup analyses that focus on study length, type of exercise and methodologic quality revealed no significant difference between each of the three categories. In summary, we provided further evidence for a low but significant effect of exercise on BMD in men. However, we are currently unable to give even rough exercise recommendations for male cohorts.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Bone mineral density; Exercise; Men; Overview

Exercise Effects on the Reduction of Low-Traumatic and Major Osteoporotic Fractures in Adults. Systematic Review and Meta-Analysis - Shojaa, Mahdieh; Hoffmann, Isabelle; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Peters, Stefan; Schöne, Daniel; et al. (Osteologie, 2023)
The aim of the present systematic review and meta-analysis was to determine the effects of exercise on low-trauma overall and major osteoporotic fractures in adults. Our systematic search of six literature databases according to the PRISMA guideline was conducted up to May 22, 2021, and included controlled clinical exercise trials with (a) individuals >= 45 years, (b) cohorts without therapies/diseases related to bone metabolism or falls, (c) an intervention of >= 3 months, and (d) the number of low-traumatic fractures listed separately for the exercise (EG) and control (CG) groups. The study was registered in PROSPERO (ID: CRD42021250467). We applied a mixed-effects conditional Poisson regression model for the analysis. A total of 20 intervention studies with 21 EGs and 20 CGs were included in the analysis. The studies comprising a pooled number of participant-years of n=11,836 in the EG and n=11,275 in the CG. The meta-analysis determined significant effects of exercise on low-trauma overall fracture incidence (rate) ratio (IR: 0.67, 95% confidence interval (95%-CI): 0.51-0.87) and major osteoporotic fractures IR (0.69, 95%-CI: 0.52-0.92). Heterogeneity between the trials was moderate for low-trauma overall (I (2) =40%), and negligible (I (2) <1%) for major osteoporotic fractures. Funnel plots suggest low to moderate evidence of publication/small-study bias in study outcomes for low-trauma overall fractures. Despite some biometric limitations the present study provides further evidence of the positive effect of exercise on low-trauma overall and major osteoporotic fractures in community dwelling middle aged to older adults. With respect to low-trauma overall and major osteoporotic fractures reduction, the study results are comparable to current pharmaceutical agents.
CRIS-Team WoS Importer:2023-06-02
Keywords: Exercise - low-trauma fracture - major osteoporotic fracture - osteoporosis - fall reduction

Exercise Reduces the Number of Overall and Major Osteoporotic Fractures in Adults. Does Supervision Make a Difference? Systematic Review and Meta-Analysis - Hoffmann, Isabelle; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Clausen, Juergen; Lange, Uwe; Middeldorf, Stefan; et al. (Journal of Bone and Mineral Research, 2022)
The purpose of this systematic review and meta-analysis (PROSPERO ID: CRD42021250467) was to evaluate the effects of exercise on low-trauma overall and major osteoporotic fractures (hip, spine, forearm, or humerus fractures) and to determine the corresponding effect of supervision of the exercise program. Our systematic search of six literature databases according to the PRISMA guideline was conducted from January 1, 2013 (ie, date of our last search) to May 22, 2021, and included controlled clinical exercise trials with (i) individuals aged ≥45 years, (ii) cohorts without therapies/diseases related to fractures, (iii) observation periods of ≥3 months, and (iv) the number of low-trauma fractures listed separately for the exercise (EG) and control (CG) groups. We included 20 intervention studies with 21 EGs and 20 CGs comprising a pooled number of participant-years of n = 11.836 in the EG and n = 11.275 in the CG. The mixed-effects conditional Poisson regression revealed significant effects of exercise on low-trauma overall incidence (rate) ratio (IR 0.67, 95% confidence interval [95% CI] 0.51–0.87) and major osteoporotic fractures IR (0.69, 95% CI 0.52–0.92). Heterogeneity between the trials was moderate for low-trauma overall (I2 = 40%) and negligible (I2 < 1%) for major osteoporotic fractures. Supervision of the exercise program plays a significant role in the reductions of overall and major osteoporotic fractures with IR about twice as favorable in the predominately supervised (IR 0.44; 95% CI 0.27–0.73 and 0.38; 0.19–0.76) versus the predominately non-supervised exercise trials (IR 0.83; 95% CI 0.60–1.14 and 0.82; 0.64–1.05). In summary, the present study provides evidence for the positive effect of exercise on low-trauma overall and major osteoporotic fractures in middle aged to older adults. Supervision of the exercise program is a crucial aspect in exercise programs on fracture reduction. Thus, home-based exercise protocols should increasingly implement online classes to ensure widely consistent supervision and monitoring of the exercise program. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2022-09-23
Keywords: EXERCISE; LOW-TRAUMA FRACTURE; OSTEOPOROTIC FRACTURES; OVERALL FRACTURES

Exercise training and bone mineral density in postmenopausal women: an updated systematic review and meta-analysis of intervention studies with emphasis on potential moderators - Mohebbi, Ramin; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Jakob, Franz; Kerschan-Schindl, Katharina; Lange, Uwe; Peters, Stefan; Thomasius, Friederike; Uder, Michael; Kemmler, Wolfgang (Osteoporosis international, 2023)
The aim of this systematic review and meta-analysis was (1) to determine exercise effects on bone mineral density (BMD) in postmenopausal women and (2) to address the corresponding implication of bone and menopausal status or supervision in postmenopausal women. A comprehensive search of eight electronic databases according to the PRISMA statement up to August 9, 2022, included controlled exercise trials ≥ 6 months. BMD changes (standardized mean differences: SMD) at the lumbar spine (LS), femoral neck (FN), and total hip (TH) were considered as outcomes. Study group comparisons were conducted for osteopenia/osteoporosis versus normal BMD, early versus late postmenopausal women, and predominantly supervised versus predominantly non-supervised study arms. We applied an inverse heterogeneity (IVhet) model. In summary, 80 studies involving 94 training and 80 control groups with a pooled number of 5581 participants were eligible. The IVhet model determined SMDs of 0.29 (95% CI: 0.16–0.42), 0.27 (95% CI: 0.16–0.39), and 0.41 (95% CI: 0.30–0.52) for LS, FN, and THBMD, respectively. Heterogeneity between the trial results varied from low (I2 = 20%, TH BMD) to substantial (I2 = 68%, LS-BMD). Evidence for publication bias/small study effects was negligibly low (FN-, TH-BMD) to high (LSBMD). We observed no significant differences (p >.09) for exercise effects on LS-, FN-, or TH-BMD-LS between studies/study arms with or without osteopenia/osteoporosis, early versus late postmenopausal women, or predominantly supervised versus non-supervised exercise programs. Using robust statistical methods, the present work provides further evidence for a positive effect of exercise on BMD in postmenopausal women. Differences in bone status (osteopenia/osteoporosis versus normal bone), menopausal status (early versus late postmenopausal), and supervision (yes versus no) did not significantly affect the exercise effects on BMD at LS or proximal femur.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Bone strength; Exercise trials; Menopause; Older women; Osteoporosis; Supervision

Exposition of the operator's eye lens and efficacy of radiation shielding in fluoroscopically guided interventions Exposition der Augenlinse des Untersuchers und Effizienz der Strahlenschutzmittel bei fluoroskopischen Interventionen - Galster, M.; Guhl, C.; Uder, Michael; Adamus, R. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: Efficacy of radiation protection tools for the eye lens dose of the radiologist in fluoroscopic interventions. Materials and Methods: A patient phantom was exposed using a fluoroscopic system. Dose measurements were made at the eye location of the radiologist using an ionization chamber. The setting followed typical fluoroscopic interventions. The reduction of scattered radiation by the equipment-mounted shielding (undercouch drapes and overcouch top) was evaluated. The ceiling-suspended lead acrylic glass screen was tested in scattered radiation generated by a slab phantom. The protective properties of different lead glass goggles and lead acrylic visors were evaluated by thermoluminescence measurements on a head phantom in the primary beam. Results: The exposition of the lens of about 110 to 550 μSv during radiologic interventions is only slightly reduced by the undercouch drapes. Applying the top in addition to the drapes reduces the lens dose by a factor of 2 for PA projections. In 25°LAO the dose is reduced by a factor between 1.2 and 5. The highest doses were measured for AP angulations furthermore the efficacy of the equipment-mounted shielding is minimal. The ceiling-suspended lead screen reduced scatter by a factor of about 30. The lead glass goggles and visors reduced the lens dose up to a factor of 8 to 10. Depending on the specific design, the tested models are less effective especially for radiation from lateral with cranial angulation of the beam. Occasionally the visors even caused an increase of dose. Conclusion: The exposition of the eye lens can be kept below the new occupational limit recommended by the ICRP if the radiation shielding equipment is used consistently. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: eye lens dose; interventional radiology; lead glass goggles; radiation shielding

Extent of simultaneous radiation dose and iodine reduction at stable image quality in computed tomography of the chest: A systematic approach using automated tube voltage adaption and iterative reconstructions - Eller, Achim; Wüst, Wolfgang; Saake, Marc; Ellmann, Stephan; Kämmerer, Nadine; Hammon, Matthias; Janka, Rolf Matthias; Uder, Michael; May, Matthias (Medicine, 2018)
BACKGROUND: Aim of this study was to systematically combine tube voltage adaptation and iterative reconstructions for reduction of iodine and radiation dose. METHODS: Settings for the study protocol were evaluated in ex-ante trials to provide image quality that is comparable to a reference protocol at 120 kV with tube current modulation. Consecutive patients were randomized to undergo computed tomography (CT) of the chest using the study protocol (n = 62) or reference protocol (n = 50). Objective and subjective image quality was assessed and compared. RESULTS: Tube voltage was decreased to 100 kV in 47 patients and to 80 kV in 15 patients in the study group. The iodine dosage (16.1 vs 10.5 g) and the effective radiation dose (3.6 vs 2.5 mSv) were significantly decreased in the study group (both P < .001). Contrast-to-noise ratio was comparable in the pulmonary trunk and increased in the aorta (P < .01). Subjective image quality was comparable without statistically significance. CONCLUSIONS: Simultaneous reductions in iodine dosage and radiation dose by one-third are feasible for CT of the chest.
EVALuna2:34701

External Beam Accelerated Partial Breast Irradiation in Early Breast Cancer and the Risk for Radiogenic Pneumonitis - Ott, Oliver; Stillkrieg, Wilhelm; Lambrecht, Ulrike; Sauer, Tim-Oliver; Schweizer, Claudia; Lamrani, Allison; Strnad, Vratislav; Hack, Caroline; Beckmann, Matthias; Uder, Michael; Fietkau, Rainer; Distel, Luitpold (Cancers, 2022)
Simple Summary Accelerated partial breast irradiation represents a well-established and safe treatment alternative for selected patients with early stage breast cancer after breast-conserving surgery. In a prospective trial on external beam partial breast irradiation, the risk for radiogenic pneumonitis is analyzed. After a median follow-up of 56 (1-129) months, radiogenic pneumonitis grade 2 appeared in only 1/170 (0.6%) patients. Compared to standard whole breast irradiation, the radiation doses applied to the lungs were very low. The patient with the radiogenic pneumonitis was found to have a generally increased radiation susceptibility. Using accelerated partial breast irradiation, the risk of radiogenic pneumonitis appeared quite low and may be limited to very exceptional cases associated with innate risk factors with an increased radiation susceptibility. In order to evaluate the risk for radiation-associated symptomatic pneumonitis in a prospective external beam accelerated partial breast irradiation (APBI) trial, between 2011 and 2021, 170 patients with early stage breast cancer were enclosed in the trial. Patients were eligible for study participation if they had a histologically confirmed breast cancer or an exclusive ductal carcinoma in situ (DCIS), a tumor size <= 3 cm, free safety margins >= 2 mm, no involved axillary lymph nodes, tumor bed clips, and were >= 50 years old. Patients received APBI with 38 Gy with 10 fractions in 10 consecutive working days. The trial was registered at the German Clinical Trials Registry, DRKS-ID: DRKS00004417. Median follow-up was 56 (1-129) months. Ipsilateral lung MLD, V20, and V30 were 4.3 +/- 1.4 Gy, 3.0 +/- 2.0%, and 1.0 +/- 1.0%, respectively. Radiogenic pneumonitis grade 2 appeared in 1/170 (0.6%) patients two months after radiotherapy. Ipsilateral MLD, V20, and V30 were 6.1 Gy, 7, and 3% in this patient. Additionally, individual radiosensitivity was increased in this specific patient. Compared to WBI, APBI leads to lower lung doses. Using APBI, the risk of symptomatic radiogenic pneumonitis is very low and may be limited, with an ipsilateral V20 < 3% to very exceptional cases associated with innate risk factors with an increased radiation susceptibility.
CRIS-Team WoS Importer:2022-08-12

Fast online-customized (FOCUS) parallel transmission pulses: A combination of universal pulses and individual optimization - Herrler, Jürgen; Liebig, Patrick; Gumbrecht, Rene; Ritter, Dieter; Schmitter, Sebastian; Maier, Andreas; Schmidt, Manuel; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To mitigate spatial flip angle (FA) variations under strict specific absorption rate (SAR) constraints for ultra-high field MRI using a combination of universal parallel transmit (pTx) pulses and fast subject-specific optimization. Methods: Data sets consisting of B0, (Formula presented.) maps, and virtual observation point (VOP) data were acquired from 72 subjects (study groups of 48/12 healthy Europeans/Asians and 12 Europeans with pathological or incidental findings) using an 8Tx/32Rx head coil on a 7T whole-body MR system. Combined optimization values (COV) were defined as combination of spiral-nonselective (SPINS) trajectory parameters and an energy regularization weight. A set of COV was optimized universally by simulating the individual RF pulse optimizations of 12 training data sets (healthy Europeans). Subsequently, corresponding universal pulses (UPs) were calculated. Using COV and UPs, individually optimized pulses (IOPs) were calculated during the sequence preparation phase (maximum 15 s). Two different UPs and IOPs were evaluated by calculating their normalized root-mean-square error (NRMSE) of the FA and SAR in simulations of all data sets. Seven additional subjects were examined using an MPRAGE sequence that uses the designed pTx excitation pulses and a conventional adiabatic inversion. Results: All pTx pulses resulted in decreased mean NRMSE compared to a circularly polarized (CP) pulse (CP = 28%, UPs = 17%, and IOPs = 12%). UPs and IOPs improved homogeneity for all subjects. Differences in NRMSE between study groups were much lower than differences between different pulse types. Conclusion: UPs can be used to generate fast online-customized (FOCUS) pulses gaining lower NRMSE and/or lower SAR values.
CRIS-Team Scopus Importer:2021-01-15
Keywords: 7 T; k; parallel transmission (pTx); SPINS; ultra-high-field MRI; universal pulses

Feasibility of deuterium magnetic resonance spectroscopy of 3-O-Methylglucose at 7 Tesla - Hartmann, Benedikt; Müller, Max; Seyler, Lisa; Bäuerle, Tobias; Wilferth, Tobias; Avdievitch, Nikolai; Ruhm, Loreen; Henning, Anke; Lesiv, Alexei; Ivashkin, Pavel; Uder, Michael; Nagel, Armin Michael (PLoS ONE, 2021)
Deuterium Magnetic Resonance Spectroscopy (DMRS) is a non-invasive technique that allows the detection of deuterated compounds in vivo. DMRS has a large potential to analyze uptake, perfusion, washout or metabolism, since deuterium is a stable isotope and therefore does not decay during biologic processing of a deuterium labelled substance. Moreover, DMRS allows the distinction between different deuterated substances. In this work, we performed DMRS of deuterated 3-O-Methylglucose (OMG). OMG is a non-metabolizable glucose analog which is transported similar to D-glucose. DMRS of OMG was performed in phantom and in vivo measurements using a preclinical 7 Tesla MRI system. The chemical shift (3.51 ± 0.1 ppm) and relaxation times were determined. OMG was injected intravenously and spectra were acquired over a period of one hour to monitor the time evolution of the deuterium signal in tumor-bearing rats. The increase and washout of OMG could be observed. Three different exponential functions were compared in terms of how well they describe the OMG washout. A mono-exponential model with offset seems to describe the observed time course best with a time constant of 1910 ± 770 s and an offset of 2.5 ± 1.2 mmol/l (mean ± std, N = 3). Chemical shift imaging could be performed with a voxel size of 7.1 mm × 7.1 mm × 7.9 mm. The feasibility of DMRS with deuterium labelled OMG could be demonstrated. These data might serve as basis for future studies that aim to characterize glucose transport using DMRS.
CRIS-Team Scopus Importer:2021-06-18

Feasibility of Dixon magnetic resonance imaging to quantify effects of physical training on muscle composition-A pilot study in young and healthy men - Grimm, Alexandra; Nickel, Marcel D.; Chaudry, Oliver; Uder, Michael; Jakob, Franz; Kemmler, Wolfgang; Quick, Harald H.; Engelke, Klaus (European Journal of Radiology, 2019)
Changes in muscle-fat-composition affect physical performance and muscular function, like strength and power. The purpose of the present study was to investigate whether changes in soft tissue composition of the thigh and changes in muscle size and composition resulting from physical training were detectable with Dixon magnetic resonance imaging (MRI).
CRIS-Team WoS Importer:2019-05-03

Feasibility of In Vivo Metal Artifact Reduction in Contrast-Enhanced Dedicated Spiral Breast Computed Tomography - Wetzl, Matthias; Wenkel, Evelyn; Steiding, Chrisitan; Ruth, Veikko; Emons, Julius; Wasser, Martin N.; Uder, Michael; Ohlmeyer, Sabine (Diagnostics, 2023)
Background: Radiopaque breast markers cause artifacts in dedicated spiral breast-computed tomography (SBCT). This study investigates the extent of artifacts in different marker types and the feasibility of reducing artifacts through a metal artifact reduction (MAR) algorithm. Methods: The pilot study included 18 women who underwent contrast-enhanced SBCT. In total, 20 markers of 4 different types were analyzed for artifacts. The extent of artifacts with and without MAR was measured via the consensus of two readers. Image noise was quantitatively evaluated, and the effect of MAR on the detectability of breast lesions was evaluated on a 3-point Likert scale. Results: Breast markers caused significant artifacts that impaired image quality and the detectability of lesions. MAR decreased artifact size in all analyzed cases, even in cases with multiple markers in a single slice. The median length of in-plain artifacts significantly decreased from 31 mm (range 11–51 mm) in uncorrected to 2 mm (range 1–5 mm) in corrected images (p ≤ 0.05). Artifact size was dependent on marker size. Image noise in slices affected by artifacts was significantly lower in corrected (13.6 ± 2.2 HU) than in uncorrected images (19.2 ± 6.8 HU, p ≤ 0.05). MAR improved the detectability of lesions affected by artifacts in 5 out of 11 cases. Conclusion: MAR is feasible in SBCT and improves the image quality and detectability of lesions.
CRIS-Team Scopus Importer:2023-10-20
Keywords: breast CT; breast imaging; computed tomography; metal artifact reduction

Feasibility of Respiratory-gated High-pitch Spiral CT:: Free-breathing Inspiratory Image Quality - Lell, Michael; Scharf, Michael; Eller, Achim; Wüst, Wolfgang; Allmendinger, Thomas; Fuchs, Florian; Achenbach, Stephan; Uder, Michael; May, Matthias (Academic Radiology, 2016)
This study aimed to develop and implement a respiratory-gated setup for dual-source computed tomography (CT) at high pitch to examine patients in a reproducible inspiratory phase.Twenty-one patients underwent free-breathing respiratory-gated chest CT using a high-pitch scan mode no more than 6 months after inspiratory breath-held nongated CT, which serves as reference. Scan parameters were as follows: pitch = 3.4, 128 × 0.6 mm collimation, 0.28 s gantry rotation time, and 150 ref.mAs per tube at 120 kV. The examinations were triggered using the tidal wave provided by a respiratory-gating system as input signal. Image quality was assessed focusing on artifacts and delineation of the anatomical and pathological structures. Lung volumes were measured on both free-breathing and reference examinations.All examinations were performed without complications. Image quality was high with both protocols. Significantly less motion artifacts were recorded with the high-pitch mode compared to the reference (P = 0.02). Most of the artifacts were located in the peripheral parts of the lower lobes for the study group and in the central part of the left lower lobe for the reference. Average total lung volume was 4.5 ± 1.5 L in respiratory-gated examinations and 5.8 ± 0.9 L in examinations with breath-hold in inspiration.High-pitch chest CT scanning during free breathing minimizes motion artifacts, improving image quality in patients with limited breath-holding abilities. To assure scanning in an inspiratory phase, data acquisition should be triggered with a respiratory-gating system.
EVALuna2:12027

Feature-guided deep learning reduces signal loss and increases lesion CNR in diffusion-weighted imaging of the liver - Führes, Tobit; Saake, Marc; Lorenz, Jennifer; Seuß, Hannes; Bickelhaupt, Sebastian; Uder, Michael; Laun, Frederik Bernd (Zeitschrift für Medizinische Physik, 2023)
Purpose: This research aims to develop a feature-guided deep learning approach and compare it with an optimized conventional post-processing algorithm in order to enhance the image quality of diffusion-weighted liver images and, in particular, to reduce the pulsation-induced signal loss occurring predominantly in the left liver lobe. Methods: Data from 40 patients with liver lesions were used. For the conventional approach, the best-suited out of five examined algorithms was chosen. For the deep learning approach, a U-Net was trained. Instead of learning “gold-standard” target images, the network was trained to optimize four image features (lesion CNR, vessel darkness, data consistency, and pulsation artifact reduction), which could be assessed quantitatively using manually drawn ROIs. A quality score was calculated from these four features. As an additional quality assessment, three radiologists rated different features of the resulting images. Results: The conventional approach could substantially increase the lesion CNR and reduce the pulsation-induced signal loss. However, the vessel darkness was reduced. The deep learning approach increased the lesion CNR and reduced the signal loss to a slightly lower extent, but it could additionally increase the vessel darkness. According to the image quality score, the quality of the deep-learning images was higher than that of the images obtained using the conventional approach. The radiologist ratings were mostly consistent with the quantitative scores, but the overall quality ratings differed among the readers. Conclusion: Unlike the conventional algorithm, the deep-learning algorithm increased the vessel darkness. Therefore, it may be a viable alternative to conventional algorithms.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Cardiac motion artifact; Deep learning; Diffusion; Liver; Neural network; Oncology

Fine needle aspiration cytology of lymph nodes in breast cancer follow-up is a feasible alternative to watchful waiting and to histology - Hammon, Matthias; Dankerl, Peter; Janka, Rolf Matthias; Wachter, David; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Uder, Michael; Wenkel, Evelyn (BMC Women's Health, 2015)
Early detection of loco-regional breast cancer recurrence improves patients' overall survival, as treatment can be initiated or active treatment can be changed. If a suspicious lymph node is diagnosed during a follow-up exam, surgical excision is often performed. The aim of this study was to evaluate the diagnostic performance of the minor invasive ultrasound-guided fine-needle aspiration cytology (FNAC) in sonomorphologically suspicious lymph nodes in breast cancer follow-up.Between April 2010 and November 2012, we performed ultrasound-guided FNAC in 38 sonographically suspicious lymph nodes of 37 breast cancer follow-up patients. Cytological specimens were evaluated if the sample material was sufficient for diagnosis and if they contained cancer cells. Patients with negative cytology were followed up clinically and sonographically. To evaluate the diagnostic performance we calculated sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for physical examination, the different sonomorphological malignancy criteria and FNAC.In 36/38 (94.7 %) lymph nodes, the pathologist had enough material to establish a final diagnosis; in 2/38 (5.3 %) lymph nodes, the probe material was non-evaluable during cytology, these 2 were excluded from further statistical evaluation. Cytology revealed malignancy in 21 lymph nodes and showed no evidence for malignancy in 15 lymph nodes. There was no evidence for malignant disease in follow-up exams in the 15 cytologically benign lymph nodes with an average follow-up time of 3 years. The diagnostic performances of physical examination and FNAC were: Sensitivity 52/100 %, specificity 88/100 %, PPV 85/100 %, NPV 60/100 %, respectively.Our preliminary results show that FNAC is a safe and fast diagnostic approach for the evaluation of suspicious lymph nodes in the follow-up of patients with breast cancer and, thus, together with follow-up represents a feasible alternative to surgery.
EVALuna2:6744

First Experience With SPECT/CT Using a 99mTc-Labeled Inhibitor for Prostate-Specific Membrane Antigen in Patients With Biochemical Recurrence of Prostate Cancer - Reinfelder, Julia; Kuwert, Torsten; Beck, Michael; Sanders, James C.; Ritt, Philipp; Schmidkonz, Christian; Hennig, Peter; Prante, Olaf; Uder, Michael; Wullich, Bernd; Goebell, Peter (Clinical Nuclear Medicine, 2017)
Prostate-specific membrane antigen (PSMA) is overexpressed in most prostate cancers (PCs). Here, we report our first experience using the Tc-labeled PSMA inhibitor MIP-1404 (Progenics Pharmaceuticals, Inc, Tarrytown, NY) in 60 patients with biochemically recurrent PC.Whole-body planar scintigraphy and SPECT/CT of the lower abdominal pelvic region of 60 patients with biochemical relapse of PC were analyzed retrospectively. In these subjects, an average dose of 733.1 ± 49.5 MBq (19.8 ± 1.3 mCi) Tc-labeled MIP-1404 was injected 4 to 5 hours prior to imaging. In addition to visual evaluation, SUVmax were determined in the tumor lesions using a previously developed protocol for quantitative SPECT/CT.In 42 of 60 patients, Tc-MIP-1404-positive lesions could be detected (70%; 95% confidence interval [CI], 0.58-0.82). Twenty patients had Tc-MIP-1404-positive lymph nodes suggestive of metastasis, 14 patients had pathological uptake in the prostate region indicative of local recurrence, and for another 19 patients, there was tracer accumulation in the skeleton (n = 18) or lungs (n = 1). Detection rate was 91.4% (95% CI, 0.82-1) at prostate-specific antigen levels greater than 2 ng/mL and 40.0% (95% CI, 0.21-0.59) at lower prostate-specific antigen values (P < 0.01). Of the 60 patients, in total, 82 positive lesions were analyzed quantitatively. Average SUVmax of the lesions was 16.3 ± 21.6 with a range of 1.7 to 142.9.Tc-labeled PSMA inhibitor MIP-1404 is a promising SPECT tracer for detection of locally recurrent or metastatic prostate cancer.
EVALuna2:13859

FLAIRfusion Processing with Contrast Inversion : Improving Detection and Reading Time of New Cerebral MS Lesions - Schmidt, Manuel; Linker, Ralf; Lang, S.; Lücking, Hannes; Engelhorn, Tobias; Kloska, Stephan; Uder, Michael; Dörfler, Arnd; Dankerl, Peter; Cavallaro, Alexander Josef (Clinical Neuroradiology, 2017)
To evaluate the performance of an innovative image processing approach for detection of T2-weighted hyperintense multiple sclerosis (MS) lesions.In this study 20 consecutive patients with inflammatory demyelinating lesions were retrospectively evaluated of whom 10 patients featured progressive disease and 10 a stable lesion load. 3 mm transversal FLAIRfusion imaging was processed and archived. Image processing was performed through landmark-based 3D co-registration of the previous and current isotropic FLAIR examination followed by inversion of image contrast. Thereby, the hyperintense signals of the unchanged MS plaques extinguish each other, while newly developed lesions appear bright on FLAIRfusion. Diagnostic performance was evaluated by 4 experienced readers. Consensus reading supplied the reference standard. Sensitivity, specificity, NPV (negative predictive value), PPV (positive predictive value), interreader agreement and reading time were the outcome measures analyzed.Combined sensitivity was 100% at a specificity of 88.2%, with PPV ranging from 83.3% to 90.1% and NPV at 100%. Reading time was nearly 5-fold faster than conventional side by side comparison (35.6 s vs. 163.7 s, p < 0.001). Cohen's kappa was excellent (>0.75; p < 0.001) and Cronbach's alpha was 0.994.FLAIRfusion provides reliable detection of newly developed MS lesions along with strong interreader agreement across all levels of expertise in 35 s of reading time.
EVALuna2:14615

Flow-compensated diffusion encoding in MRI for improved liver metastasis detection - Laun, Frederik Bernd; Führes, Tobit; Seuß, Hannes; Müller, Astrid; Bickelhaupt, Sebastian; Stemmer, Alto; Benkert, Thomas; Uder, Michael; Saake, Marc (PLoS ONE, 2022)
Magnetic resonance (MR) diffusion-weighted imaging (DWI) is often used to detect focal liver lesions (FLLs), though DWI image quality can be limited in the left liver lobe owing to the pulsatile motion of the nearby heart. Flow-compensated (FloCo) diffusion encoding has been shown to reduce this pulsation artifact. The purpose of this prospective study was to intra-individually compare DWI of the liver acquired with conventional monopolar and FloCo diffusion encoding for assessing metastatic FLLs in non-cirrhotic patients. Forty patients with known or suspected multiple metastatic FLLs were included and measured at 1.5 T field strength with a conventional (monopolar) and a FloCo diffusion encoding EPI sequence (single refocused; b-values, 50 and 800 s/mm2). Two board-certified radiologists analyzed the DWI images independently. They issued Likert-scale ratings (1 = worst, 5 = best) for pulsation artifact severity and counted the difference of lesions visible at b = 800 s/mm2 separately for small and large FLLs (i.e., < 1 cm or > 1 cm) and separately for left and right liver lobe. Differences between the two diffusion encodings were assessed with the Wilcoxon signed-rank test. Both readers found a reduction in pulsation artifact in the liver with FloCo encoding (p < 0.001 for both liver lobes). More small lesions were detected with FloCo diffusion encoding in both liver lobes (left lobe: six and seven additional lesions by readers 1 and 2, respectively; right lobe: five and seven additional lesions for readers 1 and 2, respectively). Both readers found one additional large lesion in the left liver lobe. Thus, flow-compensated diffusion encoding appears more effective than monopolar diffusion encoding for the detection of liver metastases.
CRIS-Team Scopus Importer:2022-08-05

Free-Breathing and Single-Breath Hold Compressed Sensing Real-Time MRI of Right Ventricular Function in Children with Congenital Heart Disease. - Treutlein, Christoph; Zeilinger, Martin; Dittrich, Sven; Roth, Jessica; Wetzl, Matthias; Heiß, Rafael; Wuest, Wolfgang; May, Matthias; Uder, Michael; Rompel, Oliver (Diagnostics, 2023)
(1) Purpose: to compare right ventricular (RV) functional parameters in children with surgically repaired congenital heart disease (CHD) using single/double breath hold (BH) and free-breathing (FB) real-time compressed sensing (CS) cine cardiac magnetic resonance (cMRI) with standard retrospective segmented multi breath hold (RMB) cine cMRI. (2) Methods: Twenty patients with CHD underwent BH and FB, as well as RMB cine cMRI, at 3T to obtain a stack of continuous axial images of the RV. Two radiologists independently performed qualitative analysis of the image quality (rated on a 5-point scale; 1 = non-diagnostic to 5 = excellent) and quantitative analysis of the RV volume measurements. (3) Results: The best image quality was provided by RMB (4.5; range 2-5) compared to BH (3.9; range 3-5; p = 0.04) and FB (3.6; range 3-5; p < 0.01). The RV functional parameters were comparable among BH, FB, and RMB with a difference of less than 5%. The scan times for BH (44 ± 38 s, p < 0.01) and FB (24 ± 7 s, p < 0.01) were significantly reduced compared to for RMB (261 ± 68 s). (4) Conclusions: CS-FB and CS-BH real-time cine cMRI in children with CHD provides diagnostic image quality with excellent accuracy for measuring RV function with a significantly reduced scan time compared to RMB.
EVALuna2:539552

Free-Breathing Low-Field MRI of the Lungs Detects Functional Alterations Associated With Persistent Symptoms After COVID-19 Infection. - Levy, Simon; Heiß, Rafael; Grimm, Robert; Grodzki, David; Hadler, Dominique; Voskrebenzev, Andreas; Vogel-Claussen, Jens; Fuchs, Florian; Strauss, Richard; Achenbach, Susanne; Hinsen, Maximilian; Klett, Daniel; et al. (Investigative Radiology, 2022)
OBJECTIVES: With the COVID-19 pandemic, repetitive lung examinations have become necessary to follow-up symptoms and associated alterations. Low-field MRI, benefiting from reduced susceptibility effects, is a promising alternative for lung imaging to limit radiations absorbed by patients during CT examinations, which also have limited capability to assess functional alterations. The aim of this investigative study was to explore the functional abnormalities that free-breathing 0.55 T MRI in combination with the phase-resolved functional lung (PREFUL) analysis could identify in patients with persistent symptoms after COVID-19 infection. MATERIALS AND METHODS: Seventy-four COVID-19 patients and 8 healthy volunteers were prospectively scanned in free-breathing with a balanced steady-state free-precession sequence optimized at 0.55 T, 5 months postinfection on average. Normalized perfusion (Q), fractional ventilation (FV), and flow-volume loop correlation (FVLc) maps were extracted with the PREFUL technique. Q, FV, and FVLc defects as well as defect overlaps between these metrics were quantified. Morphological turbo-spin-echo images were also acquired, and the extent of abnormalities was scored by a board-certified radiologist. To investigate the functional correlates of persistent symptoms, a recursive feature elimination algorithm was applied to find the most informative variables to detect the presence of persistent symptoms with a logistic regression model and a cross-validation strategy. All MRI metrics, sex, age, body mass index, and the presence of preexisting lung conditions were included. RESULTS: The most informative variables to detect persistent symptoms were the percentage of concurrent Q and FVLc defects and of areas free of those defects. A detection accuracy of 71.4% was obtained with these 2 variables when fitting the model on the entire dataset. Although none of the single variables differed between patients with and without persistent symptoms ( P > 0.05), the combined score of these 2 variables did ( P < 0.02). This score also showed a consistent increase from healthy volunteers (7.7) to patients without persistent symptoms (8.2) and with persistent symptoms (8.6). The morphological abnormality score showed poor correlation with the functional parameters. CONCLUSIONS: Functional pulmonary examinations using free-breathing 0.55 T MRI with PREFUL analysis revealed potential quantitative markers of impaired lung function in patients with persistent symptoms after COVID-19 infection, potentially complementing morphologic imaging. Future work is needed to explore the translational relevance and clinical implication of these findings.
EVALuna2:506323

Frequency split metal artefact reduction in pelvic computed tomography - Lell, Michael; Meyer, Esther; Schmid, Matthias; Raupach, R.; May, Matthias; Uder, Michael; Kachelrieß, Marc (European Radiology, 2013)
Objectives: Artefacts from total hip replacement affect image quality and the visualisation of pelvic lesions on computed tomography (CT). We propose a frequency split (FS) approach in addition to the normalised metal artefact reduction (NMAR) algorithm that aims to suppress artefacts and improves image quality in patients with orthopaedic hardware. Methods: Data from ten consecutive patients with metal artefacts from uni- (n = 5) and bilateral (n = 4) total hip replacement or osteosynthesis (n = 1) were reconstructed with filtered back projection (FBP), linear interpolation MAR (LIMAR), NMAR, FSLIMAR and FSNMAR and analysed for image quality and severity of artefacts. Results: NMAR and FSNMAR significantly improved the assessment of the pelvic organs, lymph nodes and vessels compared with FBP, LIMAR or FSLIMAR (P < 0.05). Assessment of the metal hardware, joint and capsule was improved with the addition of FS (FSLIMAR, FSNMAR). No algorithm-related artefacts were detected in regions that did not contain metal. Conclusions: NMAR, FSLIMAR and FSNMAR have the potential to improve image quality in patients with artefacts from metal hardware and to improve the diagnostic accuracy of CT of the organs of the pelvis. Although introducing some algorithm-related artefacts, FSNMAR most accurately displayed adjacent bone and tissue next to metal implants. Key Points: • Orthopaedic metallic hardware often creates serious artefacts in computed tomography, hindering diagnosis. • The normalised metal artefact reduction (NMAR) algorithm was developed to suppress such artefacts. • NMAR improves CT assessment of pelvic organs in patients with orthopaedic hardware. • Addition of the frequency split technique (FSNMAR) helps assess tissue near metal hardware. • NMAR and FSNMAR are robust and computationally effective sinogram interpolation algorithms. © 2013 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computed tomography; Frequency split; Metal artefact reduction; Sinogram interpolation; Total hip replacement

Full field digital mammography (FFDM) versus cmos technology, specimen radiography system (SRS) and tomosynthesis (DBT) - Which system can optimise surgical therapy? - Schulz-Wendtland, Rüdiger; Dilbat, G.; Bani, Mayada; Fasching, Peter; Heusinger, K.; Lux, Michael P.; Löhberg, Christian; Brehm, Barbara; Hammon, Matthias; Saake, Marc; Dankerl, Peter; Jud, Sebastian; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: This prospective clinical study aimed to evaluate whether it would be possible to reduce the rate of re-excisions using CMOS technology, a specimen radiography system (SRS) or digital breast tomosynthesis (DBT) compared to a conventional full field digital mammography (FFDM) system. Material and Method: Between 12/2012 and 2/2013 50 patients were diagnosed with invasive breast cancer (BI-RADS™ 5). After histological verification, all patients underwent breast-conserving therapy with intraoperative imaging using 4 different systems and differing magnifications: 1. Inspiration™ (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm; 2. BioVision™ (Bioptics, Tucson, AZ, USA), CMOS technology, photodiode array, flat panel, tungsten source, focus 0.05, resolution 50 m pixel pitch, 12 lp/mm; 3. the Trident™ specimen radiography system (SRS) (Hologic, Bedford, MA, USA), amorphous selenium, tungsten source, focus 0.05, resolution 70 m pixel pitch, 7.1 lp/mm; 4. tomosynthesis (Siemens, Erlangen, Germany), amorphous selenium, tungsten source, focus 0.1 mm, resolution 85 m pixel pitch, 8 lp/mm, angular range 50 degrees, 25 projections, scan time > 20 s, geometry: uniform scanning, reconstruction: filtered back projection. The 600 radiographs were prospectively shown to 3 radiologists. Results: Of the 50 patients with histologically proven breast cancer (BI-RADS™ 6), 39 patients required no further surgical therapy (re-excision) after breast-conserving surgery. A retrospective analysis (n = 11) showed a significant (p < 0.05) increase of sensitivity with the BioVision™, the Trident™ and tomosynthesis compared to the Inspiration™ at a magnification of 1.0: 2.0 or 1.0: 1.0 (tomosynthesis) (2.6, 3.3 or 3.6 %), i.e. re-excision would not have been necessary in 2, 3 or 4 patients, respectively, compared to findings obtained with a standard magnification of 1.0: 1.0. Conclusion: The sensitivity of the BioVision™, the Trident™ and tomosynthesis was significantly (p < 0.05) higher and the rate of re-excisions was reduced compared to FFDM using a conventional detector at a magnification of 2.0 but without zooming. © Georg Thieme Verlag KG Stuttgart New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast; breast cancer; breast malignancy; mammography

Fully automated nipple detection in 3D breast ultrasound images - Wang, Lei; Böhler, Tobias; Zöhrer, Fabian; Georgii, Joachim; Rauh, Claudia; Fasching, Peter; Brehm, Barbara; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Uder, Michael; Hahn, Horst K. (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
Nipple position provides useful diagnostic informations in reading automated 3D breast ultrasound (ABUS) images. The identification of nipples is required to localize and determine the quadrants of breast lesions. Additionally, the nipple position serves as an effective landmark to register an ABUS image to other imaging modalities, such as digital mammography, breast magnet resonance imaging (MRI), or tomosynthesis. Nevertheless, the presence of speckle noise induced by interference waves and variant imaging directions in ultrasonography poses challenges to the task. In this work, we propose a fast and automated algorithm to detect nipples in 3D breast ultrasound images. The method fully takes advantages of the consistent characteristics of ultrasonographic signals observed at nipples and employs a multi-scale Laplacian-based blob detector to eventually identify nipple positions. The accuracy of the proposed method was tested on 113 ABUS images, resulting in a distance error of 6.6±8.9 mm (mean ±std). © 2014 Springer International Publishing.
CRIS-Team Scopus Importer:2023-03-08

Functional ankle instability as a risk factor for osteoarthritis: Using T2-mapping to analyze early cartilage degeneration in the ankle joint of young athletes - Golditz, Tobias; Steib, Simon; Pfeifer, Klaus; Uder, Michael; Gelse, Kolja; Janka, Rolf Matthias; Hennig, Friedrich; Welsch, Götz (Osteoarthritis and Cartilage, 2014)
Objective: The aim of this study was to investigate, using T2-mapping, the impact of functional instability in the ankle joint on the development of early cartilage damage. Methods: Ethical approval for this study was provided. Thirty-six volunteers from the university sports program were divided into three groups according to their ankle status: functional ankle instability (FAI, initial ankle sprain with residual instability); ankle sprain Copers (initial sprain, without residual instability); and controls (without a history of ankle injuries). Quantitative T2-mapping magnetic resonance imaging (MRI) was performed at the beginning ('early-unloading') and at the end ('late-unloading') of the MR-examination, with a mean time span of 27min. Zonal region-of-interest T2-mapping was performed on the talar and tibial cartilage in the deep and superficial layers. The inter-group comparisons of T2-values were analyzed using paired and unpaired t-tests. Statistical analysis of variance was performed. Results: T2-values showed significant to highly significant differences in 11 of 12 regions throughout the groups. In early-unloading, the FAI-group showed a significant increase in quantitative T2-values in the medial, talar regions (. P=0.008, P=0.027), whereas the Coper-group showed this enhancement in the central-lateral regions (. P=0.05). Especially the comparison of early-loading to late-unloading values revealed significantly decreasing T2-values over time laterally and significantly increasing T2-values medially in the FAI-group, which were not present in the Coper- or control-group. Conclusion: Functional instability causes unbalanced loading in the ankle joint, resulting in cartilage alterations as assessed by quantitative T2-mapping. This approach can visualize and localize early cartilage abnormalities, possibly enabling specific treatment options to prevent osteoarthritis in young athletes.
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.iss.psbg.functi
Keywords: Functional ankle instability; Magnetic resonance imaging; Osteoarthritis; Sports medicine; T2-mapping

Gadolinium-based contrast agents: What we learned from acute adverse events, nephrogenic systemic fibrosis and brain retention - Bäuerle, Tobias; Saake, Marc; Uder, Michael (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background Radiologists have been administering gadolinium-based contrast agents (GBCA) in magnetic resonance imaging for several decades, so that there is abundant experience with these agents regarding allergic-like reactions, nephrogenic systemic fibrosis (NSF) and gadolinium retention in the brain.
CRIS-Team WoS Importer:2021-01-22

Galactography with Tomosynthesis Technique (Galactomosynthesis) - Renaissance of a Method? - Schulz-Wendtland, Rüdiger; Preuss, Caroline; Fasching, Peter; Löhberg, Christian; Lux, Michael P.; Emons, Julius; Beckmann, Matthias; Uder, Michael; Mueller-Schimpfle, Markus (Geburtshilfe und Frauenheilkunde, 2018)
Introduction: For decades, conventional galactography was the only imaging technique capable of showing the mammary ducts. Today, diagnosis is based on a multimodal concept which combines high-resolution ultrasound with magnetic resonance (MR) mammography and ductoscopy/galactoscopy and has a sensitivity and specificity of up to 95%. This study used tomosynthesis in galactography for the first time and compared the synthetic digital 2D full-field mammograms generated with this technique with the images created using the established method of ductal sonography. Both methods should be able to detect invasive breast cancers and their precursors such as ductal carcinoma in situ (DCIS) as well as being able to identify benign findings. Material and Methods: Five patients with pathological nipple discharge were examined using ductal sonography, contrast-enhanced 3D galactography with tomosynthesis and the synthetic digital 2D full-field mammograms generated with the latter method. Evaluation of the images created with the different imaging modalities was done by three investigators with varying levels of experience with complementary breast diagnostics (1, 5 and 15 years), and their evaluations were compared with the histological findings. Results: All 3 investigators independently evaluated the images created with ductal sonography, contrast-enhanced 3D galactography with tomosynthesis, and generated synthetic digital 2D full-field mammograms. Their evaluations were compared with the histopathological assessment of the surgical specimens resected from the 5 patients. There was 1 case of invasive breast cancer, 2 cases with ductal carcinoma in situ and 2 cases with benign findings. All 3 investigators made more mistakes when they used the standard imaging technique of ductal sonography to diagnose suspicious lesions than when they used contrast-enhanced galactography with tomosynthesis and the generated synthetic digital 2D full-field mammograms. Conclusion: This is the first time breast tomosynthesis was used in galactography (galactomosynthesis) to create digital 3-dimensional images of suspicious findings. When used together with the generated synthetic digital 2D full-field mammograms, it could be a useful complementary procedure for the diagnosis of breast anomalies and could herald a renaissance of this method. Compared with high-resolution ductal ultrasound, the investigators achieved better results with contrast-enhanced galactography using tomosynthesis and the generated synthetic digital 2D full-field mammograms, as confirmed by histopathological findings.
EVALuna2:34697

Germany’s journey toward 14 Tesla human magnetic resonance - Ladd, Mark E.; Quick, Harald H.; Speck, Oliver; Bock, Michael; Dörfler, Arnd; Forsting, Michael; Hennig, Jürgen; Ittermann, Bernd; Möller, Harald E.; Nagel, Armin M.; Niendorf, Thoralf; Remy, Stefan; et al. (Magnetic Resonance Materials in Physics Biology and Medicine, 2023)
Multiple sites within Germany operate human MRI systems with magnetic fields either at 7 Tesla or 9.4 Tesla. In 2013, these sites formed a network to facilitate and harmonize the research being conducted at the different sites and make this technology available to a larger community of researchers and clinicians not only within Germany, but also worldwide. The German Ultrahigh Field Imaging (GUFI) network has defined a strategic goal to establish a 14 Tesla whole-body human MRI system as a national research resource in Germany as the next progression in magnetic field strength. This paper summarizes the history of this initiative, the current status, the motivation for pursuing MR imaging and spectroscopy at such a high magnetic field strength, and the technical and funding challenges involved. It focuses on the scientific and science policy process from the perspective in Germany, and is not intended to be a comprehensive systematic review of the benefits and technical challenges of higher field strengths.
CRIS-Team Scopus Importer:2023-04-21
Keywords: 14T; Extremely high field; GUFI; MRI; Ultrahigh field

Glucocorticoid-induced relapse of COVID-19 in a patient with sarcoidosis - Györfi, Andrea-Hermina; Kopp, Markus; May, Matthias; Vetter, Marcel; Uder, Michael; Kremer, Andreas; Schett, Georg; Harrer, Thomas; Distler, Jörg (Annals of the Rheumatic Diseases, 2020)
CRIS-Team Scopus Importer:2020-11-20

Hemodialysis Patients with Cardiovascular Disease Reveal Increased Tissue Na+ Deposition - Friedrich, Anna Carolina; Linz, Peter; Nagel, Armin Michael; Rosenhauer, Daniela; Horn, Stephan; Schiffer, Mario; Uder, Michael; Kopp, Christoph; Dahlmann, Anke (Kidney & Blood Pressure Research, 2022)
BACKGROUND: The relationship between Na+ balance and cardiovascular disease (CVD) in hemodialysis (HD) patients is not yet fully understood. We hypothesized that HD patients co-diagnosed with CVD show increased tissue Na+ accumulation compared to HD patients without CVD. METHODS: In our observational study, 52 HD patients were divided into a group with (23 subjects) or without (29 subjects) a positive history of cardiovascular events. We used 23Na-magnetic resonance imaging (23Na-MRI) at 3.0 Tesla to quantify Na+ content in skin and muscle of both groups directly before and after HD. Additionally, total body fluid distribution was determined by bioimpedance spectroscopy (BIS) and laboratory parameters were assessed. RESULTS: Compared to HD patients without CVD, 23Na-MRI detected an increased Na+ content in skin (21.7 ± 7.3 vs. 30.2 ± 9.8 arbitrary units (a.u.), p < 0.01) and muscle tissue (21.5 ± 3.6 vs. 24.7 ± 6.0 a.u., p < 0.05) in patients with previous CVD events. Simultaneously measured fluid amount by BIS, includingexcess extracellular water (1.8 ± 1.7 vs. 2.2 ± 1.7 L, p = 0.44), was not significantly different between both groups. Tissue Na+ accumulation in HD-CVD patients was paralleled by a higher plasma concentration of the inflammation marker interleukin-6 (5.1, IQR 5.8 vs. 8.5, IQR 7.9 pg/mL, p < 0.05). CONCLUSION: In our cohort, HD patients with CVD showed higher tissue Na+ content than HD patients without CVD, while no difference in body water distribution could be detected between both groups. Our findings provide evidence that the history of a cardiovascular event is associated with disturbances in tissue Na+ content in HD patients.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 23Na-magnetic resonance imaging; Cardiovascular disease; Hemodialysis; Tissue Na+

High Intensity Resistance Exercise Training vs. High Intensity (Endurance) Interval Training to Fight Cardiometabolic Risk Factors in Overweight Men 30-50 Years Old. - Tuttor, Michael; von Stengel, Simon; Kohl, Matthias; Lell, Michael; Scharf, Michael; Uder, Michael; Wittke, Andreas; Kemmler, Wolfgang (Frontiers in Sports and Active Living, 2020)
Cardiovascular and cardiometabolic diseases are leading causes of death worldwide. Exercise favorably affects this problem, however only few invest (enough) time to favorably influence cardiometabolic risk-factors and cardiac morphology/performance. Time-effective, high-intensity, low-volume exercise protocols might increase people's commitment to exercise. To date, most research has focused on high-intensity interval training (HIIT), the endurance type of HIT, while corresponding HIT-resistance training protocols (HIT-RT) are rarely evaluated. In this study we compared the effect of HIIT vs. HIT-RT, predominately on cardiometabolic and cardiac parameters in untrained, overweight-obese, middle-aged men. Eligible, untrained men aged 30-50 years old in full-time employment were extracted from two joint exercise studies that randomly assigned participants to a HIIT, HIT-RT or corresponding control group. HIIT predominately consisted of interval training 90 s-12 min, (2-4 sessions/week), HIT-RT (2-3 sessions/week) was applied as a single set resistance training to muscular failure. Core intervention length of both protocols was 16 weeks. Main inclusion criteria were overweight-obese status (BMI 25-35 kg/m2) and full employment (occupational working time: ≥38.5 h/week). Primary study-endpoint was the Metabolic Syndrome (MetS) Z-Score, secondary study-endpoints were ventricular stroke volume index (SVI) and myocardial mass index (MMI) as determined by Magnetic Resonance Imaging. The Intention to treat (ITT) principle was applied to analyze the summarized data set. Twenty-seven eligible men of the HIT-RT and 30 men of the HIIT group were included in the ITT. Both interventions significantly (p < 0.001) improve the MetS Z-Score, however the effect of HIIT was superior (p = 0.049). In parallel, HIT-RT and HIIT significantly affect SVI and MMI, with the effect of HIIT being much more pronounced (p < 0.001). Although HIIT endurance exercise was superior in favorably affecting cardiometabolic risk and particularly cardiac performance, both exercise methods positively affect cardiometabolic risk factors in this overweight to obese, middle-aged cohort of males with low time resources. Thus, the main practical application of our finding might be that in general overweight-obese people can freely choose their preferred exercise type (HIIT-END or HIT-RT) to improve their cardiometabolic health, while investing an amount of time that should be feasible for everybody. Trial Registrations: NCT01406730, NCT01766791.
EVALuna2:423136

Highly accelerated, Dixon-based non-contrast MR angiography versus high-pitch CT angiography - Zeilinger, Martin; Giese, Daniel; Schmidt, Michaela; May, Matthias; Janka, Rolf Matthias; Heiß, Rafael; Ammon, Fabian; Achenbach, Stephan; Uder, Michael; Treutlein, Christoph (Radiologia Medica, 2023)
Objectives: To compare a novel, non-contrast, flow-independent, 3D isotropic magnetic resonance angiography (MRA) sequence that combines respiration compensation, electrocardiogram (ECG)-triggering, undersampling, and Dixon water-fat separation with an ECG-triggered aortic high-pitch computed tomography angiography (CTA) of the aorta. Materials and methods: Twenty-five patients with recent CTA were scheduled for non-contrast MRA on a 3 T MRI. Aortic diameters and cross-sectional areas were measured on MRA and CTA using semiautomatic measurement tools at 11 aortic levels. Image quality was assessed independently by two radiologists on predefined aortic levels, including myocardium, proximal aortic branches, pulmonary veins and arteries, and the inferior (IVC) and superior vena cava (SVC). Image quality was assessed on a 5-point Likert scale. Results: All datasets showed diagnostic image quality. Visual grading was similar for MRA and CTA regarding overall image quality (0.71), systemic arterial image quality (p = 0.07–0.91) and pulmonary artery image quality (p = 0.05). Both readers favored MRA for SVC and IVC, while CTA was preferred for pulmonary veins (all p < 0.05). No significant difference was observed in aortic diameters or cross-sectional areas between native MRA and contrast-enhanced CTA (p = 0.08–0.94). Conclusion: The proposed non-contrast MRA enables robust imaging of the aorta, its proximal branches and the pulmonary arteries and great veins with image quality and aortic diameters and cross-sectional areas comparable to that of CTA. Moreover, this technique represents a suitable free-breathing alternative, without the use of contrast agents or ionizing radiation. Therefore, it is especially suitable for patients requiring repetitive imaging.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Angiography; Computed tomography; Follow-up studies; Magnetic resonance imaging

High-performance low field MRI enables visualization of persistent pulmonary damage after COVID-19 - Heiß, Rafael; Grodzki, David M.; Horger, Wilhelm; Uder, Michael; Nagel, Armin Michael; Bickelhaupt, Sebastian (Magnetic Resonance Imaging, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) with the origin of the spread assumed to be located in Wuhan, China, began in December 2019, and is continuing until now. With the COVID-19 pandemic showing a progressive spread throughout the countries of the world, there is emerging interest for the potential long-term consequences of suffering from a COVID-19 pneumonia. Imaging plays a central role in the diagnosis and management of COVID-19 pneumonia, with chest X-ray examinations and computed tomography (CT) being undoubtedly the modalities most widely used, allowing for a fast and sensitive detection of infiltration patterns associated with COVID-19 pneumonia. For a better understanding of underlying pathomechanisms of pulmonary damage, longitudinal imaging series are warranted, for which CT is of limited usability due to repeated exposure of X-rays. Recent advances in MRI suggested that high-performance low-field MRI might represent a valuable method for pulmonary imaging without the need of radiation exposure. However, so far, low-field MRI has not been applied to study pulmonary damage after COVID-19 pneumonia. We present a case report of a patient who suffered from COVID-19 pneumonia using 0.55 T MRI for follow-up examinations three months after initial infection. Low-field MRI enables a precise visualization of persistent pulmonary changes including ground-glass opacities, which are consistent with CT performed on the same day. Low-field MRI seems to be feasible in the detection of pulmonary involvement in patients with COVID-19 pneumonia and may have the potential for repetitive lung examinations in monitoring the reconvalescence after pulmonary infections.
CRIS-Team Scopus Importer:2020-12-04

High resolution time-of-flight MR-angiography at 7 T exploiting VERSE saturation, compressed sensing and segmentation - Meixner, Christian; Liebig, Patrick; Speier, Peter; Forman, Christoph; Hensel, Bernhard; Schmidt, Manuel; Saake, Marc; Uder, Michael; Dörfler, Arnd; Heidemann, Robin M.; Schmitter, Sebastian; Nagel, Armin Michael (Magnetic Resonance Imaging, 2019)
Background: 3D Time-of-Flight (TOF) MR-angiography (MRA) substantially benefits from ultra-high magnetic field strengths (≥7 T) due to increased Signal-to-Noise ratio and improved contrast. However, high-resolution TOF-MRA usually requires long acquisition times. In addition, specific absorption rate constraints limit the choice of optimal pulse sequence parameters, especially if venous saturation is employed. Purpose: To implement and evaluate an arterial TOF-MRA for accelerated high-resolution angiography at ultra-high magnetic field strength. Field strengths/sequence: 7 T modified gradient-echo TOF sequence including venous saturation using Variable-Rate Selective Excitation (VERSE), Compressed Sensing (CS) and sparse application of saturation pulses, called segmentation, were included for acceleration. Assessment: To analyze the acceleration techniques all volunteers were examined with the same protocols. CS with different sampling patterns and regularization factors as well as segmentation were applied for acceleration. For comparison, conventional acceleration techniques were applied (GRAPPA PAT 3 and Partial Fourier (6/8 in slice/phase encoding)). Images were co-registered and 40 mm thick transversal maximum intensity projections were created to calculate the relative number of vessels. To analyze the visibility of small vessels, the lenticulostriate arteries (LSA) were examined. This was done via multiscale vessel enhancement filtering in a VOI and quantification via Fiji ImageJ as well as qualitatively evaluation by two radiologists. Additionally, the venous/arterial vessel-to-background ratios (vVBR/aVBR) were calculated for chosen protocols. Results: For the acceleration of a high resolution TOF-MRA (0.31 mm isotropic), under-sampling of 9.6 showed aliasing artifacts, whereas 7.2 showed no aliasing. The regularization factor R had a strong impact on the image quality according to smoothing (R = 0.01 to R = 0.005) and noise (R = 0.0005 to R = 0.00005). With the alternating sampling patterns it was shown that the k-space center should not be under-sampled too much. Additionally segmentation could be verified to be feasible for stronger acceleration with sufficient venous suppression. Conclusion: The combination of several independent techniques (VERSE, CS with acceleration factor 7.2, R = 0.001, Poisson disc radius of 80%, 3 segments) enables the application of high-resolution (0.31 mm isotropic) TOF-MRA with venous saturation at 7 T in clinical time settings (TA ≈ 5 min) and within the SAR limits.
CRIS-Team Scopus Importer:2019-08-30
Keywords: 7 Tesla; Compressed sensing; MR-angiography; Time-of-flight; Ultra-high field; VERSE

Hybrid B1+-shimming and gradient adaptions for improved pseudo-continuous arterial spin labeling at 7 Tesla - Meixner, Christian; Eisen, Christian; Schmitter, Sebastian; Müller, Max; Herrler, Jürgen; Hensel, Bernhard; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2021)
Purpose: To improve pseudo-continuous arterial spin labeling (pcASL) at 7T by exploiting a hybrid homogeneity- and efficiency-optimized (Formula presented.) -shim with adapted gradient strength as well as background suppression. Methods: The following three experiments were performed at 7T, each employing five volunteers: (1) A hybrid (ie, homogeneity-efficiency optimized) (Formula presented.) -shim was introduced and evaluated for variable-rate selective excitation pcASL labeling. Therefore, (Formula presented.) -maps in the V3 segment and time-of-flight images were acquired to identify the feeding arteries. For validation, a gradient-echo sequence was applied in circular polarized (CP) mode and with the hybrid (Formula presented.) -shim. Additionally, the gray matter (temporal) signal-to-noise ratio (tSNR) in pcASL perfusion images was evaluated. (2) Bloch simulations for the pcASL labeling were conducted and validated experimentally, with a focus on the slice-selective gradients. (3) Background suppression was added to the (Formula presented.) -shimmed, gradient-adapted 7T sequence and this was then compared to a matched sequence at 3T. Results: The (Formula presented.) -shim improved the signal within the labeling plane (23.6%) and the SNR/tSNR increased (+11%/+11%) compared to its value in CP mode; however, the increase was not significant. In accordance with the simulations, the adapted gradients increased the tSNR (35%) and SNR (45%) significantly. Background suppression further improved the perfusion images at 7T, and this protocol performed as well as a resolution-matched protocol at 3T. Conclusion: The combination of the proposed hybrid (Formula presented.) -phase-shim with the adapted slice-selective gradients and background suppression shows great potential for improved pcASL labeling under suboptimal (Formula presented.) conditions at 7T.
CRIS-Team Scopus Importer:2021-08-27
Keywords: 7 Tesla; B1 shimming; pcASL; pTx; ultra-high field strengths; VERSE

Hybrid Imaging (PET-Computed Tomography/PET-MR Imaging) of Bone Metastases - Schmidkonz, Christian; Ellmann, Stephan; Ritt, Philipp; Roemer, Frank; Guermazi, Ali; Uder, Michael; Kuwert, Torsten; Bäuerle, Tobias (PET Clinics, 2019)
Bone metastases are a common source of osseous malignancy in the skeleton and affect up to 70% of all cancer patients. Hybrid imaging modalities including positron emission tomography (PET)/computed tomography (CT) and PET/MRI play an increasing role for the detection and follow-up of metastatic disease, especially in monitoring treatment response upon local or systemic therapy. This review summarizes current applications of PET/CT and PET/MRI in the clinical setting for imaging of metastases.
CRIS-Team WoS Importer:2020-02-21

Hybrid ultrasound and single wavelength optoacoustic imaging reveals muscle degeneration in peripheral artery disease - Träger, Anna P.; Günther, Josefine; Raming, Roman; Paulus, Lars-Philip; Lang, Werner; Meyer, Alexander; Kempf, Julius; Caranovic, Milenko; Li, Yi; Wagner, Alexandra; Tan, Lina; Danko, Vera; et al. (Photoacoustics, 2024)
Peripheral arterial disease (PAD) leads to chronic vascular occlusion and results in end organ damage in critically perfused limbs. There are currently no clinical methods available to determine the muscular damage induced by chronic mal-perfusion. This monocentric prospective cross-sectional study investigated n = 193 adults, healthy to severe PAD, in order to quantify the degree of calf muscle degeneration caused by PAD using a non-invasive hybrid ultrasound and single wavelength optoacoustic imaging (US/SWL-OAI) approach. While US provides morphologic information, SWL-OAI visualizes the absorption of pulsed laser light and the resulting sound waves from molecules undergoing thermoelastic expansion. US/SWL-OAI was compared to multispectral data, clinical disease severity, angiographic findings, phantom experiments, and histological examinations from calf muscle biopsies. We were able to show that synergistic use of US/SWL-OAI is most likely to map clinical degeneration of the muscle and progressive PAD.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Muscle degeneration; Muscle imaging; Optoacoustics; Peripheral artery disease; Photoacoustics

Identification of anatomic risk factors for scalar translocation in cochlear implant patients - Eisenhut, Felix; Lang, Stefan; Hölter, Philip; Wiesmüller, Marco; Uder, Michael; Iro, Heinrich; Dörfler, Arnd; Hornung, Joachim; Taha, Lava (Zeitschrift für Medizinische Physik, 2021)
Aim: Microanatomical evaluation of cochlear implant (CI) patients to identify anatomical risk factors for a scalar translocation. Methods: CI patients with both a regular scala tympani spiralization (group A) and a scalar translocation (group B) were identified via postoperative flat-detector computed tomography (FD-CT). Then, the corresponding preoperative multislice computed tomography (MS-CT) and postoperative FD-CT datasets were assessed: First, the cochleae were separated in 6 segments of 45° each. Next, quantitative (cochlea height, length, depth, cochlear duct diameter [CD] per segment; percentual tapering of the CD per segment named cochlear geometry index [CGI]) and qualitative (identifiability of the CI model; CI-integrity; intracochlear array position) parameters were evaluated and compared for both groups. Receiver-operating-characteristics (ROC) analysis was performed for the CGI. Results: In total, 40 preoperative MS-CT and postoperative FD-CT datasets (nA = 20; nB = 20) were analysed. Model “CI 512” was successfully identified and CI-integrity has been confirmed in all cases. Quantitative analysis showed a significant difference of both the CD at 0° (CDA 0°= 2.06 ± 0.23 mm; CDB 0°= 2.19 ± 0.18 mm; p0°= 0.04) and the CGI of the first segment (CGIA 0° -45°= 18.87 ± 6.04%; CGIB 0°-45°= 28.89 ± 8.58%; p0°-45°= 0.0001). For all other 5 cochlear segments there was no significant difference of CD and CGI; there was no significant difference of external cochlea diameters. The area under the curve (AUC) of the CGI0-45° was 0.864 with 24.50° as the optimal cut-off value to discriminate patients with a scala tympani spiralization and a scalar translocation. CGI0-45° of > 24.50° allowed the correct identification of 85% of patients with a scalar translocation. Conclusion: CI insertion trauma is associated with a significantly higher narrowing of the proximal basal cochlea turn (BCT). The CGI as percentual tapering of the BCT turned out as reliable, clinically applicable parameter for identification of patients with an increased risk for a scalar translocation.
CRIS-Team Scopus Importer:2021-03-12
Keywords: anatomical parameters; Cochlear implant; flat-detector computed tomography; insertion trauma; scalar translocation

Image guiding techniques and navigation for TACE, SIRT and TIPS Bildführungstechniken und Navigation bei TACE, SIRT und TIPS - Adamus, R.; Pfister, Marcus; Uder, Michael; Loose, R. W. (Radiologe, 2013)
Clinical/methodical issue: To avoid non-targeted embolization in liver tumors, arteries important for embolization must be detected. In transarterial chemoembolization (TACE) arteries for particle embolization have to be detected and in selective internal radiotherapy (SIRT) extrahepatic arteries which must be protected from embolization have to be detected. In transjugular intrahepatic portosystemic shunt (TIPS) the problem is to achieve an exactly targeted puncture of the portal vein. Standard radiological methods: In TACE and SIRT detection of the vessels is performed from various angles by digital subtraction angiography (DSA). In TIPS puncture is guided by ultrasound or performed blindly. Methodical innovations: Using cone beam CT (CBCT) very small vessels in the liver can be visualized and 2D-3D back projection is able to detect the exact position of the portal vein in TIPS. Achievements: The use of CBCT and 2D-3D back projection significantly enhances navigation of vessels. Practical recommendations: If flat detector technique is available CBCT should be used in TACE and SIRT and 2D-3D navigation needs hardware and software updates. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cone beam computed tomography (CBCT); Digital subtraction angiography (DSA); Embolization; Navigation; Puncture

Image Quality and Detection of Small Focal Liver Lesions in Diffusion-Weighted Imaging Comparison of Navigator Tracking and Free-Breathing Acquisition - Saake, Marc; Seuß, Hannes; Riexinger, Andreas; Bickelhaupt, Sebastian; Hammon, Matthias; Uder, Michael; Laun, Frederik Bernd (Investigative Radiology, 2021)
Objectives The aim of this study was to compare intraindividual diffusion-weighted imaging (DWI) of the liver acquired with free breathing (FB) versus navigator triggering (NT) for assessing small focal liver lesions (FLLs) in noncirrhotic patients. Materials and Methods Patients with known or suspected multiple FLLs were prospectively included, and spin-echo echo-planar DWI with NT and FB acquisition was performed (b-values, 50 and 800 s/mm(2) [b50 and b800]). NT and FB DWI sequences with similar acquisitions times were used. Liver and lesion signal-to-noise ratios were measured at b800. The DWI scans were analyzed independently by 2 readers. Liver edge delineation, presence of stair-step artifacts, vessel sharpness, severity of cardiac motion artifacts, overall image quality, and lesion conspicuity were rated with 5-point Likert scales. Small and large FLLs (ie, <1 cm or >= 1 cm) were rated separately for lesion conspicuity. The FLL detectability was estimated by comparing the number of lesions visible with FB to those visible with NT. Results Forty-three patients were included in the study. The FB acquisition performed better in terms of severity of cardiac motion artifacts. The NT performed better in terms of liver edge delineation and vessel sharpness. Little difference was found for stair-step artifact, overall image quality, and conspicuity of large FLL, whereas the conspicuity of small FLL was better for NT. For small FLL, both readers found more lesions with NT in 11 cases at b800. For large FLL, this effect was much less pronounced (1 case at b800 reported by 1 of the readers). The mean liver and lesion signal-to-noise ratios were 16.8/41.5 and 19.8/38.4 for NT/FB, respectively. Conclusions Small FLL detection is better with NT. Large FLL detection by FB and NT is similarly good. We conclude that NT should be used.
CRIS-Team WoS Importer:2021-09-03

Image quality assessment using deep learning in high b-value diffusion-weighted breast MRI. - Kapsner, Lorenz; Balbach, Eva; Folle, Lukas; Laun, Frederik Bernd; Nagel, Armin Michael; Liebert, Andrzej; Emons, Julius; Ohlmeyer, Sabine; Uder, Michael; Wenkel, Evelyn; Bickelhaupt, Sebastian (Scientific Reports, 2023)
The objective of this IRB approved retrospective study was to apply deep learning to identify magnetic resonance imaging (MRI) artifacts on maximum intensity projections (MIP) of the breast, which were derived from diffusion weighted imaging (DWI) protocols. The dataset consisted of 1309 clinically indicated breast MRI examinations of 1158 individuals (median age [IQR]: 50 years [16.75 years]) acquired between March 2017 and June 2020, in which a DWI sequence with a high b-value equal to 1500 s/mm2 was acquired. From these, 2D MIP images were computed and the left and right breast were cropped out as regions of interest (ROI). The presence of MRI image artifacts on the ROIs was rated by three independent observers. Artifact prevalence in the dataset was 37% (961 out of 2618 images). A DenseNet was trained with a fivefold cross-validation to identify artifacts on these images. In an independent holdout test dataset (n = 350 images) artifacts were detected by the neural network with an area under the precision-recall curve of 0.921 and a positive predictive value of 0.981. Our results show that a deep learning algorithm is capable to identify MRI artifacts in breast DWI-derived MIPs, which could help to improve quality assurance approaches for DWI sequences of breast examinations in the future.
EVALuna2:539553

Image quality comparison of single-energy and dual-energy computed tomography for head and neck patients: a prospective randomized study - Bedernik, Andreas; Wüst, Wolfgang; May, Matthias; Heiß, Rafael; Uder, Michael; Wiesmüller, Marco (European Radiology, 2022)
Objectives: The aim of this study was to compare the quality of images obtained using single-energy computed tomography (SECT) performed with automated tube voltage adaptation (TVA) with dual-energy CT (DECT) weighted average images. Methods: Eighty patients were prospectively randomized to undergo either SECT with TVA (n = 40, ref. mAs 200) or radiation dose–matched DECT (n = 40, 80/Sn150 kV, ref. mAs tube A 91/tube B 61) on a dual-source CT scanner. Objective image quality was evaluated as dose-normalized contrast-to-noise ratio (CNRD) for the jugular veins relative to fatty tissue and muscle tissue and for muscle tissue relative to fatty issue. For subjective image quality, reproduction of anatomical structures, image artifacts, image noise, spatial resolution, and overall diagnostic acceptability were evaluated at sixteen anatomical substructures using Likert-type scales. Results: Effective radiation dose (ED) was comparable between SECT and DECT study groups (2.9 ± 0.6 mSv/3.1 ± 0.7 mSv, p = 0.5). All examinations were rated as excellent or good for clinical diagnosis. Compared to the CNRD in the SECT group, the CNRD in the DECT group was significantly higher for the jugular veins relative to fatty tissue (7.51/6.08, p < 0.001) and for muscle tissue relative to fatty tissue (4.18/2.90, p < 0.001). The CNRD for the jugular veins relative to muscle tissue (3.33/3.18, p = 0.51) was comparable between groups. Image artifacts were less pronounced and overall diagnostic acceptability was higher in the DECT group (all p = 0.01). Conclusions: DECT weighted average images deliver higher objective and subjective image quality than SECT performed with TVA in head and neck imaging. Key Points: • Weighted average images derived from dual-energy CT deliver higher objective and subjective image quality than single-energy CT using automated tube voltage adaptation in head and neck imaging. • If available, dual-energy CT acquisition may be preferred over automated low tube voltage adopted single-energy CT for both malignant and non-malignant conditions.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Automated tube voltage adaptation; Dual-energy computed tomography; Head and neck imaging; Weighted average dual-energy images

Image quality, diagnostic accuracy, and potential for radiation dose reduction in thoracoabdominal CT, using Sinogram Affirmed Iterative Reconstruction (SAFIRE) technique in a longitudinal study - Scharf, Michael; Brendel, Stephanie; Melzer, Katja; Hentschke, Christian; May, Matthias; Uder, Michael; Lell, Michael (PLoS ONE, 2017)
To step-wise evaluate image quality of sinogram-affirmed iterative reconstruction (SAFIRE) in reduced-dose (RD) thoracoabdominal computed tomography (CT) compared to full-dose (FD) and RD filtered back projection (FBP) in a longitudinal study.122 patients were included in this prospective study. 49 patients (14 men: mean age ± SD, 56±0.4 years; 35 women: 58±1.3 years) completed FD, RD1 (80%-dose) and RD2 (60%-dose) thoracoabdominal CT. Each CT dataset was reconstructed with FBP and SAFIRE. For quantitative image analysis image noise was measured in defined tissue regions. Qualitative image evaluation was performed according to the European Guidelines on Quality criteria for CT. Additionally artifacts, lesion conspicuity, and edge sharpness were assessed.Compared to FD-FBP noise in soft tissue increased by 12% in RD1-FBP and 27% in RD2-FBP reconstructions, whereas SAFIRE lead to a decrease of 28% (RD1) and 17% (RD2), respectively (all p <0.001). Visually sharp reproduction, lesion conspicuity, edge sharpness of pathologic findings, and overall image quality did not differ statistically significant between FD-FBP and RD-SAFIRE datasets. Image quality decreased in RD1- and RD2-FBP compared to FD-FBP, reaching statistically significance in RD2 datasets (p <0.001). In RD1- and RD2-FBP (p <0.001) streak artifacts were noted.Using SAFIRE the reference mAs in thoracoabdominal CT can be reduced by at least 30% in clinical routine without loss of image quality or diagnostic information.
EVALuna2:14645

Imaging Hepatocellular Carcinoma with Dynamic CT Before and After Transarterial Chemoembolization: Optimal Scan Timing of Arterial Phase - Saake, Marc; Lell, Michael; Eller, Achim; Wüst, Wolfgang; Heinz, Marco; Uder, Michael; Schmid, Axel (Academic Radiology, 2015)
The aim of this study was to determine the optimal arterial phase delay for computed tomography imaging of hepatocellular carcinoma (HCC) before and after transarterial chemoembolization (TACE) using a low iodine dose protocol.A total of 39 patients with known HCC were imaged with dynamic computed tomography of the liver (40-second scan duration, 60 mL of contrast medium), both on the same day before TACE and 1 day after TACE. Time attenuation curves of vessels, nonmalignant liver parenchyma, and 62 HCCs were normalized to a uniform aortic contrast arrival and analyzed.Maximal arterial phase HCC to liver contrast was reached between 13 and 17 seconds after aortic contrast arrival, both before and after TACE.Using our low iodine dose protocol, arterial phase imaging of HCC should be performed between 13 and 17 seconds after aortic contrast arrival, both before and after TACE.
EVALuna2:14493

Imaging of muscle injuries in sports medicine - Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Hotfiel, Thilo; Gast, Lena; Nagel, Armin Michael; Roemer, Frank (Die Radiologie, 2023)
Background: Early diagnosis of muscle injuries is indispensable in order to initiate appropriate treatment and to facilitate optimal healing.Purpose: The aim of this review is to provide an update on imaging of muscle injuries in sports medicine with a focus on ultrasound and magnetic resonance imaging (MRI) and to present experimental approaches in addition to routine diagnostic procedures.Materials and methods: A PubMed literature search for the years 2012-2022 using the following keywords was performed: muscle, muscle injury, muscle imaging, muscle injury classification, delayed onset muscle soreness, ultrasound, MRI, sodium MRI, potassium MRI, ultra-high-field MRI, injuries of athletes.Results: Imaging is crucial to confirm and assess the extent of sports-related muscle injuries and may help establishing treatment decisions, which directly affect the prognosis. This is of importance when the diagnosis or grade of injury is unclear, when recovery is taking longer than expected, and when interventional or surgical management may be necessary. In addition to established methods such as B-mode ultrasound and H-1-MRI, individual studies show promising approaches to further improve the imaging of muscle injuries in the future. Prior to the integration of contrast-enhanced ultrasound and X-nuclei into clinical routine, additional studies are needed to validate these techniques further.Conclusion: B-mode ultrasound represents an easily available, cost-effective modality for the initial diagnosis of muscle injuries. MRI is still considered the reference standard and enables an accurate morphological assessment of the extent of the injury. There are still no imaging approaches available for the objective determination of the optimal point of return to play.
CRIS-Team WoS Importer:2023-03-24

Imaging of the head and neck region - Lell, Michael; Mantsopoulos, K.; Uder, Michael; Wüst, Wolfgang (HNO, 2016)
Tumors of the head and neck are predominantly squamous cell carcinomas and those of the salivary glands are predominantly adenocarcinomas, adenoid cystic carcinomas and mucoepidermoid carcinomas. In 2011 the incidence of tumors of the oral cavity and pharynx in Germany was 6839 (5026 male and 1813 female) and of the larynx 1878 (1642 male and 236 female). The incidence of tumors of the nose and paranasal sinuses (467) and salivary glands (470) were much lower (www.krebsdaten.de/abfrage). The primary aim of imaging in head and neck cancer is staging of the disease and a precise assessment of tumor invasion. This information is essential for therapy decision-making (i. e. surgery or radiochemotherapy), planning of the extent of resection and subsequent reconstructive measures and also estimation of functional deficits after therapy. Computed tomography (CT) and magnetic resonance imaging (MRI) are the imaging modalities of choice but both have specific advantages and disadvantages. In certain cases both CT and MRI need to be performed for accurate treatment planning.
EVALuna2:14585

Imaging of the head and neck region - Lell, Michael; Mantsopoulos, K.; Uder, Michael; Wüst, Wolfgang (Radiologe, 2016)
Tumors of the head and neck are predominantly squamous cell carcinomas and those of the salivary glands are predominantly adenocarcinomas, adenoid cystic carcinomas and mucoepidermoid carcinomas. In 2011 the incidence of tumors of the oral cavity and pharynx in Germany was 6839 (5026 male and 1813 female) and of the larynx 1878 (1642 male and 236 female). The incidence of tumors of the nose and paranasal sinuses (467) and salivary glands (470) were much lower ( www.krebsdaten.de/abfrage ). The primary aim of imaging in head and neck cancer is staging of the disease and a precise assessment of tumor invasion. This information is essential for therapy decision-making (i. e. surgery or radiochemotherapy), planning of the extent of resection and subsequent reconstructive measures and also estimation of functional deficits after therapy. Computed tomography (CT) and magnetic resonance imaging (MRI) are the imaging modalities of choice but both have specific advantages and disadvantages. In certain cases both CT and MRI need to be performed for accurate treatment planning.
EVALuna2:14586

Imaging of the musculoskeletal system using low-field magnetic resonance imaging - Pogarell, Tobias; May, Matthias; Nagel, Armin Michael; Uder, Michael; Heiß, Rafael (Radiologe, 2022)
Background Magnetic resonance imaging (MRI) plays a crucial role in musculoskeletal imaging. The high prevalence and pain-related suffering of patients pose a particular challenge concerning availability and turnover times, respectively. Low-field (<= 1.0 T) MRI has the potential to fulfill these needs. However, during the past three decades, high field systems have increasingly replaced low field systems because of their limitations in image quality. Recent technological advancements in high-performance hard- and software promise musculoskeletal imaging with adequate quality at lower field strengths for several regions and indications. Objectives The goal is to provide insight into the advantages and disadvantages of low-field musculoskeletal imaging, discuss the current literature, and include our first experiences with a modern 0.55 T MRI. Materials and methods This review is based on research in various literature databases and our own musculoskeletal imaging experiences with a modern 0.55 T scanner. Conclusion Most publications pertaining to musculoskeletal imaging at low-field strength MRI are outdated, and studies regarding the diagnostic performance of modern low-field MRI systems are needed. These new systems may complement existing high-field systems and make MRI more accessible, even in low-income countries. From our own experience, modern low-field MRI seems to be adequate in musculoskeletal imaging, especially in acute injuries.
CRIS-Team WoS Importer:2022-04-29
Keywords: Field strength; Musculoskeletal injuries; Image quality; Cost; Sustainability

Imaging temporomandibular disorders: Reliability of a novel MRI-based scoring system - Willenbrock, Dorina; Lutz, Rainer; Wüst, Wolfgang; Heiß, Rafael; Uder, Michael; Behrends, Tessa; Wurm, Matthias; Kesting, Marco Rainer; Wiesmüller, Marco (Journal of Cranio-Maxillofacial Surgery, 2022)
The aim of this study was to assess the inter- and intrarater reliability of a recently proposed scoring system for temporomandibular disorders (TMD), based upon radiological findings from magnetic resonance imaging (MRI). Patients with clinically suspected uni- or bilateral TMD, and subsequently conducted MRI examination of both temporomandibular joints, were included in this study. MRI data were independently evaluated by two experienced radiologists according to the DLJ scoring system proposed by Wurm et al., which includes assessment of the following categories: articular disk (prefix ‘D’), direction of disk luxation (prefix ‘L’), and osseous joint alterations (prefix ‘J’). 60 patients (49 female and 11 male) were eligible for analysis. No significant differences were found between both observers regarding ‘D’ and ‘L’ scores (p = 0.13 and p = 0.59, respectively). Significant differences were found for the assessment of subtle osseous changes (‘J0’ category: p = 0.041; ‘J1’ category: p = 0.018). Almost perfect intra- and interrater agreements were found for ‘D’ and ‘L’ categories (intrarater and interrater agreements for ‘D’: κ = 0.92 and κ = 0.84, respectively; intrarater and interrater agreements for ‘L’: κ = 0.93 and κ = 0.89, respectively). However, the assessment of ‘J’ categories revealed only moderate interrater agreement (κ = 0.49). The DLJ scoring system based upon MRI findings is feasible for routine clinical TMD assessment, and may help to simplify interdisciplinary communication between radiologists and clinicians.
CRIS-Team Scopus Importer:2022-04-08
Keywords: DLJ score; Magnetic resonance imaging; MRI; Temporomandibular disorder; TMD

Imaging the Parasinus Region with a Third-Generation Dual-Source CT and the Effect of Tin Filtration on Image Quality and Radiation Dose - Lell, Michael; May, Matthias; Brand, Michael; Eller, A.; Buder, Thomas; Hofmann, Eva Maria; Uder, Michael; Wüst, Wolfgang (American Journal of Neuroradiology, 2015)
CT is the imaging technique of choice in the evaluation of midface trauma or inflammatory disease. We performed a systematic evaluation of scan protocols to optimize image quality and radiation exposure on third-generation dual-source CT.CT protocols with different tube voltage (70-150 kV), current (25-300 reference mAs), prefiltration, pitch value, and rotation time were systematically evaluated. All images were reconstructed with iterative reconstruction (Advanced Modeled Iterative Reconstruction, level 2). To individually compare results with otherwise identical factors, we obtained all scans on a frozen human head. Conebeam CT was performed for image quality and dose comparison with multidetector row CT. Delineation of important anatomic structures and incidental pathologic conditions in the cadaver head was evaluated.One hundred kilovolts with tin prefiltration demonstrated the best compromise between dose and image quality. The most dose-effective combination for trauma imaging was Sn100 kV/250 mAs (volume CT dose index, 2.02 mGy), and for preoperative sinus surgery planning, Sn100 kV/150 mAs (volume CT dose index, 1.22 mGy). "Sn" indicates an additional prefiltration of the x-ray beam with a tin filter to constrict the energy spectrum. Exclusion of sinonasal disease was possible with even a lower dose by using Sn100 kV/25 mAs (volume CT dose index, 0.2 mGy).High image quality at very low dose levels can be achieved by using a Sn100-kV protocol with iterative reconstruction. The effective dose is comparable with that of conventional radiography, and the high image quality at even lower radiation exposure favors multidetector row CT over conebeam CT.
EVALuna2:14481

IMPACT OF CLIMBING ACTIVITY AND AGE ON CARTILAGE STRUCTURAL COMPOSITION OF THE METACARPOPHALANGEAL AND PROXIMAL INTERPHALANGEAL JOINTS AS ASSESSED BY T2 RELAXOMETRY AT 7T MRI - Heiß, Rafael; Bayer, T.; Janka, Rolf Matthias; Brockhoff, Marie-Jo; Uder, Michael; Nagel, Armin Michael; Roemer, Frank (OSTEOARTHRITIS AND CARTILAGE, 2020)
CRIS-Team WoS Importer:2020-05-29

Impact of Contrast Media Concentration on Low-Kilovolt Computed Tomography Angiography: A Systematic Preclinical Approach - Fleischmann, Ulrike; Pietsch, Hubertus; Korporaal, Johannes G.; Flohr, Thomas G.; Uder, Michael; Jost, Gregor; Lell, Michael M. (Investigative Radiology, 2018)
OBJECTIVES: Low peak kilovoltage (kVp) protocols in computed tomography angiography (CTA) demand a review of contrast media (CM) administration practices. The aim of this study was to systematically evaluate different iodine concentrations of CM in a porcine model. MATERIALS AND METHODS: Dynamic 70 kVp CTA was performed on 7 pigs using a third-generation dual-source CT system. Three CM injection protocols (A-C) with an identical total iodine dose and iodine delivery rate (150 mg I/kg, 12 s, 0.75 g I/s) differed in iodine concentration and flow rate (protocol A: 400 mg I/mL, 1.9 mL/s; B: 300 mg I/mL, 2.5 mL/s; C: 150 mg I/mL, 5 mL/s). All protocols were applied in a randomized order and compared intraindividually. Arterial enhancement at different locations in the pulmonary artery, the aorta, and aortic branches was measured over time. Time attenuation curves, peak enhancement, time to peak, and bolus tracking delay times needed for static CTA were calculated. The reproducibility of optimal parameters was tested in single-phase CTA. RESULTS: The heart rates of the pigs were comparable for all protocols (P > 0.7). The injection pressure was significantly higher for protocol A (64 ± 5 psi) and protocol C (55 ± 3 psi) compared with protocol B (39 ± 2 psi) (P < 0.001). Average arterial peak enhancement in the dynamic scans was 359 ± 51 HU (protocol A), 382 ± 36 HU (B), and 382 ± 60 HU (C) (A compared with B and C: P < 0.01; B compared with C: P = 0.995). Time to peak enhancement decreased with increasing injection rate. The delay time for bolus tracking depended on the injection rate as well and was highest for protocol A (4.7 seconds) and lowest for protocol C (3.9 seconds) (P = 0.038). The peak enhancement values of the dynamic scans highly correlated with those of the single-phase CTA scans. CONCLUSIONS: In 70 kVp CTA, 300 mg I/mL iodine concentrations showed to be superior to high-concentration CM when keeping the iodine delivery rate constant. Besides, iodine concentrations as low as 150 mg I/mL can be administered without compromising vascular enhancement. This opens up new possibilities in CM administration.
EVALuna2:34699

Impact of different cephalometric skeletal configurations on anatomic midface parameters in adults - Willershausen, Ines; Ehrenfried, Amelie; Krautkremer, Franziska; Ströbel, Armin; Seidel, Corinna Lesley; Paulsen, Friedrich; Kopp, Markus; Uder, Michael; Gölz, Lina; May, Matthias (Clinical Oral Investigations, 2024)
Objectives: Skull morphology and growth patterns are essential for orthodontic treatment, impacting clinical decision making. We aimed to determine the association of different cephalometric skeletal configurations on midface parameters as measured in 3D CT datasets. Materials and methods: After sample size calculation, a total of 240 fully dentulous patients between 20 and 79 years of age (mean age: 42 ± 15), who had received a CT of the skull within the scope of trauma diagnosis or intracranial bleeding, were retrospectively selected. On the basis of cephalometric analysis, using MPR reconstructions, patients were subdivided into three different vertical skull configurations (brachyfacial, mesofacial, dolichofacial) and the respective skeletal Class I, II, and III relationships. Anatomic parameters were measured using a three-dimensional post-processing console: the thickness of the maxillary and palatine bones as well as the alveolar crest, maxillary body and sutural length, width and height of the hard palate, maxillary facial wall thickness, and masseter muscle thickness and length. Results: Individuals with brachyfacial configurations had a significantly increased palatal and alveolar ridge thicknesses compared to those with dolichofacial- or mesofacial configurations. Brachyfacial configurations presented a significantly increased length and thickness of the masseter muscle (4.599 cm; 1.526 cm) than mesofacial (4.431 cm; 1.466 cm) and dolichofacial configurations (4.405 cm; 1.397 cm) (p < 0.001). Individuals with a skeletal Class III had a significantly shorter palatal length (5.313 cm) than those with Class I (5.406 cm) and Class II (5.404 cm) (p < 0.01). Sutural length was also significantly shorter in Class III (p < 0.05). Conclusions: Skeletal configurations have an impact on parameters of the bony skull. Also, measurable adaptations of the muscular phenotype could result. Clinical relevance: The association between viscerocranial morphology and midface anatomy might be beneficial for tailoring orthodontic appliances to individual anatomy and planning cortically anchored orthodontic appliances.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Anatomy; Cephalometry; Computed tomography; Midface; Orthodontics; Ultra-high-resolution datasets

Impact of post-processing methods on apparent diffusion coefficient values - Zeilinger, Martin Georg; Lell, Michael; Baltzer, Pascal Andreas Thomas; Dörfler, Arnd; Uder, Michael; Dietzel, Matthias (European Radiology, 2016)
The apparent diffusion coefficient (ADC) is increasingly used as a quantitative biomarker in oncological imaging. ADC calculation is based on raw diffusion-weighted imaging (DWI) data, and multiple post-processing methods (PPMs) have been proposed for this purpose. We investigated whether PPM has an impact on final ADC values.Sixty-five lesions scanned with a standardized whole-body DWI-protocol at 3 T served as input data (EPI-DWI, b-values: 50, 400 and 800 s/mm(2)). Using exactly the same ROI coordinates, four different PPM (ADC_1-ADC_4) were executed to calculate corresponding ADC values, given as [10(-3) mm(2)/s] of each lesion. Statistical analysis was performed to intra-individually compare ADC values stratified by PPM (Wilcoxon signed-rank tests: ? = 1 %; descriptive statistics; relative difference/?; coefficient of variation/CV).Stratified by PPM, mean ADCs ranged from 1.136-1.206 *10(-3) mm(2)/s (? = 7.0 %). Variances between PPM were pronounced in the upper range of ADC values (maximum: 2.540-2.763 10(-3) mm(2)/s, ? = 8 %). Pairwise comparisons identified significant differences between all PPM (P <= 0.003; mean CV = 7.2 %) and reached 0.137 *10(-3) mm(2)/s within the 25th-75th percentile.Altering the PPM had a significant impact on the ADC value. This should be considered if ADC values from different post-processing methods are compared in patient studies.o Post-processing methods significantly influenced ADC values. o The mean coefficient of ADC variation due to PPM was 7.2 %. o To achieve reproducible ADC values, standardization of post-processing is recommended.
EVALuna2:14601

Impact of renal denervation on tissue Na(+) content in treatment-resistant hypertension - Ott, Christian; Kopp, Christoph; Dahlmann, Anke; Schmid, Andrea; Linz, Peter; Hammon, Matthias; Ditting, Tilmann; Veelken, Roland; Uder, Michael; Titze, Jens; Schmieder, Roland; Cavallaro, Alexander Josef (Clinical Research in Cardiology, 2017)
Renal denervation (RDN) has been introduced for reducing blood pressure (BP) in treatment-resistant hypertension (TRH). The precise mechanism how RDN exerts its BP-lowering effects are not yet fully understood. It is widely accepted that sodium (Na(+)) plays a crucial role in the pathogenesis of hypertensive disease. However, there is increasing evidence of osmotically inactive Na(+) storage. We investigated the impact of RDN on Na(+) homeostasis using estimation of salt intake, and measurement of tissue Na(+) content.In a study 41 patients with TRH (office BP >=140/90 mmHg and diagnosis confirmed by 24-h ambulatory BP monitoring) underwent RDN. Tissue Na(+) content was assessed non-invasively with 3.0 T magnetic resonance imaging before and 6 months after RDN. In addition, 24-h urinary Na(+) excretion as an estimate of salt intake and spot urine Na(+)/K(+) excretion were assessed. The study was registered at http://www.clinicaltrials.gov (ID: NCT01687725).There was a significant fall in BP (office: -17 ± 20/-10 ± 12 mmHg; 24-h: -11 ± 13/-6 ± 9 mmHg, all p < 0.001) 6 months after RDN. In contrast, tissue Na(+) content of the muscle (20.1 ± 3.9 vs. 20.7 ± 4.0 mmol/L, p = 0.229) and skin (24.4 ± 6.5 vs. 24.8 ± 6.6 mmol/L, p = 0.695) did not change after RDN. Moreover, there was also no change in salt intake after RDN, whereas Na(+)/K(+) ratio only acutely increased.Although RDN resulted in a substantial reduction of BP, tissue Na(+) content of the muscle and skin was not mobilized and reduced. These data indicate that the BP reduction after RDN is unrelated to Na(+) homeostasis.
EVALuna2:3743

Impact of velocity- and acceleration-compensated encodings on signal dropout and black-blood state in diffusion-weighted magnetic resonance liver imaging at clinical TEs - Führes, Tobit; Saake, Marc; Szczepankiewicz, Filip; Bickelhaupt, Sebastian; Uder, Michael; Laun, Frederik Bernd (PLoS ONE, 2023)
Purpose The study aims to develop easy-to-implement concomitant field-compensated gradient waveforms with varying velocity-weighting (M1) and acceleration-weighting (M2) levels and to evaluate their efficacy in correcting signal dropouts and preserving the black-blood state in liver diffusion-weighted imaging. Additionally, we seek to determine an optimal degree of compensation that minimizes signal dropouts while maintaining blood signal suppression. Methods Numerically optimized gradient waveforms were adapted using a novel method that allows for the simultaneous tuning of M1- and M2-weighting by changing only one timing variable. Seven healthy volunteers underwent diffusion-weighted magnetic resonance imaging (DWI) with five diffusion encoding schemes (monopolar, velocity-compensated (M1 = 0), acceleration-compensated (M1 = M2 = 0), 84%-M1–M2-compensated, 67%-M1–M2-compensated) at b-values of 50 and 800 s/mm2 at a constant echo time of 70 ms. Signal dropout correction and apparent diffusion coefficients (ADCs) were quantified using regions of interest in the left and right liver lobe. The blood appearance was evaluated using two five-point Likert scales. Results Signal dropout was more pronounced in the left lobe (19%-42% less signal than in the right lobe with monopolar scheme) and best corrected by acceleration-compensation (8%-10% less signal than in the right lobe). The black-blood state was best with monopolar encodings and decreased significantly (p < 0.001) with velocity- and/or acceleration-compensation. The partially M1–M2-compensated encoding schemes could restore the black-blood state again. Strongest ADC bias occurred for monopolar encodings (difference between left/right lobe of 0.41 μm2/ms for monopolar vs. < 0.12 μm2/ms for the other encodings). Conclusion All of the diffusion encodings used in this study demonstrated suitability for routine DWI application. The results indicate that a perfect value for the level of M1–M2-compensation does not exist. However, among the examined encodings, the 84%-M1–M2-compensated encodings provided a suitable tradeoff.
CRIS-Team Scopus Importer:2023-10-20

Implementation of machine learning into clinical breast MRI: Potential for objective and accurate decision-making in suspicious breast masses - Ellmann, Stephan; Wenkel, Evelyn; Dietzel, Matthias; Bielowski, Christian; Vesal, Sulaiman; Maier, Andreas; Hammon, Matthias; Janka, Rolf Matthias; Fasching, Peter; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Uder, Michael; et al. (PLoS ONE, 2020)
We investigated whether the integration of machine learning (ML) into MRI interpretation can provide accurate decision rules for the management of suspicious breast masses. A total of 173 consecutive patients with suspicious breast masses upon complementary assessment (BI-RADS IV/V: n = 100/76) received standardized breast MRI prior to histological verification. MRI findings were independently assessed by two observers (R1/R2: 5 years of experience/no experience in breast MRI) using six (semi-)quantitative imaging parameters. Interobserver variability was studied by ICC (intraclass correlation coefficient). A polynomial kernel function support vector machine was trained to differentiate between benign and malignant lesions based on the six imaging parameters and patient age. Ten-fold cross-validation was applied to prevent overfitting. Overall diagnostic accuracy and decision rules (rule-out criteria) to accurately exclude malignancy were evaluated. Results were integrated into a web application and published online. Malignant lesions were present in 107 patients (60.8%). Imaging features showed excellent interobserver variability (ICC: 0.81–0.98) with variable diagnostic accuracy (AUC: 0.65–0.82). Overall performance of the ML algorithm was high (AUC = 90.1%; BI-RADS IV: AUC = 91.6%). The ML algorithm provided decision rules to accurately rule-out malignancy with a false negative rate <1% in 31.3% of the BI-RADS IV cases. Thus, integration of ML into MRI interpretation can provide objective and accurate decision rules for the management of suspicious breast masses, and could help to reduce the number of potentially unnecessary biopsies.<br

Improved Image Quality in Head and Neck CT Using a 3D Iterative Approach to Reduce Metal Artifact - Wüst, Wolfgang; May, Matthias; Brand, Michael; Bayerl, N.; Krauss, A.; Uder, Michael; Lell, Michael (American Journal of Neuroradiology, 2015)
Metal artifacts from dental fillings and other devices degrade image quality and may compromise the detection and evaluation of lesions in the oral cavity and oropharynx by CT. The aim of this study was to evaluate the effect of iterative metal artifact reduction on CT of the oral cavity and oropharynx.Data from 50 consecutive patients with metal artifacts from dental hardware were reconstructed with standard filtered back-projection, linear interpolation metal artifact reduction (LIMAR), and iterative metal artifact reduction. The image quality of sections that contained metal was analyzed for the severity of artifacts and diagnostic value.A total of 455 sections (mean ± standard deviation, 9.1 ± 4.1 sections per patient) contained metal and were evaluated with each reconstruction method. Sections without metal were not affected by the algorithms and demonstrated image quality identical to each other. Of these sections, 38% were considered nondiagnostic with filtered back-projection, 31% with LIMAR, and only 7% with iterative metal artifact reduction. Thirty-three percent of the sections had poor image quality with filtered back-projection, 46% with LIMAR, and 10% with iterative metal artifact reduction. Thirteen percent of the sections with filtered back-projection, 17% with LIMAR, and 22% with iterative metal artifact reduction were of moderate image quality, 16% of the sections with filtered back-projection, 5% with LIMAR, and 30% with iterative metal artifact reduction were of good image quality, and 1% of the sections with LIMAR and 31% with iterative metal artifact reduction were of excellent image quality.Iterative metal artifact reduction yields the highest image quality in comparison with filtered back-projection and linear interpolation metal artifact reduction in patients with metal hardware in the head and neck area.
EVALuna2:14480

Improved visualization of peripherally inserted central catheters on chest radiographs of neonates using fractional multiscale image processing - Hammon, Rebecca A.; Seuß, Hannes; Hammon, Matthias; Grillhoesl, Christian; Heiß, Rafael; Zeilinger, Martin; Bayerl, Nadine; Vuylsteke, Pieter; Wanninger, Friedrich; Schroth, Michael; Uder, Michael; Rompel, Oliver (BMC Medical Imaging, 2019)
BACKGROUND: Peripherally inserted central catheters (PICCs) provide secure intravenous access for the delivery of life-sustaining medications and nutrition. They are commonly used in pediatrics. Confirmation of correct central catheter tip position is crucial. Verification is usually done by a radiograph. The aim of this study is to evaluate the ability of Fractional Multiscale image Processing (FMP) to detect PICC tips on the digital chest radiographs of neonates. METHODS: A total of 94 radiographs of 47 patients were included in the study. 29 patients were male, 18 were female. The mean age of all examined children was 9.2 days (range 0-99 days). In total, six readers (two radiologists, two residents in radiology, one last year medical student, one neonatologist) evaluated 94 unprocessed and catheter-enhanced radiographs using a 5-point Likert scale (1 = poor catheter tip visualization, 5 = excellent catheter tip visualization). Additionally, the two radiologists evaluated the diagnostic confidence for chest pathologies using a 5-point Likert scale (1 = poor diagnostic confidence, 5 = excellent diagnostic confidence). Radiographs were evaluated on a dedicated workstation. RESULTS: In all cases, the catheter-enhanced radiograph rated higher than (n = 471), or equal (n = 93) to, the unprocessed radiograph when visualizing catheter tips. 87% of the catheter-enhanced radiographs obtained a rating of 4 or higher, while only 42% of unprocessed radiographs received 4 or more points. Regarding diagnostic confidence for chest pathologies one radiologist rated two catheter-enhanced radiographs higher than the unprocessed radiographs, while all other 186 evaluations rated the catheter-enhanced radiographs equal to (n = 78) or lower than (n = 108) the unprocessed radiographs. Only 60% of the catheter-enhanced radiographs yielded a diagnostic confidence of 4 or higher, while 90% of the unprocessed images received 4 or more points. CONCLUSION: Catheter-enhanced digital chest radiographs demonstrate improved visualization of low contrast PICC tips in neonates compared to unprocessed radiographs. Furthermore, they enable detection of accompanying chest pathologies. However, definitive diagnosis of chest pathologies should be made on unprocessed radiographs.
EVALuna2:36095

Improved Visualization of Prostate Cancer Using Multichannel Computed Diffusion Images: Combining ADC and DWI - Hammon, Matthias; Saake, Marc; Laun, Frederik Bernd; Heiß, Rafael; Seuss, Nicola; Janka, Rolf Matthias; Cavallaro, Alexander Josef; Uder, Michael; Seuß, Hannes (Diagnostics, 2022)
(1) Background: For the peripheral zone of the prostate, diffusion weighted imaging (DWI) is the most important MRI technique; however, a high b-value image (hbDWI) must always be evaluated in conjunction with an apparent diffusion coefficient (ADC) map. We aimed to unify the important contrast features of both a hbDWI and ADC in one single image, termed multichannel computed diffusion images (mcDI), and evaluate the values of these images in a retrospective clinical study; (2) Methods: Based on the 2D histograms of hbDWI and ADC images of 70 patients with histologically proven prostate cancer (PCa) in the peripheral zone, an algorithm was designed to generate the mcDI. Then, three radiologists evaluated the data of 56 other patients twice in three settings (T2w images +): (1) hbDWI and ADC; (2) mcDI; and (3) mcDI, hbDWI, and ADC. The sensitivity, specificity, and inter-reader variability were evaluated; (3) Results: The overall sensitivity/specificity were 0.91/0.78 (hbDWI + ADC), 0.85/0.88 (mcDI), and 0.97/0.88 (mcDI + hbDWI + ADC). The kappa-values for the inter-reader variability were 0.732 (hbDWI + ADC), 0.800 (mcDI), and 0.853 (mcDI + hbDWI + ADC). (4) Conclusions: By using mcDI, the specificity of the MRI detection of PCa was increased at the expense of the sensitivity. By combining the conventional diffusion data with the mcDI data, both the sensitivity and specificity were improved.
CRIS-Team WoS Importer:2022-08-12

Improvement of albuminuria after renal denervation - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Ewen, Sebastian; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (International Journal of Cardiology, 2014)
The primary objective of this study was the effect of renal denervation (RDN) on elevated urinary albumin-to-creatinine ratio (UACR) in treatment-resistant hypertensive patients. In addition, patients were stratified according their UACR at baseline into micro- (30-300 mg/g, n=37) and macroalbuminuria (>= 300 mg/g, <2,200 mg/g, n=22).Increased albuminuria indicates cardiovascular and renal damage in hypertension. RDN emerged as an innovative interventional approach to reduce blood pressure (BP) and may thus reduce albumin urinary excretion.Fifty-nine treatment-resistant hypertensive patients with elevated UACR at baseline underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Santa Rosa, CA).In the whole and pre-specified subgroups both office and 24-h ambulatory BP were significantly reduced 6 months after RDN. In parallel, a significant reduction in UACR occurred in all patients (160 (65-496) versus 89 (29-319) mg/g creatinine, p<0.001) and in both subgroups (microalbuminuria: 83 (49-153) versus 58 (17-113) mg/g creatinine, p=0.001; macroalbuminuria: (536 (434-1483) versus 478 (109-1080) mg/g creatinine, p<0.001). In accordance, the prevalence of micro- and macroalbuminuria decreased significantly. Regression analysis revealed a modest positive relationship between the decrease of UACR and the fall of systolic BP (?=0.340, p=0.039) independent of renal function. Renal function remained unchanged after RDN.In summary, following RDN, the magnitude of albuminuria as well as the prevalence of micro- and macroalbuminuria decreased in treatment-resistant hypertensive patients. Since albuminuria is an independent renal and cardiovascular risk factor, our findings suggest a reduction of renal and cardiovascular risk in these patients.
EVALuna2:3681

Improvement of Deep Learning-based Auto-detection of Brain Metastases by Integrating previous MRI Images - Dörfler, Arnd; Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Maier, Andreas; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Improving diagnostic accuracy in assessing pulmonary edema on bedside chest radiographs using a standardized scoring approach - Hammon, Matthias; Dankerl, Peter; Voit-Hoehne, Heinz Leonhard; Sandmair, Martin; Kammerer, Ferdinand Josef; Uder, Michael; Janka, Rolf Matthias (BMC Anesthesiology, 2014)
To assess the value of a score-based system which allows standardized evaluation of pulmonary edema on bedside chest radiographs (CXRs) under routine clinical conditions.Seven experienced readers assessed bedside CXRs of ten patients with an extravascular lung water (EVLW)-value of <= 8 mL/kg (range: 4-8 mL/kg; indicates no pulmonary edema) and a series of ten patients with an EVLW-value of >= 15 mL/kg (range: 15-21 mL/kg; = indicates a pulmonary edema) with and without customized software which would permit a standardized assessment of the various indications of pulmonary edema. The software provides a score that identifies patients with and without pulmonary edema. EVLW-values were measured instantly after bedside CXR imaging using a pulse contour cardiac output (PiCCO) system and served as a reference standard. The patients were non-traumatic and not treated with diuretics or dobutamine during bedside CXR imaging and the PiCCO measurements. Mean sensitivity, specificity, positive and negative predictive value, the percentage of overall agreement and the free-marginal multirater kappa value was calculated for both the standard and the standardized score-based approach. The net reclassification index was calculated for each reader as well as for all readers.Evaluation of bedside CXRs by means of the score-based approach took longer (23 ± 12 seconds versus 7 ± 3 seconds without the use of the software) but improved radiologists' sensitivity (from 57 to 77%), specificity (from 90 to 100%) and the free-marginal multirater kappa value (from 0.34 to 0.68). The positive predictive value was raised from 85 to 100% and the negative predictive value from 68 to 81%. A net reclassification index of 0.3 (all readers) demonstrates an improvement in prediction performance gained by the score-based approach. The percentage of overall agreement was 67% with the standard approach and 84% with the software-based approach.The diagnostic accuracy of bedside CXRs to discriminate patients with elevated EVLW-values from those with a normal value can be improved with the use of a standardized score-based approach. The investigated system is freely available as a web-based application (accessible via: http://www.radiologie.uk-erlangen.de/aerzte-und-zuweiser/edema).
EVALuna2:14366

Individual Calculation of Effective Dose and Risk of Malignancy Based on Monte Carlo Simulations after Whole Body Computed Tomography - Kopp, Markus; Loewe, Tobias; Wüst, Wolfgang; Brand, Michael; Wetzl, Matthias; Nitsch, Wolfram; Schmidt, Daniela; Beck, Michael; Schmidt, Bernhard; Uder, Michael; May, Matthias (Scientific Reports, 2020)
Detailed knowledge about radiation exposure is crucial for radiology professionals. The conventional calculation of effective dose (ED) for computed tomography (CT) is based on dose length product (DLP) and population-based conversion factors (k). This is often imprecise and unable to consider individual patient characteristics. We sought to provide more precise and individual radiation exposure calculation using image based Monte Carlo simulations (MC) in a heterogeneous patient collective and to compare it to phantom based MC provided from the National Cancer Institute (NCI) as academic reference. Dose distributions were simulated for 22 patients after whole-body CT during Positron Emission Tomography-CT. Based on MC we calculated individual Lifetime Attributable Risk (LAR) and Excess Relative Risk (ERR) of cancer mortality. EDMC was compared to EDDLP and EDNCI. EDDLP (13.2 ± 4.5 mSv) was higher compared to EDNCI (9.8 ± 2.1 mSv) and EDMC (11.6 ± 1.5 mSv). Relative individual differences were up to −48% for EDMC and −44% for EDNCI compared to EDDLP. Matching pair analysis illustrates that young age and gender are affecting LAR and ERR significantly. Because of these uncertainties in radiation dose assessment automated individual dose and risk estimation would be desirable for dose monitoring in the future.
CRIS-Team Scopus Importer:2020-06-23

Influence of Artifact Corrections on MRI Signal Intensity Ratios for Assessment of Gadolinium Brain Retention - Saake, Marc; Hepp, Tobias; Schmidle, Alexandra; Wüst, Wolfgang; Heiß, Rafael; Dörfler, Arnd; Uder, Michael; Bäuerle, Tobias (Academic Radiology, 2019)
Rationale and Objectives: Differences in brain signal intensity ratios (SIRs) of deep brain nuclei in T1-weighted (T1w) magnetic resonance images were reported as an indicator of gadolinium brain retention. Variable methods of image reconstruction and inhomogeneity correction for T1w images exist, which might affect the accuracy of SIRs. The aim of our prospective study was to investigate the effect of flow artifact compensation (FAC) and intensity inhomogeneity correction (IIC) on the dentate nucleus-to-pons and globus pallidus-to-thalamus SIRs in study participants who had previously received multiple doses of gadobutrol. Materials and Methods: This study included 76 participants who received five or more gadobutrol-enhanced scans between 2007 and 2017. A control group of 25 participants without gadolinium-based contrast agent application in their patient history was included for comparison. Unenhanced brain magnetic resonance imaging including two T1w spin-echo sequences with and without FAC was performed in all participants. Both sequences were reconstructed with and without IIC. Images were assessed for flow artifacts and SIRs were calculated. Results: Using FAC, a lower proportion of participants had to be excluded from the final analysis of dentate nucleus-to-pons SIR due to flow artifacts (15% versus 46%, p < 0.001). Without IIC, a difference was found between the study and the control group for the dentate nucleus-to-pons ratio (p = 0.004), but not for the same sequence reconstructed with IIC (p = 0.29). For the globus pallidus-to-thalamus ratio, no difference was found between the study and control group. Conclusion: The application of an IIC algorithm has significant impact on brain nuclei SIRs for the assessment of gadolinium brain retention.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Contrast Media; Gadolinium; Magnetic resonance imaging

Influence of Cardiac MR Imaging on DNA Double-Strand Breaks in Human Blood Lymphocytes - Brand, Michael; Ellmann, Stephan; Sommer, Matthias; May, Matthias; Eller, Achim; Wüst, Wolfgang; Engert, Christina; Achenbach, Stephan; Kuefner, Michael A.; Bäuerle, Tobias; Lell, Michael; Uder, Michael (Radiology, 2015)
To evaluate the ability of magnetic resonance (MR) imaging to induce deoxyribonucleic acid (DNA) damage in patients who underwent cardiac MR imaging in daily routine by using ?-H2AX immunofluorescence microscopy.This study complies with the Declaration of Helsinki and was performed according to local ethics committee approval. Informed patient consent was obtained. Blood samples from 45 patients (13 women, 32 men; mean age, 50.3 years [age range, 20-89 years]) were obtained before and after contrast agent-enhanced cardiac MR imaging. MR imaging-induced double-strand breaks (DSBs) were quantified in isolated blood lymphocytes by using immunofluorescence microscopy after staining the phosphorylated histone variant ?-H2AX. Twenty-nine patients were examined with a myocarditis protocol (group A), 10 patients with a stress-testing protocol (group B), and six patients with flow measurements and angiography (group C). Paired t test was performed to compare excess foci before and after MR imaging.The mean baseline DSB level before MR imaging and 5 minutes after MR imaging was, respectively, 0.116 DSB per cell ± 0.019 (standard deviation) and 0.117 DSB per cell ± 0.019 (P = .71). There was also no significant difference in DSBs in these subgroups (group A: DSB per cell before and after MR imaging, respectively, 0.114 and 0.114, P = .91; group B: DSB per cell before and after MR imaging, respectively, 0.123 and 0.124, P = .78; group C: DSB per cell before and after MR imaging, respectively, 0.114 and 0.115, P = .36).By using ?-H2AX immunofluorescence microscopy, no DNA DSBs were detected after cardiac MR imaging.
EVALuna2:12028

Influence of Different Antioxidants on X-Ray Induced DNA Double-Strand Breaks (DSBs) Using ?-H2AX Immunofluorescence Microscopy in a Preliminary Study - Brand, Michael; Sommer, Matthias; Ellmann, Stephan; Wüst, Wolfgang; May, Matthias; Eller, Achim; Vogt, Sabine; Lell, Michael; Kuefner, Michael A.; Uder, Michael (PLoS ONE, 2015)
Radiation exposure occurs in X-ray guided interventional procedures or computed tomography (CT) and ?-H2AX-foci are recognized to represent DNA double-strand breaks (DSBs) as a biomarker for radiation induced damage. Antioxidants may reduce the induction of ?-H2AX-foci by binding free radicals. The aim of this study was to establish a dose-effect relationship and a time-effect relationship for the individual antioxidants on DSBs in human blood lymphocytes.Blood samples from volunteers were irradiated with 10 mGy before and after pre-incubation with different antioxidants (zinc, trolox, lipoic acid, ß-carotene, selenium, vitamin E, vitamin C, N-acetyl-L-cysteine (NAC) and Q 10). Thereby, different pre-incubation times, concentrations and combinations of drugs were evaluated. For assessment of DSBs, lymphocytes were stained against the phosphorylated histone variant ?-H2AX.For zinc, trolox and lipoic acid regardless of concentration or pre-incubation time, no significant decrease of ?-H2AX-foci was found. However, ß-carotene (15%), selenium (14%), vitamin E (12%), vitamin C (25%), NAC (43%) and Q 10 (18%) led to a significant reduction of ?-H2AX-foci at a pre-incubation time of 1 hour. The combination of different antioxidants did not have an additive effect.Antioxidants administered prior to irradiation demonstrated the potential to reduce ?-H2AX-foci in blood lymphocytes.
EVALuna2:14494

Influence of image contrasts and reconstruction methods on the classification of multiple sclerosis-like lesions in simulated sodium magnetic resonance imaging - Ruck, Laurent; Mennecke, Angelika; Wilferth, Tobias; Lachner, Sebastian; Müller, Max; Egger, Nico; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose To evaluate the classifiability of small multiple sclerosis (MS)-like lesions in simulated sodium (Na-23) MRI for different Na-23 MRI contrasts and reconstruction methods. Methods Na-23 MRI and Na-23 inversion recovery (IR) MRI of a phantom and simulated brain with and without lesions of different volumes (V = 1.3-38.2 nominal voxels) were simulated 100 times by adding Gaussian noise matching the SNR of real 3T measurements. Each simulation was reconstructed with four different reconstruction methods (Gridding without and with Hamming filter, Compressed sensing (CS) reconstruction without and with anatomical H-1 prior information). Based on the mean signals within the lesion volumes of simulations with and without lesions, receiver operating characteristics (ROC) were determined and the area under the curve (AUC) was calculated to assess the classifiability for each lesion volume. Results Lesions show higher classifiability in Na-23 MRI than in Na-23 IR MRI. For typical parameters and SNR of a 3T scan, the voxel normed minimal classifiable lesion volume (AUC > 0.9) is 2.8 voxels for Na-23 MRI and 19 voxels for Na-23 IR MRI, respectively. In terms of classifiability, Gridding with Hamming filter and CS without anatomical H-1 prior outperform CS reconstruction with anatomical H-1 prior. Conclusion Reliability of lesion classifiability strongly depends on the lesion volume and the Na-23 MRI contrast. Additional incorporation of H-1 prior information in the CS reconstruction was not beneficial for the classification of small MS-like lesions in Na-23 MRI.
CRIS-Team WoS Importer:2022-11-25

Influence of iodinated contrast media on the activities of histamine inactivating enzymes diamine oxidase and histamine N-methyltransferase in vitro - Kuefner, M. A.; Feurie, J.; Petersen, J.; Uder, Michael; Schwelberger, H. G. (Allergologia Et Immunopathologia, 2014)
Iodinated contrast media can cause pseudoallergic reactions associated with histamine release in significant numbers of patients. To clarify whether these adverse reactions may be aggravated by a compromised histamine catabolism we asked if radiographic contrast agents in vitro inhibit the histamine inactivating enzymes diamine oxidase (DAO) and histamine N-methyltransferase (HMT).Nine iodinated contrast agents were tested in vitro. Following pre-incubation of purified porcine kidney DAO and recombinant human HMT with 0.1-10mM of the respective contrast medium (H2O and specific inhibitors of DAO and HMT as controls) enzyme activities were determined by using radiometric micro assays.None of the contrast media irrespective of their structure showed significant inhibition of the activities of DAO and HMT. Pre-incubation of the enzymes with specific inhibitors led to complete inhibition of the respective enzymatic activity.The iodinated contrast media tested in vitro did not exhibit inhibition of histamine converting enzymes at physiologically relevant concentrations. However due to the in vitro character of this study these results do not directly reflect the in vivo situation.
EVALuna2:14327

Influence of risk-organ-based tube current modulation on CT-induced DNA double-strand breaks in a biological phantom model - Brand, Michael; Wüst, Wolfgang; May, Matthias; Uder, Michael; Sommer, Matthias (Journal of Radiation Research, 2018)
Techniques for dose reduction in computed tomography (CT) are receiving increasing attention. Lowering the tube current in front of the patient, known as risk-organ-based tube current modulation (RTM), represents a new approach. Physical dose parameters can determine the exposure but are not able to assess the biological-X-ray interactions. The purpose of this study was to establish a biological phantom model to evaluate the effect of RTM on X-ray-induced DNA double-strand breaks (DSBs). In breast phantoms and in the location of the spine in an Alderson phantom, isolated human blood lymphocytes were irradiated using a 128-slice CT scanner. A standard thoracic CT protocol (120 kV, 110 ref. mAs, anatomy-based tube current modulation, pitch 0.6, scan length 30 cm) with and without RTM was used. X-ray-induced DSBs were quantified in isolated blood lymphocytes using immunofluorescence microscopy after staining for the phosphorylated histone variant γ-H2AX. Using RTM, the resulting DNA damage reduction was 41% in superficial breast locations (P = 0.0001), 28% in middle breast locations (P = 0.0003) and 29% in lower breast locations (P = 0.0001), but we found a DNA damage increase of 36% in superficial spine locations (P = 0.0001) and of 26% in deep spine locations (P = 0.0001). In summary, we established a biological phantom model that is suitable for detecting DNA damage in distinct organs. In addition, we were able to show that, using RTM, X-ray-induced DNA damage in the breast can be significantly reduced; however, there is a significant increase in DSBs in the location of the spine.
EVALuna2:36108

Influence of saturation effects on biexponential liver intravoxel incoherent motion - Loh, Martin; Führes, Tobit; Stuprich, Christoph; Uder, Michael; Saake, Marc; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2023)
Purpose: Studies on intravoxel incoherent motion (IVIM) imaging in the liver have been carried out with different acquisition protocols. The number of acquired slices and the distances between slices can influence IVIM measurements due to saturation effects, but these effects have often been disregarded. This study investigated differences in biexponential IVIM parameters between two slice settings. Methods: Fifteen healthy volunteers (21–30 years) were examined at a field strength of 3 T. Diffusion-weighted images of the abdomen were acquired with 16 b values (0–800 s/mm2), with four slices for the few slices setting and 24–27 slices for the many slices setting. Regions of interest were manually drawn in the liver. The data were fitted with a monoexponential signal curve and a biexponential IVIM curve, and biexponential IVIM parameters were determined. The dependence on the slice setting was assessed with Student's t test for paired samples (normally distributed IVIM parameters) and the Wilcoxon signed-rank test (non-normally distributed parameters). Results: None of the parameters were significantly different between the settings. For few slices and many slices, respectively, the mean values (SDs) for (Formula presented.) were (Formula presented.) ((Formula presented.)) and (Formula presented.) ((Formula presented.)); for (Formula presented.) they were 29.7% (6.2%) and 27.7% (3.6%); and for (Formula presented.) they were (Formula presented.) ((Formula presented.)) and (Formula presented.) ((Formula presented.)). Conclusion: Biexponential IVIM parameters in the liver are comparable among IVIM studies that use different slice settings, with mostly negligible saturation effects. However, this may not hold for studies that use much shorter TR.
CRIS-Team Scopus Importer:2023-03-24
Keywords: diffusion; IVIM; liver; perfusion; saturation effects

Initial clinical results with a fusion prototype for mammography and three-dimensional ultrasound with a standard mammography system and a standard ultrasound probe - Emons, Julius; Wunderle, Marius; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Gaß, Paul; Fasching, Peter; Langemann, Hanna; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Jud, Sebastian (Acta Radiologica, 2018)
BACKGROUND: Combinations *Equal contributors. of different imaging techniques in fusion devices appear to be associated with improvements in diagnostic assessment. PURPOSE: The aim of this study was to test the feasibility of using an automated standard three-dimensional (3D) ultrasound (US) device fused with standard mammography for the first time in breast cancer patients. MATERIAL AND METHODS: Digital mammograms and 3D automated US images were obtained in 23 patients with highly suspicious breast lesions. A recently developed fusion machine consisting of an ABVS 3D US transducer from an Acuson S2000 machine and a conventional Mammomat Inspiration device (both Siemens Healthcare GmbH, Erlangen, Germany) were used for the purpose. The feasibility of the examinations, imaging coverage, and patients' experience of the procedure were examined. RESULTS: In 15 out of 19 patients, the region of interest (ROI) with the tumor marked in the mammogram was visible on US. The examination was experienced positively by the patients, with no unexpected pain or injury. The examination was time-saving and well tolerated. CONCLUSION: In conclusion, we have shown initial clinical feasibility of an US/radiography fusion prototype with good localization and evaluation of the ROIs. The combined examination was well tolerated. The simultaneous evaluation with mammography and US imaging may be able to improve detection and reduce examiner-related variability.
EVALuna2:34810

Initial experience with a next-generation low-field MRI scanner: Potential for breast imaging? - Dietzel, Matthias; Laun, Frederik Bernd; Heiß, Rafael; Wenkel, Evelyn; Bickelhaupt, Sebastian; Hack, Carolin; Uder, Michael; Ohlmeyer, Sabine (European Journal of Radiology, 2024)
Purpose: Broader clinical adoption of breast magnetic resonance imaging (MRI) faces challenges such as limited availability and high procedural costs. Low-field technology has shown promise in addressing these challenges. We report our initial experience using a next-generation scanner for low-field breast MRI at 0.55T. Methods: This initial cases series was part of an institutional review board-approved prospective study using a 0.55T scanner (MAGNETOM Free.Max, Siemens Healthcare, Erlangen/Germany: height < 2 m, weight < 3.2 tons, no quench pipe) equipped with a seven-channel breast coil (Noras, Höchberg/Germany). A multiparametric breast MRI protocol consisting of dynamic T1-weighted, T2-weighted, and diffusion-weighted sequences was optimized for 0.55T. Two radiologists with 12 and 20 years of experience in breast MRI evaluated the examinations. Results: Twelve participants (mean age: 55.3 years, range: 36–78 years) were examined. The image quality was diagnostic in all examinations and not impaired by relevant artifacts. Typical imaging phenotypes were visualized. The scan time for a complete, non-abbreviated breast MRI protocol ranged from 10:30 to 18:40 min. Conclusion: This initial case series suggests that low-field breast MRI is feasible at diagnostic image quality within an acceptable examination time.
CRIS-Team Scopus Importer:2024-02-23
Keywords: 0.55T; Accessibility; Breast cancer; Breast MRI; Breast neoplasms; Diagnostic techniques and procedures; Diffusion magnetic resonance imaging; Efficiency; Low-field; Low-field system; Magnetic resonance imaging; Point-of-care; Socioeconomic

Injuries of the scapholunate and lunotriquetral ligaments as well as the TFCC in intra-articular distal radius fractures. Prevalence assessed with MDCT arthrography - Klempka, A.; Wagner, M.; Fodor, S.; Prommersberger, K. J.; Uder, Michael; Schmitt, R. (European Radiology, 2016)
To evaluate the prevalence of injuries of the scapholunate and lunotriquetral interosseous ligaments (SLIL, LTIL) as well as the triangular fibrocartilage complex (TFCC) in intra-articular distal radius fractures (iaDRF).Two hundred and thirty-three patients with acute iaDRF underwent MDCT arthrography. The SLIL and LTIL were described as normal, partially or completely ruptured. Major injuries of the SLIL were defined as completely ruptured dorsal segments, those of the LTIL as completely ruptured palmar segments. The TFCC was judged as normal or injured. Interobserver variability was calculated. Injury findings were correlated with the types of iaDRF (AO classification).In 159 patients (68.2 %), no SLIL injuries were seen. Minor SLIL injuries were detected in 54 patients (23.2 %), major injuries in 20 patients (8.6 %). No correlation was found between the presence of SLIL lesions and the types of iaDRF. Minor LTIL injuries were seen in 23 patients (9.9 %), major injuries in only 5 patients (2.2 %). The TFCC was altered in 141 patients (60.5 %). Interobserver variability was high for MDCT arthrography in assessing SLIL and TFC lesions, and fair for LTIL lesions.In iaDRF, prevalence of major injuries of the most relevant SLIL is about 9 % as evaluated with CT arthrography.o The C-shaped SLIL is built of dorsal, middle and palmar segments. o In iaDRF, major SLIL injuries are associated in 8.6 % of the cases. o In iaDRF, the SLIL remains intact in 68.3 % of the cases. o IaDRF and SLIL ruptures can comprehensively be depicted with MDCT arthrography. o A three-compartment approach is recommended to assess intrinsic ligaments and the TFCC.
EVALuna2:14470

Interobserver and intermodality agreement of standardized algorithms for non-invasive diagnosis of hepatocellular carcinoma in high-risk patients: CEUS-LI-RADS versus MRI-LI-RADS - Schellhaas, Barbara; Hammon, Matthias; Strobel, Deike; Pfeifer, Lukas; Kielisch, Christian; Görtz, Rüdiger; Janka, Rolf Matthias; Neurath, Markus; Uder, Michael; Seuß, Hannes; Cavallaro, Alexander Josef (European Radiology, 2018)
OBJECTIVES: We compared the interobserver agreement for the recently introduced contrast-enhanced ultrasound (CEUS)-based algorithm CEUS-LI-RADS (Liver Imaging Reporting and Data System) versus the well-established magnetic resonance imaging (MRI)-LI-RADS for non-invasive diagnosis of hepatocellular carcinoma (HCC) in high-risk patients. METHODS: Focal liver lesions in 50 high-risk patients (mean age 66.2 ± 11.8 years; 39 male) were assessed retrospectively with CEUS and MRI. Two independent observers reviewed CEUS and MRI examinations, separately, classifying observations according to CEUS-LI-RADSv.2016 and MRI-LI-RADSv.2014. Interobserver agreement was assessed with Cohen's kappa. RESULTS: Forty-three lesions were HCCs; two were intrahepatic cholangiocarcinomas; five were benign lesions. Arterial phase hyperenhancement was perceived less frequently with CEUS than with MRI (37/50 / 38/50 lesions = 74%/78% [CEUS; observer 1/observer 2] versus 46/50 / 44/50 lesions = 92%/88% [MRI; observer 1/observer 2]). Washout appearance was observed in 34/50 / 20/50 lesions = 68%/40% with CEUS and 31/50 / 31/50 lesions = 62%/62%) with MRI. Interobserver agreement was moderate for arterial hyperenhancement (ĸ = 0.511/0.565 [CEUS/MRI]) and "washout" (ĸ = 0.490/0.582 [CEUS/MRI]), fair for CEUS-LI-RADS category (ĸ = 0.309) and substantial for MRI-LI-RADS category (ĸ = 0.609). Intermodality agreement was fair for arterial hyperenhancement (ĸ = 0.329), slight to fair for "washout" (ĸ = 0.202) and LI-RADS category (ĸ = 0.218) CONCLUSION: Interobserver agreement is substantial for MRI-LI-RADS and only fair for CEUS-LI-RADS. This is mostly because interobserver agreement in the perception of washout appearance is better in MRI than in CEUS. Further refinement of the LI-RADS algorithms and increasing education and practice may be necessary to improve the concordance between CEUS and MRI for the final LI-RADS categorization. KEY POINTS: • CEUS-LI-RADS and MRI-LIRADS enable standardized non-invasive diagnosis of HCC in high-risk patients. • With CEUS, interobserver agreement is better for arterial hyperenhancement than for "washout". • Interobserver agreement for major features is moderate for both CEUS and MRI. • Interobserver agreement for LI-RADS category is substantial for MRI, and fair for CEUS. • Interobserver-agreement for CEUS-LI-RADS will presumably improve with ongoing use of the algorithm.
EVALuna2:34689

Intramuscular Perfusion Response in Delayed Onset Muscle Soreness (DOMS): A Quantitative Analysis with Contrast-Enhanced Ultrasound (CEUS) - Kellermann, Marion; Heiss, Rafael; Swoboda, Bernd; Gelse, Kolja; Freiwald, Jürgen; Grim, Casper; Nagel, Armin Michael; Uder, Michael; Wildner, Dane; Hotfiel, Thilo (International Journal of Sports Medicine, 2017)
The purpose of this study was to analyse intramuscular perfusion response in ultrastructural muscle lesions, by applying contrast-enhanced ultrasound (CEUS) to a delayed onset muscle soreness (DOMS) model. Results of this analysis were compared to high-resolution 3 Tesla MRI T2-weighted sequences. 14 healthy participants were recruited. Average perfusion parameters, represented as Peak enhancement (contrast agent inflow) and wash-in area under curve (WiAUC) of the gastrocnemius (GM) and soleus muscle (SM) were assessed before (baseline) and 60 h after inducing DOMS by eccentric exercise. Additionally, conventional ultrasound, high-resolution 3T MRI, creatine kinase level, range of motion (ROM) of the ankle joint, calf circumference and muscle soreness data were collected. Perfusion quantification revealed a statistically significant increase of intramuscular perfusion, corresponding to an increase in peak enhancement of 129.6% (p=0.0031) and in WiAUC of 115.2% (p=0.0107) in the gastrocnemius muscle at post-intervention. At follow-up, the MRI investigations showed intramuscular oedema for GM in all participants corresponding to a significant rise in T2 signal intensity (p=0.001) and in T2 time value (p=0.005). CEUS seems to be able to detect intramuscular perfusion changes and therefore may contribute to gaining deeper insight into the histopathology, inflammatory reactions and regeneration processes of ultrastructural muscle lesions.
EVALuna2:10913

iPad-based patient briefing for radiological examinations-a clinical trial - Schlechtweg, Philipp; Hammon, Matthias; Giese, David Andreas; Heberlein, Christian; Uder, Michael; Schwab, Siegfried (Journal of Digital Imaging, 2014)
To analyze if an iPad-based patient briefing can serve as a digital alternative to conventional documentations prior to radiological examinations. One hundred one patients referred for routine MRI were randomized into two groups, who underwent iPad-based and classic written briefing in opposite order. For each briefing completion time, completeness and correctness were noted. Patient's knowledge about the content of either briefing modality was subsequently tested. The influence of patient-related factors on the performance of the electronic briefing (EB) was analyzed. Finally, the patient's subjective impression of the EB was assessed. The mean durations were 4.4 ± 2.2 min for EB and 1.7 ± 1.3 min for the classic briefing (p < 0.01). All iPad briefings were returned entirely filled out, whereas 11 % of the classic forms were returned with missing data. No significant differences in memorization of the briefing's information were objectified. There was a positive correlation between the duration of EB and age (r = 0.53; p < 0.01), whereas a negative correlation was found between computer skills and patient's age (r = -0.55; p < 0.01) or duration of EB (r = -0.62; p < 0.01). More than half of the study patients would prefer EB in the future; another 29 % had no preference at all. Patient briefing on iPads transfers the information for the patients equally well compared to the classic written approach. Although iPad briefing took patients longer to perform, the majority would prefer it to written consent briefings in the future. Nevertheless, measures have to be undertaken to improve the overall acceptance and performance.
EVALuna2:14372

iPads in Breast Imaging - A Phantom Study - Hammon, Matthias; Schlechtweg, Philipp; Schulz-Wendtland, Rüdiger; Uder, Michael; Schwab, Sibylle (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: Modern tablet PCs as the iPad are becoming more and more integrated into medicine. The aim of this study was to evaluate the display quality of iPads regarding digital mammography. Materials and Methods: Three experienced readers compared the display quality of the iPad 2 and 3 with a dedicated 10 megapixel (MP) mammography liquid crystal display (LCD) screen in consensus using the standardized Contrast Detail Mammography (CDMAM) phantom. Phantom fields without agreement between the readers were classified as "uncertain", correct 2 : 1 decisions were classified as "uncertain/readable". In a second step display quality of the three reading devices was judged subjectively in a side by side comparison. Results: The 10 MP screen was superior to both iPads in 4 (phantom-)fields and inferior in 2 fields. Comparing the iPads, version 3 was superior in 4 fields and version 2 was superior in 1 field. However these differences were not significant. Total number of "uncertain" fields did not show significant differences. The number of "uncertain" fields was 15 with the 10 MP screen, 16 with the iPad 2 and 17 with the iPad 3 (p > 0.05), the number of "uncertain/readable" fields was 4, 7 and 8, respectively. Subjective image quality of the iPad 3 and the 10 MP screen was rated superior to the iPad 2. Conclusion: The evaluated iPads, especially in version 3, seem to be adequate to display mammograms in a diagnostic quality and thus could be useful e.g. for patient consultation, clinical demonstration or educational and teaching purposes. However primary mammogram reading should still be performed on dedicated large sized reading screens.
EVALuna2:14368

Iterative Metal Artifact Reduction in Head and Neck CT Facilitates Tumor Visualization of Oral and Oropharyngeal Cancer Obscured by Artifacts From Dental Hardware - Bayerl, Nadine; May, Matthias; Wuest, Wolfgang; Roth, Jessica; Kramer, Manuel; Hofmann, Christian; Schmidt, Bernhard; Uder, Michael; Ellmann, Stephan (Academic Radiology, 2023)
Rationale and Objectives: The purpose of this study was to evaluate the diagnostic utility of iterative metal artifact reduction (iMAR) in computed tomography (CT)-imaging of oral and oropharyngeal cancers when obscured by dental hardware artifacts and to determine the most appropriate iMAR settings for this purpose. Materials and Methods: The study retrospectively enrolled 27 patients (8 female, 19 male; mean age 64 ± 12.7 years) with histologically confirmed oral or oropharyngeal cancer obscured by dental artifacts in contrast-enhanced CT. Raw CT data were reconstructed with ascending iMAR strengths (levels 1/2/3/4/5) and one reconstruction without iMAR (level 0). For subjective analysis, two blinded radiologists rated tumor visualization and artifact severity on a five-point Likert scale. For objective analysis, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and artifact index (AI) were determined. Results: iMAR reconstructions improved the subjective image quality of tumor edge and contrast, and the objective parameters of tumor SNR and CNR, reaching their optimum at iMAR levels 4 and 5 (P < .001). AI decreased with iMAR reconstructions reaching its minimum at iMAR level 5 (P < .001). Tumor detection rates increased 2.4-fold with iMAR 5, 2.1-fold with iMAR 4, and 1.9-fold with iMAR 3 compared to reconstructions without iMAR. Disadvantages such as algorithm-induced artifacts increased significantly with higher iMAR strengths (P < .05), reaching a maximum with iMAR 5. Conclusion: iMAR significantly improves CT imaging of oral and oropharyngeal cancers, as confirmed by both subjective and objective measures, with best results at highest iMAR strengths.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Artifact; Cancer imaging; Computed tomography; Head and neck; Metal artifact reduction

Left Ventricular Structure in Patients With Mild-to-Moderate CKD-a Magnetic Resonance Imaging Study - Schneider, Markus; Scheppach, Johannes B.; Raff, Ulrike; Toncar, Sebastian; Ritter, Christian; Klink, Thorsten; Stoerk, Stefan; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Reinartz, Sebastian D.; Floege, Juergen; et al. (Kidney International Reports, 2019)
Introduction: The high burden of left ventricular (LV) abnormalities in patients with advanced chronic kidney disease (CKD) is well established. However, less is known about the prevalence, patterns, and determinants of LV abnormalities in patients with early CKD.
CRIS-Team WoS Importer:2019-02-21

Local control of perivascular malignant liver lesions using percutaneous irreversible electroporation: initial experiences - Eller, Achim; Schmid, Andrea; Schmidt, Joachim; May, Matthias; Brand, Michael; Saake, Marc; Uder, Michael; Lell, Michael (Cardiovascular and Interventional Radiology, 2015)
This study was designed to assess efficacy and safety in the treatment of perivascular malignant liver lesions using percutaneous, computed tomography (CT)-guided irreversible electroporation (IRE).Fourteen patients (mean age 58 ± 11 years) with 18 malignant liver lesions were consecutively enrolled in this study. IRE was performed in patients not eligible for surgery and lesions abutting large vessels or bile ducts. Follow-up exams were performed using multislice-CT (MS-CT) or MRI.Medium lesion diameter was 20 ± 5 mm. Ten of 14 (71 %) were successfully treated with no local recurrence to date (mean follow-up 388 ± 160 days). One case left initial tumor control unclear and additional RFA was performed 4 weeks after IRE. Complications occurred in 4 of 14 (29 %) cases. In one case, intervention was terminated and abdominal bleeding required laparotomy. In two cases, a postinterventional hematothorax required intervention. In another case, abdominal bleeding could be managed conservatively. No complications related to the bile ducts occurred.Percutaneous IRE seems to be effective in perivascular lesions but is associated with a higher complication rate compared with thermoablative techniques.
EVALuna2:14379

Localized B-0 shimming based on Na-23 MRI at 7 T - Gast, Lena; Henning, Anke; Hensel, Bernhard; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2019)
Purpose To validate the feasibility of localized B-0 shimming based on B-0 maps acquired with sodium (Na-23) MRI. Methods A localized B-0 shimming routine based on a constrained regularized algorithm in combination with Na-23 MRI data acquired with a 3D density-adapted radial readout scheme was implemented on a 7T MR system. Measurements were performed using a dual-tuned Na-23/H-1 head coil. The quality of B-0 maps reconstructed from Na-23 images and the resulting shim values was examined depending on the acquisition duration between 10 minutes and 15 seconds to examine clinical applicability. The B-0 shimming based on Na-23 B-0 maps was performed both for phantom and human head of 6 healthy volunteers, and the resulting B-0 homogeneity was compared with the vendor-provided H-1 MRI-based gradient-echo brain shimming routine. Results The proposed Na-23 MRI-based shimming routine showed a reduction in B-0 variation comparable to the vendor-provided shim both in phantom and in vivo measurements. Within the examined multicompartment phantom, the B-0 variations could be reduced by up to 77% using the Na-23 MRI-based shim. In human head, B-0 variations were reduced by approximately 50% using an acquisition time of 15 seconds for the Na-23 B-0 maps and only 1 iteration of B-0 shimming. Conclusion The Na-23 MRI-based localized B-0 shimming is possible at 7 T within clinically acceptable acquisition durations (< 1 minute). It was shown that using the proposed Na-23 MRI-based shimming approach, the Na-23 image quality at ultrahigh field strength can be strongly improved.
CRIS-Team WoS Importer:2019-10-22

Low-Dose CT of the Paranasal Sinuses: Minimizing X-Ray Exposure with Spectral Shaping - Wüst, Wolfgang; May, Matthias; Saake, Marc; Brand, Michael; Uder, Michael; Lell, Michael (European Radiology, 2016)
Shaping the energy spectrum of the X-ray beam has been shown to be beneficial in low-dose CT. This study's aim was to investigate dose and image quality of tin filtration at 100 kV for pre-operative planning in low-dose paranasal CT imaging in a large patient cohort.In a prospective trial, 129 patients were included. 64 patients were randomly assigned to the study protocol (100 kV with additional tin filtration, 150mAs, 192x0.6-mm slice collimation) and 65 patients to the standard low-dose protocol (100 kV, 50mAs, 128 × 0.6-mm slice collimation). To assess the image quality, subjective parameters were evaluated using a five-point scale. This scale was applied on overall image quality and contour delineation of critical anatomical structures.All scans were of diagnostic image quality. Bony structures were of good diagnostic image quality in both groups, soft tissues were of sufficient diagnostic image quality in the study group because of a high level of noise. Radiation exposure was very low in both groups, but significantly lower in the study group (CTDIvol 1.2 mGy vs. 4.4 mGy, p < 0.001).Spectral optimization (tin filtration at 100 kV) allows for visualization of the paranasal sinus with sufficient image quality at a very low radiation exposure.o Spectral optimization (tin filtration) is beneficial to low-dose parasinus CT o Tin filtration at 100 kV yields sufficient image quality for pre-operative planning o Diagnostic parasinus CT can be performed with an effective dose <0.05 mSv.
EVALuna2:14599

Low-Field Magnetic Resonance Imaging: A New Generation of Breakthrough Technology in Clinical Imaging - Heiß, Rafael; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Bickelhaupt, Sebastian (Investigative Radiology, 2021)
ABSTRACT: Magnetic resonance imaging (MRI) plays a pivotal role in diagnostic imaging. In today's clinical environment, scanners with field strengths of 1.5 to 3 T are most commonly used. However, recent technological advancements might help to augment the clinical usage and availability of MRI via the introduction of high-performance low-field MRI systems (ranging from 0.1-0.55 T in current systems). The combination of low field strength and high-performance hardware is characterized by increased flexibility, excellent quality of results, and reduced cost. This review discusses the multifaceted potential advantages of a new generation of high-performance low-field MRI systems and presents the potential impact of such systems in terms of socioeconomic benefits as well as positive effects on patient care.
CRIS-Team Scopus Importer:2021-11-05

Low-Risk Women with Suspicious Microcalcifications in Mammography-Can an Additional Breast MRI Reduce the Biopsy Rate? - Pöschke, Patrik; Wenkel, Evelyn; Hack, Caroline; Beckmann, Matthias; Uder, Michael; Ohlmeyer, Sabine (Diagnostics, 2023)
Background: In the German Mammography Screening Program, 62% of ductal carcinoma in situ (DCIS) and 38% of invasive breast cancers are associated with microcalcifications (MCs). Vacuum-assisted stereotactic breast biopsies are necessary to distinguish precancerous lesions from benign calcifications because mammographic discrimination is not possible. The aim of this study was to investigate if breast magnetic resonance imaging (MRM) could assist the evaluation of MCs and thus help reduce biopsy rates. Methods: In this IRB-approved study, 58 women (mean age 58 +/- 24 years) with 59 suspicious MC clusters in the MG were eligible for this prospective single-center trial. Additional breast magnetic resonance imaging (MRI) was conducted before biopsy. Results: The breast MRI showed a sensitivity of 86%, a specificity of 84%, a positive predictive value (PPV) of 75% and a negative predictive value (NPV) of 91% for the differentiation between benign and malignant in these 59 MCs found with MG. Breast MRI in addition to MG could increase the PPV from 36% to 75% compared to MG alone. The MRI examination led to nine additional suspicious classified lesions in the study cohort. A total of 55% (5/9) of them turned out to be malignant. A total of 32 of 59 (54 %) women with suspicious MCs and benign histology were classified as non-suspicious by MRI. Conclusion: An additionally performed breast MRI could have increased the diagnostic reliability in the assessment of MCs. Further, in our small cohort, a considerable number of malignant lesions without mammographically visible MCs were revealed.
CRIS-Team WoS Importer:2023-04-14

Lungenbildgebung in der Niederfeld-Magnetresonanztomographie - Hinsen, Maximilian; Heiß, Rafael; Nagel, Armin Michael; Levy, Simon; Uder, Michael; Bickelhaupt, Sebastian; May, Matthias (Radiologe, 2022)
Background: Lung magnetic resonance imaging (MRI) examinations are challenging and have not become established in the routine clinical setting. Recent developments in low-field MRI, combined with computer-assisted algorithms for acquisition and evaluation, promise new perspectives for imaging of pulmonary diseases. Objectives: This review aims to inform about the physical advantages of low-field MRI for imaging the lungs, provide a review of the sparse literature, and present first results from a new low-field MRI scanner. Materials and methods: This article provides information on the physical principles, an review of the literature, and our first experiences in lung imaging on a modern 0.55 T MRI. Conclusion: Low-field MRI (< 1 T) may have technical and economic advantages over higher field strength MRI in lung imaging. The physical preconditions of low-field MRI are advantageous for imaging the lungs due to reduced susceptibility effects, increased transversal relaxation times, and lower specific absorption rates. The lower investment and operating costs may enable increased availability and sustainability. Combining modern sequences and computer-based image processing may expand beyond morphological imaging by providing spatially and temporally resolved functional examinations of the lung parenchyma without ionizing radiation. In critical scenarios, like screening and short-term follow-up examinations, and patients at risk, low-field MRI may bridge the gap. These indications may include acute and chronic pulmonary diseases in pediatric patients and suspected pulmonary embolisms in pregnant women.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Field strength; Functional analysis; Image quality; Low-field system; Lung imaging

Lungenbildgebung in der Niederfeld-Magnetresonanztomographie - Hinsen, Maximilian; Heiß, Rafael; Nagel, Armin Michael; Levy, Simon; Uder, Michael; Bickelhaupt, Sebastian; May, Matthias (Zeitschrift für Pneumologie, 2024)
Background: Lung magnetic resonance imaging (MRI) examinations are challenging and have not become established in the routine clinical setting. Recent developments in low-field MRI, combined with computer-assisted algorithms for acquisition and evaluation, promise new perspectives for imaging of pulmonary diseases. Objectives: This review aims to inform about the physical advantages of low-field MRI for imaging the lungs, provide a review of the sparse literature, and present first results from a new low-field MRI scanner. Materials and methods: This article provides information on the physical principles, an review of the literature, and our first experiences in lung imaging on a modern 0.55 T MRI. Conclusion: Low-field MRI (< 1 T) may have technical and economic advantages over higher field strength MRI in lung imaging. The physical preconditions of low-field MRI are advantageous for imaging the lungs due to reduced susceptibility effects, increased transversal relaxation times, and lower specific absorption rates. The lower investment and operating costs may enable increased availability and sustainability. Combining modern sequences and computer-based image processing may expand beyond morphological imaging by providing spatially and temporally resolved functional examinations of the lung parenchyma without ionizing radiation. In critical scenarios, like screening and short-term follow-up examinations, and patients at risk, low-field MRI may bridge the gap. These indications may include acute and chronic pulmonary diseases in pediatric patients and suspected pulmonary embolisms in pregnant women.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Field strength; Functional analysis; Image quality; Low-field system; Lung imaging

Lung Nodule Detection With Modern Low-Field MRI (0.55 T) in Comparison to CT. - Hinsen, Maximilian; Nagel, Armin M.; May, Matthias; Wiesmüller, Marco; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2024)
OBJECTIVES: The aim of this study was to evaluate the accuracy of modern low-field magnetic resonance imaging (MRI) for lung nodule detection and to correlate nodule size measurement with computed tomography (CT) as reference. MATERIALS AND METHODS: Between November 2020 and July 2021, a prospective clinical trial using low-field MRI at 0.55 T was performed in patients with known pulmonary nodules from a single academic medical center. Every patient underwent MRI and CT imaging on the same day. The primary aim was to evaluate the detection accuracy of pulmonary nodules using MRI with transversal periodically rotated overlapping parallel lines with enhanced reconstruction in combination with coronal half-Fourier acquired single-shot turbo spin-echo MRI sequences. The secondary outcome was the correlation of the mean lung nodule diameter with CT as reference according to the Lung Imaging Reporting and Data System. Nonparametric Mann-Whitney U test, Spearman rank correlation coefficient, and Bland-Altman analysis were applied to analyze the results. RESULTS: A total of 46 participants (mean age ± SD, 66 ± 11 years; 26 women) were included. In a blinded analysis of 964 lung nodules, the detection accuracy was 100% for those ≥6 mm (126/126), 80% (159/200) for those ≥4-<6 mm, and 23% (147/638) for those <4 mm in MRI compared with reference CT. Spearman correlation coefficient of MRI and CT size measurement was r = 0.87 ( P < 0.001), and the mean difference was 0.16 ± 0.9 mm. CONCLUSIONS: Modern low-field MRI shows excellent accuracy in lesion detection for lung nodules ≥6 mm and a very strong correlation with CT imaging for size measurement, but could not compete with CT in the detection of small nodules.
EVALuna2:549646

Machine Learning Algorithms for Early Detection of Bone Metastases in an Experimental Rat Model - Ellmann, Stephan; Seyler, Lisa; Gillmann, Clarissa; Popp, Vanessa; Treutlein, Christoph; Bozec, Aline; Uder, Michael; Bäuerle, Tobias (Journal of Visualized Experiments, 2020)
Machine learning (ML) algorithms permit the integration of different features into a model to perform classification or regression tasks with an accuracy exceeding its constituents. This protocol describes the development of an ML algorithm to predict the growth of breast cancer bone macrometastases in a rat model before any abnormalities are observable with standard imaging methods. Such an algorithm can facilitate the detection of early metastatic disease (i.e., micrometastasis) that is regularly missed during staging examinations. The applied metastasis model is site-specific, meaning that the rats develop metastases exclusively in their right hind leg. The model's tumor-take rate is 60%-80%, with macrometastases becoming visible in magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT) in a subset of animals 30 days after induction, whereas a second subset of animals exhibit no tumor growth. Starting from image examinations acquired at an earlier time point, this protocol describes the extraction of features that indicate tissue vascularization detected by MRI, glucose metabolism by PET/CT, and the subsequent determination of the most relevant features for the prediction of macrometastatic disease. These features are then fed into a model-averaged neural network (avNNet) to classify the animals into one of two groups: one that will develop metastases and the other that will not develop any tumors. The protocol also describes the calculation of standard diagnostic parameters, such as overall accuracy, sensitivity, specificity, negative/positive predictive values, likelihood ratios, and the development of a receiver operating characteristic. An advantage of the proposed protocol is its flexibility, as it can be easily adapted to train a plethora of different ML algorithms with adjustable combinations of an unlimited number of features. Moreover, it can be used to analyze different problems in oncology, infection, and inflammation.
CRIS-Team Scopus Importer:2020-09-11

Magnetic resonance cinematography of the fingers: a 3.0 Tesla feasibility study with comparison of incremental and continuous dynamic protocols - Bayer, Thomas; Adler, Werner; Janka, Rolf Matthias; Uder, Michael; Roemer, Frank (Skeletal Radiology, 2017)
To study the feasibility of magnetic resonance cinematography of the fingers (MRCF) with comparison of image quality of different protocols for depicting the finger anatomy during motion.MRCF was performed during a full flexion and extension movement in 14 healthy volunteers using a finger-gating device. Three real-time sequences (frame rates 17-59 images/min) and one proton density (PD) sequence (3 images/min) were acquired during incremental and continuous motion. Analyses were performed independently by three readers. Qualitative image analysis included Likert-scale grading from 0 (useless) to 5 (excellent) and specific visual analog scale (VAS) grading from 0 (insufficient) to 100 (excellent). Signal-to-noise calculation was performed. Overall percentage agreement and mean absolute disagreement were calculated.Within the real-time sequences a high frame-rate true fast imaging with steady-state free precession (TRUFI) yielded the best image quality with Likert and overall VAS scores of 3.0 ± 0.2 and 60.4 ± 25.3, respectively. The best sequence regarding image quality was an incremental PD with mean values of 4.8 ± 0.2 and 91.2 ± 9.4, respectively. Overall percentage agreement and mean absolute disagreement were 47.9 and 0.7, respectively. No statistically significant SNR differences were found between continuous and incremental motion for the real-time protocols.MRCF is feasible with appropriate image quality during continuous motion using a finger-gating device. Almost perfect image quality is achievable with incremental PD imaging, which represents a compromise for MRCF with the drawback of prolonged scanning time.
EVALuna2:14720

Magnetic resonance-determined sodium removal from tissue stores in hemodialysis patients - Dahlmann, Anke; Dörfelt, Kathrin; Eicher, Florian; Linz, Peter; Kopp, Christoph; Mössinger, Irina; Horn, Stephan; Bueschges-Seraphin, Beatrix; Wabel, Peter; Hammon, Matthias; Eckardt, Kai-Uwe; Kotanko, Peter; et al. (Kidney International, 2015)
We have previously reported that sodium is stored in skin and muscle. The amounts stored in hemodialysis (HD) patients are unknown. We determined whether (23)Na magnetic resonance imaging (sodium-MRI) allows assessment of tissue sodium and its removal in 24 HD patients and 27 age-matched healthy controls. We also studied 20 HD patients before and shortly after HD with a batch dialysis system with direct measurement of sodium in dialysate and ultrafiltrate. Age was associated with higher tissue sodium content in controls. This increase was paralleled by an age-dependent decrease of circulating levels of vascular endothelial growth factor-C (VEGF-C). Older (>60 years) HD patients showed increased sodium and water in skin and muscle and lower VEGF-C levels compared with age-matched controls. After HD, patients with low VEGF-C levels had significantly higher skin sodium content compared with patients with high VEGF-C levels (low VEGF-C: 2.3 ng/ml and skin sodium: 24.3 mmol/l; high VEGF-C: 4.1 ng/ml and skin sodium: 18.2 mmol/l). Thus, sodium-MRI quantitatively detects sodium stored in skin and muscle in humans and allows studying sodium storage reduction in ESRD patients. Age and VEGF-C-related local tissue-specific clearance mechanisms may determine the efficacy of tissue sodium removal with HD. Prospective trials on the relationship between tissue sodium content and hard end points could provide new insights into sodium homeostasis, and clarify whether increased sodium storage is a cardiovascular risk factor.
EVALuna2:3717

Magnetic Resonance Imaging and Bioelectrical Impedance Analysis to Assess Visceral and Abdominal Adipose Tissue - Chaudry, Oliver; Grimm, Alexandra; Friedberger, Andreas; Kemmler, Wolfgang; Uder, Michael; Jakob, Franz; Quick, Harald H.; von Stengel, Simon; Engelke, Klaus (Obesity, 2020)
Objective This study aimed to compare a state-of-the-art bioelectrical impedance analysis (BIA) device with two-point Dixon magnetic resonance imaging (MRI) for the quantification of visceral adipose tissue (VAT) as a health-related risk factor. Methods A total of 63 male participants were measured using a 3-T MRI scanner and a segmental, multifrequency BIA device. MRI generated fat fraction (FF) maps, in which VAT volume, total abdominal adipose tissue volume, and FF of visceral and total abdominal compartments were quantified. BIA estimated body fat mass and VAT area. Results Coefficients of determination between abdominal (r(2) = 0.75) and visceral compartments (r(2) = 0.78) were similar for both groups, but slopes differed by a factor of two. The ratio of visceral to total abdominal FF was increased in older men compared with younger men. This difference was not detected with BIA. MRI and BIA measurements of the total abdominal volume correlated moderately (r(2) = 0.31-0.56), and visceral measurements correlated poorly (r(2) = 0.13-0.44). Conclusions Visceral BIA measurements agreed better with MRI measurements of the total abdomen than of the visceral compartment, indicating that BIA visceral fat area assessment cannot differentiate adipose tissue between visceral and abdominal compartments in young and older participants.
CRIS-Team WoS Importer:2020-01-14

Magnetic resonance imaging for brain stereotactic radiotherapy - A review of requirements and pitfalls - Putz, Florian; Mengling, Veit; Perrin, Rosalind; Masitho, Siti; Weissmann, Thomas; Roesch, Johannes; Bäuerle, Tobias; Janka, Rolf Matthias; Uder, Michael; Amarteifio, Patrick; Doussin, Sylvain; Schmidt, Manuel; et al. (Strahlentherapie und Onkologie, 2020)
Due to its superior soft tissue contrast, magnetic resonance imaging (MRI) is essential for many radiotherapy treatment indications. This is especially true for treatment planning in intracranial tumors, where MRI has a long-standing history for target delineation in clinical practice. Despite its routine use, care has to be taken when selecting and acquiring MRI studies for the purpose of radiotherapy treatment planning. Requirements on MRI are particularly demanding for intracranial stereotactic radiotherapy, where accurate imaging has a critical role in treatment success. However, MR images acquired for routine radiological assessment are frequently unsuitable for high-precision stereotactic radiotherapy as the requirements for imaging are significantly different for radiotherapy planning and diagnostic radiology. To assure that optimal imaging is used for treatment planning, the radiation oncologist needs proper knowledge of the most important requirements concerning the use of MRI in brain stereotactic radiotherapy. In the present review, we summarize and discuss the most relevant issues when using MR images for target volume delineation in intracranial stereotactic radiotherapy.
CRIS-Team WoS Importer:2020-04-10

Mammographic Density and Prediction of Nodal Status in Breast Cancer Patients - Hack, Carolin; Häberle, Lothar; Geisler, K.; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Fasching, Peter; Uder, Michael; Wachter, David; Jud, Sebastian; Löhberg, Christian; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: Nodal status remains one of the most important prognostic factors in breast cancer. The cellular and molecular reasons for the spread of tumor cells to the lymph nodes are not well understood and there are only few predictors in addition to tumor size and multifocality that give an insight into additional mechanisms of lymphatic spread. Aim of our study was therefore to investigate whether breast characteristics such as mammographic density (MD) add to the predictive value of the presence of lymph node metastases in patients with primary breast cancer. Methods: In this retrospective study we analyzed primary, metastasis-free breast cancer patients from one breast center for whom data on MD and staging information were available. A total of 1831 patients were included into this study. MD was assessed as percentage MD (PMD) using a semiautomated method and two readers for every patient. Multiple logistic regression analyses with nodal status as outcome were used to investigate the predictive value of PMD in addition to age, tumor size, Ki-67, estrogen receptor (ER), progesterone receptor (PR), grading, histology, and multi-focality. Results: Multifocality, tumor size, Ki-67 and grading were relevant predictors for nodal status. Adding PMD to a prediction model which included these factors did not significantly improve the prediction of nodal status (p = 0.24, likelihood ratio test). Conclusion: Nodal status could be predicted quite well with the factors multifocality, tumor size, Ki-67 and grading. PMD does not seem to play a role in the lymphatic spread of tumor cells. It could be concluded that the amount of extracellular matrix and stromal cell content of the breast which is reflected by MD does not influence the probability of malignant breast cells spreading from the primary tumor to the lymph nodes. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: breast cancer; estrogen receptor; Ki-67; mammographic density; nodal status; progesterone receptor

Mammographic density as a risk factor for breast cancer in a German case-control study - Heusinger, Katharina; Löhberg, Christian; Häberle, Lothar; Jud, Sebastian; Klingsiek, Peter; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Uder, Michael; May, Matthias; Adamietz, Boris; Schulz-Wendtland, Rüdiger; et al. (European Journal of Cancer Prevention, 2011)
Mammographic percent density (MD) is recognized as one of the strongest risk factors associated with breast cancer. This matched case-control study investigated whether MD represents an independent risk factor. Mammograms were obtained from 1025 breast cancer patients and from 520 healthy controls. MD was measured using a quantitative computer-based threshold method (0-100%). Breast cancer patients had a higher MD than healthy controls (38 vs. 32%, P<0.01). MD was significantly higher in association with factors such as age over 60 years, body mass index (BMI) of 25-30 kg/m, nulliparity or low parity (one to two births). Average MD was inversely associated with age, BMI, parity and positively associated with age at first full-term pregnancy. MD was higher in women with at least one first-degree relative affected, but only among patients and not in the group of healthy controls (P<0.01/P=0.61). In women with an MD of 25% or more, the risk of breast cancer was doubled compared with women with an MD of less than 10% (odds ratio: 2.1; 95% confidence interval: 1.3-3.4; P<0.01); in the postmenopausal subgroup, the risk was nearly tripled (odds ratio: 2.7; 95% confidence interval: 1.6-4.7; P<0.001). This study provides further evidence that MD is an important risk factor for breast cancer. These results indicate strong associations between MD and the risk of breast cancer in a matched case-control study in Germany © 2010 Wolters Kluwer Health.
CRIS-Team Scopus Importer:2021-07-19

Mammographic density is the main correlate of tumors detected on ultrasound but not on mammography - Haeberle, Lothar; Fasching, Peter; Brehm, Barbara; Heusinger, Katharina; Jud, Sebastian; Löhberg, Christian; Hack, Carolin; Preuss, Caroline; Lux, Michael P.; Hartmann, Arndt; Vachon, Celine M.; Meier-Meitinger, Martina; et al. (International Journal of Cancer, 2016)
Although mammography screening programs do not include ultrasound examinations, some diagnostic units do provide women with both mammography and ultrasonography. This article is concerned with estimating the risk of a breast cancer patient diagnosed in a hospital-based mammography unit having a tumor that is visible on ultrasound but not on mammography. A total of 1,399 women with invasive breast cancer from a hospital-based diagnostic mammography unit were included in this retrospective study. For inclusion, mammograms from the time of the primary diagnosis had to be available for computer-assisted assessment of percentage mammographic density (PMD), as well as Breast Imaging Reporting and Data System (BIRADS) assessment of mammography. In addition, ultrasound findings were available for the complete cohort as part of routine diagnostic procedures, regardless of any patient or imaging characteristics. Logistic regression analyses were conducted to identify predictors of mammography failure, defined as BIRADS assessment 1 or 2. The probability that the visibility of a tumor might be masked at diagnosis was estimated using a regression model with the identified predictors. Tumors were only visible on ultrasound in 107 cases (7.6%). PMD was the strongest predictor for mammography failure, but age, body mass index and previous breast surgery also influenced the risk, independently of the PMD. Risk probabilities ranged from 1% for a defined low-risk group up to 40% for a high-risk group. These findings might help identify women who should be offered ultrasound examinations in addition to mammography.
EVALuna2:6818

Management of Complications of Pancreatic Anastomoses - Schmid, Axel; Uder, Michael; Grützmann, Robert; Weber, Georg (Zentralblatt für Chirurgie, 2017)
Background The pancreatic anastomosis may be the Achilles heel in pancreatic surgery. When a postoperative pancreatic fistula develops, be it mild or severe, in some cases life-threatening, POPF-associated complications can occur. Objectives Possibilities for the prophylaxis, diagnosis and therapy of POPF and POPF-associated complications in an interdisciplinary setting. Results Differentiated diagnostic and therapeutic management of POPF grade A - C is supported by recent studies to reduce morbidity and mortality. Depending on time and severity of POPF and POPF-associated complications, a conservative/interventional or surgical approach is indicated. Conclusion With the precise classification of POPF and POPF-associated complications, interdisciplinary diagnostic and therapeutic management can reduce morbidity and mortality after pancreatic surgery.
EVALuna2:15303

Measurement of kidney perfusion by magnetic resonance imaging: Comparison of MRI with arterial spin labeling to para-aminohippuric acid plasma clearance in male subjects with metabolic syndrome - Ritt, Martin; Janka, Rolf Matthias; Schneider, Markus P.; Martirosian, Petros; Hornegger, Joachim; Bautz, Werner; Uder, Michael; Schmieder, Roland (Nephrology Dialysis Transplantation, 2010)
Background. Magnetic resonance imaging with arterial spin labeling (MRI-ASL) is a non-invasive approach to measure organ perfusion. We aimed to examine whether MRI-ASL kidney perfusion measurements are related to measurements of renal plasma flow (RPF) by para-aminohippuric acid (PAH) plasma clearance and whether changes of kidney perfusion in response to treatment with telmisartan can be detected by MRI-ASL.Methods. Twenty-four patients with metabolic syndrome and an estimated creatinine clearance according to Cockroft and Gault of ≥60ml/min were included in the study. Kidney perfusion was assessed by MRI-ASL measurements of a single coronal kidney slice (with flow-sensitive alternating inversion recovery and true fast imaging with steady-state processing sequence) and by measurements of RPF using PAH plasma clearance before and after 2 weeks of treatment with the angiotensin receptor blocker telmisartan. All MRI-ASL examinations were performed on a 1.5 T scanner.Results. Two weeks of therapy with telmisartan led to a significant increase of RPF (from 313 ± 47 to 348 ± 69ml/min/m, P = 0.007) and MRI-ASL kidney perfusion measurements (from 253 ± 20 to 268 ± 25ml/min/100g, P = 0.020). RPF measurements were related with MRI-ASL kidney perfusion measurements (r = 0.575, P < 0.001). Changes of RPF measurements and changes of MRI-ASL kidney perfusion measurements in response to treatment with telmisartan revealed a close relationship when expressed in absolute terms (r = 0.548, P = 0.015) and in percentage changes (r = 0.514, P = 0.025).Conclusions. Perfusion measurement of a single coronal kidney slice by MRI-ASL is able to approximate kidney perfusion and to approximate changes in kidney perfusion due to pharmacological intervention. © 2009 The Author.

Mid-Term Vascular Safety of Renal Denervation Assessed by Follow-up MR Imaging. - Schmid, Axel; Schmieder, Raphael; Lell, Michael; Janka, Rolf Matthias; Veelken, Roland; Schmieder, Roland; Uder, Michael; Ott, Christian (Cardiovascular and Interventional Radiology, 2016)
Renal denervation (RDN) emerged as a treatment option for reducing blood pressure (BP) in patients with treatment-resistant hypertension (TRH). However, concerns have been raised regarding the incidence of late renal artery stenosis or thromboembolism after RDN. The goal of the current study was, therefore, to conduct a prospective clinical trial on the mid-term vascular integrity of the renal arteries and the perfusion of the renal parenchyma assessed by magnetic resonance imaging (MRI) in the follow-up after catheter-based RDN.In our single-centre investigator initiated study, 51 patients with true TRH underwent catheter-based RDN using the Symplicity Flex(TM) catheter (Medtronic Inc., Palo Alto, CA). Follow-up MRI was performed at a median of 11 months (interquartile range 6-18 months) after RDN on a 1.5T MR unit. High-resolution MR angiography (MRA) and MRI results were compared to the baseline digital angiography of renal arteries obtained at time of RDN. In case of uncertainties (N = 2) catheter angiography was repeated.Both office and 24-h ambulatory BP were significantly reduced 6 and 12 months after RDN. Renal function remained unchanged 6 and 12 months after RDN. In all patients, MRA excluded new or progression of pre-existing low grade renal artery stenosis as well as focal aneurysms at the sites of radiofrequency ablation. In none of the patients new segmental perfusion deficits in either kidney were detected on MRI.No vascular or parenchymal complications after radiofrequency-based RDN were detected in 51 patients followed up by MRI.
EVALuna2:3794

Mobile Image Interpretation: Diagnostic Performance of CT Exams Displayed on a Tablet Computer in Detecting Abdominopelvic Hemorrhage - Schlechtweg, Philipp; Kammerer, Ferdinand J.; Seuß, Hannes; Uder, Michael; Hammon, Matthias (Journal of Digital Imaging, 2015)
To investigate whether abdominopelvic hemorrhage shown on computed tomography (CT) images can be diagnosed with the same accuracy on a tablet computer as on a dedicated reading display. One hundred patients with a clinical suspicion of abdominopelvic hemorrhage that underwent biphasic CT imaging were retrospectively read by two readers on a dedicated reading display (reference standard) and on a tablet computer (iPad Air). Reading was performed in a dedicated reading room with ambient light conditions. Image evaluation included signs of an active hemorrhage (extravasation of contrast media) and different signs indicating a condition after abdominopelvic hemorrhage (hematoma, intestinal clots, vessel stump, free abdominopelvic fluid with a mean Hounsfield unit value >20, and asymmetric muscle volume indicating intramuscular hemorrhage). Sensitivity, specificity, and positive and negative predictive values (PPV/NPV) were calculated for the tablet-based reading. Active abdominopelvic hemorrhage (n = 72) was diagnosed with the tablet computer with a sensitivity of 0.96, a specificity of 0.93, a PPV of 0.97, and an NPV of 0.90. The results for the detection of the signs indicating a condition after abdominopelvic hemorrhage range from 0.83 to 1.00 in the case of sensitivity, from 0.95 to 1.00 in the case of specificity, from 0.94 to 1.00 in the case of the PPV, and from 0.96 to 1.00 in the case of the NPV. Abdominopelvic hemorrhage shown on CT images can be diagnosed on a tablet computer with a high diagnostic accuracy allowing mobile on-call diagnoses. This may be helpful because an early and reliable diagnosis at any time is crucial for an adequate treatment strategy.
EVALuna2:14361

Mobile Workflow in Computed Tomography of the Chest - Wetzl, Matthias; Weller, Melanie; Heiß, Rafael; Schrüfer, Eleni; Wüst, Wolfgang; Thierfelder, Carsten; Lerch, Daniel; Amarteifio, Patrick; Uder, Michael; May, Matthias; Cavallaro, Alexander Josef (Journal of Medical Systems, 2018)
A CT system with a tablet as mobile user interface and a wireless remote control for positioning and radiation release has recently been presented. Our aim was to evaluate the effects of a mobile CT examination workflow on the radiographers' performance compared to conventional examinations. A prototype of a radiation protection cabin was installed besides the gantry of a CT system. The CT system was equipped with a simplified user interface on a portable tablet and a mobile remote control. 98 patients with an indication for CT of the chest were randomly assigned to examination using the mobile devices (study group, n = 47) or using the conventional stationary workflow on the console (reference group, n = 51). Three ceiling mounted fisheye cameras were used for motion tracking of the radiographers, two in the examination room and one in the control room. Relative density of detection heat-maps and area counts were assessed using a dedicated software tool to quantify radiographers' movements. Duration of each task of the examination was manually recorded using a stopwatch. In the reference group 25% of the area counts were located inside of the examination room, while it was 48% in the study group. The time spent in the same room with the patient increased from 3:06 min (29%) to 6:01 min (57%) using the mobile workflow (p < 0.05), thereof 0:59 min (9%) were spent in moderate separation with maintained voice and visual contact in the radiation protection cabin. Heat-maps showed an increase of the radiographer's working area, indicating a higher freedom of movement. Total duration of the examination was slightly less in the study group without statistical significance (median time: study 10:36, reference 10:50 min; p = 0.29). A mobile CT examination transfers the radiographers' interaction with the scanner from the control room into the examination room. There, radiographers' freedom of movement is higher, without any tradeoffs regarding the examination duration.
EVALuna2:36096

Model-based pancreas segmentation in portal venous phase contrast-enhanced CT images - Hammon, Matthias; Cavallaro, Alexander Josef; Erdt, Marius; Dankerl, Peter; Kirschner, Matthias; Drechsler, Klaus; Wesarg, Stefan; Uder, Michael; Janka, Rolf Matthias (Journal of Digital Imaging, 2013)
This study aims to automatically detect and segment the pancreas in portal venous phase contrast-enhanced computed tomography (CT) images. The institutional review board of the University of Erlangen-Nuremberg approved this study and waived the need for informed consent. Discriminative learning is used to build a pancreas tissue classifier incorporating spatial relationships between the pancreas and surrounding organs and vessels. Furthermore, discrete cosine and wavelet transforms are used to build texture features to describe local tissue appearance. Classification is used to guide a constrained statistical shape model to fit the data. The algorithm to detect and segment the pancreas was evaluated on 40 consecutive CT data that were acquired in the portal venous contrast agent phase. Manual segmentation of the pancreas was carried out by experienced radiologists and served as reference standard. Threefold cross validation was performed. The algorithm-based detection and segmentation yielded an average surface distance of 1.7 mm and an average overlap of 61.2 % compared with the reference standard. The overall runtime of the system was 20.4 min. The presented novel approach enables automatic pancreas segmentation in portal venous phase contrast-enhanced CT images which are included in almost every clinical routine abdominal CT examination. Reliable pancreatic segmentation is crucial for computer-aided detection systems and an organ-specific decision support. © 2013 The Author(s).
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computed tomography; Computer-assisted detection; Machine learning; Pancreas; Segmentation

Modern low-field MRI - Pogarell, Tobias; Heiß, Rafael; Janka, Rolf Matthias; Nagel, Armin Michael; Uder, Michael; Roemer, Frank (Skeletal Radiology, 2024)
This narrative review explores recent advancements and applications of modern low-field (≤ 1 Tesla) magnetic resonance imaging (MRI) in musculoskeletal radiology. Historically, high-field MRI systems (1.5 T and 3 T) have been the standard in clinical practice due to superior image resolution and signal-to-noise ratio. However, recent technological advancements in low-field MRI offer promising avenues for musculoskeletal imaging. General principles of low-field MRI systems are being introduced, highlighting their strengths and limitations compared to high-field counterparts. Emphasis is placed on advancements in hardware design, including novel magnet configurations, gradient systems, and radiofrequency coils, which have improved image quality and reduced susceptibility artifacts particularly in musculoskeletal imaging. Different clinical applications of modern low-field MRI in musculoskeletal radiology are being discussed. The diagnostic performance of low-field MRI in diagnosing various musculoskeletal pathologies, such as ligament and tendon injuries, osteoarthritis, and cartilage lesions, is being presented. Moreover, the discussion encompasses the cost-effectiveness and accessibility of low-field MRI systems, making them viable options for imaging centers with limited resources or specific patient populations. From a scientific standpoint, the amount of available data regarding musculoskeletal imaging at low-field strengths is limited and often several decades old. This review will give an insight to the existing literature and summarize our own experiences with a modern low-field MRI system over the last 3 years. In conclusion, the narrative review highlights the potential clinical utility, challenges, and future directions of modern low-field MRI, offering valuable insights for radiologists and healthcare professionals seeking to leverage these advancements in their practice.
CRIS-Team Scopus Importer:2024-03-01
Keywords: 0.55 Tesla; Field strength; Joints; Knee; Low-field; MRI; Musculoskeletal radiology

Morphological, functional, and molecular assessment of breast cancer bone metastases by experimental ultrasound techniques compared with magnetic resonance imaging and histological analysis - Heinen, Henrik; Seyler, Lisa; Popp, Vanessa; Hellwig, Konstantin; Bozec, Aline; Uder, Michael; Ellmann, Stephan; Bäuerle, Tobias (Bone, 2021)
Background: The imaging of bone metastases, which is regularly performed by cross-sectional modalities, is clinically vital when characterizing and staging osseous lesions. In this paper, we aimed to establish a novel methodology using experimental ultrasound (US) techniques to assess the morphological, functional, and molecular features of breast cancer bone metastases in an animal model, compared with magnetic resonance imaging (MRI) and histological analysis. Materials and methods: Nude rats were implanted intra-arterially with MDA-MB-231 breast cancer cells to induce osteolytic metastasis in their right hind legs. Once tumors had developed, an experimental US technique using automatic 3D scanning and MRI were performed. For assessment of perfusion, functional imaging techniques included contrast-enhanced US (CEUS) and dynamic contrast-enhanced MRI (DCE-MRI). For molecular ultrasound, anti-VEGFR2 conjugated microbubbles were applied and correlated with immunostaining for VEGFR2 expression. Results: 3D US enabled the automatic assessment of osteolytic lesions, including the largest tumor diameters along the x-, y- and z-axes as well as the segmented tumor volumes, without significant differences between US and MRI (p > 0.18). The CEUS and DCE-MRI of osseous lesions showed corresponding results for the parameters peak enhancement, wash-in area under the curve (both, r > 0.5) and wash-in perfusion index (r > 0.3) when differentiating between tumor, necrotic tissue and healthy muscle tissue (all, p < 0.01). Finally, molecular US allowed the non-invasive assessment of increased VEGFR2 expression in skeletal lesions compared with surrounding muscle tissue (p = 0.03), while a control antibody could not discriminate between these tissues (p = 0.44)—a factor which was confirmed by histological analysis. Conclusion: To the best of our knowledge, this is the first report on an imaging protocol for breast cancer bone metastasis using an experimental US scanner. Therefore, we present a novel methodology to characterize these osseous lesions on the morphological, functional, and molecular level in correlation with MRI and histological analysis.
CRIS-Team Scopus Importer:2021-01-01
Keywords: Animal model; Bone metastases; Imaging; Magnetic resonance imaging; Microbubbles; Ultrasound

Morphology of the distal thoracic duct and the right lymphatic duct in different head and neck pathologies: an imaging based study - Kammerer, Ferdinand J.; Schlude, Benedikt; Kuefner, Michael A.; Schlechtweg, Philipp; Hammon, Matthias; Uder, Michael; Schwab, Siegfried (Head & Face Medicine, 2016)
The purpose of this study was to assess the influence of head and neck pathologies on the detection rate, configuration and diameter of the thoracic duct (TD) and right lymphatic duct (RLD) in computed tomography (CT) of the head and neck.One hundred ninety-seven patients were divided into the subgroups "healthy", "benign disease" and "malignant disease". The interpretation of the images was performed at a slice thickness of 3 mm in the axial and coronal plane. In each case we looked for the distal part of the TD and RLD respectively and subsequently evaluated their configuration (tubular, sacciform, dendritic) as well as their maximum diameter and correlated the results with age, gender and diagnosis group.The detection rate in the study population was 81.2 % for the TD and 64.2 % for the RLD and did not differ significantly in any of the subgroups. The predominant configuration was tubular. The configuration distribution did not differ significantly between the diagnosis groups. The mean diameter of the TD was 4.79 ± 2.41 mm and that of the RLD was 3.98 ± 1.96 mm. No significant influence of a diagnosis on the diameter could be determined.There is no significant influence of head/neck pathologies on the CT detection rate, morphology or size of the TD and RLD. However our study emphasizes that both the RLD and the TD are detectable in the majority of routine head and neck CTs and therefore reading physicians and radiologists should be familiar with their various imaging appearances.
EVALuna2:14477

Motion-corrected 23Na MRI of the human brain using interleaved 1H 3D navigator images - Wilferth, Tobias; Müller, Max; Gast, Lena; Ruck, Laurent; Meyerspeer, Martin; Kolkovsky, Alfredo L. Lopez; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2022)
Purpose: To evaluate the feasibility of motion correction for sodium (23Na) MRI based on interleaved acquired 3D proton (1H) navigator images. Methods: A 3D radial density-adapted sequence for interleaved 23Na/1H MRI was implemented on a 7 Tesla whole-body MRI system. The 1H data obtained during the 23Na acquisition were used to reconstruct 140 navigator image volumes with a nominal spatial resolution of (2.5 mm)3 and a temporal resolution of 6 s. The motion information received from co-registration was then used to correct the 23Na image dataset, which also had a nominal spatial resolution of (2.5 mm)3. The approach was evaluated on six healthy volunteers, whose motion during the scans had different intensities and characteristics. Results: Interleaved acquisition of two nuclei did not show any relevant influence on image quality (SNR of 13.0 for interleaved versus 13.2 for standard 23Na MRI and 176.4 for interleaved versus 178.0 for standard 1H MRI). The applied motion correction increased the consistency between two consecutive scans for all examined volunteers and improved the image quality for all kinds of motion. The SD of the differences ranged between 2.30% and 6.96% for the uncorrected and between 2.13% and 2.67% for the corrected images. Conclusion: The feasibility of interleaved acquired 1H navigator images to be used for retrospective motion correction of 23Na images was successfully demonstrated. The approach neither affected the 23Na image quality nor elongated the scan time and can therefore be an important tool to improve the accuracy of quantitative 23Na MRI.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 23Na MRI; 7 Tesla; brain MRI; interleaved dual-nuclear MRI; motion correction; ultrahigh field strength

MRI Brain Signal Intensity and Relaxation Times in Individuals with Prior Exposure to Gadobutrol - Saake, Marc; Schmidle, Alexandra; Kopp, Markus; Hanspach, Jannis; Hepp, Tobias; Nagel, Armin Michael; Dörfler, Arnd; Uder, Michael; Bäuerle, Tobias; Laun, Frederik Bernd (Radiology, 2019)
Purpose: To perform follow-up brain MRI in volunteer participants who had previously received multiple doses of gadobutrol and to assess for changes in signal intensities and relaxation times.
CRIS-Team WoS Importer:2019-03-06

MRI-guided core biopsy of the prostate in the supine position - Introduction of a simplified technique using large-bore magnet systems - Schwab, Siegfried; Kuefner, Michael A.; Adamietz, Boris; Engelhard, Karl; Keck, Bastian; Kunath, Frank; Wach, Sven; Wullich, Bernd; Uder, Michael; Engehausen, Dirk (European Radiology, 2013)
Objectives: To introduce a simplified technique for MRI-guided core biopsies (MRGB) of the prostate in the supine position using large-bore magnet systems. Methods: Fifty men with a history of negative transrectal ultrasound-guided biopsies underwent MRGB in either a 1.5-T (13/50) or 3.0-T (37/50) wide-bore MRI unit. MRGBs were conducted with the patients in a supine position using a dedicated MR-compatible biopsy device. Results: We developed a dedicated positioning device for the supine position. Using this device, the biopsies were performed successfully in all patients. Apart from minor rectal bleeding, only one patient developed a major side effect (urosepsis). Histology revealed prostate cancer in 25/50 (50 %) patients. Conclusions: The new technique appears feasible. Its major advantage is the more comfortable and patient-friendly supine position during the biopsy without the need to modify the MRI system's patient table. Key Points: • A novel positioning device for MRI-guided prostate biopsies has been developed. • Biopsies can be performed in the patient-friendly supine position. • The positioning device can be utilised without modifying the MRI's patient table. © 2012 European Society of Radiology.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Biopsy; Magnetic resonance imaging; Prostate cancer; Supine position

Mri of finger pulleys at 7t—direct characterization of pulley ruptures in an ex vivo model - Heiß, Rafael; Librimir, Alexander; Lutter, Christoph; Janka, Rolf Matthias; Kuerten, Stefanie; Roemer, Frank; Nagel, Armin Michael; Uder, Michael; Bayer, Thomas (Diagnostics, 2021)
The aim of this study was to evaluate 7 Tesla (7T) magnetic resonance imaging (MRI) for direct visualization and specific characterization of the finger flexor pulleys A2, A3, and A4 before and after ex vivo pulley rupture. Thirty fingers of human cadavers were examined before and after pulley disruption with a 26 min clinical 7T pulse sequence protocol. Images were assessed by two experienced radiologists for the presence of pulley rupture. Injury characterization included definition of rupture location, morphology, and complications. Image quality was evaluated according to a 4-point Likert-type scale from “not evaluable” to “excellent”. Macroscopic preparations were used as the reference standard. Direct characterization of intact A2, A3, and A4 pulleys and the corresponding pulley lesions was possible in all cases. The rupture location was distributed equally at the radial, ulnar, and central parts of the pulleys. A dislocation and intercalation of the pulley stump between the flexor tendon and finger phalanges was observed as a complication in 62.5% of cases. The average Likert score for direct visualization of pulleys was 2.67 before rupture and 2.79 after rupture creation, demonstrating adequate image quality for routine application. 7T MRI enables a direct characterization of A2, A3, and A4 pulleys before and after artificial disruption, including the definition of rupture morphology and location as well as the detection of rupture complications. This promises a precise presurgical evaluation of pulley injuries and complicated pulley stump dislocations.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Climbing; Finger flexor pulleys; Imaging; Injury classification; Ultra-high-field MRI

MRI of Potassium and Sodium Enables Comprehensive Analysis of Ion Perturbations in Skeletal Muscle Tissue After Eccentric Exercise. - Gast, Lena; Baier, Laura Marie; Meixner, Christian; Chaudry, Oliver; Engelke, Klaus; Uder, Michael; Nagel, Armin Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: The aims were to investigate if potassium ( 39 K) magnetic resonance imaging (MRI) can be used to analyze changes in the apparent tissue potassium concentration (aTPC) in calf muscle tissue after eccentric exercise and in delayed-onset muscle soreness, and to compare these to corresponding changes in the apparent tissue sodium concentration (aTSC) measured with sodium ( 23 Na) MRI. MATERIALS AND METHODS: Fourteen healthy subjects (7 female, 7 male; 25.0 ± 2.8 years) underwent 39 K and 23 Na MRI at a 7 T MR system, as well as 1 H MRI at a 3 T MR system. Magnetic resonance imaging data and blood samples were collected at baseline (t0), directly after performing eccentric exercise (t1) and 48 hours after exercise (t2). Self-reported muscle soreness was evaluated using a 10-cm visual analog scale for pain (0, no pain; 10, worst pain) at t0, t1, and t2. Quantification of aTPC/aTSC was performed after correcting the measured 39 K/ 23 Na signal intensities for partial volume and relaxation effects using 5 external reference phantoms. Edema volume and 1 H T 2 relaxation times were determined based on the 1 H MRI data. Participants were divided according to their increase in creatine kinase (CK) level into high (CK t2 ≥ 10·CK t0 ) and low CK (CK t2 < 10·CK t0 ) subjects. RESULTS: Blood serum CK and edema volume were significantly increased 48 hours after exercise compared with baseline ( P < 0.001). Six participants showed a high increase in blood serum CK level at t2 relative to baseline, whereas 8 participants had only a low to moderate increase in blood serum CK. All participants reported increased muscle soreness both at rest and when climbing stairs at t1 (0.4 ± 0.7; 1.4 ± 1.2) and t2 (1.6 ± 1.4; 4.8 ± 1.9) compared with baseline (0 ± 0; 0 ± 0). Moreover, aTSC was increased at t1 in exercised muscles of all participants (increase by 57% ± 24% in high CK, 73% ± 33% in low CK subjects). Forty-eight hours after training, subjects with high increase in blood serum CK still showed highly increased aTSC (increase by 79% ± 57% compared with t0). In contrast, aTPC at t2 was elevated in exercised muscles of low CK subjects (increase by 19% ± 11% compared with t0), in which aTSC had returned to baseline or below. Overall, aTSC and aTPC showed inverse evolution, with changes in aTSC being approximately twice as high as in aTPC. CONCLUSIONS: Our results showed that 39 K MRI is able to detect changes in muscular potassium concentrations caused by eccentric exercise. In combination with 23 Na MRI, this enables a more holistic analysis of tissue ion concentration changes.
EVALuna2:520477

MRI of Temporomandibular Joint Disorders: A Comparative Study of 0.55 T and 1.5 T MRI. - Kopp, Markus; Wiesmüller, Marco; Buchbender, Mayte; Kesting, Marco Rainer; Nagel, Armin Michael; May, Matthias; Uder, Michael; Roemer, Frank; Heiß, Rafael (Investigative Radiology, 2024)
OBJECTIVES: Temporomandibular disorders (TMDs) are common and may cause persistent functional limitations and pain. Magnetic resonance imaging (MRI) at 1.5 and 3 T is commonly applied for the evaluation of the temporomandibular joint (TMJ). No evidence is available regarding the feasibility of modern low-field MRI for the assessment of TMDs. The objective of this prospective study was to evaluate the image quality (IQ) of 0.55 T MRI in direct comparison with 1.5 T MRI. MATERIALS AND METHODS: Seventeen patients (34 TMJs) with suspected intraarticular TMDs were enrolled, and both 0.55 and 1.5 T MRI were performed on the same day. Two senior readers independently evaluated the IQ focusing on the conspicuity of disc morphology (DM), disc position (DP), and osseous joint morphology (OJM) for each joint. We analyzed the IQ and degree of artifacts using a 4-point Likert scale (LS) at both field strengths. A fully sufficient IQ was defined as an LS score of ≥3. Nonparametric Wilcoxon test for related samples was used for statistical comparison. RESULTS: The median IQ for the DM and OJM at 0.55 T was inferior to that at 1.5 T (DM: 3 [interquartile range IQR, 3-4] vs 4 [IQR, 4-4]; OJM: 3 [IQR, 3-4] vs 4 [IQR 4-4]; each P < 0.001). For DP, the IQ was comparable (4 [IQR 3-4] vs 4 [IQR 4-4]; P > 0.05). A sufficient diagnostic IQ was maintained for the DM, DP, and OJM in 92% of the cases at 0.55 T and 100% at 1.5 T. Minor image artifacts (LS score of ≥3) were more prevalent at 0.55 T (29%) than at 1.5 T (12%). CONCLUSIONS: Magnetic resonance imaging of the TMJ at 0.55 T yields a lower IQ than does MRI at 1.5 T but maintains sufficient diagnostic confidence in the majority of patients. Further improvements are needed for reliable clinical application.
EVALuna2:549645

Multicenter Evaluation Of Coronary Dual-Source CT angiography in patients with intermediate Risk of Coronary Artery Stenoses (MEDIC): study design and rationale - Hausleiter, Jörg; Abbara, Suhny; Hoffmann, Udo; Becker, Christoph; Ovrehus, Kristian; Ropers, Dieter; Bathina, Ravi; Berman, Dan; Anders, Katharina; Uder, Michael; Meave, Aloha; Alexánderson, Erick; et al. (Journal of Cardiovascular Computed Tomography, 2014)
The diagnostic performance of multidetector row CT to detect coronary artery stenosis has been evaluated in numerous single-center studies, with only limited data from large cohorts with low-to-intermediate likelihood of coronary disease and in multicenter trials. The Multicenter Evaluation of Coronary Dual-Source CT Angiography in Patients with Intermediate Risk of Coronary Artery Stenoses (MEDIC) trial determines the accuracy of dual-source CT (DSCT) to identify persons with at least 1 coronary artery stenosis among patients with low-to-intermediate pretest likelihood of disease.The MEDIC trial was designed as a prospective, multicenter, international trial to evaluate the diagnostic performance of DSCT for the detection of coronary artery stenosis compared with invasive coronary angiography. The study includes 8 sites in Germany, India, Mexico, the United States, and Denmark. The study population comprises patients referred for a diagnostic coronary angiogram because of suspected coronary artery disease with an intermediate pretest likelihood as determined by sex, age, and symptoms. All evaluations are performed by blinded core laboratory readers.The primary outcome of the MEDIC trial is the accuracy of DSCT to identify the presence of coronary artery stenoses with a luminal diameter narrowing of 50% or more on a per-vessel basis. Secondary outcome parameters include per-patient and per-segment diagnostic accuracy for 50% stenoses and accuracy to identify stenoses of 70% or more. Furthermore, secondary outcome parameters include the influence of heart rate, Agatston score, body weight, body mass index, image quality, and diagnostic confidence on the accuracy to detect coronary artery stenoses >50% on a per-vessel basis.The results of the MEDIC trial will assess the clinical utility of coronary CT angiography in the evaluation of patients with intermediate pretest likelihood of coronary artery disease.
EVALuna2:14371

Multi-echo–based fat artifact correction for CEST MRI at 7 T - Tkotz, Katharina; Liebert, Andrzej; Gast, Lena; Zeiger, Paula; Uder, Michael; Zaiß, Moritz; Nagel, Armin Michael (Magnetic Resonance in Medicine, 2024)
Purpose: CEST MRI is influenced by fat signal, which can reduce the apparent CEST contrast or lead to pseudo-CEST effects. Our goal was to develop a fat artifact correction based on multi-echo fat–water separation that functions stably for 7 T knee MRI data. Methods: Our proposed algorithm utilizes the full complex data and a phase demodulation with an off-resonance map estimation based on the Z-spectra prior to fat–water separation to achieve stable fat artifact correction. Our method was validated and compared to multi-echo–based methods originally proposed for 3 T by Bloch–McConnell simulations and phantom measurements. Moreover, the method was applied to in vivo 7 T knee MRI examinations and compared to Gaussian fat saturation and a published single-echo Z-spectrum–based fat artifact correction method. Results: Phase demodulation prior to fat–water separation reduced the occurrence of fat–water swaps. Utilizing the complex signal data led to more stable correction results than working with magnitude data, as was proposed for 3 T. Our approach reduced pseudo-nuclear Overhauser effects compared to the other correction methods. Thus, the mean asymmetry contrast at 3.5 ppm in cartilage over five volunteers increased from −9.2% (uncorrected) and −10.6% (Z-spectrum–based) to −1.5%. Results showed higher spatial stability than with the fat saturation pulse. Conclusion: Our work demonstrates the feasibility of multi-echo–based fat–water separation with an adaptive fat model for fat artifact correction for CEST MRI at 7 T. Our approach provided better fat artifact correction throughout the entire spectrum and image than the fat saturation pulse or Z-spectrum–based correction method for both phantom and knee imaging results.
CRIS-Team Scopus Importer:2023-12-08
Keywords: 7 T; CEST; fat artifact; fat–water separation; knee imaging; nuclear Overhauser effect

Multimodal imaging of bone metastases: From preclinical to clinical applications - Ellmann, Stephan; Beck, Michael; Kuwert, Torsten; Uder, Michael; Bäuerle, Tobias (Journal of Orthopaedic Translation, 2015)
Metastases to the skeletal system are commonly observed in cancer patients, highly affecting the patients' quality of life. Imaging plays a major role in detection, follow-up, and molecular characterisation of metastatic disease. Thus, imaging techniques have been optimised and combined in a multimodal and multiparametric manner for assessment of complementary aspects in osseous metastases. This review summarises both application of the most relevant imaging techniques for bone metastasis in preclinical models and the clinical setting.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bone metastases; Computed tomography; Magnetic resonance imaging; Multimodal imaging; Positron-emission tomography; Translational research

Multi-parametric analysis of below-knee compression garments on delayed-onset muscle soreness - Hotfiel, Thilo; Höger, Svenja; Nagel, Armin Michael; Uder, Michael; Kemmler, Wolfgang; Forst, Raimund; Engelhardt, Martin; Grim, Casper; Heiß, Rafael (International Journal of Environmental Research and Public Health, 2021)
To investigate below-knee compression garments during exercise and a post-exercise period of 6 h on clinical, functional, and morphological outcomes in delayed-onset muscle soreness (DOMS). Eighteen volunteers (age: 24.1 ± 3.6, BMI 22.7 ± 2.7 kg/m2 ) were enrolled. Measures were acquired at baseline, 6 h, and 48 h after eccentric and plyometric exercise, with wearing a compression garment (21–22 mmHg) on a calf during and for the first 6 h after exercise. 3T MRI was performed for quantification of intramuscular edema (T2 signal intensity (SI), T2 time, and manual volume segmentation); jump height, calf circumference, ankle dorsiflexion (DF), creatine kinase (CK), and muscle soreness were assessed. DOMS was confirmed in all participants after 48 h, with an increase in soreness (p < 0.001) and CK (p = 0.001), decrease in jump height (p < 0.01), and the presence of intramuscular edema (p < 0.01) in both the compressed and non-compressed limbs. No differences between the compressed and non-compressed limbs were observed for muscle soreness and jump height. MRI T2 SI, T2 time, soreness, and manual segmentation revealed no effect of the compression treatment. The assessment of calf circumference and DF showed no changes in either the compression or non-compression limb (p = 1.0). Wearing compression garments during combined eccentric and plyometric exercise and for 6 h post-exercise has no effect on clinical signs of DOMS, jump performance, or the development of intramuscular edema.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Ergogenic aids; Muscle fatigue; Muscle injuries; Recovery; Regeneration; Sports injuries

Multiparametric magnetic resonance imaging of experimental chronic kidney disease: A quantitative correlation study with histology - Schley, Gunnar; Jordan, Jutta; Ellmann, Stephan; Rosen, Seymour; Eckardt, Kai-Uwe; Uder, Michael; Willam, Carsten; Bäuerle, Tobias (PLoS ONE, 2018)
OBJECTIVES: In human chronic kidney disease (CKD) the extent of renal tubulointerstitial fibrosis correlates with progressive loss of renal function. However, fibrosis can so far only be assessed by histology of kidney biopsies. Magnetic resonance imaging (MRI) can provide information about tissue architecture, but its potential to assess fibrosis and inflammation in diseased kidneys remains poorly defined. MATERIALS AND METHODS: We evaluated excised kidneys in a murine adenine-induced nephropathy model for CKD by MRI and correlated quantitative MRI parameters (T1, T2, and T2* relaxation times, apparent diffusion coefficient and fractional anisotropy) with histological hallmarks of progressive CKD, including renal fibrosis, inflammation, and microvascular rarefaction. Furthermore, we analyzed the effects of paraformaldehyde fixation on MRI parameters by comparing kidney samples before and after fixation with paraformaldehyde. RESULTS: In diseased kidneys T2 and T2* relaxation times, apparent diffusion coefficient and fractional anisotropy in the renal cortex and/or outer medulla were significantly different from those in control kidneys. In particular, T2 relaxation time was the best parameter to distinguish control and CKD groups and correlated very well with the extent of fibrosis, inflammatory infiltrates, tubular dilation, crystal deposition, and loss of peritubular capillaries and normal tubules in the renal cortex and outer medulla. Fixation with paraformaldehyde had no impact on T2 relaxation time and fractional anisotropy, whereas T1 times significantly decreased and T2* times and apparent diffusion coefficients increased in fixed kidney tissue. CONCLUSIONS: MRI parameters provide a promising approach to quantitatively assess renal fibrosis and inflammation in CKD. Especially T2 relaxation time correlates well with histological features of CKD and is not influenced by paraformaldehyde fixation of kidney samples. Thus, T2 relaxation time might be a candidate parameter for non-invasive assessment of renal fibrosis in human patients.
EVALuna2:34510

Multiple interleaved mode saturation (MIMOSA) for B1+ inhomogeneity mitigation in chemical exchange saturation transfer - Liebert, Andrzej; Gumbrecht, Rene; Tkotz, Katharina; Linz, Peter; Schmitt, Benjamin; Dörfler, Arnd; Uder, Michael; Nagel, Armin Michael; Zaiss, Moritz; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2019)
Purpose: To mitigate (Formula presented.) inhomogeneity in quantitative CEST MRI at ultra-high magnetic field strengths (B 0 ≥ 7 Tesla) using a parallel transmit system. Methods: Multiple interleaved mode saturation employs interleaving of 2 complementary phase sets during the saturation pulse train. Phase differences of 45° (first mode) and 90° (second mode) between 2 adjacent transmitter coil channels are used. The influence of the new saturation scheme on the CEST contrast was analyzed using Bloch-McConnell simulations. The presented method was verified in phantom and in vivo measurements of the healthy human brain. The relayed nuclear Overhauser effect was evaluated, and the inverse magnetic transfer ratio metric was calculated. Results were compared to a published (Formula presented.) correction method. All measurements were conducted on a whole-body 7 Tesla MRI system using an 8 transmitter and 32 receiver channel head coil. Results: Simulations showed that the inverse magnetic transfer ratio metric contrast of relayed nuclear Overhauser effect shows a smaller dependency on the relative amplitudes of the 2 different modes than the contrasts of Cr and amide proton transfer. Measurements of an egg white phantom showed markedly improved homogeneity compared to the uncorrected inverse magnetic transfer ratio metric (relayed nuclear Overhauser effect) images and slightly improved results compared to (Formula presented.) corrected images. In vivo multiple interleaved mode saturation images showed similar contrast compared to (Formula presented.) corrected images. Conclusion: Multiple interleaved mode saturation can be used as a simple method to mitigate (Formula presented.) inhomogeneity effects in CEST MRI at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced because an additional scan, usually required for (Formula presented.) correction, can be omitted.
CRIS-Team Scopus Importer:2019-05-02
Keywords: 7 Tesla; B1 shimming; chemical exchange saturation transfer; parallel transmission (pTx); pulsed CEST; RF inhomogeneity; ultra-high-field MRI

Multispectral optoacoustic tomography enables assessment of disease activity in paediatric inflammatory bowel disease - Regensburger, Adrian; Eckstein, Markus; Wetzl, Matthias; Raming, Roman; Paulus, Lars-Philip; Bühler, Adrian; Nedoschill, Emmanuel; Danko, Vera; Jüngert, Jörg; Wagner, Alexandra; Schnell, Alexander; Rückel, Aline; et al. (Photoacoustics, 2024)
Multispectral optoacoustic tomography (MSOT) allows non-invasive molecular disease activity assessment in adults with inflammatory bowel disease (IBD). In this prospective pilot-study, we investigated, whether increased levels of MSOT haemoglobin parameters corresponded to inflammatory activity in paediatric IBD patients, too. 23 children with suspected IBD underwent MSOT of the terminal ileum and sigmoid colon with standard validation (e.g. endoscopy). In Crohn‘s disease (CD) and ulcerative colitis (UC) patients with endoscopically confirmed disease activity, MSOT total haemoglobin (HbT) signals were increased in the terminal ileum of CD (72.1 ± 13.0 a.u. vs. 32.9 ± 15.4 a.u., p = 0.0049) and in the sigmoid colon of UC patients (62.9 ± 13.8 a.u. vs. 35.1 ± 16.3 a.u., p = 0.0311) as compared to controls, respectively. Furthermore, MSOT haemoglobin parameters correlated well with standard disease activity assessment (e.g. SES-CD and MSOT HbT (rs =0.69, p = 0.0075). Summarizing, MSOT is a novel technology for non-invasive molecular disease activity assessment in paediatric patients with inflammatory bowel disease.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Multispectral optoacoustic tomography; Optoacoustic imaging; Paediatric inflammatory bowel disease

Muscle perfusion and the effect of compression garments in delayed-onset muscle soreness assessed with arterial spin labeling magnetic resonance imaging - Meixner, Christian; Nagel, Armin Michael; Höger, Svenja; Gast, Lena; Wiesmüller, Marco; Uder, Michael; May, Matthias; Hotfiel, Thilo; Heiß, Rafael (Quantitative Imaging in Medicine and Surgery, 2022)
Background: There is limited information about perfusion in exercise-induced muscle injuries such as delayed-onset muscle soreness (DOMS) and the effect of compression garments as a therapeutic strategy during the regeneration phase. The purpose of this prospective, explorative study was to evaluate muscle perfusion in DOMS and to assess the effect of compression garments at resting conditions and during DOMS by magnetic resonance (MR) arterial spin labeling (ASL). Methods: DOMS was induced from 03/2021 to 04/2021 using an eccentric and plyometric exercises targeting the calf muscles in 14 volunteers. A compression garment (21-22 mmHg) was worn during and for 6 h after exercise on one randomized leg. Magnetic resonance imaging (MRI) including ASL of both lower legs was performed before and directly after the exercise as well as after 6 h, and 48 h using a 3 Tesla MRI system. Perfusion analyses of the gastrocnemius muscle (GM) and the tibialis anterior muscle (TA) were performed and results were compared to baseline measurements. T2-weighted images and creatine kinase levels were acquired at baseline and after 48 h. Results: All volunteers presented a successful induction of DOMS in the GM after 48 h. Arterial muscle perfusion in the GM increased from baseline to measurements taken directly after the exercise (4.97 +/- 5.59 mL/100 g/min, P<0.001). No significant alteration in perfusion compared to baseline was observed at 6 h (P=0.16) and 48 h (P=1.0) after the induction of DOMS. Compression garments did not elicit a significant alteration in ASL parameters in the GM (P=0.65) or the TA (P=0.05) at any time point. No adverse events occurred during the study. Conclusions: After an initial exercise-associated increase in arterial muscle perfusion, a normalization of blood supply was observed at 6 and 48 h after the exercise intervention inducing DOMS. Wearing a compression garment (21-22 mmHg) during and after the induction of DOMS did not affect muscle perfusion at rest, nor did it have any significant effect on muscle perfusion during the regeneration phase. The results can help to better understand the pathophysiological properties of DOMS and may have implications for diagnostic and therapeutic strategies.
CRIS-Team WoS Importer:2022-08-05

MyCases-a portable application for radiologic case collections - Kammerer, Ferdinand Josef; Janka, Rolf Matthias; Kramer, Manuel; Hammon, Matthias; Uder, Michael; Schlechtweg, Philipp (Journal of Digital Imaging, 2014)
Radiologists come across interesting patient cases almost every day. This work proposes a novel case database server for quick and easy storage of such cases including whole image series, patient data, and annotations. Cases can be added to the database by saving DICOM images into a predefined directory on the local network. The application automatically extracts patient and study data from the DICOM header and saves it in the database while images are stored as anonymized JPEG files. Users can mark their cases as private or public (visible to all users). Different data fields for annotations and categorization of a case are available. The user frontend also provides several retrieval mechanisms allowing for browsing the cases and performing different kinds of search queries. The stored series can be scrolled interactively in the form of scrollable image stacks. The project is realized as a web-based application using a portable web and database server software package (XAMPP). This makes the system very lightweight and easy to run on almost any desktop computer, even from a USB flash drive, without the need for deeper IT knowledge and administrative rights.
EVALuna2:14373

Myocardial adaptation to high-intensity (interval) training in previously untrained men with a longitudinal cardiovascular magnetic resonance imaging study (Running Study and Heart Trial) - Scharf, Michael; Schmid, Axel; Kemmler, Wolfgang; von Stengel, Simon; May, Matthias; Wüst, Wolfgang; Achenbach, Stephan; Uder, Michael; Lell, Michael (Circulation: Cardiovascular Imaging, 2015)
To prospectively evaluate whether short-term high-intensity (interval) training (HI(I)T) induces detectable morphological cardiac changes in previously untrained men in cardiovascular magnetic resonance imaging.Eighty-four untrained volunteers were randomly assigned to a HI(I)T group (n=42; 44.1±4.7 years) or an inactive control group (n=42; 42.3±5.6 years). HI(I)T focused on interval runs (intensity: 95%-105% of individually calculated heart rate at the anaerobic threshold). Before and after 16 weeks, all subjects underwent physiological examination, stepwise treadmill test with blood lactate analysis, and contrast-enhanced cardiovascular magnetic resonance imaging (cine, tagging, and delayed enhancement). Indexed left ventricular (LV) and right ventricular (RV) volume (LV, 77.1±8.5-83.9±8.6; RV, 80.5±8.5-86.6±8.1) and mass (LV, 58.2±6.4-63.4±8.1; RV, 14.8±1.7-16.1±2.1) significantly increased with HI(I)T. Changes in LV and RV morphological parameters with HI(I)T were highly correlated with an increase in maximal aerobic capacity (VO2max) and a decrease in blood lactate concentration at the anaerobic threshold. Mean LV and RV remodeling index of HI(I)T group did not alter with training (0.76 ±0.09 and 0.24±0.10 g/mL, respectively [P=0.97 and P=0.72]), indicating balanced cardiac adaptation. Myocardial circumferential strain decreased after HI(I)T within all 6 basal segments (anteroseptal, P=0.01 and anterolateral, P<0.001). There was no late gadolinium enhancement in any of the participants before or post HI(I)T.Sixteen weeks of HI(I)T lead to measurable changes in cardiac atrial and ventricular morphology and function in previously untrained men. This correlates with improvements in parameters of endurance capacity.URL: http://www.clinicaltrials.gov. Unique identifier: NCT01406730.
EVALuna2:10107

Myocardial adaption to HI(R)T in previously untrained men with a randomized, longitudinal cardiac MR imaging study (Physical adaptions in Untrained on Strength and Heart trial, PUSH-trial) - Scharf, Michael; Özdemir, Derya; Schmid, Andrea; Kemmler, Wolfgang; von Stengel, Simon; May, Matthias; Uder, Michael; Lell, Michael M. (PLoS ONE, 2017)
Although musculoskeletal effects in resistance training are well described, little is known about structural and functional cardiac adaption in formerly untrained subjects. We prospectively evaluated whether short term high intensity (resistance) training (HI(R)T) induces detectable morphologic cardiac changes in previously untrained men in a randomized controlled magnetic resonance imaging (MRI) study.80 untrained middle-aged men were randomly assigned to a HI(R)T-group (n = 40; 43.5±5.9 years) or an inactive control group (n = 40; 42.0±6.3 years). HI(R)T comprised 22 weeks of training focusing on a single-set to failure protocol in 2-3 sessions/week, each with 10-13 exercises addressing main muscle groups. Repetitions were decreased from 8-10 to 3-5 during study period. Before and after HI(R)T all subjects underwent physiologic examination and cardiac MRI (cine imaging, tagging).Indexed left (LV) and right ventricular (RV) volume (LV: 76.8±15.6 to 78.7±14.8 ml/m2; RV: 77.0±15.5 to 78.7±15.1 ml/m2) and mass (LV: 55.5±9.7 to 57.0±8.8 g/m2; RV: 14.6±3.0 to 15.0±2.9 g/m2) significantly increased with HI(R)T (all p<0.001). Mean LV and RV remodeling indices of HI(R)T-group did not alter with training (0.73g/mL and 0.19g/mL, respectively [p = 0.96 and p = 0.87]), indicating balanced cardiac adaption. Indexed LV (48.4±11.1 to 50.8±11.0 ml/m2) and RV (48.5±11.0 to 50.6±10.7 ml/m2) stroke volume significantly increased with HI(R)T (p<0.001). Myocardial strain and strain rates did not change following resistance exercise. Left atrial volume at end systole slightly increased after HI(R)T (36.2±7.9 to 37.0±8.4 ml/m2, p = 0.411), the ratio to end-diastolic LV volume at baseline and post-training was unchanged (0.47 vs. 0.47, p = 0.79).22 weeks of HI(R)T lead to measurable, physiological changes in cardiac atrial and ventricular morphologic characteristics and function in previously untrained men.The PUSH-trial is registered at the US National Institutes of Health (ClinicalTrials.gov), NCT01766791.
EVALuna2:14716

Na-23-MRI reveals sodium accumulation in skin of patients with relapsing-remitting multiple sclerosis - Huhn, K.; Linz, Peter; Pemsel, F.; Waschbisch, Anne; Lee, De-Hyung; Kopp, C.; Uder, Michael; Titze, J.; Mueller, D. N.; Linker, Ralf (2015)
EVALuna2:14485

Na+ deposition in the fibrotic skin of systemic sclerosis patients detected by 23Na-magnetic resonance imaging - Kopp, Christoph; Beyer, Christian; Linz, Peter; Dahlmann, Anke; Hammon, Matthias; Jantsch, Jonathan; Neubert, Patrick; Rosenhauer, Daniela; Mueller, Dominik N.; Eckardt, Kai-Uwe; Schett, Georg; Luft, Friedrich C.; et al. (Rheumatology, 2017)
Skin fibrosis is the predominant feature of SSc and arises from excessive extracellular matrix deposition. Glycosaminoglycans are macromolecules of the extracellular matrix, which facilitate Na(+) accumulation in the skin. We used (23)Na-MRI to quantify Na(+) in skin. We hypothesized that skin Na(+) might accumulate in SSc and might be a biomarker for skin fibrosis.In this observational case-control study, skin Na(+) was determined by (23)Na-MRI using a Na(+) volume coil in 12 patients with diffuse cutaneous SSc and in 21 control subjects. We assessed skin fibrosis by the modified Rodnan skin score prior to (23)Na-MRI and on follow-up 12 months later.(23)Na-MRI demonstrated increased Na(+) in the fibrotic skin of SSc patients compared with skin from controls [mean (sd): 27.2 (5.6) vs 21.4 (5.3) mmol/l, P < 0.01]. Na(+) content was higher in fibrotic than in non-fibrotic SSc skin [26.2 (4.8) vs 19.2 (3.4) mmol/l, P < 0.01]. Furthermore, skin Na(+) amount was correlated with changes in follow-up modified Rodnan skin score (R(2) = 0.68).(23)Na-MRI detected increased Na(+) in the fibrotic SSc skin; high Na(+) content was associated with progressive skin disease. Our findings provide the first evidence that (23)Na-MRI might be a promising tool to assess skin Na(+) and thereby predict progression of skin fibrosis in SSc.
EVALuna:33997

Native cardiac T1 Mapping: Standardized inline analysis of long and short axis at three identical 1.5 Tesla MRI scanners - Heiß, Rafael; Wiesmüller, Marco; Uder, Michael; May, Matthias; Wüst, Wolfgang (European Journal of Radiology, 2018)
BACKGROUND: Interpretation of native T1 time values remains difficult due to limited hard- and software comparability and the lack of measurement recommendations for the number of slices and their orientation. To provide a standardized comparison of native T1 time values in short and long axis and to investigate the interscanner reproducibility. METHODS: 78 cardiac MRIs in 26 healthy volunteers were performed with three structurally identical 1.5 T MRI scanners. A commercially available software package for T1 mapping with automatic in-line motion correction was used for analysis. On T1 mapping images regions of interest were manually placed in each of the 16 myocardial segments according to the AHA model in three short and three long axis. RESULTS: A total of 2652 ROIs were drawn and 102 segments per volunteer were analysed. Interscanner reproducibility was high and the mean myocardial T1 time value for all evaluated segments was 996 ± 34 ms. Significant variations of T1 time values were found between heart segments in the same axis. Mean T1 time values were comparable between long and short axis but differed in 33% of corresponding short and long axis segments. CONCLUSIONS: Native T1 time values in short and long axis are highly reproducible but can vary significantly between heart segments in the same axis. Comparability between corresponding short and long axis segments is limited. To get representative results native T1 time values should be obtained in more than one heart segment and for follow-up studies identical segments should be used to avoid a systematic bias.
EVALuna2:34686

Neural Networks for Distinguishing Rheumatoid Arthritis from Psoriatic Arthritis by Using Magnetic Resonance Imaging - Folle, Lukas; Bayat, Sara; Kleyer, Arnd; Fagni, Filippo; Kapsner, Lorenz; Schlereth, Maja; Meinderink, Timo; Breininger, Katharina; Tascilar, Koray; Krönke, Gerhard; Uder, Michael; Sticherling, Michael; et al. (Arthritis Rheumatol., 2022)

Noise Reduction in Abdominal Computed Tomography Applying Iterative Reconstruction (ADMIRE) - Schaller, Frank; Sedlmair, Martin; Raupach, Rainer; Uder, Michael; Leii, Michael (Academic Radiology, 2016)
The study aimed to compare image quality of filtered back projection (FBP) and iterative reconstruction (advanced modeled iterative reconstruction, ADMIRE) in contrast-enhanced computed tomography (CT) of the abdomen, and to assess the differences of reconstructions according to these methods. It also aimed to investigate the potential for noise reduction of ADMIRE for different reconstructed slice thicknesses.CT data of the abdomen and pelvis were acquired using a 128-slice single-source CT system using automated kV selection and tube current adaption based on patients' anatomy. Raw data sets from patients scanned at 100 kV were selected, and images were reconstructed with slice thicknesses of 1 mm, 3 mm, and 5 mm, both with FBP and ADMIRE. Filter strength F1, F3, and F5 of the ADMIRE algorithm and the corresponding reconstruction kernels were used. In total, 58 raw data sets from 17 patients were used to reconstruct from the same raw data FBP and ADMIRE images, representing identical body regions. Identical regions of interest were placed at the same position of up to four images and image noise was measured. Differences of reconstructed images and detail preservation were tested using an image subtraction technique, and subjective image quality was assessed using a 5-point Likert scale.On average, for 1-mm slice thickness, noise reduction was 9.15% ± 2.4% with filter strength level F1, 30.2% ± 3.4% with F3, and 54.4% ± 7.0% with F5 as compared to FBP. For a slice thickness of 3 mm, noise reduction was 8.5% ± 3.7% with F1, 28.6% ± 3.9% with F3, and 52.2% ± 9.1% with F5. For 5 mm, the corresponding values are 8.9% ± 2.7%, 31.4% ± 2.8%, and 52.7% ± 7.7%. On subtraction images, edge information of tissue classes with a high attenuation gradient was found, but structures with small differences in attenuation were not detectable on subtraction images, confirming that no relevant details were lost in the iterative reconstruction process.ADMIRE is able to reduce image noise considerably (up to 50%) without any obvious negative impact on lesion depiction as assessed visually. Noise reduction of ADMIRE seems to be independent of slice thickness.
EVALuna2:14592

Non-Athletic Cohorts Enrolled in Longitudinal Whole-Body Electromyostimulation Trials—An Evidence Map - Beier, Miriam; Schöne, Daniel; Kohl, Matthias; von Stengel, Simon; Uder, Michael; Kemmler, Wolfgang (Sensors, 2024)
Whole-body electromyostimulation (WB-EMS) can be considered as a time-efficient, joint-friendly, and highly customizable training technology that attracts a wide range of users. The present evidence map aims to provide an overview of different non-athletic cohorts addressed in WB-EMS research. Based on a comprehensive systematic search according to PRISMA, eighty-six eligible longitudinal trials were identified that correspond with our eligibility criteria. In summary, WB-EMS research sufficiently covers all adult age categories in males and females. Most cohorts addressed (58%) were predominately or exclusively overweight/obese, and in about 60% of them, diseases or conditions were inclusion criteria for the trials. Cohorts specifically enrolled in WB-EMS trials suffer from cancer/neoplasm (n = 7), obesity (n = 6), diabetes mellitus (n = 5), metabolic syndrome (n = 2), nervous system diseases (n = 2), chronic heart failure (n = 4), stroke (n = 1), peripheral arterial diseases (n = 2), knee arthrosis (n = 1), sarcopenia (n = 3), chronic unspecific low back pain (n = 4), and osteopenia (n = 3). Chronic kidney disease was an eligibility criterion in five WB-EMS trials. Finally, three studies included only critically ill patients, and two further studies considered frailty as an inclusion criterion. Of importance, no adverse effects of the WB-EMS intervention were reported. In summary, the evidence gaps in WB-EMS research were particular evident for cohorts with diseases of the nervous and cerebrovascular system.
CRIS-Team Scopus Importer:2024-02-23
Keywords: body composition; cohorts; diseases; electromyostimulation; function; longitudinal studies; whole-body electrostimulation

Non-Invasive Characterization of Experimental Bone Metastasis in Obesity Using Multiparametric MRI and PET/CT - Gregoric, Gasper; Gaculenko, Anastasia; Nagel, Lisa; Popp, Vanessa; Maschauer, Simone; Prante, Olaf; Saake, Marc; Schett, Georg; Uder, Michael; Ellmann, Stephan; Bozec, Aline; Bäuerle, Tobias (Cancers, 2022)
The growth of primary tumors and metastases is associated with excess body fat. In bone metastasis formation, the bone marrow microenvironment, and particularly adipocytes, play a pivotal role as growth mediators of disseminated tumor cells in the bone marrow. The aim of the present study is to non-invasively characterize the pathophysiologic processes in experimental bone metastasis resulting from accelerated tumor progression within adipocyte-rich bone marrow using multimodal imaging from magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT). To achieve this, we have employed small animal models after the administration of MDA-MB 231 breast cancer and B16F10 melanoma cells into the bone of nude rats or C57BL/6 mice, respectively. After tumor cell inoculation, ultra-high field MRI and mu PET/CT were used to assess functional and metabolic parameters in the bone marrow of control animals (normal diet, ND), following a high-fat diet (HFD), and/or treated with the peroxisome proliferator-activated receptor-gamma (PPAR gamma) antagonist bisphenol-A-diglycidylether (BADGE), respectively. In the bone marrow of nude rats, dynamic contrast-enhanced MRI (DCE-MRI) and diffusion-weighted imaging (DWI), as well as [F-18]fluorodeoxyglucose-PET/CT([F-18]FDG-PET/CT), was performed 10, 20, and 30 days after tumor cell inoculation, followed by immunohistochemistry. DCE-MRI parameters associated with blood volume, such as area under the curve (AUC), were significantly increased in bone metastases in the HFD group 30 days after tumor cell inoculation as compared to controls (p < 0.05), while the DWI parameter apparent diffusion coefficient (ADC) was not significantly different between the groups. [F-18]FDG-PET/CT showed an enhanced glucose metabolism due to increased standardized uptake value (SUV) at day 30 after tumor cell inoculation in animals that received HFD (p < 0.05). BADGE treatment resulted in the inversion of quantitative DCE-MRI and [F-18]FDG-PET/CT data, namely a significant decrease in AUC and SUV in HFD-fed animals as compared to ND-fed controls (p < 0.05). Finally, immunohistochemistry and qPCR confirmed the HFD-induced stimulation in vascularization and glucose activity in murine bone metastases. In conclusion, multimodal and multiparametric MRI and [F-18]FDG-PET/CT were able to derive quantitative parameters in bone metastases, revealing an increase in vascularization and glucose metabolism following HFD. Thus, non-invasive imaging may serve as a biomarker for assessing the pathophysiology of bone metastasis in obesity, opening novel options for therapy and treatment monitoring by MRI and [F-18]FDG-PET/CT.
CRIS-Team WoS Importer:2022-06-10

Non-Ischemic Pneumatosis Coli in Acute Abdomen - Heiß, Rafael; Wiesmüller, Marco; Uder, Michael (Deutsches Ärzteblatt international, 2020)
CRIS-Team WoS Importer:2021-04-02

Nonparametric D-R1-R2 distribution MRI of the living human brain - Laun, Frederik Bernd; Martin, Jan; Reymbaut, Alexis; Schmidt, Manuel; Dörfler, Arnd; Topgaard, Daniel; Uder, Michael (2021)
Diffusion-relaxation correlation NMR can simultaneously characterize both the microstructure and the local chemical composition of complex samples that contain multiple populations of water. Recent developments on tensor-valued diffusion encoding and Monte Carlo inversion algorithms have made it possible to transfer diffusion-relaxation correlation NMR from small-bore scanners to clinical MRI systems. Initial studies on clinical MRI systems employed 5D D-R1 and D-R2 correlation to characterize healthy brain in vivo. However, these methods are subject to an inherent bias that originates from not including R2 or R1 in the analysis, respectively. This drawback can be remedied by extending the concept to 6D D-R1-R2 correlation. In this work, we present a sparse acquisition protocol that records all data necessary for in vivo 6D D-R1-R2 correlation MRI across 633 individual measurements within 25 min—a time frame comparable to previous lower-dimensional acquisition protocols. The data were processed with a Monte Carlo inversion algorithm to obtain nonparametric 6D D-R1-R2 distributions. We validated the reproducibility of the method in repeated measurements of healthy volunteers. For a post-therapy glioblastoma case featuring cysts, edema, and partially necrotic remains of tumor, we present representative single-voxel 6D distributions, parameter maps, and artificial contrasts over a wide range of diffusion-, R1-, and R2-weightings based on the rich information contained in the D-R1-R2 distributions.
CRIS-Team Scopus Importer:2021-12-10
Keywords: Correlation; Diffusion; Microstructure; Relaxation; Signal inversion

Non-rigid motion-corrected free-breathing 3D myocardial Dixon LGE imaging in a clinical setting - Zeilinger, Martin; Kunze, Karl Philipp; Munoz, Camila; Neji, Radhouene; Schmidt, Michaela; Croisille, Pierre; Heiß, Rafael; Wuest, Wolfgang; Uder, Michael; Botnar, René Michael; Treutlein, Christoph; Prieto, Claudia (European Radiology, 2022)
Objectives: To investigate the efficacy of an in-line non-rigid motion-compensated reconstruction (NRC) in an image-navigated high-resolution three-dimensional late gadolinium enhancement (LGE) sequence with Dixon water–fat separation, in a clinical setting. Methods: Forty-seven consecutive patients were enrolled prospectively and examined with 1.5 T MRI. NRC reconstructions were compared to translational motion-compensated reconstructions (TC) of the same datasets in overall and different sub-category image quality scores, diagnostic confidence, contrast ratios, LGE pattern, and semiautomatic LGE quantification. Results: NRC outperformed TC in all image quality scores (p < 0.001 to 0.016; e.g., overall image quality 5/5 points vs. 4/5). Overall image quality was downgraded in only 23% of NRC datasets vs. 53% of TC datasets due to residual respiratory motion. In both reconstructions, LGE was rated as ischemic in 11 patients and non-ischemic in 10 patients, while it was absent in 26 patients. NRC delivered significantly higher LGE-to-myocardium and blood-to-myocardium contrast ratios (median 6.33 vs. 5.96, p < 0.001 and 4.88 vs. 4.66, p < 0.001, respectively). Automatically detected LGE mass was significantly lower in the NRC reconstruction (p < 0.001). Diagnostic confidence was identical in all cases, with high confidence in 89% and probable in 11% datasets for both reconstructions. No case was rated as inconclusive. Conclusions: The in-line implementation of a non-rigid motion-compensated reconstruction framework improved image quality in image-navigated free-breathing, isotropic high-resolution 3D LGE imaging with undersampled spiral-like Cartesian sampling and Dixon water–fat separation compared to translational motion correction of the same datasets. The sharper depictions of LGE may lead to more accurate measures of LGE mass. Key Points: • 3D LGE imaging provides high-resolution detection of myocardial scarring. • Non-rigid motion correction provides better image quality in cardiac MRI. • Non-rigid motion correction may lead to more accurate measures of LGE mass.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Heart; Magnetic resonance imaging; Myocardium; Three-dimensional imaging

Once Weekly Whole-Body Electromyostimulation Enhances Muscle Quality in Men: Data of the Randomized Controlled Franconian Electromyostimulation and Golf Study - Zink-Rückel, Carina; Chaudry, Oliver; Engelke, Klaus; Ghasemikaram, Mansour; Kohl, Matthias; Uder, Michael; Kemmler, Wolfgang (Frontiers in Physiology, 2021)
Whole-body electromyostimulation (WB-EMS) is commercially advertised as a time-efficient resistance-type exercise technology. Indeed, the commercial, non-medical setting applies 20 min of WB-EMS only once a week. However, this setting conflicts with the approved scientific approach of higher training frequencies. Using data from an ongoing study on WB-EMS and golf performance as a vehicle, we evaluate the effect of once weekly WB-EMS on changes of fatty muscle infiltration, as a crucial parameter of muscle quality. Fifty-four moderately physically active male amateur golfers 18–70 years old were randomly allocated to a WB-EMS (n = 27) with a standard setting of once weekly 20 min and a non-WB-EMS control group (CG, n = 27). Intermuscular adipose tissue (IMAT) volume and intrafascial muscle tissue (MT) volume per unit of intrafascial volume as determined by magnetic resonance imaging were used to characterize muscle quality. Intention to treat analysis with multiple imputation was applied. WB-EMS was conducted at the participants’ homes; thus, the attendance rate was close to 100%. After 16 weeks of intervention, we observed increases in volume-adjusted IMAT (p = 0.040) and decreases in MT (p = 0.206) in the CG. IMAT decreased in the WB-EMS group (p = 0.215), while MT increased significantly (p = 0.032). Of importance, group difference (i.e., “effects”) for intra-group changes in volume-adjusted IMAT (effect size: d´ = 0.66; p = 0.028) and MT (d´ = 0.70; p = 0.020) was significant for both parameters. Once weekly WB-EMS application significantly affects muscle quality of the mid-thigh in moderately active, healthy men 18–70 years old.
CRIS-Team Scopus Importer:2021-08-13
Keywords: fatty muscle infiltration; men; muscle quality; muscle tissue; whole-body electromyostimulation

On PTV definition for glioblastoma based on fiber tracking of diffusion tensor imaging data - Witulla, Barbara; Goerig, Nicole; Putz, Florian; Frey, Benjamin; Engelhorn, Tobias; Dörfler, Arnd; Uder, Michael; Fietkau, Rainer; Bert, Christoph; Laun, Frederik Bernd (PLoS ONE, 2020)
Radiotherapy (RT) is commonly applied for the treatment of glioblastoma multiforme (GBM). Following the planning target volume (PTV) definition procedure standardized in guidelines, a 20% risk of missing non-local recurrences is present. Purpose of this study was to evaluate whether diffusion tensor imaging (DTI)-based fiber tracking may be beneficial for PTV definition taking into account the prediction of distant recurrences. 56 GBM patients were examined with magnetic resonance imaging (MRI) including DTI performed before RT after resection of the primary tumor. Follow-up MRIs were acquired in three month intervals. For the seven patients with a distant recurrence, fiber tracking was performed with three algorithms and it was evaluated whether connections existed from the primary tumor region to the distant recurrence. It depended strongly on the used tracking algorithm and the used tracking parameters whether a connection was observed. Most of the connections were weak and thus not usable for PTV definition. Only in one of the seven patients with a recurring tumor, a clear connection was present. It seems unlikely that DTI-based fiber tracking can be beneficial for predicting distant recurrences in the planning of PTVs for glioblastoma multiforme.
CRIS-Team Scopus Importer:2020-01-21

On the dependence of the cardiac motion artifact on the breathing cycle in liver diffusion-weighted imaging - Riexinger, Andreas; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Seuß, Hannes; Uder, Michael; Hensel, Bernhard; Saake, Marc (PLoS ONE, 2020)
Purpose The purpose of this study was to investigate whether the cardiac motion artifact that regularly appears in diffusion-weighted imaging of the left liver lobe might be reduced by acquiring images in inspiration, when the coupling between heart and liver might be minimal. Materials and methods 43 patients with known or suspected focal liver lesions were examined at 1.5 T with breath hold acquisition, once in inspiration and once in expiration. Data were acquired with a diffusion-weighted echo planar imaging sequence and two b-values (b50 = 50 s/mm2 and b800 = 800 s/mm2). The severity of the cardiac motion artifact in the left liver lobe was rated by two experienced radiologists for both b-values with a 5 point Likert scale. Additionally, the normalized signal S(b800)/S(b50) in the left liver lobe was computed. The Wilcoxon signed-rank test was used comparing the scores of the two readers obtained in inspiration and expiration, and to compare the normalized signal in inspiration and expiration. Results The normalized signal in inspiration was slightly higher than in expiration (0.349±0.077 vs 0.336±0.058), which would indicate a slight reduction of the cardiac motion artifact, but this difference was not significant (p = 0.24). In the qualitative evaluation, the readers did not observe a significant difference for b50 (reader 1: p = 0.61; reader 2: p = 0.18). For b800, reader 1 observed a significant difference of small effect size favouring expiration (p = 0.03 with a difference of mean Likert scores of 0.27), while reader 2 observed no significant difference (p = 0.62). Conclusion Acquiring the data in inspiration does not lead to a markedly reduced cardiac motion artifact in diffusion-weighted imaging of the left liver lobe and is in this regard not to be preferred over acquiring the data in expiration.
CRIS-Team Scopus Importer:2020-10-16

On the Field Strength Dependence of Bi- and Triexponential Intravoxel Incoherent Motion (IVIM) Parameters in the Liver - Riexinger, Andreas; Martin, Jan; Rauh, Susanne; Wetscherek, Andreas; Pistel, Mona; Kuder, Tristan Anselm; Nagel, Armin Michael; Uder, Michael; Hensel, Bernhard; Müller, Lars; Laun, Frederik Bernd (Journal of Magnetic Resonance Imaging, 2019)
Background: Studies on intravoxel incoherent motion (IVIM) imaging are carried out with different acquisition protocols. Purpose: To investigate the dependence of IVIM parameters on the B0 field strength when using a bi- or triexponential model. Study Type: Prospective. Study Population: 20 healthy volunteers (age: 19–28 years). Field Strength/Sequence: Volunteers were examined at two field strengths (1.5 and 3T). Diffusion-weighted images of the abdomen were acquired at 24 b-values ranging from 0.2 to 500 s/mm2. Assessment: ROIs were manually drawn in the liver. Data were fitted with a bi- and a triexponential IVIM model. The resulting parameters were compared between both field strengths. Statistical Tests: One-way analysis of variance (ANOVA) and Kruskal–Wallis test were used to test the obtained IVIM parameters for a significant field strength dependency. Results: At b-values below 6 s/mm2, the triexponential model provided better agreement with the data than the biexponential model. The average tissue diffusivity was D = 1.22/1.00 μm2/msec at 1.5/3T. The average pseudodiffusion coefficients for the biexponential model were D* = 308/260 μm2/msec at 1.5/3T; and for the triexponential model D* = 81.3/65.9 μm2/msec, D* 2 = 2453/2333 μm2/msec at 1.5/3T. The average perfusion fractions for the biexponential model were f = 0.286/0.303 at 1.5/3T; and for the triexponential model f1 = 0.161/0.174 and f2 = 0.152/0.159 at 1.5/3T. A significant B0 dependence was only found for the biexponential pseudodiffusion coefficient (ANOVA/KW P = 0.037/0.0453) and tissue diffusivity (ANOVA/KW: P < 0.001). Data Conclusion: Our experimental results suggest that triexponential pseudodiffusion coefficients and perfusion fractions obtained at different field strengths could be compared across different studies using different B0. However, it is recommended to take the field strength into account when comparing tissue diffusivities or using the biexponential IVIM model. Considering published values for oxygenation-dependent transversal relaxation times of blood, it is unlikely that the two blood compartments of the triexponential model represent venous and arterial blood. Level of Evidence: 1. Technical Efficacy Stage: 2. J. Magn. Reson. Imaging 2019;50:1883–1892.
CRIS-Team Scopus Importer:2019-11-22
Keywords: intravoxel incoherent motion; IVIM; liver

On the Vanishing of the t-term in the Short-Time Expansion of the Diffusion Coefficient for Oscillating Gradients in Diffusion NMR - Demberg, Kerstin; Nagel, Armin Michael; Uder, Michael; Kuder, Tristan A.; Laun, Frederik Bernd (Frontiers in Physics, 2017)
Nuclear magnetic resonance (NMR) diffusion measurements can be used to probe porous structures or biological tissues by means of the random motion of water molecules. The short-time expansion of the diffusion coefficient in powers of t(1/2), where t is the diffusion time related to the duration of the diffusion-weighting magnetic field gradient profile, is universally connected to structural parameters of the boundaries restricting the diffusive motion. The t(1/2)-term is proportional to the surface to volume ratio. The t-term is related to permeability and curvature. The short time expansion can be measured with two approaches in NMR-based diffusion experiments: First, by the use of diffusion encodings of short total duration and, second, by application of oscillating gradients of long total duration. For oscillating gradients, the inverse of the oscillation frequency becomes the relevant time scale. The purpose of this manuscript is to show that the oscillating gradient approach is blind to the t-term. On the one hand, this prevents fitting of permeability and curvature measures from this term. On the other hand, the t-term does not bias the determination of the t(1/2)-term in experiments.
EVALuna2:36111

Operative therapy of spinal metastases from urological tumors - Richter, R. H.; Hammon, Matthias; Uder, Michael; Huber, J.; Goebell, Peter; Kunath, F.; Wullich, Bernd; Keck, Bastian (Urologe, 2016)
The treatment of bone metastases from urological tumors represents a palliative form of therapy, apart from the resection of solitary metastases from renal cell carcinomas. Due to the high incidence of spinal metastases this can result in clinically significant symptoms and possible complications for patients, such as pain, spinal instability and compression of the spinal canal with corresponding neurological deficits. By the use of targeted diagnostics and induction of radiotherapeutic and/or surgical treatment, for the majority of patients an immediate reduction in pain as well as early mobilization and sometimes even regression of existing neurological deficits and therefore an improved quality of life can be achieved.
EVALuna2:14490

Opportunistic Screening With CT: Comparison of Phantomless BMD Calibration Methods - Bartenschlager, Stefan; Cavallaro, Alexander Josef; Pogarell, Tobias; Chaudry, Oliver; Uder, Michael; Khosla, Sundeep; Schett, Georg; Engelke, Klaus (Journal of Bone and Mineral Research, 2023)
Opportunistic screening is a new promising technique to identify individuals at high risk for osteoporotic fracture using computed tomography (CT) scans originally acquired for an clinical purpose unrelated to osteoporosis. In these CT scans, a calibration phantom traditionally required to convert measured CT values to bone mineral density (BMD) is missing. As an alternative, phantomless calibration has been developed. This study aimed to review the principles of four existing phantomless calibration methods and to compare their performance against the gold standard of simultaneous calibration (ΔBMD). All methods were applied to a dataset of 350 females scanned with a highly standardized CT protocol (DS1) and to a second dataset of 114 patients (38 female) from clinical routine covering a large range of CT acquisition and reconstruction parameters (DS2). Three of the phantomless calibration methods must be precalibrated with a reference dataset containing a calibration phantom. Sixty scans from DS1 and 57 from DS2 were randomly selected for this precalibration. For each phantomless calibration method first the best combination of internal reference materials (IMs) was selected. These were either air and blood or subcutaneous adipose tissue, blood, and cortical bone. In addition, for phantomless calibration a fifth method based on average calibration parameters derived from the reference dataset was applied. For DS1, ΔBMD results (mean (Formula presented.) standard deviation) for the phantomless calibration methods requiring a precalibration ranged from 0.1 (Formula presented.) 2.7 mg/cm3 to 2.4 (Formula presented.) 3.5 mg/cm3 with similar means but significantly higher standard deviations for DS2. Performance of the phantomless calibration method, which does not require a precalibration was worse (ΔBMD DS1: 12.6 (Formula presented.) 13.2 mg/cm3, DS2: 0.5 (Formula presented.) 8.8 mg/cm3). In conclusion, phantomless BMD calibration performs well if precalibrated with a reference dataset. © 2023 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2023-10-20
Keywords: BONE MINERAL DENSITY; PERFORMANCE OF PHANTOMLESS CALIBRATION; OPPORTUNISTIC SCREENING; SIMULTANEOUS CALIBRATION

Optimizing Contrast Media Injection Protocols in State-of-the Art Computed Tomographic Angiography - Lell, Michael; Jost, Gregor; Korporaal, Johannes Georg; Mahnken, Andreas Horst; Flohr, Thomas G.; Uder, Michael; Pietsch, Hubertus (Investigative Radiology, 2015)
Very short acquisition times and the increasing use of low-kilovolt protocols in standard computed tomographic (CT) angiography (CTA) examinations demand modifications in the contrast media (CM) injection regimen. The aim of this study was to optimize the use of tube voltage-adjusted CM delivery parameters, especially injection duration and iodine delivery rate (IDR), in thoracoabdominal CTA in a porcine model.Eight pigs (53-72 kg) were examined with a third-generation dual-source CT system with a dynamic CTA protocol (4-dimensional spiral, 454-mm scan length, 2.5-second temporal resolution, 70-second total acquisition time). Six CM injection protocols were applied in randomized order and intraindividually compared. The standard CTA protocol was performed at 120 kV, with an injection of 300 mg iodine/kg body weight and a flow of 5 mL/s (IDR, 1.5 g/s). On the basis of phantom measurements for the low-kilovolt CTA protocols, the iodine dosage was adjusted to 150 mg iodine/kg (70 kV) and 210 mg iodine/kg (90 kV). Therefore, either the IDR was kept constant and the injection time was reduced, or the injection time was kept constant and the IDR was reduced by modifying the CM flow or concentration. Time attenuation curves, time to peak, and peak enhancement were calculated for different locations within the aorta, renal arteries, and large veins.The heart rates were comparable among the different injection protocols (66.9-78.1 beats per minute). The average injection peak pressure depended on the flow rate and CM concentration and ranged from 42.9 to 114.7 psi. The average arterial peak enhancement was comparable for protocols with identical injection times and reduced IDR (362.4 HU [standard 120-kV protocol; 300 mg iodine/kg; IDR, 1.5 g/s], 360.0 HU [70 kV; 150 mg iodine/kg; IDR, 0.75 g/s], 365.4 HU [70 kV; 150 mg iodine/kg; IDR, 0.75 g/s; CM, 150 mg iodine/mL], 344.3 HU [90 kV; 210 mg iodine/kg; IDR, 1.1 g/s]). Higher peak enhancements could be achieved by applying protocols with identical IDR and a reduced injection time (502.5 HU [70 kV; 150 mg iodine/kg; IDR, 1.5 g/s] and 394.6 HU [90 kV; 210 mg iodine/kg; IDR, 1.5 g/s]).By adjusting the IDR, low-kilovolt CTA is able to achieve comparable aortic enhancement with a significant reduction in CM dosage. A shorter injection time at constant IDR results in higher enhancement and a narrower scan window and might be preferable for fast CTA acquisition techniques.The optimization of CM injection protocols is mandatory to achieve state-of the art CTA at low kilovolt and can reduce CM doses to patients.
EVALuna2:14370

OS 12-03 SGLT-2-INHIBITION WITH DAPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT - Schmieder, Roland; Ott, Christian; Linz, Peter; Jumar, Agnes; Friedrich, Stefanie; Titze, Jens; Hammon, Matthias; Uder, Michael; Kistner, Iris (Journal of Hypertension, 2016)
Sodium tissue content by Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and, in parallel, of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes leads to decreased tissue sodium content due to its pharmacological action.In a prospective, double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to dapagliflozin 10 mg o.d. and placebo for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analyzed the sodium content in the skin and muscles of the lower leg by the Na-MRI at baseline, after the first and second treatment phase of 6 weeks.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11, p = 0.010) and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024) 24-hour ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline (24.1 ± 6.6 vs.22.7 ± 6.4 mmol/L; p = 0.013). No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 mmol/L, p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in sodium tissue content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes known to be salt sensitive and prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition.
EVALuna2:14604

OS 28-03 SECRETORY CAPACITY OF PANCREATIC BETA CELLS IS ENHANCED 6 MONTHS AFTER RENAL DENERVATION IN TREATMENT RESISTANT HYPERTENSIVE PATIENTS - Ott, Christian; Kistner, Iris; Schmid, Axel; Friedrich, Stefanie; Ditting, Tilmann; Veelken, Roland; Mahfoud, Felix; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2016)
Renal denervation (RDN) lowers blood pressure (BP) by interruption of sympathetic nerve activity. A high sympathetic tone increases not only BP but also decreases pancreatic beta cell insulin secretion. Hence, the objective of the study was to analyze whether RDN improves secretory capacity of beta cells.In 40 patients (7 diabetics, 19 prediabetics, 14 non diabetics) with treatment resistant hypertension (defined by office BP >= 140/90 mmHg and diagnosis confirmed with 24-h ambulatory BP >= 130/80 mmHg), insulin secretion was measured before and 6 months after RDN (Simplicity flex catheter, Medtronic) by glucagon test. At each time point blood was sampled prior to glucagon administration and 6 minutes after intravenous injection of 1 ml glucagon for measurement of C-peptide, insulin and proinsulin (by ELISA).In these 40 patients (mean age 58 ± 12 years, mean office BP 154 ± 22 mmHg / 89 ± 14 mmHg while on 5.2 ± 1.4 antihypertensive drugs) office systolic and diastolic BP was significantly reduced 6 months after RDN (both p < 0.01). Fasting plasma glucose and HbA1c level was significantly reduced 6 month after RDN (both p < 0.01). Six months after RDN, the increase of C-peptide concentration and insulin concentration after glucagon injection was significantly higher compared to before RDN (both p < 0.05).Thus, our data indicate an improved pancreatic beta cell function after RDN in patients with treatment resistant hypertension.
EVALuna2:14605

Ossicular osteoma of the malleus—A rare diagnosis of middle ear mass - Sievert, Matti; Mantsopoulos, Konstantinos; Hornung, Joachim; Thimsen, Vivian; Heiß, Rafael; Kopp, Markus; Wetzl, Matthias; Iro, Heinrich; Uder, Michael; Wiesmüller, Marco (Radiology Case Reports, 2022)
Osteoma of the middle ear (MEO) is a rarity. Due to the benign nature and slow growth rate, MEO are often occasionally found by chance. Possible unspecific clinical symptoms may be conductive hearing loss, tinnitus, effusion, and a sense of fullness. If the osteoma is small and not visible in the otoscopic inspection, it may be confused with other conductive hearing loss etiologies, such as otosclerosis. Nevertheless, one should be aware of this rare but important differential diagnosis of middle ear lesions. This article presents an MEO case causing conductive hearing loss and outlines the diagnostic approach with computed tomography.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Computed tomography; Conductive hearing loss; Middle ear lesion; Middle ear osteoma; Temporal bone osteoma

Osteitis and synovitis, but not bone erosion, is associated with proteoglycan loss and microstructure damage in the cartilage of patients with rheumatoid arthritis - Herz, Barbara; Albrecht, Andreas; Englbrecht, Matthias; Welsch, Götz; Uder, Michael; Renner, Nina; Schlechtweg, Philipp; Paul, Dominik; Lauer, Lars; Engelke, Klaus; Janka, Rolf Matthias; Rech, Jürgen; et al. (Annals of the Rheumatic Diseases, 2014)
To investigate the relation between anatomic changes of the synovium, the bone, the bone marrow and the cartilage to biochemical properties of the cartilage in patients with rheumatoid arthritis (RA).33 patients with RA received 3-T MRI scans of the metacarpophalangeal joints. Two independent methods, (A) the delayed gadolinium enhanced MRI of the cartilage (dGEMRIC, T2-mapping), which was used to assess the biochemical properties of the cartilage; (B) synovitis, osteitis and bone erosions were quantified according to the RA MRI scoring (RAMRIS) method and cartilage thickness (CT), interbone joint space (IBJS, distance between proximal and distal bone surface) and intercartilage joint space (ICJS, distance between proximal and distal cartilage surface) were measured.Biochemical changes of the cartilage, corresponding to low dGEMRIC and high T2 values, were more likely to be seen in joints with decreased IBJS and ICJS as well as decreased CT. For instance, dGEMRIC was directly correlated to the IBJS (p=0.001) and ICJS (p=0.001), whereas T2 mapping was inversely correlated to IBJS and ICJS (both p=0.017). Moreover, the degree of osteitis, and to some extent synovitis, was correlated to biochemical cartilage changes as measured by dGEMRIC (p=0.003) or the T2 mapping (p=0.013). By contrast, bone erosions did not correlate to the degree of biochemical cartilage changes.These data support the concept that synovitis and osteitis may be two main triggers for cartilage damage. Thus, the actual inflammatory state of a joint, but not so much the degree of bone erosion, appears to influence cartilage properties in RA.
EVALuna2:10039

Osteoblastic lesion screening with an advanced post-processing package enabling in-plane rib reading in CT-images - Seuß, Hannes; Dankerl, Peter; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (BMC Medical Imaging, 2016)
To evaluate screening and diagnostic accuracy for the detection of osteoblastic rib lesions using an advanced post-processing package enabling in-plane rib reading in CT-images.We retrospectively assessed the CT-data of 60 consecutive prostate cancer patients by applying dedicated software enabling in-plane rib reading. Reading the conventional multiplanar reconstructions was considered to be the reference standard. To simulate clinical practice, the reader was given 10 s to screen for sclerotic rib lesions in each patient applying both approaches. Afterwards, every rib was evaluated individually with both approaches without a time limit. Sensitivities, specificities, positive/negative predictive values and the time needed for detection were calculated depending on the lesion's size (largest diameter < 5 mm, 5-10 mm, > 10 mm).In 53 of 60 patients, all ribs were properly displayed in plane, in five patients ribs were partially displayed correctly, and in two patients none of the ribs were displayed correctly. During the 10-s screening approach all patients with sclerotic rib lesions were correctly identified reading the in-plane images (including the patients without a correct rib segmentation), whereas 14 of 23 patients were correctly identified reading conventional multiplanar images. Overall screening sensitivity, specificity, and positive/negative predictive values were 100/27.0/46.0/100 %, respectively, for in-plane reading and 60.9/100/100/80.4 %, respectively, for multiplanar reading. Overall diagnostic (no time limit) sensitivity, specificity, and positive/negative predictive values of in-plane reading were 97.8/92.8/74.6/99.5 %, respectively. False positive results predominantly occurred for lesions <5 mm in size.In-plane reading of the ribs allows reliable detection of osteoblastic lesions for screening purposes. The limited specificity results from false positives predominantly occurring for small lesions.
EVALuna2:14474

Pediatric cardiac MRI: automated left-ventricular volumes and function analysis and effects of manual adjustments - Hammon, Matthias; Janka, Rolf Matthias; Dankerl, Peter; Glöckler, Martin; Kammerer, Ferdinand J.; Dittrich, Sven; Uder, Michael; Rompel, Oliver (Pediatric Radiology, 2015)
Cardiac MRI is an accurate and reproducible technique for the assessment of left ventricular volumes and function. The accuracy of automated segmentation and the effects of manual adjustments have not been determined in children.To evaluate automated segmentation and the effects of manual adjustments for left ventricular parameter quantification in pediatric cardiac MR images.Left ventricular parameters were evaluated in 45 children with suspected myocarditis (age 13.4 ± 3.5 years, range 4-17 years) who underwent cardiac MRI. Dedicated software was used to automatically segment and adjust the parameters. Results of end-diastolic volume, end-systolic volume, stroke volume, myocardial mass, and ejection fraction were documented before and after apex/base adjustment and after apex/base/myocardial contour adjustment.The software successfully detected the left ventricle in 42 of 45 (93.3%) children; failures occurred in the smallest and youngest children. Of those 42 children, automatically segmented end-diastolic volume (EDV) was 151 ± 47 ml, and after apex/base adjustment it was 146 ± 45 ml, after apex/base/myocardial contour adjustment 146 ± 45 ml. The corresponding results for end-systolic volume (ESV) were 66 ± 32 ml, 63 ± 29 ml and 64 ± 28 ml; for stroke volume (SV) they were 85 ± 25 ml, 83 ± 23 ml and 83 ± 23 ml; for ejection fracture (EF) they were 57 ± 10%, 58 ± 9% and 58 ± 9%, and for myocardial mass (MM) they were 104 ± 31 g, 95 ± 31 g and 94 ± 30 g. Statistically significant differences were found when comparing the EDV/ESV/MM results, the EF results after apex/base adjustment and after apex/base/myocardial contour adjustment and the SV results (except for comparing the SVs after apex/base adjustment and after apex/base/myocardial contour adjustment).Automated segmentation for the evaluation of left ventricular parameters in pediatric MR images proved to be feasible. Automated segmentation + apex/base adjustment provided clinically acceptable parameters for the majority of cases.
EVALuna2:14344

Percent mammographic density and dense area as risk factors for breast cancer - Rauh, C.; Hack, Caroline; Häberle, Lothar; Hein, Alexander; Engel, Anne; Schrauder, Michael G.; Fasching, Peter; Jud, Sebastian; Ekici, Arif Bülent; Loehberg, C. R.; Meier-Meitinger, Martina; Ozan-Mergner, Sevil Julia; et al. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Mammographic characteristics are known to be correlated to breast cancer risk. Percent mammographic density (PMD), as assessed by computer-assisted methods, is an established risk factor for breast cancer. Along with this assessment the absolute dense area (DA) of the breast is reported as well. Aim of this study was to assess the predictive value of DA concerning breast cancer risk in addition to other risk factors and in addition to PMD. Methods: We conducted a case control study with hospital-based patients with a diagnosis of invasive breast cancer and healthy women as controls. A total of 561 patients and 376 controls with available mammographic density were included into this study. We describe the differences concerning the common risk factors BMI, parital status, use of hormone replacement therapy (HRT) and menopause between cases and controls and estimate the odds ratios for PMD and DA, adjusted for the mentioned risk factors. Furthermore we compare the prediction models with each other to find out whether the addition of DA improves the model. Results: Mammographic density and DA were highly correlated with each other. Both variables were as well correlated to the commonly known risk factors with an expected direction and strength, however PMD (ρ = 0.56) was stronger correlated to BMI than DA (ρ = 0.11). The group of women within the highest quartil of PMD had an OR of 2.12 (95 % CI: 1.25-3.62). This could not be seen for the fourth quartile concerning DA. However the assessment of breast cancer risk could be improved by including DA in a prediction model in addition to common risk factors and PMD. Conclusions: The inclusion of the parameter DA into a prediction model for breast cancer in addition to established risk factors and PMD could improve the breast cancer risk assessment. As DA is measured together with PMD in the process of computer-assisted assessment of PMD it might be considered to include it as one additional breast cancer risk factor that is obtained from breast imaging. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: breast cancer; mammographic density; risk

Pericardial tamponade, a diagnostic chameleon: from the historical perspectives to contemporary management - Kaemmerer, Ann-Sophie; Alkhalaileh, Khaleel; Suleiman, Mathieu; Kopp, Markus; Hauer, Christine; May, Matthias; Uder, Michael; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
Background: Pericardial tamponade (PT) early after cardiac surgery is a challenging clinical entity, not infrequently misrecognized and often only detected late in its course. Because the clinical signs of pericardial tamponade can be very unspecific, a high degree of initial suspicion is required to establish the diagnosis. In addition to clinical examination the deployment of imaging techniques is almost always mandatory in order to avoid delays in diagnosis and to initiate any necessary interventions, such as pericardiocentesis or direct cardiac surgical interventions. After a brief overview of how knowledge of PT has developed throughout history, we report on an atypical life-threatening cardiac tamponade after cardiac surgery. A 74-year-old woman was admitted for elective biological aortic valve replacement and aorto-coronary-bypass grafting (left internal mammary artery to left anterior descending artery, single vein graft to right coronary artery). On the 10th postoperative day, the patient unexpectedly deteriorated. She rapidly developed epigastric pain radiating to the left upper abdomen, and features of low peripheral perfusion and shock. There were no clear signs of pericardial tamponade either clinically or echocardiographically. Therefore, for further differential diagnosis, a contrast-enhanced computed tomography scan was performed under clinical suspicion of acute abdomen. Unexpectedly, active bleeding distally from the right coronary anastomosis was revealed. While the patient was prepared for operative revision, she needed cardiopulmonary resuscitation, which was successful. Intraoperatively, the source of bleeding was located and surgically relieved. The subsequent postoperative course was uneventful. Conclusions: In the first days after cardiac surgery, the occurrence of life-threatening situations, such as cardiac tamponade, must be expected. Especially if the symptoms are atypical, the entire diagnostic armamentarium must be applied to identify the origin of the complaints, which may be cardiac, but also non-cardiac. Central message: A high level of suspicion, immediate diagnostic confirmation, and rapid treatment are required to recognize and successfully treat such an emergency (Fig. 5). Perspective: Pericardial tamponade should always be considered as a complication of cardiac surgery, even when symptoms are atypical. The full range of diagnostic tools must be used to identify the origin of the complaints, which may be cardiac, but also non-cardiac (Fig. 5).
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cardiac tamponade; Diagnostics; Historical aspects; Pericardial effusion; Postoperative complication

Personalization of thoracoabdominal CT examinations using scanner integrated clinical decision support systems – Impact on the acquisition technique, scan range, and reconstruction type - Daniel, Sascha; Kopp, Markus; Vollbrecht, Thomas; Zeilinger, Martin; Fitz, Tim; Muttke, Armin; Feuerlein, Ute; Uder, Michael; May, Matthias (European Journal of Radiology, 2023)
Objectives: This study evaluates the impact of a scanner-integrated, customized clinical decision support system (CDSS) on the acquisition technique, scan range, and reconstruction in thoracoabdominal CT. Materials and Methods: We applied CDSS in contrast–enhanced examinations of the trunk with various clinical indications on a recent scanner with the capability of dual-energy CT (DECT), anatomic landmark detection (ALD), and iterative metal-artifact reduction (MAR). Simple and comprehensive questions about the patient's breath hold capability, the anatomical region of interest, and metal implants can be answered after the localizer. The acquisition technique (single energy, SECT, or dual energy), scan range (chest-abdomen-pelvis or chest-abdomen), and reconstruction technique (with or without MAR) were then automatically adapted in the examination protocols in coherence with these selections. Retrospectively, we compared the usage rates for these techniques in 624 examinations on the study scanner with 740 examinations on a comparable scanner without CDSS. Subgroup analysis of effective dose (ED), scan duration, and image quality (IQ) was performed in the study group. Results: CDSS leads to an increased usage rate of DECT (64.4% vs. 2.8%) and MAR (75.4% vs. 44.0%). All scan range adaptations by ALD were successful. The resulting subjective IQ between single energy and DECT acquisitions was comparable (all p > 0.05). Scan duration was significantly longer in DECT than in SECT (16.9 s vs. 6.5 s; p < 0.001). However, the objective IQ was significantly higher in DECT (CNRD 2.1 vs. 1.8; p < 0.01), and the ED significantly lower (6.7 mSv vs. 7.6 mSv; p = 0.004). Conclusion: CDSS for thoracoabdominal CT leads to a substantially increased usage rate of innovative techniques during acquisition and reconstruction. Patients with adapted protocols benefit from improved image quality and increased post-processing options at lower radiation doses.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Clinical decision support systems; CT; Dual-energy; Metal artifact reduction; Radiation dose

Personalized Chest Computed Tomography: Minimum Diagnostic Radiation Dose Levels for the Detection of Fibrosis, Nodules, and Pneumonia - May, Matthias; Heiß, Rafael; Köhnen, Julia; Wetzl, Matthias; Wiesmüller, Marco; Treutlein, Christoph; Uder, Michael; Kopp, Markus; Bräuer, Lars (Investigative Radiology, 2022)
OBJECTIVES: The purpose of this study was to evaluate the minimum diagnostic radiation dose level for the detection of high-resolution (HR) lung structures, pulmonary nodules (PNs), and infectious diseases (IDs). MATERIALS AND METHODS: A preclinical chest computed tomography (CT) trial was performed with a human cadaver without known lung disease with incremental radiation dose using tin filter-based spectral shaping protocols. A subset of protocols for full diagnostic evaluation of HR, PN, and ID structures was translated to clinical routine. Also, a minimum diagnostic radiation dose protocol was defined (MIN). These protocols were prospectively applied over 5 months in the clinical routine under consideration of the individual clinical indication. We compared radiation dose parameters, objective and subjective image quality (IQ). RESULTS: The HR protocol was performed in 38 patients (43%), PN in 21 patients (24%), ID in 20 patients (23%), and MIN in 9 patients (10%). Radiation dose differed significantly among HR, PN, and ID (5.4, 1.2, and 0.6 mGy, respectively; P < 0.001). Differences between ID and MIN (0.2 mGy) were not significant (P = 0.262). Dose-normalized contrast-to-noise ratio was comparable among all groups (P = 0.087). Overall IQ was perfect for the HR protocol (median, 5.0) and decreased for PN (4.5), ID-CT (4.3), and MIN-CT (2.5). The delineation of disease-specific findings was high in all dedicated protocols (HR, 5.0; PN, 5.0; ID, 4.5). The MIN protocol had borderline IQ for PN and ID lesions but was insufficient for HR structures. The dose reductions were 78% (PN), 89% (ID), and 97% (MIN) compared with the HR protocols. CONCLUSIONS: Personalized chest CT tailored to the clinical indications leads to substantial dose reduction without reducing interpretability. More than 50% of patients can benefit from such individual adaptation in a clinical routine setting. Personalized radiation dose adjustments with validated diagnostic IQ are especially preferable for evaluating ID and PN lesions.
CRIS-Team Scopus Importer:2022-02-25

Personalized computed tomography - Automated estimation of height and weight of a simulated digital twin using a 3D camera and artificial intelligence - Geißler, Frederik; Heiß, Rafael; Kopp, Markus; Wiesmüller, Marco; Saake, Marc; Wüst, Wolfgang; Wimmer, Andreas; Prell, Veronika; Uder, Michael; May, Matthias (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
Purpose The aim of this study was to develop an algorithm for automated estimation of patient height and weight during computed tomography (CT) and to evaluate its accuracy in everyday clinical practice. Materials and methods Depth images of 200 patients were recorded with a 3D camera mounted above the patient table of a CT scanner. Reference values were obtained using a calibrated scale and a measuring tape to train a machine learning algorithm that fits a patient avatar into the recorded patient surface data. The resulting algorithm was prospectively used on 101 patients in clinical practice and the results were compared to the reference values and to estimates by the patient himself, the radiographer and the radiologist. The body mass index was calculated from the collected values for each patient using the WHO formula. A tolerance level of 5kg was defined in order to evaluate the impact on weight-dependent contrast agent dosage in abdominal CT. Results Differences between values for height, weight and BMI were non-significant over all assessments (p > 0.83). The most accurate values for weight were obtained from the patient information (R2=0.99) followed by the automated estimation via 3D camera (R2=0.89). Estimates by medical staff were considerably less precise (radiologist: R2=0.78, radiographer: R2=0.77). A body-weight dependent dosage of contrast agent using the automated estimations matched the dosage using the reference measurements in 65 % of the cases. The dosage based on the medical staff estimates would have matched in 49 % of the cases. Conclusion Automated estimation of height and weight using a digital twin model from 3D camera acquisitions provide a high precision for protocol design in computer tomography. Key points: Machine learning can calculate patient-avatars from 3D camera acquisitions. Height and weight of the digital twins are comparable to real measurements of the patients. Estimations by medical staff are less precise. The values can be used for calculation of contrast agent dosage. Citation Format Geissler F, Heiβ R, Kopp M et al. Personalized computed tomography - Automated estimation of height and weight of a simulated digital twin using a 3D camera and artificial intelligence. Fortschr Röntgenstr 2021; 193: 437-445.
CRIS-Team Scopus Importer:2021-04-09
Keywords: 3D camera; automatic data collection; CT; digital twin; machine learning

PHOTOREALISTIC DEPICTION OF RHEUMATIC PATHOLOGIES BY CINEMATIC RENDERING FACILITATES DISEASE UNDERSTANDING OF PATIENTS WITH RHEUMATIC DISEASES - Pachowsky, Milena; Morf, Harriet; Simon, David; Schönau, Verena; Valor, L.; Knitza, Johannes; Engel, K.; Uder, Michael; Hueber, Axel; Schett, Georg; Kleyer, Arnd (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

PoCaP Corpus: A Multimodal Dataset for Smart Operating Room Speech Assistant Using Interventional Radiology Workflow Analysis - Demir, Kubilay Can; May, Matthias; Schmid, Axel; Uder, Michael; Breininger, Katharina; Weise, Tobias; Maier, Andreas; Yang, Seung Hee (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2022)
This paper presents a new multimodal interventional radiology dataset, called PoCaP (Port Catheter Placement) Corpus. This corpus consists of speech and audio signals in German, X-ray images, and system commands collected from 31 PoCaP interventions by six surgeons with average duration of 81.4 ± 41.0 min. The corpus aims to provide a resource for developing a smart speech assistant in operating rooms. In particular, it may be used to develop a speech-controlled system that enables surgeons to control the operation parameters such as C-arm movements and table positions. In order to record the dataset, we acquired consent by the institutional review board and workers’ council in the University Hospital Erlangen and by the patients for data privacy. We describe the recording set-up, data structure, workflow and preprocessing steps, and report the first PoCaP Corpus speech recognition analysis results with 11.52% word error rate using pretrained models. The findings suggest that the data has the potential to build a robust command recognition system and will allow the development of a novel intervention support systems using speech and image processing in the medical domain.
CRIS-Team Scopus Importer:2022-10-14
Keywords: Automatic speech recognition; Interventional radiology; Multimodal interventional corpus; Operating room smart assistant; Port catheter placement; Surgical data science

Position Paper of the DRG, DGNR, GPR, DeGIR, ORG and DGP on the Use of clinical Data for scientific Purposes - Kuhl, Christiane; Walter, Peter; Zimmer, Claus; Mentzel, Hans-Joachim; Reimer, Peter; Hausegger, Klaus A.; Baretton, Gustavo; Hoffmann, Ralf-Thorsten; Heindel, Walter; Dueber, Christoph; Uder, Michael; Nikolaou, Konstantin; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
CRIS-Team WoS Importer:2021-02-19

Potential for Radiation Dose Reduction in Dual-Source Computed Tomography of the Lung in the Pediatric and Adolescent Population Compared to Digital Radiography - Wetzl, Matthias; May, Matthias; Weinmann, Daniel; Hammon, Matthias; Kopp, Markus; Ruppel, Renate; Trollmann, Regina; Wölfle, Joachim; Uder, Michael; Rompel, Oliver (Diagnostics, 2021)
Low-dose dual-source computed tomography (DSCT) protocols for the evaluation of lung diseases in children and adolescents are of importance since this age group is particularly prone to radiation damage. The aim of this study was to evaluate image quality of low-dose DSCT of the lung and to assess the potential of radiation dose reduction compared to digital radiographs (DR). Three groups, each consisting of 19 patients, were examined with different DSCT protocols using tin prefiltration (Sn96/64/32 ref. mAs at 100 kV). Different strengths of iterative reconstruction were applied (ADMIRE 2/3/4). DSCT groups were compared to 19 matched patients examined with posterior-anterior DR. Diagnostic confidence, detectability of anatomical structures and small lung lesions were evaluated on a 4-point Likert scale (LS 1 = unacceptable, 4 = fully acceptable; a value >= 3 was considered acceptable). Effective dose (ED) was 31-/21-/9-fold higher in Sn96/Sn64/Sn32 compared to DR. Diagnostic confidence was sufficient in Sn96/Sn64 (LS 3.4/3.2), reduced in Sn32 (LS 2.7) and the worst in DR (LS 2.4). In DSCT, detectability of small anatomical structures was always superior to DR (p < 0.05). Mean lesion size ranged from 5.1-7 mm; detectability was acceptable in all DSCT groups (LS 3.0-3.4) and superior to DR (LS 1.9; p < 0.05). Substantial dose lowering in DSCT of the pediatric lung enables acceptable detectability of small lung lesions with a radiation dose being about 10-fold higher compared to DR.
CRIS-Team WoS Importer:2021-03-12

Potential Limitations of Established Blood-Dosimetry Models for Lu-177 Therapy - Ritt, Philipp; Jobic, C.; Grings, Andreas; Beck, Michael; Schmidkonz, Christian; Kuwert, Torsten; Uder, Michael; Brand, Michael (EUROPEAN JOURNAL OF NUCLEAR MEDICINE AND MOLECULAR IMAGING, 2021)
CRIS-Team WoS Importer:2022-01-07

Potential of spiral breast computed tomography to increase patient comfort compared to DM - Wetzl, Matthias; Wenkel, Evelyn; Dietzel, Matthias; Siegler, Lisa; Emons, Julius; Dethlefsen, Ebba; Heindl, Felix; Kuhl, Christiane; Uder, Michael; Ohlmeyer, Sabine (European Journal of Radiology, 2021)
Purpose: To intra-individually compare patient comfort of spiral breast computed tomography (SBCT) versus digital mammography (DM).
CRIS-Team WoS Importer:2022-02-04

Practicability of hygienic wrapping of touchscreen operated mobile devices in a clinical setting - Hammon, Matthias; Kunz, Hans Bernd; Dinzl, Veronika; Kammerer, Ferdinand J.; Schwab, Siegfried; Bogdan, Christian; Uder, Michael; Schlechtweg, Philipp (PLoS ONE, 2014)
To prove effectiveness of wrapping tablet computers in order to reduce microbiological contamination and to evaluate whether a plastic bag-covered tablet leads to impaired user satisfaction or touchscreen functionality.Within a period of 11 days 115 patients were provided with a tablet computer while waiting for their magnetic resonance imaging examination. Every day the contamination of the surface of the tablet was determined before the first and after the final use. Before the device was handed over to a patient, it was enclosed in a customized single-use plastic bag, which was analyzed for bacterial contamination after each use. A questionnaire was applied to determine whether the plastic bag impairs the user satisfaction and the functionality of the touchscreen.Following the use by patients the outside of the plastic bags was found to be contaminated with various bacteria (657.5 ± 368.5 colony forming units/day); some of them were potentially pathogenic. In contrast, the plastic bag covered surface of the tablet was significantly less contaminated (1.7 ± 1.9 colony forming units/day). Likewise, unused plastic bags did not show any contamination. 11% of the patients reported problems with the functionality of the touchscreen. These patients admitted that they had never used a tablet or a smartphone before.Tablets get severely contaminated during usage in a clinical setting. Wrapping with a customized single-use plastic bag significantly reduces microbiological contamination of the device, protects patients from the acquisition of potentially pathogenic bacteria and hardly impairs the user satisfaction and the functionality of the touchscreen.
EVALuna2:7657

Precision of handheld multispectral optoacoustic tomography for muscle imaging - Wagner, Anna; Danko, Vera; Federle, Anna; Klett, Daniel; Simon, David; Heiß, Rafael; Jüngert, Jörg M.; Uder, Michael; Schett, Georg; Neurath, Markus; Wölfle, Joachim; Waldner, Maximilian; et al. (Photoacoustics, 2021)
Photo-or optoacoustic imaging (OAI) allows quantitative imaging of target tissues. Using multi-wavelength illumination with subsequent ultrasound detection, it may visualize a variety of different chromophores at centimeter depth. Despite its non-invasive, label-free advantages, the precision of repeated measurements for clinical applications is still elusive. We present a multilayer analysis of n = 1920 imaging datasets obtained from a prospective clinical trial (NCT03979157) in n = 10 healthy adult volunteers. All datasets were analyzed for 13 single wavelengths (SWL) between 660 nm–1210 nm and five MSOT-parameters (deoxygenated/oxygenated/total hemoglobin, collagen and lipid) by a semi-automated batch mode software. Intraclass correlation coefficients (ICC) were good to excellent for intrarater (SWL: 0.82–0.92; MSOT-parameter: 0.72−0.92) and interrater reproducibility (SWL: 0.79−0.87; MSOT-parameter: 0.78−0.86), with the exception for MSOT-parameter lipid (interrater ICC: 0.56). Results were stable over time, but exercise-related effects as well as inter-and intramuscular variability were observed. The findings of this study provide a framework for further clinical OAI implementation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: MSOT; Multispectral optoacoustic tomography; Muscle imaging; Optoacoustics; Photoacoustics

Predicting mammographic density with linear ultrasound transducers - Behrens, Annika; Fasching, Peter; Schwenke, Eva; Gaß, Paul; Häberle, Lothar; Heindl, Felix; Heusinger, Katharina; Lotz, Laura; Lubrich, Hannah; Preuß, Caroline; Schneider, Michael; Schulz-Wendtland, Rüdiger; et al. (European Journal of Medical Research, 2023)
Background: High mammographic density (MD) is a risk factor for the development of breast cancer (BC). Changes in MD are influenced by multiple factors such as age, BMI, number of full-term pregnancies and lactating periods. To learn more about MD, it is important to establish non-radiation-based, alternative examination methods to mammography such as ultrasound assessments. Methods: We analyzed data from 168 patients who underwent standard-of-care mammography and performed additional ultrasound assessment of the breast using a high-frequency (12 MHz) linear probe of the VOLUSON® 730 Expert system (GE Medical Systems Kretztechnik GmbH & Co OHG, Austria). Gray level bins were calculated from ultrasound images to characterize mammographic density. Percentage mammographic density (PMD) was predicted by gray level bins using various regression models. Results: Gray level bins and PMD correlated to a certain extent. Spearman’s ρ ranged from − 0.18 to 0.32. The random forest model turned out to be the most accurate prediction model (cross-validated R 2, 0.255). Overall, ultrasound images from the VOLUSON® 730 Expert device in this study showed limited predictive power for PMD when correlated with the corresponding mammograms. Conclusions: In our present work, no reliable prediction of PMD using ultrasound imaging could be observed. As previous studies showed a reasonable correlation, predictive power seems to be highly dependent on the device used. Identifying feasible non-radiation imaging methods of the breast and their predictive power remains an important topic and warrants further evaluation. Trial registration 325-19 B (Ethics Committee of the medical faculty at Friedrich Alexander University of Erlangen-Nuremberg, Erlangen, Germany).
CRIS-Team Scopus Importer:2023-10-13
Keywords: Breast cancer risk; Percent mammographic density; Ultrasound

Prediction of early metastatic disease in experimental breast cancer bone metastasis by combining PET/CT and MRI parameters to a Model-Averaged Neural Network - Ellmann, Stephan; Seyler, Lisa; Evers, Jochen; Heinen, Henrik; Bozec, Aline; Prante, Olaf; Kuwert, Torsten; Uder, Michael; Bäuerle, Tobias (Bone, 2019)
Macrometastases in bone are preceded by bone marrow invasion of disseminated tumor cells. This study combined functional imaging parameters from FDG-PET/CT and MRI in a rat model of breast cancer bone metastases to a Model-averaged Neural Network (avNNet) for the detection of early metastatic disease and prediction of future macrometastases. Metastases were induced in 28 rats by injecting MDA-MB-231 breast cancer cells into the right superficial epigastric artery, resulting in the growth of osseous metastases in the right hind leg of the animals. All animals received FDG-PET/CT and MRI at days 0, 10, 20 and 30 after tumor cell injection. In total, 18/28 rats presented with metastases at days 20 or 30 (64.3%). None of the animals featured morphologic bone lesions during imaging at day 10, and the imaging parameters acquired at day 10 did not differ significantly between animals with metastases at or after day 20 and those without (all p > 0.3). The avNNet trained with the imaging parameters acquired at day 10, however, achieved an accuracy of 85.7% (95% CI 67.3-96.0%) in predicting future macrometastatic disease (ROCAUC 0.90; 95% CI 0.76-1.00), and significantly outperformed the predictive capacities of all single parameters (all p <= 0.02). The integration of functional FDG-PET/CT and MRI parameters into an avNNet can thus be used to predict macrometastatic disease with high accuracy, and their combination might serve as a surrogate marker for bone marrow invasion as an early metastatic process that is commonly missed during conventional staging examinations.
CRIS-Team WoS Importer:2019-02-27

Predictive Value of Multiparametric MRI for Response to Single-Cycle Induction Chemo-Immunotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma - Hellwig, Konstantin; Ellmann, Stephan; Eckstein, Markus; Wiesmüller, Marco; Rutzner, Sandra; Semrau, Sabine; Frey, Benjamin; Gaipl, Udo; Hartmann, Arndt; Iro, Heinrich; Fietkau, Rainer; Uder, Michael; et al. (Frontiers in Oncology, 2021)
Objectives
CRIS-Team WoS Importer:2021-11-19

Preoperative assessment of the aortic arch in children younger than 1 year with congenital heart disease: utility of low-dose high-pitch dual-source computed tomography. A single-centre, retrospective analysis of 62 cases - Glöckler, Martin; Halbfass, Julia; Koch, Andreas; Dittrich, Sven; Achenbach, Stephan; Rueffer, Andre; Ihlenburg, Katharina Susanne; Cesnjevar, Robert; May, Matthias; Uder, Michael; Rompel, Oliver (European Journal of Cardio-Thoracic Surgery, 2014)
To evaluate the feasibility, image quality and impact of 3D imaging in low-dose high-pitch dual-source computed tomography (DSCT) to assess arbitrary anatomical malformations of the aortic arch in children <1 year of age with congenital heart disease (CHD).Between January 2010 and May 2013, DSCT was performed to assess the aortic arch anatomy in a total of 62 consecutive patients with CHD (aged 0-348 days). DSCT was used whenever conventional echocardiography was not sufficient to display the complex anatomy entirely. Image data acquisition was realized within a single cardiac cycle using prospective ECG triggering. 3D reconstruction for surgical planning was performed. Image quality was assessed retrospectively, using a 4-point scale from '1 = no artefacts' to '4 = uninterpretable'. The accuracy and impact of the 3D reconstructions was compared with intraoperative findings using a 5-point scale (from '1 = essential' to '5 = misleading'). Administered radiation exposure was evaluated.Imaging was successful in all patients, image quality was rated 1.34 on the 4-point scale and the impact of the 3D reconstructions for surgical planning was 2.05 on the 5-point scale. Mean dose-length product was 6.8 ± 2.6 mGy cm, and the effective dose was 0.45 ± 0.13 mSv (0.21-0.74).DSCT is a fast and appropriate imaging modality in the preoperative assessment of the aortic arch for surgical planning in CHD.
EVALuna2:11864

Prevalence and influencing factors for artifact development in breast MRI-derived maximum intensity projections - Kapsner, Lorenz; Balbach, Eva; Laun, Frederik Bernd; Baumann, Lukas; Ohlmeyer, Sabine; Uder, Michael; Bickelhaupt, Sebastian; Wenkel, Evelyn (Acta Radiologica, 2023)
Background: Magnetic resonance imaging (MRI) provides high diagnostic sensitivity for breast cancer. However, MRI artifacts may impede the diagnostic assessment. This is particularly important when evaluating maximum intensity projections (MIPs), such as in abbreviated MRI (AB-MRI) protocols, because high image quality is desired as a result of fewer sequences being available to compensate for problems. Purpose: To describe the prevalence of artifacts on dynamic contrast enhanced (DCE) MRI-derived MIPs and to investigate potentially associated attributes. Material and Methods: For this institutional review board approved retrospective analysis, MIPs were generated from subtraction series and cropped to represent the left and right breasts as regions of interest. These images were labeled by three independent raters regarding the presence of MRI artifacts. MRI artifact prevalence and associations with patient characteristics and technical attributes were analyzed using descriptive statistics and generalized linear models (GLMMs). Results: The study included 2524 examinations from 1794 patients (median age 50 years), performed on 1.5 and 3.0 Tesla MRI systems. Overall inter-rater agreement was kappa = 0.54. Prevalence of significant unilateral artifacts was 29.2% (736/2524), whereas bilateral artifacts were present in 37.8% (953/2524) of all examinations. According to the GLMM, artifacts were significantly positive associated with age (odds ratio [OR] = 1.52) and magnetic field strength (OR = 1.55), whereas a negative effect could be shown for body mass index (OR = 0.95). Conclusion: MRI artifacts on DCE subtraction MIPs of the breast, as used in AB-MRI, are a relevant topic. Our results show that, besides the magnetic field strength, further associated attributes are patient age and body mass index, which can provide possible targets for artifact reduction.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Artifacts; breast; contrast agent; magnetic resonance imaging; prevalence

Prognostic value of cta-derived left ventricular mass in neonates with congenital heart disease - Ellmann, Stephan; Nickel, Julie-Marie; Heiß, Rafael; El Amrani, Nouhayla; Wüst, Wolfgang; Rompel, Oliver; Rueffer, Andre; Cesnjevar, Robert; Dittrich, Sven; Uder, Michael; May, Matthias (Diagnostics, 2021)
For therapeutic decisions regarding uni-or biventricular surgical repair in congenital heart disease (CHD), left ventricular mass (LVM) is an important factor. The aim of this retrospective study was to determine the LVM of infants with CHD in thoracic computed tomography angiographies (CTAs) and to evaluate its usefulness as a prognostic parameter, with special attention paid to hypoplastic left heart (HLH) patients. Manual segmentation of the left ventricular endo-and epicardial volumes was performed in CTAs of 132 infants. LVMs were determined from these volumes and normalized to body surface area. LVMs of patients with different types of CHD were compared to each other using analyses of variances (ANOVA). An LVM cutoff for discrimination between uni-and biventricular repair was determined using receiver operating characteristics. Survival rates were calculated using Kaplan–Meier statistics. Patients with a clinical diagnosis of an HLH had significantly lower mean LVM (21.88 g/m2) compared to patients without applicable disease (50.22 g/m2; p < 0.0001) and compared to other CHDs, including persistent truncus arteriosus, left ventricular outflow tract obstruction, transposition of the great arteries, pulmonary artery stenosis or atresia, and double-outlet right ventricle (all, p < 0.05). The LVM cutoff for uni-vs. biventricular surgery was 33.9 g/m2 (sensitivity: 82.3%; specificity: 73.7%; PPV: 94.9%). In a subanalysis of HLH patients, a sensitivity of 50.0%, specificity of 100%, PPV of 100%, and NPV of 83.3% was determined. Patient survival was not significantly different between the surgical approaches or between patients with LVM above or below the cutoff. LVM can be measured in chest CTA of newborns with CHD and can be used as a prognostic factor.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Cardiac computed tomography; Computed tomography angiography; Congenital heart disease; Heart imaging; Heart surgery; Hypoplastic left heart

Prospectively ECG-triggered high-pitch coronary angiography with third-generation dual-source CT at 70 kVp tube voltage: Feasibility, image quality, radiation dose, and effect of iterative reconstruction - Hell, Michaela M.; Bittner, Daniel; Schuhbaeck, Annika; Muschiol, Gerd; Brand, Michael; Lell, Michael; Uder, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
Low tube voltage reduces radiation exposure in coronary CT angiography (CTA). Using 70 kVp tube potential has so far not been possible because CT systems were unable to provide sufficiently high tube current with low voltage.We evaluated feasibility, image quality (IQ), and radiation dose of coronary CTA using a third-generation dual-source CT system capable of producing 450 mAs tube current at 70 kVp tube voltage.Coronary CTA was performed in 26 consecutive patients with suspected coronary artery disease, selected for body weight <100 kg and heart rate <60 beats/min. High-pitch spiral acquisition was used. Filtered back projection (FBP) and iterative reconstruction (IR) algorithms were applied. IQ was assessed using a 4-point rating scale (1 = excellent, 4 = nondiagnostic) and objective parameters.Mean age was 62 ± 9 years (46% males; mean body mass index, 27.7 ± 3.8 kg/m(2); mean heart rate, 54 ± 5 beats/min). Mean dose-length product was 20.6 ± 1.9 mGy × cm; mean estimated effective radiation dose was 0.3 ± 0.03 mSv. Diagnostic IQ was found in 365 of 367 (FBP) and 366 of 367 (IR) segments (P nonsignificant). IQ was rated "excellent" in 53% (FBP) and 86% (IR) segments (P = .001) and "nondiagnostic" in 2 (FBP) and 1 segment (IR) (P nonsignificant). Mean IQ score was lesser in FBP vs IR (1.5 ± 0.4 vs 1.1 ± 0.2; P < .001). Image noise was lower in IR vs FBP (60 ± 10 HU vs 74 ± 8 HU; P < .001).In patients <100 kg and with a regular heart rate <60 beats/min, third-generation dual-source CT using high-pitch spiral acquisition and 70 kVp tube voltage is feasible and provides both robust IQ and very low radiation exposure.
EVALuna2:11954

Pulmonary Dysfunction after Pediatric COVID-19 - Heiß, Rafael; Tan, Lina; Schmidt, Sandy; Regensburger, Adrian; Ewert, Franziska; Mammadova, Dilbar; Bühler, Adrian; Vogel-Claussen, Jens; Voskrebenzev, Andreas; Rauh, Manfred; Rompel, Oliver; Nagel, Armin Michael; et al. (Radiology, 2022)
Background Long COVID occurs in lower frequency in children and adolescents than in adults. Morphologic and free-breathing phase-resolved functional low-field MRI may identify persistent pulmonary manifestations after SARS-CoV-2 infection. Purpose To characterize both morphologic and functional changes of lung parenchyma on low-field MRI in children and adolescents with post COVID-19 compared with healthy controls. Materials and Methods Between August and December 2021, a cross-sectional, prospective clinical trial using low-field MRI was performed in children and adolescents from a single academic medical center. The primary outcome was the frequency of morphologic changes on MRI. Secondary outcomes included MRI-derived functional proton ventilation and perfusion parameters. Clinical symptoms, the duration from positive RT-PCR test and serological parameters were compared with imaging results. Nonparametric tests for pairwise and corrected tests for groupwise comparisons were applied to assess differences in healthy controls, recovered participants and with long COVID. Results A total of 54 participants post COVID-19 infection (mean age, 11 years ±3 [SD], 56 males) and 9 healthy controls (mean age, 10 years ±3 [SD], 70 males) were included: 29 (54%) in the COVID-19 group had recovered from infection and 25 (46%) were classified as having long COVID on the day of enrollment. Morphologic abnormality was identified in one recovered participant. Both ventilated and perfused lung parenchyma (V/Q match) was reduced from 81±6.1% in healthy controls to 62±19% (P =.006) in the recovered group and 60±20% (P=.003) in the long COVID group. V/Q match was lower in post COVID patients with infection less than 180 days (63±20%, P=.03), 180 to 360 days (63±18%, P=0.03) and 360 days ago (41±12%, P<.001) as compared with the never-infected healthy controls (81±6.1%). Conclusion Low-field MRI showed persistent pulmonary dysfunction in both children and adolescents recovered from COVID-19 and with long COVI

Quantification of hand muscle volume and composition in patients with rheumatoid arthritis, psoriatic arthritis and psoriasis - Friedberger, Andreas; Figueiredo, Camille; Grimm, Alexandra; Oliveira, Isabelle; Bäuerle, Tobias; Rech, Jürgen; Kleyer, Arnd; Simon, David; Uder, Michael; Schett, Georg; Engelke, Klaus (BMC Musculoskeletal Disorders, 2020)
Background Psoriasis (Pso), psoriatic arthritis (PsA) and rheumatoid arthritis (RA) are inflammatory diseases. PsA and RA are characterized by bone and muscle loss. In RA, bone loss has been extensively characterized, but muscle loss has, to the best of our knowledge, not been quantified to date. Methods A random forest based segmentation method was used to analyze hand muscle volume in T1 weighted MRI images of 330 patients suffering from Pso, PsA or RA. In addition, fat volume was quantified using MRI Dixon sequences in a small subset (n = 32). Results Males had a higher relative muscle volume than females (14% for Pso, 11% for PsA, n.s. for RA). Between 40 and 80 years male Pso patients lost 13%, male PsA patients 16%, male RA patients 23% and female PsA patients 30% of their relative muscle volume. After adjustment for age, relative muscle volume in males RA patients was 16% and in female RA patients 9% lower than in Pso patients. In male RA patients relative muscle volume was 13% lower in than in male PsA patients. There was no difference in females. A significant negative correlation (R-2 = 0.18) between relative intramuscular fat content relative hand muscle volume was observed. Conclusion These preliminary data showed that relative hand muscle volume significantly decreased with age in male and female patients with Pso, PsA and RA patients. Independent of age, relative hand muscle volume was significantly smaller in patients with RA compared to the patients with Pso and the difference was twice as large in males compared to females. Also in male but not in female RA patients relative hand muscle volume was significantly smaller than in PsA patients.
CRIS-Team WoS Importer:2020-04-14

Quantification of plaque lipids in the aortic root of ApoE-deficient mice by 3D DIXON magnetic resonance imaging in an ex vivo model - Dietel, Barbara; Budinsky, Lubos; Kühn, Constanze; Uder, Michael; Achenbach, Stephan; Heß, Andreas (European Radiology, 2015)
To establish a dedicated protocol for the three-dimensional (3D) quantification of plaque lipids in apolipoprotein E-deficient (apoE(-/-)) mice using ex vivo MRI.ApoE(-/-) mice were fed a high-fat diet (n = 10) or normal food (n = 10) for 3 months. Subsequently, a 3D FLASH MRI sequence was used to view the anatomy of the aortic root in the isolated hearts, where a 3D double-echo two-excitation pulse sequence (DIXON sequence) was used to selectively image plaque lipids. The vessel wall, lumen and plaque lipid volumes were quantified by MRI and histology for correlation analysis.DIXON MRI allowed visualisation and accurate quantification of plaque lipids. When comparing the vessel wall, lumen and plaque lipid sizes in the aortic root, Bland-Altman and linear regression analysis revealed a close correlation between MRI results and the histological data both on a slice-by-slice basis and of the volumetric measurements (vessel wall: r (2) = 0.775, p < 0.001; vessel lumen: r (2) = 0.875; p = 0.002; plaque lipid: r (2) = 0.819, p = 0.003).The combination of 3D FLASH and DIXON-sequence MRI permits an accurate ex vivo assessment of the investigated plaque parameters in the aortic root of mice, particularly the lipid content.o Ex vivo MRI allows high resolution quantification of plaque parameters in mice o DIXON MRI enables visualisation of plaque lipids in the aortic root of mice o A close correlation between histology and MRI quantifies plaque parameters o Preservation of tissue integrity allows additional analysis to be performed o Short measurement time may permit the translation into in vivo measurements.
EVALuna2:11953

Quantitative 1H and 23Na muscle MRI in Facioscapulohumeral muscular dystrophy patients - Gerhalter, Teresa; Marty, Benjamin; Gast, Lena; Porzelt, Katharina; Heiß, Rafael; Uder, Michael; Schwab, Stefan; Carlier, Pierre G.; Nagel, Armin Michael; Türk, Matthias (Journal of Neurology, 2020)
Objective: Our aim was to assess the role of quantitative 1H and 23Na MRI methods in providing imaging biomarkers of disease activity and severity in patients with Facioscapulohumeral muscular dystrophy (FSHD). Methods: We imaged the lower leg muscles of 19 FSHD patients and 12 controls with a multimodal MRI protocol to obtain STIR-T2w images, fat fraction (FF), water T2 (wT2), water T1 (wT1), tissue sodium concentration (TSC), and intracellular-weighted sodium signal (inversion recovery (IR) and triple quantum filter (TQF) sequence). In addition, the FSHD patients underwent muscle strength testing. Results: Imaging biomarkers related with water mobility (wT1 and wT2) and ion homeostasis (TSC, IR, TQF) were increased in muscles of FSHD patients. Muscle groups with FF > 10% had higher wT2, wT1, TSC, IR, and TQF values than muscles with FF < 10%. Muscles with FF < 10% resembled muscles of healthy controls for these MRI disease activity measures. However, wT1 was increased in few muscles without fat replacement. Furthermore, few STIR-negative muscles (n = 11/76) exhibited increased wT1, TSC, IR or TQF. Increased wT1 as well as 23Na signals were also present in muscles with normal wT2. Muscle strength was related to the mean FF and all imaging biomarkers of tibialis anterior except wT2 were correlated with dorsal flexion. Conclusion: The newly evaluated imaging biomarkers related with water mobility (wT1) and ion homeostasis (TSC, IR, TQF) showed different patterns compared to the established markers like FF in muscles of FSHD patients. These quantitative biomarkers could thus contain valuable complementary information for the early characterization of disease progression.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Facioscapulohumeral muscular dystrophy; Quantitative MRI; Sodium MRI; Triple quantum filter; Water T

Quantitative 7T sodium magnetic resonance imaging of the human brain using a 32-channel phased-array head coil: Application to patients with secondary progressive multiple sclerosis - Wilferth, Tobias; Mennecke, Angelika; Gast, Lena; Lachner, Sebastian; Müller, Max; Rothhammer, Veit; Huhn, Konstantin; Uder, Michael; Dörfler, Arnd; Nagel, Armin Michael; Schmidt, Manuel (NMR in Biomedicine, 2022)
Apparent tissue sodium concentrations (aTSCs) determined by 23Na brain magnetic resonance imaging (MRI) have the potential to serve as a biomarker in pathologies such as multiple sclerosis (MS). However, the quantification is hindered by the intrinsically low signal-to-noise ratio of 23Na MRI. The purpose of this study was to improve the accuracy and reliability of quantitative 23Na brain MRI by implementing a dedicated postprocessing pipeline and to evaluate the applicability of the developed approach for the examination of MS patients. 23Na brain MRI measurements of 13 healthy volunteers and 17 patients with secondary progressive multiple sclerosis (SPMS) were performed at 7 T using a dual-tuned 23Na/1H birdcage coil with a receive-only 32-channel phased array. The aTSC values were determined for normal appearing white matter (NAWM) and normal appearing gray matter (NAGM) in healthy subjects and SPMS patients. Signal intensities were normalized using the mean cerebrospinal fluid (CSF) sodium concentration determined in 37 separate patients receiving a spinal tap for routine diagnostic purposes. Five volunteers underwent MRI examinations three times in a row to assess repeatability. Coefficients of variation (CoVs) were used to quantify the repeatability of the proposed method. aTSC values were compared regarding brain regions and subject cohort using the paired-samples Wilcoxon rank-sum test. Laboratory CSF sodium concentration did not differ significantly between patients without and with MS (p = 0.42). The proposed quantification workflow for 23Na MRI was highly repeatable with CoVs averaged over all five volunteers of 1.9% ± 0.9% for NAWM and 2.2% ± 1.6% for NAGM. Average NAWM aTSC was significantly higher in patients with SPMS compared with the control group (p = 0.009). Average NAGM aTSC did not differ significantly between healthy volunteers and MS patients (p = 0.98). The proposed postprocessing pipeline shows high repeatability and the results can serve as a baseline for further studies establishing 23Na brain MRI as a biomarker in diseases such as MS.
CRIS-Team Scopus Importer:2022-08-19
Keywords: 7 T; brain MRI; multiple sclerosis

Quantitative analysis of zirconia and titanium implant artefacts in three-dimensional virtual models of multi-slice CT and cone beam CT: does scan protocol matter? - Matta, Ragai; Knapp Giacaman, Stephanie; Wiesmüller, Marco; Lutz, Rainer; Uder, Michael; Wichmann, Manfred; Seidel, Anna (Dentomaxillofacial Radiology, 2023)
OBJECTIVES: Artefacts from dental implants in three-dimensional (3D) imaging may lead to incorrect representation of anatomical dimensions and impede virtual planning in navigated implantology. The aim of this study was quantitative assessment of artefacts in 3D STL models from cone beam CT (CBCT) and multislice CT (MSCT) using different scanning protocols and titanium-zirconium (Ti-Zr) and zirconium (ZrO2) implant materials. METHODS: Three ZrO2 and three Ti-Zr implants were respectively placed in the mandibles of two fresh human specimens. Before (baseline) and after implant placement, 3D digital imaging scans were performed (10 repetitions per timepoint: voxel size 0.2 mm³ and 0.3 mm³ for CBCT; 80 and 140 kV in MSCT). DICOM data were converted into 3D STL models and evaluated in computer-aided design software. After precise merging of the baseline and post-op models, the surface deviation was calculated, representing the extent of artefacts in the 3D models. RESULTS: Compared with baseline, ZrO2 emitted 36.5-37.3% (±0.6-0.8) artefacts in the CBCT and 39.2-50.2% (±0.5-1.2) in the MSCT models. Ti-Zr implants produced 4.1-7.1% (±0.3-3.0) artefacts in CBCT and 5.4-15.7% (±0.5-1.3) in MSCT. Significantly more artefacts were found in the MSCT vs CBCT models for both implant materials (p < 0.05). Significantly fewer artefacts were visible in the 3D models from scans with higher kilovolts in MSCT and smaller voxel size in CBCT. CONCLUSIONS: Among the four applied protocols, the lowest artefact proportion of ZrO2 and Ti-Zr implants in STL models was observed with CBCT and the 0.3 mm³ voxel size.
EVALuna2:541032

QUANTITATIVE ASSESSMENT AND ANALYSIS OF HAND MUSCLE VOLUME - Friedberger, Andreas; Figueiredo, C.; Museyko, Oleg; Grimm, Alexandra; D'Oliveira, I.; Bäuerle, Tobias; Rech, Jürgen; Chaudry, Oliver; Uder, Michael; Schett, Georg; Engelke, Klaus (2017)
EVALuna2:14726

Quantitative assessment of muscle injury by (23)Na magnetic resonance imaging - Dahlmann, Anke; Kopp, Christoph; Linz, Peter; Seuß, Hannes; Eckardt, Kai-Uwe; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (SpringerPlus, 2016)
(23)Na magnetic resonance imaging ((23)Na-MRI) is able to measure Na(+) in vivo in humans and allows quantification of tissue sodium distribution. We now tested the utility of (23)Na-MRI technique in detecting and assessing sports-related acute muscular injury.We assessed tissue Na(+) of both lower legs with a 3T MRI scanner using a customized (23)Na knee coil. The affected left calf muscle in an injured volleyball player showed a hyperintense Na(+) signal. Follow-up measurements revealed persistently increased muscle Na(+) content despite complete clinical recovery.Our findings suggest that (23)Na-MRI could have utility in detecting subtle muscular injury and might indicate when complete healing has occurred. Furthermore, (23)Na-MRI suggests the presence of substantial injury-related muscle electrolyte shifts that warrant more detailed investigation.
EVALuna2:3865

QUANTITATIVE MAGNETIC RESONANCE IMAGING CORRELATES WITH EARLY S100B PROFILE AND FUNCTIONAL OUTCOME AFTER ACUTE BRAIN INJURY - Roeckelein, Verena; Kloska, Stephan; Uder, Michael; Buchfelder, Michael; Kleindienst, Andrea (2016)
EVALuna2:14588

Radiation dose reduction in parasinus CT by spectral shaping - May, Matthias; Brand, Michael; Lell, Michael; Sedlmair, Martin; Allmendinger, Thomas; Uder, Michael; Wüst, Wolfgang (Neuroradiology, 2017)
Spectral shaping aims to narrow the X-ray spectrum of clinical CT. The aim of this study was to determine the image quality and the extent of radiation dose reduction that can be achieved by tin prefiltration for parasinus CT.All scans were performed with a third generation dual-source CT scanner. A study protocol was designed using 100 kV tube voltage with tin prefiltration (200 mAs) that provides image noise levels comparable to a low-dose reference protocol using 100 kV without spectral shaping (25 mAs). One hundred consecutive patients were prospectively enrolled and randomly assigned to the study or control group. All patients signed written informed consent. The study protocol was approved by the local Institutional Review Board and applies to the HIPAA. Subjective and objective image quality (attenuation values, image noise, and contrast-to-noise ratio (CNR)) were assessed. Radiation exposure was assessed as volumetric CT dose index, and effective dose was estimated. Mann-Whitney U test was performed for radiation exposure and for image noise comparison.All scans were of diagnostic image quality. Image noise in air, in the retrobulbar fat, and in the eye globe was comparable between both groups (all p > 0.05). CNReye globe/air did not differ significantly between both groups (p = 0.7). Radiation exposure (1.7 vs. 2.1 mGy, p < 0.01) and effective dose (0.055 vs. 0.066 mSv, p < 0.01) were significantly reduced in the study group.Radiation dose can be further reduced by 17% for low-dose parasinus CT by tin prefiltration maintaining diagnostic image quality.
EVALuna2:14651

Radiation Induced DNA Double-Strand Breaks in Radiology - Kuefner, M. A.; Brand, Michael; Engert, C.; Schwab, S. A.; Uder, Michael (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Shortly after the discovery of X-rays, their damaging effect on biological tissues was observed. The determination of radiation exposure in diagnostic and interventional radiology is usually based on physical measurements or mathematical algorithms with standardized dose simulations. ?-H2AX immunofluorescence microscopy is a reliable and sensitive method for the quantification of radiation induced DNA double-strand breaks (DSB) in blood lymphocytes. The detectable amount of these DNA damages correlates well with the dose received. However, the biological radiation damage depends not only on dose but also on other individual factors like radiation sensitivity and DNA repair capacity. Iodinated contrast agents can enhance the x-ray induced DNA damage level. After their induction DSB are quickly repaired. A protective effect of antioxidants has been postulated in experimental studies. This review explains the prinicple of the ?-H2AX technique and provides an overview on studies evaluating DSB in radiologic examinations.Radiologic examinations including CT and angiography induce DNA double-strand breaks. Even after mammography a slight but significant increase is detectable in peripheral blood lymphocytes. The number of radiation induced double-strand breaks correlates well with the radiation dose. Individual factors including radiation sensitivity, DNA repair capacity and the application of iodinated contrast media has an influence on the DNA damage level.
EVALuna2:14515

Radiation protection in interventional radiology - Adamus, R.; Loose, Reinhard; Wucherer, M.; Uder, Michael; Galster, M. (Radiologe, 2016)
The application of ionizing radiation in medicine seems to be a safe procedure for patients as well as for occupational exposition to personnel. The developments in interventional radiology with fluoroscopy and dose-intensive interventions require intensified radiation protection. It is recommended that all available tools should be used for this purpose. Besides the options for instruments, x-ray protection at the intervention table must be intensively practiced with lead aprons and mounted lead glass. A special focus on eye protection to prevent cataracts is also recommended. The development of cataracts might no longer be deterministic, as confirmed by new data; therefore, the International Commission on Radiological Protection (ICRP) has lowered the threshold dose value for eyes from 150 mSv/year to 20 mSv/year. Measurements show that the new values can be achieved by applying all X-ray protection measures plus lead-containing eyeglasses.
EVALuna2:14607

Reaching for better image quality and lower radiation dose in head and neck CT: advanced modeled and sinogram-affirmed iterative reconstruction in combination with tube voltage adaptation - Schmid, Andrea; Uder, Michael; Lell, Michael (Dentomaxillofacial Radiology, 2016)
The aim of this study was to evaluate image quality and radiation dose in low-dose head and neck CT comparing two different commercially available iterative reconstruction algorithms: sinogram-affirmed iterative reconstruction (SAFIRE) and advanced modeled iterative reconstruction (ADMIRE) with fixed and automated tube voltage adaptation (TVA).CT examinations of 103 patients were analysed. 58 patients were examined on a single-source CT at fixed tube voltage of 120 kV and reconstructed with filtered back projection (FBP) and SAFIRE (Strength Level 3). 45 patients were examined in a single-source mode on a dual-source CT with automated TVA and reconstructed with FBP and ADMIRE (Strength Levels 2 and 3). Image noise was calculated in seven anatomical volumes of interest. Subjective evaluation of the CT images was performed using a four-grade scale.Mean CT numbers of FBP and the corresponding iterative reconstruction did not differ significantly (p = 0.74-0.99). Image noise was lower with both iterative reconstruction techniques than with FBP (SAFIRE 3: -22.3%; ADMIRE 2: -14.9%; ADMIRE 3: -24.2%; all p < 0.05); hence, the signal-to-noise ratio and the contrast-to-noise values were higher. Subjective image quality revealed a more favourable result for the iterative reconstruction. ADMIRE 3 in combination with automated TVA showed 14.4% (p < 0.05) less image noise with a 7.5% lower radiation dose than SAFIRE 3 with fixed tube voltage.Higher image quality at lower radiation dose can be achieved using ADMIRE in combination with automated TVA.
EVALuna2:14596

Recommendations on exercise methods for bone strengthening - von Stengel, Simon; Kohl, Matthias; Jakob, Franz; Kerschan-Schindl, Katharina; Lange, Uwe; Peters, Stefan; Thomasius, Friederike; Uder, Michael; Shojaa, Mahdieh; Kemmler, Wolfgang (Osteologie, 2023)
The optimum composition of strain parameters (or loading parameters) is crucial in designing exercise protocols with positive effects on bone strength and associated parameters. Although strain parameters related to bone adaption differ slightly from the common terminology usually applied in sport sciences, their categorization is very similar. Introducing strain parameters, (1) strain magnitude is characterized by the extent of the deformation of the bone caused by loading, while (2) strain rate represents the alteration in strain magnitude per second during the acceleration or deceleration of loading. (3) Training frequency and (4) cycle number indicate the amount of training sessions (usually per week) and the number of loading cycles/repetitions per set/session, while (5) strain duration is characterized by the length of a single loading cycle. (6) Strain frequency represents the number of loading cycles per sec (Hz) and finally (6) strain density characterizes the relationship between loading and rest periods with respect to single loading cycles, sets of cycles, training sessions or training periods (mesocycles). In summary, exercise programs applied with high strain magnitude and rate and a short cycle duration in a dynamic mode at least twice/week showed the highest osteoanabolic potency. The number of repetitions plays a minor role, at least when high exercise intensity (high strain magnitude-/rate) was applied. However, there is some evidence that stimuli around or (slightly) below bone mechanical threshold can be raised to a supra-threshold level by increasing the number of repetitions. The same might also be the case for strain frequency in the spectrum of voluntary movements (<5 Hz). The relevance of strain density is closely related to the "desensitization phenomena" of bone after repeated intense loading. Applying regular resensitization periods without relevant mechanical loading between phases of intense bone specific exercise enables other important training aims to be addressed with high emphasis during the corresponding periods.
CRIS-Team WoS Importer:2023-05-12

Reconstruction of the vascular compromised lower extremity - report of the consensus workshop at the 35. Meeting of the DAM (Deutschsprachige Gemeinschaft für Mikrochirurgie der peripheren Nerven und Gefäße) 2013 in Deidesheim - Daigeler, A.; Kneser, U.; Fansa, H.; Riester, T.; Uder, Michael; Horch, Raymund E. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2014)
As microsurgical reconstruction is now being increasingly performed on patients with critical peripheral perfusion and/or arterial occlusive disease in numerous centres, there is a need for standardisation of interdisciplinary diagnostic approach and treatment regimens in such critically ill patients. In a consensus workshop on reconstruction of the vascular compromised lower extremity during the 35th Annual Meeting of the German working group microsurgery of the peripheral nerves and vessels (DAM) in 2013 in Deidesheim, DAM members together with vascular surgeons and interventional radiologists attempted to establish interdisciplinarily routine pathways for diagnosis and therapy and to consolidate key recommendations for treatment.By reviewing the literature and considering the results of the expert meetings, options and limits of therapy were illustrated and recommendations for successful cooperative treatment formulated.By means of interdisciplinary cooperation, limbs can be salvaged and the quality of live as well as survival of patients with severe peripheral vascular disease improved. Different techniques including angioplasty, bypass surgery and microsurgical free flaps can be applied and individualised concepts allow extremity salvage even in patients with severely compromised limbs. Revascularisation provides the possibility of free flap transfer while the risk for the patients is moderate.The poor general condition of the patient requires a sufficient interdisciplinary preoperative planning. By means of interdisciplinary cooperation, the limbs can be salvaged. This not only improves the quality of life but also increases the survival time of patients with occlusive vascular disease. Different concepts for this group of patients have been developed. Surgical treatment with a distal bypass or recanalisation and free flap not only allow for the coverage of large defects, but also represent a haemodynamic advantage by increased blood flow in the bypass. This is attributed to the additional vascular bed that is transplanted with the free flap. Limb salvage means relevant improvement, however, the initially less demanding procedure of amputation must always be considered.
EVALuna2:14357

Reduced tissue sodium content is related to improvement of vascular function in patients with chronic heart failure treated with the SGLT2 inhibitor empagliflozin - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, P.; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Reduction of the cardiac pulsation artifact and improvement of lesion conspicuity in flow-compensated diffusion images in the liver-A quantitative evaluation of postprocessing algorithms - Führes, Tobit; Saake, Marc; Lorenz, Jennifer; Seuß, Hannes; Stemmer, Alto; Benkert, Thomas; Uder, Michael; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2022)
Purpose To enhance image quality of flow-compensated diffusion-weighted liver MRI data by increasing the lesion conspicuity and reducing the cardiac pulsation artifact using postprocessing algorithms. Methods Diffusion-weighted image data of 40 patients with liver lesions had been acquired at 1.5 T. These data were postprocessed with 5 different algorithms (weighted averaging, p-mean, percentile, outlier exclusion, and exception set). Four image properties of the postprocessed data were evaluated for optimizing the algorithm parameters. These properties were the lesion to tissue contrast-to-noise ratio (CNR), the reduction of the cardiac pulsation artifact, the data consistency, and the vessel darkness. They were combined into a total quality score ( set to 1 for the trace-weighted reference image), which was used to rate the image quality objectively. Results The weighted averaging algorithm performed best according to the total quality score (). The further ranking was outlier exclusion algorithm (), p-mean algorithm (), percentile algorithm (), and exception set algorithm (). All optimized algorithms except for the exception set algorithm corrected the pulsation artifact and increased the lesion CNR. Changes in were significant for all optimized algorithms except for the percentile algorithm. Liver ADC was significantly reduced (except for the exception set algorithm), particularly in the left lobe. Conclusion Postprocessing algorithms should be used for flow-compensated liver DWI. The proposed weighted averaging algorithm seems to be suited best to increase the image quality of artifact-corrupted flow-compensated diffusion-weighted liver data.
CRIS-Team WoS Importer:2022-09-23

Reduction of Tissue Na+ Accumulation After Renal Transplantation - Dahlmann, Anke; Linz, Peter; Zucker, Isabelle; Haag, Viktor; Jantsch, Jonathan; Dienemann, Thomas; Nagel, Armin Michael; Neubert, Patrick; Rosenhauer, Daniela; Rauh, Manfred; Horn, Stephan; Müller, Dominik N.; et al. (Kidney International Reports, 2021)
Introduction: Chronic kidney disease (CKD) engenders salt-sensitive hypertension. Whether or not tissue Nathorn accumulation is increased in CKD patients remains uncertain. How tissue Nathorn is affected after renal transplantation has not been assessed.
CRIS-Team WoS Importer:2021-10-01

Reduction of tissue sodium content by SGLT-2-inhibition with dapagliflozin - Karg, M. V.; Ott, Christian; Linz, Peter; Jumar, A.; Kannenkeril, D.; Titze, J.; Hammon, Matthias; Uder, Michael; Schmieder, Roland (2017)
EVALuna2:36268

Reduction of X-ray-induced DNA damage in normal human cells treated with the PrC-210 radioprotector - Brand, Michael; Sommer, Matthias; Jermusek, Frank; Fahl, William E.; Uder, Michael (Biology Open, 2018)
The aim of our study was to determine the protective efficacy of the PrC-210 aminothiol radioprotector against X-ray-induced DNA damage in normal human cells and to establish dose- and time-effect models for future PrC-210 use in humans. The PrC-210 structure has a branched structure which enables scavenging of reactive oxygen species (ROS) away from DNA. Normal human blood lymphocytes, fibroblasts and naked genomic DNA were exposed to PrC-210 seconds to hours prior to irradiation. Biological (γ-H2AX foci), chemical (8-oxo-deoxyguanosine) and physical (genomic DNA electrophoretic migration) DNA damage endpoints were scored to determine the ability of PrC-210 to suppress radiation-induced DNA damage. X-ray-induced γ-H2AX foci in blood lymphocytes were reduced by 80% after irradiation with 10, 50 and 100 mGy, and DNA double-strand breaks in fibroblasts were reduced by 60% after irradiation with 20 Gy. Additionally, we observed a reduction of 8-oxo-deoxyguanosine (an ROS-mediated, DNA damage marker) in human genomic DNA to background in a PrC-210 dose-dependent manner. PrC-210 also eliminated radiation-induced cell death in colony formation assays after irradiation with 1 Gy. The protective efficacy of PrC-210 in each of these assay systems supports its development as a radioprotector for humans in multiple radiation exposure settings.
EVALuna2:36109

Renal denervation in moderate treatment-resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Spies, Aline; Ukena, Christian; Laufs, Ulrich; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of the American College of Cardiology, 2013)
Objectives This study sought to investigate the effect of renal denervation (RDN) in patients with treatment-resistant hypertension according to the established definition (Joint National Committee VII and European Society of Hypertension/European Society of Cardiology guidelines), that is, office blood pressure (BP) ≥140/90 mm Hg (with at least three antihypertensive drugs, including a diuretic, in adequate doses) and confirmed by 24-h ambulatory BP monitoring (ABPM). Background RDN emerged as an innovative interventional antihypertensive therapy. However, so far, only patients with severe hypertension (systolic BP ≥160 mm Hg or ≥150 mm Hg for patients with type 2 diabetes) have been investigated. Methods In this study, there were 54 patients with moderate treatment-resistant hypertension (office BP ≥140/90 mm Hg and <160/100 mm Hg and diagnosis confirmed by 24-h ABPM of ≥130/80 mm Hg) who underwent catheter-based RDN using the Symplicity catheter (Medtronic Inc., Mountain View, California). Results Patients were treated with 5.1 ± 1.4 antihypertensive drugs on average. Office BP was significantly reduced by 13/7 mm Hg 6 months after RDN (systolic: 151 ± 6 mm Hg vs. 138 ± 21 mm Hg, p < 0.001; diastolic: 83 ± 11 mm Hg vs. 75 ± 11 mm Hg, p < 0.001). In patients (n = 36) who underwent ABPM 6 months after treatment, there was a reduction in average 24-h ABPM by 14/7 mm Hg (systolic: 150 ± 16 mm Hg vs. 136 ± 16 mm Hg, p < 0.001; diastolic: 83 ± 10 mm Hg vs. 76 ± 10 mm Hg, p < 0.001). In 51% of patients, office BP was controlled below 140/90 mm Hg after RDN. In addition, heart rate decreased from 67 ± 11 to 63 ± 10 beats/min (p = 0.006). Conclusions Our data indicate that RDN may reduce office and 24-h ambulatory BP substantially in patients with moderate treatment-resistant hypertension. (Renal Denervation in Treatment Resistant Hypertension; NCT01687725). © 2013 by the American College of Cardiology Foundation.
CRIS-Team Scopus Importer:2023-03-08
Keywords: 24-h ambulatory blood pressure; renal denervation; treatment-resistant hypertension

Renal denervation in refractory hypertension: joint statement of the German hypertension league DHL eV and the German societies of cardiology, angiology, nephrology and radiology - Vonend, Oliver; Boehm, Michael; Eckert, Siegfried; Hausberg, Martin; Rittger, Harald; Rump, Lars-Christian; Schmieder, Roland; Schulte, Karl-Ludwig; Schunkert, Heribert; Uder, Michael; Veelken, Roland; Vorwerk, Dierk; et al. (Deutsche Medizinische Wochenschrift, 2015)
Arterial hypertension is a major risk factor for cardiovascular mortality and remains insufficiently controlled in Germany. The sham controlled Symplicity HTN-3 trial did meet its primary safety endpoint but failed to meet its primary efficacy endpoint. Renal denervation can not replace established, well-proven therapies. It can only be used in selected truly resistant hypertensive patients as an additive approach and should be performed by specialized centers only. Randomized controlled trials are needed to further evaluate renal denervation.
EVALuna2:3770

Renal denervation preserves renal function in patients with chronic kidney disease and resistant hypertension - Ott, Christian; Mahfoud, Felix; Schmid, Axel; Toennes, Stefan W.; Ewen, Sebastian; Ditting, Tilmann; Veelken, Roland; Ukena, Christian; Uder, Michael; Boehm, Michael; Schmieder, Roland (Journal of Hypertension, 2015)
Arterial hypertension and increased sympathetic activity are underlying pathogenetic mechanisms of the progressive loss of renal function in patients with chronic kidney disease (CKD). Meta-analyses have shown that impaired renal function is an independent cardiovascular risk factor. We hypothesized that renal denervation (RDN) decreases the decline of renal function in patients with CKD stages 3 and 4 and treatment-resistant hypertension.We performed an observational study of 27 patients with CKD stages 3 and 4, office blood pressure (BP) >= 140/90 mmHg, while on at least three antihypertensive drug classes including diuretic, and diagnosis confirmed by 24-h ambulatory BP measurement >= 130/80 mmHg. All patients underwent catheter-based RDN using the Symplicity Flex RDN System (Medtronic Inc., Santa Rosa, California, USA). Renal function was evaluated for up to 3 years prior and 1 year after RDN. The change in estimated glomerular filtration rate (eGFR) was calculated by regression slope individually for each patient before and after RDN. The study was registered at http://www.clinicaltrials.gov (ID: NCT01442883).Mean baseline BP was 156 ± 12/82 ± 13 mmHg, despite treatment with 6.2 ± 1.1 antihypertensive drugs. One year after RDN, office BP was reduced by 20 ± 20 (P < 0.001)/8 ± 14 mmHg (P = 0.005) and average 24-h ambulatory BP by 9 ± 14 (P = 0.009)/4 ± 7 mmHg (P = 0.019). Before RDN, eGFR declined by -4.8 ± 3.8 ml/min per 1.73 m per year, and after RDN eGFR improved by +1.5 ± 10 ml/min per 1.73 m at 12 months (P = 0.009).Our observational pilot study in patients with CKD stages 3 and 4 indicates that treatment of hypertension with RDN decreases BP and slows or even halts the decline of renal function.
EVALuna2:3767

Renal fibrosis is the common feature of autosomal dominant tubulointerstitial kidney diseases caused by mutations in mucin 1 or uromodulin - Ekici, Arif Bülent; Hackenbeck, Thomas; Moriniere, Vincent; Panness, Andrea; Büttner, Maike; Uebe, Steffen; Janka, Rolf Matthias; Wiesener, Antje; Hermann, Ingo; Grupp, Sina; Hornberger, Martin; Huber, Tobias B.; et al. (Kidney International, 2014)
For decades, ill-defined autosomal dominant renal diseases have been reported, which originate from tubular cells and lead to tubular atrophy and interstitial fibrosis. These diseases are clinically indistinguishable, but caused by mutations in at least four different genes: UMOD, HNF1B, REN, and, as recently described, MUC1. Affected family members show renal fibrosis in the biopsy and gradually declining renal function, with renal failure usually occurring between the third and sixth decade of life. Here we describe 10 families and define eligibility criteria to consider this type of inherited disease, as well as propose a practicable approach for diagnosis. In contrast to what the frequently used term 'Medullary Cystic Kidney Disease' implies, development of (medullary) cysts is neither an early nor a typical feature, as determined by MRI. In addition to Sanger and gene panel sequencing of the four genes, we established SNaPshot minisequencing for the predescribed cytosine duplication within a distinct repeat region of MUC1 causing a frameshift. A mutation was found in 7 of 9 families (3 in UMOD and 4 in MUC1), with one indeterminate (UMOD p.T62P). On the basis of clinical and pathological characteristics we propose the term 'Autosomal Dominant Tubulointerstitial Kidney Disease' as an improved terminology. This should enhance recognition and correct diagnosis of affected individuals, facilitate genetic counseling, and stimulate research into the underlying pathophysiology.
EVALuna2:3695

RENAL HEMODYNAMIC CHANGES AFTER RENAL DENERVATION - Schmieder, R. S.; Schmid, Axel; Janka, Rolf Matthias; Ditting, T.; Veelken, Roland; Uder, Michael; Schmieder, Roland; Ott, Christian (2016)
EVALuna2:34706

Repeatability of Dixon magnetic resonance imaging and magnetic resonance spectroscopy for quantitative muscle fat assessments in the thigh - Grimm, Alexandra; Meyer, Heiko; Nickel, Marcel D.; Nittka, Mathias; Raithel, Esther; Chaudry, Oliver; Friedberger, Andreas; Uder, Michael; Kemmler, Wolfgang; Engelke, Klaus; Quick, Harald H. (Journal of Cachexia, Sarcopenia and Muscle, 2018)
BACKGROUND: Changes in muscle fat composition as for example observed in sarcopenia or muscular dystrophy affect physical performance and muscular function, like strength and power. The purpose of the present study is to measure the repeatability of Dixon magnetic resonance imaging (MRI) for assessing muscle volume and fat in the thigh. Furthermore, repeatability of magnetic resonance spectroscopy (MRS) for assessing muscle fat is determined. METHODS: A prototype 6-point Dixon MRI method was used to measure muscle volume and muscle proton density fat fraction (PDFF) in the left thigh. PDFF was measured in musculus semitendinosus of the left thigh with a T2-corrected multi-echo MRS method. For the determination of short-term repeatability (consecutive examinations), the root mean square coefficients of variation of Dixon MRI and MRS data of 23 young and healthy (29 ± 5 years) and 24 elderly men with sarcopenia (78 ± 5 years) were calculated. For the estimation of the long-term repeatability (13 weeks between examinations), the root mean square coefficients of variation of MRI data of seven young and healthy (31 ± 7 years) and 23 elderly sarcopenic men (76 ± 5 years) were calculated. Long-term repeatability of MRS was not determined. RESULTS: Short-term errors of Dixon MRI volume measurement were between 1.2% and 1.5%, between 2.1% and 1.6% for Dixon MRI PDFF measurement, and between 9.0% and 15.3% for MRS. Because of the high short-term repeatability errors of MRS, long-term errors were not determined. Long-term errors of MRI volume measurement were between 1.9% and 4.0% and of Dixon MRI PDFF measurement between 2.1% and 4.2%. CONCLUSIONS: The high degree of repeatability of volume and PDFF Dixon MRI supports its use to predict future mobility impairment and measures the success of therapeutic interventions, for example, in sarcopenia in aging populations and muscular dystrophy. Because of possible inhomogeneity of fat infiltration in muscle tissue, the application of MRS for PDFF measurements in muscle is more problematic because this may result in high repeatability errors. In addition, the tissue composition within the MRS voxel may not be representative for the whole muscle.
EVALuna2:36107

Reproducibility of aortic annulus measurements by computed tomography - Schuhbaeck, Annika; Achenbach, Stephan; Pflederer, Tobias; Schmid, Julia; Nef, Holger; Rixe, Johannes; Hecker, Franziska; Schneider, Christian; Lell, Michael; Uder, Michael; Arnold, Martin; Marwan, Mohamed (European Radiology, 2014)
To evaluate a systematic approach for measurement of aortic annulus dimensions by cardiac computed tomography.CT data sets of 64 patients were evaluated. An oblique cross-section aligned with the aortic root was created by systematically identifying the caudal insertion points of the three aortic cusps and sequentially aligning them in a double oblique plane. Aortic annulus dimensions, distances of coronary ostia and a suitable fluoroscopic projection angle were independently determined by two observers.Interobserver intraclass correlation coefficients (ICC) for aortic annulus diameters were excellent (ICC 0.89-0.93). Agreement for prosthesis size selection was excellent (? = 0.86 for mean, ? = 0.84 for area-derived and ? = 0.91 for circumference-derived diameter). Mean distances of the left/right coronary ostium were 13.4 ± 2.4/14.4 ± 2.8 mm for observer 1 and 13.2 ± 2.7/13.5 ± 3.2 mm for observer 2 (p = 0.30 and p = 0.0001, respectively; ICC 0.76/0.77 for left/right coronary artery). A difference of less than 10° for fluoroscopic projection angle was achieved in 84.3% of patients.A systematic approach to generate a double oblique imaging plane exactly aligned with the aortic annulus demonstrates high interobserver and intraobserver agreements for derived measurements which are not influenced by aortic root calcification.o Systematic approach to generate a double oblique imaging plane for TAVI evaluation. o This method is straightforward and software independent. o An approach with high reproducibility, not influenced by aortic root calcification.
EVALuna2:11952

Reproducibility of Kidney Perfusion Measurements With Arterial Spin Labeling at 1.5 Tesla MRI Combined With Semiautomatic Segmentation for Differential Cortical and Medullary Assessment - Hammon, Matthias; Janka, Rolf Matthias; Siegl, Christian; Seuß, Hannes; Grosso, Roberto; Martirosian, Petros; Schmieder, Roland; Uder, Michael; Kistner, Iris (Medicine, 2016)
Magnetic resonance imaging with arterial spin labeling (ASL) is a noninvasive approach to measure organ perfusion. The purpose of this study was to evaluate the reproducibility of ASL kidney perfusion measurements with semiautomatic segmentation, which allows separate quantification of cortical and medullary perfusion.The right kidneys of 14 healthy volunteers were examined 6 times on 2 occasions (3 times at each occasion). There was a 10-minute pause between each examination and a 14-day interval between the 2 occasions. Cortical, medullary, and whole kidney parenchymal perfusion was determined with customized semiautomatic segmentation software. Coefficient of variances (CVs) and intraclass correlations (ICCs) were calculated.Mean whole, cortical, and medullary kidney perfusion was 307.26 ± 25.65, 337.10 ± 34.83, and 279.61 ± 26.73 mL/min/100 g, respectively. On session 1, mean perfusion for the whole kidney, cortex, and medulla was 307.08 ± 26.91, 336.79 ± 36.54, and 279.60 ± 27.81 mL/min/100 g, respectively, and on session 2, 307.45 ± 24.65, 337.41 ± 33.48, and 279.61 ± 25.94 mL/min/100 g, respectively (P > 0.05; R = 0.60/0.59/0.54). For whole, cortical, and medullary kidney perfusion, the total ICC/CV were 0.97/3.43 ± 0.86%, 0.97/4.19 ± 1.33%, and 0.96/4.12 ± 1.36%, respectively. Measurements did not differ significantly and showed a very good correlation (P > 0.05; R = 0.75/0.76/0.65).ASL kidney measurements combined with operator-independent semiautomatic segmentation revealed high correlation and low variance of cortical, medullary, and whole kidney perfusion.
EVALuna2:3854

Rescue therapy of antisynthetase syndrome with CD19-targeted CAR-T cells after failure of several B-cell depleting antibodies - Taubmann, Jule; Knitza, Johannes; Müller, Fabian; Völkl, Simon; Aigner, Michael; Kleyer, Arnd; Gary, Regina; Kretschmann, Sascha; Böltz, Sebastian; Atzinger, Armin; Kuwert, Torsten; Roemer, Frank; et al. (Rheumatology, 2024)
EVALuna2:539551

Research in radiology - Semelka, Richard C.; Brand, Michael; Uder, Michael; Kuefner, Michael A.; Stonestreet, John; Elias, Jorge (Wiley Blackwell, 2013)
CRIS-Team Scopus Importer:2023-03-08

Resolution of vascular inflammation in patients with new-onset giant cell arteritis: data from the RIGA study - Schönau, Verena; Roth, Jessica; Tascilar, Koray; Corte, Giulia; Manger, Bernhard; Rech, Jürgen; Schmidt, Daniela; Cavallaro, Alexander Josef; Uder, Michael; Crescentini, Filippo; Boiardi, Luigi; Casali, Massimiliano; et al. (Rheumatology, 2021)
OBJECTIVES: Efficacy evaluation of GCA treatment is primarily based on non-specific symptoms and laboratory markers. We aimed to assess the change in vascular inflammation in patients with large vessel (LV)-GCA under different treatments using [18F]FDG PET/CT. METHODS: Observational study on patients with new-onset, active LV-GCA starting treatment with either prednisolone monotherapy (PRED) or combination with MTX or tocilizumab (TOC). All patients underwent baseline and follow-up PET/CT. The aorta and its major branches were assessed using PET vascular activity score (PETVAS) by independent readers. Cumulative glucocorticoid doses and cessation of glucocorticoid treatment were documented in all patients. RESULTS: We included 88 LV-GCA patients, 27 were treated with PRED, 42 with MTX and 19 with TOC. PETVAS decreased from 18.9-8.0 units at follow-up in the overall population (P <0.001). PETVAS changes were numerically higher in patients receiving MTX (-12.3 units) or TOC (-11.7 units) compared with PRED (-8.7). Mean cumulative prednisolone dosages were 5637, 4418 and 2984 mg in patients treated with PRED, MTX and TOC (P =0.002). Risk ratios for glucocorticoid discontinuation at the time of follow-up PET/CT were 6.77 (95% CI: 1.01, 45.29; P =0.049) and 16.25 (95% CI: 2.60, 101.73; P =0.003) for MTX and TOC users compared with PRED users. CONCLUSION: Treatment of LV-GCA inhibits vascular inflammation in the aorta and its major branches. While similar control of vascular inflammation was achieved with PRED, MTX and TOC treatments, TOC showed a strong glucocorticoid sparing effect, supporting the concept of initial combination therapy.
CRIS-Team Scopus Importer:2021-09-24
Keywords: 18F-fluorodeoxyglucose positron emission tomography/computed tomography; giant cell arteritis; glucocorticoids; large vessel vasculitis; methotrexate; tocilizumab; treatment

Retinal microperfusion after renal denervation in treatment-resistant hypertensive patients - Ott, Christian; Harazny, Joanna M.; Schmid, Axel; Ditting, Tilmann; Veelken, Roland; Bladowski, Marek; Michelson, Georg; Uder, Michael; Schmieder, Roland (Clinical Research in Cardiology, 2015)
High pulsatile pressure and flow in the arteries causes microvascular damage, and hence increased cardio-, and cerebrovascular complications. With advanced stages of hypertensive disease, an exaggerated pulsatile retinal capillary flow (RCF) has been shown, but data about interventional effect are missing.Fifty-one patients with true treatment-resistant hypertension (TRH) underwent renal denervation (RDN) using the Symplicity Flex(TM) catheter and were followed for 12 months. RCF was assessed non-invasively using Scanning laser Doppler flowmetry (SLDF) before, 6 (6 M), and 12 (12 M) months after RDN. RCF was measured in systole and diastole and pulsed RCF (difference of RCF in systole minus diastole) was calculated. In addition, flicker light-induced vasodilation (representing vasodilatory capacity) was assessed.Systolic and diastolic office blood pressure (BP) as well as 24-h ABPM decreased significantly 6 M and 12 M after RDN, compared to baseline values (all p < 0.001). There was a significant reduction of pulsed RCF 6 M (231 ± 81 versus 208 ± 68 AU, p = 0.046) and 12 M (194 ± 72 AU, p = 0.001) after RDN, whereas the mean RCF was unchanged. Moreover, there was a significant increase of flicker light-induced vasodilation after RDN (p = 0.043).In hypertensive patients with TRH, we observed a decrease of pulsed RCF 6 M and 12 M after RDN and an increase of vasodilatory capacity, in parallel to decreases in BP and heart rate. The reduction of pulsed RCF after RDN implies a decrease of shear stress on the vascular wall by the pulsed blood flow. This and the increment of vasodilatory capacity suggest an improvement of retinal (and potentially cerebral) microcirculation.
EVALuna2:3762

Sample size estimation: Current practice and considerations for original investigations in MRI technical development studies - Hanspach, Jannis; Nagel, Armin Michael; Hensel, Bernhard; Uder, Michael; Koros, Leon; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2020)
Purpose: To investigate and to provide guidance for sample size selection based on the current practice in MR technical development studies in which healthy volunteers are examined. Methods: All original articles published in Magnetic Resonance in Medicine between 2017 and 2019 were investigated and categorized according to technique, anatomical region, and magnetic field strength. The number of examined healthy volunteers (ie, the sample size) was collected and evaluated, whereas the number of patients was not considered. Papers solely measuring patients, animals, phantoms, specimens, or studies using existing data, for example, from an open databank, or consisting only of theoretical work or simulations were excluded. Results: The median sample size of the 882 included studies was 6. There were some peaks in the sample size distribution (eg, 1, 5, and 10). In 49.9%, 82.1%, and 95.6% of the studies, the sample size was smaller or equal to 5, 10, and 20, respectively. Conclusion: We observed a large variance in sample sizes reflecting the variety of studies published in Magnetic Resonance in Medicine. Therefore, it can be concluded that it is current practice to balance the need for statistical power with the demand to minimize experiments involving healthy humans, often by choosing small sample sizes between 1 and 10. Naturally, this observation does not release an investigator from ensuring that sufficient data are acquired to reach statistical conclusions.
CRIS-Team Scopus Importer:2020-10-23
Keywords: current practice; methodological MRI developments; number of subjects; number of volunteers; proof-of-principle studies; sample size estimation

Scanned versus Fused-Reconstructed Oblique MR-Images for Assessment of the Tibiofibular Syndesmosis-Diagnostic PerFormance and Reader Agreement - Seuß, Hannes; Hammon, Matthias; Roemer, Frank; Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Dankerl, Peter (Diagnostics, 2021)
To evaluate the diagnostic performance and reader agreement of a novel MRI image fusion method enabling the reconstruction of oblique images for the assessment of the tibiofibular syndesmosis. We evaluated 40 magnetic resonance imaging examinations of patients with ankle sprains (16 with ruptures and 24 without) for the presence of anteroinferior tibiofibular ligament rupture. For all patients, we performed a fusion of standard two-dimensional transversal and coronal 3 mm PDw TSE images into an oblique-fusion reconstruction (OFR) and compared these against conventionally scanned oblique sequence for the evaluation of the tibiofibular syndesmosis. To evaluate diagnostic performance, two expert readers independently read the OFR images twice. We analyzed sensitivity, specificity, negative and positive predictive values, accuracy, and agreement. Reader 1 misinterpreted one OFR as a false negative, demonstrating a sensitivity of 0.94 and specificity of 1.00, reader 2 demonstrated perfect accuracy. Intrareader agreement was almost perfect for reader 1 (alpha = 0.95) and was perfect for reader 2 (alpha = 1.00). Additionally, interreader agreement between all fusion sequence reads was almost perfect (alpha = 0.97). The proposed OFR enables reliable detection of anteroinferior tibiofibular ligament rupture with excellent inter- and intrareader agreement, making conventional scanning of oblique images redundant and supplies a method to retroactively create oblique images, e.g., from external examinations.
CRIS-Team WoS Importer:2021-03-19

Secretory Capacity of Pancreatic Beta-Cells Is Enhanced 6 Months After Renal Denervation in Hypertensive Patients - Ott, Christian; Schmid, Axel; Mahfoud, Felix; Akarca, Ertan; Kistner, Iris; Ditting, Tilmann; Veelken, Roland; Boehm, Michael; Uder, Michael; Schmieder, Roland (Journal of the American College of Cardiology, 2018)
EVALuna2:35226

Segmentation of the fascia lata and reproducible quantification of intermuscular adipose tissue (IMAT) of the thigh - Chaudry, Oliver; Friedberger, Andreas; Grimm, Alexandra; Uder, Michael; Nagel, Armin Michael; Kemmler, Wolfgang; Engelke, Klaus (Magnetic Resonance Materials in Physics Biology and Medicine, 2020)
Objective: To develop a precise semi-automated segmentation of the fascia lata (FL) of the thigh to quantify IMAT volume in T1w MR images and fat fraction (FF) in Dixon MR images. Materials and methods: A multi-step segmentation approach was developed to identify fibrous structures of the FL and combining them into a closed 3D surface. 23 healthy young men with low and 50 elderly sarcopenic men with moderate levels of IMAT were measured by T1w and 6pt Dixon MRI at 3T. 20 datasets were used to determine reanalysis precision errors. IMAT volume was compared using the new FL segmentation versus an easier to segment but less accurate, tightly fitting envelope of the thigh muscle ensemble. Results: The segmentation was successfully applied to all 73 datasets and took about 7 min per 28 slices. In particular, in elderly subjects, it includes a large amount of adipose tissue below the FL typically not accounted for in other segmentation approaches. Inter- and intra-operator RMS-CVs were 0.33% and 0.14%, respectively, for IMAT volume and 0.04% and 0.02%, respectively, for FFMT. Discussion: The FL segmentation is an important step to quantify IMAT with high precision and may be useful to investigate effects of aging and treatment on changes of IMAT and FF. ClinicalTrials.gov identifier NCT2857660, August 5, 2016. Trial registration: ClinicalTrials.gov identifier NCT2857660, August 5, 2016.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Adipose tissue; Fascia lata; MRI

Selective Venous Blood Sampling for Hyperparathyroidism with unclear Localization of the Parathyroid Gland - Hader, Christopher; Uder, Michael; Loose, R. W. R.; Linnemann, U.; Bertsch, T.; Adamus, R. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Evaluation of the benefit of selective venous blood sampling (SVS) for the preoperative identification of parathyroid adenomas with unclear localization in non-invasive diagnostics. Materials and Methods: In a retrospective study, all patients (n = 23) with primary (n = 21) or tertiary (n = 2) hyperparathyroidism were evaluated from 2005 to 2016 at the Hospital Nuremberg-North. These patients all received one (n = 20) or more (n = 3) SVS. 15 patients had one or more previous unsuccessful surgeries (group A), 8 patients received the SVS primarily before the first surgery (group B). Results of SVS were compared with the results of surgery, non-invasive diagnostic procedures and clinical follow up. Results: In 24 out of 26 SVS a significant PTH peak was found. 19 patients underwent surgery after SVS. In 16 of these cases (84 %) the SVS peak was concordant with the intraoperative localization. Thus, SVS of all operated patients had a sensitivity of 94 %. Considering only patients with prior HPT surgery the sensitivity was 89 %. In none of the 26 examinations complications occurred. Conclusion: Our results demonstrate that selective venous blood sampling SVS in cases with unclear imaging of parathyroid adenomas is an effective and low-risk invasive diagnostic method to localize parathyroid adenomas and helps to improve surgical therapy. Key points: o?low risk invasive diagnostic procedure to localize parathyroid adenomaso?additional step if non-invasive diagnostics are negative or inconclusiveo?high sensitivity in the detection of parathyroid adenomas Citation Format: o?Hader C, Uder M, Loose RWR et al. Selective Venous Blood Sampling for Hyperparathyroidism with unclear Localization of the Parathyroid Gland. Fortschr Röntgenstr 2016; 188: 1144 - 1150.
EVALuna2:14609

Semantic representation of reported measurements in radiology - Oberkampf, Heiner; Zillner, Sonja; Overton, James A.; Bauer, Bernhard; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (BMC Medical Informatics and Decision Making, 2016)
In radiology, a vast amount of diverse data is generated, and unstructured reporting is standard. Hence, much useful information is trapped in free-text form, and often lost in translation and transmission. One relevant source of free-text data consists of reports covering the assessment of changes in tumor burden, which are needed for the evaluation of cancer treatment success. Any change of lesion size is a critical factor in follow-up examinations. It is difficult to retrieve specific information from unstructured reports and to compare them over time. Therefore, a prototype was implemented that demonstrates the structured representation of findings, allowing selective review in consecutive examinations and thus more efficient comparison over time.We developed a semantic Model for Clinical Information (MCI) based on existing ontologies from the Open Biological and Biomedical Ontologies (OBO) library. MCI is used for the integrated representation of measured image findings and medical knowledge about the normal size of anatomical entities. An integrated view of the radiology findings is realized by a prototype implementation of a ReportViewer. Further, RECIST (Response Evaluation Criteria In Solid Tumors) guidelines are implemented by SPARQL queries on MCI. The evaluation is based on two data sets of German radiology reports: An oncologic data set consisting of 2584 reports on 377 lymphoma patients and a mixed data set consisting of 6007 reports on diverse medical and surgical patients. All measurement findings were automatically classified as abnormal/normal using formalized medical background knowledge, i.e., knowledge that has been encoded into an ontology. A radiologist evaluated 813 classifications as correct or incorrect. All unclassified findings were evaluated as incorrect.The proposed approach allows the automatic classification of findings with an accuracy of 96.4 % for oncologic reports and 92.9 % for mixed reports. The ReportViewer permits efficient comparison of measured findings from consecutive examinations. The implementation of RECIST guidelines with SPARQL enhances the quality of the selection and comparison of target lesions as well as the corresponding treatment response evaluation.The developed MCI enables an accurate integrated representation of reported measurements and medical knowledge. Thus, measurements can be automatically classified and integrated in different decision processes. The structured representation is suitable for improved integration of clinical findings during decision-making. The proposed ReportViewer provides a longitudinal overview of the measurements.
EVALuna2:14471

Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics - Seuß, Hannes; Dankerl, Peter; Ihle, Matthias; Grandjean, Andrea; Hammon, Rebecca; Kaestle, Nicola; Fasching, Peter; Maier, Christian; Christoph, Jan; Sedlmayr, Martin; Uder, Michael; Hammon, Matthias; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose Projects involving collaborations between different institutions require data security via selective de-identification of words or phrases. A semi-automated de-identification tool was developed and evaluated on different types of medical reports natively and after adapting the algorithm to the text structure. Materials and Methods A semi-automated de-identification tool was developed and evaluated for its sensitivity and specificity in detecting sensitive content in written reports. Data from 4671 pathology reports (4105 + 566 in two different formats), 2804 medical reports, 1008 operation reports, and 6223 radiology reports of 1167 patients suffering from breast cancer were de-identified. The content was itemized into four categories: direct identifiers (name, address), indirect identifiers (date of birth/operation, medical ID, etc.), medical terms, and filler words. The software was tested natively (without training) in order to establish a baseline. The reports were manually edited and the model re-trained for the next test set. After manually editing 25, 50, 100, 250, 500 and if applicable 1000 reports of each type re-training was applied. Results In the native test, 61.3 % of direct and 80.8 % of the indirect identifiers were detected. The performance (P) increased to 91.4 % (P25), 96.7 % (P50), 99.5 % (P100), 99.6 % (P250), 99.7 % (P500) and 100 % (P1000) for direct identifiers and to 93.2 % (P25), 97.9 % (P50), 97.2 % (P100), 98.9 % (P250), 99.0 % (P500) and 99.3 % (P1000) for indirect identifiers. Without training, 5.3 % of medical terms were falsely flagged as critical data. The performance increased, after training, to 4.0 % (P25), 3.6 % (P50), 4.0 % (P100), 3.7 % (P250), 4.3 % (P500), and 3.1 % (P1000). Roughly 0.1 % of filler words were falsely flagged. Conclusion Training of the developed de-identification tool continuously improved its performance. Training with roughly 100 edited reports enables reliable detection and labeling of sensitive data in different types of medical reports. Key Points: · Collaborations between different institutions require de-identification of patients' data. · Software-based de-identification of content-sensitive reports grows in importance as a result of 'Big data'. · A de-identification software was developed and tested natively and after training. · The proposed de-identification software worked quite reliably, following training with roughly 100 edited reports. · A final check of the texts by an authorized person remains necessary. Citation Format · Seuss H, Dankerl P, Ihle M et al. Semi-automated De-identification of German Content Sensitive Reports for Big Data Analytics. Fortschr Röntgenstr 2017; 189: 661 - 671.
EVALuna2:14623

Semi-automated delineation of breast cancer tumors and subsequent materialization using three-dimensional printing (rapid prototyping) - Schulz-Wendtland, Rüdiger; Harz, Markus; Meier-Meitinger, Martina; Brehm, Barbara; Wacker, Till; Hahn, Horst K.; Wagner, Florian; Wittenberg, Thomas; Beckmann, Matthias; Uder, Michael; Fasching, Peter; Emons, Julius (Journal of Surgical Oncology, 2017)
Three-dimensional (3D) printing has become widely available, and a few cases of its use in clinical practice have been described. The aim of this study was to explore facilities for the semi-automated delineation of breast cancer tumors and to assess the feasibility of 3D printing of breast cancer tumors.In a case series of five patients, different 3D imaging methods-magnetic resonance imaging (MRI), digital breast tomosynthesis (DBT), and 3D ultrasound-were used to capture 3D data for breast cancer tumors. The volumes of the breast tumors were calculated to assess the comparability of the breast tumor models, and the MRI information was used to render models on a commercially available 3D printer to materialize the tumors.The tumor volumes calculated from the different 3D methods appeared to be comparable. Tumor models with volumes between 325 mm(3) and 7,770 mm(3) were printed and compared with the models rendered from MRI. The materialization of the tumors reflected the computer models of them.3D printing (rapid prototyping) appears to be feasible. Scenarios for the clinical use of the technology might include presenting the model to the surgeon to provide a better understanding of the tumor's spatial characteristics in the breast, in order to improve decision-making in relation to neoadjuvant chemotherapy or surgical approaches. J. Surg. Oncol. 2017;115:238-242. © 2016 Wiley Periodicals, Inc.
EVALuna2:14618

Semiautomatic segmentation of the kidney in magnetic resonance images using unimodal thresholding - Sandmair, Martin; Hammon, Matthias; Seuss, Hannes; Theis, Ragnar; Uder, Michael; Janka, Rolf Matthias (BMC Research Notes, 2016)
Total kidney volume (TKV) is an important marker for the presence or progression of chronic kidney disease, however, routine ultrasonography underestimates renal volume to a high and varying degree.The aim of this work was to adapt and evaluate a semi-automatic unimodal thresholding method for volumetric analysis of the kidney in native T2-weighted magnetic resonance (MR) images.In a group of healthy volunteers (n = 24; 48 kidneys), we defined a region of interest (ROI) by manually tracing the outline of the kidney in every MR image. An automatic unimodal thresholding algorithm with visual feedback was applied to the probability distribution function of voxel intensities in the ROI to remove intrarenal non-parenchyma volume. For comparison, reference volumes were created by manual segmentation. Intra- and inter-observer reliability was evaluated.There was a small, significant mean difference of 1.5 ml between semi-automatically and manually segmented TKV (p = 0.009, 95% CI [0.4, 2.7]). While intra-observer reliability was good (mean difference 2.9 ml, p < 0.01, 95% CI [1.5, 4.2]) there was a small but significant mean difference of 4.8 ml (p < 0.01, 95% CI [3.6, 5.9]) between the TKV results of different observers. Reference volume correlations were excellent (r = 0.97-0.98). Semi-automated segmentation was significantly faster than manual segmentation; mean difference = 234 s [91-483 s]; p < 0.05. Automatic unimodal thresholding removed a considerable mean volume of 18.7 ml (13.1%) from the coarse manual pre-segmentations.Unimodal thresholding of native MR images is a robust and sufficiently reliable method for kidney segmentation and volumetric analysis. The manual pre-segmentation can be done by non-experts with little introduction.
EVALuna2:14594

SGLT-2-inhibition with dapagliflozin reduces tissue sodium content: a randomised controlled trial - Karg, Margarete; Bosch, A.; Kannenkeril, D.; Striepe, Kristina; Ott, Christian; Schneider, M. P.; Boemke-Zelch, Franziska; Linz, Peter; Nagel, Armin Michael; Titze, Jens; Uder, Michael; Schmieder, Roland (Cardiovascular Diabetology, 2018)
Sodium tissue content by 23Na magnetic resonance imaging (Na-MRI) has been validated in experimental and human studies. SGLT-2 inhibition blocks the reabsorption of glucose and of sodium in the proximal tubular cells in a 1:1 fashion. We hypothesized that SGLT-2 inhibition in patients with type 2 diabetes characterized by sodium retention leads to decreased tissue sodium content due to its pharmacological action.In a prospective double blind, placebo controlled, cross-over trial 59 patients (61 ± 7.6 years) with type 2 diabetes were randomized to either dapagliflozin 10 mg or placebo once daily for 6 weeks each. In addition to metabolic parameters and ambulatory blood pressure (BP) we analysed the sodium content in the skin and muscles of the lower leg by Na-MRI.Compared to baseline 6 weeks treatment with the SGLT-2 inhibitor dapagliflozin decreased fasting (132 ± 28 vs. 114 ± 19 mg/dl, p < 0.001), postprandial blood glucose (178 ± 66 mg/dl vs. 153 ± 46 mg/dl, p < 0.001), body weight (87.6 vs. 86.6 kg, p < 0.001) and systolic (129 ± 12 vs. 126 ± 11 mmHg, p = 0.010), and diastolic (77.4 ± 9 vs. 75.6 ± 8 mmHg, p = 0.024), 24-h ambulatory BP. Tissue sodium content in the skin was reduced after 6 weeks treatment with dapagliflozin compared to baseline [24.1 ± 6.6 vs. 22.7 ± 6.4 A.U.(arbitrary unit) p = 0.013]. No significant reduction of tissue sodium content was observed in the muscle (M. triceps surae: 20.5 ± 3.5 vs. 20.4 ± 3.7 A.U. p = 0.801). No clear significant difference in tissue water content of muscle and skin was observed after 6 weeks of treatment with dapagliflozin, compared to baseline.SGLT-2 inhibition with dapagliflozin resulted in a significant decrease in tissue sodium content of the skin after 6 weeks. This observation point to a decrease of total sodium content in patients with type 2 diabetes prone to cardiovascular complications, that might be mitigated by SGLT-2 inhibition. Trial registration The study was registered at http://www.clinicaltrials.gov (NCT02383238) retrospectively registered.
EVALuna2:4043

Signal decomposition for X-ray dark-field imaging - Käppler, Sebastian; Bayer, Florian; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Beckmann, Matthias; Fasching, Peter; Hartmann, Arndt; Heindl, Felix; Michel, Thilo; Oezguel, Gueluemser; et al. (MICCAI 2014, 2014)
Grating-based X-ray dark-field imaging is a new imaging modality. It allows the visualization of structures at micrometer scale due to small-angle scattering of the X-ray beam. However, reading darkfield images is challenging as absorption and edge-diffraction effects also contribute to the dark-field signal, without adding diagnostic value. In this paper, we present a novel–and to our knowledge the first–algorithm for isolating small-angle scattering in dark-field images, which greatly improves their interpretability. To this end, our algorithm utilizes the information available from the absorption and differential phase images to identify clinically irrelevant contributions to the dark-field image. Experimental results on phantom and ex-vivo breast data promise a greatly enhanced diagnostic value of dark-field image
EVALuna2:6632

Significant Suppression of CT Radiation-Induced DNA Damage in Normal Human Cells by the PrC-210 Radioprotector - Jermusek, Frank; Benedict, Chelsea; Dreischmeier, Emma; Brand, Michael; Uder, Michael; Jeffery, Justin J.; Ranallo, Frank N.; Fahl, William E. (Radiation Research, 2018)
While computed tomography (CT) is now commonly used and considered to be clinically valuable, significant DNA double-strand breaks (γ-H2AX foci) in white blood cells from adult and pediatric CT patients have been frequently reported. In this study to determine whether γ-H2AX foci and X-ray-induced naked DNA damage are suppressed by administration of the PrC-210 radioprotector, human blood samples were irradiated in a CT scanner at 50-150 mGy with or without PrC-210, and γ-H2AX foci were scored. X-ray-induced naked DNA damage was also studied, and the DNA protective efficacy of PrC-210 was compared against 12 other common "antioxidants." PrC-210 reduced CT radiation-induced γ-H2AX foci in white blood cells to near background ( P < 0.0001) at radiation doses of 50-150 mGy. PrC-210 was most effective among the 13 "antioxidants" in reducing naked DNA X-ray damage, and its addition at 30 s before an •OH pulse reduced to background the •OH insult that otherwise induced >95% DNA damage. A systemic PrC-210 dose known to confer 100% survival in irradiated mice had no discernible effect on micro-CT image signal-to-noise ratio and CT image integrity. PrC-210 suppressed DNA damage to background or near background in each of these assay systems, thus supporting its development as a radioprotector for humans in multiple radiation exposure settings.
EVALuna2:34691

Simultaneous Multislice Echo Planar Imaging for Accelerated Diffusion-Weighted Imaging of Malignant and Benign Breast Lesions - Ohlmeyer, Sabine; Palm, Theresa; Janka, Rolf Matthias; Weiland, Elisabeth; Uder, Michael; Wenkel, Evelyn; Laun, Frederik Bernd (Investigative Radiology, 2019)
Objectives Comparison of the diagnostic value of simultaneous multislice (SMS) accelerated diffusion-weighted echo planar imaging (EPI) of malignant and benign lesions of the breast compared with a reference EPI sequence. Materials and Methods The study was approved by the institutional ethics committee. Sixty-eight patients were examined with a diffusion-weighted EPI (reference EPI; TE = 54 milliseconds; TR = 9000 milliseconds; TA, 3:27 minutes) and a diffusion-weighted SMS accelerated EPI (SMS EPI; acceleration factor 2; TE = 58 milliseconds; TR = 4300 milliseconds; TA, 1:53 minutes) in addition to the standard magnetic resonance imaging (MRI) protocol. Further acquisition parameters were as follows: 3 T MAGNETOM Skyra (Siemens Healthcare, Erlangen, Germany), 2.5-mm isotropic resolution, field of view = 185 to 190 × 350 mm2, 62 slices, b = 50 and 800 s/mm2 with 1 and 4 averages, respectively. A dedicated 16-channel bilateral breast coil was used for imaging. Image quality was evaluated with respect to the presence of artifacts, signal voids, and quality of fat suppression. These parameters were rated using a 5-point Likert scale (1 = very strong to 5 = negligible). The apparent diffusion coefficient (ADC) was measured in 72 focal lesions (46 breast carcinomas and 26 benign lesions), and the diagnostic value of the 2 datasets was statistically evaluated and compared. The evaluation was performed a second time excluding cysts. Results Artifacts and signal voids were negligible in both sequences (mean on Likert scale for reference EPI 4.68 vs SMS EPI 4.65, P = 0.52, and mean on Likert scale for reference EPI 4.85 vs SMS EPI 4.77, P = 0.14). Fat suppression was significantly better in SMS EPI (mean on Likert scale 3.28 vs 2.97, P < 0.001, Pearson r = 0.49). For benign lesions, the mean ADC in both EPI sequences was 1.86 · 10-3 mm2/s. For malignant lesions, a mean ADC of 0.90 · 10-3 mm2/s for the reference EPI and 0.89 · 10-3 mm2/s for the SMS EPI was found. No significant difference between the EPI sequences was observed for ADC values (P = 0.75) and for the area under the curve (SMS, 0.985; no SMS, 0.975). The cutoff for differentiation of benign and malignant lesions was at ADC = 1.42 · 10-3 mm2/s for SMS EPI (sensitivity, 1; specificity, 0.88) and at 1.23 · 10-3 mm2/s for the reference EPI (sensitivity, 1; specificity, 0.92). Excluding the cysts, the cutoff for differentiation of benign and malignant lesions was at ADC = 1.11 · 10-3 mm2/s for SMS EPI (sensitivity, 0.89; specificity, 0.93) and at 1.23 · 10-3 mm2/s for the reference EPI (sensitivity, 1; specificity, 0.87). Conclusions Our data indicate that SMS acceleration can be used for diffusion imaging in breast MRI in clinical practice. Simultaneous multislice EPI achieved the same diagnostic accuracy in breast MRI, but in a substantially reduced scan time.
CRIS-Team Scopus Importer:2019-07-26
Keywords: breast; diffusion; DW MRI; DWI; EPI; lesions; simultaneous multislice acceleration; SMS

Single-cycle induction chemotherapy followed by chemoradiotherapy or surgery in patients with head and neck cancer: What are the best predictors of remission and prognosis? - Semrau, Sabine; Haderlein, Marlen; Schmidt, Daniela; Lell, Michael; Wolf, Walburga; Waldfahrer, Frank; Uder, Michael; Iro, Heinrich; Kuwert, Torsten; Fietkau, Rainer (Cancer, 2015)
There is controversy over the concept of function and organ preservation by chemotherapy/chemoradiation instead of surgery in locally advanced cancer of the larynx or pharynx. Tumor response to induction chemotherapy (ICT) can help in choosing between conservative and surgical treatment. This study compared 3 methods of assessing response to ICT: endoscopy, computed tomography, and (18) F-FDG-PET/CT.Primary response to 1 cycle of ICT with docetaxel plus platinum was assessed by the aforementioned methods in 62 laryngopharyngeal cancer patients. Endoscopic response was the deciding factor for selecting further treatment: surgery for endoscopic nonresponders (<30% tumor response) versus chemoradiotherapy for endoscopic responders.ICT achieved endoscopic response in 48 of 62 patients (77%). Individual relative residual tumor activity of standardized uptake value (resSUVmax ) in (18) F-FDG-PET/CT was a median 0.38 of baseline (0.09-1.71), whereas residual tumor extent in CT (resCT) was 0.75 of baseline (0.32-1.20). Endoscopic responders and nonresponders differed significantly in SUVmax after ICT (postSUVmax , 6.0 vs 14.5; P < .001), resSUVmax (0.34 vs 0.81, P < .001), and resCT (0.71 vs 0.87, P = .004), but not in maximum tumor diameter after ICT (14 vs 20 mm, P = .11). resSUVmax <0.8 and absolute postSUVmax <10 provided the best discriminatory power for long-term success criteria (tumor-free survival, overall survival).Metabolic tumor response showed very good correlation with clinical tumor response to ICT. The value of metabolic response detected by (18) F-FDG-PET/CT should be explored in a prospective clinical trial. Cancer 2015;121:1214-1222. © 2014 American Cancer Society.
EVALuna2:13821

Single source split filter dual energy: Image quality and liver lesion detection in abdominal CT - Eichler, Mathis; May, Matthias; Wiesmüller, Marco; Saake, Marc; Heiß, Rafael; Uder, Michael; Wüst, Wolfgang (European Journal of Radiology, 2020)
Purpose: Aim of this study was to evaluate image quality of single source dual energy CT (SSDE-CT) using split filter technique in oncologic abdominal CT. Method: 51 consecutive patients with newly diagnosed breast carcinoma were prospectively enrolled in this study and underwent a staging examination of the abdomen using SSDE-CT (120 kV, split filter technique, 400 ref. mAs). Inline default images (DI) and post-processed virtual monoenergetic images at 40 keV, 50 keV, 60 keV, 70 keV and 80 keV were reconstructed. Objective image quality was evaluated as contrast to noise ratio (CNR) for liver parenchyma, portal vein, spleen, pancreas, aorta and hypoattenuating liver lesions. Subjective image quality was rated on a 5-point scale. Image quality at different keV settings was analyzed in paired t-tests. Results: CNR was highest at 40 keV for vessels (portal vein: 9.0, aorta: 8.8, all p < 0.001) and for upper abdominal organs (spleen: 4.8, all p < 0.001; pancreas: 2.7, all p < 0.01 except p = 0.93 for 50 keV; liver parenchyma: 3.4, all p < 0.01). Highest CNR values for hypoattenuating liver lesions were found at 40 keV (7.7, all p < 0.001). Overall subjective image quality was highest with 80 keV and DI (both 4.8, all p < 0.001). Artifacts were most pronounced at 40 keV. Conclusions: High image quality can be obtained with SSDE-CT of the abdomen. Lowest monoenergetic reconstructions provide the highest image contrast and should be used for vessel evaluation. The best trade-off between artifacts and parenchymal contrast can be obtained with 80 keV images.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Abdominal imaging; Breast carcinoma; Single source dual energy

Skin Sodium Concentration Correlates with Left Ventricular Hypertrophy in CKD - Schneider, Markus P.; Raff, Ulrike; Kopp, Christoph; Scheppach, Johannes B.; Toncar, Sebastian; Wanner, Christoph; Schlieper, Georg; Saritas, Turgay; Floege, Juergen; Schmid, Matthias; Birukov, Anna; Dahlmann, Anke; et al. (Journal of the American Society of Nephrology, 2017)
The pathogenesis of left ventricular hypertrophy in patients with CKD is incompletely understood. Sodium intake, which is usually assessed by measuring urinary sodium excretion, has been inconsistently linked with left ventricular hypertrophy. However, tissues such as skin and muscle may store sodium. Using (23)sodium-magnetic resonance imaging, a technique recently developed for the assessment of tissue sodium content in humans, we determined skin sodium content at the level of the calf in 99 patients with mild to moderate CKD (42 women; median [range] age, 65 [23-78] years). We also assessed total body overhydration (bioimpedance spectroscopy), 24-hour BP, and left ventricular mass (cardiac magnetic resonance imaging). Skin sodium content, but not total body overhydration, correlated with systolic BP (r=0.33, P=0.002). Moreover, skin sodium content correlated more strongly than total body overhydration did with left ventricular mass (r=0.56, P<0.001 versus r=0.35, P<0.001; P<0.01 between the two correlations). Linear regression analysis demonstrated that skin sodium content is a strong explanatory variable for left ventricular mass, unaffected by BP and total body overhydration. In conclusion, we found skin sodium content to be closely linked to left ventricular mass in patients with CKD. Interventions that reduce skin sodium content might improve cardiovascular outcomes in these patients.
EVALuna2:3863

Skin sodium content as a predictor of blood pressure response to renal denervation - Günes-Altan, Merve; Schmid, Axel; Kannenkeril, Dennis; Linz, Peter; Ott, Christian; Bosch, Agnes; Schiffer, Mario; Uder, Michael; Schmieder, Roland (Hypertension Research, 2023)
Patients with treatment resistant hypertension (TRH) are known to have elevated sodium (Na) content in muscle and skin. Renal denervation (RDN) emerged as an adjacent therapeutic option in this group of patients. This analysis aimed at evaluating whether tissue Na content predicts blood pressure (BP) response after RDN in patients with TRH. Radiofrequency-device based RDN was performed in 58 patients with uncontrolled TRH. Office and 24-h ambulatory BP were measured at baseline and after 6 months. To assess tissue Na content Na magnetic resonance imaging (Na-MRI) was performed at baseline prior to RDN. We splitted the study cohort into responders and non-responders based on the median of systolic 24-h ambulatory blood pressure (ABP) reduction after 6 months and evaluated the association between BP response to RDN and tissue Na content in skin and muscle. The study was registered at http://www.clinicaltrials.gov (NCT01687725). Six months after RDN 24-h ABP decreased by −8.6/−4.7 mmHg. BP-Responders were characterized by the following parameters: low tissue sodium content in the skin (p = 0.040), female gender (p = 0.027), intake of aldosterone antagonists (p = 0.032), high baseline 24-h night-time heart rate (p = 0.045) and high LDL cholesterol (p < 0.001). These results remained significant after adjustment for baseline 24-h systolic BP. Similar results were obtained when the median of day-time and night-time ABP reduction after 6 months were used as cut-off criteria for defining BP response to RDN. We conclude that in addition to clinical factors including baseline 24-h ABP Na-MRI may assist to select patients with uncontrolled TRH for RDN treatment. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-11-03
Keywords: Renal denervation; Sodium MRI; Tissue sodium

Skin sodium is increased in male patients with multiple sclerosis and related animal models - Huhn, Konstantin; Linz, Peter; Pemsel, Franziska; Michalke, Bernhard; Seyferth, Stefan; Kopp, Christoph; Chaudri, Mohammad Anwar; Rothhammer, Veit; Dörfler, Arnd; Uder, Michael; Nagel, Armin M.; Müller, Dominik N.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Novel MRI techniques allow a noninvasive quantification of tissue sodium and reveal the skin as a prominent compartment of sodium storage in health and disease. Since multiple sclerosis (MS) immunopathology is initiated in the periphery and increased sodium concentrations induce proinflammatory immune cells, the skin represents a promising compartment linking high sodium concentrations and MS immunopathology. We used a 7-T sodium MRI (23Na-MRI) and inductively coupled plasma mass spectrometry to investigate the skin sodium content in two mouse models of MS. We additionally performed 3-T 23Na-MRI of calf skin and muscles in 29 male relapsing-remitting MS (RRMS) patients and 29 matched healthy controls. Demographic and clinical information was collected from interviews, and disease activity was assessed by expanded disability status scale scoring. 23Na-MRI and chemical analysis demonstrated a significantly increased sodium content in the skin during experimental autoimmune encephalomyelitis independent of active immunization. In male patients with RRMS, 23Na-MRI demonstrated a higher sodium signal in the area of the skin compared to age- and biological sex-matched healthy controls with higher sodium, predicting future disease activity in cranial MRI. In both studies, the sodium enrichment was specific to the skin, as we found no alterations of sodium signals in the muscle or other tissues. Our data add to the recently identified importance of the skin as a storage compartment of sodium and may further represent an important organ for future investigations on salt as a proinflammatory agent driving autoimmune neuroinflammation such as that in MS.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Experimental autoimmune encephalomyelitis; Multiple sclerosis; Skin; Sodium magnetic resonance imaging

Small direct right ventricular cardiac metastasis of osteosarcoma in a 10-year-old boy affirmed by cardiac MRI - Linder, Verena; Fritscher, Torsten; Hammon, Matthias; Schroth, Michael; Schmidt, Wolfgang; Uder, Michael; Rompel, Oliver (Radiology Case Reports, 2020)
Background: Metastatic osteosarcoma with direct cardiac involvement is an exceptionally rare finding. Reliable detection of cardiac metastases is known to be crucial for patients therapy and prognosis. Case Summary: In a 10-year-old boy affected by osteosarcoma of the left femur, a baseline Fluorine-18-fluorodeoxy-glucose positron emission tomography/computed tomography (18F-FDG PET/CT) was performed to assess the full extent of disease. Whole-body scan detected numerous bone metastases together with a single pulmonary metastasis. Moreover, increased tracer uptake was observed in the intracavitary right cardiac ventricle in the position of a subtle spot of calcification. Because of nondetectability of a cavitary lesion on echocardiography, cardiac magnetic resonance imaging (CMRI) examination was performed to evaluate cardiac 18F-FDG PET/CT finding. CMRI revealed a small nodule in the right ventricle attached to the trabeculae, highly suspicious of a direct cardiac metastasis. After 4 cycles of chemotherapy, complete regression of tracer uptake of the lesion was observed on a follow-up 18F-FDG PET/CT scan. Conclusion: CMRI is able to detect even small, clinically asymptomatic cardiac metastases in young patients affected by osteosarcoma.
CRIS-Team Scopus Importer:2020-04-17
Keywords: CMRI; Direct cardiac metastasis; Osteosarcoma

Smart forecasting of artifacts in contrast-enhanced breast MRI before contrast agent administration - Liebert, Andrzej; Das, Badhan Kumar; Kapsner, Lorenz; Eberle, Jörg; Skwierawska, Dominika; Folle, Lukas; Schreiter, Hannes; Laun, Frederik Bernd; Ohlmeyer, Sabine; Uder, Michael; Wenkel, Evelyn; Bickelhaupt, Sebastian (European Radiology, 2023)
Objectives: To evaluate whether artifacts on contrast-enhanced (CE) breast MRI maximum intensity projections (MIPs) might already be forecast before gadolinium-based contrast agent (GBCA) administration during an ongoing examination by analyzing the unenhanced T1-weighted images acquired before the GBCA injection. Materials and methods: This IRB-approved retrospective analysis consisted of n = 2884 breast CE MRI examinations after intravenous administration of GBCA, acquired with n = 4 different MRI devices at different field strengths (1.5 T/3 T) during clinical routine. CE-derived subtraction MIPs were used to conduct a multi-class multi-reader evaluation of the presence and severity of artifacts with three independent readers. An ensemble classifier (EC) of five DenseNet models was used to predict artifacts for the post-contrast subtraction MIPs, giving as the input source only the pre-contrast T1-weighted sequence. Thus, the acquisition directly preceded the GBCA injection. The area under ROC (AuROC) and diagnostics accuracy scores were used to assess the performance of the neural network in an independent holdout test set (n = 285). Results: After majority voting, potentially significant artifacts were detected in 53.6% (n = 1521) of all breast MRI examinations (age 49.6 ± 12.6 years). In the holdout test set (mean age 49.7 ± 11.8 years), at a specificity level of 89%, the EC could forecast around one-third of artifacts (sensitivity 31%) before GBCA administration, with an AuROC = 0.66. Conclusion: This study demonstrates the capability of a neural network to forecast the occurrence of artifacts on CE subtraction data before the GBCA administration. If confirmed in larger studies, this might enable a workflow-blended approach to prevent breast MRI artifacts by implementing in-scan personalized predictive algorithms. Clinical relevance statement: Some artifacts in contrast-enhanced breast MRI maximum intensity projections might be predictable before gadolinium-based contrast agent injection using a neural network. Key Points: • Potentially significant artifacts can be observed in a relevant proportion of breast MRI subtraction sequences after gadolinium-based contrast agent administration (GBCA). • Forecasting the occurrence of such artifacts in subtraction maximum intensity projections before GBCA administration for individual patients was feasible at 89% specificity, which allowed correctly predicting one in three future artifacts. • Further research is necessary to investigate the clinical value of such smart personalized imaging approaches.
CRIS-Team Scopus Importer:2023-12-22
Keywords: Artifact; Breast; Forecasting; Magnetic resonance imaging; Neural networks (computer)

Sodium and quantitative hydrogen parameter changes in muscle tissue after eccentric exercise and in delayed-onset muscle soreness assessed with magnetic resonance imaging - Höger, Svenja; Gast, Lena; Marty, Benjamin; Hotfiel, Thilo; Bickelhaupt, Sebastian; Uder, Michael; Heiß, Rafael; Nagel, Armin Michael (NMR in Biomedicine, 2022)
The objective of the current study was to assess sodium (Na-23) and quantitative proton (H-1) parameter changes in muscle tissue with magnetic resonance imaging (MRI) after eccentric exercise and in delayed-onset muscle soreness (DOMS). Fourteen participants (mean age: 25 +/- 4 years) underwent Na-23/H-1 MRI of the calf muscle on a 3-T MRI system before exercise (t0), directly after eccentric exercise (t1), and 48 h postintervention (t2). In addition to tissue sodium concentration (TSC), intracellular-weighted sodium (ICwS) signal was acquired using a three-dimensional density-adapted radial projection readout with an additional inversion recovery preparation module. Phantoms containing saline solution served as references to quantify sodium concentrations. The H-1 MRI protocol consisted of a T-1-weighted turbo spin echo sequence, a T-2-weighted turbo inversion recovery, as well as water T-2 mapping and water T-1 mapping. Additionally, blood serum creatine kinase (CK) levels were assessed at baseline and 48 h after exercise. The TSC and ICwS of exercised muscles increased significantly from t0 to t1 and decreased significantly from t1 to t2. In the soleus muscle (SM), ICwS decreased below baseline values at t2. In the tibialis anterior muscle (TA), TSC and ICwS remained at baseline levels at each measurement point. However, high-CK participants (i.e., participants with a more than 10-fold CK increase, n = 3) displayed different behavior, with 2- to 4-fold increases in TSC values in the medial gastrocnemius muscle (MGM) at t2. H-1 water T-1 relaxation times increased significantly after 48 h in the MGM and SM. H-1 water T-2 relaxation times and muscle volume increased in the MGM at t2. Sodium MRI parameters and water relaxation times peaked at different points. Whereas water relaxation times were highest at t2, sodium MRI parameters had already returned to baseline values (or even below baseline values, for low-CK participants) by this point. The observed changes in ion concentrations and water relaxation time parameters could enable a better understanding of the physiological processes during DOMS and muscle regeneration. In the future, this might help to optimize training and to reduce associated sports injuries.
CRIS-Team WoS Importer:2022-11-25

Spatial Distribution of Muscular Effects of Acute Whole-Body Electromyostimulation at the Mid-Thigh and Lower Leg-A Pilot Study Applying Magnetic Resonance Imaging - Götz, Marina; Heiß, Rafael; von Stengel, Simon; Roemer, Frank; Berger, Joshua; Nagel, Armin Michael; Uder, Michael; Kemmler, Wolfgang (Sensors, 2022)
Whole-body electromyostimulation (WB-EMS) is an innovative training method that stimulates large areas simultaneously. In order to determine the spatial distribution of WB-EMS with respect to volume involvement and stimulation depth, we determined the extent of intramuscular edema using magnetic resonance imaging (MRI) as a marker of structural effects. Intense WB-EMS first application (20 min, bipolar, 85 Hz, 350 mu s) was conducted with eight physically less trained students without previous WB-EMS experience. Transversal T2-weighted MRI was performed at baseline and 72 h post WB-EMS to identify edema at the mid-thigh and lower leg. The depth of the edema ranged from superficial to maximum depth with superficial and deeper muscle groups of the mid-thigh or lower leg area approximately affected in a similar fashion. However, the grade of edema differed between the muscle groups, which suggests that the intensity of EMS-induced muscular contraction was not identical for all muscles. WB-EMS of the muscles via surface cuff electrodes has an effect on deeper parts of the stimulated anatomy. Reviewing the spatial and volume distribution, we observed a heterogeneous pattern of edema. We attribute this finding predominately to different stimulus thresholds of the muscles and differences in the stress resistance of the muscles.
CRIS-Team WoS Importer:2023-01-27

SPECT/CT With the PSMA Ligand 99mTc-MIP-1404 for Whole-Body Primary Staging of Patients With Prostate Cancer - Schmidkonz, Christian; Cordes, Michael; Beck, Michael; Goetz, Theresa Ida; Schmidt, Daniela; Prante, Olaf; Bäuerle, Tobias; Uder, Michael; Wullich, Bernd; Goebell, Peter; Kuwert, Torsten; Ritt, Philipp (Clinical Nuclear Medicine, 2018)
BACKGROUND: Tc-MIP-1404 (Progenics Pharmaceuticals, Inc, New York, NY) is a novel ligand binding to prostate-specific membrane antigen suitable for SPECT. There are, as yet, no data concerning its use in whole-body primary staging and its interobserver variability in patients with prostate cancer (PC) prior to therapy. METHODS: A search of our clinical database from April 2013 to May 2017 yielded 93 patients with histologically confirmed cancer in whom Tc-MIP-1404 SPECT/CT had been performed for primary whole-body staging before therapy. Whole-body planar and SPECT/CT images of the lower abdomen and thorax had been obtained 3 to 4 hours postinjection of 706 ± 72 MBq Tc-MIP-1404. Images were visually analyzed for extent and location of abnormal uptake by 2 experienced nuclear physicians. Interobserver agreement for detection of primary tumor and metastatic lesions was assessed. In addition, SUVs of prostate-specific membrane antigen-positive regions of the prostate were determined in all patients, and from these, a variable reflecting total tumor load in the prostate gland was calculated (TUprostate). Follow-up reports of subsequent therapeutic interventions were available in 52 (56%) of all patients with a median follow-up of 18 months. RESULTS: In 90 (97%) of 93 patients, prostate uptake above background was detected as correlate of the histologically diagnosed PC. Forty-eight lymph node and 29 bone metastases were detected in 16 and 9 patients, respectively. In addition, 3 patients had disseminated bone metastases. No distant organ metastases were found. Interobserver agreement was high for the overall scan result (97%), as well as for the detection of the primary tumor (97%), of lymph node metastases (97%), and of bone metastases (99%). Recurrence of PC occurred in 5 patients in whom follow-up was available (10%). TUprostate was significantly higher in patients with Gleason scores of 8 or greater compared with patients with Gleason scores of 7 or less and at prostate-specific antigen (PSA) serum levels of 10 ng/mL or greater compared with PSA serum levels of 10 ng/mL or less. TUprostate of greater than 26 in the primary tumor predicted the occurrence of lymph node or bone metastases with a sensitivity of 82% and specificity of 76%. CONCLUSIONS: MIP-1404 SPECT/CT has a high accuracy and low interobserver variability in the diagnosis of PC and allows detection of lymph node and bone metastases in a significant proportion of as yet untreated PC patients. TUprostate is correlated with Gleason score and PSA serum concentration and allows prediction of the occurrence of lymph node and bone metastases with moderate accuracy at primary staging.
EVALuna2:32786

Spiral breast computed tomography with a photon-counting detector (SBCT): The future of breast imaging? - Wetzl, Matthias; Dietzel, Matthias; Ohlmeyer, Sabine; Uder, Michael; Wenkel, Evelyn (European Journal of Radiology, 2022)
Dedicated breast computed tomography (BCT) is an emerging breast imaging modality. The latest development has been the introduction of a spiral breast computed tomography scanner equipped with a photon-counting detector (SBCT). SBCT promises multiple advantages: Unlike conventional mammography, contrast enhanced spectral mammography (CESM: both 2D), and digital breast tomosynthesis (DBT: pseudo 3D), SBCT enables 3D breast imaging without tissue overlap. SBCT achieves high isotropic spatial resolution of breast tissue enabling the assessment of both soft tissue and microcalcifications. Similar to CESM and MRI, SBCT supports contrast-enhanced imaging, enabling the assessment of breast neovascularization. Unlike mammography and its derived methods (CESM, DBT), SBCT does not require compression of the breast. Accordingly, women consistently report significantly increased patient comfort compared to mammography in a previous investigation. Radiation safety is crucial in breast imaging. Studies showed different results in terms of dose, with some staying within the limits of two-view FFDM defined by the ACR and others exceeding the limit by up to 21%. Therefore, a higher radiation dose compared to state-of-the-art mammography and DBT systems has to be acknowledged. SBCT is currently under scientific investigation in multiple trials. Three major indications are currently explored: Whereas our colleagues in Zurich/Switzerland investigate the role of SBCT for opportunistic screening, in our department SBCT is mainly indicated for the work-up of equivocal lesions, and for preoperative staging. In this narrative review, we summarize the concepts of SBCT and potential implications for patient care. We report on our initial clinical experience with the technology and outline future developments of SBCT.
CRIS-Team Scopus Importer:2022-12-09
Keywords: Breast imaging; Dedicated breast computed tomography

Stent evaluation in low-dose coronary CT angiography: Effect of different iterative reconstruction settings - Wüst, Wolfgang; May, Matthias; Scharf, Michael; Layritz, Christian; Eisentopf, Jasmin; Ropers, Dieter; Pflederer, Tobias; Uder, Michael; Achenbach, Stephan; Lell, Michael (Journal of Cardiovascular Computed Tomography, 2013)
Background: Different iterative reconstruction (IR) techniques compensate increased noise from lower tube current-time product settings, yet the differences between IR settings remain unclear. Objective: Aim of this study was to test whether different IR settings have a clinically relevant influence on image quality and on the diagnostic accuracy of low-dose CT angiography in patients with a stent. Methods: Forty-two patients with 73 coronary stents were prospectively enrolled. Data were acquired with dual-source CT, and images were reconstructed with standard filtered back projection (FBP) and raw data-based IR with different settings (I3, I4, I5). Quantitative parameters, including CT-attenuation, noise, signal-to-noise ratio, contrast-to-noise ratio, as well as the presence of in-stent stenosis > 50% were determined. All patients had invasive angiography as reference standard. Results: Mean effective dose was 0.32 ± 0.02 mSv. Image noise decreased significantly compared with FBP (I3= 29%; I4= 38% and I5= 45%), whereas signal-to-noise and contrast-to-noise ratios increased significantly (all IR settings P <.01). Subjective image quality was superior with all IR settings (P < .01). FBP sensitivity, specificity, positive predictive value, and negative predictive value were 83%, 71%, 36%, and 96% per stent compared with 100%, 76%, 44%, and 100%, respectively, in IR reconstructions independent of the IR setting applied. Conclusion: In low-dose coronary CT angiography, higher IR settings significantly improved subjective and objective image quality but had no effect on accuracy. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiac CT; Coronary stents; Iterative reconstruction; Low dose; SAFIRE

Stent Implantation for Superior Vena Cava Syndrome of Malignant Cause - Büstgens, Felix; Loose, Reinhard; Ficker, Joachim H.; Wucherer, Michael; Uder, Michael; Adamus, Ralf (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The purpose of this paper is the retrospective analysis of endovascular therapy for the treatment of superior vena cava syndrome (SVCS) of malignant cause. This study focuses on the effectiveness of the therapy regarding the duration of remission, symptom control and practicability. Materials and Methods From January 2003 to November 2012, therapeutic implantation of one or more stents was performed in 141 patients suffering from SVCS. The medical history was retrospectively researched using digitalized patient files. If those were incomplete, secondary research was conducted using the cancer registry of the General Hospital Nuremberg, the cancer registry of the tumor center at Friedrich-Alexander-University Erlangen-Nuremberg (FAU) or information given by physicians in private practice. This data was collected using Microsoft Office Excel(®) and statistically analyzed using IBM SPSS Statistics 22(®). Results 168 stents were implanted in 141 patients (median age: 64.6 years; range: 36 - 84), 86 being male and 55 being female. In 121 patients, SVCS was caused by lung cancer (85.8 %), in 9 patients by mediastinal metastasis of an extrathoracic carcinoma (6.4 %), in 3 patients by mesothelioma of the pleura (2.1 %) and in 1 patient by Hodgkin's disease (0.7 %). There was no histological diagnosis in 7 cases (4.9 %). The primary intervention was successful in 138 patients (97.9 %). Immediate thrombosis in the stent occurred in the remaining 3 cases. Recurrence of SVCS was observed in 22 patients (15.6 %), including 5 early and 17 late occlusions. Stent dislocation or breakage was not observed. As expected, the survival after implantation was poor. The median survival was 101 days, and the median occlusion-free survival was 80 days. Conclusion The symptomatic therapy of SVCS with endovascular stents is effective and safe. Despite effective symptom control and a low rate of recurrence, the patients' prognosis is poor. Key Points: · Patients with SVCS of malignant cause have a poor prognosis.. · Lung cancer is the most common cause for SVCS.. · Endovascular therapy is safe and effective.. Citation Format · Büstgens FA, Loose R, Ficker JH et al. Stent Implantation for Superior Vena Cava Syndrome of Malignant Cause. Fortschr Röntgenstr 2017; 189: 423 - 430.
EVALuna2:14658

Stereotactic vacuum-assisted breast biopsy (VABB)–a patients' survey - Eller, Achim; Janka, Rolf Matthias; Lux, Michael P.; Saake, Marc; Schulz-Wendtland, Rüdiger; Uder, Michael; Wenkel, Evelyn (Anticancer Research, 2014)
To analyze how patients experience Stereotactic guided vacuum-assisted breast biopsy (VABB) both physically and mentally.Two hundred and eleven consecutive women underwent VABB using one of two different biopsy devices (ATEC® and Mammotome®). Patients were queried using a questionnaire.One hundred and eighty-nine patients were included. 90% would again prefer VABB over a surgical biopsy. Average grading for the condition during the procedure was 2.5 (very good to good) and 2.1 (very good) for the condition the week following VABB. Minor complications were mentioned in 37%. (>90% pain and hematoma). 97% of the women were satisfied by the cosmetic results. Patients with malignant histology and younger age experienced the procedure significantly worse. A significant higher rate of minor complications was found in younger patients and in the ATEC® group.VABB is a physical and mental stressor to the women. Nonetheless, the majority of women indeed prefer the VABB.
EVALuna2:14365

Stress fractures - Current recommendations and principles for diagnosis and therapy Problemdiagnose Stressfraktur – Aktuelle Empfehlungen und Prinzipien zur Diagnostik und Therapie - Heiß, Rafael; Lutter, Christoph; Kastner, Tom; Janka, Rolf Matthias; Uder, Michael; Hotfiel, Thilo (Sport-Orthopädie, Sport-Traumatologie, 2022)
Stress fractures and stress reactions are among the injuries caused by overuse (“overuse injuries”) and can result in significant training and competition failures for affected athletes. Repetitive load effects that exceed the ability to cope with stress and adaptability, combined with intrinsic and extrinsic risk factors or tactical training errors, are considered to be the main cause of stress fractures. These and possible accompanying individual risk profiles are diverse and require complex and often interdisciplinary care. The majority of stress fractures heal easily and the recovery of full performance and resilience is usually given. However, if the diagnosis is delayed or inadequate (some injury entities require consistent decision-making regarding surgical therapy) or if secondary risk factors are not taken into account, prolonged healing processes, recurrent injuries or even multiple injury locations can occur at the same time. An early diagnosis and the beginning of a stage-appropriate therapy, including the consideration of existing risk factors, are therefore of essential importance.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Marching fracture; MRI; Running injury; Stress fracture; Stress reaction; X-ray

Structured Digital Self-Assessment of Patient Anamnesis Prior to Computed Tomography: Performance Evaluation and Added Value - Kopp, Markus; Wetzl, Matthias; Geißler, Frederik; Roth, Jessica; Wallner, R.; Hoefler, D.; Faby, S.; Allmendinger, T.; Amarteifio, P.; Wüst, Wolfgang; Uder, Michael; May, Matthias; et al. (Journal of Medical Systems, 2021)
The aim of this study was to evaluate the performance of a tablet-based, digitized structured self-assessment (DSSA) of patient anamnesis (PA) prior to computed tomography (CT). Of the 317 patients consecutively referred for CT, the majority (n = 294) was able to complete the tablet-based questionnaire, which consisted of 67 items covering social anamnesis, lifestyle factors (e.g., tobacco abuse), medical history (e.g., kidney diseases), current symptoms, and the usability of the system. Patients were able to mark unclear questions for a subsequent discussion with the radiologist. Critical issues for the CT examination were structured and automatically highlighted as “red flags” (RFs) in order to improve patient interaction. RFs and marked questions were highly prevalent (69.5% and 26%). Missing creatinine values (33.3%), kidney diseases (14.4%), thyroid diseases (10.6%), metformin (5.5%), claustrophobia (4.1%), allergic reactions to contrast agents (2.4%), and pathological TSH values (2.0%) were highlighted most frequently as RFs. Patient feedback regarding the comprehensibility of the questionnaire and the tablet usability was mainly positive (90.9%; 86.2%). With advanced age, however, patients provided more negative feedback for both (p = 0.007; p = 0.039). The time effort was less than 20 min for 85.1% of patients, and faster patients were significantly younger (p = 0.046). Overall, the DSSA of PA prior to CT shows a high success rate and is well accepted by most patients. RFs and marked questions were common and helped to focus patients’ interactions and reporting towards decisive aspects.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Computed tomography; Digital informed patient consent; Digital medical history; Mobile devices; Structured anamnesis

Systemic PPAR gamma Antagonism Reduces Metastatic Tumor Progression in Adipocyte-Rich Bone in Excess Weight Male Rodents - Gaculenko, Anastasia; Gregoric, Gasper; Popp, Vanessa; Seyler, Lisa; Ringer, Mark; Kachler, Katerina; Wu, Zhengquan; Kisel, Wadim; Hofbauer, Christine; Hofbauer, Lorenz C.; Uder, Michael; Schett, Georg; et al. (Journal of Bone and Mineral Research, 2021)
Primary tumors are widely associated with an excess in body fat. The role of adipose tissue on tumor cell homing to bone is yet poorly defined. In this study, we aimed to assess whether bone colonization by tumor cells is favored by an adipocyte-rich bone marrow. We delineated the accompanying alterations of the bone microenvironment and established a treatment approach that interferes with high fat diet (HFD)-induced bone metastasis formation. We were able to show that adipocytes affect skeletal tumor growth in a metastatic model of breast cancer in male rats and melanoma in male mice as well as in human breast cancer bone biopsies. Indeed, HFD-induced bone marrow adiposity was accompanied by accelerated tumor progression and increased osteolytic lesions. In human bone metastases, bone marrow adiposity correlated with tumor cell proliferation. By antagonization of the adipocyte differentiation and storage pathway linked to the peroxisome proliferator-activated receptor gamma (PPAR gamma) with bisphenol-A-diglycidylether (BADGE), we were able to decelerate tumor progression and subsequent osteolytic damage in the bones of two distinct metastatic animal models exposed to HFD. Overall these data show that adipose tissue is a critical factor in bone metastases and cancer-induced bone loss. 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team WoS Importer:2021-09-03

T-2* Accelerated quantification of tissue sodium concentration in skeletal muscle tissue: quantitative capability of dictionary learning compressed sensing - Utzschneider, Matthias; Behl, Nicolas G. R.; Lachner, Sebastian; Gast, Lena; Maier, Andreas; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Materials in Physics Biology and Medicine, 2020)
OBJECTIVE: To accelerate tissue sodium concentration (TSC) quantification of skeletal muscle using 23Na MRI and 3D dictionary-learning compressed sensing (3D-DLCS). MATERIALS AND METHODS: Simulations and in vivo 23Na MRI examinations of calf muscle were performed with a nominal spatial resolution of [Formula: see text]. Fully sampled and three undersampled 23Na MRI data sets (undersampling factors (USF) = 3, 4.4, 6.7) were evaluated. Ten healthy subjects were examined on a 3 Tesla MRI system. Results of the simulation study and the in vivo measurements were compared to the ground truth (GT) and the fully sampled fast Fourier transform (NUFFT) reconstruction, respectively. RESULTS: Reconstruction results of simulated data with optimized 3D-DLCS yielded a lower deviation (< 4%) from the GT than results of the NUFFT reconstruction (> 5%) and a lower standard deviation (SD). For in vivo measurements, a TSC of [Formula: see text] was observed. The mean deviation from the reference is lower for the undersampled 3D-DLCS reconstructions (3.4%) than for NUFFT reconstructions (4.6%). SD is reduced using 3D-DLCS. Compared to a fully sampled NUFFT reconstruction, acquisition time could be reduced by a factor of 4.4 while maintaining similar quantitative accuracy. DISCUSSION: The optimized 3D-DLCS reconstruction enables accelerated TSC measurements with high quantification accuracy.
CRIS-Team WoS Importer:2020-01-31

T2 Mapping as a New Method for Quantitative Assessment of Cartilage Damage in RA - Renner, Nina; Kleyer, Arnd; Krönke, Gerhard; Simon, David; Söllner, Stefan; Rech, Jürgen; Uder, Michael; Janka, Rolf Matthias; Schett, Georg; Welsch, Goetz; Pachowsky, Milena (Journal of Rheumatology, 2019)
OBJECTIVE: Rheumatoid arthritis (RA) is associated with damage of the articular cartilage and the periarticular bone. While imaging of bone damage has substantially improved in the last years, direct imaging of the articular cartilage of the hand joints in patients with RA is still challenging. METHODS: 3 Tesla Magnetic Resonance Imaging (MRI) was done in 30 RA patients and T2 relaxation times visualizing alteration in the collagen network and hydration of articular cartilage were mapped in six cartilage regions of the metacarpophalangeal joints 2 and 3. Values were related to autoantibody (anti-citrullinated peptide antibodies (ACPA), rheumatoid factor (RF)) status, disease duration, disease activity as well as sex and age of the RA patients. RESULTS: T2 relaxation times could be reliably measured in the six regions of the metacarpophalangeal joints. Significantly higher relaxation times indicating more advanced cartilage alterations were observed in ACPA-positive (p=0.001-0.010) and RF-positive patients (p=0.013-0.025) as well as those with longer disease duration (>3 years; p=0.028-0.043). Current disease activity, sex and age did not influence T2 relaxation times. CONCLUSION: These data show that cartilage damage can be localized and quantified in the hand joints of RA patients by T2 mapping. Furthermore, ACPA and RF positivity as well as disease duration appear to be the crucial factors influencing cartilage damage.
EVALuna2:210913

Targeting Muscular Hemoglobin Content for Classification of Peripheral Arterial Disease by Noninvasive Multispectral Optoacoustic Tomography - Günther, Josefine; Knieling, Ferdinand; Träger, Anna P.; Lang, Werner; Meyer, Alexander; Regensburger, Adrian; Wagner, Alexandra; Trollmann, Regina; Wölfle, Joachim; Klett, Daniel; Uter, Wolfgang; Uder, Michael; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Created from Fastlane, Scopus look-up

The effect of ageing on fat infiltration of thigh and paraspinal muscles in men - Engelke, Klaus; Ghasemikaram, Mansour; Chaudry, Oliver; Uder, Michael; Nagel, Armin Michael; Jakob, Franz; Kemmler, Wolfgang (Aging Clinical and Experimental Research, 2022)
Background Myosteatosis, skeletal muscle fat infiltration, is associated with inflammation and fibrosis. The age-related increase of myosteatosis is an important characteristic of sarcopenia and contributes to fragility. Aims To investigate the impact of healthy aging on intermuscular adipose tissue (IMAT) and muscle fat fraction (FF) in the thigh and the paraspinal muscles in males. Methods In 54 healthy males (age 20-70), all active hobby golfers, magnetic resonance imaging was performed to determine volume of IMAT, volume of muscle tissue (MT) and of percentage of FF. Results Between ages 20-70, at the thigh, IMAT/MT volume and MT FF increased annually by 2.9% and 1.3%, respectively. At the psoas IMAT/Psoas volume did not change with age. MT FF increased by 1.5% annually. At the erector spinae IMAT/Erector volume decreased by 0.3% and MT FF increased by 2.8% annually. Discussion With increasing age, in males, thigh muscle atrophied, muscle tissue was partly replaced by adipose tissue and remaining muscle tissue also contained more fat. Similar effects were observed in the erector spinae. The psoas muscle did not atrophy, although MT FF also increased with age. Overall correlations with age were weak to moderate with higher correlations observed in the paraspinal muscles. Conclusions Age-related increases of muscle fat infiltration were observed in the thigh and in the spine. Muscle atrophy did not occur in the psoas. In cross-sectional studies, an adjustment of volumetric parameters by muscle volume is advisable when comparing age-dependent results.
CRIS-Team WoS Importer:2022-06-10
Keywords: MRI; Thigh; Erector spinae; Psoas; IMAT; Muscle fat fraction

The effect of aquatic exercise on bone mineral density in older adults. A systematic review and meta-analysis - Schinzel, Eileen; Kast, Stephanie; Kohl, Matthias; von Stengel, Simon; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Peters, Stefan; Thomasius, Friederike; Clausen, Juergen; Uder, Michael; et al. (Frontiers in Physiology, 2023)
Introduction: Aquatic or water-based exercise is a very popular type of exercise in particular for people with physical limitations, joint problems and fear of falling. The present systematic review and meta-analysis aimed to provide evidence for the effect of aquatic exercise on Bone Mineral Density (BMD) in adults.Methods: A systematic literature search of five electronic databases (PubMed/MEDLINE, Cochrane Library, Scopus, Web of Science and CINAHL) according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was conducted until 2022/01/30, with an update to 2022/10/07. We included controlled trials with a duration of more than 6 months and at least two study groups, aquatic exercise (EG) versus non-training controls (CG) with no language restrictions. Outcome measures were standardized mean differences (SMD) with 95%-confidence intervals (95%-CI) for BMD changes at the lumbar spine (LS) and femoral neck (FN). We applied a random-effects meta-analysis and used the inverse heterogeneity (IVhet) model to analyze the data.Results: Excluding an outlier study with an exceptionally high effect size for LS-BMD, we observed a statistically significant (p = .002) effect (EG vs. CG) of aquatic exercise for the LS-BMD (n = 10; SMD: 0.30; 95%-CI: 0.11-0.49). In parallel, the effect of aquatic exercise on FN-BMD was statistically significant (p = .034) compared to the CG (n = 10; SMD: 0.76, 95%-CI: 0.06-1.46). Of importance, heterogeneity between the trial results was negligible for LS (I-2: 7%) but substantial for FN-BMD (I-2: 87%). Evidence for risks of small study/publication bias was low for LS-BMD and considerable for FN-BMD.Discussion: In summary, the present systematic review and meta-analysis provides further evidence for the favorable effect of exercise on bone health in adults. Due to its safety and attractiveness, we particularly recommend water-based exercise for people unable, afraid or unmotivated to conduct intense land-based exercise programs.
CRIS-Team WoS Importer:2023-04-21

The effect of calyculin A on the dephosphorylation of the histone γ-H2AX after formation of X-ray-induced DNA double-strand breaks in human blood lymphocytes - Kuefner, Michael A.; Brand, Michael; Engert, Christina; Kappey, Hanna; Uder, Michael; Distel, Luitpold (International Journal of Radiation Biology, 2013)
Purpose: The purpose of this study was to investigate the effect of calyculin A on the number of γ-H2AX foci (phosphorylated histone variant 2AX) in lymphocytes after in vitro and in vivo irradiation with rather low doses as they are used in diagnostic and interventional radiology. Materials and methods: For in vitro experiments blood samples of 14 healthy volunteers were irradiated with different doses (10, 50, 100 mGy) and incubated with (0.01, 0.1, 1, 10 nM) or without calyculin A for up to 2 hours. Non-irradiated samples with and without calyculin A served as controls. For in vivo evaluation blood samples were collected from seven patients undergoing computed tomography (CT) both with 1 nM calyculin A containing vials and vials without calyculin A. Foci were quantified in isolated lymphocytes using γ-H2AX immunofluorescence microscopy. Results: 1 nM calyculin A led to a complete inhibition of γ-H2AX foci loss in irradiated samples whereas no inhibition of p53 binding protein 1 (53 BP1) foci was found. Lower concentrations of the phosphatase inhibitor did not have a sufficient effect on foci decrease. Calyculin A did not affect foci levels in non-irradiated samples. If no calyculin A was added into the vial before the blood draws detectable CT-induced foci levels were lower in all patients with a reduction of the medians of 35%. Conclusions: Using γ-H2AX immunofluorescence microscopy calyculin A can be a useful tool to mark the induced γ-H2AX foci after low dose irradiation and to avoid an underestimation of the real deoxyribonucleic acid (DNA) damage in in vitro and in vivo experiments. © 2013 Informa UK, Ltd.
CRIS-Team Scopus Importer:2023-03-08
Keywords: γ-H2AX; Calyculin A; DNA double-strand break repair

The effect of different training frequency on bone mineral density in older adults. A comparative systematic review and meta-analysis - Zitzmann, Anna Lena; Shojaa, Mahdieh; Kast, Stephanie; Kohl, Matthias; von Stengel, Simon; Borucki, Diana; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Middeldorf, Stefan; et al. (Bone, 2022)
Exercise frequency is a key aspect of exercise protocols. In this systematic review and meta-analysis, we determined the effect of training frequency on (areal) bone mineral density (BMD) at lumbar spine (LS) and hip. Reviewing seven electronic databases up to April 2021, we conducted a systematic review of the literature according to the PRISMA statement. Inclusion criteria were (a) controlled exercise trials (b) with at least two study arms that compared low versus high exercise frequency, (c) an intervention ≥6 months and (d) BMD assessments at lumbar spine (LS) or hip. The analysis was conducted as a mixed-effect meta-analysis and used “type of exercise” and “study duration” as moderators in subgroup analyses. Standardized mean differences (SMD) for LS- and hip-BMD changes were defined as outcome measures. Seven studies with 17 exercise groups were included in the analysis. We observed significantly higher effects of high (≥2 sessions/week) vs. low net training frequency (1–<2 sessions/week) exercise on LS- (SMD 0.55, 95%-CI: 0.20–0.90) but not hip-BMD (0.19, −0.06 to 0.45). Study duration was found to be a significant moderator for the effect of training frequency at LS- but not hip-BMD. In parallel, the type of exercise moderately influences the effect of training frequency on LS- but not on hip-BMD. We observed a superior effect of higher net training frequency on BMD. Longer exercise exposition increases this effect. Considering e.g. holidays, indisposition or other temporary absence, exercise programs on osteoporosis should provide at least 3 sessions/week/year to allow a net training frequency of more than two sessions/week. Study registration: PROSPERO (CRD42021246804).
CRIS-Team Scopus Importer:2021-10-22
Keywords: Bone mineral density; Exercise; Guideline; Training frequency

The effect of renal denervation in moderate treatment-resistant hypertension with confirmed medication adherence - Ott, Christian; Mahfoud, Felix; Schmid, Andrea; Ewen, Sebastian; Toennes, Stefan W.; Meyer, Markus R.; Helfer, Andreas G.; Maurer, Hans H.; Ditting, Tilmann; Veelken, Roland; Zivanovic, Ina; Uder, Michael; et al. (Journal of Hypertension, 2016)
Data on the blood pressure (BP)-lowering effect of renal denervation (RDN) in moderate treatment-resistant hypertension (TRH) are limited. Moreover, change of adherence to medication, as one potential confounder of BP response, has never been analyzed rigorously in this group of patients. We analyzed the effect of RDN on BP in patients with moderate TRH who were retrospectively found to be completely adherent to their antihypertensive medication.Our study cohort comprised 40 patients with moderate TRH [office BP >= 140/90 but <160/100 mmHg and 24-h ambulatory BP monitoring (ABPM) >=130/80 mmHg] who underwent catheter-based RDN. Further major inclusion criterion was complete adherence to their medication (>=80% intake of their prescribed antihypertensive drugs) at baseline (assessed by retrospective toxicological analysis).Six months after RDN, office BP was reduced by -10/-6 mmHg (SBP: 149 ± 6 vs. 139 ± 15 mmHg; DBP: 81 ± 12 vs. 75 ± 10 mmHg; both P < 0.001) and 24-h ABPM by -7/-4 mmHg (SBP: 150 ± 14 vs. 143 ± 16 mmHg, P = 0.005; DBP: 82 ± 10 vs. 78 ± 9 mmHg, P = 0.009). Number of prescribed antihypertensive medication [6.0 (5.0-6.0) vs. 5.5 (5.0-6.0), P = 0.013] and adherence rate (95.2 ± 7.6 vs. 91.7 ± 13.9%, P = 0.065) was slightly reduced 6 months after RDN, both likely to underestimate the true BP reduction.Thus, our data indicate that even after given full respect to drug adherence as potential confounder of BP response after RDN, both office and 24-h ABPM were substantially reduced in patients with moderate TRH.
EVALuna2:3907

The potential of predictive and prognostic breast MRI (P2-bMRI) - Dietzel, Matthias; Trimboli, Rubina Manuela; Zanardo, Moreno; Schultz-Wendtland, Rudiger; Uder, Michael; Clauser, Paola; Sardanelli, Francesco; Baltzer, Pascal A. T. (European Radiology Experimental, 2022)
Magnetic resonance imaging (MRI) is an important part of breast cancer diagnosis and multimodal workup. It provides unsurpassed soft tissue contrast to analyse the underlying pathophysiology, and it is adopted for a variety of clinical indications. Predictive and prognostic breast MRI (P2-bMRI) is an emerging application next to these indications. The general objective of P2-bMRI is to provide predictive and/or prognostic biomarkers in order to support personalisation of breast cancer treatment. We believe P2-bMRI has a great clinical potential, thanks to the in vivo examination of the whole tumour and of the surrounding tissue, establishing a link between pathophysiology and response to therapy (prediction) as well as patient outcome (prognostication). The tools used for P2-bMRI cover a wide spectrum: standard and advanced multiparametric pulse sequences; structured reporting criteria (for instance BI-RADS descriptors); artificial intelligence methods, including machine learning (with emphasis on radiomics data analysis); and deep learning that have shown compelling potential for this purpose. P2-bMRI reuses the imaging data of examinations performed in the current practice. Accordingly, P2-bMRI could optimise clinical workflow, enabling cost savings and ultimately improving personalisation of treatment. This review introduces the concept of P2-bMRI, focusing on the clinical application of P2-bMRI by using semantic criteria.
CRIS-Team WoS Importer:2022-09-02

THE SGLT2 INHIBITOR EMPAGLIFLOZIN REDUCES TISSUE SODIUM CONTENT IN PATIENTS WITH CHRONIC HEART FAILURE - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Uder, Michael; Achenbach, Stephan; Schmieder, Roland (JOURNAL OF THE AMERICAN COLLEGE OF CARDIOLOGY, 2021)
CRIS-Team WoS Importer:2021-06-04

The SGLT2 inhibitor empagliflozin reduces tissue sodium content in patients with chronic heart failure: results from a placebo-controlled randomised trial - Kolwelter, Julie; Kannenkeril, Dennis; Linz, Peter; Jung, Susanne; Nagel, Armin Michael; Bosch, Agnes; Ott, Christian; Bramlage, Peter; Nöh, Lisa; Schiffer, Mario; Uder, Michael; Achenbach, Stephan; et al. (Clinical Research in Cardiology, 2022)
Introduction: Sodium-glucose co-transporter 2 (SGLT2) inhibitors have cardiovascular protective properties in addition to the metabolic effects and represent a cornerstone of treating patients with chronic heart failure (CHF). We hypothesised that empagliflozin reduces tissue sodium content in patients with CHF. Methods: In a double-blind, randomised (2:1), placebo-controlled, parallel-group, clinical trial, 74 patients with NYHA class II–III CHF and an ejection fraction of 49% or less received empagliflozin 10 mg once daily or placebo for 3 months. In each patient, tissue sodium content of the lower leg was assessed non-invasively by sodium-MRI (23Na-MRI) at baseline, after 1 and 3 months of treatment. Results: After 1 and 3 months treatment with empagliflozin (n = 48), a significant decrease in skin sodium content was observed (1 month: 22.8 ± 6.1 vs. 21.6 ± 6.0 AU, p = 0.039; 3 months: 22.9 ± 6.1 vs. 21.6 ± 6.1 AU, p = 0.013), while there was no change in muscle sodium and muscle water content. In direct comparison, the change in skin sodium content between baseline and 3 months was − 1.3 ± 3.5 AU in the empagliflozin group versus 0.6 ± 3.5 AU in the placebo group (p for between-group difference = 0.022). No significant difference regarding change in muscle sodium and in muscle water content was observed after 3 months treatment between the two groups. Conclusion: This trial showed a significant decrease in skin sodium content after 1 and 3 months of treatment with empagliflozin. The decrease in skin sodium content may reflect a decrease in subclinical micro-oedema or/and in non-osmotic bound tissue sodium, both reported to impair left ventricular function. Trial registration number: NCT03128528 (http://www.clinicaltrials.gov). Trial registration date: 25th April 2017.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Chronic heart failure; Empagliflozin; Magnetic resonance imaging; SGLT2 inhibitor; Sodium; Tissue sodium content

The structural basis of MRI bone erosions: An assessment by microCT - Albrecht, Andreas; Finzel, Stephanie; Englbrecht, Matthias; Rech, Jürgen; Hueber, Axel; Schlechtweg, Philipp; Uder, Michael; Schett, Georg (Annals of the Rheumatic Diseases, 2013)
Objective To determine whether erosions appearing in MRI in patients with rheumatoid arthritis (RA) represent true erosions. Methods 50 RA patients received 1.5 T MRI and microCT (μCT) of the dominant hand. Erosion counts were assessed in coronal T1 weighted MRI sections and in coronal as well as axial μCT sections of the metacarpophalangeal (MCP) joints II-IV. Extent of erosions was assessed by RA MRI Score (RAMRIS) erosion score (MRI) and by three-dimensional assessment of erosion volume (μCT). Results 111 of the 600 evaluated joint regions showed erosions in the MRI and 137 in the μCT. In only 28 regions false negative lesions (μCT positive, MRI negative) were found, all of which were very small lesions with a volume of less than 10 mm3. Only two results were false-positive (μCT negative, MRI positive). RAMRIS erosion scores were strongly correlated to erosion volumes in the μCT (Pearson's r=0.514, p<0.001). Mean RAMRIS erosion scores were below 1 with erosion volumes up to 1.5 mm3, below 2 with erosion volumes up to 20 mm3 and over 2 with volumes of more than 20 mm3. Discussion MRI erosions are generally based on true cortical breaks as shown by μCT. MRI is sensitive to detect bone erosions and only very small lesions escape detection. Moreover, RAMRIS erosion scores are closely linked to the absolute size of bone erosions in the μCT.
CRIS-Team Scopus Importer:2021-02-03

The value of “constant sharpness” as a diagnostic sign in MR-Mammography - Kaiser, Clemens G.; Baltzer, Pascal; Kaiser, Anna K.; Krammer, Julia; Uder, Michael; Kaiser, Werner A.; Dietzel, Matthias (European Journal of Radiology Open, 2016)
Purpose To examine “constant lesion sharpness” as a morphological diagnostic sign in the differential diagnosis between benign and malignant lesions. Material and methods This prospective study had institutional review board approval and was HIPAA compliant. In total 1014 consecutive patients were examined (mean age 55 years ± 13 years) and evaluated in our University hospital towards the morphological shape of the lesion borders. The “Constant sharpness Sign” was defined as a lesion remaining continuously sharp for the duration of the dynamic scan. Inclusion criteria were unclear findings (e.g. BIRADS III/IV), Preoperative staging (BRIDAS IV/V), and referred patients from local clinic of gynecology. Exclusion criteria were MRM-examination ≤1 year before, status after surgery and/or biopsy, chemotherapy and/or radiation therapy. Reference Standard was histological verification. Images were diagnosed by two experienced radiologists in consensus, blinded to the standard of reference. Results 1014 patients with 1084 lesions (436 benign, 648 malignant lesions) were included into the study. 41.5% of benign lesions and 6.8% (181/436) of malignant lesions displayed a constant sharpness as an accompanying morphological sign (P < 0.001). This resulted in a sensitivity of 41.5%, specificity of 93.2%, a positive likelihood ratio of 6.1%, a negative likelihood ratio of 0.63 and an odd's ratio of 9,7%. Summary and conclusion The constant sharpness sign seems to be an accurate predictor of benign breast lesions, which may help to increase the accuracy of MRM as a morphological sign.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Breast-MR; Constant sharpness; Morphology; MR-Mammography

Third-generation dual-source 70-kVp chest CT angiography with advanced iterative reconstruction in young children: image quality and radiation dose reduction - Rompel, Oliver; Glöckler, Martin; Janka, Rolf Matthias; Dittrich, Sven; Cesnjevar, Robert; Lell, Michael; Uder, Michael; Hammon, Matthias (Pediatric Radiology, 2016)
Many technical updates have been made in multi-detector CT.To evaluate image quality and radiation dose of high-pitch second- and third-generation dual-source chest CT angiography and to assess the effects of different levels of advanced modeled iterative reconstruction (ADMIRE) in newborns and children.Chest CT angiography (70 kVp) was performed in 42 children (age 158 ± 267 days, range 1-1,194 days). We evaluated subjective and objective image quality, and radiation dose with filtered back projection (FBP) and different strength levels of ADMIRE. For comparison were 42 matched controls examined with a second-generation 128-slice dual-source CT-scanner (80 kVp).ADMIRE demonstrated improved objective and subjective image quality (P < .01). Mean signal/noise, contrast/noise and subjective image quality were 11.9, 10.0 and 1.9, respectively, for the 80 kVp mode and 11.2, 10.0 and 1.9 for the 70 kVp mode. With ADMIRE, the corresponding values for the 70 kVp mode were 13.7, 12.1 and 1.4 at strength level 2 and 17.6, 15.6 and 1.2 at strength level 4. Mean CTDIvol, DLP and effective dose were significantly lower with the 70-kVp mode (0.31 mGy, 5.33 mGy*cm, 0.36 mSv) compared to the 80-kVp mode (0.46 mGy, 9.17 mGy*cm, 0.62 mSv; P < .01).The third-generation dual-source CT at 70 kVp provided good objective and subjective image quality at lower radiation exposure. ADMIRE improved objective and subjective image quality.
EVALuna2:14476

Thoracic non-osseous lesions in cancer patients detected in low-dose CT images acquired as part of skeletal SPECT/CT examinations - Wüst, Wolfgang; Lell, Michael; May, Matthias; Saake, Marc; Kuwert, Torsten; Uder, Michael; Linke, Rainer (Nuklearmedizin-Nuclear Medicine, 2015)
Hybrid single-photon emission tomographic (SPECT) and X-ray computed tomography (CT) systems are increasingly used in oncologic imaging. With SPECT/CT not only the thoracic spine but also the surrounding soft tissue needs to be evaluated for pathological findings. The purpose of this study was to assess the prevalence of non-osseous findings detectable on low-dose CT datasets from patients studied by thoracic 99mTc-dicarboxypropane diphosphonate (DPD)-SPECT/CT.119 consecutive oncologic patients (81 breast cancer, 38 with other cancer) who underwent DPD-SPECT CT of the thoracic region were included in this study. Non-osseous findings on CT were classified as either probably benign or suspicious. Suspicious findings were correlated with retrievable previous imaging and if performed with follow up imaging (MRI, CT with contrast medium, Ultrasound) or biopsy results.In 80/119 (67%) patients no imaging was performed before SPECT/CT. Only 7/119 subjects (6%) had no other lesions than bone lesions. In 101/119 (85%) patients lesions found on SPECT/CT images were rated as benign and in 65/119 (55%) patients as suspicious. In 8/119 (7%) patients with previously unknown suspicious lesions on SPECT/CT images suspicious findings were confirmed by biopsy.7% of patients referred to SPECT/CT of the thoracic spine for staging of malignant disease had previously unknown suspicious non-osseous lesions detectable on the low-dose CT images which were confirmed by biopsy. This could be especially relevant for cancer entities like breast and prostate, in which no thorax-CT is routinely intended for staging.
EVALuna2:13854

Three-dimensional mapping of the arteriovenous loop model using two-dimensional histological methods - Seuß, Hannes; Arkudas, Andreas; Hammon, Matthias; Bleiziffer, Oliver; Uder, Michael; Horch, Raymund E.; Yuan, Quan (Microscopy Research and Technique, 2016)
The aim of this study was to create an analytical tool for the three-dimensional distribution of immunohistochemically stained cells in the arteriovenous (AV) loop model of the femoral vessels of rats that fuses two-dimensional histological slides into stacks.A total of 22 AV loops were implanted into male syngeneic Lewis rats by creating an arteriovenous fistula between the femoral artery and vein by interposing a femoral vein graft of the contralateral extremity. This fistula was embedded into an isolation chamber filled with a fibrin matrix. Specimens were explanted after 7 to 14 days, and the AV loop was processed using standard histological protocols. Immunohistochemical staining for HIF-1? and a counter staining with hematoxylin was performed. Various layouts with different cutting planes, regions of interest, and post-processing algorithms were evaluated. Results and observations: The proximal-to-distal cutting perpendicular to the vascular axis proved to be the best layout for mapping the three-dimensional constructs containing the AV loop. A semi-automatic algorithm for the differentiation of immunohistochemical positive and negative cells was developed.The newly established methods from this study constitute an excellent tool for the general evaluation of the AV loop model - particularly with regard to the three-dimensional distribution of immunohistochemical positive and negative cells.
EVALuna2:14606

Time-extended local rtPA infiltration for acutely thrombosed hemodialysis fistulas - Regus, Susanne; Lang, Werner; Heinz, Marco; Rother, Ulrich; Meyer, Alexander; Almási-Sperling, Veronika; Uder, Michael; Schmid, Axel (Hemodialysis International, 2018)
This study describes results of a modified local thrombolysis technique for acutely thrombosed hemodialysis (HD) arteriovenous fistulas (AVF), which is characterized by prolonged recombinant tissue plasminogen activator (rtPA) local exposure times. Contrary to the standard lyse- and- wait (L&W) technique with local reaction times of 20-40 minutes, the modified protocol allows timing of challenging angioplasty maneuvers to the next regular working day.From February 2009 to April 2014, 84 patients on HD presented with 152 acutely thrombosed AVF. They proceeded to local thrombolysis including a single shot infiltration of rtPA, local reaction time up to 40 hours and finally percutaneous stenosis angioplasty. Success rates, major adverse events and need for temporary catheter placements (TCP) were retrospectively analyzed.The local thrombolysis time after single shot infiltration was 18.6 ± 6.2 (range 2-40) hours. Mean rtPA- dosage was 2.7 mg ± 1.2. The overall success rate was 89.5% and the major complication rate was 3.3%, whereas TCP was necessary in 12.5%. The PP/SP at 1, 3, 6, 12, 18, and 24 month were 86% ± 3%/95% ± 2%, 68% ± 4%/92% ± 2%, 43% ± 4%/90% ± 2%, 28% ± 4%/82% ± 3%, 12% ± 3%/82% ± 3%, 7% ± 2%/63% ± 4%, respectively.The modified L&W technique with prolonged local rtPA reaction times is a safe and effective declotting procedure. The need for TCP was not increased and therefore comparable to the standard technique.
EVALuna2:15322

Time-of-Flight Angiography in Ultra-High-Field 7 T MRI for the Evaluation of Peroneal Perforator Arteries Before Osseomyocutaneous Flap Surgery - Wiesmüller, Marco; Meixner, Christian; Weber, Manuel; Kesting, Marco Rainer; Nagel, Armin M.; Wüst, Wolfgang; May, Matthias; Roemer, Frank W.; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: Presurgical identification and morphologic characterization of the peroneal perforator arteries (PPAs) are essential for osseomyocutaneous flap surgery. The aim of this study was to evaluate PPAs using time-of-flight (TOF) angiography in 7 T magnetic resonance imaging in comparison with dual-energy computed tomographic angiography (CTA). MATERIALS AND METHODS: In this prospective study, TOF angiography and CTA of both lower legs were acquired before flap surgery from 07/2019 to 02/2020. Magnetic resonance imaging was performed using a dedicated 28-channel knee coil with an acquisition time of 9:55 minutes (voxel size: 0.4 × 0.4 × 0.8 mm). Computed tomographic angiography was acquired with a third-generation dual-source computed tomography on the same day. Virtual monoenergetic reconstructions at 40 keV photon energy served as the standard of reference for PPA identification and subtyping. Two independent readers assessed the image quality, quantity, length assessment, and classification according to surgical considerations of PPAs for TOF angiography and CTA. Both TOF angiography and CTA were used for presurgical flap design and were evaluated by an orofacial surgeon. RESULTS: Ten patients (mean age, 59.9 ± 14.9 years; 7 men) were included. Time-of-flight angiography and CTA identified 53 and 51 PPAs in total, respectively. Time-of-flight angiography showed superior image quality (both readers, P < 0.05). Time-of-flight angiography enabled specific classification of PPA subtypes more often (53 vs 39; P < 0.05), and both readers reported higher diagnostic confidence for TOF angiography than CTA in all patients (interrater agreement κ = 0.8; P < 0.05). Regarding length assessment, PPAs were significantly more conspicuous with TOF angiography (TOF mean , 50 ± 11 mm; CTA mean , 40 ± 9 mm; P = 0.001). In comparison with CTA, TOF angiography prospectively changed the orofacial surgeon's final decision on the presurgical selected PPAs in 60% of cases. CONCLUSIONS: Presurgical assessment of PPAs is feasible using TOF in 7 T magnetic resonance imaging. Moreover, TOF angiography was superior to CTA for classifying and identifying PPAs, which may facilitate the planning of reconstructive surgery.
CRIS-Team Scopus Importer:2023-02-24

Tissue sodium concentration correlates with hypertrophic vascular remodelling in type 2 diabetes - Kannenkeril, D.; Jung, Susan; Harazny, Jeremy; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (DIABETOLOGIA, 2019)
CRIS-Team WoS Importer:2019-10-11

Tissue sodium concentration emerged as a determinant of hypertrophic vascular remodeling in type 2 diabetes - Schmieder, Roland; Jung, Susanne; Kannenkeril, D.; Harazny, J. M.; Striepe, Kristina; Ott, Christian; Linz, Peter; Nagel, Angela; Uder, Michael (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Tissue sodium content correlates with hypertrophic vascular remodeling in type 2 diabetes - Kannenkeril, Dennis; Jung, Susanne; Harazny, Joanna; Striepe, Kristina; Ott, Christian; Dahlmann, Anke; Kopp, Christoph; Schiffer, Mario; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2021)
Background: Prospective studies describe a linkage between increased sodium intake and higher incidence of cardiovascular organ damage and end points. We analyzed whether tissue sodium content in the skin and muscles correlate with vascular hypertrophic remodeling, a risk factor for cardiovascular disease.
CRIS-Team WoS Importer:2021-12-03

Tissue sodium content in hypertension and related organ damage - Kolwelter, Julie; Uder, Michael; Schmieder, Roland (Journal of Hypertension, 2020)
Most textbooks state that sodium (Na) accumulation goes hand in hand with fluid retention to maintain the environmental isotonicity. In the last century, several studies found, however, that Na is stored in the extravascular space leading to an activation of the monocyte phagocytic system cells that work as a regulator of the interstitial electrolyte homeostasis. Na-23-MRI was developed to quantify noninvasively, accurately and reliably tissue Na content. In this review, we give an up-to-date overview of clinical studies utilizing this Na-23-MRI technique to elucidate the importance of tissue Na content in patients with cardiovascular risk factors leading to microvascular and macrovascular complications. Na storage leads ultimately to organ damage such as left ventricular hypertrophy or hypertrophic vascular remodeling of resistance vessels. Elevated Na content in muscle and skin has been detected in patients with treatment resistant hypertension, type 2 diabetes mellitus, acute and chronic heart failure, chronic kidney disease and end-stage renal failure. Pharmacological interventions have shown that a mobilization of extracellular accumulated Na is possible and may emerge as a new therapeutic approach in some diseases.
CRIS-Team WoS Importer:2021-01-01

Tissue sodium content in patients with type 2 diabetes mellitus - Kannenkeril, Dennis; Karg, Marina V.; Bosch, Agnes; Ott, Christian; Linz, Peter; Nagel, Armin Michael; Uder, Michael; Schmieder, Roland (Journal of Diabetes and Its Complications, 2019)
Background: Tissue sodium content by 23 Na magnetic resonance imaging (MRI)has been found to be increased in arterial hypertension. We analyzed whether tissue sodium content is increased in patients with type-2 diabetes (T2DM). Methods: Patients with T2DM were compared to those with primary hypertension. Patients with T2DM were off any antidiabetic and hypertensive patients off any antihypertensive therapy for at least 4 weeks. Skin and muscle sodium content was assessed non-invasively with a 3.0 T clinical MRI system (Magnetom Verio, Siemens Health Care, Erlangen, Germany)in each patient. Results: In patients with T2DM (N = 59)we observed significantly greater muscle sodium content (diabetes: 20.6 ± 3.5 vs hypertension: 16.3 ± 2.5 mmol/l, p < 0.001)and skin sodium content (diabetes: 24.5 ± 7.2 vs hypertension: 20.6 ± 5.7 mmol/l, p = 0.01)than in those with primary hypertension (N = 33). When potential confounders (age, body mass index, gender, systolic and diastolic blood pressure, estimated glomerular filtration rate)were entered in a covariance analysis, both skin sodium content (p = 0.037)and muscle sodium content (p < 0.001)were still clearly elevated. Conclusion: Patients with T2DM have greater skin and muscle sodium content. These are the first known data to demonstrate increased tissue sodium content in patients with T2DM, measured by 23 Na magnetic resonance imaging. Since tissue sodium content is related to organ damage, therapeutic intervention should aim at reducing tissue sodium content.
CRIS-Team Scopus Importer:2019-05-21
Keywords: 23Na-MRI; T2DM; Tissue sodium content; Salt; Sodium retention

Tolvaptan treatment in an adult Fontan patient with protein-losing enteropathy: a serial 23Na-MRI investigation - Moosmann, Julia; Toka, Okan; Linz, Peter; Dahlmann, Anke; Nagel, Armin M.; Schiffer, Mario; Uder, Michael; Cesnjevar, Robert; Dittrich, Sven; Kopp, Christoph (Therapeutic Advances in Chronic Disease, 2021)
Background: Protein-losing enteropathy (PLE) is a severe complication of the univentricular Fontan circulation and associated with disturbances in salt and water homeostasis. Fontan patients with PLE have a poor prognosis, with increased morbidity and mortality. Due to limited therapeutic strategies, patients are often treated only symptomatically. Methods: We report our first experience of Tolvaptan (TLV) treatment in a Fontan patient with PLE, severe volume retention and hyponatraemia, refractory to conventional diuretic therapy. In addition to clinical parameters, we monitored drug effects including tissue sodium and volume status via serial 23Na-magnetic resonance imaging (23Na-MRI) and bioimpedance spectroscopy compared with age-matched controls. Results: 23Na-MRI identified elevated tissue sodium, which decreased under TLV treatment, as well as volume status, while serum sodium increased and the patient’s symptoms improved. During long-term treatment, we were able to differentiate between sodium and volume status in our patient, suggesting that TLV uncoupled body sodium from water. Conclusion: TLV in addition to loop diuretics improved clinical symptoms of PLE and lowered tissue sodium overload. Long-term effects should be further evaluated in Fontan patients.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Congenital heart disease; Fontan; RAAS; Tolvaptan

Tomosynthese - Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Fasching, Peter; Uder, Michael (Chirurgische Praxis, 2016)
Full field digital mammography (FFDM) is the most important method for early diagnosis of breast cancer. The typical overlapping of normal and pathological tissue during the standard 2D projection, however, often reduces the specificity and sensitivity of the mammographic investigation. Digital breast tomosynthesis (DBT) provides on the basis of a limited number of single images with different projection angles not superimposed tomograms and may remove the unwanted masking by superimposed structures. Clinical studies show that the digital tomosynthesis has the real potential to reduce the recall rate and simultaneously increase the cancer detection rate, especially in women with dense breasts (detection and volumetry). The use of tomosynthesis seems to be superior to full field digital mammography in mammography screening. Other possibilities of the tomosynthesis are the dual energy mammography, contrast medium-enhanced mammography and intervention.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contrast medium-enhanced mammography; Dual energy mammography; Full-field digital mammography; Intervention; Mammography screening; Tomosynthesis

Touch Imprint Cytology and Stereotactically-Guided Core Needle Biopsy of Suspicious Breast Lesions: 15-Year Follow-up - Schulz-Wendtland, Rüdiger; Fasching, Peter; Bani, Mayada; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C.; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Uder, Michael; Löhberg, Christian (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Stereotactically-guided core needle biopsies (CNB) of breast tumours allow histological examination of the tumour without surgery. Touch imprint cytology (TIC) of CNB promises to be useful in providing same-day diagnosis for counselling purposes and for planning future surgery. Having addressed the issue of accuracy of immediate microscopic evaluation of TIC, we wanted to re-examine the usefulness of this procedure in light of the present health care climate of cost containment by incorporating the surgical 15-year follow-up data and outcome. Patients and Methods: From January until December 1996 we performed TIC in core needle biopsies of 173 breast tumours in 169 patients, consisting of 122 malignant and 51 benign tumours. Histology of core needle biopsies was proven by surgical histology in all malignant and in 5 benign tumours. Surgical breast biopsy was not performed in 46 patients with 46 benign lesions, as the histological result from the core needle biopsy and the result of the TIC were in agreement with the suspected diagnosis from the complementary breast diagnostics. A 15-year follow-up of these patients followed in 2013 and follow-up data was collected from 40 women. Results: In the 15-year follow-up of the 40 benign lesions primarily confirmed using CNB and TIC, a diagnostic sensitivity, specificity, positive and negative predictive value and accuracy of 100 % was found. Conclusion: TIC and stereotactically guided CNB showed excellent long-term follow-up in patients with benign breast lesions. The use of TIC to complement CNB can therefore provide immediate cytological diagnosis of breast lesions.
EVALuna2:6752

Towards accelerated quantitative sodium MRI at 7 T in the skeletal muscle: Comparison of anisotropic acquisition- and compressed sensing techniques - Utzschneider, Matthias; Müller, Max; Gast, Lena; Lachner, Sebastian; Behl, Nicolas G.R.; Maier, Andreas; Uder, Michael; Nagel, Armin Michael (Magnetic Resonance Imaging, 2021)
Purpose: To compare three anisotropic acquisition schemes and three compressed sensing (CS) approaches for accelerated tissue sodium concentration (TSC) quantification using 23Na MRI at 7 T. Materials and methods: Three anisotropic 3D-radial acquisition sequences were evaluated using simulations, phantom- and in vivo TSC measurements: An anisotropic density-adapted 3D-radial sequence (3DPR-C), a 3D acquisition-weighted density-adapted stack-of-stars sampling scheme (SOS) and a SOS approach with golden-ratio rotation (SOS-GR). Eight healthy volunteers were examined at a 7 Tesla MRI system. TSC measurements of the calf were conducted with a nominal spatial resolution of Δx = (3.0 × 3.0 × 15.0) mm3 and a field of view of (156.0 × 156.0 × 240.0) mm3 for multiple undersampling factors (USF). Three CS reconstructions were evaluated: Total variation CS (TV-CS), 3D dictionary-learning compressed sensing (3D-DLCS) and TV-CS with a block matching prior (TV-BL-CS). Results of the simulations and measurements were compared to a simulated ground truth (GT) or a fully sampled reference measurement (FS), respectively. The deviation of the mean TSC evaluated in multiple ROI (mEGT/FS) and the normalized root-mean-squared error (NRMSE) for simulations were evaluated for CS and NUFFT reconstructions. Results: In simulations, the SOS-GR yielded the lowest NRMSE and mEGT (< 4%) with NUFFT for an acquisition time (TA) of less than 2 min. CS further improved the results. In simulations and measurements, the best TSC quantification results were obtained with 3D-DLCS and SOS-GR (lowest NRMSE, mEGT < 2.6% in simulations, mEGT < 10.7% for phantom measurements and mEFS < 6% in vivo) with an USF = 4.1 (TA < 2 min). TV-CS showed no or only slight improvements to NUFFT. The results of TV-BL-CS were similar to 3D-DLCS. Discussion: The TA for TSC measurements could be reduced to less than 2 min by using adapted sequences such as SOS-GR and CS reconstruction approaches such as 3D-DLCS or TV-BL-CS, while the quantitative accuracy stays comparable to a fully sampled NUFFT reconstruction (approx. 8 min TA). In future, the lower TA could improve clinical applicability of TSC measurements.
CRIS-Team Scopus Importer:2020-11-06
Keywords: 7 tesla; Anisotropic acquisition schemes; Compressed sensing; Image reconstruction; Skeletal muscle; Sodium (

TRABECULAR SUBCHONDRAL BONE ANALYSIS OF THE DISTAL RADIUS AT ULTRA-HIGH FIELD (7T) MRI: COMPARISON WITH 3T MRI AND RADIOGRAPHY - Jarraya, M.; Heiß, Rafael; Duryea, J.; Nagel, Armin Michael; Lynch, J. A.; Guermazi, A.; Weber, M. -A.; Arkudas, Andreas; Horch, Raymund E.; Uder, Michael; Roemer, Frank (OSTEOARTHRITIS AND CARTILAGE, 2021)
CRIS-Team WoS Importer:2021-05-21

Transcatheter Intervention of Bilateral Renal Artery Stenosis in an Infant after arterial Switch to Control Arterial Hypertension - Wiewrodt, B.; Dittrich, Sven; Uder, Michael; Wirbelauer, J. (Klinische Pädiatrie, 2016)
EVALuna2:14584

Transhepatic forceps biopsy after PTCD for histological assessment of bile duct stenoses or occlusions - Warnken, Eva-Marie; Uder, Michael; Stein, Hubert; Wucherer, Michael; Lell, Michael; Muschweck, Herbert; Adamus, Ralf (Zeitschrift für Gastroenterologie, 2019)
Purpose The goal of this study was to evaluate the experience of 11 years of wire-guided forceps biopsy via PTCD in patients with obstructive jaundice.
CRIS-Team WoS Importer:2019-03-12

Transvascular kidney biopsy in adolescent patients-safe alternative to open procedures - Utsch, Boris; Hoppe, Hanno; Dittrich, Katalin; Amann, Kerstin Ute; Gugger, Mathias; Tschumi, Sibylle; Galiano, Matthias; Plank, Christian Georg; Rascher, Wolfgang; Schmid, Axel; Uder, Michael; Dötsch, Jörg (Clinical Kidney Journal, 2021)
CRIS-Team WoS Importer:2021-05-21

Transvenous renal transplant biopsy via a transfemoral approach - Schmid, Axel; Jacobi, Johannes; Kuefner, M. A.; Lell, Michael; Wüst, Wolfgang; Mayer-Kadner, I.; Benz, Kerstin; Schmid, Matthias; Amann, Kerstin Ute; Uder, Michael (American Journal of Transplantation, 2013)
Percutaneous renal biopsy (PRB) of kidney transplants might be prevented by an elevated risk of bleeding or limited access to the allograft. In the following, we describe our initial experience with 71 transvenous renal transplant biopsies in 53 consecutive patients with unexplained reduced graft function who were considered unsuitable candidates for PRB (4.2% of all renal transplant biopsies at our institution). Biopsies were performed via the ipsilateral femoral vein with a renal biopsy set designed for transjugular renal biopsy (TJRB) of native kidneys. Positioning of the biopsy system within the transplant vein was achievable in 58 of 71 (81.7%) procedures. The specimen contained a median of 10 glomeruli (range 0-38). Tissue was considered as adequate for diagnosis in 56 of 57 (98.2%) biopsies. With respect to BANFF 50.9% of the specimen were adequate (>10 glomeruli), 47.4% marginally adequate (1-9 glomeruli) and 1.8% inadequate (no glomeruli). After implementation of real-time assessment all specimen contained glomeruli. One of the fifty-eight (1.8%) procedure-related major complications occurred (hydronephrosis requiring nephrostomy due to gross hematuria). Transfemoral renal transplant biopsy (TFRTB) is feasible and appears to be safe compared to PRB. It offers a useful new alternative for histological evaluation of graft dysfunction in selected patients with contraindications to PRB. The authors report on an experience using transvenous renal transplant biopsy to enable histological evaluation in patients unsuitable for percutaneous transplant biopsy. © 2013 The American Society of Transplantation and the American Society of Transplant Surgeons.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Kidney transplant; percutaneous renal transplant biopsy; renal allograft; renal transplant biopsy; transjugular renal biopsy; transvenous biopsy

Treatment of a patient with severe systemic sclerosis (SSc) using CD19-targeted CAR T cells. - Bergmann, Christina; Müller, Fabian; Distler, Jörg; Györfi, Andrea Hermina; Völkl, Simon; Aigner, Michael; Kretschmann, Sascha; Reimann, Hannah; Harrer, Thomas; Bayerl, Nadine; Böltz, Sebastian; Wirsching, Andreas; et al. (Annals of the Rheumatic Diseases, 2023)
EVALuna2:537682

Twice-refocused stimulated echo diffusion imaging: Measuring diffusion time dependence at constant T-1 weighting - Martin, Jan; Endt, Sebastian; Wetscherek, Andreas; Kuder, Tristan Anselm; Dörfler, Arnd; Uder, Michael; Hensel, Bernhard; Laun, Frederik Bernd (Magnetic Resonance in Medicine, 2019)
Purpose Diffusion times longer than 50 ms are typically probed with stimulated-echo sequences. Varying the diffusion time in stimulated-echo sequences affects the T-1 weighting of subcompartments, complicating the analysis of diffusion time dependence. Although inversion recovery preparation could be used to change the T-1 weighting, it cannot ensure equal T-1 weighting at arbitrary mixing times. In this article, a sequence that ensures constant T-1 weighting over a wide range of diffusion times is presented. Methods The proposed sequence features 2 independent longitudinal storage periods: TM1 and TM2. Diffusion encoding is performed during TM1, effectively coupling the diffusion time and TM1. Equal T-1 weighting at arbitrary diffusion times is realized by keeping the total mixing time TM1 + TM2 constant. The sequence was compared with conventional stimulated-echo measurements of diffusion in a 2-compartment phantom consisting of distilled water and paraffinum perliquidum. Additionally, in vivo DTI of the brain was carried out for 8 healthy volunteers with diffusion times ranging from 50 to 500 ms. Results Diffusion time dependence of the axial and radial diffusivity was detected in the brain. Both sequences resulted in almost identical diffusivities in white matter. In regions containing partial volumes of gray and white matter, a dependency on T-1 weighting was observed. Conclusion In accordance with previous studies, little variance of T-1 values appeared to be present in healthy white matter. However, this is likely different in diseased tissue. Here, the proposed sequence can be effective in differentiating between diffusion time dependence and T-1 weighting effects.
CRIS-Team WoS Importer:2019-11-12

Ultra-High b-Value Diffusion-Weighted Imaging-Based Abbreviated Protocols for Breast Cancer Detection - Ohlmeyer, Sabine; Laun, Frederik Bernd; Bickelhaupt, Sebastian; Palm, Theresa; Janka, Rolf Matthias; Weiland, Elisabeth; Uder, Michael; Wenkel, Evelyn (Investigative Radiology, 2021)
Objectives Contrast-enhanced (CE) magnetic resonance imaging (MRI) is the most effective imaging modality for breast cancer detection. A contrast agent-free examination technique would be desirable for breast MRI screening. The purpose of this study was to evaluate the capability to detect and characterize suspicious breast lesions with an abbreviated, non-contrast-enhanced MRI protocol featuring ultra-high b-value diffusion-weighted imaging (DWI) compared with CE images. Materials and Methods The institutional review board-approved prospective study included 127 female subjects with different clinical indications for breast MRI. Magnetic resonance imaging examinations included DWI sequences with b-values of 1500 s/mm(2) (b1500) and 2500 s/mm(2) (b2500), native T1- and T2-weighted images, and CE sequences at 1.5 T and 3 T scanners. Two reading rounds were performed, including either the b1500 or the b2500 DWI in consecutive assessment steps: (A) maximum intensity projections (MIPs) of DWI, (B) DWI and apparent diffusion coefficient maps, (C) as (B) but with additional native T1- and T2-weighted images, and (D) as (C) but with additional CE images (full-length protocol). Two readers independently determined the presence of a suspicious lesion. Histological confirmation was obtained for conspicuous lesions, whereas the full MRI data set was obtained for inconspicuous and clearly benign lesions. Statistical analysis included calculation of diagnostic accuracy and interrater agreement via the intraclass correlation coefficient. Results The cohort comprised 116 cases with BI-RADS 1 findings and 138 cases with BI-RADS >= 2 findings, including 38 histologically confirmed malignancies. For (A), breasts without pathological findings could be recognized with high diagnostic accuracy (negative predictive value, >= 97.0%; sensitivity, >= 92.1% for both readers), but with a limited specificity (>= 58.3%; positive predictive value, >= 28.6%). Within the native readings, approach (C) with b2500 performed best (negative predictive value, 99.5%; sensitivity, 97.4%; specificity, 88.4%). The intraclass correlation coefficient was between 0.683 (MIP b1500) and 0.996 (full protocol). Conclusions A native abbreviated breast MRI protocol with advanced high b-value DWI might allow nearly equivalent diagnostic accuracy as CE breast MRI and seems to be well suited for lesion detection purposes.
CRIS-Team WoS Importer:2021-10-01

Ultra-high field MRI of human hippocampi: Morphological and multiparametric differentiation of hippocampal sclerosis subtypes - Gillmann, Clarissa; Coras, Roland; Roessler, Karl; Dörfler, Arnd; Uder, Michael; Blümcke, Ingmar; Bäuerle, Tobias (PLoS ONE, 2018)
The aim of the present study is to differentiate subtypes of hippocampal sclerosis (HS) using ex vivo ultra-high field magnetic resonance imaging (MRI). Included were 14 surgically resected hippocampi of patients with medically intractable temporal lobe epilepsy. The resected hippocampi were histologically categorized into subtypes of hippocampal sclerosis (HS type 1 (n = 10), HS type 2 (n = 2) and no-HS (n = 2)) and subsequently scanned on a preclinical 7T MRI acquiring T2-weighted morphology, relaxometry and diffusion tensor imaging. On the morphological images, the pyramidal cell layer (PCL) of the hippocampus was segmented and the following parameters were derived: T2 signal intensity, T1-, T2- and T2*-relaxation times, apparent diffusion coefficient (ADC), fractional anisotropy (FA) and mean diffusivity (MD). Furthermore, the area of the PCL was determined, as well as the parameter product which refers to the widths of the PCL parallel and perpendicular to the stratum moleculare. Spearman correlation coefficient was used to demonstrate relationships between MR-parameters and type of sclerosis. In comparison to no-HS specimens, the PCL was significantly narrower in HS type 1 and HS type 2 hippocampi. This narrowing affected the entire cornu ammonis sector (CA) 1 in HS type 1, while it was limited to the upper half of CA1 in direction to CA2 in HS type 2. The parameter product median increased from 0.43 to 1.67 and 2.91 mm2 for HS type 1, HS type 2 and no-HS, respectively. Correlation coefficients were significant for the PCL parameters product (0.73), area (0.71), T2*-time (-0.67), FA (0.65) and ADC (0.55). Our initial results suggest that HS type 1, HS type 2 and no-HS subtypes can be distinguished from each other using ex vivo UHF MRI based on T2-weighted morphologic images and the assessment of the parameter product. Upon clinical translation, UHF-MRI may provide a promising technique for the preoperative differentiation of HS subtypes in patients.
EVALuna2:34592

Ultrasound Elastography of Pulmonary Lesions - A Feasibility Study - Adamietz, B. R.; Fasching, Peter; Jud, Sebastian; Schulz-Wendtland, Rüdiger; Anders, Katharina; Uder, Michael; Wüst, Wolfgang; Rauh, C.; Meier-Meitinger, M. (Ultraschall in der Medizin, 2014)
Introduction: The potential of sonography in the examination of lung tissue is extremely limited by the air-filled alveoles of the lung. Only in special circumstances like pleural adhesion lesions, atelectasis or pneumonia can lung tissue be visualized by B-mode sonography. Real-time elastography was primarily applied to detect and visualize pulmonary lesions. Methods and Patients: 8 patients with a total of 18 histologically proven metastases of the lung were included. All pulmonary lesions were detected by computed tomography. Sonographic examination was performed with a 7.5 MHz linear transducer (Acuson Antares premium edition, Siemens, Erlangen, Germany), including B-mode and real-time elastography (RTE). The mean distance between pleura and the lesions ranged from 0 to 2.5 cm. Two lesions were located in the upper right lobe, eleven lesions in the lower right and five in the lower left lobe. Results: RTE was able to detect and visualize all 18 pulmonary lesions in contrast to B-mode. The size and distance of the lesions from the pleura correlated with the CT findings. Conclusion: In contrast to B-mode sonography, RTE is able to detect and visualize peripheral, non-pleural adherent pulmonary lesions.
EVALuna2:14352

Update cartilage imaging of the small joints: Focus on high-field MRI [Update Knorpelbildgebung der kleinen Gelenke: Fokus Hochfeld-MRT] - Heiß, Rafael; Janka, Rolf Matthias; Uder, Michael; Nagel, Armin Michael; Trattnig, S.; Roemer, Frank (Radiologe, 2019)
Background: Cartilage imaging of small joints is increasingly of interest, as early detection of cartilage damage may be relevant regarding individualized surgical therapies and long-term outcomes. Purpose: The aim of this review is to explain modern cartilage imaging of small joints with emphasis on MRI and to discuss the role of methods such as CT arthrography as well as compositional and high-field MRI. Materials and methods: A PubMed literature search was performed for the years 2008–2018. Results: Clinically relevant cartilage imaging to detect chondral damage in small joints remains challenging. Conventional MRI at 3 T can still be considered as a reference for cartilage imaging in clinical routine. In terms of sensitivity, MR arthrography (MR-A) and computed tomography arthrography (CT-A) are superior to non-arthrographic MRI at 1.5 T in the detection of chondral damage. Advanced degenerative changes of the fingers and toes are usually sufficiently characterized by conventional radiography. MRI at field strengths of 3 T and ultrahigh-field imaging at 7 T can provide additional quantifiable, functional and metabolic information. Conclusion: Standardized cartilage imaging plays an important role in clinical diagnostics in the ankle joint due to the availability of different and individualized therapeutic concepts. In contrast, cartilage imaging of other small joints as commonly performed in clinical studies has not yet become standard of care in daily clinical routine. Although individual study results are promising, additional studies with large patient collectives are needed to validate these techniques. With rapid development of new treatment concepts radiological diagnostics will play a more significant role in the diagnosis of cartilage lesions of small joints.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Ankle; Glycosaminoglycans; Literature review; Magnetic resonance imaging; Wrist

Update: Posttreatment Imaging of the Knee after Cartilage Repair. - Heiß, Rafael; Guermazi, Ali; Janka, Rolf Matthias; Uder, Michael; Li, Xinning; Hayashi, Daichi; Roemer, Frank (Seminars in Musculoskeletal Radiology, 2022)
Focal cartilage lesions are common pathologies at the knee joint that are considered important risk factors for the premature development of osteoarthritis. A wide range of surgical options, including but not limited to marrow stimulation, osteochondral auto- and allografting, and autologous chondrocyte implantation, allows for targeted treatment of focal cartilage defects. Arthroscopy is the standard of reference for the assessment of cartilage integrity and quality before and after repair. However, deep cartilage layers, intrachondral composition, and the subchondral bone are only partially or not at all visualized with arthroscopy. In contrast, magnetic resonance imaging offers noninvasive evaluation of the cartilage repair site, the subchondral bone, and the soft tissues of the joint pre- and postsurgery. Radiologists need to be familiar with the different surgical procedures available and their characteristic postsurgical imaging appearances to assess treatment success and possible complications adequately. We provide an overview of the most commonly performed surgical procedures for cartilage repair at the knee and typical postsurgical imaging characteristics.
EVALuna2:506329

Usability of magnetic resonance images acquired at a novel low-field 0.55 T scanner for brain radiotherapy treatment planning - Grigo, Johanna; Masitho, Siti; Fautz, Hans Peter; Voigt, Raphaela; Schonath, Miriam; Oleszczuk, Annika; Uder, Michael; Heiß, Rafael; Fietkau, Rainer; Putz, Florian; Bert, Christoph (Physics and Imaging in Radiation Oncology, 2023)
Background and Purpose: Low-field magnetic resonance imaging (MRI) may offer specific advantages over high-field MRI, e.g. lower susceptibility-dependent distortions and simpler installation. The study aim was to evaluate if a novel 0.55 T MRI scanner provides sufficient image accuracy and quality for radiotherapy (RT) treatment planning. Material and methods: The geometric accuracy of images acquired at a low-field MRI scanner was evaluated in phantom measurements regarding gradient non-linearity-related distortions. Patient-induced B0-susceptibility changes were investigated via B0-field-mapping in ten volunteers. Patients were positioned in RT-setup using a 3D-printed insert for the head/neck-coil that was tested for sufficient signal-to-noise-ratio (SNR). The suitability of the MRI-system for detection of metastases was evaluated in eleven patients. In comparison to diagnostic images, acquired at ≥1.5 T, three physicians evaluated the detectability of metastases by counting them in low- and high-field-images, respectively. Results: The phantom measurements showed a high imaging fidelity after 3D-distortion-correction with (1.2 ± 0.9) mm geometric distortion in 10 cm radius from isocentre. At the edges remaining distortions were greater than at 1.5 T. The mean susceptibility-induced distortions in the head were (0.05 ± 0.05) mm and maximum 0.69 mm. SNR analysis showed that optimised positioning of RT-patients without signal loss in the head/neck-coil was possible with the RT-insert. No significant differences (p = 0.48) in detectability of metastases were found. Conclusion: The 0.55 T MRI system provided sufficiently geometrically accurate and high-resolution images that can be used for RT-planning for brain metastases. Hence, modern low-field MRI may contribute to simply access MRI for RT-planning after further investigations.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Low-Field-MRI; MRI; Radiotherapy

Using automated texture features to determine the probability for masking of a tumor on mammography, but not ultrasound - Haeberle, Lothar; Hack, Carolin; Heusinger, Katharina; Wagner, Florian; Jud, Sebastian; Uder, Michael; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Fasching, Peter (European Journal of Medical Research, 2017)
BACKGROUND: Tumors in radiologically dense breast were overlooked on mammograms more often than tumors in low-density breasts. A fast reproducible and automated method of assessing percentage mammographic density (PMD) would be desirable to support decisions whether ultrasonography should be provided for women in addition to mammography in diagnostic mammography units. PMD assessment has still not been included in clinical routine work, as there are issues of interobserver variability and the procedure is quite time consuming. This study investigated whether fully automatically generated texture features of mammograms can replace time-consuming semi-automatic PMD assessment to predict a patient's risk of having an invasive breast tumor that is visible on ultrasound but masked on mammography (mammography failure). METHODS: This observational study included 1334 women with invasive breast cancer treated at a hospital-based diagnostic mammography unit. Ultrasound was available for the entire cohort as part of routine diagnosis. Computer-based threshold PMD assessments ("observed PMD") were carried out and 363 texture features were obtained from each mammogram. Several variable selection and regression techniques (univariate selection, lasso, boosting, random forest) were applied to predict PMD from the texture features. The predicted PMD values were each used as new predictor for masking in logistic regression models together with clinical predictors. These four logistic regression models with predicted PMD were compared among themselves and with a logistic regression model with observed PMD. The most accurate masking prediction was determined by cross-validation. RESULTS: About 120 of the 363 texture features were selected for predicting PMD. Density predictions with boosting were the best substitute for observed PMD to predict masking. Overall, the corresponding logistic regression model performed better (cross-validated AUC, 0.747) than one without mammographic density (0.734), but less well than the one with the observed PMD (0.753). However, in patients with an assigned mammography failure risk >10%, covering about half of all masked tumors, the boosting-based model performed at least as accurately as the original PMD model. CONCLUSION: Automatically generated texture features can replace semi-automatically determined PMD in a prediction model for mammography failure, such that more than 50% of masked tumors could be discovered.
UnivIS-Import:2017-12-18:Pub.2017.tech.IMMD.IMMD9.usinga
Keywords: Mammographic density; Mammography screening; Masking; Risk prediction; Sensitivity; Texture analysis; Variable selection

Using Cartilage MRI T2-Mapping to Analyze Early Cartilage Degeneration in the Knee Joint of Young Professional Soccer Players - Waldenmeier, Leonie; Evers, Christoph; Uder, Michael; Janka, Rolf Matthias; Hennig, Friedrich; Pachowsky, Milena; Welsch, Götz Hannes (Cartilage, 2019)
Objective: To evaluate and characterize the appearance of articular cartilage in the tibiofemoral joint of young professional soccer players using T2-relaxation time evaluation on magnetic resonance imaging (MRI). Design: In this study, we included 57 male adolescents from the youth academy of a professional soccer team. The MRI scans were acquired of the knee joint of the supporting leg. An “early unloading” (minute 0) and “late unloading” (minute 28) T2-sequence was included in the set of images. Quantitative T2-analysis was performed in the femorotibial joint cartilage in 4 slices with each 10 regions of interest (ROIs). Statistical evaluation, using Wilcoxon signed-rank tests, was primarily performed to compare the T2 values of the “early unloading” and “late unloading.” Results: When comparing “early unloading” with “late unloading,” our findings showed a significant increase of T2-relaxation times in the weightbearing femoral cartilage of the medial (P < 0.001) and lateral (P < 0.001) compartment of the knee and in the tibial cartilage of the medial compartment (P < 0.001). Conclusion: In this study, alterations of the cartilage were found with a maximum in the medial condyle where the biomechanical load of the knee joint is highest, as well as where most of the chronic cartilage lesions occur. To avoid chronic damage, special focus should be laid on this region.
CRIS-Team Scopus Importer:2019-07-02
Keywords: articular cartilage; biomechanics; knee; magnetic resonance imaging; sports injury

Variation in cartilage T2 and T2* mapping of the wrist: a comparison between 3- and 7-T MRI - Heiß, Rafael; Weber, Marc André; Balbach, Eva; Hinsen, Maximilian; Geißler, Frederik; Nagel, Armin Michael; Ladd, Mark E.; Arkudas, Andreas; Horch, Raymund E.; Gall, Christine; Uder, Michael; Roemer, Frank (European Radiology Experimental, 2023)
Background: To analyze regional variations in T2 and T2* relaxation times in wrist joint cartilage and the triangular fibrocartilage complex (TFCC) at 3 and 7 T and to compare values between field strengths. Methods: Twenty-five healthy controls and 25 patients with chronic wrist pain were examined at 3 and 7 T on the same day using T2- and T2*-weighted sequences. Six different regions of interest (ROIs) were evaluated for cartilage and 3 ROIs were evaluated at the TFCC based on manual segmentation. Paired t-tests were used to compare T2 and T2* values between field strengths and between different ROIs. Spearman’s rank correlation was calculated to assess correlations between T2 and T2* time values at 3 and 7 T. Results: T2 and T2* time values of the cartilage differed significantly between 3 and 7 T for all ROIs (p ≤ 0.045), with one exception: at the distal lunate, no significant differences in T2 values were observed between field strengths. T2* values differed significantly between 3 and 7 T for all ROIs of the TFCC (p ≤ 0.001). Spearman’s rank correlation between 3 and 7 T ranged from 0.03 to 0.62 for T2 values and from 0.01 to 0.48 for T2* values. T2 and T2* values for cartilage varied across anatomic locations in healthy controls at both 3 and 7 T. Conclusion: Quantitative results of T2 and T2* mapping at the wrist differ between field strengths, with poor correlation between 3 and 7 T. Local variations in cartilage T2 and T2* values are observed in healthy individuals. Relevance statement: T2 and T2* mapping are feasible for compositional imaging of the TFCC and the cartilage at the wrist at both 3 and 7 T, but the clinical interpretation remains challenging due to differences between field strengths and variations between anatomic locations. Key points: •Field strength and anatomic locations influence T2 and T2* values at the wrist. •T2 and T2* values have a poor correlation between 3 and 7 T. •Local reference values are needed for each anatomic location for reliable interpretation. Graphical Abstract: [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-12-22
Keywords: Cartilage (articular); Image processing (computer-assisted); Magnetic resonance imaging; Triangular fibrocartilage; Wrist joint

Vascular and renal hemodynamic changes after renal denervation - Ott, Christian; Janka, Rolf Matthias; Schmid, Axel; Titze, Stephanie; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical Journal of the American Society of Nephrology, 2013)
Background and objectives Renal denervation (RDN) has been shown to be effective in reducing BP in treatmentresistant hypertension. Measurement of the renal and sympathetic activity revealed a decrease in sympathetic drive to the kidney and small resistance vessels after RDN. However, the consequences on renal perfusion and renal vascular resistance (RVR), as well as central hemodynamics, are unknown. Design, setting, participants, & measurements Nineteen patients with treatment-resistant hypertension (office BP140/90mmHg, despite at least three antihypertensive drugs [including a diuretic], and diagnosis confirmed by 24-hour ambulatory BPmonitoring) underwent RDNbetween January andOctober 2011. Renal perfusion and RVR were noninvasively assessed by magnetic resonance imaging with arterial spin labeling, and renal function was assessed by estimating GFR before (day 21), after (day +1), and again after 3 months of RDN. Central hemodynamics was assessed using pulse wave analysis at day 21 and after 6 months of RDN. Results Peripheral office BP (systolic, 158±26 versus 142±23mmHg, P=0.002; diastolic, 83±13 versus 76±9mmHg, P=0.02) and mean systolic 24-hour ambulatory BP (159±17 versus 152±17 mmHg, P=0.02) were significantly reduced 6 months after RDN. Renal perfusion was not statistically different between day 21 and day +1 (256.8 [interquartile range (IQR), 241-278] versus 263.4 [IQR, 252-277] ml/min per 100 g; P=0.17) as well as after 3 months (256.8 [IQR, 241-278] versus 261.2 [IQR, 240-285] ml/min per 100 g; P=0.27) after RDN. RVR dropped (432.1 [IQR, 359-525] versus 390.6 [IQR, 338-461] AU; P=0.02), whereas renal function was not statistically different at any time point. Central systolic BP (145±31 versus 131628 mmHg; P=0.009), diastolic BP (85±18 versus 80±14 mmHg; P=0.03), and central pulse pressure (61±18 versus 52±18 mmHg; P=0.02) were significantly reduced 6 months after RDN. Central augmentation index (24±8 versus 20±8%; P=0.02) was decreased 6 months after RDN. Conclusion The data indicate that RDN significantly reduced peripheral and central BP. Despite reduced systemic BP, renal perfusion and function did not change after RDN. © 2013 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2023-03-08

Vascularization of the Arteriovenous Loop in a Rat Isolation Chamber Model-Quantification of Hypoxia and Evaluation of Its Effects - Yuan, Quan; Arkudas, Andreas; Horch, Raymund E.; Hammon, Matthias; Bleiziffer, Oliver; Uder, Michael; Seuß, Hannes (Tissue Engineering: Parts A, B, and C, 2017)
The aim of this study was to analyze the three-dimensional distribution of hypoxia in the arteriovenous (AV) loop model in rats, by examining the distribution of hypoxia-inducible factor-1 alpha (HIF-1?).AV loops were created from the femoral artery and vein of male Lewis rats and an interpositional graft from the contralateral femoral vein. This AV fistula was embedded in a fibrin-filled isolation chamber and subcutaneously implanted into the thigh. The specimens were harvested after 7 days (n = 4), 10 days (n = 5), and 14 days (n = 4). The fibrin clots were stained for lectin, HIF-1?, and ectodysplasin 1 (ED1). The distribution of positive and negative cells was analyzed in three dimensions and at different points in time.The HIF-1?-positive rate increased from the proximity of the central vessel to the distant regions. From day 7 to 10, we noted a decrease in the HIF-1?-positive rate in the proximity of the vessels and an increase in the periphery. A global decrease in positive cells was seen at day 14. HIF-1? and macrophage (ED1) double staining indicated that macrophages accounted for a significant fraction of the cells. Double staining for endothelium (with lectin) demonstrated that no HIF-1? was detectable in well-vascularized areas.In the AV loop model, the HIF-1?-positive cell distribution is highly related to the vascularization process. The onset of rapid vessel outgrowth follows the increase of the HIF-1? rate closely, indicating that HIF-1? may be a driving force for vascularization.
EVALuna2:14719

Verbesserung der Deep Learning basierten Autodetektion von Hirnmetastasen durch Integration von MRT-Voraufnahmen - Huang, Yixing; Bert, Christoph; Sommer, Philipp; Frey, Benjamin; Gaipl, Udo; Distel, Luitpold; Weissmann, Thomas; Uder, Michael; Schmidt, Manuel; Dörfler, Arnd; Maier, Andreas; Fietkau, Rainer; et al. (Strahlentherapie und Onkologie, 2022)
Keywords: Deep learning; brain metastasis

Vertebral body fractures of unknown origin in cancer patients receiving MDCT: reporting by radiologists and awareness by clinicians - Wild, Melanie; Dankerl, Peter; Hammon, Matthias; Uder, Michael; Janka, Rolf Matthias (SpringerPlus, 2016)
To evaluate prevalence, radiological reporting and clinical management of pathologic vertebral body fractures (VBFs) of unknown origin in cancer patients receiving computed tomography (CT) examinations.We investigated all CT examinations (over 1 year) of male and female patients with an underlying malignancy and an increased risk of osteoporosis (age 55-79 years) for the presence of VBFs. We evaluated midline sagittal CT-reformations of the spine for prevalence, fracture type, severity and location, the accuracy and style of radiological reporting, subsequent clinical management and documentation in hospital discharge letters.848 patients were investigated. We found 143 VBFs in 94 (11 %) patients. 6, 49, and 45 % were grade 1, grade 2, and grade 3 fractures, respectively, while 20, 66, and 14 % were wedge, biconcave and crush fractures, respectively. 32 (34 %) radiological reports correctly classified VBFs as fractures, 25 (27 %) reports recognized VBFs, but did not type them, and VBFs were not described in 37 (39 %) reports. In 3 (3 %) patients further clinical work-up of VBFs was performed, while only 8 (9 %) hospital discharge letters contained the information of the presence of pathologic VBFs of unknown origin.VBFs of unknown origin appear frequently in cancer patients, however, clinical management and documentation was found in only few cases. Moreover, especially in cancer patients consistent radiological reporting of VBFs seems important, as aetiology of VBFs could be from osteoporosis, disease progression or oncological therapy, however, reporting is still performed inconsistently.
EVALuna2:14589

Vertebral metastases of urogenital carcinomas : Diagnosis and conservative therapy - Keck, Bastian; Hammon, Matthias; Uder, Michael; Huber, J.; Goebell, Peter; Kunath, F.; Wullich, Bernd; Richter, R. H. (Urologe, 2016)
The high incidence of bone metastases of urologic neoplasms and their morbidity, especially of vertebral metastases, requires exact diagnosis and consequent therapy. Conventional radiography plays an important role in the diagnosis of symptomatic bone lesions. Computed tomography can evaluate the stability of metastatic lesions and is indispensable for therapy planning. MRI and PET-CT have the highest diagnostic accuracy for the detection of bone metastases and MRI can evaluate their intra- and extraosseus components. PET-CT, PET-MRI, or SPECT-CT in combination with specific tracers - due to their high specificity and sensitivity - have the potential to replace conventional methods in the future. Conservative treatment basically consists of analgesic therapy, the administration of calcium and vitamin D3 and bisphosphonates or inhibitors of RANKL (denosumab). Moreover radium-223-dichloride can improve overall survival and the time to the first symptomatic skeletal event in castration-resistant prostate cancer patients with bone metastases.
EVALuna2:14491

Virtual Computed Tomography Colonography: Evaluation of 2D and Virtual 3D Image Quality of Sub-mSv Examinations Enabled by Third-generation Dual Source Scanner Featuring Tin Filtering - Seuß, Hannes; Janka, Rolf Matthias; Hammon, Matthias; Uder, Michael; Dankerl, Peter; Cavallaro, Alexander Josef (Academic Radiology, 2018)
RATIONALE AND OBJECTIVES: To evaluate two- and three-dimensional (2D and 3D) image quality of sub-milliSievert (mSv) computed tomography (CT) colonography utilizing a third-generation dual source CT scanner featuring a tin filter. METHODS: We retrospectively evaluated 26 consecutive patients who underwent third-generation dual source CT colonography, nine with the standard-dose clinical-scan protocol (SDP) and 17 with a low-dose protocol (LDP) featuring a tin filter. Radiation dose was evaluated by volume computed tomography dose index (CTDIvol), dose length product (DLP), effective dose (E), and size-specific dose estimate. Objective image quality was evaluated utilizing signal-to-noise ratio (SNR) derived from standardized placed regions of interest on the transverse 2D images and the ratio of SNR/CTDIvol (normalized SNR). Two radiologists in consensus assessed subjective image quality of the virtual 3D images. RESULTS: There were no significant differences in subjective image quality (P = .661). All examinations were rated "excellent" or "good" for diagnostic confidence. The mean total for DLP/E was 143.4 ± 29.8 mGy/3.00 ± 0.40 mSv in the SDP and therefore significantly higher than in the LDP with 36.9 ± 8.7 mGy/0.75 ± 0.16 mSv (P < .001). The SNR was 8.9 ± 2.1 in the SDP and 4.9 ± 0.8 in the LDP. CONCLUSIONS: Third-generation dual source CT featuring a tin filter enables consistent sub-mSv colonography without substantially impairing image quality.
EVALuna2:34692

Visualization of the epimysium and fascia thoracolumbalis at the lumbar spine using MRI - Adamietz, Boris; Schoenberg, Stefan O.; Reiser, Maximilian; Uder, Michael; Frank, Andreas; Strecker, Ralph; Weiss, Christel; Heiß, Rafael (Radiologe, 2021)
Background The fascia thoracolumbalis (FTL) is an important component for stabilization and motion control of the lumbar spine. It coordinates the traction forces of the autochthonous muscles of the back (AM) and connects them to the muscles of the abdominal wall, shoulder, and buttocks. Objectives The aim of our study was to describe the assessment of the normal FTL and epimysium of the AM in MRI and to identify patterns associated with pathological changes in the lumbar spine. Material and methods A total of 33 patients were retrospectively evaluated: 15 patients had no pathology at the lumbar spine; six patients had previous hemilaminectomy, three had spondylodesis, two had ventrolisthesis, and seven had scoliosis. The thickness of the FTL and EM was measured, and the adhesion of both structures was assessed. Results The fascial thickness at the levels of the lumbar vertebral bodies LVB 3 was 1.8, of LVB 4 it was 2.0, of LVB 5 it was 2.1, and at the sacral vertebra SVB 1 it was 1.8 mm. Fascial adhesions together with thickening of the EM occurred at the level of LVB 4 in 36% of the cases independently of the underlying disorder. Only thickening of the EM was seen in 48% of cases at the level of SVB 1. By contrast, adhesion of the FTL without epimysial changes occurred in 36% of cases at the level of LVB 3. Conclusion Thickening and adhesions at the EM and FTL occurred both postoperatively and in the case of scoliosis. Furthermore, lipomatous and muscular herniation could be detected in the FTL postoperatively. Epimysial and fascial alterations may be imaging manifestations of chronic myofascial back pain and should be included in radiological assessments.
CRIS-Team WoS Importer:2021-05-28

White paper: clinical studies in radiology - Antoch, G.; Barkhausen, J.; Dueber, C.; Epsch, R.; Heindel, W.; Krombach, G.; Maintz, D.; Schlemmer, H. P.; Schoenberg, S.; Wigge, P.; Adam, G.; Beer, M.; et al. (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
EVALuna2:14521

White Paper: Radiological Curriculum for Undergraduate Medical Education in Germany - Ertl-Wagner, Birgit; Barkhausen, J.; Mahnken, A. H.; Mentzel, H. J.; Uder, Michael; Weidemann, J.; Stumpp, P.; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Radiology represents a highly relevant part of undergraduate medical education from preclinical studies to subinternship training. It is therefore important to establish a content base for teaching radiology in German Medical Faculties. Materials and Methods: The German Society of Radiology (DRG) developed a model curriculum for radiological teaching at German medical universities, which is presented in this article. There is also a European model curriculum for undergraduate teaching (U-level curriculum of the European Society of Radiology). In a modular concept, the students shall learn important radiological core principles in the realms of knowledge, skills and competences as well as core scientific competences in the imaging sciences. Results: The curriculum is divided into two modules. Module 1 includes principles of radiation biology, radiation protection and imaging technology, imaging anatomy as well as the risks and side effects of radiological methods, procedures and contrast media. This module is modality-oriented. Module 2 comprises radiological diagnostic decision-making and imaging-based interventional techniques for various disease entities. This module is organ system-oriented. Conclusion: The curriculum is meant as a living document to be amended and revised at regular intervals. The curriculum can be used as a basis for individual curricular development at German Medical Faculties. It can be integrated into traditional or reformed medical teaching curricula. Key Points: • Radiology is an integral and important part of medical education. • The German Society of Radiology (DRG) developed a model curriculum for teaching radiology at German Medical Faculties to help students develop the ability to make medical decisions based on scientific knowledge and act accordingly. • This curriculum can be used for individual curricular development at medical departments. It is divided into two modules with several chapters. Citation Format: • Ertl-Wagner B, Barkhausen J, Mahnken AH et al. White Paper: Radiological Curriculum for Undergraduate Medical Education in Germany. Fortschr Röntgenstr 2016; 188: 1017 1023.
CRIS-Team Scopus Importer:2023-03-08
Keywords: competence-based learning; curriculum; medical education; radiological teaching; undergraduate teaching

Whole body magnetic resonance angiography and computed tomography angiography in the vascular mapping of head and neck: an intraindividual comparison - Kramer, Manuel; Schwab, Siegfried; Nkenke, Emeka; Eller, Achim; Kammerer, Ferdinand; May, Matthias; Baigger, Joao F.; Uder, Michael; Lell, Michael (Head & Face Medicine, 2014)
The aim of the study was to compare the detectability of neck vessels with contrast enhanced magnetic resonance angiography (MRA) in the setting of a whole-body MRA and multislice computed tomography angiography (CTA) for preoperative vascular mapping of head and neck.In 20 patients MRA was performed prior to microvascular reconstruction of the mandible with osteomyocutaneous flaps. CTA of the neck served as the method of reference.1.5 T contrast enhanced magnetic resonance angiograms were acquired to visualize the vascular structures of the neck in the setting of a whole-body MRA examination. 64-slice spiral computed tomography was performed with a dual-phase protocol, using the arterial phase images for 3D CTA reconstruction. Maximum intensity projection was employed to visualize MRA and CTA data. To retrieve differences in the detectability of vessel branches between MRA and CTA, a McNemar test was performed.All angiograms were of diagnostic quality. There were no statistically significant differences between MRA and CTA for the detection of branches of the external carotid artery that are relevant host vessels for microsurgery (p = 0.118). CTA was superior to MRA if all the external carotid artery branches were included (p < 0.001).MRA is a reliable alternative to CTA in vascular mapping of the cervical vasculature for planning of microvascular reconstruction of the mandible. In the setting of whole-body MRA it could serve as a radiation free one-stop-shop tool for preoperative assessment of the arterial system, potentially covering both, the donor and host site in one single examination.
EVALuna2:14369

Whole-brain quantitative CEST MRI at 7T using parallel transmission methods and B1+ correction - Liebert, Andrzej; Tkotz, Katharina; Herrler, Jürgen; Linz, Peter; Mennecke, Angelika; German, Alex; Liebig, Patrick; Gumbrecht, Rene; Schmidt, Manuel; Dörfler, Arnd; Uder, Michael; Zaiß, Moritz; et al. (Magnetic Resonance in Medicine, 2021)
Purpose: To enable whole-brain quantitative CEST MRI at ultra-high magnetic field strengths (B0 ≥ 7T) within short acquisition times. Methods: Multiple interleaved mode saturation (MIMOSA) was combined with fast online-customized (FOCUS) parallel transmission (pTx) excitation pulses and (Formula presented.) correction to achieve homogenous whole-brain coverage. Examinations of 13 volunteers were performed on a 7T MRI system with 3 different types of pulse sequences: (1) saturation in circular polarized (CP) mode and CP mode readout, (2) MIMOSA and CP readout, and (3) MIMOSA and FOCUS readout. For comparison, the inverse magnetic transfer ratio metric for relayed nuclear Overhauser effect and amide proton transfer were calculated. To investigate the number of required acquisitions for a good (Formula presented.) correction, 4 volunteers were measured with 6 different B1 amplitudes. Finally, time point repeatability was investigated for 6 volunteers. Results: MIMOSA FOCUS sequence using (Formula presented.) correction, with both single and multiple points, reduced inhomogeneity of the CEST contrasts around the occipital lobe and cerebellum. Results indicate that the most stable inter-subject coefficient of variation was achieved using the MIMOSA FOCUS sequence. Time point repeatability of MIMOSA FOCUS with single-point (Formula presented.) correction showed a maximum coefficient of variation below 8% for 3 measurements in a single volunteer. Conclusion: A combination of MIMOSA FOCUS with a single-point (Formula presented.) correction can be used to achieve quantitative CEST measurements at ultra-high magnetic field strengths. Compared to previous (Formula presented.) correction methods, acquisition time can be reduced as additional scans required for (Formula presented.) correction can be omitted.
CRIS-Team Scopus Importer:2021-03-12
Keywords: 7T; chemical exchange saturation transfer; fast-online customized pulses; multiple interleaved mode saturation; parallel transmission; spiral non-selective trajectory

X-Ray Induced Formation of γ-H2AX Foci after Full-Field Digital Mammography and Digital Breast-Tomosynthesis - Schwab, Siegfried; Brand, Michael; Schlude, Ina-Kristin; Wüst, Wolfgang; Meier-Meitinger, Martina; Distel, Luitpold; Schulz-Wendtland, Rüdiger; Uder, Michael; Uder, Michael; Kuefner, Michael A. (PLoS ONE, 2013)
Purpose:To determine in-vivo formation of x-ray induced γ-H2AX foci in systemic blood lymphocytes of patients undergoing full-field digital mammography (FFDM) and to estimate foci after FFDM and digital breast-tomosynthesis (DBT) using a biological phantom model.Materials and Methods:The study complies with the Declaration of Helsinki and was performed following approval by the ethic committee of the University of Erlangen-Nuremberg. Written informed consent was obtained from every patient. For in-vivo tests, systemic blood lymphocytes were obtained from 20 patients before and after FFDM. In order to compare in-vivo post-exposure with pre-exposure foci levels, the Wilcoxon matched pairs test was used. For in-vitro experiments, isolated blood lymphocytes from healthy volunteers were irradiated at skin and glandular level of a porcine breast using FFDM and DBT. Cells were stained against the phosphorylated histone variant γ-H2AX, and foci representing distinct DNA damages were quantified.Results:Median in-vivo foci level/cell was 0.086 (range 0.067-0.116) before and 0.094 (0.076-0.126) after FFDM (p = 0.0004). In the in-vitro model, the median x-ray induced foci level/cell after FFDM was 0.120 (range 0.086-0.140) at skin level and 0.035 (range 0.030-0.050) at glandular level. After DBT, the median x-ray induced foci level/cell was 0.061 (range 0.040-0.081) at skin level and 0.015 (range 0.006-0.020) at glandular level.Conclusion:In patients, mammography induces a slight but significant increase of γ-H2AX foci in systemic blood lymphocytes. The introduced biological phantom model is suitable for the estimation of x-ray induced DNA damages in breast tissue in different breast imaging techniques. © 2013 Schwab et al.
CRIS-Team Scopus Importer:2023-03-08

Zukunft mammographie-basierter Bildgebung [Future of mammography-based imaging] - Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Michel, Thilo; Hartmann, Arndt; Beckmann, Matthias; Rauh, Claudia; Judt, Sebastian; Brehm, Barbara; Meier-Meitinger, Martina; Anton, Gisela; Uder, Michael; Fasching, Peter (Radiologe, 2014)
Mammography is the central diagnostic method for clinical diagnostics of breast cancer and the breast cancer screening program. In the clinical routine complementary methods, such as ultrasound, tomosynthesis and optional magnetic resonance imaging (MRI) are already combined for the diagnostic procedure. Future developments will utilize investigative procedures either as a hybrid (combination of several different imaging modalities in one instrument) or as a fusion method (the technical fusion of two or more of these methods) to implement fusion imaging into diagnostic algorithms. For screening there are reasonable hypotheses to aim for studies that individualize the diagnostic process within the screening procedure. Individual breast cancer risk prediction and individualized knowledge about sensitivity and specificity for certain diagnostic methods could be tested. The clinical implementation of these algorithms is not yet in sight. (orig.) [German] Die Mammographie ist die zentrale diagnostische Methode der klinischen symptombezogenen Abklaerung von Brusterkrankungen und des Brustkrebsscreenings. In der klinischen Diagnostik wird sie heute schon oft durch zusaetzliche Untersuchungsmethoden wie dem Ultraschall, der Tomosynthese und ggf. auch der MRT-Bildgebung unterstuetzt. Zukuenftige Entwicklungen gehen in die Richtung, dass diese Kombination aus 2 oder mehr Untersuchungsverfahren entweder in Hybrid- (Aufnahme mehrerer unterschiedlicher Bildmodalitaeten in einem einzigen Geraet) oder in Fusionsmethoden (Zusammenfuehrung und Registrierung von Bilddaten aus verschiedenen Modalitaeten) technisch professionalisiert werden. Des Weiteren koennten an subgruppenbezogene Erkrankungsrisiken und individuelle Sensitivitaeten und Spezifitaeten angepasste Diagnostikkombinationen fuer eine Screeningdiagnostik Gegenstand kuenftiger Studien sein. Wir stellen die aktuellen Entwicklungen auf diesen Gebieten und deren momentane Relevanz fuer die klinische Praxis und Entwicklungspotenzial fuer die Zukunft dar. (orig
UnivIS-Import:2015-04-14:Pub.2014.tech.IMMD.IMMD9.zukunf
Keywords: MAMMOgraphy

Zusammengefasste Empfehlungen für ein körperliches Training zur Frakturprophylaxe postmenopausaler Frauen und Männer 45 Jahre und älter - von Stengel, Simon; Schöne, Daniel; Kohl, Matthias; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan-Schindl, Katharina; Kladny, Bernd; Lange, Uwe; Peters, Stefan; Sieber, Cornel; Thomasius, Friederike; et al. (Osteologie, 2023)
The design and implementation of promising training protocols for fracture prevention is a multi-step approach that has to consider a wide range of diverging aspects. Apart from the effectiveness as such, a large number of individual, logistical and financial aspects have to be taken into account to generate ideally persistantly applicable exercise training programs. Applying a sport scientific approach, the definition of dedicated training aims, based on the individual fracture risk profile, is the first step of the training process. The appropriate selection of training content and types along with training tools and methods that best possibly address the defined training aim(s) should also consider the (fracture) risk profile, health status and predispositions of the individual. Since training programs should be maintained as long as possible, ideally for life, particular attention should be paid to training principles (e. g. progressive overload, periodization), something often overlooked in scientific studies of limited duration. Summing up the applicability of exercise programms for fracture prevention, in view of the large variaty of training options and technologies, exercise is a feasible and promizing therapy for most if not all cohorts at risk for fractures - individually adjustable relating to functional status, health issues and potential contraindications. With the exception of structures for fall prevention programs as an individual home-based approach, health care systems already provide closely supervised, qualified and co-financed training programs that could be increasingly used as vehicles for fracture prevention. Unfortunately, the broad applicability of training programs on fracture prevention for almost all risk and propensity groups is often stymied by the frequently insufficient level of information of stakeholders and decision-makers regarding effectiveness, feasibility and applicability of exercise.
CRIS-Team Scopus Importer:2023-09-22
Keywords: contraindications; exercise training; fracture prevention; recommendations; setting